A CCL1/CCR8-dependent feed-forward mechanism drives ILC2 functions in type 2-mediated inflammation - Knipfer, Lisa; Schulz-Kuhnt, Anja; Kindermann, Markus; Greif, Vicky; Symowski, Cornelia; Vöhringer, David; Neurath, Markus; Atreya, Imke; Wirtz, Stefan (Journal of Experimental Medicine, 2019)
Group 2 innate lymphoid cells (ILC2s) possess indispensable roles during type 2-mediated inflammatory diseases. Although their physiological and detrimental immune functions seem to depend on the anatomical compartment they reside, their tissue tropism and the molecular and immunological processes regulating the self-renewal of the local pool of ILC2s in the context of inflammation or infection are incompletely understood. Here, we analyzed the role of the CC-chemokine receptor CCR8 for the biological functions of ILC2s. In vitro and in vivo experiments indicated that CCR8 is in comparison to the related molecule CCR4 less important for migration of these cells. However, we found that activated mouse and human ILC2s produce the CCR8 ligand CCL1 and are a major source of CCL1 in vivo. CCL1 signaling to ILC2s regulates their proliferation and supports their capacity to protect against helminthic infections. In summary, we identify a novel chemokine receptor-dependent mechanism by which ILC2s are regulated during type 2 responses.
CRIS-Team Scopus Importer:2019-12-13

A comparative analysis of articular bone in large cohort of patients with chronic inflammatory diseases of the joints, the gut and the skin - Simon, David; Kleyer, Arnd; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Kocijan, Roland; Haschka, Judith; Hirschmann, Simon; Atreya, Raja; Neurath, Markus; Sticherling, Michael; et al. (Bone, 2018)
Chronic inflammatory diseases are associated with bone loss. While the occurrence of systemic bone loss is well described in chronic inflammatory diseases, the impact of these conditions on articular bone has not been systematically investigated. Recent refinements in high-resolution CT assessment of the joints now allow the accurate measure of articular bone composition. In this study 476 subjects comprising healthy individuals and patients with anticitrullinated protein antibody (ACPA)-positive rheumatoid arthritis (RA), ACPA-negative RA, Crohn's disease (CD), ulcerative colitis (UC), psoriasis (PsO) and psoriatic arthritis (PsA) were subjected to high-resolution quantitative computed tomography (HR-pQCT) of the hand. Metacarpal heads were assessed for total, trabecular and cortical volumetric bone mineral density (vBMD). Only ACPA+RA, but not the remaining inflammatory diseases (ACPA-RA, CD, UC, PsO, PsA) showed significant (p < 0.001) loss of articular bone affecting both the trabecular and the cortical compartments. Age and body mass index were also associated with articular bone changes, the former with lower, the latter with higher articular bone mass. In multivariate models, presence of ACPA+RA was an independent factor for articular bone loss. Among chronic inflammatory diseases ACPA+RA is the most potent precipitator for articular bone loss pointing out the role of autoimmunity in the development of articular bone disease in the context of chronic inflammatory disease.
EVALuna2:34480

Acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface for the diagnosis of compensated liver cirrhosis - Pfeifer, Lukas; Görtz, Rüdiger; Sturm, Jörg; Wachter, David; Riener, M. O.; Schwitulla, Judith; Bernatik, T.; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2014)
To evaluate the diagnostic value of acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface, using histology as a gold standard for the diagnosis of compensated liver cirrhosis.73 patients without ascites undergoing liver biopsy were included in the study. The left and right liver lobes were examined with ARFI and high-frequency ultrasound. Liver surface irregularity was quantified using image analysis software to calculate the difference between the real surface and the approximated physiological surface through a 20 mm standardized line.There is a significant difference between cirrhotic and non-cirrhotic patients for both quantified liver surface (QLS) and ARFI (p < 0.001). The mean values for QLS of the left lobe were 0.71 ± 0.24 mm and 1.17 ± 0.80 mm, of the right lobe 0.56 ± 0.26 mm and 0.87 ± 0.26 mm for non-cirrhotic and cirrhotic patients, respectively. The mean values of ARFI measurements of the left lobe were 2.04 ± 0.76 m/s and 2.85 ± 0.81 m/s, of the right lobe 1.65 ± 0.61 m/s and 3.02 ± 0.77 m/s for non-cirrhotic and cirrhotic patients, respectively. Diagnostic accuracy (AUROC) was 0.78/0.80 for QLS and 0.77/0.91 for ARFI of the left/right lobe, respectively. ARFI of the right lobe is significantly better than ARFI of the left (p = 0.023) or QLS of the left (p = 0.025)/right (p = 0.046) lobe of the liver.Assessment of liver surface irregularity by high-frequency ultrasound (QLS) is a useful diagnostic test for the assessment of compensated liver cirrhosis. ARFI of the right liver lobe is significantly better than high-frequency ultrasound (QLS of the left/right lobe of the liver) and ARFI of the left lobe of the liver.
EVALuna2:1858

Acoustic Radiation Force Impulse (ARFI) Elastography in Autoimmune and Cholestatic Liver Diseases - Görtz, Rüdiger; Gassmann, Luise; Strobel, Deike; Wildner, Dane; Schellhaas, Barbara; Neurath, Markus; Pfeifer, Lukas (Annals of Hepatology, 2019)
Introduction. Acoustic Radiation Force Impulse (ARFI) elastography evaluates hepatic fibrosis non-invasively and has been mainly validated in viral hepatitis. Data on rare liver diseases such as autoimmune hepatitis (AIH), overlap syndrome, primary biliary cholangitis (PBC) or primary sclerosing cholangitis (PSC) are sparse. Material and methods. 85 patients (including 31 AIH, 26 PBC, 16 PSC and 3 PSC- and 9 PBC-AIH-overlap syndromes) were retrospectively analysed pointing at ARFI elastography of the liver and the correlation with histologic Ishak fibrosis score (F0-6). Results of shear wave velocities (m/s) were expressed as mean +/- standard deviation. Results. The mean shear wave velocity of all 85 patients showed 1.80 +/- 0.84 m/s (0.74-3.98). The ARFI elastography values correlated with the degree of fibrosis in all patients overall and in patients with AIH, overlap syndrome and PSC, respectively. The subgroup of 26 patients with PBC (only with Ishak F <= 3) revealed no correlation between ARFI and these early fibrosis stages (r = 0.019, p = 0.927). ARFI elastography correlated with bilirubin, AST, but not with patient age, body mass index or measurement depth. The cut-off of 2.04 m/s for detecting cirrhosis (Ishak F >= 5) leads to a sensitivity of 90.0% and specificity of 74.7% (AUROC 87.2%). Conclusion. ARFI elastography can evaluate fibrosis in AIH, PSC and PSC-/PBC-AIH-overlap syndrome with good accuracy for the detection of hepatic cirrhosis. Shear wave velocities in PBC should be interpreted with caution in early stages of fibrosis.
CRIS-Team WoS Importer:2019-03-20

Acoustic radiation force impulse (ARFI) elastography of the bowel wall as a possible marker of inflammatory activity in patients with Crohn's disease - Görtz, Rüdiger; Lueke, C.; Wildner, Dane; Vitali, Francesco; Neurath, Markus; Strobel, Deike (Clinical Radiology, 2018)
AIM: To evaluate acoustic radiation force impulse (ARFI) shear-wave velocities of the bowel wall in patients with Crohn's disease (CD). MATERIAL AND METHODS: ARFI shear-wave elastography was analysed within the wall of the stomach, terminal ileum, and sigmoid, and correlated with ultrasound signs of activity in CD patients both retrospectively and in a prospective cohort. RESULTS: A total of 77 retrospective and 21 prospective CD patients were included. ARFI elastography in the stomach, the normal ileum, and sigmoid was lower than in ileitis or sigmoiditis. Retrospectively, the ARFI values correlated with the bowel wall thickness and Limberg vascularisation score. Prospectively, there was no correlation between ARFI and bowel wall thickness, Limberg score, clinical activity, or C-reactive protein. A cut-off analysis of 105 ileal ARFI measurements showed a cut-off value of 1.92 m/s for the diagnosis of ileal inflammation with 75.3% sensitivity and 87.5% specificity. CONCLUSION: In patients with CD, ARFI shear-wave velocities show a trend to higher values in inflamed bowel wall thickening on B-mode ultrasound; however, the differences appear small and may not be clinically significant. The factors influencing ARFI measurements of the bowel wall require further investigation.
EVALuna2:35159

Acoustic radiation force impulse (ARFI) shear wave elastography of the bowel wall in healthy volunteers and in ulcerative colitis - Görtz, Rüdiger; Lueke, Christian; Schellhaas, Barbara; Pfeifer, Lukas; Wildner, Dane; Neurath, Markus; Strobel, Deike (Acta Radiologica Open, 2019)
Background Acoustic radiation force impulse (ARFI) elastography is a non-invasive, ultrasound-based approach of evaluation of tissue elasticity. It has not yet been systematically applied to the bowel wall. Purpose To perform ARFI elastography of the bowel wall in healthy volunteers and patients with ulcerative colitis (UC). Material and Methods A high-frequency ultrasound (with bowel wall thickness and vascularization score) and an ARFI elastography of the bowel wall were performed in 20 patients with UC and 13 healthy volunteers. At least 10 ARFI measurements were obtained within the terminal ileum and the ascending, transverse, descending, and sigmoid colon and correlated with results of high-frequency ultrasound. Results The UC group had mostly moderate disease activity. All patients had signs of inflammation upon B-mode ultrasound. Eight patients showed an ulcerative (ileo)pancolitis. Overall, ARFI elastography values and wall thickness were higher in the UC group than in the group of healthy volunteers (P = 0.021 and P < 0.001, respectively). ARFI velocities of the separate segments were significantly higher in the transverse (P = 0.045) and sigmoid colon (P = 0.032) in case of UC. Conclusion ARFI elastography of the bowel wall of the colonic frame and the terminal ileum is feasible but shows high standard deviation. ARFI shear wave velocities appear to be slightly higher in patients with UC than in healthy volunteers, particularly in the sigmoid and transverse colon. Further studies are needed.
CRIS-Team WoS Importer:2019-04-30

Acoustic radiation force impulse elastography: comparison and combination with other noninvasive tests for the diagnosis of compensated liver cirrhosis - Pfeifer, Lukas; Adler, Werner; Zopf, Steffen; Wildner, Dane; Görtz, Rüdiger; Schellhaas, Barbara; Neurath, Markus; Strobel, Deike; Siebler, Jürgen (European Journal of Gastroenterology & Hepatology, 2017)
BACKGROUND AND AIMS: The aim of this study was to compare acoustic radiation force impulse (ARFI) elastography with other noninvasive tests and to develop a new score for the assessment of liver fibrosis/cirrhosis. MATERIALS AND METHODS: B-mode ultrasound (including high-frequency liver surface evaluation), routine blood tests, ARFI quantification, and mini-laparoscopic liver evaluation were obtained in compensated patients scheduled for mini-laparoscopic biopsy. Our new cirrhosis score (CS) for the assessment of liver cirrhosis, based on a linear combination of ARFI, platelet (PLT), liver surface, and prothrombin index (PI), was calculated by linear discriminant analysis. Its performance was compared with ARFI-elastography, APRI, FIB-4, alanine aminotransferase (ALT)/aspartate aminotransferase (AST)-ratio, PLT, and PI. For the diagnosis of cirrhosis, a combined gold standard (cirrhosis at histology and/or at macroscopic liver evaluation) was used. RESULTS: In total, 171 patients, of whom 38 had compensated cirrhosis, were included. The CS was significantly better for the diagnosis of cirrhosis compared with ARFI (P=0.028), APRI (P=0.012), PLTs (P=0.013), PI (P=0.025), and ALT/AST ratio (P=0.001), but not the FIB-4 score (P=0.207), with an area under the receiver operating characteristic curve of 0.92 [95% confidence interval (CI): 0.87-0.97], 0.86 (95% CI:0.79-0.93), 0.80 (95% CI: 0.72-0.87), 0.79 (95% CI: 0.7-0.87), 0.81 (95% CI: 0.73-0.89), 0.72 (95% CI:0.64-0.81), and 0.86 (95% CI: 0.8-0.93), respectively. Sensitivity, specificity, positive predictive value, and negative predictive value for CS were 87%, 86%, 63%, and 96%, respectively. The FIB-4 score was significantly superior to the APRI score (P=0.041) and the ALT/AST ratio (P=0.011), with no significant difference from ARFI elastography (P=0.88) for the diagnosis of cirrhosis. CONCLUSION: Combining ARFI elastography with other noninvasive tests that are used routinely in the workup of patients with suspected liver disease can improve diagnostic accuracy for compensated liver cirrhosis as compared with ARFI elastography alone. The FIB-4 score showed an overall comparable diagnostic accuracy to ARFI-elastography for compensated cirrhosis.
EVALuna2:33816

Acoustic radiation force impulse shear wave elastography (ARFI) of acute and chronic pancreatitis and pancreatic tumor - Görtz, Rüdiger; Schuderer, Johanna; Strobel, Deike; Pfeifer, Lukas; Neurath, Markus; Wildner, Dane (European Journal of Radiology, 2016)
Acoustic Radiation Force Impulse (ARFI) elastography evaluates tissue stiffness non-invasively and has rarely been applied to pancreas examinations so far. In a prospective and retrospective analysis, ARFI shear wave velocities of healthy parenchyma, pancreatic lipomatosis, acute and chronic pancreatitis, adenocarcinoma and neuroendocrine tumor (NET) of the pancreas were evaluated and compared.In 95 patients ARFI elastography of the pancreatic head, and also of the tail for a specific group, was analysed retrospectively. Additionally, prospectively in 100 patients ARFI was performed in the head and tail of the pancreas.A total of 195 patients were included in the study. Healthy parenchyma (n=21) and lipomatosis (n=30) showed similar shear wave velocities of about 1.3m/s. Acute pancreatitis (n=35), chronic pancreatitis (n=53) and adenocarcinoma (n=52) showed consecutively increasing ARFI values, respectively. NET (n=4) revealed the highest shear wave velocities amounting to 3.62m/s. ARFI elastography showed relevant differences between acute pancreatitis and chronic pancreatitis or adenocarcinoma. With a cut-off value of 1.74m/s for the diagnosis of a malignant disease the sensitivity was 91.1% whereas the specificity amounted to 60.4%.ARFI shear wave velocities present differences in various pathologies of the pancreas. Acute and chronic pancreatitis as well as neoplastic lesions show high ARFI values. Very high elasticity values may indicate malignant disease of the pancreas. However, there is a considerable overlap between the entities.
EVALuna2:2188

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease. - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea T.; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon ?2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing.Colitis was induced in C57BL/6JCrl mice (controls), mice with IEC-specific disruption of Stat1 (Stat1IEC-KO), mice with disruption of the interferon ? receptor 1 gene (Il28ra(-/-)), and mice with disruption of the interferon regulatory factor 3 gene (Irf3(-/-)), with or without disruption of Irf7 (Irf7(-/-)). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging.Lamina propria cells in colon tissues of patients with IBD, and mice with colitis, had increased expression of IL28 compared with controls; levels of IL28R were increased in the colonic epithelium of patients with IBD and mice with colitis. Administration of IL28 induced phosphorylation of STAT1 in primary human and mouse IECs, increasing with dose. Il28ra(-/-), Irf3(-/-), Irf3(-/-)Irf7(-/-), as well as Stat1IEC-KO mice, developed more severe colitis after administration of dextran sulfate sodium than control mice, with reduced epithelial restitution. Il28ra(-/-) and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing.IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD.
EVALuna2:9356

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of intestinal epithelial Stat3 orchestrates tissue defense during gastrointestinal infection - Wittkopf, Nadine; Pickert, Geethanjali; Billmeier, Ulrike; Mahapatro, Mousumi; Wirtz, Stefan; Martini, Eva; Leppkes, Moritz; Neurath, Markus; Becker, Christoph (PLoS ONE, 2015)
Gastrointestinal infections with EHEC and EPEC are responsible for outbreaks of diarrheal diseases and represent a global health problem. Innate first-line-defense mechanisms such as production of mucus and antimicrobial peptides by intestinal epithelial cells are of utmost importance for host control of gastrointestinal infections. For the first time, we directly demonstrate a critical role for Stat3 activation in intestinal epithelial cells upon infection of mice with Citrobacter rodentium - a murine pathogen that mimics human infections with attaching and effacing Escherichia coli. C. rodentium induced transcription of IL-6 and IL-22 in gut samples of mice and was associated with activation of the transcription factor Stat3 in intestinal epithelial cells. C. rodentium infection induced expression of several antimicrobial peptides such as RegIII? and Pla2g2a in the intestine which was critically dependent on Stat3 activation. Consequently, mice with specific deletion of Stat3 in intestinal epithelial cells showed increased susceptibility to C. rodentium infection as indicated by high bacterial load, severe gut inflammation, pronounced intestinal epithelial cell death and dissemination of bacteria to distant organs. Together, our data implicate an essential role for Stat3 activation in intestinal epithelial cells during C. rodentium infection. Stat3 concerts the host response to bacterial infection by controlling bacterial growth and suppression of apoptosis to maintain intestinal epithelial barrier function.
EVALuna2:1990

Addiction in IBD patients: more than just smoke? - Hirschmann, Simon; Koehnen, J.; Schuster, B.; Atreya, Raja; Krauss, N.; Mudter, J.; Dauer, M.; Hagel, A.; Neurath, Markus; Albrecht, Heinz (JOURNAL OF CROHNS & COLITIS, 2019)
CRIS-Team WoS Importer:2019-03-20

Add-on multiple submucosal injections of the RNA oligonucleotide GUT-1 to anti-TNF antibody treatment in patients with moderate-to-severe ulcerative colitis: an open-label, proof-of concept study - Suzuki, Kenji; Sameshima, Yukinori; Yokoyama, Junji; Terai, Shuji; Yoneyama, Hiroyuki; Atreya, Raja; Neurath, Markus; Hibi, Toshifumi; Asakura, Hitoshi (Inflammation and Regeneration, 2024)
Background: Carbohydrate sulfotransferase 15 (CHST15) is an enzyme biosynthesizing matrix glycosaminoglycan that modulates tissue remodeling. We evaluated the efficacy of add-on submucosal injections of GUT-1, the RNA oligonucleotide inhibitor of CHST15, to ongoing anti-tumor necrosis factor (TNF) antibody treatment in patients with moderate-to-severe ulcerative colitis (UC). Methods: This was an open-label study of 250 nM of GUT-1 by endoscopic submucosal injections at weeks 0, 2, 4 in five UC patients who lost response during maintenance treatment to anti-TNF antibodies. The primary endpoint was the rate of endoscopic improvement at week 6 and secondary endpoints included the rates of clinical remission by modified Mayo Score (mMS). Patients received follow-up observation with continuous maintenance treatment by the same anti-TNF antibody till the time of clinical recurrence or for overall 52 weeks. Results: At week 6, rates of endoscopic improvement and clinical remission were 80% (n = 4/5) and 60% (n = 3/5), respectively. The mean Endoscopy Subscore was reduced from 2.4 (95%CI: 1.7 to 3.1) at baseline, to 1.0 (95%CI: 0.1 to 1.9) at week 6. The mean mMS was reduced from 7.8 (95%CI: 6.2 to 9.4) to 1.3 (95%CI: 2.9 to 4.3). GUT-1 was well tolerated. Three patients did not show clinical recurrence for 52 weeks. All three corticosteroid-dependent patients showed no corticosteroid exposure for at least 24 weeks after achieving clinical remission. Multiple dosing was also well tolerated. Conclusions: Add-on multiple injections of GUT-1 to ongoing anti-TNF antibody was able to induce rapid and durable clinical responses in UC patients who lost response to anti-TNF therapy. Trial registration: Clinical trial Registration Number (Japan): UMIN000020900.
CRIS-Team Scopus Importer:2024-05-03
Keywords: CHST15; Clinical remission; Endoscopic improvement; TNF antibody; Ulcerative colitis

Adherence and acceptance of a new oral nutritional supplement in cancer patients - a pilot study in crossover design - Hardt, Luisa; Konturek, Peter; Herrmann, Hans Joachim; Reljic, Dejan; Kugler, L.; Meyer, J.; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2024)
Oral nutritional supplements (ONS) play a key role in the therapy of cancer-cachexia, but adherence to ONS-intake remains challenging. To improve adherence, a wide variety of ONS is crucial. We compared the acceptance and adherence of a commercial liquid ONS (LS) with a newly developed, energy- and protein-rich, semisolid, fruit-gum based product (FG) in oncological patients. Forty cancer patients with indication for artificial nutritional therapy were randomly assigned to LS and FG in crossover design for 4 weeks with a 1-week washout phase in-between. Adherence to ONS was recorded with MARS-D questionnaire. Sensory properties were evaluated and safety monitoring was performed. Energy and nutrient intake, nutrition and performance status and quality of life remained stable in both groups throughout the study (all p-values for the comparison between baseline and after 9 weeks were >0.05). Taste (p=0.004), smell (p=0.025) and enjoyment (p=0.027) of the LS were rated significantly better compared to FG and a higher adherence (p=0.005) for the LS was found. Nevertheless, patients were very interested about the new alternative of ONS, so that 16 of the study participants would buy it or strive for a medical prescription. The balanced, protein-rich ONS based on fruit gum is an innovative formulation that stabilizes nutritional status and might therefore extend the options for nutritional support in cancer patients in the future. However, the sensory properties must first be further improved to increase acceptance and adherence.
CRIS-Team Scopus Importer:2024-10-25
Keywords: cancer; oral nutritional supplement; cachexia; malnutrition; adherence; daily energy intake; body composition parameters; quality of life; sensory properties and preferences

A Dual Role for TNF-Producing T Cells in the Fetal Intestine - Leppkes, Moritz; Neurath, Markus (Immunity, 2019)
The role of tumor necrosis factor (TNF) in the fetal intestine is poorly understood. In this issue of Immunity, Schreurs et al. (2019) identify important roles of TNF-producing T cells as both regulators of gut development and potential inducers of colitis.
CRIS-Team WoS Importer:2019-03-06

Advanced colonoscopic imaging using endocytoscopy - Neumann, Helmut; Kudo, Shin-Ei; Kiesslich, Ralf; Neurath, Markus (Digestive Endoscopy, 2015)
Optical biopsy techniques were recently introduced to luminal gastrointestinal endoscopy. These include confocal laser endomicroscopy, spectroscopic imaging techniques and endocytoscopy. Optical biopsy techniques allow on demand in vivo histology during ongoing endoscopy, thereby potentially accelerating clinical diagnosis and specific therapy. In the present review, we focus on endocytoscopy as one of the rapidly emerging optical biopsy techniques. We provide technical details of currently available endocytoscopy systems and give tips on their use in clinical practice. We also summarize applications of endocytoscopy for colorectal pathologies.
EVALuna2:2024

Advanced endoscopic imaging for diagnosis of Crohn's disease - Neumann, Helmut; Moenkemueller, Klaus; Günther, Claudia; Atreya, Raja; Neurath, Markus; Vieth, Michael (Gastroenterology Research and Practice, 2012)
Endoscopy in IBD has tremendous importance to diagnose inflammatory activity, to evaluate therapeutic success and for the surveillance of colitis associated cancer. Thus it becomes obvious that there is a need for new and more advanced endoscopic imaging techniques for better characterization of mucosal inflammation and early neoplasia detection in IBD. This paper describes the concept of advanced endoscopic imaging for the diagnosis and characterization of Crohn's disease, including magnification endoscopy, chromoendoscopy, balloon-assisted enteroscopy, capsule endoscopy, confocal laser endomicroscopy, and endocytoscopy. Copyright © 2012 Helmut Neumann et al.
CRIS-Team Scopus Importer:2020-10-28

Advanced Endoscopic Imaging in Colonic Neoplasia - Rath, Timo; Morgenstern, Nadine; Vitali, Francesco; Atreya, Raja; Neurath, Markus (Visceral Medicine, 2020)
Background: Endoscopic imaging is a rapidly evolving field with a constant influx of new concepts and technologies. Since the introduction of video endoscopy and subsequently high-definition imaging as the first revolutions in gastrointestinal endoscopy, several technologies of virtual chromoendoscopy have been developed and brought to the market in the past decade, which have shaped and revolutionized for a second time our approach to endoscopic imaging. In parallel to these developments, microscopic imaging technologies, such as endomicroscopy and endocytoscopy, allow us to examine single cells within the mucosa in real time, thereby enabling histological diagnoses during ongoing endoscopy. Summary: In this review, we provide an overview on the technical background of different technologies of advanced endoscopic imaging, and then review and discuss their role and applications for the diagnosis and management of colorectal neoplasms as well as limitations and challenges that exist despite all technological improvements. Key Messages: Technologies of advanced endoscopic imaging have profound impact not only on our imaging capabilities, they are also about to fundamentally change our approach to managing lesions in the gastrointestinal tract: Not every lesion found during colonoscopy has to be excised or sent for histopathologic evaluation. However, before this becomes widespread reality, major obstacles such as patient acceptance, adoption by less trained endoscopists, and also legal aspects need to carefully addressed. The development of computer-aided diagnosis and artificial intelligence algorithms hold the potential to overcome the obstacles associated with the concept of optical biopsy and will most likely fundamentally facilitate, shape, and change decision making in the management of colorectal lesions.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Colorectal cancer; Colorectal polyps; Endocytoscopy; Endomicroscopy; Endoscopy

Advanced endoscopic imaging techniques in Crohn's disease - Tontini, Gian Eugenio; Vecchi, Maurizio; Neurath, Markus; Neumann, Helmut (Journal of Crohns & Colitis, 2014)
Endoscopy is of pivotal importance in Crohn's disease (CD) patients for diagnosis, surveillance and assessment of disease activity and extent. Device-assisted enteroscopy (DAE) and small-bowel capsule endoscopy (SBCE) have recently changed our endoscopic approach to small-bowel imaging. Furthermore, new advanced endoscopic imaging techniques have been implemented into clinical practice to improve both characterization of mucosal inflammation and detection of dysplastic lesions.To provide readers with a review about the concept of advanced endoscopic imaging for the diagnosis and characterization of CD.A literature search on the use of advanced endoscopy techniques in IBD patients was performed.DAE and SBCE allow for deep enteroscopy with high diagnostic yields and low complication's rate but their collocation in the diagnostic algorithm is still not clearly defined. Dye-based chromoendoscopy (DBC) and magnification chromoendoscopy improved dysplasia's detection in long standing colitis and prediction of inflammatory activity and extent. Dye-less chromoendoscopy (DLC) might offer the potential to replace conventional DBC for surveillance. However, both narrow band imaging and i-scan have already shown to significantly improve activity and extent assessment in comparison to white-light endoscopy. Confocal laser endomicroscopy (CLE) can detect more dysplastic lesions in surveillance colonoscopy and predict neoplastic and inflammatory changes with high accuracy compared to histology. Moreover, CLE-based molecular imaging may anticipate the therapeutic responses to biological therapy. Endocytoscopy can identify in vivo inflammatory mucosal cells harboring a new method to assess the mucosal activity.Recent progresses in small-bowel enteroscopy offer several potential benefits to improve both diagnosis and characterization of CD. New advanced endoscopic imaging techniques can improve detection of dysplasia and refine mucosal healing assessment, even looking beyond the morphological parameters revealed by conventional endoscopic imaging.
EVALuna2:1907

Advanced endoscopic imaging using narrow-band imaging for diagnosis of Whipple's disease - Neumann, Helmut; Mönkemüller, K.; Neurath, Markus; Vieth, M. (Endoscopy, 2012)
CRIS-Team Scopus Importer:2025-03-05

Advanced endoscopy imaging in inflammatory bowel diseases - Kiesslich, Ralf; Neurath, Markus (Gastrointestinal Endoscopy, 2017)
BACKGROUND AND AIMS: Rapid assessment of mucosal inflammation is of crucial importance for the initial diagnosis and the assessment of mucosal healing in inflammatory bowel disease (IBD). Moreover, the identification of intraepithelial neoplasias in IBD is of key relevance for clinical management. Here, we systematically analyzed the utility of advanced endoscopic imaging techniques for optimized diagnosis in IBD. METHODS: PubMed/Medline, Web of Knowledge, and Cochrane library were searched twice for diagnostic studies on advanced endoscopic imaging in IBD. Clinical and technical information was retrieved and subsequently analyzed. Main outcome parameters consisted of the quality of the results, adverse events, and diagnostic yield. RESULTS: Fifty-six clinical studies with a total of 3296 patients were selected for final analysis. Filter technologies permitted a more detailed analysis of mucosal inflammation in IBD. In spite of substantial heterogeneity across studies, dye-based chromoendoscopy with targeted biopsy sampling yielded higher detection rates of intraepithelial neoplasias in ulcerative colitis as compared with white-light endoscopy with random biopsy sampling. Moreover, endocytoscopy and endomicroscopy allowed subsurface imaging of inflamed or neoplastic mucosa in IBD at subcellular resolution. Finally, endomicroscopy-aided molecular imaging enabled the identification of membrane-bound tumor necrosis factor on mucosal cells as a potential driver of disease activity in Crohn's disease. No relevant adverse events were reported. CONCLUSIONS: Advanced endoscopic imaging technologies are feasible, safe, and partially effective tools for detailed diagnosis of mucosal inflammation and detection of neoplasias in IBD. Results obtained from these advanced techniques may provide a rational basis for individualized, optimized therapy for IBD patients.
EVALuna2:33824

Advanced Imaging of Lung Homing Human Lymphocytes in an Experimental In Vivo Model of Allergic Inflammation Based on Light-sheet Microscopy - Schulz-Kuhnt, Anja; Zundler, Sebastian; Grüneboom, Anika; Neufert, Clemens; Wirtz, Stefan; Neurath, Markus; Atreya, Imke (Journal of Visualized Experiments, 2019)
Overwhelming tissue accumulation of highly activated immune cells represents a hallmark of various chronic inflammatory diseases and emerged as an attractive therapeutic target in the clinical management of affected patients. In order to further optimize strategies aiming at therapeutic regulation of pathologically imbalanced tissue infiltration of pro-inflammatory immune cells, it will be of particular importance to achieve improved insights into disease- and organ-specific homing properties of peripheral lymphocytes. The here described experimental protocol allows to monitor lung accumulation of fluorescently labeled and adoptively transferred human lymphocytes in the context of papain-induced pulmonary inflammation. In contrast to standard in vitro assays frequently used for the analysis of immune cell migration and chemotaxis, the now introduced in vivo setting takes into account lung-specific aspects of tissue organization and the influence of the complex inflammatory scenario taking place in the living murine organism. Moreover, three-dimensional cross-sectional light-sheet fluorescence microscopic imaging does not only provide quantitative data on infiltrating immune cells, but also depicts the pattern of immune cell localization within the inflamed lung. Overall, we are able to introduce an innovative technique of high value for immunological research in the field of chronic inflammatory lung diseases, which can be easily applied by following the provided step-by-step protocol.
CRIS-Team Scopus Importer:2019-05-24

Advances in detection and management of dysplasia in inflammatory bowel disease: Is endoscopic submucosal dissection ready for prime time in inflammatory bowel disease? - Kiesslich, Ralf; Neurath, Markus (Gastrointestinal Endoscopy, 2015)
EVALuna2:1981

Advances in hepatitis C therapy: What is the current state - what come's next? - Zopf, Steffen; Kremer, Andreas; Neurath, Markus; Siebler, Jürgen (World Journal of Hepatology, 2016)
Chronic hepatitis C virus (HCV) infection affects 80-160 million people worldwide and is one of the leading causes of chronic liver disease. It is only a few years ago that standard treatment regimes were based on pegylated interferon alpha and ribavirin. However, treatment of HCV has undergone a revolutionary change in recent years. The admission of the nucleotide polymerase inhibitor Sofosbuvir enabled an interferon-free regimen with direct antiviral agents (DAA). Meanwhile seven DAAs are available and can be applied in several combinations for 8 to 24 wk depending on HCV genotype and patient characteristics such as cirrhosis and chronic renal failure. High rates of sustained virological response (SVR) rates can be achieved with these novel drugs. Even in difficult to treat populations such as patients with liver cirrhosis, HCV-human immunodeficiency virus co-infections, after liver transplantion, or with chronic kidney disease comparable high rates of SVR can be achieved. The anticipated 2(nd) generation DAAs are strikingly effective in patients so far classified as difficult to treat including decompensated liver cirrhosis or post-transplant patients. These 2(nd) generations DAAs will have higher resistance barriers, higher antiviral effects and a pan-genotypic spectrum. This review highlights the current state of the art of antiviral treatment in hepatitis C and gives an outlook for upcoming therapies.
EVALuna2:2078

Advances in imaging to allow personalized medicine in Crohn's disease - Neurath, Markus (Current Opinion in Pharmacology, 2015)
Crohn's disease is a destructive inflammatory bowel disease of unknown origin that may lead to various complications such as strictures, stenosis, fistulas and colitis-associated neoplasias. However, the course of the disease varies substantially among patients and disease behaviour may also change with time. At diagnosis behaviour is inflammatory in the majority of patients, while penetrating or structuring behaviour become more prominent at later time points. Thus, medication in Crohn's disease needs frequent optimization over time. Therefore, new strategies for prediction of response to therapy are urgently needed. Here, recent advantages in imaging techniques for personalized medicine in Crohn's disease are reviewed. Such advantages include ultrasonography, computed tomography, magnetic resonance imaging and new endoscopic approaches such as molecular endoscopy. It is expected that these novel techniques will lead to marked improvements in the assessment of disease behaviour and the prediction of response to clinical therapy with biologicals.
EVALuna2:1980

A group of cationic amphiphilic drugs activates MRGPRX2 and induces scratching behavior in mice - Wolf, Katharina; Kühn, Helen; Boehm, Felicitas; Gebhardt, Lisa; Glaudo, Markus; Agelopoulos, Konstantin; Ständer, Sonja; Ectors, Philipp; Zahn, Dirk; Riedel, Yvonne K.; Thimm, Dominik; Müller, Christa E.; et al. (Journal of Allergy and Clinical Immunology, 2021)
Background: Mas gene–related G protein–coupled receptors (MRGPRs) are a G protein–coupled receptor family responsive to various exogenous and endogenous agonists, playing a fundamental role in pain and itch sensation. The primate-specific family member MRGPRX2 and its murine orthologue MRGPRB2 are expressed by mast cells mediating IgE-independent signaling and pseudoallergic drug reactions. Objectives: Our aim was to increase knowledge about the function and regulation of MRGPRX2/MRGPRB2, which is of major importance in prevention of drug hypersensitivity reactions and drug-induced pruritus. Methods: To identify novel MRGPR (ant)agonists, we screened a library of pharmacologically active compounds by utilizing a high-throughput calcium mobilization assay. The identified hit compounds were analyzed for their pseudoallergic and pruritogenic effects in mice and human. Results: We found a class of commonly used drugs activating MRGPRX2 that, to a large extent, consists of antidepressants, antiallergic drugs, and antipsychotics. Three-dimensional pharmacophore modeling revealed structural similarities of the identified agonists, classifying them as cationic amphiphilic drugs. Mast cell activation was investigated by using the 3 representatively selected antidepressants clomipramine, paroxetine, and desipramine. Indeed, we were able to show a concentration-dependent activation and MRGPRX2-dependent degranulation of the human mast cell line LAD2 (Laboratory of Allergic Diseases-2). Furthermore, clomipramine, paroxetine, and desipramine were able to induce degranulation of human skin and murine peritoneal mast cells. These substances elicited dose-dependent scratching behavior following intradermal injection into C57BL/6 mice but less so in MRGPRB2-mutant mice, as well as wheal-and-flare reactions following intradermal injections in humans. Conclusion: Our results contribute to the characterization of structure-activity relationships and functionality of MRGPRX2 ligands and facilitate prediction of adverse reactions such as drug-induced pruritus to prevent severe drug hypersensitivity reactions.
CRIS-Team Scopus Importer:2021-04-19
Keywords: (drug-induced) pruritus; Mas gene–related G protein–coupled receptors; mast cells; pseudoallergic drug reactions

A Hybrid Type III Effectiveness-Implementation Trial to Optimize Medication Safety With Oral Antitumor Therapy in Real-World: The AMBORA Competence and Consultation Center. - Cuba, Lisa; Dürr, Pauline; Geßner, Katja; Häcker, Babette; Fietkau, Rainer; Siebler, Jürgen; Pavel, Marianne Ellen; Neurath, Markus; Berking, Carola; Wullich, Bernd; Brückl, Valeska; Beckmann, Matthias; et al. (JCO Oncology Practice, 2024)
PURPOSE: Implementation science endeavors to facilitate the translation of evidence-based research into clinical routine. The clinical pharmacological/pharmaceutical care program evaluated in the randomized AMBORA trial on medication safety with oral antitumor therapeutics (OAT) optimizes care delivery and provides significant benefits for patients, treatment teams, and health care systems. Thus, we aimed to investigate the implementation of this care program within the AMBORA Competence and Consultation Center (AMBORA Center). METHODS: The AMBORA Center within a University Comprehensive Cancer Center offered several services (eg, patient consultations) and was evaluated according to the RE-AIM framework. This multicenter hybrid type III trial focused on implementation outcomes (eg, patient recruitment, referring units, evaluation of services) while concurrently investigating effectiveness (eg, side effects, medication errors). Quantitative and qualitative assessments were combined. RESULTS: The AMBORA Center conducted over 800 consultations with 420 patients in seven institutions. The primary end point of counseling 70% of patients treated with OAT was not reached. Patients were referred by 15 treatment units compared with 11 units in the AMBORA trial. On the basis of heterogeneous referral rates and characteristics across the institutions, barriers and facilitators of the implementation process were derived. Several survey results (eg, stakeholder interviews, online/paper-based questionnaires) reflected a high appreciation of services by patients and health care professionals. The severity of 60.1% (178 of 296) of detected side effects improved, and 86.3% (297 of 344) of medication errors were resolved. CONCLUSION: Despite not reaching the primary implementation outcome, the AMBORA Center included more treatment units and demonstrated patient benefit of the AMBORA care program by meeting all effectiveness outcomes. We outlined quantitative and qualitative implementation characteristics to enhance outreach and foster further dissemination of centers to optimize medication safety with OAT.
EVALuna2:569426

A key regulatory role for Vav1 in controlling lipopolysaccharide endotoxemia via macrophage-derived IL-6 - Zenker, Stefanie; Panteleev-Ivlev, Julia; Wirtz, Stefan; Kishimoto, Tadamitsu; Waldner, Maximilian; Ksionda, Olga; Tybulewicz, Victor L. J.; Neurath, Markus; Atreya, Imke (Journal of Immunology, 2014)
Macrophages are centrally involved in the pathogenesis of acute inflammatory diseases, peritonitis, endotoxemia, and septic shock. However, the molecular mechanisms controlling such macrophage activation are incompletely understood. In this article, we provide evidence that Vav1, a member of the RhoGEF family, plays a crucial role in macrophage activation and septic endotoxemia. Vav1-deficient mice demonstrated a significantly increased susceptibility for LPS endotoxemia that could be abrogated by anti-IL-6R Ab treatment. Subsequent studies showed that Vav1-deficient macrophages display augmented production of the proinflammatory cytokine IL-6. Nuclear Vav1 was identified as a key negative regulator of macrophage-derived IL-6 production. In fact, Vav1 formed a nuclear DNA-binding complex with heat shock transcription factor 1 at the HSE2 region of the IL-6 promoter to suppress IL-6 gene transcription in macrophages. These findings provide new insights into the pathogenesis of endotoxemia and suggest new avenues for therapy.
EVALuna2:1870

A large cohort of patients with hepatocellular carcinoma in a single European centre: aetiology and prognosis now and in a historical cohort - Ganslmayer, Marion; Hagel, Alexander; Dauth, Wolfgang; Zopf, Steffen; Strobel, Deike; Mueller, Volker; Uder, Michael; Neurath, Markus; Siebler, Jürgen (Swiss Medical Weekly, 2014)
The incidence of hepatocellular carcinoma is rising. However, this is occurring not only in developing nations, but in industrial countries as well. Surveillance programmes, classification systems and therapeutic options have improved, but there is a lack of data regarding their impact on the prognosis of this difficult-to-treat cancer.We evaluated 484 patients and reported on disease stage, therapeutic procedures and survival time. Data were compared with a historical cohort treated in the same centre 10 years before.In this cohort, the main reason for liver disease was alcoholism, although hepatitis B remains the leading cause of hepatocellular carcinoma worldwide. Now, most patients have compensated liver function and hepatocellular carcinoma is diagnosed in the early tumour stages (it was diagnosed in the advanced disease stages in the previous cohort). Overall, median survival time was 62.4 weeks, 1-year survival was 58.6% and 3-year survival was 23.2%. Survival time correlated with the stage of liver disease, tumour stage and with therapeutic options.Surveillance programmes lead to diagnosis in earlier tumour stages. Differentiated classification systems allow individualised therapeutic approaches. Earlier cancer stage and compensated liver function allow combination or sequential therapy, which was nearly impossible some years ago but is an option for most now. Primary liver cancer remains a difficult-to-treat malignancy, but the prognosis has improved remarkably, at least in the western world.
EVALuna2:1851

All are Equal, Some are More Equal: Targeting IL 12 and 23 in IBD - A Clinical Perspective - Jefremow, Andre; Neurath, Markus (ImmunoTargets and Therapy, 2020)
Chronic inflammatory diseases like inflammatory bowel diseases (IBD) or psoriasis represents a worldwide health burden. Researchers provided great achievements in understanding the origin of these diseases leading to improved therapeutic options. The discovery of cytokines like tumor necrosis factor-a or transforming growth factor-beta are examples for these efforts. Interleukin 12 (IL 12) and interleukin 23 (IL 23) represent different important cytokines in this regard. They both belong to the interleukin 12 family and are related by sharing the subunit p40. Ustekinumab is an antibody that blocks p40 and thereby interleukins 12 and 23. Trials showed promising results in treating IBD patients with this drug. Consequently, new questions arose about the distinct features of IL 12 and 23. This review focuses on these interleukins regarding their functions in the healthy and inflamed gut and provides an overview about the results from in vitro and in vivo studies as well as clinical trials.
CRIS-Team WoS Importer:2021-01-22

Alpha 4 beta 7 Integrin-dependent gut homing of non-classical monocytes is essential for intestinal wound healing mediated by M2 macrophages - Schleier, L.; Wiendl, Maximilian; Binder, M. -T.; Atreya, Raja; Watson, A.; Neufert, Clemens; Atreya, I.; Neurath, Markus; Zundler, Sebastian (2018)
EVALuna2:34111

Alternative Splice Forms of CYLD Mediate Ubiquitination of SMAD7 to Prevent TGFB Signaling and Promote Colitis - Tang, Yilang; Reissig, Sonja; Glasmacher, Elke; Regen, Tommy; Wanke, Florian; Nikolaev, Alexei; Gerlach, Katharina; Popp, Vanessa; Karram, Khalad; Fantini, Massimo C.; Schattenberg, Jam M.; Galle, Peter R.; et al. (Gastroenterology, 2019)
BACKGROUND & AIMS: The CYLD lysine 63 deubiquitinase gene (CYLD) encodes tumor suppressor protein that is mutated in familial cylindromatosus, and variants have been associated with Crohn disease (CD). Splice forms of CYLD that lack exons 7 and 8 regulate transcription factors and functions of immune cells. We examined the expression of splice forms of CYLD in colon tissues from patients with CD and their effects in mice. METHODS: We performed immunohistochemical analyses of colon tissues from patients with untreated CD and patients without inflammatory bowel diseases (controls). We obtained mice that expressed splice forms of CYLD (sCYLD mice) without or with SMAD7 (sCYLD/SMAD7 mice) from transgenes and CYLD-knockout mice (with or without transgenic expression of SMAD7) and performed endoscopic analyses. Colitis was induced in Rag1(-/-) mice by transfer of CD4(+) CD62L(+) T cells from C57/Bl6 or transgenic mice. T cells were isolated from mice and analyzed by flow cytometry and quantitative realtime polymerase chain reaction and intestinal tissues were analyzed by histology and immunohistochemistry. CYLD forms were expressed in mouse embryonic fibroblasts, primary T cells, and HEK293T cells, which were analyzed by immunoblot, mobility shift, and immunoprecipitation assays. RESULTS: The colonic lamina propria from patients with CD was infiltrated by T cells and had higher levels of sCYLD (but not full-length CYLD) and SMAD7 than tissues from controls. Incubation of mouse embryonic fibroblasts and T cells with transforming growth factor b increased their production of sCYLD and decreased full-length CYLD. Transgenic expression of sCYLD and SMAD7 in T cells prevented the differentiation of regulatory T cells and T-helper type 17 cells and increased the differentiation of T-helper type 1 cells. The same effects were observed in colon tissues from sCYLD/SMAD7 mice but not in those from CYLD-knockout SMAD7 mice. The sCYLD mice had significant increases in the numbers of T-helper type 1 cells and CD44high CD62Llow memory-effector CD4(+) T cells in the spleen and mesenteric lymph nodes compared with wild-type mice; sCYLD/SMAD7 mice had even larger increases. The sCYLD/ SMAD7 mice spontaneously developed severe colitis, with infiltration of the colon by dendritic cells, neutrophils, macrophages, and CD4(+) T cells and increased levels of Ifng, Il6, Il12a, Il23a, and Tnf mRNAs. Co-transfer of regulatory T cells from wild-type, but not from sCYLD/SMAD7, mice prevented the induction of colitis in Rag1(-/-) mice by CD4(+) T cells. We found increased levels of poly-ubiquitinated SMAD7 in sCYLD CD4(+)T cells. CYLD formed a nuclear complex with SMAD3, whereas sCYLD recruited SMAD7 to the nucleus, which inhibited the expression of genes regulated by SMAD3 and SMAD4. We found that sCYLD mediated lysine 63-linked ubiquitination of SMAD7. The sCYLD-SMAD7 complex inhibited transforming growth factor beta signaling in CD4(+)T cells. CONCLUSIONS: Levels of the spliced form of CYLD are increased in colon tissues from patients with CD. sCYLD mediates ubiquitination and nuclear translocation of SMAD7 and thereby decreases transforming growth factor beta signaling in T cells. This prevents immune regulatory mechanisms and leads to colitis in mice.
CRIS-Team WoS Importer:2019-02-21

Alzheimer’s disease-related presenilins are key to intestinal epithelial cell function and gut immune homoeostasis - Erkert, Lena; Gamez-Belmonte, Reyes; Kabisch, Melanie; Schödel, Lena; Patankar, Jay; Gonzalez Acera, Miguel; Mahapatro, Mousumi; Bao, Lili; Plattner, Christina; Kühl, Anja A.; Shen, Jie; Serneels, Lutgarde; et al. (Gut, 2024)
Objective Mutations in presenilin genes are the major cause of Alzheimer’s disease. However, little is known about their expression and function in the gut. In this study, we identify the presenilins Psen1 and Psen2 as key molecules that maintain intestinal homoeostasis. Design Human inflammatory bowel disease (IBD) and control samples were analysed for Psen1 expression. Newly generated intestinal epithelium-specific Psen1-deficient, Psen2-deficient and inducible Psen1/Psen2 double-deficient mice were used to dissect the functional role of presenilins in intestinal homoeostasis. Results Psen1 expression was regulated in experimental gut inflammation and in patients with IBD. Induced deletion of Psen1 and Psen2 in mice caused rapid weight loss and spontaneous development of intestinal inflammation. Mice exhibited epithelial barrier disruption with bacterial translocation and deregulation of key pathways for nutrient uptake. Wasting disease was independent of gut inflammation and dysbiosis, as depletion of microbiota rescued Psen-deficient animals from spontaneous colitis development but not from weight loss. On a molecular level, intestinal epithelial cells lacking Psen showed impaired Notch signalling and dysregulated epithelial differentiation. Conclusion Overall, our study provides evidence that Psen1 and Psen2 are important guardians of intestinal homoeostasis and future targets for barrier-promoting therapeutic strategies in IBD.
CRIS-Team Scopus Importer:2024-08-30

An IFN-STAT1-MLKL axis drives programmed necrosis of Paneth cells in Crohn's ileitis - Hartmann, Leonie; Siegmund, B.; Weidinger, C.; Becker, Christoph; Neurath, Markus; Günther, Claudia (JOURNAL OF CROHNS & COLITIS, 2020)
CRIS-Team WoS Importer:2020-04-10

An IFN-STAT Axis Augments Tissue Damage and Inflammation in a Mouse Model of Crohn's Disease - Stolzer, Iris; Dressel, Anja; Neurath, Markus; Günther, Claudia; Chiriac, Mircea-Teodor (Frontiers in Medicine, 2021)
Blocking interferon-function by therapeutic intervention of the JAK-STAT-axis is a novel promising treatment option for inflammatory bowel disease (IBD). Although JAK inhibitors have proven efficacy in patients with active ulcerative colitis (UC), they failed to induce clinical remission in patients with Crohn's disease (CD). This finding strongly implicates a differential contribution of JAK signaling in both entities. Here, we dissected the contribution of different STAT members downstream of JAK to inflammation and barrier dysfunction in a mouse model of Crohn's disease like ileitis and colitis (Casp8ΔIEC mice). Deletion of STAT1 in Casp8ΔIEC mice was associated with reduced cell death and a partial rescue of Paneth cell function in the small intestine. Likewise, organoids derived from the small intestine of these mice were less sensitive to cell death triggered by IBD-key cytokines such as TNFα or IFNs. Further functional in vitro and in vivo analyses revealed the impairment of MLKL-mediated necrosis as a result of deficient STAT1 function, which was in turn associated with improved cell survival. However, a decrease in inflammatory cell death was still associated with mild inflammation in the small intestine. The impact of STAT1 signaling on gastrointestinal inflammation dependent on the localization of inflammation, as STAT1 is essential for intestinal epithelial cell death regulation in the small intestine, whereas it is not the key factor for intestinal epithelial cell death in the context of colitis. Of note, additional deletion of STAT2 was not sufficient to restore Paneth cell function but strongly ameliorated ileitis. In summary, we provide here compelling molecular evidence that STAT1 and STAT2, both contribute to intestinal homeostasis, but have non-redundant functions. Our results further demonstrate that STATs individually affect the distinct pathophysiology of inflammation in the ileum and colon, respectively, which might explain the diverse outcome of JAK inhibitors on inflammatory bowel diseases.
CRIS-Team Scopus Importer:2021-06-25
Keywords: cell death; inflammation; inflammatory bowel disease; Paneth cells; STAT signaling

An intravital microscopy-based approach to assess intestinal permeability and epithelial cell shedding performance - Martínez Sánchez, Luz del Carmen; Pradhan, Rashmita; Ngo, Phuong A.; Erkert, Lena; Becker, Lea; Watson, Alastair J.; Atreya, Imke; Neurath, Markus; Lopez Posadas, Rocío (Journal of Visualized Experiments, 2020)
Intravital microscopy of the gut using confocal imaging allows real time observation of epithelial cell shedding and barrier leakage in living animals. Therefore, the intestinal mucosa of anesthetized mice is topically stained with unspecific staining (acriflavine) and a fluorescent tracer (rhodamine-B dextran), mounted on a saline solution-rinsed plate and directly imaged using a confocal microscope. This technique can complement other non-invasive techniques to identify leakage of intestinal permeability, such as transmucosal passage of orally administered tracers. Besides this, the approach presented here allows the direct observation of cell shedding events at real-time. In combination with appropriate fluorescent reporter mice, this approach is suitable for shedding light into cellular and molecular mechanisms controlling intestinal epithelial cell extrusion, as well as to other biological processes. In the last decades, interesting studies using intravital microscopy have contributed to knowledge on endothelial permeability, immune cell gut homing, immune-epithelial communication and invasion of luminal components, among others. Together, the protocol presented here would not only help increase the understanding of mechanisms controlling epithelial cell extrusion, but could also be the basis for the developmental of other approaches to be used as instruments to visualize other highly dynamic cellular process, even in other tissues. Among technical limitations, optical properties of the specific tissue, as well as the selected imaging technology and microscope configuration, would in turn, determine the imaging working distance, and resolution of acquired images.
CRIS-Team Scopus Importer:2020-12-25

A Novel Mobile Phone App (OncoFood) to Record and Optimize the Dietary Behavior of Oncologic Patients: Pilot Study - Orlemann, Till; Reljic, Dejan; Zenker, Björn; Meyers, Julia; Eskofier, Björn; Thiemt, Jana; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (JMIR Cancer, 2018)
BACKGROUND: Catabolism and tumor-specific therapy lead to reduced nutrient intake and weight loss in cancer patients. Maintaining a specific individualized diet can be challenging for the patient as the nutritional counseling options are limited. Monitoring of nutrient intake and frequent feedback are, however, vital for successful nutritional therapy because they support the patient's compliance and realization of dietary therapeutic goals. OBJECTIVE: This study aimed at investigating the feasibility and applicability of a novel mobile phone app to assess and evaluate dietary behaviors in oncologic patients. METHODS: To determine dietary habits and food preferences in oncologic patients, initially 1400 nutritional records were evaluated and analyzed. The results provided the basis for creating a nutritional mobile phone app. Key requirements for the app included simple handling, recording the daily intake, and a comparison of nutrient targets and current status. In total, 39 cancer patients were recruited for the study; 15 patients dropped out prior to the study. All patients received a nutritional anamnesis, nutritional analysis, and nutritional counseling. Individual energy and nutrient aims were defined. The intervention group (n=12) additionally used the app. Weight and body composition of each group were evaluated after 4 weeks. RESULTS: The app group gained significantly more weight (P=.045; mean weight 1.03 kg vs -1.46 kg). Also, skeletal muscle mass showed a significant increase in the app group (P=.009; mean skeletal muscle mass 0.58 kg vs -0.61 kg) compared with the control group. There was no significant difference between groups relating to the daily protein intake (P=.06). Additionally, there was a decrease in macronutrient intake during the study period in the control group. CONCLUSIONS: Our study indicates that patients who track their daily dietary habits using a mobile phone app are more likely to reach their nutritional goals than the control patients. Further large-scale studies are needed to confirm these initial findings and test the applicability on a broader basis.
EVALuna2:208323

Anti-beta 7 integrin treatment impedes the recruitment on non-classical monocytes to the gut and delays macrophage-mediated intestinal wound healing - Sommer, Katrin; Heidbreder, Karin; Kreiß, Lucas; Dedden, Mark; Paap, Eva-Maria; Wiendl, Maximilian; Becker, Emily; Atreya, Raja; Müller, Tanja; Atreya, Imke; Waldner, Maximilian; Schürmann, Sebastian; et al. (Clinical and Translational Medicine, 2023)
BackgroundClosing mucosal defects to reach mucosal healing is an important goal of therapy in inflammatory bowel disease (IBD). Among other cells, monocyte-derived macrophages are centrally involved in such intestinal wound healing. We had previously demonstrated that the anti-alpha 4 beta 7 integrin antibody vedolizumab blocks the recruitment of non-classical monocytes as biased progenitors of wound healing macrophages to the gut and delays wound healing. However, although important for the interpretation of disappointing results in recent phase III trials in IBD, the effects of the anti-beta 7 antibody etrolizumab on wound healing are unclear so far. MethodsWe analyzed the expression of etrolizumab targets on human and mouse monocyte subsets by flow cytometry and assessed their function in adhesion and homing assays. We explored wound-associated monocyte recruitment dynamics with multi-photon microscopy and compared the effects of etrolizumab and vedolizumab surrogate (-s) antibodies on experimental wound healing and wound-associated macrophage abundance. Finally, we investigated wound healing macrophage signatures in the large intestinal transcriptome of patients with Crohn's disease treated with etrolizumab. ResultsHuman and mouse non-classical monocytes expressed more alpha E beta 7 integrin than classical monocytes and were a target of etrolizumab-s, which blocked non-classical monocyte adhesion to MAdCAM-1 and E-Cadherin as well as gut homing in vivo. Intestinal wound healing was delayed on treatment with etrolizumab-s along with a reduction of peri-lesional wound healing macrophages. Wound healing macrophage signatures in the colon of patients with Crohn's disease were substantially down-regulated on treatment with etrolizumab, but not with placebo. ConclusionsCombined blockade of alpha E beta 7 and alpha 4 beta 7 with etrolizumab seems to exceed the effect of anti-alpha 4 beta 7 treatment on intestinal wound healing, which might help to inform further investigations to understand the recent observations in the etrolizumab phase III trial program.
CRIS-Team WoS Importer:2023-05-05

ANTICOAGULANT-RELATED GASTROINTESTINAL BLEEDING: A REAL-LIFE DATA ANALYSIS ON BLEEDING PROFILES, FREQUENCY AND ETIOLOGY OF PATIENTS RECEIVING DIRECT ORAL ANTICOAGULANTS VERSUS VITAMIN K ANTAGONISTS - Albrecht, Heinz; Maass, L. S.; Hagel, Alexander; Neurath, Markus; Konturek, P. C.; Raithel, M. (Journal of Physiology and Pharmacology, 2019)
Vitamin K antagonists (VKA) continue to be the standard of long-term anticoagulation. Direct oral anticoagulants (DOAC) are increasingly used. In many trials DOAC were at least as effective as VKA. In this study we evaluate the bleeding profiles, frequencies and etiologies of patients receiving DOAC versus VKA in a real-life setting. All patients presenting with suspected gastrointestinal bleeding (GIB) in the emergency department of the University Hospital Erlangen in one year were enrolled in this study. They were looked up for the intake of either DOAC (dabigatran, rivaroxaban and apixaban) or VKA. The results showed that 406 patients with suspected GIB were admitted to the emergency unit of the University Hospital Erlangen. In 228 of those patients GIB could be verified (56.2%). Fifty four of those patients (23.7%) were administered either VKA or DOAC. In 35 of those 54 patients (64.8%) GIB was classified as 'major bleeding'. In 27 patients with administration of VKA upper GIB was recorded and lower GIB was detected four times. In 16 patients with administration of DOAC upper GIB was found and lower GIB was found in 7 patients. The presented data do not show higher GIB rates for DOAC (mainly dabigatran and rivaroxaban), but do also not indicate a significantly higher safety of DOAC concerning GIB than VKA. This finding represents a clear contrast to the reduced bleeding rates of DOAC for intracerebral bleeding and other non-GIB events. According to our study, the absolute number of DOAC-associated GIB events is lower than in the VKA group.
CRIS-Team WoS Importer:2020-04-28

Anti-TNF-refractory colitis after checkpoint inhibitor therapy: Possible role of CMV-mediated immunopathogenesis - Lankes, Katharina; Hundorfean, Gheorghe; Harrer, Thomas; Pommer, Ansgar J.; Agaimy, Abbas; Angelovska, Irena; Tajmir-Riahi, Azadeh; Göhl, Jonas; Schuler, Gerold; Neurath, Markus; Hohenberger, Werner; Heinzerling, Lucie (OncoImmunology, 2016)
Immune-related adverse events (irAEs) induced by checkpoint inhibitors are well known. Since fatal outcomes have been reported early detection and adequate management are crucial. In particular, colitis is frequently observed and can result in intestinal perforation. This is the first report of an autoimmune colitis that was treated according to algorithms but became resistant due to a CMV reactivation. The 32-y-old male patient with metastatic melanoma treated within an anti-PD-1/ipilimumab combination study developed severe immune-mediated colitis (CTCAE grade 3) with up to 18 watery stools per day starting 2 weeks after treatment initiation. After improving upon therapy with immunosuppressive treatment (high dose steroids and infliximab) combined with parenteral nutrition diarrhea again exacerbated. Additionally, the patient had asymptomatic grade 3 CTCAE amylase and lipase elevation. Colitis was monitored by weekly endoscopies and colon biopsies were analyzed histologically with CMV staining, multi-epitope ligand cartography (MELC) and qRT-PCR for inflammatory genes. In the course, CMV reactivation was detected in the colon and treated with antiviral medication in parallel to a reduction of corticosteroids. Subsequently, symptoms improved. The patient showed a complete response for 2 y now including regression of bone metastases. CMV reactivation under checkpoint inhibitor therapy in combination with immunosuppressive treatment for autoimmune side effects has to be considered in these patients and if present treated. Potentially, CMV reactivation is underdiagnosed. Treatment algorithms should include CMV diagnostics.
EVALuna2:2063

Anti-trafficking agents in the treatment of inflammatory bowel disease - Zundler, Sebastian; Wiendl, Maximilian; Neurath, Markus (Current Opinion in Gastroenterology, 2019)
Purpose of review To describe the latest developments in the field of anti-trafficking agents (ATAs), a class of therapeutics with growing importance in the field of inflammatory bowel diseases (IBDs) that specifically inhibit steps of immune cell trafficking. Recent findings Several translational and clinical studies have further shaped the knowledge about the mechanisms and effects of the anti-α4β7 integrin antibody vedolizumab. In parallel, new ATAs like the anti-β7 integrin antibody etrolizumab and the anti-MAdCAM-1 antibody ontamalimab are investigated in phase III clinical trials and might soon increase the therapeutic armamentarium in IBD. Summary ATAs have unique mechanisms of action and can meanwhile be considered an indispensable column of IBD therapy. Further efforts are necessary to elucidate complex mechanistic aspects, to exactly define their role in relation to other therapeutic approaches and to identify novel treatment targets as well as biomarkers for personalized medicine.
CRIS-Team Scopus Importer:2019-10-01
Keywords: etrolizumab; gut homing; ontamalimab; trafficking; vedolizumab

Apoptosis, necrosis and necroptosis: cell death regulation in the intestinal epithelium. - Günther, Claudia; Neumann, Helmut; Neurath, Markus; Becker, Christoph (Gut, 2013)
Intestinal epithelial cells (IEC) are organised as a single cell layer which covers the intestine. Their primary task is to absorb nutrients present in the intestinal lumen. However, IEC also play an important role in the immune defence of our body by building a barrier that separates the bowel wall from potentially hazardous bacteria present in the gut lumen. The life cycle of IEC is determined by the time span in which cells migrate from their place of origin at the crypt base to the villus tip, from where they are shed into the lumen. Cell death in the intestinal epithelium has to be tightly regulated and irregularities might cause pathologies. Excessive cell death has been associated with chronic inflammation as seen in patients with Crohn's disease and ulcerative colitis. While until recently apoptosis was discussed as being essential for epithelial turnover and tissue homeostasis in the intestinal epithelium, recent data using gene deficient mice have challenged this concept. Moreover, an apoptosis-independent mode of programmed cell death, termed necroptosis, has been identified and described in the intestinal epithelium. The following article reviews previous studies on cell death regulation in IEC and a potential role of necroptosis for gut homeostasis.
Keywords: Cell death; Paneth cells; RIP; bacterial translocation; caspase-8; cytokines; endoscopy; epithelial cells; gene expression; inflammatory bowel disease; necroptosis; signal transduction

Apoptosis, necrosis and necroptosis: cell death regulation in the intestinal epithelium. - Günther, Claudia; Neumann, Helmut; Neurath, Markus; Becker, Christoph (Gut, 2013)
Intestinal epithelial cells (IEC) are organised as a single cell layer which covers the intestine. Their primary task is to absorb nutrients present in the intestinal lumen. However, IEC also play an important role in the immune defence of our body by building a barrier that separates the bowel wall from potentially hazardous bacteria present in the gut lumen. The life cycle of IEC is determined by the time span in which cells migrate from their place of origin at the crypt base to the villus tip, from where they are shed into the lumen. Cell death in the intestinal epithelium has to be tightly regulated and irregularities might cause pathologies. Excessive cell death has been associated with chronic inflammation as seen in patients with Crohn's disease and ulcerative colitis. While until recently apoptosis was discussed as being essential for epithelial turnover and tissue homeostasis in the intestinal epithelium, recent data using gene deficient mice have challenged this concept. Moreover, an apoptosis-independent mode of programmed cell death, termed necroptosis, has been identified and described in the intestinal epithelium. The following article reviews previous studies on cell death regulation in IEC and a potential role of necroptosis for gut homeostasis.
Keywords: Cell death; Paneth cells; RIP; bacterial translocation; caspase-8; cytokines; endoscopy; epithelial cells; gene expression; inflammatory bowel disease; necroptosis; signal transduction.

A Possible Distinct Molecular Subtype (Quintuple-Wildtype) of Metastatic Colorectal Cancer in First-Line Anti-EGFR Therapy with Cetuximab Plus FOLFIRI - Palliative Precision Therapy and a Multidisciplinary Treatment Approach: Interim Analysis of the IVOPAK II Trial with Early Results - Wein, Axel; Stöhr, Robert; Kersting, Stephan; Siebler, Jürgen; Merkel, Susanne; Busse, Daniel; Wolff, Kerstin; Ostermeier, Nicola; Neufert, Clemens; Vitali, Francesco; Eckstein, Markus; Roth, Jan-Peter; et al. (Oncology, 2021)
Objective: The study aimed to prospectively evaluate a new molecular biomarker panel (KRAS, NRAS, BRAF, PIK3CA, and ERBB2) for palliative first-line treatment of colorectal cancer (CRC), including a multidisciplinary treatment approach. The rate of secondary metastasis resections was assessed. Patients and Methods: A total of 40 patients with definitively nonresectable metastatic CRC were enrolled from 10 centers before the interim analysis (June 2019) of the IVOPAK II trial (Interdisciplinary Care with Quality Control in Palliative Treatment of Colorectal Cancer). After determination of 5 molecular biomarkers in the tumor (KRAS, exons 2-4; NRAS, exons 2-4; BRAF V600E; PIK3CA; and ERBB2), patients in the IVOPAK II study received FOLFIRI plus cetuximab for all-RAS/quintuple-wildtype disease and FOLFIRI plus bevacizumab in the case of RAS mutations. The current article presents the early description of the clinical outcome of the interim analysis of IVOPAK II comparing the all-RAS/quintuple-wildtype and RAS-mutations populations, including a multidisciplinary-treated case report of a quintuple-wildtype patient. Results: The quintuple-wildtype population treated with FOLFIRI plus cetuximab in first-line exhibited a significantly higher response rate and enhanced early tumor shrinkage in the interim analysis than the RAS-mutations population, as well as a high rate of secondary metastatic resections. Conclusion: Initial results of this new biomarker panel (quintuple-wildtype) are promising for anti-EGFR therapy with cetuximab plus doublet chemotherapy (FOLFIRI) in first-line treatment of metastatic CRC. These results warrant confirmation with higher case numbers in the IVOPAK II trial.
CRIS-Team WoS Importer:2021-11-05

Application of the BIA: Case studies from the University of Erlangen - Reljic, Dejan; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (Ernährungsumschau, 2019)
CRIS-Team Scopus Importer:2021-04-20

Application of the BIA Case Studies from the University of Erlangen - Reljic, Dejan; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (Ernährungsumschau, 2019)
CRIS-Team WoS Importer:2019-10-04

Apremilast for active ulcerative colitis: a phase 2, randomised, double-blind, placebo-controlled induction study - Danese, S.; Neurath, Markus; Kopon, A.; Zakko, S.; Simmons, T.; Fogel, R.; Maccarone, J.; Zhan, X.; Usiskin, K.; Chitkara, D. (2018)
EVALuna2:207780

Apremilast Prevents Intestinal Inflammation in Colitis Models via Influencing Epithelial Barrier - Weigmann, Benno; Popp, Vanessa; Neurath, Markus; Horan, Gerald; Schafer, Peter (2017)
EVALuna2:33923

Are Guideline Recommendations on Supportive Nutrition and Exercise Therapy for Cancer Patients Implemented in Clinical Routine? A National Survey with Real-Life Data - Hardt, Luisa; Herrmann, Hans J.; Reljic, Dejan; Jaensch, Peter; Zerth, Jürgen; Neurath, Markus; Zopf, Yurdagül (Nutrients, 2023)
Malnutrition and cancer cachexia are highly prevalent comorbidities of cancer, limiting patients’ quality of life and being relevant to prognosis. International and national clinical guidelines recommend supportive nutrition and exercise therapy for cancer patients. However, there is little current epidemiological evidence on the implementation of these guideline recommendations in clinical routine. To close this data gap, a national survey in Germany using an online questionnaire was conducted. There were 261 of a total of 5074 contacted hospitals and medical offices who participated in the survey (5.1% response rate). The data indicated that nutrition and exercise therapy for cancer patients is so far inadequately implemented, with 59% of the respondents reporting nutrition therapy as an integral part of oncological treatment, 66.7% having a nutrition specialist/team, and 65.1% routinely conducting a screening for nutritional status. Only half of the participants stated that there are defined goals in nutrition therapy. The majority of respondents (85.8%) generally recommend exercise therapy, but only a few of them provide specific offers at their own institution (19.6%) or at cooperation partners (31.7%). In order to implement the recommended combined nutrition and exercise therapy as part of regular care, there is a need for nationwide availability of multidisciplinary nutrition teams and targeted offers of individualized exercise therapy. Health policy support would be important to create the structural, financial, and staff conditions for appropriate guideline implementation in order to achieve the optimal treatment of cancer patients.
CRIS-Team Scopus Importer:2023-08-11
Keywords: cancer patients; exercise therapy; healthcare research; nutrition therapy; supportive cancer therapy; tumor cachexia

Artificial intelligence for the classification of focal liver lesions in ultrasound - a systematic review. - Vetter, Marcel; Waldner, Maximilian; Zundler, Sebastian; Klett, Daniel; Bocklitz, Thomas; Neurath, Markus; Adler, Werner; Jesper, Daniel (Ultraschall in der Medizin, 2023)
Focal liver lesions are detected in about 15% of abdominal ultrasound examinations. The diagnosis of frequent benign lesions can be determined reliably based on the characteristic B-mode appearance of cysts, hemangiomas, or typical focal fatty changes. In the case of focal liver lesions which remain unclear on B-mode ultrasound, contrast-enhanced ultrasound (CEUS) increases diagnostic accuracy for the distinction between benign and malignant liver lesions. Artificial intelligence describes applications that try to emulate human intelligence, at least in subfields such as the classification of images. Since ultrasound is considered to be a particularly examiner-dependent technique, the application of artificial intelligence could be an interesting approach for an objective and accurate diagnosis. In this systematic review we analyzed how artificial intelligence can be used to classify the benign or malignant nature and entity of focal liver lesions on the basis of B-mode or CEUS data. In a structured search on Scopus, Web of Science, PubMed, and IEEE, we found 52 studies that met the inclusion criteria. Studies showed good diagnostic performance for both the classification as benign or malignant and the differentiation of individual tumor entities. The results could be improved by inclusion of clinical parameters and were comparable to those of experienced investigators in terms of diagnostic accuracy. However, due to the limited spectrum of lesions included in the studies and a lack of independent validation cohorts, the transfer of the results into clinical practice is limited.
EVALuna2:550718

A Severe Case of Tuberculosis Radiologically and Endoscopically Mimicking Colorectal Cancer with Peritoneal Carcinomatosis - Rath, Timo; Atreya, Raja; Geissdorfer, Walter; Lang, Roland; Nägel, Andreas; Neurath, Markus (Case Reports in Gastrointestinal Medicine, 2017)
Although generally rising in incidence, intestinal tuberculosis is still rare in western countries and due to unspecific manifestations mainly as ulcerations on endoscopy, diagnosis of intestinal tuberculosis is challenging. Within this report, we describe a case of severe intestinal tuberculosis radiologically and endoscopically masquerading as colorectal cancer with peritoneal carcinomatosis. Our case exemplifies that intestinal tuberculosis needs to be considered as a differential diagnosis in patients at risk and that undelayed and sensitive diagnosis of intestinal tuberculosis is of central importance for avoiding unfavorable disease outcome.
EVALuna2:33728

A spotlight on intestinal permeability and inflammatory bowel diseases - Rath, Timo; Atreya, Raja; Neurath, Markus (Expert Review of Gastroenterology and Hepatology, 2023)
Introduction: The intestinal barrier is a multi-faced structure lining the surface of the intestinal mucosa of the GI tract. To exert its main functions as a physical and immunological defense barrier, several components of the intestinal barrier act in a concerted and cooperative manner. Areas covered: Herein, we first introduce to the basic organization of the intestinal barrier and then summarize different methods to assess barrier function in and ex vivo. Finally, we provide an in-depth overview of the relevance of intestinal barrier dysfunction in inflammatory bowel diseases. Expert opinion: In parallel to a more fundamental understanding of the intestinal barrier as a key component for intestinal integrity is the notion that intestinal barrier defects are associated with a variety of diseases such as inflammatory bowel diseases. Recent research has fueled and perpetuated the concept that barrier defects are critical components of disease development, disease behavior, and potentially also an area of therapeutic intervention in IBD patients. Although being far away from standard, new technologies can be used to easily assess barrier healing in IBD and to derive clinical consequences from these findings such as more accurate forecasting of future disease behavior or the identification of novel therapeutic targets.
CRIS-Team Scopus Importer:2023-11-24
Keywords: confocal laser endomicroscopy; Crohn’s disease; inflammatory bowel diseases; Intestinal barrier; intestinal permeability; leaky gut; ulcerative colitis

Assessing cachexia in older patients: Different definitions – But which one is the most practical for clinical routine? - Zopf, Yurdagül; Schink, Kristin; Reljic, Dejan; Herrmann, Hans J.; Dieterich, Walburga; Kiesswetter, Eva; Sieber, Cornel; Neurath, Markus; Volkert, Dorothee (Archives of gerontology and geriatrics, 2020)
Objective: Patients with chronic inflammatory diseases and malignant tumors have an increased risk of cachexia. No consistent definition exists to rapidly identify cachexia in older patients with and without cancer. Methods: One-hundred patients (53% male) aged 70 + years were included in the study by a university hospital. In addition to the detection of malnutrition and determination of body composition by bioelectrical impedance analysis, cachexia was assessed according to the well-established definitions of Evans (weight loss ≥ 5% within the last 12 months plus additional clinical parameters), Fearon (weight loss > 5% in 6 months) and Bozzetti (weight loss ≥ 10% of habitual weight). After a follow-up of 3.5 years, the mortality rate was recorded. Results: Thirty-three patients had a malignant tumor disease. The patients with a non-malignant underlying disease did not differ in their mental state, physical condition and state of health compared to patients with cancer. A higher percentage of patients with underlying malignancy had cachexia. There were significant differences in the body composition between the patients with or without cachexia. Cachectic patients exhibited a significantly lower skeletal muscle mass and fat mass. The risk of death was increased in cachectic patients of all three cachexia definitions. Conclusion: For clinical daily routine, the assessments by a weight loss according to Fearon and Bozzetti are suggested to be practicable methods to detect cachexia in older patients with and without cancer.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Body composition; Cachexia; Cancer; Malnutrition; Muscle mass; Weight loss

Assessment of gait parameters and physical function in patients with advanced cancer participating in a 12-week exercise and nutrition programme: A controlled clinical trial - Schink, Kristin; Gaßner, Heiko; Reljic, Dejan; Herrmann, Hans J.; Kemmler, Wolfgang; Schwappacher, Raphaela; Meyer, Julia; Eskofier, Björn; Winkler, Jürgen; Neurath, Markus; Klucken, Jochen; Zopf, Yurdagül (European Journal of Cancer Care, 2019)
Objective: Gait is a sensitive marker for functional declines commonly seen in patients treated for advanced cancer. We tested the effect of a combined exercise and nutrition programme on gait parameters of advanced-stage cancer patients using a novel wearable gait analysis system. Methods: Eighty patients were allocated to a control group with nutritional support or to an intervention group additionally receiving whole-body electromyostimulation (WB-EMS) training (2×/week). At baseline and after 12 weeks, physical function was assessed by a biosensor-based gait analysis during a six-minute walk test, a 30-s sit-to-stand test, a hand grip strength test, the Karnofsky Index and EORTC QLQ–C30 questionnaire. Body composition was measured by bioelectrical impedance analysis and inflammation by blood analysis. Results: Final analysis included 41 patients (56.1% male; 60.0 ± 13.0 years). After 12 weeks, the WB-EMS group showed higher stride length, gait velocity (p <.05), six-minute walking distance (p <.01), bodyweight and skeletal muscle mass, and emotional functioning (p <.05) compared with controls. Correlations between changes in gait and in body composition, physical function and inflammation were detected. Conclusion: Whole-body electromyostimulation combined with nutrition may help to improve gait and functional status of cancer patients. Sensor-based mobile gait analysis objectively reflects patients’ physical status and could support treatment decisions.
CRIS-Team Scopus Importer:2019-12-24
Keywords: cancer; exercise; gait; nutrition; physical function; whole-body electromyostimulation

Assessment of sorafenib induced changes in tumor perfusion of uveal melanoma metastases with dynamic contrast-enhanced ultrasound (DCE-US) - Wildner, Dane; Heinzerling, Lucie; Scheulen, Max E.; Kämpgen, Eckhart; Schuler, Gerold; Strobel, Deike; Janka, Rolf Matthias; Neurath, Markus; Sturm, Jörg; Knieling, Ferdinand (Journal of Cancer Research and Clinical Oncology, 2021)
Purpose Dynamic contrast-enhanced ultrasound (DCE-US) was used to monitor early response to sorafenib therapy in patients with liver metastases from uveal melanoma. Methods In total, 21 patients with liver metastases were recruited within a prospective trial and underwent daily sorafenib therapy. DCE-US of a target lesion was performed before initiation of treatment, on day 15 and 56. Two independent blinded investigators performed software analysis for DCE-US parameters and inter-observer-correlation was calculated. Response to treatment was evaluated on day 56. DCE-US parameters were correlated with clinical response and RECIST1.1 criteria. Results Inter-observer-correlation (r) of DCE-US parameters [time-to-peak (TTP), mean-transit-time (MTT), peak intensity (PI), regional blood volume (RBV), regional blood flow (RBF)] at baseline, day 15, and day 56 was highly significant (r-range 0.73-0.97, all p < 0.001). Out of 17 evaluable patients, 12 patients survived day 56 (clinical responders, cRE), whereas, five patients died before day 56 and were classified as non-responders (cNR). TTP values significantly increased in the cRE group 15 days after initiation of treatment for investigator 1 (p = 0.034) and at day 56 for both investigators (p = 0.028/0.028). MTT had increased significantly in the cRE group on day 56 (p = 0.037/0.022). In the cNR group changes for TTP and MTT remained insignificant. Thus, increase of the DCE-US parameters TTP and MTT are associated with response to treatment and prognosis. Conclusion An increase of TTP and MTT at frequent intervals could serve as a surrogate marker for early response evaluation to anti-angiogenic treatment of metastatic uveal melanoma.
CRIS-Team WoS Importer:2021-06-04

Assessment of tumor development and wound healing using endoscopic techniques in mice - Günther, Claudia; Neurath, Markus; Waldner, Maximilian; Neufert, Clemens; Wirtz, Stefan; Becker, Christoph; et al. (Gastroenterology, 2010)
Mouse models of intestinal inflammation and colon cancer are valuable tools to gain insights into the pathogenesis of the corresponding human diseases. Recently, in vivo mouse endoscopy has been developed, allowing not only the high-resolution monitoring and scoring of experimental disease development, but also enables the investigator to perform manipulations, including local injection of reagents or the taking of biopsies for molecular and histopathologic analyses. Chromoendoscopic staining with methylene blue enables visualization of the crypt structure and allows discrimination between inflammatory and neoplastic changes. The development of endoscopic techniques in live mice opened new options for the investigation of disease mechanisms in the gut and for the preclinical testing of potential therapeutic effects of drug candidates. Finally, mouse endoscopy can help to reduce animal numbers needed to gain significant experimental data.

Association of C-reactive Protein and Partial Mayo Score With Response to Tofacitinib Induction Therapy: Results From the Ulcerative Colitis Clinical Program - Dubinsky, Marla C.; Magro, Fernando; Steinwurz, Flavio; Hudesman, David P.; Kinnucan, Jami A.; Ungaro, Ryan C.; Neurath, Markus; Kulisek, Nicole; Paulissen, Jerome; Su, Chinyu; De Leon, Dario Ponce; Regueiro, Miguel (Inflammatory Bowel Diseases, 2022)
Lay Summary Early decreases in partial Mayo score and C-reactive protein were found to be associated with achieving efficacy outcomes following tofacitinib 10 mg twice daily induction therapy in the ulcerative colitis clinical program.
CRIS-Team WoS Importer:2022-04-29

ATP citrate lyase (ACLY)-dependent immunometabolism in mucosal T cells drives experimental colitis in vivo - Schulz-Kuhnt, Anja; Rühle, Katharina; Javidmehr, Asal; Döbrönti, Michael; Biwank, Jana; Knittel, Selina; Neidlinger, Peter; Leupold, Jannik; Liu, Lijuan; Dedden, Mark; Taudte, Regina Verena; Geßner, Arne; et al. (Gut, 2024)
Objective Mucosal T cells play a major role in inflammatory bowel disease (IBD). However, their immunometabolism during intestinal inflammation is poorly understood. Due to its impact on cellular metabolism and proinflammatory immune cell function, we here focus on the enzyme ATP citrate lyase (ACLY) in mucosal T cell immunometabolism and its relevance for IBD. Design ACLY expression and its immunometabolic impact on colitogenic T cell function were analysed in mucosal T cells from patients with IBD and in two experimental colitis models. Results ACLY was markedly expressed in colon tissue under steady-state conditions but was significantly downregulated in lamina propria mononuclear cells in experimental dextran sodium sulfate-induced colitis and in CD4+ and to a lesser extent in CD8+ T cells infiltrating the inflamed gut in patients with IBD. ACLY-deficient CD4+ T cells showed an impaired capacity to induce intestinal inflammation in a transfer colitis model as compared with wild-type T cells. Assessment of T cell immunometabolism revealed that ACLY deficiency dampened the production of IBD-relevant cytokines and impaired glycolytic ATP production but enriched metabolites involved in the biosynthesis of phospholipids and phosphatidylcholine. Interestingly, the short-chain fatty acid butyrate was identified as a potent suppressor of ACLY expression in T cells, while IL-36α and resolvin E1 induced ACLY levels. In a translational approach, in vivo administration of the butyrate prodrug tributyrin downregulated mucosal infiltration of ACLYhigh CD4+ T cells and ameliorated chronic colitis. Conclusion ACLY controls mucosal T cell immunometabolism and experimental colitis. Therapeutic modulation of ACLY expression in T cells emerges as a novel strategy to promote the resolution of intestinal inflammatio

A true vascular aneurysm of the hepatic artery proper as a rare cause of nonmalignant painless jaundice - Raithel, Martin; Ganzleben, Ingo; Gschossmann, Juergen; Hagel, Alexander; Neurath, Markus; Görtz, Rüdiger (Endoscopy, 2014)
EVALuna2:2006

Autologous regulatory T-cell transfer in refractory ulcerative colitis with concomitant primary sclerosing cholangitis - Voskens, Caroline; Stoica, Diane; Rosenberg, Marita; Vitali, Francesco; Zundler, Sebastian; Ganslmayer, Marion; Knott, Heike; Wiesinger, Manuel; Wunder, Jutta; Kummer, Mirko; Siegmund, Britta; Schnoy, Elisabeth; et al. (Gut, 2022)
Objective Ulcerative colitis (UC) is a chronic, debilitating immune-mediated disease driven by disturbed mucosal homeostasis, with an excess of intestinal effector T cells and an insufficient expansion of mucosal regulatory T cells (Tregs). We here report on the successful adoptive transfer of autologous, ex vivo expanded Tregs in a patient with refractory UC and associated primary sclerosing cholangitis (PSC), for which effective therapy is currently not available.
CRIS-Team WoS Importer:2022-04-29

Automated inflammatory bowel disease detection using wearable bowel sound event spotting - Baronetto, Annalisa; Fischer, Sarah; Neurath, Markus; Amft, Oliver (Frontiers in Digital Health, 2025)
Introduction: Inflammatory bowel disorders may result in abnormal Bowel Sound (BS) characteristics during auscultation. We employ pattern spotting to detect rare bowel BS events in continuous abdominal recordings using a smart T-shirt with embedded miniaturised microphones. Subsequently, we investigate the clinical relevance of BS spotting in a classification task to distinguish patients diagnosed with inflammatory bowel disease (IBD) and healthy controls. Methods: Abdominal recordings were obtained from 24 patients with IBD with varying disease activity and 21 healthy controls across different digestive phases. In total, approximately 281 h of audio data were inspected by expert raters and thereof 136 h were manually annotated for BS events. A deep-learning-based audio pattern spotting algorithm was trained to retrieve BS events. Subsequently, features were extracted around detected BS events and a Gradient Boosting Classifier was trained to classify patients with IBD vs. healthy controls. We further explored classification window size, feature relevance, and the link between BS-based IBD classification performance and IBD activity. Results: Stratified group K-fold cross-validation experiments yielded a mean area under the receiver operating characteristic curve ≥0.83 regardless of whether BS were manually annotated or detected by the BS spotting algorithm. Discussion: Automated BS retrieval and our BS event classification approach have the potential to support diagnosis and treatment of patients with IBD.
CRIS-Team Scopus Importer:2025-04-11
Keywords: bowel sound; digestion monitoring; inflammatory bowel disease; machine learning; ubiquitous computing

Autophagy in cancer therapy—molecular mechanisms and current clinical advances - Ganzleben, Ingo; Neurath, Markus; Becker, Christoph (Cancers, 2021)
Autophagy is a crucial general survival tactic of mammalian cells. It describes the capability of cells to disassemble and partially recycle cellular components (e.g., mitochondria) in case they are damaged and pose a risk to cell survival or simply if their resources are urgently needed elsewhere at the time. Autophagy-associated pathomechanisms have been increasingly recognized as important disease mechanisms in non-malignant (neurodegeneration, diffuse parenchymal lung disease) and malignant conditions alike. However, the overall consequences of autophagy for the organism depend particularly on the greater context in which autophagy occurs, such as the cell type or whether the cell is proliferating. In cancer, autophagy sustains cancer cell survival under challenging, i.e., resource-depleted, conditions. However, this leads to situations in which cancer cells are completely dependent on autophagy. Accordingly, autophagy represents a promising yet complex target in cancer treatment with therapeutically induced increase and decrease of autophagic flux as important therapeutic principles.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Autophagy; Cancer; Glutamine; Hydroxychloroquine; Mitophagy; Reverse Warburg effect

Baseline levels of dynamic CD4+ T cell adhesion to MAdCAM-1 correlate with clinical response to vedolizumab treatment in ulcerative colitis: a cohort study - Allner, Clarissa; Melde, Michaela; Becker, Elisabeth; Fuchs, Friederike; Mühl, Laura; Klenske, Entcho; Müller, Lisa; Morgenstern, Nadine; Fietkau, Konstantin; Hirschmann, Simon; Atreya, Raja; Atreya, Imke; et al. (BMC Gastroenterology, 2020)
BACKGROUND: While the number of therapeutic options for treating inflammatory bowel diseases (IBD) is increasing, evidence for rational treatment decisions is scarce in many cases. In particular, appropriate biomarkers to predict the response to the anti-α4β7 integrin antibody vedolizumab are currently lacking. METHODS: We performed a cohort study with 21 patients suffering from ulcerative colitis (UC), in which first-time treatment with vedolizumab was initiated. CD4+ T cells were isolated from the peripheral blood and dynamic adhesion to recombinant mucosal vascular addressin cell adhesion molecule (MAdCAM-)1 in vitro as well as the effect of vedolizumab on such adhesion in vitro was determined. The expression of α4β1 integrin on peripheral blood CD4+ T cells was quantified by flow cytometry. Electronic patient records were reviewed to determine clinical response to vedolizumab. RESULTS: Dynamic adhesion of peripheral blood CD4+ T cells to MAdCAM-1 and the reduction of adhesion following vedolizumab treatment in vitro were higher and the change in α4β1 expression on CD4+ T cells was different in vedolizumab responders and non-responders. Responders could be identified with high specificity and positive-predictive value. CONCLUSIONS: Determining dynamic adhesion of CD4+ T cells to MAdCAM-1 and the in vitro response to vedolizumab before treatment initiation or dynamic integrin regulation in the early course of treatment seem to be promising tools to predict the clinical response to vedolizumab therapy. Larger prospective studies are warranted.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Adhesion; Gut homing; Inflammatory bowel diseases; T cells; Vedolizumab

BATF-dependent IL-7RhiGM-CSF+ T cells control intestinal graft-versus-host disease - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Büttner-Herold, Maike; Buchele, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (Journal of Clinical Investigation, 2018)
Acute graft-versus-host disease (GVHD) represents a severe, T cell-driven inflammatory complication following allogeneic hematopoietic cell transplantation (allo-HCT). GVHD often affects the intestine and is associated with a poor prognosis. Although frequently detectable, proinflammatory mechanisms exerted by intestinal tissue-infiltrating Th cell subsets remain to be fully elucidated. Here, we show that the Th17-defining transcription factor basic leucine zipper transcription factor ATF-like (BATF) was strongly regulated across human and mouse intestinal GVHD tissues. Studies in complete MHC-mismatched and minor histocompatibility-mismatched (miHA-mismatched) GVHD models revealed that BATF-expressing T cells were functionally indispensable for intestinal GVHD manifestation. Mechanistically, BATF controlled the formation of colon-infiltrating, IL-7 receptor-positive (IL-7R+), granulocyte-macrophage colony-stimulating factor-positive (GM-CSF+), donor T effector memory (Tem) cells. This T cell subset was sufficient to promote intestinal GVHD, while its occurrence was largely dependent on T cell-intrinsic BATF expression, required IL-7-IL-7R interaction, and was enhanced by GM-CSF. Thus, this study identifies BATF-dependent pathogenic GM-CSF+ effector T cells as critical promoters of intestinal inflammation in GVHD and hence putatively provides mechanistic insight into inflammatory processes previously assumed to be selectively Th17 drive
EVALuna2:25783

Batf-dependent Th17 cells critically regulate IL-23 driven colitis-associated colon cancer - Punkenburg, Elise; Vogler, Tina; Büttner, Maike; Amann, Kerstin Ute; Waldner, Maximilian; Atreya, Raja; Abendroth, Benjamin; Mudter, Jonas; Merkel, Susanne; Gallmeier, Eike; Rose-John, Stefan; Neurath, Markus; et al. (Gut, 2016)
IBDs have an increased risk for development of colorectal cancer (CRC). Here, we aimed at the characterisation of the functional role of Th17-associated transcription factors in sporadic and colitis-associated colon cancer in vivo.We used mice deficient or transgenic for the activating protein 1 family member basic leucine zipper transcription factor ATF-like (Batf) to evaluate the role of Th17 cells during sporadic and inflammation-induced colon carcinogenesis. We also studied the expression of Batf and ROR?t in patients with IBD and CRC.Batf but not retinoic acid-related orphan receptor ?t(ROR?t) expression was significantly increased together with interleukin (IL) 23 expression in UC but not in Crohn's disease (CD) tissue samples. In CRC also Batf but not ROR?t expression was increased and its expression correlated with the IL-23 and IL-23 receptor (IL-23R) expression. Finally, Batf but not ROR?t was coexpressed with IL-17a, IL-23R and IL-6 within CRC-infiltrating CD4(+) T cells. Functional studies in mice revealed that Batf-dependent T cells are crucial regulators of sporadic and inflammation-induced CRC. Colitis-associated Batf(-/-) tumours lacked IL-17a(+)IL-23R(+)IL-6(+)CD4(+) T cells, hence displaying characteristics reminiscent of human CRC-infiltrating CD4(+) T cells. Strikingly, Batf(-/-) tumours contained low IL-23 but high IL-17a expression levels. Tumour formation and intratumoral IL-23 expression could be restored by administration of Hyper-IL-6 consisting of IL-6 and soluble IL-6 receptor.Batf-dependent IL-23R(+)IL-6(+)CD4(+) Th17 cells critically control IL-23 driven colitis-associated tumour formation and the progression of sporadic colon tumours. Batf-dependent IL-23R(+) T cells represent a potential future therapeutic target limiting CRC progression.
EVALuna2:2026

Beyond endoscopic assessment in inflammatory bowel disease: real-time histology of disease activity by non-linear multimodal imaging. - Chernavskaia, Olga; Heuke, Sandro; Friedrich, Oliver; Schürmann, Sebastian; Atreya, Raja; Stallmach, Andreas; Neurath, Markus; Waldner, Maximilian; Petersen, Iver; Schmitt, Michael; Bocklitz, Thomas; Popp, Juergen; et al. (Scientific Reports, 2016)
Assessing disease activity is a prerequisite for an adequate treatment of inflammatory bowel diseases (IBD) such as Crohn's disease and ulcerative colitis. In addition to endoscopic mucosal healing, histologic remission poses a promising end-point of IBD therapy. However, evaluating histological remission harbors the risk for complications due to the acquisition of biopsies and results in a delay of diagnosis because of tissue processing procedures. In this regard, non-linear multimodal imaging techniques might serve as an unparalleled technique that allows the real-time evaluation of microscopic IBD activity in the endoscopy unit. In this study, tissue sections were investigated using the non-linear multimodal microscopy combination of coherent anti-Stokes Raman scattering (CARS), two-photon excited auto fluorescence (TPEF) and second-harmonic generation (SHG). After the measurement a gold-standard assessment of histological indexes was carried out based on a conventional H&E stain. Subsequently, various geometry and intensity related features were extracted from the multimodal images. An optimized feature set was utilized to predict histological index levels based on a linear classifier. Based on the automated prediction, the diagnosis time interval is decreased. Therefore, non-linear multimodal imaging may provide a real-time diagnosis of IBD activity suited to assist clinical decision making within the endoscopy unit.

Beyond the border: The use of lenvatinib in advanced hepatocellular carcinoma after different treatment lines: A retrospective analysis - Jefremow, Andre; Wiesmüller, Marco; Rouse, R. A.; Dietrich, Peter; Kremer, Andreas; Waldner, Maximilian; Neurath, Markus; Siebler, Jürgen (Journal of Physiology and Pharmacology, 2020)
The systemic treatment of unresectable hepatocellular carcinoma (HCC) has been improved throughout the past years. Different tyrosine kinase inhibitors (TKI) and checkpoint inhibitors have approval for first-and second-line treatment. Still, data are missing about the choice for the right agent and senseful therapy sequences. Between 2017 and 2019 we treated 149 HCC patients. From those, we identified the patients, who received lenvatinib either as a first-line treatment or in a later treatment line. We investigated seven patients retrospectively, who received lenvatinib in second, third, or fourth treatment line regarding efficacy and safety. Besides that, we compared those patients with 13 patients, who received lenvatinib as a first-line treatment regarding duration of therapy, overall survivial (OS), side effects and best response to treatment. We discovered remission (PR) showed 4/7, stable disease (SD) 2/7 and 1/7 mixed response with an overall tolerable safety profile in patients with a later line lenvatinib treatment. The duration and overall survival for therapy is similar in first-and later treatment lines with comparable results. Most side effects are moderate in each treatment line. Remarkably, on patient diagnoses with HCC (the Barcelona Clinic Liver Cancer C algorithm), who received lenvatinib in fourth line reached 67 months OD since diagnosis. We conclude, that lenvatinib could be considered as a treatment option of HCC for later treatment lines.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Advanced hepatocellular carcinoma; Lenvatinib; Liver cancer; Sequence therapy; Systemic treatment; Treatment lines; Tyrosine kinase inhibitors

Bile salt subspecies activate MRGX4 expressed on sensory neurons and cause itching in humans - Wolf, Katharina; Kühn, Helen; Leibl, Victoria; Gebhardt, Lisa; Glaudo, Markus; Reeh, Peter; Fischer, Michael J. M.; Neurath, Markus; Namer, Barbara; Kremer, Andreas (HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-25

Bioelectrical Impedance Analysis (BIA) Basics and Application - Reljic, Dejan; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (Ernährungsumschau, 2019)
CRIS-Team WoS Importer:2019-10-04

Bioelektrische Impedanzanalyse (BIA): Grundlagen und Anwendung - Reljic, Dejan; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (Ernährungsumschau, 2019)
CRIS-Team Scopus Importer:2021-04-20

Biomarkers for Personalizing IBD Therapy: The Quest Continues - Atreya, Raja; Neurath, Markus (Clinical Gastroenterology and Hepatology, 2024)
Despite recent advances in the understanding of the pathogenesis of inflammatory bowel diseases (IBD) and advent of multiple targeted therapies, approximately one-third of patients are primary non-responders to initiated treatment, and half of patients lose response over time. There is currently a lack of available biomarkers that would prognosticate therapeutic effectiveness of these advanced therapies. This is partly explained by insufficient characterization of the functional roles assumed by the chosen molecular targets during disease treatment. There is a dire need for validated objective biomarkers, which could be indicators of a biological process, that can be applied in clinical practice to assist us in assigning therapies to patients with the highest probability of response. An appropriate molecular and cellular characterization that accounts for the interindividual differences in drug efficacy and potential side effects would help to guide clinicians in the management of patients with IBD and represent a major step to tailor a more personalized approach to treatment. An appropriate combination of complementing biomarkers should ideally incorporate a multimodal analysis in which genetic, microbial, transcriptional, proteomic, metabolic, and immunologic data are combined to enable a truly personalized approach. This would classify patients into disease subgroups according to molecular characteristics, which would enable us to initiate the most appropriate therapeutic substance. Emergence of single-cell technologies to map the intestinal cellular landscape and multiomic approaches have helped to further dissect the pathogenic mechanisms of mucosal inflammation, but the clinical translation of potential biomarkers remains cumbersome, and an ongoing concerted effort by the IBD community is required.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Biomarker; Inflammatory Bowel Diseases; Molecular Resistance

Blockade of αEβ7 integrin suppresses accumulation of CD8+ and Th9 lymphocytes from patients with IBD in the inflamed gut in vivo - Zundler, Sebastian; Schillinger, Daniela; Fischer, Anika; Atreya, Raja; Lopez Posadas, Rocío; Watson, Alastair; Neufert, Clemens; Atreya, Imke; Neurath, Markus (Gut, 2016)
Objective Therapeutically targeting lymphocyte adhesion is of increasing relevance in IBD. Yet, central aspects of the action of antiadhesion compounds are incompletely understood. We investigated the role of αEβ7 and α4β7 integrins and their blockade by vedolizumab and etrolizumab for trafficking of IBD T lymphocytes in an in vivo model of homing to and retention in the inflamed gut. Design We explored integrin expression in patients with IBD by flow cytometry and immunohistochemistry, while regulation of integrins was studied in T cell cultures. The functional relevance of integrins was assessed by adhesion assays and a recently established humanised mouse model in dextran sodium sulfate-treated immunodeficient mice. Results High expression of αEβ7 was noted on CD8+ and CD4+ Th9 cells, while α4β7 was expressed on CD8+, Th2 and Th17 cells. T cell receptor stimulation and transforming growth factor β were key inducers of αEβ7 on human T cells, while butyric acid suppressed αEβ7. In comparison to α4β7 blockade via vedolizumab, blockade of β7 via etrolizumab surrogate antibody superiorly reduced colonic numbers of CD8+ and Th9 cells in vivo after 3 hours, while no difference was noted after 0.5 hours. AEβ7 expression was higher on CD8+ T cells from patients with IBD under vedolizumab therapy. Conclusions AEβ7 is of key relevance for gut trafficking of IBD CD8+ T cells and CD4+ Th9 cells in vivo and mainly retention might account for this effect. These findings indicate that blockade of αEβ7 in addition to α4β7 may be particularly effective in intestinal disorders with expansion of CD8+ and Th9 cells such as IBD.
EVALuna2:2222

Blocking GPR15 Counteracts Integrin-dependent T Cell Gut Homing in Vivo - Schramm, Sebastian; Liu, Lijuan; Saad, Marek; Dietz, Lisa; Dedden, Mark; Müller, Tanja; Atreya, Imke; Bosch-Voskens, Caroline; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (Journal of Crohns & Colitis, 2024)
Background and Aims: The G protein coupled receptor GPR15 is expressed on and functionally important for T cells homing to the large intestine. However, the precise mechanisms by which GPR15 controls gut homing have been unclear. Thus, we aimed to elucidate these mechanisms as well as to explore the potential of targeting GPR15 for interfering with T cell recruitment to the colon in inflammatory bowel disease [IBD]. Methods: We used dynamic adhesion and transmigration assays, as well as a humanised in vivo model of intestinal cell trafficking, to study GPR15-dependent effects on gut homing. Moreover, we analysed GPR15 and integrin expression in patients with and without IBD, cross-sectionally and longitudinally. Results: GPR15 controlled T cell adhesion to MAdCAM-1 and VCAM-1 upstream of α4β7 and α4β1 integrin, respectively. Consistently, high co-expression of these integrins with GPR15 was found on T cells from patients with IBD, and GPR15 also promoted T cell recruitment to the colon in humanised mice. Anti-GPR15 antibodies effectively blocked T cell gut homing in vitro and in vivo. In vitro data, as well as observations in a cohort of patients treated with vedolizumab, suggest that this might be more effective than inhibiting α4β7. Conclusions: GPR15 seems to have a broad, but organ-selective, impact on T cell trafficking and is therefore a promising target for future therapy of IBD. Further studies are needed.
CRIS-Team Scopus Importer:2024-08-16
Keywords: adhesion; GPR15; Inflammatory bowel disease; T cell homing; vedolizumab

Bloody diarrhea caused by enterohemorrhagic Escherichia coli (EHEC) - Neumann, Helmut; Hunstiger, M.; Langner, C.; Neurath, Markus; Vieth, M. (Endoscopy, 2011)
CRIS-Team Scopus Importer:2025-03-05

Bowel wall thickening and hyperemia assessed by high-frequency ultrasound indicate histological inflammation in Crohn's ileitis - Görtz, Rüdiger; Hensel, Stefanie; Wildner, Dane; Neurath, Markus; Strobel, Deike (Abdominal Radiology, 2020)
Purpose We evaluated ileal bowel wall thickness and semiquantitative vascularization by ultrasound in correlation with the presence or absence of histopathological inflammation in patients with Crohn's disease (CD). Methods We conducted a retrospective analysis of 221 ultrasound examinations of the terminal ileum or neoterminal ileum in CD patients with biopsies of the ileum during colonoscopies within 8 weeks of the ultrasound. Ultrasound data were obtained from an inflammatory bowel disease ultrasound register from 2011 to 2017. Bowel wall ultrasound was performed by a high-frequency, linear transducer (7-12 MHz). Presence of bowel wall thickening (> 3 mm), vascularization by the Limberg score, and presence of ileal histopathological inflammation were analyzed. Results In 221 bowel wall ultrasound examinations of CD patients (128 female, 93 male, mean age 37.5 years), a thickened bowel wall was found in 140 (63.3%) and hypervascularization (corresponding to a Limberg score >= 2) in 96 (43.4%) cases. In 187 (84.6%) cases, ileal inflammation was confirmed by histopathology and in 34 (15.4%) cases no inflammation was shown. Bowel wall thickening showed a sensitivity of 70.1%, a negative predictive value (NPV) of 30.9%, a specificity of 73.5% and a positive predictive value (PPV) of 93.6% for the detection of histopathological ileal inflammation. Hypervasularization had a low sensitivity (49.7%) and NPV (24.8%), but high specificity (91.2%) and PPV (96.9%). Conclusion In this CD subcohort of an ultrasound register, pathologic ultrasound findings were quite common. Bowel wall thickening (> 3 mm) and hypervascularization are good predictors of histopathological inflammation within the terminal ileum or neoterminal ileum. Normal ultrasound findings without bowel wall thickening and without hypervascularization do not rule out histopathological inflammation.
CRIS-Team WoS Importer:2021-01-08

Brown bowel syndrome: a rare complication in diseases associated with long-standing malabsorption - Albrecht, Heinz; Hagel, Alexander; De Rossi, Thomas; Rau, Tilman; Kirchner, Thomas; Neurath, Markus; Raithel, Martin (Digestion, 2014)
Longtime chronic malabsorption may among other things cause a lack of liposoluble vitamins. Vitamin E deficiency can lead to formation of lipofuscin aggregates. Its deficiency is also associated with an increased lipofuscinosis of the bowel, i.e. brown bowel syndrome.Systematic research via Medline on brown bowel syndrome, lipofuscinosis, and vitamin E deficiency was performed. We combined our own clinical experience and a review of the literature for this paper. Its goal is to inform about the possible consequences of severe malabsorption and brown bowel syndrome.Systematic data about the occurrence of severe malabsorption and brown bowel syndrome are rare. Only about 27 scientific reports can be found on this subject. Brown bowel syndrome is found mostly in conjunction with vitamin E deficiency and lipofuscinosis of the bowel. The clinical findings are caused by both malabsorption and lipofuscinosis. Case reports show a therapeutic effect of vitamin E.Vitamin deficiency caused by longtime chronic malabsorption can lead to the development of brown bowel syndrome, which is seen as the expression of lipofuscinosis of the bowel, and can cause further clinical disorders. Patients with malabsorption should therefore be monitored regarding their vitamin E levels.
EVALuna2:1837

Budesonide loaded nanoparticles with pH-sensitive coating for improved mucosal targeting in mouse models of inflammatory bowel diseases - Ali, H.; Weigmann, Benno; Neurath, Markus; Collnot, E. M.; Windbergs, M.; Lehr, C. -M. (Journal of Controlled Release, 2014)
The purpose of this study was to investigate the therapeutic potential of budesonide loaded nanocarriers for the treatment of inflammatory bowel disease (IBD). First, budesonide was encapsulated in poly(lactic-co-glycolic) acid (PLGA) nanoparticles by an oil in water (O/W) emulsion technique. A second batch of the same nanoparticles was additionally coated with a pH-sensitive methyl-methacrylate-copolymer. The particle sizes of the plain and the coated PLGA were 200±10.1nm and 240±14.7nm, respectively. As could be shown in vitro, the pH-sensitive coating prevented premature drug release at acidic pH and only releases the drug at neutral to slightly alkaline pH. The efficacy of both coated and plain nanoparticle formulations was assessed in different acute and chronic colitis mouse models, also in comparison to an aqueous solution of the drug. The dose was always the same (0.168mg/kg). It was found that delivery by coated PLGA nanoparticles alleviated the induced colitis significantly better than by plain PLGA particles, which was already more effective than treatment with the same dose of the free drug. These data further corroborate the potential of polymeric nanocarriers for targeted drug delivery to the inflamed intestinal mucosa, and that this concept can still be further improved regarding the oral route of administration by implementing pH-dependent drug release characteristics.
EVALuna2:1906

Can Serum Proteomic Profiling Annunciate Individual Disease Progression in Newly Diagnosed Inflammatory Bowel Disease Patients? - Atreya, Raja; Neurath, Markus (Journal of Crohns & Colitis, 2021)
CRIS-Team Scopus Importer:2021-06-04

Case Report: IBD-like colitis following CAR T cell therapy for diffuse large B cell lymphoma - Zundler, Sebastian; Vitali, Francesco; Kharboutli, Soraya; Völkl, Simon; Polifka, Iris; Mackensen, Andreas; Atreya, Raja; Neurath, Markus; Mougiakakos, Dimitrios (Frontiers in Oncology, 2023)
Chimeric antigen receptor (CAR) T cell therapy has become a new mainstay in the treatment of several hematologic malignancies, but the spectrum of associated complications is still incompletely defined. Here, we report the case of a 70-year-old female patient treated with tisagenlecleucel for diffuse large B cell lymphoma (DLBCL), who developed chronic diarrhea with characteristics of inflammatory bowel disease (IBD)-like colitis. CAR T cells were substantially enriched in the colon lamina propria and other diagnoses were ruled out. Thus, we conclude that IBD-like colitis in this patient was associated to CAR T cell therapy and needs to be considered as a rare potential complication.
CRIS-Team Scopus Importer:2023-06-16
Keywords: CAR T cells; case report; diffuse large B cell lymphoma; inflammatory bowel disease (IBD); tisagenlecleucel

Case report of severe constrictive perimyocarditis and ischemic hepatitis in a Crohn’s disease patient upon infliximab-induced lupus-like syndrome - Hirschmann, Simon; Fischer, Sarah; Klenske, Entcho; Dechant, Katharina; Distler, Jörg; Treutlein, Christoph; Neurath, Markus; Atreya, Raja (Therapeutic Advances in Gastroenterology, 2021)
Anti-tumor necrosis factor (TNF) antibodies have become an indispensable part in the therapeutic landscape of treating inflammatory bowel disease (IBD) patients. Nevertheless, they can be associated with the occurrence of severe systemic side effects. Here, we report the case of a 23-year-old patient with ileocolonic Crohn’s disease in endoscopic remission under ongoing anti-TNF infliximab therapy with occurrence of novel generalized arthralgia, pleuritic chest pain, and dyspnea. Clinical, laboratory, and imaging diagnostic workup in an extended clinical routine setting at the University Hospital of Erlangen, Germany, was used by a multidisciplinary team consisting of gastroenterologists, radiologists, cardiologists, and rheumatologists to investigate the underlying cause of the clinical symptoms in the patient. The results received using the aforementioned diagnostic setup led to the diagnosis of severe constrictive perimyocarditis due to infliximab-induced lupus-like syndrome with distinct ANA reactivity and elevated anti-dsDNA levels. Furthermore, pronounced ischemic hepatitis was diagnosed. Infliximab treatment was immediately stopped, and initiated corticosteroid pulse therapy only led to partial response as it had to be reduced due to pronounced psychiatric side effects. Persistent signs of pericarditis required additional ibuprofen therapy, which led to subsequent resolution of cardial symptoms. Formerly elevated liver enzymes returned to normal, and there were no clinical signs of recurrence of Crohn’s disease activity over 18 months of follow-up. The patient was subsequently switched to ustekinumab therapy for further treatment of underlying Crohn’s disease. This case report describes for the first time severe infliximab-induced lupus-like syndrome in an IBD patient, concurrently mimicking ST-elevation myocardial infarction with MRI visualization of pericarditis, occurrence of ischemic hepatitis, and pronounced signs of systemic inflammation.
CRIS-Team Scopus Importer:2021-10-15
Keywords: anti-TNF antibody; case report; Crohn’s disease; infliximab; lupus-like syndrome

Case report: persistent fever after SARS-CoV-2 infection Fallbericht: Persistierendes Fieber nach SARS-CoV-2-Infektion - Kliem, Thorsten; Strobel, Deike; Heinke, Fabian; Pavel, Marianne Ellen; Neurath, Markus; Neufert, Clemens (Internist, 2022)
A 44-year-old man had persistent fever following a severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection. Because of progressive sinus tachycardia, thyroid hormones were measured which showed hyperthyroidism. Thyroid sonography revealed enlargement of the thyroid gland with hypoechoic areas with blurred margins. We diagnosed subacute granulomatous thyroiditis associated with SARS-CoV‑2 infection and initiated therapy with prednisolone. This therapy resulted in rapid improvement of the patient’s clinical condition and complete remission after three months.
CRIS-Team Scopus Importer:2022-04-01
Keywords: COVID-19; De Quervain’s thyroiditis; Diagnostic ultrasound; Subacute granulomatous thyroiditis; Tachycardia

Caspase-8 controls the gut response to microbial challenges by Tnf-?-dependent and independent pathways - Günther, Claudia; Buchen, Barbara; He, Gui-Wei; Hornef, Mathias; Torow, Natalia; Neumann, Helmut; Wittkopf, Nadine; Martini, Eva; Basic, Marijana; Bleich, Andre; Watson, Alastair J. M.; Neurath, Markus; et al. (Gut, 2015)
Intestinal epithelial cells (IEC) express toll-like receptors (TLR) that facilitate microbial recognition. Stimulation of TLR ligands induces a transient increase in epithelial cell shedding, a mechanism that serves the antibacterial and antiviral host defence of the epithelium and promotes elimination of intracellular pathogens. Although activation of the extrinsic apoptosis pathway has been described during inflammatory shedding, its functional involvement is currently unclear.We investigated the functional involvement of caspase-8 signalling in microbial-induced intestinal cell shedding by injecting Lipopolysaccharide (LPS) to mimic bacterial pathogens and poly(I:C) as a probe for RNA viruses in vivo.TLR stimulation of IEC was associated with a rapid activation of caspase-8 and increased epithelial cell shedding. In mice with an epithelial cell-specific deletion of caspase-8 TLR stimulation caused Rip3-dependent epithelial necroptosis instead of apoptosis. Mortality and tissue damage were more severe in mice in which IECs died by necroptosis than apoptosis. Inhibition of receptor-interacting protein (Rip) kinases rescued the epithelium from TLR-induced gut damage. TLR3-induced necroptosis was directly mediated via TRIF-dependent pathways, independent of Tnf-? and type III interferons, whereas TLR4-induced tissue damage was critically dependent on Tnf-?.Together, our data demonstrate an essential role for caspase-8 in maintaining the gut barrier in response to mucosal pathogens by permitting inflammatory shedding and preventing necroptosis of infected cells. These data suggest that therapeutic strategies targeting the cell death machinery represent a promising new option for the treatment of inflammatory and infective enteropathies.
EVALuna2:1993

Caspase-8 controls the gut response to microbial challenges by Tnf-α-dependent and independent pathways. - Günther, Claudia; Buchen, Barbara; He, Guiwei; Hornef, Mathias W.; Torow, Natalia; Neumann, Helmut; Martini, Eva; Basic, Marijana; Bleich, André; Watson, Alastair J.M.; Neurath, Markus; Becker, Christoph; et al. (Gut, 2015)
Together, our data demonstrate an essential role for caspase-8 in maintaining the gut barrier in response to mucosal pathogens by permitting inflammatory shedding and preventing necroptosis of infected cells. These data suggest that therapeutic strategies targeting the cell death machinery represent a promising new option for the treatment of inflammatory and infective enteropathies. TLR stimulation of IEC was associated with a rapid activation of caspase-8 and increased epithelial cell shedding. In mice with an epithelial cell-specific deletion of caspase-8 TLR stimulation caused Rip3-dependent epithelial necroptosis instead of apoptosis. Mortality and tissue damage were more severe in mice in which IECs died by necroptosis than apoptosis. Inhibition of receptor-interacting protein (Rip) kinases rescued the epithelium from TLR-induced gut damage. TLR3-induced necroptosis was directly mediated via TRIF-dependent pathways, independent of Tnf-α and type III interferons, whereas TLR4-induced tissue damage was critically dependent on Tnf-α. Intestinal epithelial cells (IEC) express toll-like receptors (TLR) that facilitate microbial recognition. Stimulation of TLR ligands induces a transient increase in epithelial cell shedding, a mechanism that serves the antibacterial and antiviral host defence of the epithelium and promotes elimination of intracellular pathogens. Although activation of the extrinsic apoptosis pathway has been described during inflammatory shedding, its functional involvement is currently unclear. We investigated the functional involvement of caspase-8 signalling in microbial-induced intestinal cell shedding by injecting Lipopolysaccharide (LPS) to mimic bacterial pathogens and poly(I:C) as a probe for RNA viruses in vivo. CONCLUSIONS RESULTS OBJECTIVES DESIGN
Keywords: Apoptosis; Cell Biology; Cell Death; Intestinal Epithelium; TNF

Caspase-8 controls the gut response to microbial challenges by Tnf-α-dependent and independent pathways - Günther, Claudia; Buchen, Barbara; Hornef, Mathias; Torow, Natalia; Neumann, Helmut; Martini, Eva; Basic, Marijana; Bleich, Andre; Watson, Alastair; Neurath, Markus; Becker, Christoph; et al. (Gut, 2015)
Together, our data demonstrate an essential role for caspase-8 in maintaining the gut barrier in response to mucosal pathogens by permitting inflammatory shedding and preventing necroptosis of infected cells. These data suggest that therapeutic strategies targeting the cell death machinery represent a promising new option for the treatment of inflammatory and infective enteropathies. TLR stimulation of IEC was associated with a rapid activation of caspase-8 and increased epithelial cell shedding. In mice with an epithelial cell-specific deletion of caspase-8 TLR stimulation caused Rip3-dependent epithelial necroptosis instead of apoptosis. Mortality and tissue damage were more severe in mice in which IECs died by necroptosis than apoptosis. Inhibition of receptor-interacting protein (Rip) kinases rescued the epithelium from TLR-induced gut damage. TLR3-induced necroptosis was directly mediated via TRIF-dependent pathways, independent of Tnf-α and type III interferons, whereas TLR4-induced tissue damage was critically dependent on Tnf-α. Intestinal epithelial cells (IEC) express toll-like receptors (TLR) that facilitate microbial recognition. Stimulation of TLR ligands induces a transient increase in epithelial cell shedding, a mechanism that serves the antibacterial and antiviral host defence of the epithelium and promotes elimination of intracellular pathogens. Although activation of the extrinsic apoptosis pathway has been described during inflammatory shedding, its functional involvement is currently unclear. We investigated the functional involvement of caspase-8 signalling in microbial-induced intestinal cell shedding by injecting Lipopolysaccharide (LPS) to mimic bacterial pathogens and poly(I:C) as a probe for RNA viruses in vivo. CONCLUSIONS RESULTS OBJECTIVES DESIGN
Keywords: Apoptosis; Cell Biology; Cell Death; Intestinal Epithelium; TNF

Caspase-8 regulates TNF-α-induced epithelial necroptosis and terminal ileitis - Günther, Claudia; Martini, Eva; Amann, Kerstin Ute; Weigmann, Benno; Neumann, Helmut; Waldner, Maximilian; Tenzer, Stefan; Neurath, Markus; Becker, Christoph; et al. (Nature, 2011)
Dysfunction of the intestinal epithelium is believed to result in the excessive translocation of commensal bacteria into the bowel wall that drives chronic mucosal inflammation in Crohn's disease, an incurable inflammatory bowel disease in humans characterized by inflammation of the terminal ileum. In healthy individuals, the intestinal epithelium maintains a physical barrier, established by the tight contact of cells. Moreover, specialized epithelial cells such as Paneth cells and goblet cells provide innate immune defence functions by secreting mucus and antimicrobial peptides, which hamper access and survival of bacteria adjacent to the epithelium. Epithelial cell death is a hallmark of intestinal inflammation and has been discussed as a possible pathogenic mechanism driving Crohn's disease in humans. However, the regulation of epithelial cell death and its role in intestinal homeostasis remain poorly understood. Here we demonstrate a critical role for caspase-8 in regulating necroptosis of intestinal epithelial cells (IECs) and terminal ileitis. Mice with a conditional deletion of caspase-8 in the intestinal epithelium (Casp8(ΔIEC)) spontaneously developed inflammatory lesions in the terminal ileum and were highly susceptible to colitis. Casp8(ΔIEC) mice lacked Paneth cells and showed reduced numbers of goblet cells, indicating dysregulated antimicrobial immune cell functions of the intestinal epithelium. Casp8(ΔIEC) mice showed increased cell death in the Paneth cell area of small intestinal crypts. Epithelial cell death was induced by tumour necrosis factor (TNF)-α, was associated with increased expression of receptor-interacting protein 3 (Rip3; also known as Ripk3) and could be inhibited on blockade of necroptosis. Lastly, we identified high levels of RIP3 in human Paneth cells and increased necroptosis in the terminal ileum of patients with Crohn's disease, suggesting a potential role of necroptosis in the pathogenesis of this disease. Together, our data demonstrate a critical function of caspase-8 in regulating intestinal homeostasis and in protecting IECs from TNF-α-induced necroptotic cell death.

CCR8 Signaling via CCL1 Regulates Responses of Intestinal IFN-γ Producing Innate Lymphoid CelIs and Protects From Experimental Colitis - Kang, Le; Schmalzl, Angelika; Leupold, Tamara; Gonzalez-Acera, Miguel; Atreya, Raja; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Frontiers in Immunology, 2021)
A diverse spectrum of immune cells populates the intestinal mucosa reflecting the continuous stimulation by luminal antigens. In lesions of patients with inflammatory bowel disease, an aberrant inflammatory process is characterized by a very prominent infiltrate of activated immune cells producing cytokines and chemokines. These mediators perpetuate intestinal inflammation or may contribute to mucosal protection depending on the cellular context. In order to further characterize this complex immune cell network in intestinal inflammation, we investigated the contribution of the chemokine receptor CCR8 to development of colitis using a mouse model of experimental inflammation. We found that CCR8−/− mice compared to wildtype controls developed strong weight loss accompanied by increased histological and endoscopic signs of mucosal damage. Further experiments revealed that this gut protective function of CCR8 seems to be selectively mediated by the chemotactic ligand CCL1, which was particularly produced by intestinal macrophages during colitis. Moreover, we newly identified CCR8 expression on a subgroup of intestinal innate lymphoid cells producing IFN-γ and linked a functional CCL1/CCR8 axis with their abundance in the gut. Our data therefore suggest that this pathway supports tissue-specific ILC functions important for intestinal homeostasis. Modulation of this regulatory circuit may represent a new strategy to treat inflammatory bowel disease in humans.
CRIS-Team Scopus Importer:2021-03-05
Keywords: CCR8; chemokines; cytokines; inflammatory bowel disease; innate immunity; innate lymphoid cell

Cellular FLICE-like inhibitory protein secures intestinal epithelial cell survival and immune homeostasis by regulating caspase-8. - Günther, Claudia; Martini, Eva; He, Guiwei; Amann, Kerstin Ute; He, You-Wen; Neurath, Markus; Becker, Christoph; et al. (Gastroenterology, 2013)
The intestinal epithelium generates a barrier that protects mammals from potentially harmful intestinal contents, such as pathogenic bacteria. Dysregulation of epithelial cell death has been implicated in barrier dysfunction and in the pathogenesis of intestinal inflammation. We investigated mechanisms of cell-death regulation in the intestinal epithelium of mice. Conditional knockout mice (either inducible or permanent) with deletion of cellular FLICE-inhibitory protein (cFlip) or caspase-8 in the intestinal epithelium were analyzed by histology and high-resolution endoscopy. We assessed the effects of cFlip or caspase-8 deficiency on intestinal homeostasis. Expression of cFlip in the intestinal epithelium was required for constitutive activation of caspase-8 under steady-state conditions. Intestinal expression of cFlip was required for development; disruption of the gene encoding cFlip from the intestinal epithelium (cFlip(fl/fl) VillinCre(+) mice) resulted in embryonic lethality. When cFlip was deleted from the intestinal epithelium of adult mice (cFlip(iΔIEC) mice), the animals died within a few days from severe tissue destruction, epithelial cell death, and intestinal inflammation. Death of cFlip-depleted intestinal epithelial cells was regulated extrinsically and required the presence of death receptor ligands, such as tumor necrosis factor-α and CD95 ligand, but was independent of receptor-interacting protein 3. cFlip deficiency was associated with strong up-regulation of caspase-8 and caspase-3 activity and excessive apoptosis in intestinal crypts. cFlip is required for intestinal tissue homeostasis in mice. It controls the level of activation of caspase-8 to promote survival of intestinal epithelial cells. BACKGROUND & AIMS METHODS RESULTS CONCLUSIONS
Keywords: CASP8; CFLAR; Fadd; Fadd-Like Apoptosis Regulator; Fas-associated protein with death domain; IEC; NEMO; NF-κB essential modulator; Rip; TNF; TUNEL; cFLIP; cellular FLICE-like inhibitory protein; intestinal epithelial cell; receptor interacting protein; terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate nick-end labeling; tumor necrosis factor

Cellular immunotherapies and immune cell depleting therapies in inflammatory bowel diseases: the next magic bullet? - Neurath, Markus; Sands, Bruce Eric; Rieder, Florian (Gut, 2024)
Despite significant advances in biologic and small molecule treatments and the emergence of combination therapies to treat inflammatory bowel diseases (IBD) a large unmet need remains to control intestinal inflammation. New approaches targeting several pathways simultaneously with a favorable safety profile and agents that trigger anti-inflammatory pathways to drive durable resolution of inflammation are needed. This article discusses novel cellular immunotherapies and immune cell depleting therapies in IBD, including CAR-T cell approaches, Tr1 and T regulatory (Treg) cells and cell depleting antibodies such as rosnilimab. These novel approaches have the potential to overcome current therapeutic limitations in the treatment of IBD.
CRIS-Team Scopus Importer:2024-08-02
Keywords: CELLULAR IMMUNOLOGY; IBD CLINICAL

Cellular Mechanisms of Etrolizumab Treatment in Inflammatory Bowel Disease - Lichnog, Charlotte; Klabunde, Sha; Becker, Emily; Fuh, Franklin; Tripal, Philipp; Atreya, Raja; Klenske, Entcho; Erickson, Rich; Chiu, Henry; Reed, Chae; Chung, Shan; Neufert, Clemens; et al. (Frontiers in Pharmacology, 2019)
Background: Anti-integrin therapy is a new frontline strategy in the treatment of inflammatory bowel diseases (IBD). The anti-beta 7 integrin antibody etrolizumab is currently being investigated for safety and efficacy in Crohn's disease (CD) and ulcerative colitis (UC) in several phase III trials. Mechanistically, etrolizumab is known to block beta 7 integrin ligand binding and reduces intestinal trafficking of beta 7-expressing cells. Etrolizumab blocks beta 7 integrin ligand binding and reduces beta 7-positive lymphocyte migration and retention in the inflamed gut mucosa, but the exact mechanisms by which this inhibition occurs are not fully understood.
CRIS-Team WoS Importer:2019-02-21

CELLULAR SENESCENCE OF CD4+T CELLS IN THE ADAPTIVE IMMUNE RESPONSE AGAINST COLORECTAL CANCER - Thoma, Oana-Maria; Neurath, Markus; Waldner, Maximilian (2019)
EVALuna2:209000

CEUS in hepatocellular carcinoma and intrahepatic cholangiocellular carcinoma in 320 patients - early or late washout matters: a subanalysis of the DEGUM multicenter trial - Wildner, Dane; Bernatik, T.; Greis, C.; Seitz, K.; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2015)
The aim of the study was the comparison of tumor vascularization and contrast enhancement in contrast-enhanced ultrasound (CEUS) for the characterization of hepatocellular carcinoma (HCC) and intrahepatic cholangiocellular carcinoma (ICC). We present data of the subpopulations HCC and ICC examined in the DEGUM multicenter trial for the characterization of focal liver lesions in clinical practice.Based on the data of the DEGUM multicenter trial (1349 patients), all patients with histologically proven HCC (n = 278) and ICC (n = 42) were analyzed. The vascularity pattern and contrast enhancement pattern during the arterial, portal-venous and late phase were compared.An underlying liver cirrhosis was found in 214/278 patients with HCC (76.9 %) and 7/42 patients with ICC (16.7 %). In CEUS, HCC showed a global arterial hyperenhancement compared to ICC (HCC: tumor center: 60.3 %; tumor periphery: 75 %; ICC: tumor center: 16.7 %; tumor periphery: 40.5 %). ICC showed an initial contrast enhancement primarily at the tumor periphery (ICC: 85.7 % vs. HCC: 61 %) followed by an early portal-venous contrast washout in the tumor center (ICC: 85.8 % vs. HCC: 49.8 %) and tumor periphery (ICC: 66.7 % vs. HCC: 32.6 %). HCC showed a delayed contrast washout (late phase hypoenhancement: HCC: 75 % vs. ICC: 92.9 %).ICCs are rare in cirrhotic livers. CEUS can demonstrate differences in the vascularization patterns between HCC and ICC. HCC showed an arterial global hyperenhancement and delayed contrast washout in the late phase. ICCs are characterized by an arterial contrast enhancement at the tumor periphery with early contrast washout of the vascularized parts of the lesions in the portal-venous and late phase.
EVALuna2:1988

Challenges for the crosstalk between endoscopists and pathologists - Neurath, Markus; Vieth, Michael (Endoscopy, 2019)
CRIS-Team WoS Importer:2019-03-15

Characterization and Expansion of Autologous GMP-ready Regulatory T Cells for TREG-based Cell Therapy in Patients with Ulcerative Colitis - Voskens, Caroline J.; Fischer, Anika; Roessner, Susanne; Lorenz, Carmen; Hirschmann, Simon; Atreya, Raja; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Schuler, Gerold (Inflammatory Bowel Diseases, 2017)
BACKGROUND: A local imbalance between regulatory (Treg) and effector T cells is believed to play a major role in gut-specific inflammation, including ulcerative colitis (UC). Restoration of this balance through an adoptive Treg transfer is an attractive new treatment approach in patients who are refractory to current standard therapies. It was our goal to develop a Good Manufacturing Practices (GMP)-conform protocol for expansion of UC Treg cells as a rational backbone for future studies on Treg therapy in UC. METHODS: CD25 blood T cells derived from patients with UC were ex vivo expanded in the presence of IL-2, rapamycin, and anti-CD3/anti-CD28 expander beads using a GMP-conform protocol. Cells were subsequently assessed for stability and function. RESULTS: Patient-derived ex vivo rapamycin-expanded GMP-ready CD25 cells were polyclonal, hypomethylated at intron 1 of the FoxP3 locus, and suppressive in carboxyfluorescein succinimidyl ester-dilution assays against autologous peripheral blood-derived and allogeneic colon-derived responder cells. Function was mediated by soluble factors, including toxic granules. In addition to CD4 T cells, suppressive hypermethylated CD8 T-cell subsets were also induced during the expansion process. CONCLUSIONS: Patient-derived rapamycin-expanded CD25 cells are stable and functional, and as such, ready to serve in a phase I dose-escalation safety study in UC.
EVALuna2:33805

Chemically induced mouse models of acute and chronic intestinal inflammation - Wirtz, Stefan; Popp, Vanessa; Kindermann, Markus; Gerlach, Katharina; Weigmann, Benno; Fichtner-Feigl, Stefan; Neurath, Markus (Nature Protocols, 2017)
Inflammatory bowel diseases (IBDs) result in diarrhea and abdominal pain with further potential complications such as tissue fibrosis and stenosis. Animal models help in understanding the immunopathogenesis of IBDs and in the design of novel therapeutic concepts. Here we present an updated version of a protocol we published in 2007 for key models of acute and chronic forms of colitis induced by 2,4,6-trinitro-benzene sulfonic acid (TNBS), oxazolone and dextran sulfate sodium (DSS). This protocol update describes an adaptation of the existing protocol that modifies the technique. This protocol has been used to generate improved mouse models that better reflect the nature of IBDs in humans. In TNBS and oxazolone colitis models, topical administration of hapten reagents results in T-cell-mediated immunity against haptenized proteins and luminal antigens. By contrast, to generate DSS colitis models, mice orally receive DSS, causing death of epithelial cells, compromising barrier function and causing subsequent inflammation. The analysis of the acute colitis models can be performed within 1-2 weeks, whereas that of the chronic models may take 2-4 months. The strengths of the acute models are that they are based on the analysis of short-lasting barrier alterations, innate immune effects and flares. The advantages of the chronic models are that they may offer better insight into adaptive immunity and complications such as neoplasia and tissue fibrosis. The protocol requires basic skills in laboratory animal research.
EVALuna2:33810

Chronic intestinal inflammation in mice expressing viral Flip in epithelial cells - Ruder, Barbara; Murtadak, Vinay; Stürzl, Michael; Wirtz, Stefan; Distler, Ute; Tenzer, Stefan; Mahapatro, Mousumi; Greten, Florian R.; Hu, Yinling; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; et al. (Mucosal Immunology, 2018)
Viruses are present in the intestinal microflora and are currently discussed as a potential causative mechanism for the development of inflammatory bowel disease. A number of viruses, such as Human Herpesvirus-8, express homologs to cellular FLIPs, which are major contributors for the regulation of epithelial cell death. In this study we analyzed the consequences of constitutive expression of HHV8-viral FLIP in intestinal epithelial cells (IECs) in mice. Surprisingly, expression of vFlip disrupts tissue homeostasis and induces severe intestinal inflammation. Moreover vFlipIEC-tg mice showed reduced Paneth cell numbers, associated with excessive necrotic cell death. On a molecular level vFlip expression altered classical and alternative NFκB activation. Blocking of alternative NFκB signaling by deletion of Ikka in vivo largely protected mice from inflammation and Paneth cell loss induced by vFLIP. Collectively, our data provide functional evidence that expression of a single viral protein in IECs can be sufficient to disrupt epithelial homeostasis and to initiate chronic intestinal inflammation.
EVALuna2:35131

Chronic pruritus represents a major burden in non-cholestatic hepatobiliary disorders - Düll, Miriam; Karlen, Vanessa; Vetter, Marcel; Dietrich, Peter; Kupfer, Joerg; Neurath, Markus; Kremer, Andreas (JOURNAL OF HEPATOLOGY, 2022)
CRIS-Team WoS Importer:2022-08-12

Circadian profiling reveals higher histamine plasma levels and lower diamine oxidase serum activities in 24% of patients with suspected histamine intolerance compared to food allergy and controls - Pinzer, T. C.; Tietz, E.; Waldmann, Elisabeth; Schink, Monic; Neurath, Markus; Zopf, Yurdagül (Allergy, 2018)
BACKGROUND: Histamine intolerance is thought to trigger manifold clinical symptoms after ingesting histamine-rich food due to reduced activity of diamine oxidase (DAO). No study has hitherto systematically assessed daily fluctuations of histamine levels and DAO activities in symptomatic patients. The aim of the study was to investigate the presence of histamine intolerance, to therefore establish day profiles of histamine levels and DAO activities, and to compare the results between patients with suspected histamine intolerance, food allergy and healthy controls. METHODS: We determined day profiles of histamine plasma levels and DAO serum activities in 33 patients with suspected histamine intolerance, in 21 patients with proven food allergy and in 10 healthy control patients. Clinical symptoms, food intolerances and further clinical and laboratory chemical parameters were evaluated. RESULTS: Twenty-four percent (8 of 33) suspected histamine-intolerant patients showed elevated histamine levels during the day. That might be caused by constantly and significantly reduced DAO activities in these patients compared to food-allergic and control patients. The remaining 25 patients presented normal histamine levels and DAO activities, but an increased prevalence of multiple food intolerances compared to the other subgroup of suspected histamine-intolerants. There was no correlation between subjective complaints and serological histamine parameters in patients with suspected histamine intolerance. CONCLUSIONS: We determined by daily profiling that decreased DAO activities correlated with elevated histamine levels in a subgroup of suspected histamine-intolerants. This finding discriminates these patients from food intolerant individuals with similar clinical symptoms and strongly suggests the presence of histamine intolerance.
EVALuna2:34072

Circulating Adaptive Immune Cells Expressing the Gut Homing Marker α4β7 Integrin Are Decreased in COVID-19 - Müller, Tanja; Becker, Elisabeth; Wiendl, Maximilian; Schulze, Lisa; Voskens, Caroline; Kremer, Andreas; Neurath, Markus; Zundler, Sebastian; Völkl, Simon (Frontiers in Immunology, 2021)
Background: Infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a wide range of symptoms including gastrointestinal manifestations, and intestinal epithelial cells are a target of the virus. However, it is unknown how the intestinal immune system contributes to systemic immune responses in coronavirus disease 2019 (COVID-19). Methods: We characterized peripheral blood lymphocytes from patients with active COVID-19 and convalescent patients as well as healthy controls by flow cytometry. Results: The frequency and absolute number of circulating memory T and B cells expressing the gut homing integrin α4β7 integrin was reduced during COVID-19, whether gastrointestinal symptoms were present or not. While total IgA-expressing B cells were increased, gut-imprinted B cells with IgA expression were stable. Conclusion: COVID-19 is associated with a decrease in circulating adaptive immune cells expressing the key gut homing marker α4β7 suggesting that these cells are preferentially recruited to extra-intestinal tissues independently of α4β7 or that the systemic immune response against SARS-CoV-2 is at least numerically dominated by extraintestinal, particularly pulmonary, immune cell priming.
CRIS-Team Scopus Importer:2021-05-21
Keywords: COVID-19; gut homing; integrins; SARS-CoV-2 infection; T cell trafficking

Citrullination licenses calpain to decondense nuclei in neutrophil extracellular trap formation - Goesswein, Stefanie; Lindemann, Aylin; Mahajan, Aparna; Maueröder, Christian; Martini, Eva; Patankar, Jay; Schett, Georg; Becker, Christoph; Wirtz, Stefan; Naumann-Bartsch, Nora; Bianchi, Marco E.; Greer, Peter A.; et al. (Frontiers in Immunology, 2019)
Neutrophils respond to various stimuli by decondensing and releasing nuclear chromatin characterized by citrullinated histones as neutrophil extracellular traps (NETs). This achieves pathogen immobilization or initiation of thrombosis, yet the molecular mechanisms of NET formation remain elusive. Peptidyl arginine deiminase-4 (PAD4) achieves protein citrullination and has been intricately linked to NET formation. Here we show that citrullination represents a major regulator of proteolysis in the course of NET formation. Elevated cytosolic calcium levels trigger both peptidylarginine deiminase-4 (PAD4) and calpain activity in neutrophils resulting in nuclear decondensation typical of NETs. Interestingly, PAD4 relies on proteolysis by calpain to achieve efficient nuclear lamina breakdown and chromatin decondensation. Pharmacological or genetic inhibition of PAD4 and calpain strongly inhibit chromatin decondensation of human and murine neutrophils in response to calcium ionophores as well as the proteolysis of nuclear proteins like lamin B1 and high mobility group box protein 1 (HMGB1). Taken together, the concerted action of PAD4 and calpain induces nuclear decondensation in the course of calcium-mediated NET formation.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Calpain; Cell death; Chromatin; Citrullination; Neutrophil; Nucleus; PAD4

Clinical Characteristics of Influenza in Season 2017/2018 in a German Emergency Department: A Retrospective Analysis - Mohammad, Sonia; Korn, Klaus; Schellhaas, Barbara; Neurath, Markus; Görtz, Rüdiger (Microbiology Insights, 2019)
Introduction: Influenza infection is a viral disease with significant morbidity and mortality during the cold months. Clinical presentation typically includes cough, fever, and pain. Influenza disease is hardly diagnosed only on the basis of clinical symptoms due to similar clinical presentation of other diseases such as a typical cold or other flu-like diseases. We evaluated patients with proven influenza who presented at an emergency department of internal medicine in a university hospital according to the clinical presentation and different age groups. Materials and Methods: From October 2017 to April 2018, 723 reverse transcription-polymerase chain reaction (RT-PCR) tests for influenza were performed in the emergency department on patients with suspected influenza diagnosed clinically. A total of 240 influenza-positive patients were retrospectively assessed for documented main symptoms, vital parameters, risk factors for an unfavorable course, hospitalization, and death. Results: The mean age of influenza patients was 65 years. Overall, 30 patients were aged 18 to 39 years, 48 patients 40 to 59 years, and 162 patients ⩾60 years. Influenza B in 168 (70%) was predominant to 72 influenza A (mostly H1N1). In only 30% of the patients all three typical symptoms (cough, fever, and headache/myalgia) were documented. Headache or myalgia (with 34%) was rather uncommon in influenza B. Sudden onset was cited in only 5.4%; 57% of all influenza patients were in hospital for a mean of 7.1 days, and 5.8% of all influenza patients died. Patients aged above 60 years had more risk factors, showed typical symptoms less frequently, and were hospitalized longer than younger patients (<60 and <40 years). Conclusions: At an emergency department of internal medicine, influenza-diseased patients are of higher age, show an increased number of comorbidities, and are more likely to have milder symptoms documented. Elderly patients with influenza have a higher hospitalization rate with a longer hospital stay as compared with younger patients.
EVALuna2:212379

Clinical Effects of a Topically Applied Toll-like Receptor 9 Agonist in Active Moderate-to-Severe Ulcerative Colitis - Atreya, Raja; Bloom, Stuart; Scaldaferri, Franco; Gerardi, Viviana; Admyre, Charlotte; Karlsson, Asa; Knittel, Thomas; Kowalski, Jan; Lukas, Milan; Lofberg, Robert; Nancey, Stephane; Petryka, Robert; et al. (Journal of Crohns & Colitis, 2016)
Toll-like receptors [TLRs] are potential drug targets for immunomodulation. We determined the safety and efficacy of the TLR-9 agonist DNA-based immunomodulatory sequence 0150 [DIMS0150] in ulcerative colitis [UC] patients refractory to standard therapy.In this randomized, double-blind, placebo-controlled trial, 131 patients with moderate-to-severe active UC were randomized to receive two single doses of the oligonucleotide DIMS0150 [30 mg] or placebo administered topically during lower GI endoscopy at baseline and Week 4. The primary endpoint was clinical remission, defined as Clinical Activity Index [CAI] <=4, at Week 12. Secondary endpoints included mucosal healing and symptomatic remission of key patient-reported outcomes [absence of blood in stool and weekly stool frequency <35].There was no statistical significant difference between the groups in the induction of clinical remission at Week 12, with 44.4% in the DIMS0150 group vs. 46.5% in the placebo group. However, the proportion of patients who achieved symptomatic remission was 32.1% in the DIMS0150 group vs. 14.0% in the placebo group at Week 4 [p = 0.020], and 44.4% vs. 27.9% at Week 8 [p = 0.061]. More patients on DIMS0150 compared with those on placebo had mucosal healing [34.6% vs. 18.6%; p = 0.09] and histological improvement regarding the Geboes score [30.9% vs. 9.3%; p = 0.0073] at Week 4. Significantly more patients on DIMS0150 were in clinical remission with mucosal healing at Week 4: 21% vs. 4.7% in the placebo group [p = 0.02]. DIMS0150 was well tolerated, and no safety signals compared with placebo were evident.Therapy with the topically applied TLR-9 agonist DIMS0150 is a promising and well-tolerated novel therapeutic option for treatment-refractory, chronic active UC patients, warranting further clinical trials.
EVALuna2:2191

Clinical efficacy of the Toll-like receptor 9 agonist cobitolimod using patient-reported-outcomes defined clinical endpoints in patients with ulcerative colitis - Atreya, Raja; Reinisch, Walter; Peyrin-Biroulet, Laurent; Scaldaferri, Franco; Admyre, Charlotte; Knittel, Thomas; Kowalski, Jan; Neurath, Markus; Hawkey, Christopher (Digestive and Liver Disease, 2018)
BACKGROUND: The Toll-like-receptor 9 (TLR-9) agonist cobitolimod (DIMS0150, Kappaproct®) is a promising therapeutic option for ulcerative colitis (UC) patients. AIMS: The objectives of this post-hoc analysis using the COLLECT study data was to investigate the clinical effects of cobitolimod using patient-reported-outcomes (PRO) defined endpoints. METHODS: Dual topical administration of cobitolimod was studied in a randomised, multicentre clinical trial named COLLECT in moderate-to-severe UC patients. Symptomatic remission (SR) was studied in 104 patients based on their e-diary records and was defined as absence of blood in stool and a mean daily stool frequency (SF) < 4. RESULTS: SR was achieved at week 4 in 17.1% of cobitolimod vs. 5.9% of placebo treated patients (p = 0.13), at week 8 in 35.7% vs. 17.6% (p = 0.07), and at week 12 in 38.6% vs. 17.6% (p = 0.04) of the patients, respectively. SR rates with cobitolimod and placebo in anti-TNFα experienced patients were smaller but with a broadly similar relative effect-size to anti-TNFα naïve patients. Clinical efficacy was higher in patients with moderate compared to severe disease. CONCLUSIONS: Application of the Toll-like-receptor 9 (TLR-9) agonist cobitolimod is able to induce remission as assessed by PRO measures in UC patients with moderate-to-severe activity as well as in anti-TNFα experienced and naïve patients supporting the overall efficacy of the substance.
EVALuna2:35138

Clinical experiences and predictors of success of treatment with vedolizumab in IBD patients: a cohort study - Mühl, Laura; Becker, Elisabeth; Müller, Tanja; Atreya, Raja; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (BMC Gastroenterology, 2021)
Background: Vedolizumab has become a standard treatment for the inflammatory bowel diseases ulcerative colitis (UC) and Crohn’s disease (CD). However, there is an ongoing debate on the ideal individual treatment algorithms and means to predict treatment response are not routinely established. Aims: We aimed to describe our experiences with vedolizumab at a large German tertiary referral center and to identify clinical predictors of success of vedolizumab treatment. Methods: We performed a retrospective single-center cohort study employing univariable and multivariable analyses as well as Kaplan–Meier analyses of persistence on treatment. Results: 36% and 35% of the patients with UC and CD, respectively, reached clinical remission after 17 weeks. Patients with lower clinical disease activity were more likely to achieve remission. The median persistence on treatment was 33 months for UC and 29 months for CD. Conclusion: Our study confirms that vedolizumab is an efficient option for the treatment of UC and CD. Clinical parameters of disease activity may help to predict the success of treatment.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Inflammatory bowel diseases; Real-world data; Vedolizumab

Clinical outcomes and immunogenicity analysis over 6 months following a switch from originator infliximab (Remicade (R)) to the biosimilar SB2 (Flixabi (R)) in inflammatory bowel disease patients - Fischer, Sven Moritz; Klenske, E.; Schmitt, H.; Vitali, Francesco; Hirschmann, S.; Koch, F.; Ramming, A.; Zundler, Sebastian; Nagore, D.; Uter, Wolfgang; Neurath, Markus; Atreya, Raja (2018)
EVALuna2:34075

Clinical Pharmacist Counselling Improves Long-term Medication Safety and Patient-reported Outcomes in Anti-TNF-treated Patients With Inflammatory Bowel Diseases: The Prospective, Randomized AdPhaNCED Trial. - Plechschmidt, Johannes; Fietkau, Konstantin; Hepp, Tobias; Dietrich, Peter; Fischer, Sarah; Krebs, Sabine; Neurath, Markus; Dörje, Frank; Atreya, Raja (Inflammatory Bowel Diseases, 2025)
BACKGROUND: Antitumor necrosis factor (anti-TNF) antibody treatment has led to marked improvements in the management of patients with inflammatory bowel diseases (IBDs). Nevertheless, anti-TNF therapy is associated with potential adverse drug reactions (ADRs). Our prospective, randomized trial investigated the effect of intensified clinical pharmacist counselling in a multidisciplinary team on medication safety in anti-TNF-treated IBD patients. METHODS: Patients with IBD with ongoing anti-TNF treatment were enrolled in our tertiary center AdPhaNCED trial and randomized to either receive conventional standard of care (control group) or additional clinical pharmacist counselling (intervention group) over 12 months. The primary end point consisted of the number and severity of ADRs associated with anti-TNF therapy. Secondary end points included patient satisfaction with medication information and medication safety. RESULTS: One hundred twenty-seven IBD patients were included in this study. Anti-TNF-related ADRs were significantly lower in the intervention compared with the control group (0.20 vs 0.32 [mean] ADR/patient/month, P = .006) after 12 months. The risk of more severe ADRs (Common Terminology Criteria for Adverse Events [CTCAE] grade ≥2) was significantly higher in the control compared with the intervention group (hazard ratio, 0.34; P = .001). The probability of ADR resolution (hazard ratio, 2.02; P < .001) and patient satisfaction with medication information (14.82 vs 11.60; P < .001) were significantly higher in the intervention group compared with the control group. CONCLUSIONS: Our study results demonstrate that intensified pharmacist counselling significantly reduces the occurrence and severity of therapy-related ADRs and improves patient satisfaction. Clinical pharmacists should therefore be part of a holistic approach to IBD care delivered by a multidisciplinary team.
EVALuna2:566019
Keywords: inflammatory bowel diseases; patient reported outcomes; adverse drug reaction management; medication safety; patient support program

Clinical Response to Vedolizumab in Ulcerative Colitis Patients Is Associated with Changes in Integrin Expression Profiles - Fuchs, Florian; Schillinger, Daniela; Atreya, Raja; Hirschmann, Simon; Fischer, Sören; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2017)
BACKGROUND: Despite large clinical success, deeper insights into the immunological effects of vedolizumab therapy for inflammatory bowel diseases are scarce. In particular, the reasons for differential clinical response in individual patients, the precise impact on the equilibrium of integrin-expressing T cell subsets, and possible associations between these issues are not clear. METHODS: Blood samples from patients receiving clinical vedolizumab therapy were sequentially collected and analyzed for expression of integrins and chemokine receptors on T cells. Moreover, clinical and laboratory data from the patients were collected, and changes between homing marker expression and clinical parameters were analyzed for possible correlations. RESULTS: While no significant correlation of changes in integrin expression and changes in outcome parameters were identified in Crohn's disease (CD), increasing α4β7 levels in ulcerative colitis (UC) seemed to be associated with favorable clinical development, whereas increasing α4β1 and αEβ7 correlated with negative changes in outcome parameters. Changes in α4β1 integrin expression after 6 weeks were significantly different in responders and non-responders to vedolizumab therapy as assessed after 16 weeks with a cutoff of +4.2% yielding 100% sensitivity and 100% specificity in receiver-operator-characteristic analysis. DISCUSSION: Our data show that clinical response to vedolizumab therapy in UC but not in CD is associated with specific changes in integrin expression profiles opening novel avenues for mechanistic research and possibly prediction of response to therapy.
EVALuna2:33807

Cobitolimod for moderate-to-severe, left-sided ulcerative colitis (CONDUCT): a phase 2b randomised, double-blind, placebo-controlled, dose-ranging induction trial - Atreya, Raja; Peyrin-Biroulet, Laurent; Klymenko, Andrii; Augustyn, Monica; Bakulin, Igor; Slankamenac, Dusan; Miheller, Pal; Gasbarrini, Antonio; Hébuterne, Xavier; Arnesson, Karin; Knittel, Thomas; Kowalski, Jan; et al. (Lancet Gastroenterology and Hepatology, 2020)
Background: Cobitolimod is a topically administered, DNA-based oligonucleotide that activates Toll-like receptor 9 (TLR9), and previous research has shown clinical efficacy in patients with moderate-to-severe ulcerative colitis. Here we assessed the efficacy and safety of different dose regimens of cobitolimod for induction therapy in patients with moderate-to-severe, left-sided ulcerative colitis. Methods: CONDUCT was a randomised, double-blind, five-arm, placebo-controlled, dose-ranging phase 2b study that recruited patients with moderate-to-severe, left-sided ulcerative colitis, with inadequate response to conventional or biological therapies, from 91 hospitals or outpatient clinics in 12 European countries. Eligible patients had a Mayo score of 6–12 with a centrally read endoscopic subscore (modified to exclude friability from grade 1) of 2 or higher and no individual subscore of less than 1, and confirmation of left-sided disease. Patients were randomised (1:1:1:1:1; block size of ten) via a computer-generated schedule and centralised interactive voice and web response system to receive rectal enemas of cobitolimod at 31 mg, 125 mg, or 250 mg at weeks 0 and 3 (2 × 31 mg, 2 × 125 mg, and 2 × 250 mg groups), cobitolimod at 125 mg at weeks 0, 1, 2, and 3 (4 × 125 mg group), or placebo. Randomisation was stratified by current glucocorticosteroid and previous tumour necrosis factor inhibitor treatment. Patients and all study personnel were masked to treatment allocation. The primary endpoint was the proportion of patients achieving clinical remission (Mayo subscores for rectal bleeding of 0, for stool frequency of 0 or 1 [with ≥1-point decrease from baseline], and for endoscopy of 0 or 1 [excluding friability]) at week 6. The primary analysis (based on intention to treat) and safety analysis were done in all randomly assigned patients who received at least one dose of active study drug or placebo. In this exploratory study, statistical tests were one-sided; p values of less than 0·10 were regarded as statistically significant, with no adjustment for multiplicity. This study is registered with ClinicalTrials.gov, NCT03178669, and is completed; the results here represent the final analysis. Findings: 213 patients were randomly assigned between June 30, 2017, and June 26, 2019. Of these, 211 patients received study treatment: 40 in the cobitolimod 2 × 31 mg group, 43 in the 2 × 125 mg group, 42 in the 4 × 125 mg group, 42 in the 2 × 250 mg group, and 44 in the placebo group. A greater proportion of patients were in clinical remission at week 6 in the cobitolimod 2 × 250 mg group than in the placebo group (nine [21%] of 42 patients vs three [7%] of 44; odds ratio [OR] 3·8 [80% CI 1·5–9·5]; one-sided p=0·025). We identified no significant difference in the proportion of patients with clinical remission in the cobitolimod 2 × 31 mg group (five [13%] of 40 patients; OR 2·0 [80% CI 0·7–5·5], p=0·18), 2 × 125 mg group (two [5%] of 43; 0·7 [0·2–2·2], p=0·66), or 4 × 125 mg (four [10%] of 42; 1·4 [0·5–3·9], p=0·33) compared with the placebo group. Treatment-emergent adverse events occurred in 21 (48%) patients in the placebo group, ten (25%) patients in the cobitolimod 2 × 31 mg group, 17 (40%) patients in the 2 × 125 mg group, 15 (36%) patients in the 4 × 125 mg group, and 18 (43%) patients in the 2 × 250 mg group. Severe adverse events occurred in eight (4%) of 211 patients (worsening of ulcerative colitis [seven patients] and abdominal hernia and wound dehiscence [one patient]). Ten patients (two [5%] in the placebo group, two [5%] in the cobitolimod 2 × 31 mg group, two [5%] in the 4 × 125 mg, and four [10%] in the 2 × 250 mg group) had a total of 13 serious adverse events; these were worsening of ulcerative colitis (eight events) and pruritus, rash, abdominal hernia, fascia dehiscence, and deep vein thrombosis (one event each). One patient in the placebo group died from total organ failure after receiving a colectomy for a serious adverse event of disease worsening. Interpretation: Two topical administrations of cobitolimod 250 mg were well tolerated and more effective than placebo in inducing clinical remission 6 weeks after the start of treatment. TLR9 activation is a promising novel therapeutic target in ulcerative colitis and warrants further testing, with phase 3 trials of cobitolimod planned. Funding: InDex Pharmaceuticals.
CRIS-Team Scopus Importer:2020-11-13

Cobitolimod for Moderate-to-Severe Left-Sided Ulcerative Colitis (CONDUCT): A Phase 2b, Randomized, Double-Blind, Placebo-Controlled, Dose-Ranging Trial - Atreya, Raja; Peyrin-Biroulet, Laurent; Klymenko, Andrii; Augustyn, Monica; Bakulin, Igor; Slankamenac, Dusan; Miheller, Pal; Gasbarrini, Antonio; Hebuterne, Xavier; Arnesson, Karin; Knittel, Thomas; Kowalski, Jan; et al. (AMERICAN JOURNAL OF GASTROENTEROLOGY, 2020)
CRIS-Team WoS Importer:2021-02-12

Cold or hot snare in endoscopy - that is the question - Vieth, Michael; Neurath, Markus (Endoscopy International Open, 2022)
In the current issue of Endoscopy International Open, Ikeda et al. [1] present a feasibility study on cold snare removal of colonic polyps. The aim was to elucidate whether the quality of the cold snare specimens can be increased by placing the tissues on filter pape
CRIS-Team WoS Importer:2022-05-27

Colitis-associated neoplasia: molecular basis and clinical translation - Försch, Sebastian; Neurath, Markus (Cellular and Molecular Life Sciences, 2014)
Crohn's disease and ulcerative colitis are both associated with an increased risk of inflammation-associated colorectal carcinoma. Colitis-associated cancer (CAC) is one of the most important causes for morbidity and mortality in patients with inflammatory bowel diseases (IBD). Colitis-associated neoplasia distinctly differs from sporadic colorectal cancer in its biology and the underlying mechanisms. This review discusses the molecular mechanisms of CAC and summarizes the most important genetic alterations and signaling pathways involved in inflammatory carcinogenesis. Then, clinical translation is evaluated by discussing new endoscopic techniques and their contribution to surveillance and early detection of CAC. Last, we briefly address different types of concepts for prevention (i.e., anti-inflammatory therapeutics) and treatment (i.e., surgical intervention) of CAC and give an outlook on this important aspect of IBD.
EVALuna2:1861

Colonoscopy, inflammatory bowel disease - Neumann, Helmut; Neurath, Markus (Endoscopy, 2014)
EVALuna2:1891

Combined de‐repression of chemoresistance associated mitogen‐activated protein kinase 14 and activating transcription factor 2 by loss of microrna‐622 in hepatocellular carcinoma - Fritz, Valerie; Malek, Lara; Gaza, Anne; Wormser, Laura; Appel, Majken; Kremer, Andreas; Thasler, Wolfgang E.; Neurath, Markus; Hellerbrand, Claus; Boßerhoff, Anja Katrin; Dietrich, Peter; Siebler, Jürgen (Cancers, 2021)
Chemoresistance is a major hallmark driving the progression and poor prognosis of hepatocellular carcinoma (HCC). Limited chemoresponse of HCC was demonstrated to be mediated by mitogen‐activated protein kinase 14 (MAPK14) and activating transcription factor 2 (ATF2). Recently, we have demonstrated loss of control of RAS‐RAF‐ERK‐signaling as a consequence of miR‐622 downregulation in HCC. However, the majority of target genes of this potent tumorsuppressive microRNA had remained elusive. The MAPK14‐ATF2‐axis represents a collateral pathway ensuring persisting ERK‐activation in the presence of sorafenib‐mediated RAF-inhibition. In contrast to the function of the MAPK14‐ATF2‐axis, both the expression and regulation of MAPK14 and ATF2 in human HCC remained to be clarified. We found combined overexpression of MAPK14 and ATF2 in human HCC cells, tissues and in sorafenib resistant cell lines. High expression of MAPK14 and ATF2 was associated with reduced overall survival in HCC patients. Deciphering the molecular mechanism promoting combined upregulation of MAPK14 and ATF2 in HCC, we revealed that miR‐622 directly targets both genes, resulting in combined de‐repression of the MAPK14‐ATF2‐axis. Together, miR‐622 represents a superior regulator of both RAS‐RAF‐ERK as well as MAPK14‐ATF2‐signaling pathways in liver cancer.
CRIS-Team Scopus Importer:2021-03-19
Keywords: HCC; Hepatocellular carcinoma; Liver cancer; MAPK14; MicroRNA; MiR‐622; RAS

Comparative Transcriptomics of IBD Patients Indicates Induction of Type 2 Immunity Irrespective of the Disease Ideotype - Gonzalez Acera, Miguel; Patankar, Jay; Diemand, Leonard; Siegmund, Britta; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Frontiers in Medicine, 2021)
Inflammatory cytokines initiate and sustain the perpetuation of processes leading to chronic inflammatory conditions such as inflammatory bowel diseases (IBD). The nature of the trigger causing an inflammatory reaction decides whether type 1, type 17, or type 2 immune responses, typically characterized by the respective T- helper cell subsets, come into effect. In the intestine, Type 2 responses have been linked with mucosal healing and resolution upon an immune challenge involving parasitic infections. However, type 2 cytokines are frequently elevated in certain types of IBD in particular ulcerative colitis (UC) leading to the assumption that Th2 cells might critically support the pathogenesis of UC raising the question of whether such elevated type 2 responses in IBD are beneficial or detrimental. In line with this, previous studies showed that suppression of IL-13 and other type 2 related molecules in murine models could improve the outcomes of intestinal inflammation. However, therapeutic attempts of neutralizing IL-13 in ulcerative colitis patients have yielded no benefits. Thus, a better understanding of the role of type 2 cytokines in regulating intestinal inflammation is required. Here, we took a comparative transcriptomic approach to address how Th2 responses evolve in different mouse models of colitis and human IBD datasets. Our data show that type 2 immune-related transcripts are induced in the inflamed gut of IBD patients in both Crohn's disease and UC and across widely used mouse models of IBD. Collectively our data implicate that the presence of a type 2 signature rather defines a distinct state of intestinal inflammation than a disease-specific pathomechanism.
CRIS-Team Scopus Importer:2021-06-25
Keywords: chronic inflammation; IBD; intestine; type 2 immunity; ulcerative colitis

Comparison of Acoustic Radiation Force Impulse (ARFI) Elastography Measurements with the 4C1 Transducer to the 6C1HD Transducer: A Phantom and Patient Study - Pfeifer, Lukas; Görtz, Rüdiger; Neurath, Markus; Strobel, Deike; Wildner, Dane (Ultraschall in der Medizin, 2016)
Purpose: The aim of this study was to evaluate whether acoustic radiation force impulse (ARFI) elastography done with the 4C1 probe yields comparable results to the recently introduced 6C1HD probe. Materials and Methods: Measurements with the 4C1 and 6C1HD probes (Acuson S2000) were performed and compared in four different inclusions of an elasticity phantom model (QA049 CIRS) as well as in the liver of healthy individuals and patients with liver cirrhosis. Results: Measurements with the 6C1HD probe were slightly higher in all phantom inclusions (8, 14, 45, 80kPA) with a mean of 1.48 m/s (95 %-CI; 1.47 - 1.49), 2.18 m/s (95 %-CI; 2.17 - 2.19), 3.61 m/s (95 %-CI; 3.57 - 3.64) and 4.34 m/s (95 %-CI; 4.29 - 4.39) compared to the 4C1 transducer with 1.46 m/s (95 %-CI; 1.45 - 1.47), 2.15 m/s (95 %-CI; 2.14 - 2.16), 3.39 m/s (95 %-CI; 3.37 - 3.41) and 3.98 m/s (95 %-CI; 3.75 - 4.21), respectively (p = 0.04, p < 0.01, p < 0.01, p < 0.01). Cirrhotic patients (n = 40) had a higher mean shear wave speed with 3.00 m/s (95 %-CI; 2.80 - 3.21) with the 6C1HD transducer compared to 2.81 m/s (95 %-CI; 2.64 - 2.99) with the 4C1 transducer (p = 0.03). Healthy individuals (n = 20) had a mean shear wave speed of 1.12 m/s (95 %-CI; 1.06 - 1.17) with the 6C1HD probe and 1.12 m/s (95 %-CI; 1.05 - 1.19) with the 4C1 probe (p = 0.96). Conclusion: ARFI values assessed with a 6C1HD transducer are slightly higher than measurements with a 4C1 transducer in an ARFI phantom and in patients with liver cirrhosis. As the difference is small, current cut-off values keep their usefulness but should be interpreted with caution if measurements are close to the cut-off.
EVALuna2:2195

Comparison of Hemospray® and Endoclot™ for the treatment of gastrointestinal bleeding - Vitali, Francesco; Naegel, Andreas; Atreya, Raja; Zopf, Steffen; Neufert, Clemens; Neurath, Markus; Rath, Timo; Siebler, Jürgen (World Journal of Gastroenterology, 2019)
BACKGROUND Gastrointestinal (GI) bleeding is a common indication for endoscopy. For refractory cases, hemostatic powders (HP) represent “touch-free” agents. AIM To analyze short term (ST-within 72 h-) and long-term (LT-within 30 d-) success for achieving hemostasis with HP and to directly compare the two agents Hemospray (HS) and Endoclot (EC). METHODS HP was applied in 154 consecutive patients (mean age 67 years) with GI bleeding. Patients were followed up for 1 mo (mean follow-up: 3.2 mo). RESULTS Majority of applications were in upper GI tract (89%) with following bleeding sources: peptic ulcer disease (35%), esophageal varices (7%), tumor bleeding (11.7%), reflux esophagitis (8.7%), diffuse bleeding and erosions (15.3%). Overall ST success was achieved in 125 patients (81%) and LT success in 81 patients (67%). Re-bleeding occurred in 27% of all patients. In 72 patients (47%), HP was applied as a salvage hemostatic therapy, here ST and LT success were 81% and 64%, with re-bleeding in 32%. As a primary hemostatic therapy, ST and LT success were 82% and 69%, with re-bleeding occurring in 22%. HS was more frequently applied for upper GI bleeding (P = 0.04) CONCLUSION Both HP allow for effective hemostasis with no differences in ST, LT success and re-bleeding.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Endoclot; Gastrointestinal bleeding; Haemostasis; Hemospray; Hemostatic powder

Comparison of Hemospray (R) and Endoclot (TM) for the treatment of gastrointestinal bleeding - Vitali, Francesco; Naegel, Andreas; Atreya, Raja; Zopf, Steffen; Neufert, Clemens; Neurath, Markus; Rath, Timo; Siebler, Jürgen (World Journal of Gastroenterology, 2019)
BACKGROUND
CRIS-Team WoS Importer:2019-04-16

Complementary roles of murine NaV1.7, NaV1.8 and NaV1.9 in acute itch signalling - Kühn, Helen; Kappes, Leonie; Wolf, Katharina; Gebhardt, Lisa; Neurath, Markus; Reeh, Peter; Fischer, Michael J.M.; Kremer, Andreas (Scientific Reports, 2020)
Acute pruritus occurs in various disorders. Despite severe repercussions on quality of life treatment options remain limited. Voltage-gated sodium channels (NaV) are indispensable for transformation and propagation of sensory signals implicating them as drug targets. Here, NaV1.7, 1.8 and 1.9 were compared for their contribution to itch by analysing NaV-specific knockout mice. Acute pruritus was induced by a comprehensive panel of pruritogens (C48/80, endothelin, 5-HT, chloroquine, histamine, lysophosphatidic acid, trypsin, SLIGRL, β-alanine, BAM8-22), and scratching was assessed using a magnet-based recording technology. We report an unexpected stimulus-dependent diversity in NaV channel-mediated itch signalling. NaV1.7−/− showed substantial scratch reduction mainly towards strong pruritogens. NaV1.8−/− impaired histamine and 5-HT-induced scratching while NaV1.9 was involved in itch signalling towards 5-HT, C48/80 and SLIGRL. Furthermore, similar microfluorimetric calcium responses of sensory neurons and expression of itch-related TRP channels suggest no change in sensory transduction but in action potential transformation and conduction. The cumulative sum of scratching over all pruritogens confirmed a leading role of NaV1.7 and indicated an overall contribution of NaV1.9. Beside the proposed general role of NaV1.7 and 1.9 in itch signalling, scrutiny of time courses suggested NaV1.8 to sustain prolonged itching. Therefore, NaV1.7 and 1.9 may represent targets in pruritus therapy.
CRIS-Team Scopus Importer:2020-02-21

Computed Tomography-Guided Percutaneous Gastrostomy/Jejunostomy for Feeding and Decompression - Albrecht, Heinz; Hagel, Alexander; Schlechtweg, Philipp; Förtsch, Thomas; Neurath, Markus; Mudter, Jonas (Nutrition in Clinical Practice, 2017)
An effective method for long-term enteral feeding or stomach decompression is the use of a percutaneous gastrostomy (PEG) or sometimes jejunostomy (PEJ). Under certain circumstances (eg, inadequate transillumination), endoscopic placement of PEG/PEJ tubes is impossible. In these cases, computed tomography (CT)-guided PEG/PEJ may represent an alternative technique. In this study, we evaluate indications, results, and complications of CT-guided PEG/PEJ.A total of 102 consecutive referred patients were enrolled in the study. Patients came to the endoscopy unit of our department to undergo a CT-guided PEG/PEJ for long-term intragastric/intrajejunal feeding (n = 57) or decompression (n = 45). The majority (n = 98) received a pull-through PEG/PEJ with simultaneous gastroscopy/jejunoscopy. Dose length product and the effective dose for every patient were calculated.PEG/PEJ tube placement was successful in 87.3% (89 of 102). Feeding PEG/PEJ tube placement was successfully completed in 91.2% (52 of 57); decompressive PEG/PEJ tube placement was likewise successfully completed in 82.2% (37 of 45). No procedure-related mortality was observed. Minor complications (eg, tube dysfunction, local bleeding, minimal leakage, local skin infection) were observed in 13 patients. The complication rate was similar between the feeding and decompression groups ( P = .9).CT-guided PEG/PEJ is a feasible and safe method with a low procedure-related morbidity rate for patients where endoscopic placement via transillumination is not successful. Thus, the procedure is an attractive alternative to surgical tube placement. Long-term complications, mainly tube disturbances, can be treated easily.
EVALuna2:14587

Computer-aided detection of colorectal polyps using a newly generated deep convolutional neural network: from development to first clinical experience - Pfeifer, Lukas; Neufert, Clemens; Leppkes, Moritz; Waldner, Maximilian; Hafner, Michael; Beyer, Albert; Hoffman, Arthur; Siersema, Peter D.; Neurath, Markus; Rath, Timo (European Journal of Gastroenterology & Hepatology, 2021)
Aim The use of artificial intelligence represents an objective approach to increase endoscopist's adenoma detection rate (ADR) and limit interoperator variability. In this study, we evaluated a newly developed deep convolutional neural network (DCNN) for automated detection of colorectal polyps ex vivo as well as in a first in-human trial.
CRIS-Team WoS Importer:2022-03-18

Concept to gain trust for a German personal health record system using public cloud and FHIR - Ploner, Nico; Neurath, Markus; Schoenthaler, Martin; Zielke, Andreas; Prokosch, Hans-Ulrich (Journal of Biomedical Informatics, 2019)
Objective: Although a national Personal Health Record (PHR) infrastructure was supposed to have been introduced in Germany by law in 2006 and different providers are entering the market, no system has yet been widely adopted in Germany. There is also little information available on how current technical advancements affect German patients' and physicians' trust in PHR systems. Methods: Supporting scenarios obtained from clinicians, this study proposes a concept for a German PHR system using a public cloud infrastructure, smartphone access and focusing on trust, privacy, and interoperability. In advance to an eventual implementation, a multi-center questionnaire study has been conducted to predict patients' and physicians' intention to use that system and evaluate their trust in different providers of such a system. Results: Our results show that both patients and physicians are highly likely to use the PHR based on the present concept. Trust in healthcare providers exceeds trust in other institutions like private companies, health insurance companies, or even governmental institutions when offering such a PHR system. Conclusions: We recommend the implementation of this PHR system. To maximize patients' and physicians' trust in the system, it should be offered to patients by their healthcare provider. Further evaluation regarding its actual adoption and expected improvement in patient outcome based on the scenarios is advisable.
CRIS-Team Scopus Importer:2019-07-26
Keywords: Electronic medical records; FHIR; Health information exchange; Personal health records

Confocal endomicroscopy identifies loss of local barrier function in the duodenum of patients with Crohn's disease and ulcerative colitis - Lim, Lee G.; Neumann, Janina; Hansen, Torsten; Goetz, Martin; Hoffman, Arthur; Neurath, Markus; Galle, Peter R.; Chan, Yiong H.; Kiesslich, Ralf; Watson, Alastair J. (Inflammatory Bowel Diseases, 2014)
Increased cell shedding with gap formation and local barrier dysfunction can be identified endomicroscopically in the terminal ileum of patients with inflammatory bowel disease. We aim to evaluate whether these changes are also present in the duodenum of patients with inflammatory bowel disease.Fifteen patients with Crohn's disease (CD), 10 patients with ulcerative colitis (UC), and 10 controls underwent fluorescein-aided confocal laser endomicroscopy (CLE). CLE was performed on macroscopically normal antral and duodenal (D1, D2, D3, D4) mucosa. Representative CLE images were prospectively analyzed. Images were scored for the number of epithelial gaps, cell shedding, and the degree of fluorescein leakage into the intestinal lumen.Both CD and UC patients had significantly more epithelial gaps, epithelial cell shedding, and leakage of fluorescein into the duodenal lumen than controls. The degree of cell shedding and epithelial gap formation was similar in CD and UC patients. In all cases, macroscopic endoscopic appearances of the duodenum were normal, and conventional histological analysis showed a mild nonspecific duodenitis in 7 of 15 patients with CD. Patients with UC had a histologically normal duodenum. Gap formation, cell shedding, and fluorescein leakage was similar in CD with active compared with inactive disease, except for D2 shedding.CLE can detect epithelial damage and barrier loss in the duodenum of CD and UC patients that is not apparent on conventional endoscopy or histology.
EVALuna2:1900

Confocal Laser Endomicroscopy Can Identify Microscopic Signs of Inflammation in Patients With Food Allergy - Rath, Timo; Atreya, Raja; Neurath, Markus; Zopf, Yurdagül; Siebler, Jürgen (2017)
EVALuna2:33903

CONFOCAL LASER ENDOMICROSCOPY CAN PREDICT MAJOR CLINICAL EVENTS WITH VERY HIGH SENSITIVITY IN PATIENTS WITH INFLAMMATORY BOWEL DISEASES - Klenske, Entcho; Atreya, Raja; Zundler, Sebastian; Fischer, Sven Moritz; Neurath, Markus; Rath, Timo (GASTROINTESTINAL ENDOSCOPY, 2019)
CRIS-Team WoS Importer:2019-06-21

Confocal laser endomicroscopy for diagnosing lung cancer in vivo - Fuchs, Florian; Zirlik, Sabine; Hildner, Kai; Schubert, Juergen; Vieth, Michael; Neurath, Markus (European Respiratory Journal, 2013)
Confocal laser endomicroscopy is a novel endoscopic technique that may allow imaging of living cells in lung tissue in vivo. We assessed the potential of this technique for the detection of histology during screening bronchoscopy for lung cancer. 32 patients with suspected malignancies underwent bronchoscopy with endomicroscopy using acriflavine hydrochloride. Standardised areas and localised lesions were analysed by in vivo confocal imaging during bronchoscopy and biopsies were taken. Confocal images were graded and correlated prospectively with conventional histology from biopsies. Acriflavine hydrochloride yielded high-quality confocal images and strongly labelled airway epithelial cells. No side-effects were noted. 75 522 confocal images from 56 different locations were compared prospectively with histological data from biopsy specimens. Endomicroscopy allowed subsurface imaging with detailed analysis of cellular and subcellular structures. Neoplastic changes could be predicted with high accuracy (sensitivity 96.0%, specificity 87.1%, accuracy 91.0%). Confocal laser endomicroscopy with acriflavine is a novel diagnostic tool for the analysis of living cells during bronchoscopy and permits virtual histology of neoplastic changes in the airways with high accuracy. This technique may enable the rapid diagnosis of neoplasia during ongoing endoscopy in patients with suspected lung cancer. Copyright©ERS 2013.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Bronchoscopy; Endomicroscopy; In vivo imaging; Lung cancer

Confocal Laser Endomicroscopy for Diagnosing Malignant Pleural Effusions - Zirlik, Sabine; Hildner, Kai; Rieker, Ralf; Neurath, Markus; Fuchs, Florian; Vieth, Michael (Medical Science Monitor, 2018)
BACKGROUND Confocal laser endomicroscopy (CLE) enables "in vivo" microscopic tissue diagnosis based on tissue reflectance or tissue fluorescence upon application of fluorescence agents. The aim of the present study was to evaluate CLE as a new diagnostic approach for differentiation between malignant versus non-malignant pleural effusions. MATERIAL AND METHODS In 100 patients with pleural effusions, thoracentesis was performed. Cresyl violet and acriflavine were used as contrast agents for probe-based CLE of effusions. CLE video sequences were assessed by 4 independent investigators (2 experienced in this technique, 2 with only basic knowledge). In addition, all CLE samples were evaluated by an expert pathologist (p). Results were compared with conventional cytology of effusions and histology of cell blocks. RESULTS CLE reliably permitted identification of malignant cells in pleural effusions. Sensitivity for detection of malignant effusions was 87% (p: 87%) and 81% (p: 72%) for acriflavine and cresyl violet, respectively. With regard to specificity, acriflavine and cresyl violet yielded a mean value of 99% (p: 100%) and 92% (p: 100%). CONCLUSIONS In this pilot study, CLE permitted simple and rapid detection of malignant pleural effusions. Larger prospective studies are warranted to corroborate our findings.
EVALuna2:35147

Confocal laser endomicroscopy for diagnosis of Barrett's esophagus - Neumann, Helmut; Langner, Cord; Neurath, Markus; Vieth, Michael (Frontiers in Oncology, 2012)
Barrett's esophagus (BE) is established as a premalignant condition in the distal esophagus. Current surveillance guidelines recommend random biopsies every 1-2 cm at intervals of 3-5 years. Advanced endoscopic imaging of BE underwent several technical revolutions within the last decade including broad-field (red-flag) techniques (e.g., chromoendoscopy) and small-field techniques with confocal laser endomicroscopy (CLE) at the forefront. In this review we will focus on advanced endoscopic imaging using CLE for the diagnosis and characterization of BE and associated neoplasia. In addition, we will critically discuss the technique of CLE and provide some tricks and hints for the daily routine practice of CLE for diagnosis of BE. © 2012 Neumann, Langner, Neurath and Vieth.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Advanced imgaging; Barrett; Cancer; CLE; Dysplasia; Endomicroscopy; Fluorescein

Confocal laser endomicroscopy for functional barrier imaging in Crohn's disease - Neurath, Markus (Endoscopy, 2016)
EVALuna2:2099

Confocal laser endomicroscopy for IBD assessment: An update - Neumann, Helmut; Atreya, Raja; Vieth, Michael; Neurath, Markus (Inflammatory Bowel Disease Monitor, 2011)
Advanced endoscopic imaging with virtual histology has become clinical reality since the introduction of confocal laser endomicroscopy (CLE) in 2004. In the meantime, various studies have shown the explicit potential of CLE for the diagnosis and characterization of different disease entities, including IBD. In this review, we will focus on the basic concepts of endomicroscopy and its increasing potential in IBD.
CRIS-Team Scopus Importer:2025-03-05

Confocal laser endomicroscopy for the differential diagnosis of ulcerative colitis and Crohn's disease: a pilot study - Tontini, Gian Eugenio; Mudter, Jonas; Atreya, Raja; Günther, Claudia; Zopf, Yurdagül; Wildner, Dane; Kiesslich, Ralf; Vecchi, Maurizio; Neurath, Markus; Neumann, Helmut; Vieth, Michael (Endoscopy, 2015)
The differential diagnosis of ulcerative colitis from Crohn's disease is of pivotal importance for the management of inflammatory bowel diseases, as both entities involve specific therapeutic management strategies. Confocal laser endomicroscopy (CLE) allows on-demand, in vivo characterization of architectural and cellular details during endoscopy. The aim of this study was to assess the efficacy of CLE to differentiate between ulcerative colitis and Crohn's disease.This was a prospective study involving consecutive patients with a well-established diagnosis of ulcerative colitis or Crohn's disease who underwent colonoscopy with fluorescein-aided confocal imaging.Overall, 79 patients were included (40 Crohn's disease, 39 ulcerative colitis). CLE findings in patients with Crohn's disease, showed significantly more discontinuous inflammation (87.5 % vs. 5.1 %), focal cryptitis (75.0 % vs. 12.8 %), and discontinuous crypt architectural abnormality (87.5 % vs. 10.3 %) than in ulcerative colitis (P < 0.0001). Conversely, ulcerative colitis was associated with severe, widespread crypt distortion (87.2 % vs. 17.5 % in Crohn's disease), decreased crypt density (79.5 % vs. 22.5 %), and frankly irregular surface (89.7 % vs. 17.5 %; P < 0.0001 for all comparisons). Statistically significant differences were not seen for heavy, diffuse lamina propria cell increase or mucin preservation. No granulomas were visible. Based on these findings, a CLE scoring system was developed that revealed excellent accuracy (93.7 %) when compared with the historical clinical diagnosis and the histopathological gold standard.CLE could visualize several disease-specific microscopic features, which are conventionally used in standard histopathology to differentiate between ulcerative colitis and Crohn's disease. However, because of the limited penetration depth of CLE, submucosal details or granulomas were not visible. The new scoring system may allow in vivo diagnosis of ulcerative colitis or Crohn's disease. Trial registered at ClinicalTrials.gov: NCT 02238665.
EVALuna2:2020

Contrast-Enhanced Multispectral Optoacoustic Tomography for Functional Assessment of the Gastrointestinal Tract - Paulus, Lars-Philip; Bühler, Adrian; Wagner, Alexandra; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Rother, Ulrich; Eckstein, Markus; Lang, Werner; Hörning, André; et al. (Advanced Science, 2023)
Real-time imaging and functional assessment of the intestinal tract and its transit pose a significant challenge to conventional clinical diagnostic methods. Multispectral optoacoustic tomography (MSOT), a molecular-sensitive imaging technology, offers the potential to visualize endogenous and exogenous chromophores in deep tissue. Herein, a novel approach using the orally administered clinical-approved fluorescent dye indocyanine green (ICG) for bedside, non-ionizing evaluation of gastrointestinal passage is presented. The authors are able to show the detectability and stability of ICG in phantom experiments. Furthermore, ten healthy subjects underwent MSOT imaging at multiple time points over eight hours after ingestion of a standardized meal with and without ICG. ICG signals can be visualized and quantified in different intestinal segments, while its excretion is confirmed by fluorescent imaging of stool samples. These findings indicate that contrast-enhanced MSOT (CE-MSOT) provides a translatable real-time imaging approach for functional assessment of the gastrointestinal tract.
CRIS-Team Scopus Importer:2023-06-30
Keywords: indocyanine green; intestine; multispectral optoacoustic tomography; optoacoustics; photoacoustics

Contrast-Enhanced µCT for Visualizing and Evaluating Murine Intestinal Inflammation - Jung, Dennis; Heiß, Rafael; Kramer, Viktoria; Thoma, Oana-Maria; Regensburger, Adrian; Rascher, Wolfgang; Uder, Michael; Neurath, Markus; Knieling, Ferdinand; Waldner, Maximilian (Theranostics, 2018)
Rationale: To develop a simple and fast protocol for the assessment of acute and chronic experimental intestinal inflammation using contrast-enhanced µCT. Methods: For the imaging studies, an acute 2% and 3% dextran sodium sulfate (n = 15, female, 8-12 weeks) and a chronic adoptive transfer colitis model (n = 10, female, 8-9 weeks) were established over 9 days or 6 weeks, respectively. Throughout the experiments, longitudinal measurement of murine intestinal wall thickness and time dependent perfusion was performed on a small animal µCT system (90 kV, 160 μA, FOV: 60 mm, scan time: 17 s, image size: 512x512, layer thickness: 118 µm) between 0.5 and 30 min after intravenous bolus injection of an iodine contrast agent. Weight development, small animal endoscopy, and histological ex vivo analysis were compared to contrast-enhanced µCT imaging findings. Results: Murine intestinal wall thickness was significantly increased in inflamed colons of acute colitis at day 9 in comparison to pre-inflamed state. Perfusion analysis revealed a late contrast enhancement in acute inflamed colons and the renal medulla at day 9 compared to control mice. An increasing intestinal wall thickness was monitored 3, 5 and 6 weeks after on-set of chronic colitis in comparison to controls. A good correlation with endoscopic (r = 0.75, p < 0.0001) and histologic degree of inflammation (r = 0.83, p = 0.04) was found. Conclusion: Contrast-enhanced µCT is a simple and fast method to assess acute intestinal inflammation and to monitor disease progression in experimental models of chronic colitis. According to our findings, one single contrast-enhanced µCT-scan is a valid non-invasive modality to quantify the degree of inflammation in the entire digestive tract in murine inflammatory models.
EVALuna2:35195

Controlling in and out - the future of interfering with immune cell trafficking in inflammatory bowel disease - Zundler, Sebastian; Schulze, Lisa; Neurath, Markus (Expert Review of Clinical Immunology, 2022)
IntroductionImmune cell trafficking is a key requirement in the pathogenesis of inflammatory bowel diseases. Consistently, therapeutic strategies to target immune cell trafficking have been established and continue to be developed for the treatment of ulcerative colitis and Crohn's disease.Areas coveredIn this review, we briefly summarize the most important checkpoints of intestinal immune cell trafficking and their importance during IBD. Moreover, we provide an overview of associated therapeutic targets and previous as well as current efforts on treatment strategies related to these targets.Expert opinionFinally, we comment on potential future developments that might shape the field of immune cell trafficking in the context of IBD.
CRIS-Team WoS Importer:2023-01-06

Correction to: Influence of cancer and acute inflammatory disease on taste perception: a clinical pilot study - Schalk, Priska; Kohl, M.; Herrmann, H. J.; Schwappacher, R.; Rimmele, M. E.; Büttner, Andrea; Neurath, Markus; Zopf, Yurdagül; Siebler, Jürgen (Supportive Care in Cancer, 2019)
The "Acknowledgment Statement" of the published paper is incorrect. The correct statement should be the below: Acknowledgements We thank Sarah Vogel for her support in taste test realization and Yvonne Sauermann for preparation of the tastant solutions. The present work was carried out by Ms. Schalk in order to meet the requirements for the awarding of the title of Dr. med. at the FAU.
EVALuna2:184490

Correction to: Influence of cancer and acute inflammatory disease on taste perception: a clinical pilot study (Supportive Care in Cancer, (2019), 27, 4, (1579), 10.1007/s00520-019-4642-6) - Schalk, Priska; Kohl, M.; Herrmann, H. J.; Schwappacher, R.; Rimmele, Martina; Büttner, Andrea; Neurath, Markus; Zopf, Yurdagül; Siebler, Jürgen (Supportive Care in Cancer, 2020)
The Acknowledgement Statement was incorrect in the original publication of this article [1] and the previous correction note [2]. The correct statement is as follows:
CRIS-Team Scopus Importer:2020-02-28

COVID-19 and immune-mediated inflammatory diseases: effect of disease and treatment on COVID-19 outcomes and vaccine responses - Fagni, Filippo; Simon, David; Tascilar, Koray; Schoenau, Verena; Sticherling, Michael; Neurath, Markus; Schett, Georg (The Lancet Rheumatology, 2021)
At the beginning of the COVID-19 pandemic, patients with immune-mediated inflammatory diseases were considered to be at high risk for SARS-CoV-2 infection and the development of severe COVID-19. Data collected over the past year, however, suggest that a diagnosis of inflammatory arthritis, psoriasis, or inflammatory bowel diseases does not increase risk for SARS-CoV-2 infection or severe COVID-19 compared with people without these diseases. Furthermore, substantial data suggest that certain medications frequently used in patients with immune-mediated inflammatory diseases, in particular cytokine inhibitors, might even lower the risk for severe COVID-19. Conversely, glucocorticoids and potentially B-cell-depleting treatments seem to worsen COVID-19 outcomes. Additionally, the first data on SARS-CoV-2 vaccination in patients with these diseases suggest that tolerability of vaccination in patients with immune-mediated inflammatory diseases is good, although the immune response to vaccination can be somewhat reduced in this patient group, particularly those taking methotrexate or CD20-targeted treatment.
CRIS-Team Scopus Importer:2021-10-01

Covid-19 and immunomodulation in IBD - Neurath, Markus (Gut, 2020)
The current coronavirus pandemic is an ongoing global health crisis due to covid-19, caused by severe acute respiratory syndrome coronavirus 2. Although covid-19 leads to little or mild flu-like symptoms in the majority of affected patients, the disease may cause severe, frequently lethal complications such as progressive pneumonia, acute respiratory distress syndrome and organ failure driven by hyperinflammation and a cytokine storm syndrome. This situation causes various major challenges for gastroenterology. In the context of IBD, several key questions arise. For instance, it is an important question to understand whether patients with IBD (eg, due to intestinal ACE2 expression) might be particularly susceptible to covid-19 and the cytokine release syndrome associated with lung injury and fatal outcomes. Another highly relevant question is how to deal with immunosuppression and immunomodulation during the current pandemic in patients with IBD and whether immunosuppression affects the progress of covid-19. Here, the current understanding of the pathophysiology of covid-19 is reviewed with special reference to immune cell activation. Moreover, the potential implications of these new insights for immunomodulation and biological therapy in IBD are discussed.
CRIS-Team Scopus Importer:2020-05-08
Keywords: cytokines; inflammation; inflammatory bowel disease

COVID-19: biologic and immunosuppressive therapy in gastroenterology and hepatology - Neurath, Markus (Nature Reviews Gastroenterology & Hepatology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic is an ongoing global health crisis causing major challenges for clinical care in patients with gastrointestinal diseases. Although triggering of anti-viral immune responses is essential for clearance of infection, some patients have severe lung inflammation and multiorgan failure due to marked immune cell dysregulation and cytokine storm syndrome. Importantly, the activation of cytotoxic follicular helper T cells and a reduction of regulatory T cells have a crucial, negative prognostic role. These findings lead to the question of whether immunosuppressive and biologic therapies for gastrointestinal diseases affect the incidence or prognosis of COVID-19 and, thus, whether they should be adjusted to prevent or affect the course of the disease. In this Review, data on the use of such therapies are discussed with a primary focus on inflammatory bowel disease, autoimmune hepatitis and liver transplantation. In particular, the roles of corticosteroids, classic immunosuppressive agents (such as thiopurines and mycophenolate mofetil), small molecules (such as Janus kinase (JAK) inhibitors), and biologic agents (such as tumour necrosis factor (TNF) blockers, vedolizumab and ustekinumab) are reviewed. Finally, the use of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines for the prevention of infection in patients with gastrointestinal diseases and concomitant immunosuppressive or biologic therapy will be discussed.
CRIS-Team Scopus Importer:2021-07-16

COVID-19 - more than respiratory disease: a gastroenterologist's perspective. - Konturek, P. C.; Harsch, I. A.; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2020)
Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV2) outbreak is the most dramatic event since World War II. Originating as a cluster of unexplained cases of pneumonia, it turned out that this viral disease termed COVID-19 is not only a respiratory infection, but a systemic disease associated with a number of extrapulmonary complications. One of the medical disciplines that is strongly affected by this viral infection is gastroenterology. COVID-19 causes in some patients typical symptoms of enteritis such as diarrhea or abdominal pain. There is also evidence that this infection may lead to liver and pancreatic injury. Since the SARS-CoV2 virus was detected in stool, a fecal-oral route of transmission is possible. Moreover, viral receptor angiotensin converting enzyme 2 (ACE2) is highly expressed in the gastrointestinal tract and enables the invasion of the gastrointestinal epithelium as demonstrated in vitro and in vivo. COVID-19 pandemic has an impact on the daily practice and the workflows in endoscopy leading to a dramatic decrease of screening and surveillance procedures. COVID-19 impacts the therapy of patients with inflammatory bowel disease (IBD), particularly those using high doses of corticosteroids, immunosuppressive agents and biologics. Patients with preexisting liver disease, especially metabolic associated liver fatty disease (MALFD) with fibrosis or liver cirrhosis, are at high risk for severe COVID-19. As long as no active vaccine against SARS-CoV2 is available, gastroenterologists have to be aware of these problems that affect their daily routine practice.
EVALuna2:489598
Keywords: SARS-CoV2; pandemic; COVID-19; gastrointestinal manifestations; anti-inflammatory therapy; gut microbiota; endoscopy; inflammatory bowel disease; liver disease

COVID-19: risk for cytokine targeting in chronic inflammatory diseases? - Schett, Georg; Sticherling, Michael; Neurath, Markus (Nature Reviews Immunology, 2020)
CRIS-Team Scopus Importer:2020-04-28

CRISPR/Cas9 in Gastrointestinal Malignancies - Jefremow, André; Neurath, Markus; Waldner, Maximilian (Frontiers in Cell and Developmental Biology, 2021)
Gastrointestinal (GI) cancers such as colorectal cancer (CRC), gastric cancer (GC), esophageal cancer (EG), pancreatic duct adenocarcinoma (PDAC) or hepatocellular cancer (HCC) belong to the most commonly diagnosed types of cancer and are among the most frequent causes of cancer related death worldwide. Most types of GI cancer develop in a stepwise fashion with the occurrence of various driver mutations during tumor progression. Understanding the precise function of mutations driving GI cancer development has been regarded as a prerequisite for an improved clinical management of GI malignancies. During recent years, CRISPR/Cas9 has developed into a powerful tool for genome editing in cancer research by knocking in and knocking out even multiple genes at the same time. Within this review, we discuss recent applications for CRISPR/Cas9-based genome editing in GI cancer research including CRC, GC, EG, PDAC and HCC. These applications include functional studies of candidate genes in cancer cell lines or organoids in vitro as well as in murine cancer models in vivo, library screening for the identification of previously unknown driver mutations and even gene therapy of GI cancers.
CRIS-Team Scopus Importer:2021-12-31
Keywords: cancer of the biliary tract; colorectal cancer; CRISPR/cas9; esophageal cancer; gastrointestinal cancer; hepatocellular cancer; pancreatic cancer

Cross-sectional imaging of intestinal barrier dysfunction by confocal laser endomicroscopy can identify patients with food allergy in vivo with high sensitivity - Rath, Timo; Dieterich, Walburga; Kätscher-Murad, Christiane; Neurath, Markus; Zopf, Yurdagül (Scientific Reports, 2021)
Food allergy (FA) affects approximately 3 to 4% of the adult population in westernized countries. Suspected FA is even more prevalent and requires extensive diagnostic work-up. Within this study, we evaluated whether assessment of the integrity of the epithelial barrier by confocal laser endomicroscopy (CLE) during colonoscopy can be used as a screening tool to identify patients with FA. 60 patients with suspected FA were prospectively included. Serology with total and food-specific IgE, anti-tissue transglutaminase, skin prick testing, food intolerance tests, food intake registration and assessment of clinical complaints were performed. During colonocopy, standardized CLE was performed in the terminal ileum and at two colorectal sites. Analysis of CLE images included functional (i.e. presence of epithelial barrier dysfunction) and quantitative parameters of intestinal architecture. 27 of 60 patients (45%) were diagnosed with FA. Barrier dysfunction was analyzed on 65.837 ileal and on 93.251 colonic images. 96% of patients with FA exhibited functional and structural barrier defects while barrier dysfunction was found in only 33% of patients without FA (p < 0.0001). Visualizing barrier dysfunction with CLE for in vivo diagnosis of FA had a sensitivity and specificity of 96% and 67%, respectively, with a positive and negative prediction of 70% and 96%, respectively. Parameters intrinsic to the crypt architecture including crypt diameter, intercrypt distance, crypt lumen diameter and colonic vasculature were not different between patients with and without FA. CLE-based imaging of the intestinal barrier during colonoscopy might help in stratifying patients with suspected FA for further diagnostic work-up.
CRIS-Team Scopus Importer:2021-06-25

Current and Emerging Targeted Therapies for Ulcerative Colitis. - Pietschner, Robert; Rath, Timo; Neurath, Markus; Atreya, Raja (Visceral Medicine, 2023)
BACKGROUND: Ulcerative colitis is one of the main entities of inflammatory bowel diseases. The clinical course of this immune-mediated disorder is marked by unpredictable exacerbations and asymptomatic remission, causing lifelong morbidity. Optimized anti-inflammatory treatment is a prerequisite to not only restore the quality of life of the affected patients but also halt progressive bowel damage and reduce the risk for colitis-associated neoplasia. Advances in understanding the underlying immunopathogenesis of ulcerative colitis have led to the advent of targeted therapies that selectively inhibit crucial molecular structures or signaling pathways that perpetuate the inflammatory reaction. SUMMARY: We will delineate the mode of action and summarize efficacy and safety data of current and emerging targeted therapies in ulcerative colitis, which encompasses representatives of the drug classes of antibodies, small molecules, and oligonucleotides. These substances have already been approved for induction and maintenance treatment or are being tested in late-stage clinical trials in moderately-to-severely active ulcerative colitis patients. These advanced therapies have enabled us to define and achieve novel therapeutic outcomes, such as clinical and endoscopic remission, histological remission, mucosal healing, and recently, also barrier healing as an emerging outcome measure. KEY MESSAGES: Established and emerging targeted therapies and monitoring modalities broaden our therapeutic armamentarium and have enabled us to define novel therapeutic outcomes that have the potential to modify the individual disease course of patients with ulcerative colitis.
EVALuna2:550705

Current and emerging therapeutic targets for IBD - Neurath, Markus (Nature Reviews Gastroenterology & Hepatology, 2017)
Various therapeutic advances have led to a paradigm shift in the clinical management of patients with IBD. The introduction of immunosuppressive (such as azathioprine) and biologic agents (such as TNF blockers) has markedly reduced the need to use corticosteroids for therapy. Furthermore, the α4β7 integrin blocker vedolizumab has been introduced for clinical IBD therapy. Moreover, various new inhibitors of cytokines (for example, IL-6-IL-6R and IL-12-IL-23 blockers or apremilast), modulators of cytokine signalling events (for example, JAK inhibitors or SMAD7 blocker), inhibitors of transcription factors (for example, GATA3 or RORγt) and new anti-adhesion and anti-T-cell-activation and migration strategies (for example, β7 integrin, sphingosine 1-phosphate receptors and MAdCAM1 inhibitors, regulatory T-cell therapy and stem cells) are currently being evaluated in controlled clinical trials. This Review aims to provide a comprehensive overview about current and future therapeutic approaches for IBD therapy. Furthermore, potential mechanisms of action of these therapeutic approaches and their implications for clinical therapy in IBD are discussed.
EVALuna2:33815

Current and Future Targets for Mucosal Healing in Inflammatory Bowel Disease - Atreya, Raja; Neurath, Markus (Visceral Medicine, 2017)
The induction and subsequent maintenance of mucosal healing has emerged as one of the central therapeutic goals in the management of patients with inflammatory bowel disease (IBD) (Crohn's disease and ulcerative colitis). Current and novel treatment options are assessed regarding their therapeutic efficacy on the basis of their ability to induce mucosal healing. However, there is still substantial debate about the precise definition of mucosal healing. Here, we will give an overview regarding the definitions of mucosal healing as well as its probable effects on long-term disease behavior and finally focus on current and potential therapeutic targets to achieve this therapeutic goal in IBD patients.
EVALuna2:35478

Current concepts in chronic inflammatory diseases: Interactions between microbes, cellular metabolism, and inflammation - Garn, Holger; Bahn, Sabine; Baune, Bernhard T.; Binder, Elisabeth B.; Bisgaard, Hans; Chatila, Talal A.; Chavakis, Triantafyllos; Culmsee, Carsten; Dannlowski, Udo; Gay, Steffen; Gern, James; Haahtela, Tari; et al. (Journal of Allergy and Clinical Immunology, 2016)
Recent research indicates that chronic inflammatory diseases, including allergies and autoimmune and neuropsychiatric diseases, share common pathways of cellular and molecular dysregulation. It was the aim of the International von-Behring-Röntgen Symposium (October 16-18, 2014, in Marburg, Germany) to discuss recent developments in this field. These include a concept of biodiversity; the contribution of urbanization, lifestyle factors, and nutrition (eg, vitamin D); and new mechanisms of metabolic and immune dysregulation, such as extracellular and intracellular RNAs and cellular and mitochondrial stress. Epigenetic mechanisms contribute further to altered gene expression and therefore to the development of chronic inflammation. These novel findings provide the foundation for further development of preventive and therapeutic strategies.
EVALuna2:2160

Current Endoscopic Resection Techniques for Gastrointestinal Lesions: Endoscopic Mucosal Resection, Submucosal Dissection, and Full-Thickness Resection - Hoffman, Arthur; Atreya, Raja; Rath, Timo; Neurath, Markus (Visceral Medicine, 2021)
Background: Endoscopic resection of dysplastic lesions in early stages of cancer reduces mortality rates and is recommended by many national guidelines throughout the world. Snare polypectomy and endoscopic mucosal resection (EMR) are established techniques of polyp removal. The advantages of these methods are their relatively short procedure times and acceptable complication rates. The latter include delayed bleeding in 0.9% and a perforation risk of 0.4-1.3%, depending on the size and location of the resected lesion. EMR is a recent modification of endoscopic resection. A limited number of studies suggest that larger lesions can be removed en bloc with low complication rates and short procedure times. Novel techniques such as endoscopic submucosal dissection (ESD) are used to enhance en bloc resection rates for larger, flat, or sessile lesions. Endoscopic full-thickness resection (EFTR) is employed for non-lifting lesions or those not easily amenable to resection. Procedures such as ESD or EFTR are emerging standards for lesions inaccessible to EMR techniques. Summary: Endoscopic treatment is now regarded as first-line therapy for benign lesions. Key Message: Endoscopic resection of dysplastic lesions or early stages of cancer is recommended. A plethora of different techniques can be used dependent on the lesions.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Complication rates; Early cancer; Endoscopic resection; Resection techniques

Cyclin-Dependent Kinase Inhibitors and Their Therapeutic Potential in Colorectal Cancer Treatment - Thoma, Oana-Maria; Neurath, Markus; Waldner, Maximilian (Frontiers in Pharmacology, 2021)
Cyclin-dependent kinases (CDKs) are key players in cell cycle regulation. So far, more than ten CDKs have been described. Their direct interaction with cyclins allow progression through G1 phase, transitions to S and G2 phase and finally through mitosis (M). While CDK activation is important in cell renewal, its aberrant expression can lead to the development of malignant tumor cells. Dysregulations in CDK pathways are often encountered in various types of cancer, including all gastrointestinal (GI) tract tumors. This prompted the development of CDK inhibitors as novel therapies for cancer. Currently, CDK inhibitors such as CDK4/6 inhibitors are used in pre-clinical studies for cancer treatment. In this review, we will focus on the therapeutic role of various CDK inhibitors in colorectal cancer, with a special focus on the CDK4/6 inhibitors.
CRIS-Team WoS Importer:2022-02-04

Cyclosporine A regulates pro-inflammatory cytokine production in ulcerative colitis - Steiner, Stefanie; Daniel, Carolin; Fischer, Anika; Atreya, Imke; Hirschmann, Simon; Waldner, Maximilian; Neumann, Helmut; Neurath, Markus; Atreya, Raja; Weigmann, Benno (Archivum Immunologiae Et Therapiae Experimentalis, 2015)
Crohn's disease (CD) and ulcerative colitis (UC) are the two major forms of inflammatory bowel diseases (IBD), which are defined as relapsing inflammations of the gastrointestinal tract. Cyclosporine A (CsA) is a potential rescue treatment to avoid colectomy in severe steroid-refractory UC patients. The molecular mechanism of action of CsA in UC is nevertheless still not well understood. The aim of this study was to investigate the effect of CsA on a possible modulation of cytokine production by peripheral blood mononuclear cells (PBMCs) of controls and patients with UC or CD. Upon CsA treatment, analyses of cytokine levels revealed a significant reduction of IL-13 expression in PBMCs from patients with UC, whereas other cytokine expression levels remained unaffected. To address the question whether CsA treatment impinges on the induction of cell death, apoptosis assays were performed using CD4(+) T cells from peripheral blood of patients suffering from either UC or CD. It became clear that CsA treatment resulted in a specific induction of apoptosis in samples from controls and patients with UC but not with CD. Apoptosis induction was not mediated via the mitochondrial apoptosis pathway. The present data support the concept that CsA treatment modulates pro-inflammatory cytokine production and T cell survival in UC via the induction of apoptosis and might therefore help to explain the clinical efficacy of CsA in patients with UC.
EVALuna2:1844

Cytokines in inflammatory bowel disease - Neurath, Markus (Nature Reviews Immunology, 2014)
Cytokines have a crucial role in the pathogenesis of inflammatory bowel diseases (IBDs), such as Crohn's disease and ulcerative colitis, where they control multiple aspects of the inflammatory response. In particular, the imbalance between pro-inflammatory and anti-inflammatory cytokines that occurs in IBD impedes the resolution of inflammation and instead leads to disease perpetuation and tissue destruction. Recent studies suggest the existence of a network of regulatory cytokines that has important implications for disease progression. In this Review, we discuss the role of cytokines produced by innate and adaptive immune cells, as well as their relevance to the future therapy of IBD.
EVALuna2:1846

Cytokines in inflammatory bowel diseases – Update 2020 - Leppkes, Moritz; Neurath, Markus (Pharmacological research, 2020)
Inflammatory Bowel Diseases (IBD), namely Crohn's Disease and Ulcerative Colitis, cause a significant disease burden in modern civilization. Ever since the introduction of anti-TNF-directed therapies 20 years ago, cytokines have attracted a lot of research attention and several cytokine-directed therapies have been implemented in the clinical treatment of these diseases. The research progress in these past years has underlined the importance of both myeloid and lymphoid elements of the immune system in the pathogenesis of IBD and their cytokine-mediated interplay. The conceptual framework of the mucosal cytokine network has shifted during these years from a T helper (Th) dichotomy (Th1/Th2) to the effector/regulatory T cell balance, while nowadays, the importance of myeloid cell instruction of lymphocytes, namely by IL-12 and IL-23, is increasingly recognized. Anti-IL-12p40 agents, like ustekinumab, groundbreakingly changed patient care, and anti-IL23p19-directed approaches are on the verge of grand success. In this review we present a modular approach to understand the cytokine network and put it into the context of the pathogenesis of IBD with a special focus on publications since 2014.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Biologicals; Crohn's disease; Cytokines; Gastroenterology; IBD; Ulcerative colitis

Deciphering Novel Mechanistic and Pharmacokinetic Effects of Tofacitinib in Intestinal Inflammation: Expect the Unexpected - Atreya, Raja; Neurath, Markus (Cellular and Molecular Gastroenterology and Hepatology, 2022)
CRIS-Team Scopus Importer:2022-02-04

Designer Thiopurine-analogues for Optimised Immunosuppression in Inflammatory Bowel Diseases - Atreya, Imke; Diall, Alexandra; Dvorsky, Radovan; Atreya, Raja; Henninger, Christian; Gruen, Mathias; Hofmann, Ute; Schaeffeler, Elke; Lopez Posadas, Rocío; Daehn, Ilse; Zenker, Stefanie; Doebroenti, Michael; et al. (Journal of Crohns & Colitis, 2016)
The clinical use of azathioprine and 6-mercaptopurine is limited by their delayed onset of action and potential side effects such as myelosuppression and hepatotoxicity. As these drugs specifically target the Vav1/Rac1 signalling pathway in T lamina propria lymphocytes via their metabolite 6-thio-GTP, we studied expression and optimised suppression of this pathway in inflammatory bowel diseases [IBD].Rac1 and Vav1 expressions were analysed in mucosal immune cells in IBD patients. Targeted molecular modelling of the 6-thio-GTP molecule was performed to optimise Rac1 blockade; 44 modified designer thiopurine-analogues were tested for apoptosis induction, potential toxicity, and immunosuppression. Activation of the Vav1/Rac1 pathway in lymphocytes was studied in IBD patients and in lamina propria immune cells in the presence or absence of thiopurine-analogues.Several thiopurine-analogues induced significantly higher T cell apoptosis than 6-mercaptopurine. We identified a compound, denoted B-0N, based on its capacity to mediate earlier and stronger induction of T cell apoptosis than 6-mercaptopurine. B-0N-treatment resulted in accelerated inhibition of Rac1 activity in primary peripheral blood T cells as well as in intestinal lamina propria immune cells. Compared with 6-thio-GTP and 6-mercaptopurine, B-0N-treatment was associated with decreased myelo- and hepatotoxicity.The Vav1/Rac1 pathway is activated in mucosal immune cells in IBD. The designer thiopurine-analogue B-0N induces immunosuppression more potently than 6-mercaptopurine.
EVALuna2:2190

Detection by flow cytometry of anti-neutrophil cytoplasmic antibodies in a novel approach based on neutrophil extracellular traps - Roitsch, Stefan; Goesswein, Stefanie; Neurath, Markus; Leppkes, Moritz (Autoimmunity, 2018)
Background:Anti-neutrophil-cytoplasmic antibodies (ANCA) are auto-antibodies directed against components of neutrophil granulocytes and may be found in various inflammatory conditions, like small-vessel vasculitis or ulcerative colitis (UC). Routine ANCA screening is performed on ethanol-fixed neutrophils using indirect immunofluorescence technique. Yet, how neutrophil granule proteins become available to immunologic presentation is a matter of debate. In recent years, various studies have shown that neutrophils are able to extrude their chromatin decorated with granular proteins as neutrophil extracelullar traps (NETs).Aim: We hypothesized that (I) ANCA immunoreactivity may be found on NETs and (II) NETs may serve as a useful tool in a novel approach for ANCA detection.Methods: Sera from patients suffering from either ANCA-associated vasculitis (n=10), UC (n=30) or sera from patients without diagnosed ANCA-associated diseases (n=20), respectively, were subjected to indirect immunofluorescence and a newly developed method to detect ANCA by flow cytometry employing microbead technology.Results: ANCA-related immunofluorescence was readily detectable on ethanol-fixed NETs, establishing NETs as a structure carrying ANCA target antigens. Moreover, we observed that neutrophils form NETs in response to microbeads and stick to the surface of these beads. Using these NET-coated microbeads in flow cytometry, we were capable of reliably detecting p-ANCA, c-ANCA, and a-ANCA in tested patient sera. UC-related complex DNase-1-sensitive ANCA (NET-ANCA) antigens were also detected on NET-coated microbeads.Conclusion: NET-coated microbeads may be commercially developed as a novel tool for automated ANCA screening assays using flow cytometry.
EVALuna2:35193

Detection of circulating extracelluar mRNAs by modified small-RNA-sequencing analysis - Akat, Kemal M.; Lee, Youngmin A.; Hurley, Arlene; Morozov, Pavel; Max, Klaas E. A.; Brown, Miguel; Bogardus, Kimberly; Sopeyin, Anuoluwapo; Hildner, Kai; Diacovo, Thomas G.; Neurath, Markus; Borggrefe, Martin; et al. (JCI Insight, 2019)
Extracellular mRNAs (ex-mRNAs) potentially supersede extracellular miRNAs (ex-miRNAs) and other RNA classes as biomarkers. We performed conventional small-RNA-sequencing (sRNA-seq) and sRNA-seq with T4 polynucleotide kinase (PNK) end treatment of total extracellular RNAs (exRNAs) isolated from serum and platelet-poor EDTA, acid citrate dextrose (ACD), and heparin plasma to study the effect on ex-mRNA capture. Compared with conventional sRNA-seq, PNK treatment increased the detection of informative ex-mRNAs reads up to 50-fold. The exRNA pool was dominated by RNA originating from hematopoietic cells and platelets, with additional contribution from the liver. About 60% of the 15- to 42-nt reads originated from the coding sequences, in a pattern reminiscent of ribosome profiling. Blood sample type had a considerable influence on the exRNA profile. On average approximately 350-1100 distinct ex-mRNA transcripts were detected depending on plasma type. In serum, additional transcripts from neutrophils and hematopoietic cells increased this number to near 2300. EDTA and ACD plasma showed a destabilizing effect on ex-mRNA and noncoding RNA ribonucleoprotein complexes compared with other plasma types. In a proof-of-concept study, we investigated differences between the exRNA profiles of patients with acute coronary syndrome and healthy controls. The improved tissue resolution of ex-mRNAs after PNK treatment enabled us to detect a neutrophil signature in ACS that escaped detection by ex-miRNA analysis.
CRIS-Team WoS Importer:2019-05-17

Detection of collagens by multispectral optoacoustic tomography as an imaging biomarker for Duchenne muscular dystrophy - Regensburger, Adrian; Fonteyne, Lina M.; Jüngert, Jörg; Wagner, Anna; Gerhalter, Teresa; Nagel, Armin Michael; Heiß, Rafael; Flenkenthaler, Florian; Qurashi, Matthias; Neurath, Markus; Klymiuk, Nikolai; Kemter, Elisabeth; et al. (Nature Medicine, 2019)
Biomarkers for monitoring of disease progression and response to therapy are lacking for muscle diseases such as Duchenne muscular dystrophy. Noninvasive in vivo molecular imaging with multispectral optoacoustic tomography (MSOT) uses pulsed laser light to induce acoustic pressure waves, enabling the visualization of endogenous chromophores. Here we describe an application of MSOT, in which illumination in the near- and extended near-infrared ranges from 680–1,100 nm enables the visualization and quantification of collagen content. We first demonstrated the feasibility of this approach to noninvasive quantification of tissue fibrosis in longitudinal studies in a large-animal Duchenne muscular dystrophy model in pigs, and then applied this approach to pediatric patients. MSOT-derived collagen content measurements in skeletal muscle were highly correlated to the functional status of the patients and provided additional information on molecular features as compared to magnetic resonance imaging. This study highlights the potential of MSOT imaging as a noninvasive, age-independent biomarker for the implementation and monitoring of newly developed therapies in muscular diseases.
CRIS-Team Scopus Importer:2019-12-17

Detection of Crohn's typical Anti-Yeast Glycan Antibodies by a novel Assay based on Flow Cytometry - Roth, Dominik; Lindemann, Aylin; Goesswein, S.; Neurath, Markus; Armbruster, F. P.; Leppkes, Moritz (Mycoses, 2021)
CRIS-Team WoS Importer:2021-10-08

Development and Validation of a Confocal Laser Endomicroscopy-Based Score for In Vivo Assessment of Mucosal Healing in Ulcerative Colitis Patients - Hundorfean, Gheorghe; Chiriac, Mircea T.; Mihai, Sidonia; Hartmann, Arndt; Mudter, Jonas; Neurath, Markus (Inflammatory Bowel Diseases, 2017)
Background: Endoscopic monitoring is fundamental for evaluating the therapeutic response in IBD, but a validated endomicroscopic mucosal healing (MH) score is not available to date. However, confocal laser endomicroscopy (CLE) might define MH more precisely than conventional endoscopy. The major aim was to establish and validate an MH score for ulcerative colitis (UC), based on CLE. Methods: In an initial pilot study (n = 10), various CLE changes were analyzed for identification of reproducible criteria for establishing a CLE score. Four reproducible CLE criteria were implemented in a following validation study. Subsequently, active UC patients (n = 23, Mayo score ≥6) were prospectively included and underwent colonoscopy with CLE before and after 3 anti-TNF applications. Patients were clinically followed over a period of 3 years. The endomicroscopic MH score (eMHs; range, 0-4) was compared with histopathology and endoscopy scores from the same colonic location. Results: The eMHs showed high sensitivity, specificity, and accuracy values (100% with 95% confidence interval [CI] of 15.81%-100%; 93.75% with 95% CI of 69.77%-99.84%, and 94.44%, respectively). The eMHs showed a good correlation with the histological Gupta score (rs = 0.82, P < 0.0001) and the endoscopic Mayo subscore (rs = 0.81%, P < 0.0001). Sixty percent of therapy responders presented an eMHs <1, which translated into long-lasting clinical remission and reduced hospitalization, steroid, and surgery need. Conclusions: CLE can accurately assess MH based on the newly developed and statistically validated eMHs in UC, and it is superior in predicting the long-lasting clinical outcome based on both descriptive and functional barrier imaging (NCT01417728).
EVALuna2:33794

Diagnostic accuracy and interobserver variability of Dynamic Vascular Pattern (DVP) in primary liver malignancies - A simple semiquantitative tool for the analysis of contrast enhancement patterns - Schellhaas, B.; Waldner, Maximilian; Goertza, R. S.; Vitali, Francesco; Kielisch, Ch.; Pfeifer, Lukas; Strobel, Deike; Janka, Rolf Matthias; Neurath, Markus; Wildner, Dane (Clinical Hemorheology and Microcirculation, 2017)
Contrast-enhanced ultrasound (CEUS) is a valuable tool in the diagnostic approach of focal liver lesions, but occasionally subjective and observer-dependent. Semiquantitative evaluation of dynamic CEUS (DCEUS) with standardised software programmes such as Dynamic Vascular Pattern (DVP) could help to improve diagnostic accuracy and objectivity in liver tumour assessment.The present study aimed at evaluation of diagnostic accuracy of DVP in a clinical setting.DVP images of 52 focal liver lesions [30 hepatocellular carcinomas (HCCs), 15 intrahepatic cholangiocellular carcinomas (ICCs), 7 focal nodular hyperplasias (FNHs)] were analysed by four blinded observers with different levels of CEUS-experience. Diagnostic accuracies for the assessment of dignity and entity were evaluated.Mean sensitivity, specificity, positive and negative predictive value for detection of malignancy with DVP were 48.4% /67.8% /92.7% and 29.3%, respectively. Total diagnostic accuracies for dignity/entity were 63.9% /38.5% (HCC: 58.3% /25.8%; ICC: 73.3% /50%; FNH: 67.9% /67.9%). Interreader-agreement was moderate (?= 0.42-0.58). Differential diagnosis between ICC and HCC was most challenging.Although developed to improve diagnostic accuracy and objectivity in the assessment of focal liver lesions, DVP alone seems insufficient for differential diagnosis of HCC, ICC and FNH and cannot replace the skills of an experienced observer.
EVALuna2:14711

Diagnostic accuracy of contrast-enhanced ultrasound for the differential diagnosis of hepatocellular carcinoma: ESCULAP versus CEUS-LI-RADS - Schellhaas, Barbara; Görtz, Rüdiger; Pfeifer, Lukas; Kielisch, Christian; Neurath, Markus; Strobel, Deike (European Journal of Gastroenterology & Hepatology, 2017)
OBJECTIVE: A comparison is made of two contrast-enhanced ultrasound (CEUS) algorithms for the diagnosis of hepatocellular carcinoma (HCC) in high-risk patients: Erlanger Synopsis of Contrast-enhanced Ultrasound for Liver lesion Assessment in Patients at Risk (ESCULAP) and American College of Radiology Contrast-Enhanced Ultrasound-Liver Imaging Reporting and Data System (ACR-CEUS-LI-RADSv.2016). PATIENTS AND METHODS: Focal liver lesions in 100 high-risk patients were assessed using both CEUS algorithms (ESCULAP and CEUS-LI-RADSv.2016) for a direct comparison. Lesions were categorized according to size and contrast enhancement in the arterial, portal venous and late phases.For the definite diagnosis of HCC, categories ESCULAP-4, ESCULAP-Tr and ESCULAP-V and CEUS-LI-RADS-LR-5, LR-Tr and LR-5-V were compared. In addition, CEUS-LI-RADS-category LR-M (definitely/probably malignant, but not specific for HCC) and ESCULAP-category C [intrahepatic cholangiocellular carcinoma (ICC)] were compared.Histology, CE-computed tomography and CE-MRI served as reference standards. RESULTS: The reference standard among 100 lesions included 87 HCCs, six ICCs and seven non-HCC-non-ICC-lesions. For the diagnosis of HCC, the diagnostic accuracy of CEUS was significantly higher with ESCULAP versus CEUS-LI-RADS (94.3%/72.4%; p<0.01). Sensitivity, specificity and positive predictive value (PPV) and negative predictive value for ESCULAP/CEUS-LI-RADS were 94.3%/72.4%; 61.5%/69.2%; 94.3%/94%; and 61.5%/27.3%, respectively.The diagnostic accuracy for ICC (LR-M/ESCULAP-C) was identical with both algorithms (50%), with higher PPV for ESCULAP-C versus LR-M (75 vs. 50%). CONCLUSION: CEUS-based algorithms contribute toward standardized assessment and reporting of HCC-suspect lesions in high-risk patients. ESCULAP shows significantly higher diagnostic accuracy, sensitivity and negative predictive value with no loss of specificity compared with CEUS-LI-RADS. Both algorithms have an excellent PPV. Arterial hyperenhancement is the key feature for the diagnosis of HCC with CEUS. Washout should not be a necessary prerequisite for the diagnosis of definite HCC. CEUS-LI-RADS in its current version is inferior to ESCULAP for the noninvasive diagnosis of HCC. There are two ways to improve CEUS-LI-RADS: firstly, combination of the categories LR-4 and LR-5 for the diagnosis of definite HCC, and secondly, use of subtotal infiltration of a liver lobe as an additional feature.
EVALuna2:33804

Diagnostic Endoscopic Ultrasound in Pancreatology: Focus on Normal Variants and Pancreatic Masses - Vitali, Francesco; Zundler, Sebastian; Jesper, Daniel; Wildner, Dane; Strobel, Deike; Frulloni, Luca; Neurath, Markus (Visceral Medicine, 2023)
Background: Endoscopic ultrasound (EUS) is a main tool in gastroenterology for both diagnosis and exclusion of pancreatic pathology. It allows minimally invasive assessment of various diseases or anatomic variations affecting the pancreas also with the help of new Doppler technologies, elastography, contrast-enhanced imaging including post hoc image processing with quantification analyses, three-dimensional reconstruction, and artificial intelligence. EUS also allows interventional direct access to the pancreatic parenchyma and the retroperitoneal space, to the pancreatic duct, pancreatic masses, cysts, and vascular structures. Summary: This review aimed to summarize new developments of EUS in the field of pancreatology. We highlight the role of EUS in evaluating pancreatic pathology by describing normal anatomic variants like pancreas divisum, pancreatic lipomatosis, pancreatic fibrosis in the elderly and characterizing pancreatic masses, both in the context of chronic pancreatitis and within healthy pancreatic parenchyma. EUS is considered the optimal imaging modality for pancreatic masses of uncertain dignity and allows both cytological diagnosis and histology, which is essential not only for neoplastic conditions but also for tailoring therapy for benign inflammatory conditions. Key Messages: EUS plays an indispensable role in pancreatology and the development of new diagnostic and interventional approaches to the retroperitoneal space and the pancreas exponentially increased over the last years. The development of computer-aided diagnosis and artificial intelligence algorithms hold the potential to overcome the obstacles associated with interobserver variability and will most likely support decision-making in the management of pancreatic disease.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Contrast-enhanced endoscopic ultrasound; Elastometry; Endoscopic ultrasound; Pancreatic cancer; Pancreatitis

Differences in the bacterial pattern of histamine intolerant patients - Schink, Monic; Tietz, Esther; Dieterich, Walburga; Pinzer, Theresa C.; Wirtz, Stefan; Neurath, Markus; Zopf, Yurdagül (2018)
EVALuna2:35188

Differences in the Bacterial Pattern of Patients with Histamine Intolerance Veränderte intestinale bakterielle Zusammensetzung bei Patienten mit Histaminintoleranz - Schink, Monic; Konturek, Peter C.; Tietz, Esther; Dieterich, Walburga; Neurath, Markus; Zopf, Yurdagül (Aktuelle Ernährungsmedizin, 2019)
Background Histamine intolerance (HIT) is a controversially discussed disorder. An impaired degradation of oral histamine intake due to diamine oxidase (DAO) deficiency is suggested as main cause, but other factors, including an altered gut flora, may also contribute to elevated histamine levels. We aimed to determine differences in the intestinal bacterial pattern of HIT-patients in comparison to healthy persons (HC). Material and methods All participants had a blood testing for total IgE, food-specific IgEs, TNF-α, plasma histamine and serum DAO activities. Stool samples were collected for analysis of stool histamine and zonulin levels. The bacterial composition of the stool samples was analysed by 16s rRNA sequencing using Illumina platform. Results A total of 18 participants (30.2±12.5yrs, 94,4% female) were included in the study, and categorized into HIT-patients (n=8, 28.9±11.2 yrs, 100% female) and healthy controls (n=10, 31.3±13.9yrs, 90% female). No significant differences in stool histamine levels were observed between groups, but HIT-patients showed tendentially increased levels of fecal zonulin. Microbiome analysis revealed a reduced bacterial diversity (p=0.05) and a higher abundance of Proteobacteria in the HIT-group. Additionally, HIT-patients showed a significantly decreased abundance of the butyrate-producing genera Faecalibacterium (p=0.045) and Butyricimonas (p=0.003) as well as lower proportions of Sutterella (p=0.043) and Hespellia (p=0.043). No increased numbers of known histamine-producing bacteria were detected in the study groups. Conclusion Our study results suggest an alteration of the microbial composition in HIT-patients. The higher abundance of Proteobacteria and lower abundance of butyrate-producing bacteria, as well as elevated stool zonulin levels indicate a dysbiosis and impaired intestinal barrier. However, an elevated histamine exposure due to gut bacteria may not be responsible for HIT pathogenesis.
CRIS-Team Scopus Importer:2019-11-05
Keywords: dysbiosis; histamine intolerance; intestinal barrier; microbiome

Differential Contribution of TRPA1, TRPV4 and TRPM8 to Colonic Nociception in Mice - Müller-Tribbensee, Sonja; Karna, Manoj; Khalil, Mohammad; Neurath, Markus; Reeh, Peter; Engel, Matthias (PLoS ONE, 2015)
Various transient receptor potential (TRP) channels in sensory neurons contribute to the transduction of mechanical stimuli in the colon. Recently, even the cold-sensing menthol receptor TRPM(melastatin)8 was suggested to be involved in murine colonic mechano-nociception.To analyze the roles of TRPM8, TRPA1 and TRPV4 in distension-induced colonic nociception and pain, TRP-deficient mice and selective pharmacological blockers in wild-type mice (WT) were used. Visceromotor responses (VMR) to colorectal distension (CRD) in vivo were recorded and distension/pressure-induced CGRP release from the isolated murine colon ex vivo was measured by EIA.Distension-induced colonic CGRP release was markedly reduced in TRPA1-/- and TRPV4-/- mice at 90/150 mmHg compared to WT. In TRPM8-deficient mice the reduction was only distinct at 150 mmHg. Exposure to selective pharmacological antagonists (HC030031, 100 ?M; RN1734, 10 ?M; AMTB, 10 ?M) showed corresponding effects. The unselective TRP blocker ruthenium red (RR, 10 ?M) was as efficient in inhibiting distension-induced CGRP release as the unselective antagonists of mechanogated DEG/ENaC (amiloride, 100 ?M) and stretch-activated channels (gadolinium, 50 ?M). VMR to CRD revealed prominent deficits over the whole pressure range (up to 90 mmHg) in TRPA1-/- and TRPV4-/- but not TRPM8-/- mice; the drug effects of the TRP antagonists were again highly consistent with the results from mice lacking the respective TRP receptor gene.TRPA1 and TRPV4 mediate colonic distension pain and CGRP release and appear to govern a wide and congruent dynamic range of distensions. The role of TRPM8 seems to be confined to signaling extreme noxious distension, at least in the healthy colon.
EVALuna2:2004

Differential diagnosis in inflammatory bowel disease colitis: state of the art and future perspectives - Tontini, Gian Eugenio; Vecchi, Maurizio; Pastorelli, Luca; Neurath, Markus; Neumann, Helmut (World Journal of Gastroenterology, 2015)
Distinction between Crohn's disease of the colon-rectum and ulcerative colitis or inflammatory bowel disease (IBD) type unclassified can be of pivotal importance for a tailored clinical management, as each entity often involves specific therapeutic strategies and prognosis. Nonetheless, no gold standard is available and the uncertainty of diagnosis may frequently lead to misclassification or repeated examinations. Hence, we have performed a literature search to address the problem of differential diagnosis in IBD colitis, revised current and emerging diagnostic tools and refined disease classification strategies. Nowadays, the differential diagnosis is an untangled issue, and the proper diagnosis cannot be reached in up to 10% of patients presenting with IBD colitis. This topic is receiving emerging attention, as medical therapies, surgical approaches and leading prognostic outcomes require more and more disease-specific strategies in IBD patients. The optimization of standard diagnostic approaches based on clinical features, biomarkers, radiology, endoscopy and histopathology appears to provide only marginal benefits. Conversely, emerging diagnostic techniques in the field of gastrointestinal endoscopy, molecular pathology, genetics, epigenetics, metabolomics and proteomics have already shown promising results. Novel advanced endoscopic imaging techniques and biomarkers can shed new light for the differential diagnosis of IBD, better reflecting diverse disease behaviors based on specific pathogenic pathways.
EVALuna2:2010

Differential effects of ?4?7 and GPR15 on homing of effector and regulatory T cells from patients with UC to the inflamed gut in vivo - Fischer, Anika; Zundler, Sebastian; Atreya, Raja; Rath, Timo; Voskens, Caroline; Hirschmann, Simon; Lopez Posadas, Rocío; Watson, Alastair; Becker, Christoph; Schuler, Gerold; Neufert, Clemens; Atreya, Imke; et al. (Gut, 2016)
Gut homing of lymphocytes via adhesion molecules has recently emerged as new target for therapy in IBDs. We aimed to analyse the in vivo homing of effector (Teff) and regulatory (Treg) T cells to the inflamed gut via ?4?7 and G protein receptor GPR15.We assessed the expression of homing receptors on T cells in peripheral blood and inflamed mucosa. We studied the migration pattern and homing of Teff and Treg cells to the inflamed gut using intravital confocal microscopy and FACS in a humanised mouse model in dextran sodium sulfate-treated NSG (NOD.Cg-Prkdcscid-Il2rgtm1Wjl/SzJ) mice.Expression of GPR15 and ?4?7 was significantly increased on Treg rather than Teff cells in peripheral blood of patients with UC as compared with Crohn's disease and controls. In vivo analysis in a humanised mouse model showed augmented gut homing of UC Treg cells as compared with controls. Moreover, suppression of UC (but not control) Teff and Treg cell homing was noted upon treatment with the ?4?7 antibody vedolizumab. In contrast, siRNA blockade of GPR15 had only effects on homing of Teff cells but did not affect Treg homing in UC. Clinical vedolizumab treatment was associated with marked expansion of UC Treg cells in peripheral blood.?4?7 rather than GPR15 is crucial for increased colonic homing of UC Treg cells in vivo, while both receptors control UC Teff cell homing. Vedolizumab treatment impairs homing of UC Treg cells leading to their accumulation in peripheral blood with subsequent suppression of systemic Teff cell expansion.
EVALuna2:2173

Differential Effects of Ontamalimab Versus Vedolizumab on Immune Cell Trafficking in Intestinal Inflammation and Inflammatory Bowel Disease - Schulze, Lisa; Becker, Emily; Dedden, Mark; Liu, Lijuan; Van Passen, Chiara; Mohamed Abdou, Mariam; Müller, Tanja; Wiendl, Maximilian; Ullrich, Karen; Atreya, Imke; Leppkes, Moritz; Ekici, Arif Bülent; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: The anti-MAdCAM-1 antibody ontamalimab demonstrated efficacy in a phase II trial in ulcerative colitis and results of early terminated phase III trials are pending, but its precise mechanisms of action are still unclear. Thus, we explored the mechanisms of action of ontamalimab and compared it to the anti-α4β7 antibody vedolizumab. Methods: We studied MAdCAM-1 expression with RNA sequencing and immunohistochemistry. The mechanisms of action of ontamalimab were assessed with fluorescence microscopy, dynamic adhesion and rolling assays. We performed in vivo cell trafficking studies in mice and compared ontamalimab and vedolizumab surrogate [-s] antibodies in experimental models of colitis and wound healing. We analysed immune cell infiltration under anti-MAdCAM-1 and anti-α4β7 treatment by single-cell transcriptomics and studied compensatory trafficking pathways. Results: MAdCAM-1 expression was increased in active inflammatory bowel disease. Binding of ontamalimab to MAdCAM-1 induced the internalization of the complex. Functionally, ontamalimab blocked T cell adhesion similar to vedolizumab, but also inhibited L-selectin-dependent rolling of innate and adaptive immune cells. Despite conserved mechanisms in mice, the impact of ontamalimab-s and vedolizumab-s on experimental colitis and wound healing was similar. Single-cell RNA sequencing demonstrated enrichment of ontamalimab-s-treated lamina propria cells in specific clusters, and in vitro experiments indicated that redundant adhesion pathways are active in these cells. Conclusions: Ontamalimab has unique and broader mechanisms of action compared to vedolizumab. However, this seems to be compensated for by redundant cell trafficking circuits and leads to similar preclinical efficacy of anti-α4β7 and anti-MAdCAM-1 treatment. These results will be important for the interpretation of pending phase III data.
CRIS-Team Scopus Importer:2023-12-15

Differential Effects of Very-Low-Volume Exercise Modalities on Telomere Length, Inflammation, and Cardiometabolic Health in Obese Metabolic Syndrome Patients: A Subanalysis from Two Randomized Controlled Trials - Reljic, Dejan; Koller, Adriana; Herrmann, Hans J.; Ekici, Arif Bülent; Neurath, Markus; Zopf, Yurdagül (Antioxidants, 2023)
Oxidative stress (OS) and inflammation are features of metabolic syndrome (MetS) that can contribute to the shortening of telomere length (TL), a marker of cellular ageing. Research indicates that exercise can positively influence MetS-associated conditions and TL. However, the effects of low-volume exercise types on TL are still unknown. We investigated the impact of very-low-volume high-intensity interval training (LV-HIIT), one-set resistance training (1-RT), and whole-body electromyostimulation (WB-EMS) on TL, inflammation, and cardiometabolic indices in 167 MetS patients. Data were derived from two randomized controlled trials where patients were allocated to an exercise group (2 sessions/week, for 12 weeks) or a control group. All groups received standard-care nutritional weight loss counselling. TL was determined as the T/S ratio (telomere to single-copy gene amount). All groups significantly reduced body weight (p < 0.05), but the T/S-ratio (p < 0.001) only increased with LV-HIIT. OS-related inflammatory markers (C-reactive protein, interleukin-6, and lipopolysaccharide-binding protein) only decreased (p < 0.05) following LV-HIIT. The MetS severity z-score improved with LV-HIIT (p < 0.001) and 1-RT (p = 0.014) but not with WB-EMS. In conclusion, very-low-volume exercise modalities have differential effects on telomeres, inflammation, and cardiometabolic health. Only LV-HIIT but not strength-based low-volume exercise increased TL in MetS patients, presumably due to superior effects on OS-related inflammatory markers.
CRIS-Team Scopus Importer:2023-11-10
Keywords: anti-aging; cellular age; electromyostimulation; high-intensity interval training; inflammatory markers; metabolic diseases; oxidative stress; resistance training; telomeres

Differentiation of malignant liver tumors by software-based perfusion quantification with dynamic contrast-enhanced ultrasound (DCEUS) - Wildner, Dane; Schellhaas, Barbara; Strack, Daniel; Görtz, Rüdiger; Pfeifer, Lukas; Fießler, Cornelia; Neurath, Markus; Strobel, Deike (Clinical Hemorheology and Microcirculation, 2019)
BACKGROUND: Enhancement patterns on contrast-enhanced ultrasound (CEUS) help to distinguish different liver tumors.
CRIS-Team WoS Importer:2019-04-16

Different levels of healing in inflammatory bowel diseases: mucosal, histological, transmural, barrier and complete healing - Neurath, Markus; Vieth, Michael (Gut, 2023)
Mucosal healing on endoscopy has emerged as a key prognostic parameter in the management of patients with IBD (Crohn's disease, ulcerative colitis/UC) and can predict sustained clinical remission and resection-free survival. The structural basis for this type of mucosal healing is a progressive resolution of intestinal inflammation with associated healing of ulcers and improved epithelial barrier function. However, in some cases with mucosal healing on endoscopy, evidence of histological activity in mucosal biopsies has been observed. Subsequently, in UC, a second, deeper type of mucosal healing, denoted histological healing, was defined which requires the absence of active inflammation in mucosal biopsies. Both levels of mucosal healing should be considered as initial events in the resolution of gut inflammation in IBD rather than as indicators of complete transmural healing. In this review, the effects of anti-inflammatory, biological or immunosuppressive agents as well as small molecules on mucosal healing in clinical studies are highlighted. In addition, we focus on the implications of mucosal healing for clinical management of patients with IBD. Moreover, emerging techniques for the analysis of mucosal healing as well as potentially deeper levels of mucosal healing such as transmural healing and functional barrier healing of the mucosa are discussed. Although none of these new levels of healing indicate a definitive cure of the diseases, they make an important contribution to the assessment of patients' prognosis. The ultimate level of healing in IBD would be a resolution of all aspects of intestinal and extraintestinal inflammation (complete healing).
CRIS-Team Scopus Importer:2023-09-22
Keywords: Crohn's disease; endoscopy; mucosal barrier; ulcerative colitis

DIFFERENT NUTRIENT INTAKE AND PREVALENCE OF GASTROINTESTINAL COMORBIDITIES IN WOMEN WITH ENDOMETRIOSIS - Schink, Monic; Konturek, P. C.; Herbert, S. L.; Renner, S. P.; Burghaus, Stefanie; Blum, Simon; Fasching, Peter; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2019)
Even though endometriosis presents one of the most common gynaecological diseases, the pathogenesis is insufficiently studied. Besides immunologic, inflammatory or oxidative processes, recent studies also suggest an influence of nutrition on disease onset and progression. Because data about the actual nutrient intake of endometriosis patients are scarce, we aimed to examine the actual nutrient intake and potential influencing factors in these women. A total of 156 women with endometriosis (EM) and 52 age-matched controls were included in this retrospective case-control study. All women filled in a validated food frequency questionnaire to acquire the nutrient intake of the past 12 months and a disease-related questionnaire for the determination of disease status, clinical symptoms and comorbidities. Patients with endometriosis suffered significantly more from diet-related comorbidities like food intolerances (25.6% versus 7.7%; P = 0.009) and allergies (57% versus 31%; P < 0.001) compared to controls. Also gastrointestinal symptoms, including constipation, flatulence, pyrosis, diarrhea or frequent defecation, were higher in the EM group (77% versus 29%; P < 0.001). The nutrient intake of patients with endometriosis differed significantly compared to controls with a significantly lower ingestion of organic acids (P = 0.006), maltose (P = 0.0.16), glycogen (P = 0.035), tetradecenoic acid (P = 0.041), methionine (P = 0.046), lysine (P = 0.048), threonine (P = 0.046) and histidine (P = 0.049). The total intake of animal proteins was significantly lower in the EM group compared to the controls (P = 0.047). EM patients showed a decreased intake of vitamin C (P = 0.031), vitamin B-12 (P = 0.008) and magnesium (P = 0.043) compared to controls. This study confirms a high association of endometriosis and gastrointestinal disorders accompanied by an altered nutrient intake. A dietary intervention by a professional nutritionist may help to reduce disease burden in the affected women.
CRIS-Team WoS Importer:2019-10-18

Digital Chromoendoscopy With i-Scan for In Vivo Prediction of Advanced Colorectal Neoplasia: A Multicenter Study - Albrecht, Heinz; Naegel, Andreas; Tasdelen, Hueseyin; Rath, Timo; Grauer, Martin; Neurath, Markus; Neumann, Helmut; Vieth, Michael (Journal of Clinical Gastroenterology, 2016)
Recent studies have analyzed the potential of advanced endoscopic imaging techniques for differentiating hyperplastic and adenomatous colorectal lesions. Latest endoscopic resection techniques now also allow for treatment of more advanced staged lesions including treatment of early cancerous lesions.To assess the potential of the i-scan technology to differentiate between adenomatous polyps and advanced staged neoplasia.Consecutive patients undergoing colonoscopy at a tertiary referral center were included. After a dedicated training, participating endoscopists underwent a review of 298 unknown images of colonic lesions to assess colorectal lesion histology.Overall accuracy for prediction of advanced staged neoplasia was 92.2% (sensitivity: 94.2%, specificity 90.9%). The positive and negative predictive values were calculated as 87.5% and 95.9%, respectively. The ?-value for differentiating adenomatous polyps and advanced staged neoplasia was 0.8193 (0.7894 to 0.8492). Intraobserver agreement was calculated with a ?-value of 0.9301 (0.8875 to 0.9727).Accurate interpretation of i-scan images for prediction of advanced colorectal neoplasia can successfully be performed even by nonexpert endoscopists with a high overall accuracy and excellent interobserver agreements.
EVALuna2:2189

Discrepant Phenotyping of Monocytes Based on CX3CR1 and CCR2 Using Fluorescent Reporters and Antibodies - Sommer, Katrin; Garibagaoglu, Hilal; Paap, Eva-Maria; Wiendl, Maximilian; Müller, Tanja; Atreya, Imke; Krönke, Gerhard; Neurath, Markus; Zundler, Sebastian (Cells, 2024)
Monocytes, as well as downstream macrophages and dendritic cells, are essential players in the immune system, fulfilling key roles in homeostasis as well as in inflammatory conditions. Conventionally, driven by studies on reporter models, mouse monocytes are categorized into a classical and a non-classical subset based on their inversely correlated surface expression of Ly6C/CCR2 and CX3CR1. Here, we aimed to challenge this concept by antibody staining and reporter mouse models. Therefore, we took advantage of Cx3cr1GFP and Ccr2RFP reporter mice, in which the respective gene was replaced by a fluorescent reporter protein gene. We analyzed the expression of CX3CR1 and CCR2 by flow cytometry using several validated fluorochrome-coupled antibodies and compared them with the reporter gene signal in these reporter mouse strains. Although we were able to validate the specificity of the fluorochrome-coupled flow cytometry antibodies, mouse Ly6Chigh classical and Ly6Clow non-classical monocytes showed no differences in CX3CR1 expression levels in the peripheral blood and spleen when stained with these antibodies. On the contrary, in Cx3cr1GFP reporter mice, we were able to reproduce the inverse correlation of the CX3CR1 reporter gene signal and Ly6C surface expression. Furthermore, differential CCR2 surface expression correlating with the expression of Ly6C was observed by antibody staining, but not in Ccr2RFP reporter mice. In conclusion, our data suggest that phenotyping strategies for mouse monocyte subsets should be carefully selected. In accordance with the literature, the suitability of CX3CR1 antibody staining is limited, whereas for CCR2, caution should be applied when using reporter mice.
CRIS-Team Scopus Importer:2024-05-31
Keywords: C-X3-C motif chemokine receptor 1 (CX3CR1); chemokine (C-C motif) receptor 2 (CCR2); classical monocytes; lymphocyte antigen 6C (Ly6C); non-classical monocytes

Discrimination between Inflammatory and Fibrotic Activity in Crohn's Disease-Associated Ileal-Colonic Anastomotic Strictures by Combined Ga-68-FAPI-46 and F-18-FDG-PET/CT Imaging - Beck, Michael; Kuwert, Torsten; Atzinger, Armin; Gerner, Maximilian; Hartmann, Arndt; Saake, Marc; Uder, Michael; Neurath, Markus; Atreya, Raja (Visceral Medicine, 2024)
Introduction: The development of an intestinal stricture in patients with Crohn s disease represents an important and frequent complication, reflecting the progressive nature of the disease. Depending on the inflammatory and fibrotic composition of the stricture, intensified medical therapy, interventional endoscopy, or surgical intervention is required. However, currently available diagnostic approaches can only assess the level of inflammation, but not the degree of fibrosis, limiting rational therapeutic management of Crohn s disease patients. Recently, prolyl endopeptidase fibroblast activating protein (FAP) has been functionally implicated in fibrotic tissue remodelling, indicating it as a promising target for detection of sites of fibrotic tissue remodelling. Thus, intestinal fibrosis might be visualized using Gallium-68 labelled inhibitors of FAP (FAPI). While F-18-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/CT is a standard diagnostic tool for visualizing inflammatory processes, we combined Ga- 68-FAPI-46-PET/CT and F-18-FDG-PET/CT to differentiate predominantly fibrotic or inflammatory areas in Crohn s disease patients with ileo-colonic strictures. Methods: In our study, we analysed three Crohn s disease patients with anastomotic ileo-colonic strictures who underwent both dynamic Ga-68-FAPI-46-PET/CT and static F-18-FDG-PET/CT imaging to assess the level of visualized fibrotic areas within the stricture and differentiate it from inflammatory ones. PET images were analysed both visually and quantitatively. Furthermore, conventional MR enterography and endoscopy were performed in parallel to correlate observed findings. Two of the included patients underwent surgery and the histological specimen were analysed for the level of inflammation and fibrosis, which results were similarly compared to the findings of the PET imaging procedures. Results: Different uptake patterns of Ga-68- FAPI-46 could be observed in the anastomotic ileo-colonic strictures of the examined Crohn s disease patients, respectively. Immunohistochemical analyses demonstrated that there was a correlation between the level of Ga-68- FAPI-46 uptake and severity of fibrosis, while FDG uptake correlated with the inflammatory activity in the analysed strictures. Discussion: The combination with F-18-FDGPET/CT represents a promising imaging modality to distinguish inflammation from fibrosis and guide subsequent therapy in stricturing Crohn s disease patients, warranting further studies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Crohn s disease; FAPI-PET/CT; Fibrosis; Ga-68-FAPI-46; Strictures

Dose-dependent differential effects of vedolizumab therapy on adhesion of regulatory and effector T cells - Becker, Elisabeth; Wiendl, Maximilian; Schulz-Kuhnt, Anja; Atreya, I.; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (JOURNAL OF CROHNS & COLITIS, 2020)
CRIS-Team WoS Importer:2020-04-10

Double-Balloon Enteroscopy-detected Lipid Islets in the Small Bowel are Strong Predictors of Cardiovascular Disease when associated with Angiectasia and Bleeding - Albrecht, Heinz; Hagel, Wolfgang H.; Hagel, Alexander; Neurath, Markus; Raithel, Martin (Journal of Gastrointestinal and Liver Diseases, 2016)
Double-balloon enteroscopy (DBE) is a sensitive and safe procedure for the detection and treatment of mid-gastrointestinal bleeding (MGIB). It combines the possibility of a panenteroscopy with the immediate chance for intervention. This study evaluates the yield of DBE for the detection and treatment of MGIB in an unselected patient cohort.In a five-year period a total of 119 DBEs were carried out on 62 patients due to MGIB. Inclusion criteria were hematochezia, melena, anemia, positive hemoccult-test and iron deficiency. All pre-existing diseases or comorbidities were evaluated. Two main statistical methodologies were used in data analysis: descriptive statistics to describe the basic features of our data and Fisher's exact test for comparisons of proportions.The diagnostic yield was 69% (pathological findings in 43/62 patients) and the main diagnoses in all DBE-procedures were angiodysplasia (22%, 26/119 DBE), followed by lipid islets (18%, 21/119 DBE). In all patients with lipid islets this diagnosis was significantly connected with cardiovascular diseases. The combination of lipid islets and a relevant bleeding source appeared in 79% of the 19 patients with these findings. Of these, 53% had to be treated due to the bleeding event. The overall therapeutic intervention rate was 58%. Serious complications such as perforation or pancreatitis did not occur.Double-balloon enteroscopy as the gold standard for small bowel investigation in MGIB confirmed its high diagnostic yield in an unselected cohort of patients. A new strong combination of lipid islets with cardiovascular disease was revealed, with a high incidence of angiectasia bleeding. This combination should be evaluated in more detail as a new risk factor for MGIB, and should be regarded in this population when therapeutic anticoagulation is needed.
EVALuna2:2076

Drug Levels in the Maternal Serum, Cord Blood and Breast Milk of a Ustekinumab-Treated Patient with Crohn's Disease - Klenske, Entcho; Osaba, Lourdes; Nagore, Daniel; Rath, Timo; Neurath, Markus; Atreya, Raja (Journal of Crohns & Colitis, 2019)
Ustekinumab [UST] therapy during pregnancy has not yet been extensively evaluated in patients with Crohn's disease. Here, we present the case of a 24-year-old woman with therapy-refractory Crohn's disease, who was treated with UST until Week 30 of pregnancy and successfully delivered a healthy baby boy, who had normal development in the follow-up period of one year. The cord blood UST level was markedly higher than the measured maternal serum drug level. The trough level in the breast milk after re-initiating postpartum UST therapy was initially in the same range as the corresponding serum trough level, and then decreased during maintenance therapy. This is one of the first reports describing the drug levels in the breast milk after re-initiating UST treatment in a Crohn's disease patient.
CRIS-Team WoS Importer:2019-03-06

Drug rediscovery in gastroenterology: From off-label to on-label use of thioguanine in inflammatory bowel disease - De Boer, Nanne K.H.; Simsek, Melek; Meijer, Berrie; Neurath, Markus; Van Bodegraven, Ad; Mulder, Chris J.J. (Gut, 2023)
Drug rediscovery refers to the principle of using € old' drugs outside the indications mentioned in the summary of product characteristics. In the past decades, several drugs were rediscovered in a wide variety of medical fields. One of the most recent examples is the unconditional registration of thioguanine (TG), a thiopurine derivative, in patients with inflammatory bowel disease in the Netherlands. In this paper, we aim to visualise potential hurdles that hamper drug rediscovery in general, emphasise the global need for optimal use and development of potentially useful drugs, and provide an overview of the registration process for TG in the Netherlands. With this summary, we aim to guide drug rediscovery trajectories in the near future.
CRIS-Team Scopus Importer:2023-07-21
Keywords: azathioprine; crohn's disease; drug development; drug metabolism; inflammatory bowel disease

Drug Therapy in Gastroenterology: Molecular Basis of IBD - Neurath, Markus (Drug Research, 2021)
CRIS-Team WoS Importer:2021-12-03

Dynamic Adhesion Assay for the Functional Analysis of Anti-adhesion Therapies in Inflammatory Bowel Disease - Becker, Elisabeth; Schramm, Simon; Binder, Marie-Theres; Allner, Clarissa; Wiendl, Maximilian; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Journal of Visualized Experiments, 2018)
Gut homing of immune cells is important for the pathogenesis of inflammatory bowel diseases (IBD). Integrin-dependent cell adhesion to addressins is a crucial step in this process and therapeutic strategies interfering with adhesion have been successfully established. The anti-α4β7 integrin antibody, vedolizumab, is used for the clinical treatment of Crohn's disease (CD) and ulcerative colitis (UC) and further compounds are likely to follow. The details of the adhesion procedure and the action mechanisms of anti-integrin antibodies are still unclear in many regards due to the limited available techniques for the functional research in this field. Here, we present a dynamic adhesion assay for the functional analysis of human cell adhesion under flow conditions and the impact of anti-integrin therapies in the context of IBD. It is based on the perfusion of primary human cells through addressin-coated ultrathin glass capillaries with real-time microscopic analysis. The assay offers a variety of opportunities for refinements and modifications and holds potentials for mechanistic discoveries and translational applications.
EVALuna2:207768

Dynamic Contrast-Enhanced Ultrasound (DCE-US) for the Characterization of Hepatocellular Carcinoma and Cholangiocellular Carcinoma - Wildner, D.; Pfeifer, Lukas; Görtz, Rüdiger; Bernatik, T.; Sturm, J.; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2014)
Purpose: In a prospective study, we compared the different perfusion kinetics of HCC and ICC using dynamic contrast-enhanced ultrasound (DCE-US). Materials and Methods: Patients with proven HCC and ICC were included. Three-minute video clips of CEUS examinations (CPS - low MI mode) after a bolus injection of 1.2 ml SonoVue(®) were recorded and analyzed with quantification software (VueBox(®)). Parameters for the arterial contrast enhancement [rise time (RT), time-to-peak (TTP)] towards portal venous contrast enhancement [mean transit time (local) (mTTl) and fall time (FT)] were quantified. Furthermore, contrast wash-out after peak enhancement (PE) (40 s, 80 s, 100 s and 120 s after PE) was compared between HCC and ICC. Results: 43 patients with proven HCC (n = 23 HCC; cirrhosis n = 16) and ICC (n = 20 ICC; Cirrhosis n = 6) were examined. No statistical difference of the arterial DCEUS parameters was found between HCC and ICC. Contrast enhancement of the portal venous and late phases showed significantly lower values in the ICC group indicating early wash-out of the contrast agent: mTTl (p = 0.0209): HCC 118.4 s (SD± 88.4); ICC 64.8 s (SD± 49.7). FT (p = 0.0433): HCC 42.5 s (SD± 27.7); ICC 27.7 s (SD± 16.2). The percental loss of intensity at a definite time point after PE was significantly higher in ICC than in HCC lesions. Conclusion: DCE-US is able to detect and quantify differences in perfusion kinetics between HCC and ICC. Whereas arterial contrast enhancement patterns may overlap between HCC and ICC, a timed characterization of wash-out kinetics may offer an additional tool to characterize HCC and ICC. The presence of a rapid loss of signal intensity in the early portal venous phase is significantly higher in ICC than in HCC lesions.
EVALuna2:1876

Dynamic imaging of iel-iec co-cultures allows for quantification of cd103-dependent t cell migration - Enderle, Karin; Dinkel, Martin; Spath, Eva-Maria; Schmid, Benjamin; Zundler, Sebastian; Tripal, Philipp; Neurath, Markus; Hildner, Kai; Neufert, Clemens (International Journal of Molecular Sciences, 2021)
Intraepithelial lymphocytes (IEL) are widely distributed within the small intestinal epithelial cell (IEC) layer and represent one of the largest T cell pools of the body. While implicated in the pathogenesis of intestinal inflammation, detailed insight especially into the cellular cross-talk between IELs and IECs is largely missing in part due to lacking methodologies to monitor this interaction. To overcome this shortcoming, we employed and validated a murine IEL-IEC (organoids) ex vivo co-culture model system. Using livecell imaging we established a protocol to visualize and quantify the spatio-temporal migratory behavior of IELs within organoids over time. Applying this methodology, we found that IELs lacking CD103 (i.e., integrin alpha E, ITGAE) surface expression usually functioning as a retention receptor for IELs through binding to E-cadherin (CD324) expressing IECs displayed aberrant mobility and migration patterns. Specifically, CD103 deficiency affected the ability of IELs to migrate and reduced their speed during crawling within organoids. In summary, we report a new technology to monitor and quantitatively assess especially migratory characteristics of IELs communicating with IEC ex vivo. This approach is hence readily applicable to study the effects of targeted therapeutic interventions on IEL-IEC cross-talk.
CRIS-Team Scopus Importer:2021-05-21
Keywords: CD103; Intestinal organoids; Intraepithelial lymphocytes; Life cell imaging; Lympho-cyte migration

Dynamics of Fukuoka Criteria and Patient Management in Pancreatic Intraductal Papillary Mucinous Neoplasms (IPMNs) During Follow-Up - Schellhaas, Barbara; Vitali, Francesco; Wildner, Dane; Görtz, Rüdiger; Pfeifer, Lukas; Konturek, Peter C.; Neurath, Markus; Strobel, Deike (Medical Science Monitor, 2017)
BACKGROUND Pancreatic intraductal papillary mucinous neoplasms (IPMNs) present a clinical challenge. Evidence-based guidelines are lacking. The so-called "Fukuoka criteria" were developed to assess the risk of malignancy in IPMNs upon imaging. However, little is known about their diagnostic value and the natural course of IPMNs. Thus, the aim of this study was the assessment of Fukuoka criteria and patient management in pancreatic IPMNs -during follow-up. MATERIAL AND METHODS IPMNs were identified via retrospective survey of endoscopic ultrasound (EUS) examinations. Fukuoka criteria were assessed on EUS findings and additional imaging (CT, MRI, ultrasound). Patients' symptoms and comorbidities were recorded. Dynamics of Fukuoka criteria and patient management were compared at first presentation and during follow-up. RESULTS We screened 1324 EUS examinations. Sixty-five patients (male/female, 14/37; mean age, 68.8 years; range, 48-85 years) with IPMNs were identified (57 branch duct (BD-)IPMNs, 3 main duct (MD-) IPMNs, 5 mixed-type (MT)-IPMNs). Seven patients received surgical resection (4 BD-IPMNs, 2 MD-IPMNs, 1 MT-IPMN). Nine BD-IPMNs had neither surgery nor follow-up. Fifty-one patients (44 BD-IPMNs, 2 MD-IPMNs, 5 MT-IPMNs) underwent follow-up (mean duration, 18.7 months; range, 3-139 months). There were 15/51 patients who were initially Fukuoka-positive. One MD-IPMN, 4/5 MT-IPMNs, and 13/44 BD-IPMNs showed progressive changes but were not resected due to patients' refusal or comorbidities. Four BD-IPMNs converted to Fukuoka-positive. CONCLUSIONS Evidence-based guidelines for non-invasive dignity assessment of IPMNs are lacking. In our study, MD-IPMNs displayed greater dynamics than BD-IPMNs and MT-IPMNs concerning Fukuoka criteria. Prospective long-term studies are needed to clarify prognostic significance of the single Fukuoka criteria and sensible duration of follow-up.
EVALuna2:33822

Dynamic, transient, and robust increase in the innervation of the inflamed mucosa in inflammatory bowel diseases - Gonzalez Acera, Miguel; Bubeck, Marvin; Mascia, Fabrizio; Diemand, Leonard; Sturm, Gregor; Kuehl, Anja A.; Atreya, Raja; Lie, Dieter Chichung; Neurath, Markus; Schumann, Michael; Klose, Christoph S. N.; Trajanoski, Zlatko; et al. (Cells, 2021)
Inflammatory bowel diseases (IBD) are characterized by chronic dysregulation of immune homeostasis, epithelial demise, immune cell activation, and microbial translocation. Each of these processes leads to proinflammatory changes via the release of cytokines, damage-associated molecular patterns (DAMPs), and pathogen-associated molecular patterns (PAMPs), respectively. The impact of these noxious agents on the survival and function of the enteric nervous system (ENS) is poorly understood. Here, we show that in contrast to an expected decrease, experimental as well as clinical colitis causes an increase in the transcript levels of enteric neuronal and glial genes. Immunostaining revealed an elevated neuronal innervation of the inflamed regions of the gut mucosa. The increase was seen in models with overt damage to epithelial cells and models of T cell-induced colitis. Transcriptomic data from treatment naïve pediatric IBD patients also confirmed the increase in the neuroglial genes and were replicated on an independent adult IBD dataset. This induction in the neuroglial genes was transient as levels returned to normal upon the induction of remission in both mouse models as well as colitis patients. Our data highlight the dynamic and robust nature of the enteric nervous system in colitis and open novel questions on its regulation.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Crohn’s disease; Enteric nervous system; Inflammatory bowel diseases; Neurogenesis; Ulcerative colitis

Early Symptom Improvement With Risankizumab Treatment in Patients With Moderately to Severely Active Crohn's Disease: Analysis From a Phase 2 Study - Feagan, Brian G.; Sandborn, William J.; D'Haens, Geert R.; Panes, Julian; Kaser, Arthur; Ferrante, Marc; Louis, Edouard; Dewit, Olivier; Seidler, Ursula; Kim, Kyung-Jo; Kligys, Kristina; Wallace, Kori; et al. (AMERICAN JOURNAL OF GASTROENTEROLOGY, 2019)
CRIS-Team WoS Importer:2020-02-28

Editorial: Modulating Cytokines as Treatment for Autoimmune Diseases and Cancer - Mortier, Erwan; Ma, Averil; Malynn, Barbara A.; Neurath, Markus (Frontiers in Immunology, 2020)
CRIS-Team Scopus Importer:2020-11-06
Keywords: cytokine; inflammation; inhibitor; oncology; therapy

Effects of Adjuvant Exercise and Nutrition Therapy on Muscle Fibre Biomechanics in Gastrointestinal Cancer Patients - Haug, Michael; Schwappacher, Raphaela; Pollmann, Charlotte; Ritter, Paul; Michael, Mena; Herrmann, Hans Joachim; Grützmann, Robert; Mittelstädt, Anke; Neurath, Markus; Zopf, Yurdagül; Friedrich, Oliver (Cancers, 2024)
Patients with aggressive cancer, e.g., gastrointestinal cancer, are prone (≥50% chance) to developing cancer cachexia (CC). Little is known about the effects of CC on the biomechanical function of muscle. A promising prevention strategy was found in the form of a multi-modal therapy combining mild resistance exercise (e.g., whole-body electro-myostimulation, WB-EMS) and a protein-rich diet. In a previous study of ours, this was effective in counteracting the loss of muscle mass, yet a systematic and comprehensive assessment of active and passive single muscle fibre functions was so far absent. This pilot study investigated the biomechanical function of single muscle fibres (rectus abdominis) from the biopsies of conventionally treated (pre-)cachectic cancer ((pre-)CC) patients (m = 9), those receiving the multi-modal therapy comprising WB-EMS training and protein-rich nutrition (m = 3), and a control group (m = 5). Our findings not only align with previous findings showing the absolute force loss in CC that is accelerated by atrophy but also speak in favour of a different, potentially energy- and Ca2+-homeostasis-related effect that compromises muscle contraction (F 0.9 mN vs. F 0.6 mN in control patients). However, myofibrillar Ca2+ sensitivity and the quality of contraction were unaltered (pCa50: 5.6–5.8). Single fibres from the (pre-)CC patients receiving WB-EMS training and protein supplementation were significantly more compliant (p < 0.001 at ≥130% of resting length L0). Those fibres displayed a similar softness to the ones from the control patients (axial compliance 15 m/N at ≥130% L0), while single fibres from the patients with (developing) cachexia were significantly stiffer (axial compliance 7 m/N, p < 0.001 at ≥130% L0). Adjuvant multi-modal therapy (WB-EMS training and nutritional support) contributes to maintaining the axial compliance of single fibres and potentially improves the quality of life for patients at risk of developing CC.
CRIS-Team Scopus Importer:2024-05-03
Keywords: cancer cachexia; multi-modal therapy; protein-rich diet; resistance training; single fibres; skeletal muscle

Effects of Anti-Integrin Treatment With Vedolizumab on Immune Pathways and Cytokines in Inflammatory Bowel Diseases - Rath, Timo; Billmeier, Ulrike; Ferrazzi, Fulvia; Ekici, Arif Bülent; Neurath, Markus; Atreya, Raja; Vieth, Michael (Frontiers in Immunology, 2018)
Background and aims: Despite proven clinical efficacy of vedolizumab (VDZ) for inducing and maintaining remission in patients with Crohn's disease (CD) and ulcerative colitis (UC), subgroups of patients have no therapeutic benefit from anti-α4β7 integrin therapy with VDZ. Within this study, we aimed to identify genetic, cellular, and immunological mechanisms that define response and failure to VDZ treatment. Methods: Intestinal RNA sequencing was performed in UC and CD patients before and at week 14 of VDZ therapy. α4β7 expression on peripheral and mucosal immune cells was assessed by flow cytometry and immunohistochemistry. Cellular modes of VDZ-mediated action were analyzed ex vivo and in VDZ-treated inflammatory bowel disease patients. Results: Transcriptome analysis showed an impairment of signaling cascades associated with adhesion, diapedesis, and migration of granulocytes and agranulocytes upon VDZ therapy. In non-remitters to VDZ therapy, a tissue destructive and leukocyte-mediated inflammatory activity with activation of TNF-dependent pathways was present, all of which were inhibited in remitters to VDZ. Clinical remission was associated with a significant reduction of α4β7 expression on Th2 and Th17 polarized mucosal CD4+ T cells at week 14 of VDZ therapy and with significantly higher numbers of α4β7-expressing mucosal cells prior to the initiation of VDZ therapy compared with non-remitters. Conclusion: Intestinal α4β7 expression prior to VDZ therapy might represent a biomarker that predicts therapeutic response to subsequent VDZ treatment. Due to high activation of TNF signaling in VDZ non-remitters, anti-TNF treatment might represent a promising therapeutic strategy in VDZ refractory patients.
EVALuna2:34622

Effects of Apremilast, an Oral Inhibitor of Phosphodiesterase 4, in a Randomized Trial of Patients With Active Ulcerative Colitis - Danese, Silvio; Neurath, Markus; Kopoń, Adam; Zakko, Salam F.; Simmons, Timothy C.; Fogel, Ronald; Siegel, Corey A.; Panaccione, Remo; Zhan, Xiaojiang; Usiskin, Keith; Chitkara, Denesh (Clinical Gastroenterology and Hepatology, 2020)
Background & Aims: New oral therapeutic agents are needed for patients with ulcerative colitis (UC) who are unresponsive or intolerant to conventional therapy. Methods: We performed a double-blind, phase 2 trial of adults with active UC for 3 months or more who were naïve to biologic therapy or had been failed by, could not tolerate, or had contraindications to conventional therapies. The study was performed at 61 sites in 14 countries (screening from January 2015 through May 2017). Patients were randomly assigned to groups given apremilast 30 mg (n = 57), apremilast 40 mg (n = 55), or placebo (n = 58) twice daily for 12 weeks; patients were then randomly assigned to groups that received apremilast, 30 or 40 mg twice daily, for an additional 40 weeks. Endoscopies were performed and biopsies were collected during the screening phase, at week 12, and at week 52. Blood and fecal samples were also collected and analyzed throughout the study. The primary endpoint was clinical remission at week 12, defined as a total Mayo score of 2 or less, with no individual subscore above 1. Results: Clinical remission was achieved at week 12 by 31.6% of patients in the 30 mg apremilast group and 12.1% of patients in the placebo group (P =.01). However, only 21.8% of patients in the 40 mg apremilast group achieved clinical remission at week 12 (P =.27 compared with placebo). Differences in clinical remission between the 30 mg and 40 mg apremilast groups were associated with differences in endoscopic improvement. Both apremilast groups had similar improvements from baseline in Mayo score components (stool frequency score, rectal bleeding score, physician's global assessment). The 30 mg and 40 mg apremilast groups had greater median percent reductions in C-reactive protein (measured by a high-sensitivity blood test) and fecal calprotectin through week 12 than the placebo group. At week 52, clinical remission was achieved by 40.4% of patients initially assigned to the apremilast 30 mg group and 32.7% of patients initially assigned to the apremilast 40 mg group. The most frequent apremilast-associated adverse events were headache and nausea. Conclusions: Although the primary endpoint of clinical remission was not met in this phase 2 trial, a greater proportion of patients with active UC who received apremilast (30 mg or 40 mg) had improvements in clinical and endoscopic features, and markers of inflammation, at 12 weeks. Clinical remission was maintained to week 52 in up to 40% of patients who continued apremilast until that time point. ClinicalTrials.gov no: NCT02289417
CRIS-Team Scopus Importer:2020-09-25
Keywords: Biologic-Naïve; CRP; IBD; TMS

Effects of liver cirrhosis and patient condition on clinical outcomes in intrahepatic cholangiocarcinoma: a retrospective analysis of 156 cases in a single center - Jesper, Daniel; Heyn, Sabrina; Schellhaas, Barbara; Pfeifer, Lukas; Görtz, Rüdiger; Zopf, Steffen; Neurath, Markus; Strobel, Deike (European Journal of Gastroenterology & Hepatology, 2018)
OBJECTIVE: The incidence of intrahepatic cholangiocarcinoma (iCCA) has been increasing over the past few decades. Liver cirrhosis is an independent risk factor for the development of iCCA. This study aimed to examine the prognostic impact of liver cirrhosis and patient condition on the treatment of iCCA. PATIENTS AND METHODS: We retrospectively analyzed the cases of 156 patients diagnosed with iCCA between 1990 and 2014 in our center. Patients were divided into subgroups depending on the presence and severity of liver cirrhosis and the type of treatment. Clinical data, patient characteristics, and overall survival were compared between these groups. RESULTS: Forty-seven (30%) of 156 patients had liver cirrhosis, predominantly with Child-Pugh scores A (n=27) and B (n=12). The median survival differed between patients receiving tumor resection (34 months), chemotherapy (10 months), and best supportive care (2 months). An Eastern Cooperative Oncology Group Performance Status score more than 1 was a predictor of poor survival in all patients (P<0.001), independent of the presence of cirrhosis. Resection could be performed less frequently in cirrhotic patients (6 vs. 31 patients; P=0.04). If resection was performed, the presence of cirrhosis A/B did not influence survival. Cirrhosis A/B did not influence the outcome in patients receiving chemotherapy either. In cirrhotic patients receiving chemotherapy, cancer antigen 19-9 levels above 129 U/ml were associated with a significantly shorter survival (22.5 vs. 3 months, P=0.0003). CONCLUSION: The presence of liver cirrhosis in iCCA has been underestimated. There was no difference in survival between noncirrhotic patients and patients with compensated cirrhosis. Patients' general condition seems to be of more prognostic value in the treatment of iCCA than the presence of cirrhosis. Therefore, the presence of cirrhosis A/B should not prevent patients with a good Eastern Cooperative Oncology Group Performance Status score from receiving tumor resection or chemotherapy.
EVALuna2:34071

Effects of very low volume high intensity versus moderate intensity interval training in obese metabolic syndrome patients: a randomized controlled study - Reljic, Dejan; Frenk, Fabienne; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (Scientific Reports, 2021)
Physical activity is a cornerstone in the treatment of obesity and metabolic syndrome (MetS). Given the leading physical activity barrier of time commitment and safety concerns about vigorous exercise in high-risk groups, this study aimed to investigate the effects of two extremely time-efficient training protocols (< 30 min time effort per week), either performed as high- (HIIT) or moderate-intensity interval training (MIIT) over 12 weeks, in obese MetS patients. In total, 117 patients (49.8 ± 13.6 years, BMI: 38.2 ± 6.2 kg/m2) were randomized to HIIT (n = 40), MIIT (n = 37) or an inactive control group (n = 40). All groups received nutritional counseling to support weight loss. Maximal oxygen uptake (VO2max), MetS severity (MetS z-score), body composition and quality of life (QoL) were assessed pre-and post-intervention. All groups significantly reduced body weight ( 3%) but only the exercise groups improved VO2max, MetS z-score and QoL. VO2max (HIIT: + 3.1 mL/kg/min, p < 0.001; MIIT: + 1.2 mL/kg/min, p < 0.05) and MetS z-score (HIIT: − 1.8 units, p < 0.001; MIIT: − 1.2 units, p < 0.01) improved in an exercise intensity-dependent manner. In conclusion, extremely low-volume interval training, even when done at moderate intensity, is sufficiently effective to improve cardiometabolic health in obese MetS patients. These findings underpin the crucial role of exercise in the treatment of obesity and MetS.
CRIS-Team Scopus Importer:2021-02-12

Effects of whole-body electromyostimulation combined with individualized nutritional support on body composition in patients with advanced cancer: a controlled pilot trial - Schink, Kristin; Herrmann, Hans J.; Schwappacher, Raphaela; Meyer, Julia; Orlemann, Till; Waldmann, Elisabeth; Wullich, Bernd; Kahlmeyer, Andreas; Fietkau, Rainer; Lubgan, Dorota; Beckmann, Matthias; Hack, Carolin; et al. (BMC Cancer, 2018)
BACKGROUND: Physical exercise and nutritional treatment are promising measures to prevent muscle wasting that is frequently observed in advanced-stage cancer patients. However, conventional exercise is not always suitable for these patients due to physical weakness and therapeutic side effects. In this pilot study, we examined the effect of a combined approach of the novel training method whole-body electromyostimulation (WB-EMS) and individualized nutritional support on body composition with primary focus on skeletal muscle mass in advanced cancer patients under oncological treatment. METHODS: In a non-randomized controlled trial design patients (56.5% male; 59.9 ± 12.7 years) with advanced solid tumors (UICC III/IV, N = 131) undergoing anti-cancer therapy were allocated to a usual care control group (n = 35) receiving individualized nutritional support or to an intervention group (n = 96) that additionally performed a supervised physical exercise program in form of 20 min WB-EMS sessions (bipolar, 85 Hz) 2×/week for 12 weeks. The primary outcome of skeletal muscle mass and secondary outcomes of body composition, body weight and hand grip strength were measured at baseline, in weeks 4, 8 and 12 by bioelectrical impedance analysis and hand dynamometer. Effects of WB-EMS were estimated by linear mixed models. Secondary outcomes of physical function, hematological and blood chemistry parameters, quality of life and fatigue were assessed at baseline and week 12. Changes were analyzed by t-tests, Wilcoxon signed-rank or Mann-Whitney-U-tests. RESULTS: Twenty-four patients of the control and 58 of the WB-EMS group completed the 12-week trial. Patients of the WB-EMS group had a significantly higher skeletal muscle mass (0.53 kg [0.08, 0.98]; p = 0.022) and body weight (1.02 kg [0.05, 1.98]; p = 0.039) compared to controls at the end of intervention. WB-EMS also significantly improved physical function and performance status (p < 0.05). No significant differences of changes in quality of life, fatigue and blood parameters were detected between the study groups after 12 weeks. CONCLUSIONS: Supervised WB-EMS training is a safe strength training method and combined with nutritional support it shows promising effects against muscle wasting and on physical function in advanced-stage cancer patients undergoing treatment. TRIAL REGISTRATION: ClinicalTrials.gov NCT02293239 (Date: November 18, 2014).
EVALuna2:35141

Effects of whole-body electromyostimulation exercise and caloric restriction on cardiometabolic risk profile and muscle strength in obese women with the metabolic syndrome: a pilot study - Reljic, Dejan; Konturek, Peter; Herrmann, H. J.; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2020)
Obesity, particularly in conjunction with further cardiometabolic risk factors, is associated with an increased risk of cardiovascular disease and mortality. Increased physical activity and dietary modifications are cornerstones of therapeutic interventions to treat obesity and related risk factors. Whole-body electromyostimulation (WB-EMS) has emerged as an innovative, time-efficient type of exercise that can provide positive effects on body composition and muscle strength. However, the impact of WB-EMS on cardiometabolic health in obese individuals with metabolic syndrome (MetS) has yet to be determined. The aim of this pilot study was, therefore, to investigate the feasibility and effects of WB-EMS on cardiometabolic risk markers and muscle strength in obese women diagnosed with MetS. Twenty-nine obese women (56.0 ± 10.9 years, BMI: 36.7 ± 4.6 kg/m2) with the clinical diagnosis of MetS were randomized to either 12 weeks of WB-EMS (n = 15) or an inactive control group (CON, n = 14). Both groups received nutritional counseling (aim: -500 kcal energy deficit/day). WB-EMS was performed 2x/week (20 min/session). Body composition, maximum strength (Fmax) of major muscle groups, selected cardiometabolic risk indices and the metabolic syndrome Z-score (MetS-Z) were determined baseline and after the intervention. WB-EMS was well tolerated and no adverse events occurred. Body weight was significantly reduced in both groups by an average of 3 kg (P < 0.01). The body fat percentage was only decreased in the WB-EMS group (P = 0.018). Total cholesterol concentrations decreased in the WB-EMS group (P = 0.018) and in CON (P = 0.027). Only the WB-EMS group increased Fmax significantly in all major muscle groups (P < 0.05) and improved the overall cardiometabolic risk score (MetS-Z, P = 0.029). This pilot study indicates that WB-EMS can be considered as a feasible and time-efficient exercise option for improving body composition, muscle strength and cardiometabolic health in obese women with MetS. Moreover, these findings underpin the crucial role of exercise during weight loss interventions in improving health outcomes.
CRIS-Team Scopus Importer:2020-06-30

EFFICACY OF HEMOSPRAY AND ENDOCLOT IN THE TREATMENT OF GASTROINTESTINAL BLEEDING: RESULTS FROM A TERTIARY REFFERAL CENTER - Vitali, Francesco; Naegel, Andreas; Neurath, Markus; Rath, Timo; Siebler, Jürgen (2018)
EVALuna2:35162

Efficacy, safety, and pharmacokinetics after switching from infliximab originator to biosimilar SB2 in inflammatory bowel disease patients: A long-term observational, prospective cohort study - Fischer, Sören; Mesfin, Sarah Ellen; Klenske, E.; Schmitt, Heike; Vitali, Francesco; Hirschmann, Simon; Ramming, A.; Zundler, Sebastian; Rath, Timo; Krebs, Sabine; Dörje, Frank; Uter, Wolfgang; et al. (JOURNAL OF CROHNS & COLITIS, 2020)
CRIS-Team WoS Importer:2020-04-10

Efficiency and Toxicity of Lenvatinib in Advanced HCC in Later Treatment Lines - Jefremow, Andre; Wiesmüller, Marco; Rouse, Rachel Amanda; Dietrich, Peter; Kremer, Andreas; Waldner, Maximilian; Neurath, Markus; Siebler, Jürgen (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Efficient and Easy Conversion of Human iPSCs into Functional Induced Microglia-like Cells - Lanfer, Jonas; Winner, Beate; Kaindl, Johanna; Krumm, Laura; Acera, Miguel Gonzalez; Neurath, Markus; Regensburger, Martin; Krach, Florian (International Journal of Molecular Sciences, 2022)
Current protocols converting human induced pluripotent stem cells (iPSCs) into induced microglia-like cells (iMGL) are either dependent on overexpression of transcription factors or require substantial experience in stem-cell technologies. Here, we developed an easy-to-use two-step protocol to convert iPSCs into functional iMGL via: (1) highly efficient differentiation of hematopoietic progenitor cells (HPCs) from iPSCs, and (2) optimized maturation of HPCs to iMGL. A sequential harvesting approach led to an increased HPC yield. The protocol implemented a freezing step, thus allowing HPC biobanking and flexible timing of differentiation into iMGL. Our iMGL responded adequately to the inflammatory stimuli LPS, and iMGL RNAseq analysis matched those of other frequently used protocols. Comparing three different coating modalities, we increased the iMGL yield by culturing on uncoated glass surfaces, thereby retaining differentiation efficiency and functional hallmarks of iMGL. In summary, we provide a high-quality, easy-to-use protocol, rendering generation and functional studies on iMGL an accessible lab resource.
CRIS-Team Scopus Importer:2022-04-29
Keywords: cell differentiation; immunology; microglia; neurology; pluripotent stem cells

Elevated levels of Bcl-3 inhibits Treg development and function resulting in spontaneous colitis - Reissig, Sonja; Tang, Yilang; Nikolaev, Alexei; Gerlach, Katharina; Wolf, Christine; Davari, Kathrin; Gallus, Christian; Masri, Joumana; Mufazalov, Ilgiz A.; Neurath, Markus; Wunderlich, F. Thomas; Schattenberg, Joern M.; et al. (Nature Communications, 2017)
Bcl-3 is an atypical NF-κB family member that regulates NF-κB-dependent gene expression in effector T cells, but a cell-intrinsic function in regulatory T (Treg) cells and colitis is not clear. Here we show that Bcl-3 expression levels in colonic T cells correlate with disease manifestation in patients with inflammatory bowel disease. Mice with T-cell-specific overexpression of Bcl-3 develop severe colitis that can be attributed to defective Treg cell development and function, leading to the infiltration of immune cells such as pro-inflammatory γδT cells, but not αβ T cells. In Treg cells, Bcl-3 associates directly with NF-κB p50 to inhibit DNA binding of p50/p50 and p50/p65 NF-κB dimers, thereby regulating NF-κB-mediated gene expression. This study thus reveals intrinsic functions of Bcl-3 in Treg cells, identifies Bcl-3 as a potential prognostic marker for colitis and illustrates the mechanism by which Bcl-3 regulates NF-κB activity in Tregs to prevent colitis.
EVALuna2:33818

Emerging oral targeted therapies in inflammatory bowel diseases: opportunities and challenges - Vetter, Marcel; Neurath, Markus (Therapeutic Advances in Gastroenterology, 2017)
To improve quality of life and prevent long-term risks in patients with inflammatory bowel diseases (IBDs: Crohn's disease, ulcerative colitis), it is essential to suppress inflammatory activity adequately. However, corticosteroids are only suitable for therapy of acute flares and the evidence for positive effects of immunosuppressive substances like azathioprine or 6-mercapropurine is mainly limited to maintenance of remission. In addition, only subgroups of patients benefit from biologicals targeting tumour necrosis factor α or α4β7 integrins. In summary, until now the disease activity is not sufficiently controlled in a relevant fraction of the patients with IBD. Thus, there is an urge for the development of new substances in the therapy of ulcerative colitis and Crohn's disease. Fortunately, new oral and parenteral substances are in the pipeline. This review will focus on oral substances, which have already passed phase II studies successfully at this stage. In this article, we summarize data regarding AJM300, phosphatidylcholine (LT-02), mongersen, ozanimod, filgotinib and tofacitinib. AJM300 and ozanimod were tested in patients with ulcerative colitis and target lymphocyte trafficking through inhibition of the α subunit of integrin, respectively binding to the sphingosine-1-phosphate receptor (subtypes 1 and 5) on lymphocytes. Mongersen was utilized in patients with Crohn's disease and accelerates the degradation of SMAD7 mRNA, which consequently strengthens the mainly anti-inflammatory signalling pathway of transforming growth factor β1. Various Janus kinase (JAK) inhibitors were developed, which inhibit the intracellular signalling pathway of cytokines. For example, the JAK1 blocker filgotinib was tested in Crohn's disease, whereas the JAK1/3 inhibitor tofacitinib was tested in clinical trials for both Crohn's disease and ulcerative colitis. A different therapeutic approach is the substitution of phosphatidylcholine (LT-02), which might recover the colonic mucus. Taken together, clinical trials with these new agents have opened avenues for further clinical studies and it can be expected that at least some of these agents will be finally approved for clinical therapy.
EVALuna2:33802

Endocytoscopy allows accurate in vivo differentiation of mucosal inflammatory cells in IBD: A pilot study - Neumann, Helmut; Vieth, Michael; Neurath, Markus; Atreya, Raja (Inflammatory Bowel Diseases, 2013)
Background: Precise activity assessment of inflammatory bowel disease (IBD) is essential to determine extent and severity of disease for optimized therapy. Despite ongoing developments in endoscopy, final diagnosis still relies on the interpretation of histopathological features. Recently, endocytoscopy (EC) was introduced as a new endoscopic imaging modality, enabling in vivo microscopic imaging within the mucosal layer of the gut at a magnification up to 1400-fold. The aim of our study was to determine the reliability of EC for the discrimination of mucosal inflammatory cells and intestinal inflammatory disease activity in patients with IBD. Methods: In all, 40 patients with IBD (Crohn's disease n = 19; ulcerative colitis n = 21) who underwent colonoscopy were prospectively included in this study. Methylene blue or toluidine blue was topically applied to enable EC. Data were digitally saved and analyzed blinded to clinical and endoscopic data. Results: EC enabled visualization of different histopathological features. Based on these specifications, it was possible to reliably distinguish single inflammatory cells by EC with the following respective sensitivities and specificities: neutrophilic (60% and 95%), basophilic (74.43% and 94.44%), eosinophilic granulocytes (75% and 90.48%), and lymphocytes (88.89% and 93.33%). Interobserver agreement between two investigators was substantial (kappa 0.61-0.78), while intraobserver agreement was substantial to almost perfect (kappa 0.76-0.88). Concordance between EC and histopathology for grading intestinal disease activity was 100%. Conclusions: EC enabled the detection and discrimination of single mucosal inflammatory cells and inflammatory disease activity. Therefore, this technique has the potential to improve both in vivo diagnosis and clinical management of IBD patients. Copyright © 2013 Crohn's & Colitis Foundation of America, Inc.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Advanced imaging; Crohn's disease; Endocytoscopy; Endomicroscopy; IBD; Mucosal inflammatory cells; Ulcerative colitis

Endocytoscopy-Based Detection of Focal High-Grade Intraepithelial Neoplasia in Colonic Polyps - Neumann, Helmut; Vieth, Michael; Neurath, Markus (Clinical Gastroenterology and Hepatology, 2011)
CRIS-Team Scopus Importer:2025-03-05

Endocytoscopy for assessing histologic inflammation in ulcerative colitis: development and prospective validation of the ELECT (ErLangen Endocytoscopy in ColiTis) score (with videos) - Vitali, Francesco; Morgenstern, Nadine; Eckstein, Markus; Atreya, Raja; Waldner, Maximilian; Hartmann, Arndt; Neurath, Markus; Rath, Timo (Gastrointestinal Endoscopy, 2022)
Background and Aims: Apart from endoscopic healing as an established treatment goal in patients with inflammatory bowel disease (IBD), histologic remission is an emerging endpoint that might even better predict disease outcome, especially in ulcerative colitis (UC). Within this study, we aimed to evaluate whether endocytoscopy (EC) as an in vivo contact microscopy technology can accurately assess histologic inflammation and predict the further course of disease in UC patients. Methods: Initially, a new and intuitive EC score reflecting the entire spectrum of microscopic disease activity in UC was consensually developed. Subsequently, this score was independently validated in 46 patients with UC who underwent close-meshed follow-up during which major adverse outcomes (MAOs; defined as disease flare, IBD-related hospitalization, IBD-related surgery, necessity for initiation or escalation therapy) were recorded. Results of EC grading of inflammatory activity were compared against 2 validated histologic scores in UC. Diagnostic performance of endoscopic remission under white-light endoscopy (Mayo Endoscopic Score and Ulcerative Colitis Endoscopic Index of Severity), EC, and histology were compared for the prediction of MAOs. Results: Endocytoscopic assessment of inflammatory activity in UC based on the newly developed ErLangen Endocytoscopy in ColiTis score showed strong correlation with histopathologic scoring (Robarts Histopathology Index, r = .70; Nancy Histologic Index, r = .73) and was superior to white-light endoscopy for grading of microscopic disease activity, with a sensitivity of 88%, specificity of 95.2%, and area under the curve of .916. Furthermore, EC exhibited a high interobserver agreement for in vivo grading of microscopic inflammation and was comparably accurate as histopathology for forecasting the occurrence of MAOs in UC. Conclusions: Endocytoscopic grading of inflammatory activity along a newly developed scoring system enabled real-time histology in UC patients and better predicted clinical outcome in UC patients than endoscopic remission.
CRIS-Team Scopus Importer:2022-12-16

Endogenous Opioid Levels Do Not Correlate With Itch Intensity and Therapeutic Interventions in Hepatic Pruritus - Düll, Miriam; Wolf, Katharina; Vetter, Marcel; Dietrich, Peter; Neurath, Markus; Kremer, Andreas (Frontiers in Medicine, 2021)
Background: Chronic pruritus affects up to 70% of patients with immune-mediated hepatobiliary disorders. Antagonists of the μ-opioid receptor (MOR) and agonists of the κ-opioid receptor (KOR) are used to treat hepatic itch, albeit with limited success. An imbalance between ligands of MOR and KOR receptors has recently been suggested as a potential mechanism of hepatic pruritus. In this study, we therefore investigated systemic levels of important endogenous opioids such as β-endorphin, dynorphin A, Leu- and Met-enkephalin in plasma of a large cohort of well-characterized patients with immune-mediated cholestatic disorders, including patients with liver cirrhosis, and during effective anti-pruritic therapy. Methods: Plasma samples and clinical data were prospectively collected from well-characterized patients with primary/secondary sclerosing cholangitis (PSC/SSC), primary biliary cholangitis (PBC) and overlap syndromes suffering from pruritus (n = 29) and age-, gender- and disease-matched controls without pruritus (n = 27) as well as healthy controls (n = 20). General laboratory testing for hepatobiliary and renal function was performed. Levels of β-endorphin, dynorphin A, Leu- and Met-enkephalin were quantified in plasma by ELISA. Intensity of pruritus over the last week was evaluated using a visual analog scale (VAS, 0–10). Results: PBC and PSC patients with or without pruritus did neither differ in disease entity, disease stage, nor in the presence of cirrhosis. While both dynorphin A and β-endorphin concentrations were lower in pruritic patients compared to those without pruritus and healthy controls, the MOR/KOR ligand ratio was unaltered. No significant differences were observed for Leu- and Met-enkephalin concentrations. Opioid levels correlated with neither itch intensity nor stage of disease. Cirrhotic patients displayed higher concentrations of MOR agonist Leu-enkephalin and KOR agonist dynorphin A. Endogenous opioid levels remained largely unchanged after successful treatment with the potent anti-pruritic drugs rifampicin and bezafibrate. Conclusions: Endogenous opioid levels and the MOR/KOR ligand ratio neither correlate with itch intensity nor differentiate pruritic from non-pruritic patients with immune-mediated liver diseases. Thus, endogenous opioids may modulate signaling pathways involved in hepatic pruritus, but are unlikely to represent the major pruritogens in liver disease.
CRIS-Team Scopus Importer:2021-05-14
Keywords: bezafibrate; cholestasis; dynorphin; endorphin; enkephalin; liver; rifampicin; therapy

ENDOSCOPIC FULL-THICKNESS RESECTION IN THE COLORECTUM USING THE FTRD: RESULTS FROM A UNIVERSITY TERTIARY REFERRAL CENTER - Vitali, Francesco; Naegel, Andreas; Neurath, Markus; Rath, Timo; Siebler, Jürgen (2018)
EVALuna2:35163

Endoscopic management of buried bumper syndrome using a novel grasping-type scissor forceps - Rath, Timo; Vitali, Francesco; Naegel, Andreas; Neurath, Markus (Endoscopy, 2021)
CRIS-Team WoS Importer:2021-01-29

Endoscopic recanalization of complete esophageal obstruction - Vitali, Francesco; Naegel, Andreas; Pfeifer, Lukas; Goetz, Martin; Neurath, Markus; Rath, Timo; Siebler, Jürgen (Surgical Endoscopy, 2021)
Background and aims Complete esophageal obstruction (CEO) is a rare complication after radiochemotherapy that dramatically impairs quality of life. Within this study, we assessed the outcome of two different endoscopic techniques for lumen restoration in patients with CEO.
CRIS-Team WoS Importer:2021-02-26

Endoscopic Ultrasound in Pancreatology: Focus on Inflammatory Diseases and Interventions - Vitali, Francesco; Zundler, Sebastian; Jesper, Daniel; Strobel, Deike; Wildner, Dane; De Pretis, Nicoló; Frulloni, Luca; Crinó, Stefano Francesco; Neurath, Markus (Visceral Medicine, 2023)
Background: Endoscopic ultrasound (EUS) is a main tool in pancreatology for both diagnosis and therapy. It allows minimally invasive differentiation of various diseases, with a minimal degree of inflammation or anatomic variations. EUS also enables interventional direct access to the pancreatic parenchyma and the retroperitoneal space, the pancreatic duct, the pancreatic masses, cysts, vascular structures for diagnostic and therapeutic purposes. Summary: This review aimed to summarize the new developments of EUS in the field of pancreatology, with special interest on inflammation and interventions. EUS enables way to perform pseudocyst drainage, necrosectomy, transenteral drainage and transenteric access of the main pancreatic duct, or the direct visualization or therapy of vascular structures adjacent to the pancreas. Key Messages: EUS has a deep impact on pancreatology, and the development of new diagnostic and interventional approaches to the retroperitoneal space and the pancreas has increased in the last years exponentially, allowing minimal invasive diagnostics and therapy and avoiding surgery and percutaneous therapy.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Endoscopic ultrasound; Endoscopic ultrasound-guided biopsy; Endoscopic ultrasound-guided drainage; Pancreatic cancer; Pancreatitis

Endoscopy: Chromoendoscopy in IBD: indispensable in real-life screening - Atreya, Raja; Neurath, Markus (Nature Reviews Gastroenterology & Hepatology, 2016)
Long-standing IBD is associated with an increased risk of neoplasia. Chromoendoscopy was proven to be the most sensitive modality for dysplasia detection in several clinical trials, but a new study has now shown ityto be an effective screening strategy in a routine clinical setting, further warranting its implementation into real-world practice.
EVALuna2:2193

Endoscopy in Inflammatory Bowel Diseases: From Proven to New Endoskopie bei chronisch entzündlichen Darmerkrankungen: Neues und Bewährtes - Rath, Timo; Neurath, Markus (Deutsche Medizinische Wochenschrift, 2025)
Inflammatory bowel diseases with the 2 main forms - ulcerative colitis and Crohn's disease - are chronic relapsing diseases of the gastrointestinal tract in which dysregulation of the intestinal immune system against commensal components of the microbiome leads to perpetuated intestinal inflammation based on a genetic predisposition. While in the past symptom control was the focus of therapy, more recent data show that achieving endoscopic remission is superior to sole clinical symptom control for the further course and prognosis of the diseases. In this review article, we will present the significance of endoscopy for inflammatory bowel diseases, describe established scoring systems for endoscopic graduation of inflammatory activity and, last but not least, also present and review new endoscopic developments.
CRIS-Team Scopus Importer:2025-05-30
Keywords: colonoscopy; confocal laser endomicroscopy; Crohn's disease; endocytoscopy; endoscopy; inflammatory bowel diseases; ulcerative Colitis

Endoscopy on the way to molecular imaging: Endocytoscopy Endoskopie auf dem weg zur molekularen bildgebung: Endozytoskopie - Neumann, Helmut; Langner, C.; Vieth, M.; Neurath, Markus (Verdauungskrankheiten, 2012)
Endocytoscopy is a new imaging modality which enables in vivo microscopic imaging of the mucosa at 1.400-fold magnification. Various studies have addressed the potential of endocytoscopy for different disease entities. including esophageal squamous cell carcinoma. celiac disease and colorectal polyps. In this review we will focus on the technique of endocytoscopy and potential applications. Furthermore, we will give an outlook on future possible applications of this emerging endoscopic imaging technique.© 2012.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Chromoendoscopy; Endocytoscopy; Endomicroscopy; Endoscopy; In vivo histology; Molecular imaging; Optical biopsy

Engineering Therapeutic Regulatory T Cells to Overexpress G Protein-Coupled Receptor 15 Improves Functional Fitness for In Vivo Gut Homing - Müller, Tanja; Liu, Lijuan; Wiesinger, Manuel; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; Diefenbach, Andreas; et al. (Gastroenterology, 2025)
CRIS-Team Scopus Importer:2025-01-31

Environmental Microbial Factors Determine the Pattern of Inflammatory Lesions in a Murine Model of Crohn's Disease-Like Inflammation - Stolzer, Iris; Kaden-Volynets, Valentina; Ruder, Barbara; Letizia, Marilena; Bittel, Miriam; Rausch, Philipp; Basic, Marijana; Bleich, André; Baines, John F.; Neurath, Markus; Wirtz, Stefan; Weidinger, Carl; et al. (Inflammatory Bowel Diseases, 2019)
Crohn's disease (CD) patients can be grouped into patients suffering from ileitis, ileocolitis, jejunoileitis, and colitis. The pathophysiological mechanism underlying this regional inflammation is still unknown. Although most murine models of inflammatory bowel disease (IBD) develop inflammation in the colon, there is an unmet need for novel models that recapitulate the spontaneous and fluctuating nature of inflammation as seen in CD. Recently, mice with an intestinal epithelial cell-specific deletion for Caspase-8 (Casp8ΔIEC mice), which are characterized by cell death-driven ileitis and disrupted Paneth cell homeostasis, have been identified as a novel model of CD-like ileitis. Here we uncovered that genetic susceptibility alone is sufficient to drive ileitis in Casp8ΔIEC mice. In sharp contrast, environmental factors, such as a disease-relevant microbial flora, determine colonic inflammation. Accordingly, depending on the microbial environment, isogenic Casp8ΔIEC mice either exclusively developed ileitis or suffered from pathologies in several parts of the gastrointestinal tract. Colitis in these mice was characterized by massive epithelial cell death, leading to spread of commensal gut microbes to the extra-intestinal space and hence an aberrant activation of the systemic immunity. We further uncovered that Casp8ΔIEC mice show qualitative and quantitative changes in the intestinal microbiome associated with an altered mucosal and systemic immune response. In summary, we identified that inflammation in this murine model of CD-like inflammation is characterized by an immune reaction, presumably directed against a disease-relevant microbiota in a genetically susceptible host, with impaired mucosal barrier function and bacterial clearance at the epithelial interface.
Keywords: Crohn’s disease; Paneth cells; cell death; colitis; ileitis; microflora

Environmental triggers in IBD: a review of progress and evidence - Ananthakrishnan, Ashwin N.; Bernstein, Charles N.; Iliopoulos, Dimitrios; Macpherson, Andrew; Neurath, Markus; Ali, Raja A. Raja; Vavricka, Stephan R.; Fiocchi, Claudio (Nature Reviews Gastroenterology & Hepatology, 2018)
A number of environmental factors have been associated with the development of IBD. Alteration of the gut microbiota, or dysbiosis, is closely linked to initiation or progression of IBD, but whether dysbiosis is a primary or secondary event is unclear. Nevertheless, early-life events such as birth, breastfeeding and exposure to antibiotics, as well as later childhood events, are considered potential risk factors for IBD. Air pollution, a consequence of the progressive contamination of the environment by countless compounds, is another factor associated with IBD, as particulate matter or other components can alter the host's mucosal defences and trigger immune responses. Hypoxia associated with high altitude is also a factor under investigation as a potential new trigger of IBD flares. A key issue is how to translate environmental factors into mechanisms of IBD, and systems biology is increasingly recognized as a strategic tool to unravel the molecular alterations leading to IBD. Environmental factors add a substantial level of complexity to the understanding of IBD pathogenesis but also promote the fundamental notion that complex diseases such as IBD require complex therapies that go well beyond the current single-agent treatment approach. This Review describes the current conceptualization, evidence, progress and direction surrounding the association of environmental factors with IBD.
EVALuna2:33797

Eosinophilic gastroenteritis with refractory ulcer disease and gastrointestinal bleeding as a rare manifestation of seronegative gastrointestinal food allergy - Raithel, Martin; Hahn, Markus; Donhuijsen, Konrad; Hagel, Alexander; Nagel, Andreas; Rieker, Ralf J.; Neurath, Markus; Reinshagen, Max (Nutrition Journal, 2014)
Gastrointestinal bleeding and iron deficiency anaemia may cause severe symptoms and may require extensive diagnostics and substantial amounts of health resources.This case report focuses on the clinical presentation of a 22 year old patient with recurrent gastrointestinal bleeding from multilocular non-healing ulcers of the stomach, duodenum and jejunum over a period of four years. Extensive gastroenterological and allergological standard diagnostic procedures showed benign ulcerative lesions with tissue eosinophilia, but no conclusive diagnosis. Multiple diagnostic procedures were performed, until finally, endoscopically guided segmental gut lavage identified locally produced, intestinal IgE antibodies by fluoro-enzyme-immunoassay.IgE antibody concentrations at the intestinal level were found to be more-fold increased for total IgE and food-specific IgE against nuts, rye flour, wheat flour, pork, beef and egg yolk compared with healthy controls.Thus, a diet eliminating these allergens was introduced along with antihistamines and administration of a hypoallergenic formula, which resulted in complete healing of the multilocular ulcers with resolution of gastrointestinal bleeding. All gastrointestinal lesions disappeared and total serum IgE levels dropped to normal within 9 months. The patient has been in remission now for more than two years.Eosinophilic gastroenteritis (EG) is well known to induce refractory ulcer disease. In this case, the mechanisms for intestinal damage and gastrointestinal bleeding were identified as local gastrointestinal type I allergy. Therefore, future diagnostics in EG should also be focused on the intestinal level as identification of causative food-specific IgE antibodies proved to be effective to induce remission in this patient.
EVALuna2:1913

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Epithelial presenilin-1 drives colorectal tumour growth by controlling EGFR-COX2 signalling - Gámez Belmonte, Maria de los Reyes; Mahapatro, Mousumi; Erkert, Lena; Gonzalez Acera, Miguel; Naschberger, Elisabeth; Yu, Yuqiang; Tena-Garitaonaindia, Mireia; Patankar, Jay; Wagner, Yara; Podstawa, Eva; Schoedel, Lena; Bubeck, Marvin; et al. (Gut, 2022)
Objective Psen1 was previously characterised as a crucial factor in the pathogenesis of neurodegeneration in patients with Alzheimer's disease. Little, if any, is known about its function in the gut. Here, we uncovered an unexpected functional role of Psen1 in gut epithelial cells during intestinal tumourigenesis. Design Human colorectal cancer (CRC) and control samples were investigated for PSEN1 and proteins of the gamma-secretase complex. Tumour formation was analysed in the AOM-DSS and Apc (min/+) mouse models using newly generated epithelial-specific Psen1 deficient mice. Psen1 deficient human CRC cells were studied in a xenograft tumour model. Tumour-derived organoids were analysed for growth and RNA-Seq was performed to identify Psen1-regulated pathways. Tumouroids were generated to study EGFR activation and evaluation of the influence of prostanoids. Results PSEN1 is expressed in the intestinal epithelium and its level is increased in human CRC. Psen1-deficient mice developed only small tumours and human cancer cell lines deficient in Psen1 had a reduced tumourigenicity. Tumouroids derived from Psen1-deficient Apc (min/+) mice exhibited stunted growth and reduced cell proliferation. On a molecular level, PSEN1 potentiated tumour cell proliferation via enhanced EGFR signalling and COX-2 production. Exogenous administration of PGE(2) reversed the slow growth of PSEN1 deficient tumour cells via PGE(2) receptor 4 (EP4) receptor signalling. Conclusions Psen1 drives tumour development by increasing EGFR signalling via NOTCH1 processing, and by activating the COX-2-PGE(2) pathway. PSEN1 inhibition could be a useful strategy in treatment of CRC.
CRIS-Team WoS Importer:2022-11-04
Keywords: colorectal cancer; colorectal adenomas; arachidonic and metabolism

Epithelial RAC1-dependent cytoskeleton dynamics controls cell mechanics, cell shedding and barrier integrity in intestinal inflammation - Martínez Sánchez, Luz del Carmen; Phuong Anh Ngo,; Pradhan, Rashmita; Becker, Lukas S; Böhringer, David; Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Koch, Tatyana; Thonn, Veronika; Erkert, Lena; Stolzer, Iris; et al. (Gut, 2022)
Objective Increased apoptotic shedding has been linked to intestinal barrier dysfunction and development of inflammatory bowel diseases (IBD). In contrast, physiological cell shedding allows the renewal of the epithelial monolayer without compromising the barrier function. Here, we investigated the role of live cell extrusion in epithelial barrier alterations in IBD. Design Taking advantage of conditional GGTase and RAC1 knockout mice in intestinal epithelial cells (Pggt1b (i Delta IEC) and Rac1 (i Delta IEC) mice), intravital microscopy, immunostaining, mechanobiology, organoid techniques and RNA sequencing, we analysed cell shedding alterations within the intestinal epithelium. Moreover, we examined human gut tissue and intestinal organoids from patients with IBD for cell shedding alterations and RAC1 function. Results Epithelial Pggt1b deletion led to cytoskeleton rearrangement and tight junction redistribution, causing cell overcrowding due to arresting of cell shedding that finally resulted in epithelial leakage and spontaneous mucosal inflammation in the small and to a lesser extent in the large intestine. Both in vivo and in vitro studies (knockout mice, organoids) identified RAC1 as a GGTase target critically involved in prenylation-dependent cytoskeleton dynamics, cell mechanics and epithelial cell shedding. Moreover, inflamed areas of gut tissue from patients with IBD exhibited funnel-like structures, signs of arrested cell shedding and impaired RAC1 function. RAC1 inhibition in human intestinal organoids caused actin alterations compatible with arresting of cell shedding. Conclusion Impaired epithelial RAC1 function causes cell overcrowding and epithelial leakage thus inducing chronic intestinal inflammation. Epithelial RAC1 emerges as key regulator of cytoskeletal dynamics, cell mechanics and intestinal cell shedding. Modulation of RAC1 might be exploited for restoration of epithelial integrity in the gut of patients with IBD.
CRIS-Team WoS Importer:2022-03-25

Etrolizumab-s Does Not Induce Residual Trafficking of Regulatory T Cells - Schweda, Anna; Becker, Emily; Wiendl, Maximilian; Atreya, Raja; Atreya, Imke; Müller, Tanja; Neurath, Markus; Zundler, Sebastian (Inflammatory Bowel Diseases, 2022)
Background Blocking immune cell gut homing via α4β7 integrin with the monoclonal antibody vedolizumab is an established therapeutic strategy in inflammatory bowel disease. However, despite promising preclinical and phase 2 clinical data, the anti-β7 antibody etrolizumab yielded disappointing results in a large phase 3 trial program in UC. Mechanistic explanations are still lacking. We have recently shown that vedolizumab is associated with residual homing of regulatory T (Treg) cells in a certain exposure range and aimed to investigate whether a similar mechanism applies for etrolizumab. Methods We used flow cytometry, competitive dynamic adhesion, and transmigration assays to assess binding of the etrolizumab surrogate (etrolizumab-s) antibody FIB504 to Treg and effector T cells (Teff) and to explore the impact on cell trafficking. Results We observed only minimal differences in the binding of etrolizumab-s to Treg and Teff cells. Dynamic adhesion and transmigration of Treg and Teff cells was not substantially differentially affected at relevant concentrations. The β1+ and PI16+ Treg cells were only resistant to etrolizumab-s at low concentrations. Conclusions Etrolizumab does not seem to induce notable residual trafficking of Treg cells. Thus, the Teff overweight in the inflamed gut might persist despite reduced overall T cell recruitment. This might be one piece of the puzzle to explain recent clinical results in phase 3.
CRIS-Team WoS Importer:2022-07-22

Etrolizumab-s fails to control E-Cadherin-dependent co-stimulation of highly activated cytotoxic T cells - Wiendl, Maximilian; Dedden, Mark; Liu, Lijuan; Schweda, Anna; Paap, Eva-Maria; Ullrich, Karen; Hartmann, Leonie; Wieser, Luisa; Vitali, Francesco; Atreya, Imke; Müller, Tanja; Günther, Claudia; et al. (Nature Communications, 2024)
Despite promising preclinical and earlier clinical data, a recent phase III trial on the anti-β7 integrin antibody etrolizumab in Crohn’s disease (CD) did not reach its primary endpoint. The mechanisms leading to this outcome are not well understood. Here we characterize the β7+ T cell compartment from patients with CD in comparison to cells from individuals without inflammatory bowel disease. By flow cytometric, transcriptomic and functional profiling of circulating T cells, we find that triple-integrin-expressing (α4+β7+β1hi) T cells have the potential to home to the gut despite α4β7 blockade and have a specific cytotoxic signature. A subset of triple-integrin-expressing cells readily acquires αE expression and could be co-stimulated via E-Cadherin-αEβ7 interactions in vitro. Etrolizumab-s fails to block such αEβ7 signalling at high levels of T cell stimulation. Consistently, in CD patients treated with etrolizumab, T cell activation correlates with cytotoxic signatures. Collectively, our findings might add one important piece to the puzzle to explain phase III trial results with etrolizumab, while they also highlight that αEβ7 remains an interesting target for future therapeutic approaches in inflammatory bowel disease.
CRIS-Team Scopus Importer:2024-02-16

E-type prostanoid receptor 4 drives resolution of intestinal inflammation by blocking epithelial necroptosis - Patankar, Jay; Muller, Tanja M.; Kantham, Srinivas; Acera, Miguel Gonzalez; Mascia, Fabrizio; Scheibe, Kristina; Mahapatro, Mousumi; Heichler, Christina; Yu, Yuqiang; Li, Wei; Ruder, Barbara; Günther, Claudia; et al. (Nature Cell Biology, 2021)
Inflammatory bowel diseases present with elevated levels of intestinal epithelial cell (IEC) death, which compromises the gut barrier, activating immune cells and triggering more IEC death. The endogenous signals that prevent IEC death and break this vicious cycle, allowing resolution of intestinal inflammation, remain largely unknown. Here we show that prostaglandin E2 signalling via the E-type prostanoid receptor 4 (EP4) on IECs represses epithelial necroptosis and induces resolution of colitis. We found that EP4 expression correlates with an improved IBD outcome and that EP4 activation induces a transcriptional signature consistent with resolution of intestinal inflammation. We further show that dysregulated necroptosis prevents resolution, and EP4 agonism suppresses necroptosis in human and mouse IECs. Mechanistically, EP4 signalling on IECs converges on receptor-interacting protein kinase 1 to suppress tumour necrosis factor-induced activation and membrane translocation of the necroptosis effector mixed-lineage kinase domain-like pseudokinase. In summary, our study indicates that EP4 promotes the resolution of colitis by suppressing IEC necroptosis.
CRIS-Team WoS Importer:2021-07-23

Expansion of IL-23 receptor bearing TNFR2+ T cells is associated with molecular resistance to anti-TNF therapy in Crohn's disease - Schmitt, Heike; Billmeier, Ulrike; Dieterich, Walburga; Rath, Timo; Sonnewald, Sophia; Reid, Stephen; Hirschmann, Simon; Hildner, Kai; Waldner, Maximilian; Mudter, Jonas; Hartmann, Arndt; Grützmann, Robert; et al. (Gut, 2018)
OBJECTIVE: Anti-tumour necrosis factor (TNF) antibodies are successfully used for treatment of Crohn's disease. Nevertheless, approximately 40% of patients display failure to anti-TNF therapy. Here, we characterised molecular mechanisms that are associated with endoscopic resistance to anti-TNF therapy. DESIGN: Mucosal and blood cells were isolated from patients with Crohn's disease prior and during anti-TNF therapy. Cytokine profiles, cell surface markers, signalling proteins and cell apoptosis were assessed by microarray, immunohistochemistry, qPCR, ELISA, whole organ cultures and FACS. RESULTS: Responders to anti-TNF therapy displayed a significantly higher expression of TNF receptor 2 (TNFR2) but not IL23R on T cells than non-responders prior to anti-TNF therapy. During anti-TNF therapy, there was a significant upregulation of mucosal IL-23p19, IL23R and IL-17A in anti-TNF non-responders but not in responders. Apoptosis-resistant TNFR2+IL23R+ T cells were significantly expanded in anti-TNF non-responders compared with responders, expressed the gut tropic integrins α4β7, and exhibited increased expression of IFN-γ, T-bet, IL-17A and RORγt compared with TNFR2+IL23R- cells, indicating a mixed Th1/Th17-like phenotype. Intestinal TNFR2+IL23R+ T cells were activated by IL-23 derived from CD14+ macrophages, which were significantly more present in non-responders prior to anti-TNF treatment. Administration of IL-23 to anti-TNF-treated mucosal organ cultures led to the expansion of CD4+IL23R+TNFR2+ lymphocytes. Functional studies demonstrated that anti-TNF-induced apoptosis in mucosal T cells is abrogated by IL-23. CONCLUSIONS: Expansion of apoptosis-resistant intestinal TNFR2+IL23R+ T cells is associated with resistance to anti-TNF therapy in Crohn's disease. These findings identify IL-23 as a suitable molecular target in patients with Crohn's disease refractory to anti-TNF therapy.
EVALuna2:34305

Expansion of T memory stem cells with superior anti-tumor immunity by Urolithin A-induced mitophagy - Denk, Dominic; Petrocelli, Valentina; Conche, Claire; Drachsler, Moritz; Ziegler, Paul K.; Braun, Angela; Kress, Alena; Nicolas, Adele M.; Mohs, Kathleen; Becker, Christoph; Neurath, Markus; Farin, Henner F.; et al. (Immunity, 2022)
T memory stem cells (TSCM) display increased self-renewal and prolonged survival capabilities, thus preventing T cell exhaustion and promoting effective anti-tumor T cell responses. TSCM cells can be expanded by Urolithin A (UA), which is produced by the commensal gut microbiome from foods rich in ellagitannins and is known to improve mitochondrial health. Oral UA administration to tumor-bearing mice conferred strong anti-tumor CD8+ T cell immunity, whereas ex vivo UA pre-treated T cells displayed improved anti-tumor function upon adoptive cell transfer. UA-induced TSCM formation depended on Pink1-mediated mitophagy triggering cytosolic release of the mitochondrial phosphatase Pgam5. Cytosolic Pgam5 dephosphorylated β-catenin, which drove Wnt signaling and compensatory mitochondrial biogenesis. Collectively, we unravel a critical signaling pathway linking mitophagy to TSCM formation and suggest that the well-tolerated metabolic compound UA represents an attractive option to improve immune therapy.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anti-tumor immunity; mitophagy; T

Expression and function of α4β7 integrin predict the success of vedolizumab treatment in inflammatory bowel disease - Schneider, Ines; Allner, Clarissa; Mühl, Laura; Melde, Michaela; Lissner, Donata; Mantzivi, Eleni; Glauben, Rainer; Vitali, Francesco; Becker, Emily; Atreya, Imke; Müller, Tanja; Atreya, Raja; et al. (Translational Research, 2022)
Inflammatory bowel diseases are medically intractable and require constant therapy in many cases. While a growing number of biologicals and small molecules is available for treatment, a substantial portion of patients experiences primary non-response to these compounds and head-to-head evidence for therapy selection is scarce. Thus, approaches to predict treatment success in individual patients are a huge unmet need. We had previously suggested that the expression and function of α4β7 integrin on T cells in the peripheral blood correlate to outcomes of therapy with the anti-α4β7 integrin antibody vedolizumab. Here, we conducted a translational multicenter trial to prospectively evaluate this hypothesis. In a cohort of 89 patients with inflammatory bowel disease undergoing regular therapy with vedolizumab, lower baseline expression of α4β7 was associated with short-term clinical response. Consistently, low α4β7 expression in patients achieving remission predicted sustained remission in week 30. Moreover, high dynamic adhesion of CD4+ T cells to MAdCAM-1 and high reduction of adhesion by vedolizumab in vitro at baseline were associated with clinical remission. These data substantiate the potential of α4β7 integrin function and expression to forecast outcomes of vedolizumab therapy. Further translational efforts are necessary to improve the performance of the assays and to implement the concept in clinical practice.
CRIS-Team Scopus Importer:2023-01-31

Expression of inflammatory mediators in biofilm samples and clinical association in inflammatory bowel disease patients—a preliminary study - Buchbender, Mayte; Fehlhofer, Jakob Paul; Proff, Peter; Möst, Tobias; Ries, Jutta; Hannig, Matthias; Neurath, Markus; Gund, Madline; Atreya, Raja; Kesting, Marco Rainer (Clinical Oral Investigations, 2021)
Objectives: Inflammatory bowel disease (IBD) has multiple impacts on soft and hard tissues in the oral cavity. The aim of this study was to analyze the expression of cytokines in biofilm samples from patients suffering from IBD and compare them to healthy patients. It was hypothesized that different cytokine expression levels and clinical associations might be drawn. Material and methods: A total of 56 biofilm samples from three different patient cohorts (group 0 = healthy, HC n = 30; group 1 = Crohn’s disease, CD, n = 19; group 2 = ulcerative colitis, UC, n = 7) were examined for the expression levels of the cytokine interleukins IL-2, -6, and -10; matrix metalloproteinases 7 and 9; and surface antigens CD90/CD11a by quantitative real-time PCR and according to clinical parameters (plaque index, BOP, PD, DMFT, CAL). Relative gene expression was determined using the ∆∆CT method. Results: The mean BOP values (p = 0.001) and PD (p = 0.000) were significantly higher in the CD group compared to controls. Expression of IL-10 was significantly higher in the CD (p = 0.004) and UC groups (p = 0.022). Expression of MMP-7 was significantly higher in the CD group (p = 0.032). IBD patients treated with TNF inhibitors (p = 0.007) or other immunosuppressants (p = 0.014) showed significant overexpression of IL-10 compared to controls. Conclusion: Different expression levels of IL-10 and MMP-7 were detected in plaque samples from IBD patients. As only BOP was significantly increased, we conclude that no clinical impairment of periodontal tissue occurred in IBD patients. Clinical relevance: With the worldwide increasing incidence of IBD, it is important to obtain insights into the effects of the disease on the oral cavity. The study was registered (01.09.2020) at the German clinical trial registry (DRKS00022956). Clinical trial registration: The study is registered at the German clinical trial registry (DRKS00022956).
CRIS-Team Scopus Importer:2021-08-20
Keywords: Crohn’s disease; Cytokine expression; Oral biofilm; Periodontitis; Ulcerative colitis

Extensive small-bowel Crohn's disease detected by the newly introduced 360° panoramic viewing capsule endoscopy system - Tontini, Gian Eugenio; Cavallaro, Flaminia; Neumann, Helmut; Pastorelli, Luca; Neurath, Markus; Spina, Luisa; Vecchi, Maurizio (Endoscopy, 2014)
EVALuna2:1893

Extent of Mucosal Inflammation in Ulcerative Colitis Influences the Clinical Remission Induced by Vedolizumab - Scarozza, Patrizio; Marafini, Irene; Laudisi, Federica; Troncone, Edoardo; Schmitt, Heike; Lenti, Marco Vincenzo; Costa, Stefania; Rocchetti, Irene; De Cristofaro, Elena; Salvatori, Silvia; Frezzati, Ludovica; Di Sabatino, Antonio; et al. (Journal of Clinical Medicine, 2020)
Randomized controlled clinical trials and real-life observations indicate that less than 50% of patients with Crohn's disease (CD) or ulcerative colitis (UC) respond to vedolizumab, a humanized monoclonal antibody that blocks the alpha 4 beta 7 integrin. Since alpha 4 beta 7-expressing lymphocytes mainly infiltrate the left colon, we assessed whether localization of CD and UC influences vedolizumab-induced remission. One hundred and eighty-one patients (74 CD and 107 UC) receiving vedolizumab in 3 referral centers were retrospectively evaluated for clinical remission at week 14. Demographic and clinical characteristics were compared between remitters and non-responders, and multivariable multinomial analysis was performed to identify predictors of remission. Remission was achieved in 17 CD (23%) and 34 UC (32%) patients, respectively. In CD, localization of the lesions did not influence clinical remission. In UC, the remitters had more frequently a distal/left-sided colitis (21/34, 62%) as compared to the non-responders (9/47, 19%), and extensive colitis was more frequent in the non-responders (38/47, 81%) than in the remitters (13/34, 38%). The multivariable multinomial analysis showed that distal/left-sided colitis was associated with a higher probability of clinical remission while extensive colitis was inversely associated with induction of remission. Data indicate that UC patients with distal or left-sided colitis are more likely to achieve remission than patients with extensive colitis following vedolizumab treatment.
CRIS-Team WoS Importer:2020-03-24

Externalized decondensed neutrophil chromatin occludes pancreatic ducts and drives pancreatitis - Leppkes, Moritz; Maueröder, Christian; Hirth, Sebastian; Nowecki, Stefanie; Günther, Claudia; Billmeier, Ulrike; Paulus, Susanne; Biermann, Mona; Munoz, Luis Enrique; Hoffmann, Markus; Wildner, Dane; Croxford, Andrew L.; et al. (Nature Communications, 2016)
Ductal occlusion has been postulated to precipitate focal pancreatic inflammation, while the nature of the primary occluding agents has remained elusive. Neutrophils make use of histone citrullination by peptidyl arginine deiminase-4 (PADI4) in contact to particulate agents to extrude decondensed chromatin as neutrophil extracellular traps (NETs). In high cellular density, NETs form macroscopically visible aggregates. Here we show that such aggregates form inside pancreatic ducts in humans and mice occluding pancreatic ducts and thereby driving pancreatic inflammation. Experimental models indicate that PADI4 is critical for intraductal aggregate formation and that PADI4-deficiency abrogates disease progression. Mechanistically, we identify the pancreatic juice as a strong instigator of neutrophil chromatin extrusion. Characteristic single components of pancreatic juice, such as bicarbonate ions and calcium carbonate crystals, induce aggregated NET formation. Ductal occlusion by aggregated NETs emerges as a pathomechanism with relevance in a plethora of inflammatory conditions involving secretory ducts.
EVALuna2:2052

Extremely time-efficient Interval Endurance Training improves cardiometabolic Risk Profile and Inflammation Status for Obese Patient with increased risk of Metabolic Syndrome: A randomized-controlled Pilot Study - Reljic, Dejan; Frenk, Fabienne; Tobschall, Maike; Klaussner, Melanie; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (INTERNIST, 2019)
CRIS-Team WoS Importer:2019-05-17

Faecal Microbiota Therapy as a Treatment Option for a Clostridium difficile-induced toxic Megacolon - Konturek, Peter; Dieterich, Walburga; Hess, Thomas; Neurath, Markus; Zopf, Yurdagül (2018)
EVALuna2:35183

Feasibility and Efficacy of high intensity Interval Endurance Exercise (HIIT) in Tumor Patients: A systematic Overview with Meta-Analysis - Reljic, Dejan; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (2018)
EVALuna2:35186

Feasibility, Safety, and Preliminary Efficacy of Very Low-Volume Interval Training in Advanced Cancer Patients - Reljic, Dejan; Herrmann, Hans J.; Jakobs, Benedikt; Dieterich, Walburga; Mougiakakos, Dimitrios; Neurath, Markus; Zopf, Yurdagül (Medicine and science in sports and exercise, 2022)
Purpose High-intensity interval training (HIIT) has been shown to improve cardiorespiratory fitness (CRF) and health-related outcomes in various chronic diseases, including cancer. However, data on feasibility and efficacy of HIIT in advanced cancer patients are still sparse, presumably because of safety concerns, like suspected immunosuppression after vigorous exercise. This randomized, sham-intervention controlled study aimed to investigate feasibility, safety, and preliminary efficacy of very low-volume HIIT (LOW-HIIT) in advanced cancer patients. Methods Twenty-seven patients (55.4 ± 13.2 yr) with different advanced cancers (Union for International Cancer Control [UICC] III/IV) were randomly allocated to LOW-HIIT (n = 13), consisting of 5 × 1 min cycle ergometer intervals (14 min per session total duration) at 80% to 95% HRpeak (two sessions per week for 12 wk), or a sham intervention (n = 14) performing light physical mobilization exercises (SHAM). Primary outcomes were attrition and attendance rates, with values of ≤25% and ≥80%, respectively, considered acceptable. Secondary outcomes were safety, protocol fidelity, physiological (including CRF measures) and patient-reported outcomes (including fatigue and quality of life). Results One of 13 patients (8%) receiving LOW-HIIT dropped out. Mean attendance rate was 93%. The prescribed minimum exercise intensity was consistently reached by all patients. Low-volume HIIT was well tolerated and not associated with any serious adverse event nor with increased infection susceptibility. There were no biochemical signs of acute immunosuppression after LOW-HIIT. Contrarily, differentiation and degranulation of natural killer cells was acutely increased postexercise. Low-volume HIIT improved CRF measures including peak oxygen uptake, self-reported fatigue, physical, and social functioning. No significant changes occurred in the SHAM group. Conclusions Low-volume HIIT can be regarded as feasible and safe in advanced cancer patients. Our preliminary data indicate favorable acute effects on NK-cells and beneficial chronic adaptations in CRF, fatigue, and aspects of quality of life.
CRIS-Team Scopus Importer:2022-10-28
Keywords: AEROBIC EXERCISE; CARDIOPULMONARY FITNESS; HIIT; NK CELLS; ONCOLOGY; SUPPORTIVE CARE

First case report of exacerbated ulcerative colitis after anti-interleukin-6R salvage therapy - Atreya, Raja; Billmeier, Ulrike; Rath, Timo; Mudter, Jonas; Neumann, Helmut; Neurath, Markus; Vieth, Michael (World Journal of Gastroenterology, 2015)
We present the case of a 53-year-old woman with long-standing ulcerative colitis and severe, steroid-dependent disease course unresponsive to treatment with azathioprine, methotrexate, anti-TNF antibodies (infliximab, adalimumab) and tacrolimus, who refused colectomy as a therapeutic option. As the pro-inflammatory cytokine interleukin-6 (IL-6) had been identified as a crucial regulator in the immunopathogenesis of inflammatory bowel diseases, we treated the patient with biweekly intravenous infusions of an anti-IL-6R antibody (tocilizumab) for 12 wk. However, no clinical improvement of disease activity was noted. In fact, endoscopic, histological and endomicroscopic assessment demonstrated exacerbation of mucosal inflammation and ulcer formation upon anti-IL-6R therapy. Mechanistic studies revealed that tocilizumab treatment failed to suppress intestinal IL-6 production, impaired epithelial barrier function and induced production of pro-inflammatory cytokines such as TNF, IL-21 and IFN-?. Inhibition of IL-6 by tocilizumab had no clinical benefit in this patient with intractable ulcerative colitis and even led to exacerbation of mucosal inflammation. Our findings suggest that anti-IL-6R antibody therapy may lead to aggravation of anti-TNF resistant ulcerative colitis. When targeting IL-6, the differential responsiveness of target cells has to be taken into account, as IL-6 on the one side promotes acute and chronic mucosal inflammation via soluble IL-6R signaling but on the other side also strongly contributes to epithelial cell survival via membrane bound IL-6R signaling.
EVALuna2:2079

Food Intolerance of Unknown Origin: Caused by Mucosal Inflammation? A Pilot Study - Dieterich, Walburga; Tietz, Esther; Kohl, Matthias; Konturek, Peter C.; Rath, Timo; Neurath, Markus; Zopf, Yurdagül (Clinical and Translational Gastroenterology, 2021)
INTRODUCTION: The prevalence of patients with food intolerance (FI) has increased significantly. Immunoglobulin (Ig)E-mediated food allergies (FAs) are detected by determining IgE antibodies and skin prick test. Carbohydrate malabsorptions are clarified with breath tests. However, these diagnostic measures cannot capture all intolerances and have limitations in case of gut-mediated FI. The aims of this pilot study were to evaluate different methods to determine intestinal mucosal IgE in patients with FA and to characterize the intestinal mucosa in patients with FI of unknown origin (FH). METHODS: Patients with FA and FH were compared with healthy controls. To determine the IgE antibodies and the cytokines tumor necrosis factor (TNF)-α and interferon (IFN)-γ of the intestinal mucosal, a lavage was performed as part of an ileocolonoscopy and samples were taken using the cytobrush and biopsy forceps. In a subgroup, mucosal samples were also taken from the duodenum. RESULTS: Data in homogenates of intestinal mucosal samples yielded the highest sensitivity for IgE antibody titers compared with lavage and cytobrush. Patients with FA presented increased intestinal TNF-α and low IFN-γ values. This was in contrast to FH patients, who showed low intestinal IgE antibodies and TNF-α levels, but increased IFN-γ values. DISCUSSION: The determination of IgE antibodies to diagnose intestinal IgE-mediated FA is most reliable in intestinal mucosal samples. Increased TNF-α and low IFN-γ levels in patients with FA characterize an allergic reaction. Decreased TNF-α and increased IFN-γ levels in patients with FH indicate an inflammation-related intolerance reaction (see Visual Abstract, Supplementary Digital Content 1, http://links.lww.com/CTG/A520).
CRIS-Team Scopus Importer:2021-04-16

From bench to bedside: molecular imaging in inflammatory bowel diseases - Atreya, Raja; Neurath, Markus (Current Opinion in Gastroenterology, 2016)
Standard structural imaging procedures such as endoscopy, ultrasonography, or MRI are an integral part of the rational management of patients with inflammatory bowel diseases (IBDs). There is nevertheless the need for further refined imaging approaches that are able to overcome the limitations of currently used formats. The advent of molecular imaging modalities that allow real-time visualization of cellular processes not only in the preclinical setting but also in clinical trials has demonstrated its ability to improve current therapeutic strategies. The purpose of this review is to present and discuss advancements in the field of molecular imaging approaches in the IBD field.Recent preclinical and clinical studies have addressed the applicability of molecular imaging for improving the differentiation between benign and malignant mucosal alterations, increasing the detection of dysplastic intestinal lesions, and predicting individual responses to biological therapies.Molecular imaging in IBD represents an exciting and evolving field that has the potential to impact on current diagnostic and therapeutic algorithms in the treatment of IBD patients by analyzing and visualizing the molecular mechanisms that drive mucosal inflammation. It might enable us to base individualized therapeutic decisions on preceded molecular level analysis by suitable imaging modalities.
EVALuna2:2091

From physiology to disease and targeted therapy: interleukin-6 in inflammation and inflammation-associated carcinogenesis - Rath, Timo; Billmeier, Ulrike; Waldner, Maximilian; Atreya, Raja; Neurath, Markus (Archives of Toxicology, 2015)
Since its discovery in 1986, originally as B cell stimulating factor 2, the knowledge on IL-6 for immune homeostasis and its pathophysiological implications has rapidly increased. It is now clear that IL-6, alone or in combination with other cytokines, is an architect for shaping and generating immune responses which exerts profound activities on the induction of acute-phase reactions, the differentiation of B lymphocytes, the modulation of T cell apoptosis, the activation of T helper cells and the balance between regulatory T cells and Th17 cells. In parallel to the identification of these physiologic functions, IL-6 has emerged as a critical mediator for perpetuating chronic inflammation and autoimmunity and is increasingly recognized as a key cytokine for linking chronic inflammation to cancer development. In this review, we begin by briefly summarizing the molecular events of IL-6 regulation and signaling and then describe the role of IL-6 in orchestrating innate and adaptive immune responses and its immunopathological relevance for chronic inflammatory diseases. We further outline how IL-6 links chronic inflammation and cancer development and finally provide an outlook on novel therapeutic strategies targeting IL-6 signaling for the treatment of chronic inflammatory diseases and cancer.
EVALuna2:1974

From the surface to the single cell: Novel endoscopic approaches in inflammatory bowel disease - Rath, Timo; Tontini, Gian Eugenio; Neurath, Markus; Neumann, Helmut (World Journal of Gastroenterology, 2015)
Inflammatory bowel diseases (IBD) comprise the two major entities Crohn's disease and ulcerative colitis and endoscopic imaging of the gastrointestinal tract has always been an integral and central part in the management of IBD patients. Within the recent years, mucosal healing emerged as a key treatment goal in IBD that substantially decides about the clinical outcome of IBD patients, thereby demanding for a precise, timely and detailed endoscopic assessment of the mucosal inflammation associated with IBD. Further, molecular imaging has tremendously expanded the clinical utility and applications of modern endoscopy, now encompassing not only diagnosis, surveillance, and treatment but also the prediction of individual therapy response. Within this review we describe novel endoscopic approaches and advanced endoscopic imaging methods for the diagnosis, treatment and surveillance of IBD patients. We begin by providing an overview over novel and advanced imaging techniques such as magnification endoscopy and dye-based and dye-less chromoendoscopy, endomicroscopy and endocytoscopy. We then describe how these techniques can be utilized for the precise and ultrastructural assessment of mucosal inflammation and dysplasia development associated with IBD and outline how they have enabled the endoscopist to gain insight onto the cellular level in real-time. Finally, we provide an outlook on how molecular imaging has rapidly evolved in the recent past and can be used to make individual predictions about the therapeutic response towards biological treatment.
EVALuna2:2011

Functional Brain Imaging Reveals Rapid Blockade of Abdominal Pain Response Upon Anti-TNF Therapy in Crohn's Disease - Heß, Andreas; Roesch, Julie; Saake, Marc; Sergeeva, Marina; Hirschmann, Simon; Neumann, Helmut; Dörfler, Arnd; Neurath, Markus; Atreya, Raja (Gastroenterology, 2015)
EVALuna2:2003

Functional Contribution and Targeted Migration of Group-2 Innate Lymphoid Cells in Inflammatory Lung Diseases: Being at the Right Place at the Right Time - Wirtz, Stefan; Schulz-Kuhnt, Anja; Neurath, Markus; Atreya, Imke (Frontiers in Immunology, 2021)
During the last decade, group-2 innate lymphoid cells (ILC2s) have been discovered and successfully established as crucial mediators of lung allergy, airway inflammation and fibrosis, thus affecting the pathogenesis and clinical course of many respiratory diseases, like for instance asthma, cystic fibrosis and chronic rhinosinusitis. As an important regulatory component in this context, the local pulmonary milieu at inflammatory tissue sites does not only determine the activation status of lung-infiltrating ILC2s, but also influences their motility and migratory behavior. In general, many data collected in recent murine and human studies argued against the former concept of a very strict tissue residency of innate lymphoid cells (ILCs) and instead pointed to a context-dependent homing capacity of peripheral blood ILC precursors and the inflammation-dependent capacity of specific ILC subsets for interorgan trafficking. In this review article, we provide a comprehensive overview of the so far described molecular mechanisms underlying the pulmonary migration of ILC2s and thereby the numeric regulation of local ILC2 pools at inflamed or fibrotic pulmonary tissue sites and discuss their potential to serve as innovative therapeutic targets in the treatment of inflammatory lung diseases.
CRIS-Team WoS Importer:2021-07-09

Functional molecular network analysis enables prediction of response to vedolizumab therapy in anti-TNF refractory IBD patients - Breidert, Matthias; Eftekhari, Pierre; Louis, François; Rotoiu, Claudia; Rath, Timo; Neurath, Markus; Atreya, Raja (Crohn's & Colitis 360, 2020)
Background: We applied for the first time 2 label-free technologies, physiological intermolecular modulation spectroscopy (PIMS) and nematic protein organization technic (NPOT) in anti-tumor necrosis factor (TNF) refractory inflammatory bowel disease (IBD) patients to identify clinical responders to vedolizumab therapy and elucidate their underlying functional molecular network. Methods: PIMS analysis was performed in peripheral blood taken prior to the first vedolizumab application in 20 IBD patients (Crohn disease n = 13; ulcerative colitis n = 7) refractory to at least 1 previous anti-TNF agent therapy. Peripheral blood taken from clinical responders and nonresponders at week 14 of vedolizumab therapy were additionally subjected to NPOT analysis. Response to therapy was assessed by respective clinical disease activity scores (partial Mayo Score and Harvey-Bradshaw Index). Results: Clinical response to vedolizumab treatment was observed in 7 of 13 Crohn disease and 4 of 7 ulcerative colitis patients at week 14. Response to therapy was accurately predicted by PIMS blood analysis in 100% of ulcerative colitis and 77% of Crohn disease patients. Overall prediction of clinical response with PIMS blood analysis was achieved with a 89% positive predictive value and a 82% negative predictive value. NPOT analysis revealed the heightened expression of the proteins ITGB7, ITGAV, ITG3, PF4, and ASGH in the peripheral blood of vedolizumab responders compared to nonresponders. Conclusions: PIMS analysis of the blood of anti-TNF refractory IBD patients was able to stratify responders to vedolizumab therapy with high accuracy and specificity. NPOT technology could decipher underling molecular networks in the blood of responders, enabling subsequent personalized therapeutic approaches in IBD.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Anti-TNF antibody; Inflammatory bowel disease; Nematic protein organization technic (NPOT); Physiological intermolecular modification spectroscopy (PIMS); Responder interactors; Vedolizumab

Functional role of the Tec kinase ITK in the pathogenesis of inflammatory bowel disease - Lechner, K.; Neurath, Markus; Weigmann, Benno (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Further efficacy and safety data for maintenance upadacitinib in ulcerative colitis - Atreya, Raja; Neurath, Markus (Lancet Gastroenterology and Hepatology, 2023)
CRIS-Team Scopus Importer:2023-10-06

Gastric hyperplastic polyps (hyperplasiogenic polyps): a constant debate! - Neurath, Markus; Vieth, Michael (Endoscopy, 2021)
CRIS-Team WoS Importer:2021-01-29

GastroDigitalShirt: A smart shirt for digestion acoustics monitoring - Baronetto, Annalisa; Graf, Luisa; Fischer, Sören; Neurath, Markus; Amft, Oliver (Proceedings - International Symposium on Wearable Computers, ISWC, 2020)
We present the GastroDigitalShirt, a smart T-Shirt for capturing abdominal sounds produced during digestion. The garment prototype embeds an array of eight miniaturised microphones connected to a low-power wearable computer and is designed for long-term recording. We present the microphone integration and shirt wiring layout. With the GastroDigitalShirt we monitored the different digestion phases over six hours in four healthy participants with no prior gastro-intestinal diseases. The collected data were annotated by two independent raters to mark Bowel Sounds (BS) instances. The interrater agreement was substantial, with Cohen's Kappa of 0.7, confirming a consistent labeling approach. Overall 3046 BS instances were individually annotated. The extracted BS were structured by Hierarchical Agglomerative Clustering. The analysis highlighted the presence of 4 BS types. The results show that our prototype can capture the main BS types reported in literature.
CRIS-Team Scopus Importer:2020-11-13
Keywords: bowel sounds; smart garments; wearable sensors

Gastrointestinal microbiome in Parkinson's disease in a Bavarian cohort - Marxreiter, Franz; Cosma-Grigorov, Alexandra; Gaßner, Heiko; Meixner, Holger; Kohl, Zacharias; Neurath, Markus; Wirtz, Stefan; Winkler, Jürgen (2019)
EVALuna2:209001

Glucose-Restricted Diet Regulates the Tumor Immune Microenvironment and Prevents Tumor Growth in Lung Adenocarcinoma - Gähler, Alexander; Trufa, Denis; Chiriac, Mircea-Teodor; Tausche, Patrick; Hohenberger, Katja; Brunst, Ann-Kathrin; Rauh, Manfred; Geppert, Carol-Immanuel; Rieker, Ralf; Krammer, Susanne; Leberle, Anna; Neurath, Markus; et al. (Frontiers in Oncology, 2022)
BackgroundLung cancer is the second common cancer type in western countries and has a high mortality. During the development and progression of the tumor, the nutrients in its environment play a central role. The tumor cells depend crucially on glucose metabolism and uptake. Tumor cell metabolism is dominated by the Warburg effect, where tumor cells produce large amounts of lactate from pyruvate under aerobic conditions. We thus reasoned that, reducing carbohydrates in the diet might support anti-tumoral effects of current immunotherapy and additionally target tumor immune escape. ObjectivesThe link between reducing carbohydrates to improve current immunotherapy is not clear. We thus aimed at analyzing the effects of different glucose levels on the tumor development, progression and the anti-tumoral immune response. MethodsWe correlated the clinical parameters of our LUAD cohort with different metabolic markers. Additionally, we performed cell culture experiments with A549 tumor cell line under different glucose levels. Lastly, we investigated the effect of low and high carbohydrate diet in an experimental murine model of lung cancer on the tumor progression and different immune subsets. ResultsHere we found a positive correlation between the body mass index (BMI), blood glucose levels, reduced overall survival (OS) and the expression of Insulin-like growth factor-1 receptor (IGF1R) in the lung tumoral region of patients with lung adenocarcinoma (LUAD). Furthermore, increasing extracellular glucose induced IGF1R expression in A549 LUAD cells. Functional studies in a murine model of LUAD demonstrated that, glucose restricted diet resulted in decreased tumor load in vivo. This finding was associated with increased presence of lung infiltrating cytotoxic CD8+ T effector memory (TEM), tissue resident memory T (TRM) and natural killer cells as well as reduced IGFR mRNA expression, suggesting that glucose restriction regulates lung immunity in the tumor microenvironment. ConclusionsThese results indicate that, glucose restricted diet improves lung immune responses of the host and suppresses tumor growth in experimental lung adenocarcinoma. As glucose levels in LUAD patients were negatively correlated to postoperative survival rates, glucose-restricted diet emerges as therapeutic avenue for patients with LUAD.
CRIS-Team WoS Importer:2022-05-27

Good Manufacturing Practice-Compliant Production and Lot-Release ofEx VivoExpanded Regulatory T Cells As Basis for Treatment of Patients with Autoimmune and Inflammatory Disorders - Wiesinger, Manuel; Stoica, Diane; Roessner, Susanne; Lorenz, Carmen; Fischer, Anika; Atreya, Raja; Neufert, Clemens; Atreya, Imke; Scheffold, Alexander; Schuler-Thurner, Beatrice; Neurath, Markus; Schuler, Gerold; et al. (Frontiers in Immunology, 2017)
In recent years, the exploration of regulatory T cell (Treg)-based cellular therapy has become an attractive strategy to ameliorate inflammation and autoimmunity in various clinical settings. The main obstacle to the clinical application of Treg in human is their low number circulating in peripheral blood. Therefore,ex vivoexpansion is inevitable. Moreover, isolation of Treg bears the risk of concurrent isolation of unwanted effector cells, which may trigger or deteriorate inflammation upon adoptive Treg transfer. Here, we present a protocol for the GMP-compliant production, lot-release and validation ofex vivoexpanded Tregs for treatment of patients with autoimmune and inflammatory disorders. In the presented production protocol, large numbers of Treg, previously enriched from a leukapheresis product by using the CliniMACS®system, areex vivoexpanded in the presence of anti-CD3/anti-CD28 expander beads, exogenous IL-2 and rapamycin during 21 days. The expanded Treg drug product passed predefined lot-release criteria. These criteria include (i) sterility testing, (ii) assessment of Treg phenotype, (iii) assessment of non-Treg cellular impurities, (iv) confirmation of successful anti-CD3/anti-CD28 expander bead removal after expansion, and (v) confirmation of the biological function of the Treg product. Furthermore, the Treg drug product was shown to retain its stability and suppressive function for at least 1 year after freezing and thawing. Also, dilution of the Treg drug product in 0.9% physiological saline did not affect Treg phenotype and Treg function for up to 90 min. These data indicate that these cells are ready to use in a clinical setting in which a cell infusion time of up to 90 min can be expected. The presented production process has recently undergone on site GMP-conform evaluation and received GMP certification from the Bavarian authorities in Germany. This protocol can now be used for Treg-based therapy of various inflammatory and autoimmune disorders.
EVALuna2:33800

Gp96 Peptide Antagonist gp96-II Confers Therapeutic Effects in Murine Intestinal Inflammation - Nold-Petry, Claudia A.; Nold, Marcel F.; Levy, Ofer; Kliger, Yossef; Oren, Anat; Borukhov, Itamar; Becker, Christoph; Wirtz, Stefan; Sandhu, Manjeet K.; Neurath, Markus; Dinarello, Charles A. (Frontiers in Immunology, 2017)
Background: The expression of heat shock protein gp96 is strongly correlated with the degree of tissue inflammation in ulcerative colitis and Crohn's disease, thereby leading us to the hypothesis that inhibition of expression via gp96-II peptide prevents intestinal inflammation. Methods: We employed daily injections of gp96-II peptide in two murine models of intestinal inflammation, the first resulting from five daily injections of IL-12/IL-18, the second via a single intrarectal application of TNBS (2,4,6-trinitrobenzenesulfonic acid). We also assessed the effectiveness of gp96-II peptide in murine and human primary cell culture. Results: In the IL-12/IL-18 model, all gp96-II peptide-treated animals survived until day 5, whereas 80% of placebo-injected animals died. gp96-II peptide reduced IL-12/IL-18-induced plasma IFNγ by 89%, IL-1β by 63%, IL-6 by 43% and tumor necrosis factor (TNF) by 70% compared to controls. The clinical assessment Disease Activity Index of intestinal inflammation severity was found to be significantly lower in the gp96-II-treated animals when compared to vehicle-injected mice. gp96-II peptide treatment in the TNBS model limited weight loss to 5% on day 7 compared with prednisolone treatment, whereas placebo-treated animals suffered a 20% weight loss. Histological disease severity was reduced equally by prednisolone (by 40%) and gp96-II peptide (35%). Mice treated with either gp96-II peptide or prednisolone exhibited improved endoscopic scores compared with vehicle-treated control mice: vascularity, fibrin, granularity, and translucency scores were reduced by up to 49% by prednisolone and by up to 30% by gp96-II peptide. In vitro, gp96-II peptide reduced TLR2-, TLR4- and IL-12/IL-18-induced cytokine expression in murine splenocytes, with declines in constitutive IL-6 (54%), lipopolysaccharide-induced TNF (48%), IL-6 (81%) and in Staphylococcus epidermidis-induced TNF (67%) and IL-6 (81%), as well as IL-12/IL-18-induced IFNγ (75%). gp96-II peptide reduced IL-1β, IL-6, TNF and GM-CSF in human peripheral blood mononuclear cells to a similar degree without affecting cell viability, whereas RANTES, IL-25 and MIF were twofold to threefold increased. Conclusion: gp96-II peptide protects against murine intestinal inflammation by regulating inflammation in vivo and in vitro, pointing to its promise as a novel treatment for inflammatory bowel disease.
EVALuna2:33887

Group 2 Innate Lymphoid Cells (ILC2) Suppress Beneficial Type 1 Immune Responses During Pulmonary Cryptococcosis - Kindermann, Markus; Knipfer, Lisa; Obermeyer, Stephanie; Müller, Uwe; Alber, Gottfried; Bogdan, Christian; Schleicher, Ulrike; Neurath, Markus; Wirtz, Stefan (Frontiers in Immunology, 2020)
Cryptococcus neoformans is an opportunistic fungal pathogen preferentially causing disease in immunocompromised individuals such as organ-transplant-recipients, patients receiving immunosuppressive medications or, in particular, individuals suffering from HIV infection. Numerous studies clearly indicated that the control of C. neoformans infections is strongly dependent on a prototypic type 1 immune response and classical macrophage activation, whereas type 2-biased immunity and alternative activation of macrophages has been rather implicated in disease progression and detrimental outcomes. However, little is known about regulatory pathways modulating and balancing immune responses during early phases of pulmonary cryptococcosis. Here, we analyzed the role of group 2 innate lymphoid cells (ILC2s) for the control of C. neoformans infection. Using an intranasal infection model with a highly virulent C. neoformans strain, we found that ILC2 numbers were strongly increased in C. neoformans-infected lungs along with induction of a type 2 response. Mice lacking ILC2s due to conditional deficiency of the transcription factor RAR-related orphan receptor alpha (Rora) displayed a massive downregulation of features of type 2 immunity as reflected by reduced levels of the type 2 signature cytokines IL-4, IL-5, and IL-13 at 14 days post-infection. Moreover, ILC2 deficiency was accompanied with increased type 1 immunity and classical macrophage activation, while the pulmonary numbers of eosinophils and alternatively activated macrophages were reduced in these mice. Importantly, this shift in pulmonary macrophage polarization in ILC2-deficient mice correlated with improved fungal control and prolonged survival of infected mice. Conversely, adoptive transfer of ILC2s was associated with a type 2 bias associated with less efficient anti-fungal immunity in lungs of recipient mice. Collectively, our date indicate a non-redundant role of ILC2 in orchestrating myeloid anti-cryptococcal immune responses toward a disease exacerbating phenotype.
CRIS-Team Scopus Importer:2020-03-10
Keywords: fungi (Candida; Cryptococcus); ILC2; innate immunity; lung infection; type 2 immune response

Guided Multispectral Optoacoustic Tomography for 3D Imaging of the Murine Colon - Knieling, Ferdinand; Brown, Emma L.; Eckstein, Markus; Thoma, Oana-Maria; Wachter, Felix; Mandelbaum, Henriette; Ludwig, Petra; Claßen, Merle; Oraiopoulou, Mariam Eleni; Rother, Ulrich; Neurath, Markus; Wölfle, Joachim; et al. (Advanced Science, 2025)
Multispectral optoacoustic tomography is a promising medical imaging modality that combines light and sound to provide molecular imaging information at depths of several centimeters, based on the optical absorption of endogenous chromophores, such as hemoglobin. Assessment of inflammatory bowel disease has emerged as a promising clinical application of optoacoustic tomography. In this context, preclinical studies in animal models are essential to identify novel disease-specific imaging biomarkers and understand findings from emerging clinical pilot studies, however to-date, these studies have been limited by the precise identification of the bowel wall. Herein, a transrectal-absorber guide is applied, serving as a high-contrast landmark for 3D optoacoustic tomography of the colon. This study shows that guided multispectral optoacoustic tomography is able to measure changes in blood oxygenation status over the course of acute, chemically-induced colitis in mice and correlates with standard disease activity scores. This novel approach depicts intestinal hemoglobin composition non-invasively during murine inflammation. These results underscore the potential for optoacoustic imaging in translational inflammatory bowel disease research.
CRIS-Team Scopus Importer:2025-01-31
Keywords: dextran sodium sulfate induced colitis; inflammatory bowel disease; multispectral optoacoustic tomography; murine acute colitis; optoacoustic imaging; photoacoustic imaging

Gut as viral reservoir: Lessons from gut viromes, HIV and COVID-19 - Neurath, Markus; Überla, Klaus; Ng, Siew C. (Gut, 2021)
CRIS-Team Scopus Importer:2021-05-07
Keywords: immunology

Gut immune cell trafficking: inter-organ communication and immune-mediated inflammation - Zundler, Sebastian; Günther, Claudia; Kremer, Andreas E.; Rothhammer, Veit; Neurath, Markus; Zaiss, Mario (Nature Reviews Gastroenterology & Hepatology, 2022)
Immune cell trafficking is a complex and tightly regulated process that is indispensable for the body’s fight against pathogens. However, it is also increasingly acknowledged that dysregulation of cell trafficking contributes to the pathogenesis of immune-mediated inflammatory diseases (IMIDs) in gastroenterology and hepatology, such as inflammatory bowel disease and primary sclerosing cholangitis. Moreover, altered cell trafficking has also been implicated as a crucial step in the immunopathogenesis of other IMIDs, such as rheumatoid arthritis and multiple sclerosis. Over the past few years, a central role of the gut in mediating these disorders has progressively emerged, and the partly microbiota-driven imprinting of particular cell trafficking phenotypes in the intestine seems to be crucially involved. Therefore, this Review highlights achievements in understanding immune cell trafficking to, within and from the intestine and delineates its consequences for immune-mediated pathology along the gut–liver, gut–joint and gut–brain axes. We also discuss implications for current and future therapeutic approaches that specifically interfere with homing, retention, egress and recirculation of immune cells.
CRIS-Team Scopus Importer:2022-08-26

Gut⁻Liver Axis: How Do Gut Bacteria Influence the Liver? - Konturek, Peter Christopher; Harsch, Igor Alexander; Konturek, Kathrin; Schink, Monic; Konturek, Thomas; Neurath, Markus; Zopf, Yurdagül (Medical Sciences, 2018)
Chronic liver diseases are a major cause of morbidity and mortality worldwide. Recently, gut dysbiosis was identified as an important factor in the pathogenesis of liver diseases. The relationship between gut microbiota and the liver is still not well understood; however, dysfunction of the gut mucosal barrier ("leaky gut") and increased bacterial translocation into the liver via the gut⁻liver axis probably play crucial roles in liver disease development and progression. The liver is an important immunological organ, and, after exposure to gut-derived bacteria via portal circulation, it responds with activation of the innate and adaptive immune system, leading to hepatic injury. A better understanding of the pathophysiological links among gut dysbiosis, the integrity of the gut barrier, and the hepatic immune response to gut-derived factors is essential for the development of new therapies to treat chronic liver diseases.
CRIS-Team Scopus Importer:2023-03-23
Keywords: chronic liver diseases; dysbiosis; gut microbiota

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

Healing of the epithelial barrier in the ileum is superior to endoscopic and histologic remission for predicting major adverse outcomes in ulcerative colitis - Rath, Timo; Atreya, Raja; Bodenschatz, Julia; Uter, Wolfgang; Geppert, Carol-Immanuel; Vitali, Francesco; Zundler, Sebastian; Waldner, Maximilian; Hartmann, Arndt; Neurath, Markus (Frontiers in Medicine, 2023)
Background: Achieving endoscopic remission is a key therapeutic goal in patients with ulcerative colitis (UC) that is associated with favorable long-term disease outcomes. Here, we prospectively compared the predictive value of endoscopic and/or histologic remission against ileal barrier healing for predicting long-term disease behavior in a large cohort of UC patients in clinical remission. Methods: At baseline, UC patients in clinical remission underwent ileocolonoscopy with assessment of ileal barrier function by confocal endomicroscopy. Endoscopic and histologic disease activity and ileal barrier healing were scored using validated scores. During subsequent follow-up (FU), patients were closely monitored for clinical disease activity and occurrence of major adverse outcomes (MAO) defined as the following: disease relapse; UC-related hospitalization; UC-related surgery; necessity for initiation or dose escalation of systemic steroids, immunosuppressants, small molecules or biological therapy. Results: Of the 73 UC patients included, 67% experienced MAO during a mean FU of 25 months. The probability of MAO-free survival was significantly higher in UC patients with endoscopic and/or histologic remission compared to patients with endoscopically and/or histologically active disease. Ileal barrier healing on endomicroscopy was highly accurate for predicting the further course of UC and outcompeted endoscopic and histologic remission for predicting MAO-free survival. Conclusion: Ileal barrier healing in clinically remittent UC patients can accurately predict future MAO development and is superior in its predictive capabilities than endoscopic and histologic remission. Ileal barrier healing therefore represents a novel and superior surrogate parameter for stratification of UC patients according to their risk for development of complicated disease behavior. Clinical trial registration: https://classic.clinicaltrials.gov/ct2/show/NCT05157750, identifier NCT05157750.
CRIS-Team Scopus Importer:2023-11-03
Keywords: endoscopy; histology; inflammatory bowel diseases; intestinal barrier; ulcerative colitis

High-definition endoscopy with digital chromoendoscopy for histologic prediction of distal colorectal polyps - Rath, Timo; Tontini, Gian E.; Naegel, Andreas; Zopf, Steffen; Günther, Claudia; Hoffman, Arthur; Neurath, Markus; Neumann, Helmut; Vieth, Michael (BMC Gastroenterology, 2015)
Distal diminutive colorectal polyps are common and accurate endoscopic prediction of hyperplastic or adenomatous polyp histology could reduce procedural time, costs and potential risks associated with the resection. Within this study we assessed whether digital chromoendoscopy can accurately predict the histology of distal diminutive colorectal polyps according to the ASGE PIVI statement.In this prospective cohort study, 224 consecutive patients undergoing screening or surveillance colonoscopy were included. Real time histology of 121 diminutive distal colorectal polyps was evaluated using high-definition endoscopy with digital chromoendoscopy and the accuracy of predicting histology with digital chromoendoscopy was assessed.The overall accuracy of digital chromoendoscopy for prediction of adenomatous polyp histology was 90.1 %. Sensitivity, specificity, positive and negative predictive values were 93.3, 88.7, 88.7, and 93.2 %, respectively. In high-confidence predictions, the accuracy increased to 96.3 % while sensitivity, specificity, positive and negative predictive values were calculated as 98.1, 94.4, 94.5, and 98.1 %, respectively. Surveillance intervals with digital chromoendoscopy were correctly predicted with >90 % accuracy.High-definition endoscopy in combination with digital chromoendoscopy allowed real-time in vivo prediction of distal colorectal polyp histology and is accurate enough to leave distal colorectal polyps in place without resection or to resect and discard them without pathologic assessment. This approach has the potential to reduce costs and risks associated with the redundant removal of diminutive colorectal polyps.ClinicalTrials NCT02217449 .
EVALuna2:1977

High-definition endoscopy with iScan and Lugol's solution for the detection of inflammation in patients with nonerosive reflux disease: histologic evaluation in comparison with a control group - Rey, J. W.; Deris, N.; Marquardt, J. U.; Thomaidis, T.; Moehler, M.; Kittner, J. M.; Nguyen-Tat, M.; Duemcke, S.; Tresch, A.; Biesterfeld, S.; Goetz, M.; Mudter, J.; et al. (Diseases of the Esophagus, 2016)
Nonerosive reflux disease (NERD) is commonly diagnosed in patients with symptoms of reflux. The aim of the present study was to determine whether high-definition endoscopy (HD) plus equipped with the iScan function or chromoendoscopy with Lugol's solution might permit the differentiation of NERD patients from those without reflux symptoms, proven by targeted biopsies of endoscopic lesions. A total of 100 patients without regular intake of proton pump inhibitors and with a normal conventional upper endoscopy were prospectively divided into NERD patients and controls. A second upper endoscopy was performed using HD+ with additional iScan function and then Lugol's solution was applied. Biopsy specimens were taken from the gastroesophageal junction in all patients. A total of 65 patients with reflux symptoms and 27 controls were included. HD(+) endoscopy with iScan revealed subtle mucosal breaks in 52 patients; the subsequent biopsies confirmed esophagitis in all cases. After Lugol's solution, 58 patients showed mucosal breaks. Sensitivity for the iScan procedure was 82.5%, whereas that for Lugol's solution was 92.06%. Excellent positive predictive values of 100% and 98.3%, respectively, were noted. The present study suggests that the majority of patients with NERD and typical symptoms of reflux disease can be identified by iScan or Lugol's chromoendoscopy as minimal erosive reflux disease (ERD) patients.
EVALuna2:2096

High-definition endoscopy with i-scan enables diagnosis of characteristic mucosal lesions in Whipple's disease - Neumann, Helmut; Neufert, Clemens; Vieth, M.; Siebler, Jürgen; Mönkemüller, K.; Neurath, Markus (Endoscopy, 2012)
CRIS-Team Scopus Importer:2025-03-05

High-protein Nutrition and Whole-body Electromyostimulation in Hematologic-oncological Patients: Is a new Option? - Reljic, Dejan; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (2018)
EVALuna2:35185

High-resolution quantitative computed tomography demonstrates structural defects in cortical and trabecular bone in IBD patients. - Haschka, Judith; Hirschmann, Simon; Kleyer, Arnd; Englbrecht, Matthias; Faustini, Francesca; Simon, David; Figueiredo, Camille P; Schuster, Louis; Muschitz, Christian; Kocijan, Roland; Resch, Heinrich; Atreya, Raja; et al. (Journal of Crohns & Colitis, 2016)
Background and Aims To investigate the macro- and microstructural changes of bone in patients with inflammatory bowel disease (IBD) and to define the factors associated with bone loss in IBDMethods A total of148 subjects, 59 with Crohn's Disease (CD), 39 with Ulcerative Colitis (UC) and 50 healthy controls were assessed for the geometric, volumetric and microstructural properties of bone using high-resolution peripheral quantitative computed tomography. In addition, demographic and disease-specific characteristics of IBD patients were recorded.Results IBD patients and controls were comparable in age, sex and body mass index. Total (p=0.001), cortical (p<0.001) and trabecular volumetric BMD (p=0.03) were significantly reduced in IBD patients compared to healthy controls. Geometric and microstructure analysis revealed significantly lower cortical area (p=0.001) and cortical thickness (p<0.001) without differences in cortical porosity, pore volume or pore diameter. CD showed a more severe bone phenotype than UC: While cortical bone loss was observed in both diseases, CD additionally showed profound trabecular bone loss with reduced trabecular BMD (p=0.008), bone volume (p=0.008) and trabecular thickness (p=0.009).Multivariate regression models identified the diagnosis of CD, female sex, lower body mass index and the lack of remission as factors independently associated with bone loss in IBD.Conclusion IBD patients develop significant cortical bone loss impairing bone strength. Trabecular bone loss is limited to CD patients, which exhibits a more severe bone phenotype compared to UC patients.
EVALuna2:2046

“HIIT the Inflammation”: Comparative Effects of Low-Volume Interval Training and Resistance Exercises on Inflammatory Indices in Obese Metabolic Syndrome Patients Undergoing Caloric Restriction - Reljic, Dejan; Dieterich, Walburga; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (Nutrients, 2022)
Exercise is a cornerstone in metabolic syndrome (MetS) treatment. However, the effects of low-volume exercise modalities on MetS-associated low-grade inflammation are unclear. A total of 106 MetS patients (53.7 ± 11.4 years) were randomized to low-volume high-intensity interval training (LOW-HIIT, 14 min/session), single-set resistance training (1-RT, 15 min/session), whole-body electromyostimulation (WB-EMS, 20 min/session), three-set resistance training (3-RT, 50 min/session), each performed 2 ×/week for 12 weeks, or a control group (CON). All groups received nutritional counseling for weight loss. Inflammatory and cardiometabolic indices were analyzed pre-and post-intervention. All groups significantly reduced body weight by an average of 3.6%. Only LOW-HIIT reduced C-reactive protein (CRP) (−1.6 mg/L, p = 0.001) and interleukin-6 (−1.1 pg/mL, p = 0.020). High-sensitivity CRP and lipopolysaccharide-binding protein decreased following LOW-HIIT (−1.4 mg/L, p = 0.001 and −2.1 ng/mL, p = 0.004) and 3-RT (−0.6 mg/L, p = 0.044 and −2.0 ng/mL, p < 0.001). MetS severity score improved with LOW-HIIT (−1.8 units, p < 0.001), 1-RT (−1.6 units, p = 0.005), and 3-RT (−2.3 units, p < 0.001). Despite similar effects on body weight, low-volume exercise modalities have different impact on inflammatory and cardiometabolic outcomes in MetS patients. LOW-HIIT has superior efficacy for improving inflammation compared to 1-RT and WB-EMS. Resistance-based exercise appears to require a higher volume to promote beneficial impact on inflammation.
CRIS-Team Scopus Importer:2022-05-20
Keywords: cardiometabolic health; CRP; high-intensity interval training; obesity; single-set resistance training; whole-body electromyostimulation

Hobit- and Blimp-1-driven CD4(+) tissue-resident memory T cells control chronic intestinal inflammation - Zundler, Sebastian; Becker, Emily; Spocinska, Marta; Slawik, Monique; Parga-Vidal, Loreto; Stark, Regina; Wiendl, Maximilian; Atreya, Raja; Rath, Timo; Leppkes, Moritz; Hildner, Kai; Lopez Posadas, Rocío; et al. (Nature Immunology, 2019)
Although tissue-resident memory T cells (T-RM cells) have been shown to regulate host protection in infectious disorders, their function in inflammatory bowel disease (IBD) remains to be investigated. Here we characterized T-RM cells in human IBD and in experimental models of intestinal inflammation. Pro-inflammatory T-RM cells accumulated in the mucosa of patients with IBD, and the presence of CD4(+)CD69(+)CD103(+) T-RM cells was predictive of the development of flares. In vivo, functional impairment of T-RM cells in mice with double knockout of the T-RM-cell-associated transcription factors Hobit and Blimp-1 attenuated disease in several models of colitis, due to impaired cross-talk between the adaptive and innate immune system. Finally, depletion of T-RM cells led to a suppression of colitis activity. Together, our data demonstrate a central role for T-RM cells in the pathogenesis of chronic intestinal inflammation and suggest that these cells could be targets for future therapeutic approaches in IBD.
CRIS-Team WoS Importer:2019-03-06

Hobit- and Blimp1-driven tissue resident memory T cells critically control chronic intestinal inflammation - Zundler, Sebastian; Becker, E.; Spocinska, M.; Parga-Vidal, L.; Stark, R.; Atreya, Raja; Rath, T.; Leppkes, Moritz; Neufert, Clemens; Atreya, I.; Van Gisbergen, K.; Neurath, Markus (2018)
EVALuna2:34078

Host–microbiota interactions in inflammatory bowel disease - Neurath, Markus (Nature Reviews Gastroenterology & Hepatology, 2019)
CRIS-Team Scopus Importer:2019-12-31

How Much Liver Tissue Is Required for Sufficient Histological Staging in Patients with Primary Biliary Cholangitis? - Vetter, Marcel; Kremer, Andreas; Agaimy, Abbas; Pfeifer, Lukas; Neurath, Markus; Zopf, Steffen; Siebler, Jürgen (Digestion, 2020)
Introduction: Histological alterations in primary biliary cholangitis (PBC) are heterogeneously distributed throughout the liver. Thus, the quality of histological staging is probably dependent on the available amount of liver tissue. The goals of this study were to test this hypothesis and to define biopsy conditions for obtaining sufficient tissue. Methods: In this retrospective analysis, we investigated 34 patient cases who fulfilled the criteria of the European Association for the Study of the Liver (EASL) for PBC and underwent a mini-laparoscopic liver biopsy between 2011 and 2018 using 16 or 18G needles. For histological assessment of fibrosis, we used the Ishak score, and the amount of tissue was measured by the number of portal fields. Histological staging was compared with the macroscopic mini-laparoscopic fibrosis score (MLFS), and non-invasive liver stiffness measurements using acoustic radiation force impulse (ARFI) imaging and the FIB-4 score. Results: Biopsy was successful in 33 of 34 patients (97%). Fibrosis assessment by MLFS and ARFI correlated strongly with each other (r = 0.7088, p = 0.000017). However, the correlation of both methods with the histological staging was weaker (MLFS vs. histology: r = 0.4231, p = 0.0142; ARFI vs. histology: r = 0.3564, p = 0.0577). The correlation of ARFI and MLFS with the histological staging was better in the subgroup of biopsies with at least 10 portal fields (= SG≥10PF) (MLFS vs. histology: r = 0.6369, p = 0.006; ARFI vs. histology: r = 0.7538, p = 0.0012). FIB-4 correlated weakly with the histological staging, which was statistically not significant (all samples: r = 0.2693, p = 0.1296; SG≥10PF: r = 0.2244, p = 0.3866). The number of portal fields correlated well with the length of the samples (r = 0.6436, p = 0.00012). The probability to attain at least 10 portal fields depended on the needle diameter and number of samples (1 × 16G or 18G [n = 10]: 30.0%; 2 × 18G [n = 15]: 53.3%; 2 × 16G [n = 5]: 100%; p = 0.0414). Conclusion: ARFI and MLFS are probably well suited for the assessment of liver fibrosis in patients with PBC. A minimum of 10 portal fields could improve the histological assessment in PBC and can probably be achieved by obtaining two 16G biopsies.
CRIS-Team Scopus Importer:2020-06-19

How the Tumor Micromilieu Modulates the Recruitment and Activation of Colorectal Cancer-Infiltrating Lymphocytes - Atreya, Imke; Neurath, Markus (Biomedicines, 2022)
The successful treatment of advanced colorectal cancer disease still represents an insufficiently solved clinical challenge, which is further complicated by the fact that the majority of malignant colon tumors show only relatively low immunogenicity and therefore have only limited responsiveness to immunotherapeutic approaches, such as, for instance, the use of checkpoint inhibitors. As it has been well established over the past two decades that the local tumor microenvironment and, in particular, the quantity, quality, and activation status of intratumoral immune cells critically influence the clinical prognosis of patients diagnosed with colorectal cancer and their individual benefits from immunotherapy, the enhancement of the intratumoral accumulation of cytolytic effector T lymphocytes and other cellular mediators of the antitumor immune response has emerged as a targeted objective. For the future identification and clinical validation of novel therapeutic target structures, it will thus be essential to further decipher the molecular mechanisms and cellular interactions in the intestinal tumor microenvironment, which are crucially involved in immune cell recruitment and activation. In this context, our review article aims at providing an overview of the key chemokines and cytokines whose presence in the tumor micromilieu relevantly modulates the numeric composition and antitumor capacity of tumor-infiltrating lymphocytes.
CRIS-Team WoS Importer:2022-12-23

How will new and future therapies change our treatment of IBD? - Zundler, Sebastian; Neurath, Markus (Expert Review of Clinical Immunology, 2016)
Fundamental insights into the pathogenesis of inflammatory bowel diseases (IBD) have led to the development of new therapies and lots of experimental compounds in the pipeline. Our treatment of IBD is therefore constantly evolving. In this editorial, we postulate that bi- or even polyspecific therapy will be an important mainstay of future IBD treatment. Moreover, we highlight some promising new therapeutic concepts currently under investigation and point at the outstanding and growing importance of personalized medicine to assign drugs from the increasing pool of options to the individual patient.
EVALuna2:2069

Hybrid reflected-ultrasound computed tomography versus B-mode-ultrasound for muscle scoring in spinal muscular atrophy - Danko, Vera; Jüngert, Jörg M.; Schüssler, Stephanie; Bühler, Adrian; Klett, Daniel; Federle, Anna; Roos, Andreas; Lochmüller, Hanns; Neurath, Markus; Wölfle, Joachim; Trollmann, Regina; Waldner, Maximilian; et al. (Journal of Neuroimaging, 2023)
Background and Purpose: Novel light- and sound-based technologies like multispectral optoacoustic tomography (MSOT) with co-registered reflected-ultrasound computed tomography (RUCT) could add additional value to conventional ultrasound (US) for disease phenotyping in pediatric spinal muscular atrophy (SMA). The aim of this study was to investigate the quality of RUCT compared to US for qualitative and quantitative assessment of imaging neuromuscular disorders. Methods: Subanalyzing the MSOT SMA study, 288 RUCT and 276 US images from 10 SMA patients (mean age 9.0 ± 3.7) and 10 gender- and age-matched healthy volunteers (HV; mean age 8.7 ± 4.3) were analyzed for quantitative (grayscale levels [GSLs]) and qualitative (echogenicity, distribution pattern, Heckmatt scale, and muscle texture) muscle changes. RUCT and US measures were further correlated with clinical standard motor outcomes. Results: Quantitative agreement using GSLs revealed significantly higher GSLs in muscles of SMA patients compared to healthy muscles in both techniques (US mean GSL [SD] SMA vs. HV: 110.70 [27.8] vs. 68.85 [19.2], p <.0001; RUCT mean GSL [SD] SMA vs. HV: 91.81 [21.8] vs. 59.86 [8.2], p <.0001) with good correlation with motor outcome tests, respectively. Qualitative agreement between methods for muscle composition was excellent for differentiation of pathological versus healthy muscles, echogenicity, and distribution pattern, moderate for Heckmatt scale, and poor for muscle texture. Conclusions: The data suggest that RUCT may allow the assessment of basic qualitative and quantitative measures for muscular diseases with comparable results to conventional US.
CRIS-Team Scopus Importer:2023-01-20
Keywords: neuromuscular disorders; optoacoustics; photoacoustics; spinal muscular atrophy; ultrasound

Hybrid ultrasound and single wavelength optoacoustic imaging reveals muscle degeneration in peripheral artery disease - Träger, Anna P.; Günther, Josefine; Raming, Roman; Paulus, Lars-Philip; Lang, Werner; Meyer, Alexander; Kempf, Julius; Caranovic, Milenko; Li, Yi; Wagner, Alexandra; Tan, Lina; Danko, Vera; et al. (Photoacoustics, 2024)
Peripheral arterial disease (PAD) leads to chronic vascular occlusion and results in end organ damage in critically perfused limbs. There are currently no clinical methods available to determine the muscular damage induced by chronic mal-perfusion. This monocentric prospective cross-sectional study investigated n = 193 adults, healthy to severe PAD, in order to quantify the degree of calf muscle degeneration caused by PAD using a non-invasive hybrid ultrasound and single wavelength optoacoustic imaging (US/SWL-OAI) approach. While US provides morphologic information, SWL-OAI visualizes the absorption of pulsed laser light and the resulting sound waves from molecules undergoing thermoelastic expansion. US/SWL-OAI was compared to multispectral data, clinical disease severity, angiographic findings, phantom experiments, and histological examinations from calf muscle biopsies. We were able to show that synergistic use of US/SWL-OAI is most likely to map clinical degeneration of the muscle and progressive PAD.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Muscle degeneration; Muscle imaging; Optoacoustics; Peripheral artery disease; Photoacoustics

IBD pathogenesis in 2014: Molecular pathways controlling barrier function in IBD - Atreya, Raja; Neurath, Markus (Nature Reviews Gastroenterology & Hepatology, 2015)
Several key studies published in 2014 have shed light on the pathogenesis of IBD by investigating the molecular mechanisms controlling mucosal homeostasis and intestinal barrier function. These studies revealed that alterations of intestinal homeostasis drive chronic intestinal inflammation. Here, we describe these findings and discuss future directions for translational research in IBD.
EVALuna2:2013

„Ich habe Durchfall und Erbrechen“ - Fischer, Sarah; Neurath, Markus (MMW Fortschritte der Medizin, 2020)
CRIS-Team Scopus Importer:2020-02-07
Keywords: Diarrhea; endoscopy; epidemiology; gastrointestinal infection; vomiting

Identification of Bronchoalveolar Lavage Components Applying Confocal Laser Endomicroscopy - Zirlik, Sabine; Neurath, Markus; Meidenbauer, Norbert; Fuchs, Florian; Vieth, Michael (Medical Science Monitor, 2018)
BACKGROUND In many studies, confocal laser endomicroscopy (CLE) has proven to be a useful tool in pulmonology; nevertheless, the application in this field is still experimental. By contrast, CLE is almost a standard technique in gastroenterology. The aim of the present study was to demonstrate the identification of bronchoalveolar lavage (BAL) components applying CLE, using a dye. MATERIAL AND METHODS In 21 patients with various underlying diseases a bronchoscopy with BAL was performed. As in routine clinical practice common, BAL fluid (BALF) was analyzed in terms of cytologic, virologic, and microbiologic aspects. To one fraction of BALF, we added acriflavine. After centrifugation CLE was applied and the video sequences were analyzed by an experienced investigator. RESULTS Using CLE, BALF components (such as alveolar macrophages or leucocytes) could be easily identified. A further subdivision of leucocytes (neutrophilic, eosinophilic granulocytes, and lymphocytes) was not possible. Analogous to conventional cytology, a precise distinction of lymphocyte subpopulation (cd 4/cd 8 ratio) was not feasible. In terms of quantification, this is still the application field of flow cytometry and immunohistochemistry. CONCLUSIONS Using CLE, alveolar macrophages and leucocytes in stained BALF can be differentiated independent of smoking status. Further studies should be initiated in order to subclassify leucocytes in eosinophilic, neutrophilic granulocytes, and lymphocytes, which is important for routine clinical practice.
EVALuna2:34445

IgA2 Antibodies against SARS-CoV-2 Correlate with NET Formation and Fatal Outcome in Severely Diseased COVID-19 Patients - Staats, Leonie A. N.; Pfeiffer, Hella; Knopf, Jasmin; Lindemann, Aylin; Fürst, Julia; Kremer, Andreas; Hackstein, Holger; Neurath, Markus; Munoz, Luis Enrique; Achenbach, Susanne; Leppkes, Moritz; Herrmann, Martin; et al. (Cells, 2020)
Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) leads to an adaptive immune response in the host and the formation of anti-SARS-CoV-2 specific antibodies. While IgG responses against SARS-CoV-2 have been characterized quite well, less is known about IgA. IgA2 activates immune cells and induces inflammation and neutrophil extracellular trap (NET) formation which may contribute to organ injury and fatal outcome in SARS-CoV-2-infected patients. SARS-CoV-2 spike protein specific antibody levels were measured in plasma samples of 15 noninfected controls and 82 SARS-CoV-2-infected patients with no or mild symptoms, moderate symptoms (hospitalization) or severe disease (intensive care unit, ICU). Antibody levels were compared to levels of C-reactive protein (CRP) and circulating extracellular DNA (ecDNA) as markers for general inflammation and NET formation, respectively. While levels of SARS-CoV-2-specific IgG were similar in all patient groups, IgA2 antibodies were restricted to severe disease and showed the strongest discrimination between nonfatal and fatal outcome in patients with severe SARS-CoV-2 infection. While anti-SARS-CoV-2 IgG and IgA2 levels correlated with CRP levels in severely diseased patients, only anti-SARS-CoV-2 IgA2 correlated with ecDNA. These data suggest that the formation of anti-SARS-CoV-2 IgA2 during SARS-CoV-2 infection is a marker for more severe disease related to NET formation and poor outcome.
CRIS-Team WoS Importer:2021-01-15

IL-12 and IL-23 pathway inhibition in inflammatory bowel disease - Verstockt, Bram; Salas, Azucena; Sands, Bruce E.; Abraham, Clara; Leibovitzh, Haim; Neurath, Markus; Vande Casteele, Niels (Nature Reviews Gastroenterology & Hepatology, 2023)
Interleukin-12 (IL-12) and interleukin-23 (IL-23), which belong to the IL-12 family of cytokines, have a key role in intestinal homeostasis and inflammation and are implicated in the pathogenesis of inflammatory bowel disease. Upon their secretion by antigen-presenting cells, they exert both pro-inflammatory and anti-inflammatory receptor-mediated effects. An increased understanding of these biological effects, particularly the pro-inflammatory effects mediated by IL-12 and IL-23, has led to the development of monoclonal antibodies that target a subunit common to IL-12 and IL-23 (p40; targeted by ustekinumab and briakinumab), or the IL-23-specific subunit (p19; targeted by risankizumab, guselkumab, brazikumab and mirikizumab). This Review provides a summary of the biology of the IL-12 family cytokines IL-12 and IL-23, discusses the role of these cytokines in intestinal homeostasis and inflammation, and highlights IL-12- and IL-23-directed drug development for the treatment of Crohn's disease and ulcerative colitis.
CRIS-Team WoS Importer:2023-05-26

IL-20 controls resolution of experimental colitis by regulating epithelial IFN/STAT2 signalling - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Günther, Claudia; Gonzalez Acera, Miguel; Atreya, Raja; Stolzer, Iris; Wittner, Leonie; Dressel, Anja; Schickedanz, Laura; Gámez Belmonte, Maria de los Reyes; Erkert, Lena; Hundorfean, Gheorghe; et al. (Gut, 2023)
Objective: We sought to investigate the role of interleukin (IL)-20 in IBD and experimental colitis. Design: Experimental colitis was induced in mice deficient in components of the IL-20 and signal transducer and activator of transcription (STAT)2 signalling pathways. In vivo imaging, high-resolution mini-endoscopy and histology were used to assess intestinal inflammation. We further used RNA-sequencing (RNA-Seq), RNAScope and Gene Ontology analysis, western blot analysis and co-immunoprecipitation, confocal microscopy and intestinal epithelial cell (IEC)-derived three-dimensional organoids to investigate the underlying molecular mechanisms. Results were validated using samples from patients with IBD and non-IBD control subjects by a combination of RNA-Seq, organoids and immunostainings. Results: In IBD, IL20 levels were induced during remission and were significantly higher in antitumour necrosis factor responders versus non-responders. IL-20RA and IL-20RB were present on IECs from patients with IBD and IL-20-induced STAT3 and suppressed interferon (IFN)-STAT2 signalling in these cells. In IBD, experimental dextran sulfate sodium (DSS)-induced colitis and mucosal healing, IECs were the main producers of IL-20. Compared with wildtype controls, Il20-/-, Il20ra-/- and Il20rb-/- mice were more susceptible to experimental DSS-induced colitis. IL-20 deficiency was associated with increased IFN/STAT2 activity in mice and IFN/STAT2-induced necroptotic cell death in IEC-derived organoids could be markedly blocked by IL-20. Moreover, newly generated Stat2ΔIEC mice, lacking STAT2 in IECs, were less susceptible to experimental colitis compared with wildtype controls and the administration of IL-20 suppressed colitis activity in wildtype animals. Conclusion: IL-20 controls colitis and mucosal healing by interfering with the IFN/STAT2 death signalling pathway in IECs. These results indicate new directions for suppressing gut inflammation by modulating IL-20-controlled STAT2 signals.
CRIS-Team Scopus Importer:2023-11-17
Keywords: experimental colitis; inflammatory bowel disease; interferon; interleukins; signal transduction

IL-23 Blockade in Anti-TNF Refractory IBD: From Mechanisms to Clinical Reality - Atreya, Raja; Neurath, Markus (Journal of Crohns & Colitis, 2022)
Increasing insights into the immunopathogenesis of inflammatory bowel diseases [IBD] have led to the advent of targeted therapies that inhibit crucial mediators of the inflammatory process, thereby widening our available therapeutic armamentarium. Anti-tumour necrosis factor (anti-TNF) agents are still a mainstay of our therapeutic endeavours and the introduction of corresponding biosimilars has further widened their use. Nevertheless, only a subgroup of treated patients benefit from the initiated treatment and there is secondary non-response in the course of therapy. Initiation of subsequent therapy often poses a challenge to the treating physician, as non-response to primary anti-TNF treatment generally characterizes a patient group that is more treatment-resistant, which may be due to the immunological impregnation by prior anti-TNF exposure. At present, there is currently no guidance for the most appropriate second-line therapy after anti-TNF failure. Here, we review the efficacy of secondary biological therapy in anti-TNF-treated patients. We focus on and assess available clinical trial data of the emerging substance class of IL-23p19 inhibitors, which have demonstrated remarkable efficacy not only in anti-TNF-nalve but also refractory patients. We present molecular mechanisms that drive IL-23-mediated resistance to ongoing anti-TNF therapy and discuss the dynamic fluidity of the mucosal cytokine network in the course of therapy that perpetuates the mucosal inflammatory reaction. Translation of these findings into clinical practice might finally lead to initiation of the most appropriate therapy at the right time of the individual disease course, which would have important implications for the patient's probability of response to treatment.
CRIS-Team WoS Importer:2022-05-27

IL-23 in inflammatory bowel diseases and colon cancer - Neurath, Markus (Cytokine & Growth Factor Reviews, 2019)
Studies in recent years have identified a pivotal role of the cytokine IL-23 in the pathogenesis of inflammatory bowel diseases (IBD: Crohn's disease, ulcerative colitis) and colitis-associated colon cancer. Genetic studies revealed that subgroups of IBD patients have single nucleotide polymorphisms in the IL-23R gene suggesting that IL-23R signaling affects disease susceptibility. Furthermore, increased production of IL-23 by macrophages, dendritic cells or granulocytes has been observed in various mouse models of colitis, colitis-associated cancer and IBD patients. Moreover, in several murine models of colitis, suppression of IL-12/IL-23 p40, IL-23 p19 or IL-23R function led to marked suppression of gut inflammation. This finding was associated with reduced activation of IL-23 target cells such as T helper 17 cells, innate lymphoid cells type 3, granulocytes and natural killer cells as well as with impaired production of proinflammatory cytokines. Based on these findings, targeting of IL-23 emerges as important concept for suppression of gut inflammation and inflammation-associated cancer growth. Consistently, neutralizing antibodies against IL-12/IL-23 p40 and IL-23 p19 have been successfully used in clinical trials for therapy of Crohn's disease and pilot studies in ulcerative colitis are ongoing. These findings underline the crucial regulatory role of IL-23 in chronic intestinal inflammation and colitis-associated cancer and indicate that therapeutic strategies aiming at IL-23 blockade may be of key relevance for future therapy of IBD patients.
CRIS-Team WoS Importer:2019-03-20

IL-23 is centrally involved in mediating molecular resistance to anti-TNF therapy in Crohn's disease patients - Schmitt, H.; Billmeier, Ulrike; Dieterich, Walburga; Rath, T.; Sonnewald, Sophia; Reid, Stephen; Hirschmann, S.; Hildner, Kai; Waldner, Maximilian; Mudter, J.; Hartmann, Arndt; Grützmann, Robert; et al. (2018)
EVALuna2:34077

IL-27 suppresses type 2 immune responses in vivo via direct effects on group 2 innate lymphoid cells - Mchedlidze, T.; Kindermann, M.; Neves, A. T.; Vöhringer, David; Neurath, Markus; Wirtz, Stefan (Mucosal Immunology, 2016)
Group 2 innate lymphoid cells (ILC2) were recently characterized by their ability to produce significant amounts of type-2 signature cytokines and drive central beneficial and pathological features of type-2 immune responses. Although factors such as IL-33 and IL-25 were shown to have ILC2 activating capacity, it is not well understood, how ILC2 responses are regulated in vivo. Here we provide compelling evidence that IL-27-signalling directly inhibits ILC2 responses and reveal a novel mechanism for negative regulation of the innate arm of type-2 immunity. We demonstrate that IL-27-deficiency is linked to increased mucosal presence of ILC2 in a model of inflammatory lung disease. Moreover, IL-27-treatment inhibited ILC2 proliferation and cytokine production and significantly reduced their accumulation in vivo. During helminth infection, regulation of ILC2 by IL-27 directly impacted anti-parasitic immunity. Thus, therapeutic modulation of the IL-27/IL-27R axis may be relevant in a number of inflammatory conditions associated with dysregulated type-2 responses.
EVALuna2:2062

IL-35-producing B cells are critical regulators of immunity during autoimmune and infectious diseases - Shen, Ping; Roch, Toralf; Lampropoulou, Vicky; O'Connor, Richard A.; Stervbo, Ulrik; Hilgenberg, Ellen; Ries, Stefanie; Van Duc Dang,; Jaimes, Yarua; Daridon, Capucine; Li, Rui; Jouneau, Luc; et al. (Nature, 2014)
B lymphocytes have critical roles as positive and negative regulators of immunity. Their inhibitory function has been associated primarily with interleukin 10 (IL-10) because B-cell-derived IL-10 can protect against autoimmune disease and increase susceptibility to pathogens. Here we identify IL-35-producing B cells as key players in the negative regulation of immunity. Mice in which only B cells did not express IL-35 lost their ability to recover from the T-cell-mediated demyelinating autoimmune disease experimental autoimmune encephalomyelitis (EAE). In contrast, these mice displayed a markedly improved resistance to infection with the intracellular bacterial pathogen Salmonella enterica serovar Typhimurium as shown by their superior containment of the bacterial growth and their prolonged survival after primary infection, and upon secondary challenge, compared to control mice. The increased immunity found in mice lacking IL-35 production by B cells was associated with a higher activation of macrophages and inflammatory T cells, as well as an increased function of B cells as antigen-presenting cells (APCs). During Salmonella infection, IL-35- and IL-10-producing B cells corresponded to two largely distinct sets of surface-IgM(+)CD138(hi)TACI(+)CXCR4(+)CD1d(int)Tim1(int) plasma cells expressing the transcription factor Blimp1 (also known as Prdm1). During EAE, CD138(+) plasma cells were also the main source of B-cell-derived IL-35 and IL-10. Collectively, our data show the importance of IL-35-producing B cells in regulation of immunity and highlight IL-35 production by B cells as a potential therapeutic target for autoimmune and infectious diseases. This study reveals the central role of activated B cells, particularly plasma cells, and their production of cytokines in the regulation of immune responses in health and disease.
EVALuna2:1911

IL-36 in chronic inflammation and cancer - Neurath, Markus (Cytokine & Growth Factor Reviews, 2020)
IL-36 belongs to the IL-1 family of cytokines and activates target cells by binding to a specific cytokine receptor (IL-36R) followed by activation of intracellular regulators such as MAP kinases and NF-kappaB. Three subforms of IL-36, denoted IL-36alpha, IL-36beta and IL-36gamma, have been described that require N-terminal cleavage for activation. Functional studies have shown that IL-36 may activate a broad spectrum of immune and non-immune cells such as macrophages, T cells, keratinocytes and epithelial cells in an IL-1-independent fashion and thereby controls various inflammatory or oncogenic processes in the skin, the lung, the kidney, the liver and the intestine, respectively. Based on the presence of mutations of the IL-36RN in patients with generalized pustular psoriasis, successful clinical pilot trials with IL-36R blocking antibodies were conducted in these patients and further studies in patients with autoimmune or chronic inflammatory disorders such as inflammatory bowel diseases are under way. Collectively, these findings highlight a crucial regulatory role of IL-36 signaling in driving various inflammatory disorders that provide a rational basis for clinical targeting of this cytokine.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Cytokines; IL-36; Immune cells; Inflammation

IL-36 in chronic inflammation and fibrosis - bridging the gap? - Elias, Michael; Zhao, Shuai; Le, Hongnga T.; Wang, Jie; Neurath, Markus; Neufert, Clemens; Fiocchi, Claudio; Rieder, Florian (Journal of Clinical Investigation, 2021)
IL-36 is a member of the IL-1 superfamily and consists of three agonists and one receptor antagonist (IL-36Ra). The three endogenous agonists, IL-36α, -β, and -γ, act primarily as proinflammatory cytokines, and their signaling through the IL-36 receptor (IL-36R) promotes immune cell infiltration and secretion of inflammatory and chemotactic molecules. However, IL-36 signaling also fosters secretion of profibrotic soluble mediators, suggesting a role in fibrotic disorders. IL-36 isoforms and IL-36 have been implicated in inflammatory diseases including psoriasis, arthritis, inflammatory bowel diseases, and allergic rhinitis. Moreover, IL-36 has been connected to fibrotic disorders affecting the kidney, lung, and intestines. This review summarizes the expression, cellular source, and function of IL-36 in inflammation and fibrosis in various organs, and proposes that IL-36 modulation may prove valuable in preventing or treating inflammatory and fibrotic diseases and may reveal a mechanistic link between inflammation and fibrosis.
CRIS-Team Scopus Importer:2021-02-05

IL-36R signalling activates intestinal epithelial cells and fibroblasts and promotes mucosal healing in vivo - Scheibe, Kristina; Backert, Ingo; Wirtz, Stefan; Hueber, Axel; Schett, Georg; Vieth, Michael; Probst, Hans Christian; Bopp, Tobias; Neurath, Markus; Neufert, Clemens (Gut, 2016)
Interleukin (IL)-36R signalling plays a proinflammatory role in different organs including the skin, but the expression of IL-36R ligands and their molecular function in intestinal inflammation are largely unknown.We studied the characteristics of IL-36R ligand expression in IBDs and experimental colitis. The functional role of IL-36R signalling in the intestine was addressed in experimental colitis and wound healing models in vivo by using mice with defective IL-36R signalling (IL-36R-/-) or Myd88, neutralising anti-IL-36R antibodies, recombinant IL-36R ligands and RNA-seq genome expression analysis.Expression of IL-36? and IL-36? was significantly elevated in active human IBD and experimental colitis. While IL-36? was predominantly detected in nuclei of the intestinal epithelium, IL-36? was mainly found in the cytoplasm of CD14(+) inflammatory macrophages. Functional studies showed that defective IL-36R signalling causes high susceptibility to acute dextran sodium sulfate colitis and impairs wound healing. Mechanistically, IL-36R ligands released upon mucosal damage activated IL-36R(+) colonic fibroblasts via Myd88 thereby inducing expression of chemokines, granulocyte-macrophage colony-stimulating factor (GM-CSF) and IL-6. Moreover, they induced proliferation of intestinal epithelial cells (IECs) and expression of the antimicrobial protein lipocalin 2. Finally, treatment of experimental intestinal wounds with IL-36R ligands significantly accelerated mucosal healing in vivo.IL-36R signalling is activated upon intestinal damage, stimulates IECs and fibroblasts and drives mucosal healing. Modulation of the IL-36R pathway emerges as a potential therapeutic strategy for induction of mucosal healing in IBD.
EVALuna2:2028

IL-3 drives IL-10-secreting Tr1 cells to counteract experimental colitis - Zundler, Sebastian; Spocinska, M.; Popp, V.; Becker, E.; Atreya, Raja; Neufert, Clemens; Atreya, I.; Weigmann, Benno; Neurath, Markus (2018)
EVALuna2:34113

IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells. - Ullrich, Karen; Derdau, Julia; Baltes, Carsten; Battistella, Alice; Rosso, Gonzalo; Uderhardt, Stefan; Schulze, Lisa; Liu, Lijuan; Dedden, Mark; Spocinska, Marta; Kainka, Lucina; Kubánková, Markéta; et al. (Gut, 2023)
IL-3 has been reported to be involved in various inflammatory disorders, but its role in inflammatory bowel disease (IBD) has not been addressed so far. Here, we determined IL-3 expression in samples from patients with IBD and studied the impact of Il3 or Il3r deficiency on T cell-dependent experimental colitis. We explored the mechanical, cytoskeletal and migratory properties of Il3r -/- and Il3r +/+ T cells using real-time deformability cytometry, atomic force microscopy, scanning electron microscopy, fluorescence recovery after photobleaching and in vitro and in vivo cell trafficking assays. We observed that, in patients with IBD, the levels of IL-3 in the inflamed mucosa were increased. In vivo, experimental chronic colitis on T cell transfer was exacerbated in the absence of Il-3 or Il-3r signalling. This was attributable to Il-3r signalling-induced changes in kinase phosphorylation and actin cytoskeleton structure, resulting in increased mechanical deformability and enhanced egress of Tregs from the inflamed colon mucosa. Similarly, IL-3 controlled mechanobiology in human Tregs and was associated with increased mucosal Treg abundance in patients with IBD. Collectively, our data reveal that IL-3 signaling exerts an important regulatory role at the interface of biophysical and migratory T cell features in intestinal inflammation and suggest that this might be an interesting target for future intervention.
EVALuna2:539503

IL-9 Producing Tumor-Infiltrating Lymphocytes and Treg Subsets Drive Immune Escape of Tumor Cells in Non-Small Cell Lung Cancer - Heim, Lisanne; Yang, Zuqin; Tausche, Patrick; Hohenberger, Katja; Chiriac, Mircea-Teodor; Kölle, Julia; Geppert, Carol-Immanuel; Kachler, Katerina; Miksch, Sarah; Graser, Anna; Friedrich, Juliane; Kharwadkar, Rakshin; et al. (Frontiers in Immunology, 2022)
Although lung cancer is the leading cause of cancer deaths worldwide, the mechanisms how lung cancer cells evade the immune system remain incompletely understood. Here, we discovered IL-9-dependent signaling mechanisms that drive immune evasion in non-small cell lung cancer (NSCLC). We found increased IL-9 and IL-21 production by T cells in the tumoral region of the lung of patients with NSCLC, suggesting the presence of Th9 cells in the lung tumor microenvironment. Moreover, we noted IL-9 producing Tregs in NSCLC. IL-9 target cells in NSCLC consisted of IL-9R+ tumor cells and tumor-infiltrating lymphocytes. In two murine experimental models of NSCLC, and in vitro, IL-9 prevented cell death and controlled growth of lung adenocarcinoma cells. Targeted deletion of IL-9 resulted in successful lung tumor rejection in vivo associated with an induction of IL-21 and reduction of Treg cells. Finally, anti-IL-9 antibody immunotherapy resulted in suppression of tumor development even in established experimental NSCLC and was associated with reduced IL-10 production in the lung. In conclusion, our findings indicate that IL-9 drives immune escape of lung tumor cells via effects on tumor cell survival and tumor infiltrating T cells. Thus, strategies blocking IL-9 emerge as a new approach for clinical therapy of lung cancer.
CRIS-Team Scopus Importer:2022-05-20
Keywords: IL-9; immune escape; NSCLC; TIL; tumor immunotherapy

IL-9 regulates intestinal barrier function in experimental T cell-mediated colitis - Gerlach, Katharina; McKenzie, Andrew N.; Neurath, Markus; Weigmann, Benno (Tissue Barriers, 2015)
As previous studies suggested that IL-9 may control intestinal barrier function, we tested the role of IL-9 in experimental T cell-mediated colitis induced by the hapten reagent 2,4,6-trinitrobenzenesulfonic acid (TNBS). The deficiency of IL-9 suppressed TNBS-induced colitis and led to lower numbers of PU.1 expressing T cells in the lamia propria, suggesting a regulatory role for Th9 cells in the experimental TNBS colitis model. Since IL-9 is known to functionally alter intestinal barrier function in colonic inflammation, we assessed the expression of tight junction molecules in intestinal epithelial cells of TNBS-inflamed mice. Therefore we made real-time PCR analyses for tight junction molecules in the inflamed colon from wild-type and IL-9 KO mice, immunofluorescent stainings and investigated the expression of junctional proteins directly in intestinal epithelial cells of TNBS-inflamed mice by Western blot studies. The results demonstrated that sealing proteins like occludin were up regulated in the colon of inflamed IL-9 KO mice. In contrast, the tight junction protein Claudin1 showed lower expression levels when IL-9 is absent. Surprisingly, the pore-forming molecule Claudin2 revealed equal expression in TNBS-treated wild-type and IL-9-deficient animals. These results illustrate the pleiotropic functions of IL-9 in changing intestinal permeability in experimental colitis. Thus, modulation of IL-9 function emerges as a new approach for regulating barrier function in intestinal inflammation.
EVALuna2:2009

IL-9 signaling as key driver of chronic inflammation in mucosal immunity - Neurath, Markus; Finotto, Susetta (Cytokine & Growth Factor Reviews, 2016)
Recent studies have highlighted a crucial regulatory role of the cytokine IL-9 in driving immune responses in chronic inflammatory and autoimmune diseases at mucosal surfaces. IL-9 activates various types of immune and non-immune cells carrying the membrane bound IL-9R. IL-9 signaling plays a pivotal role in controlling the differentiation and activation of these cells by inducing the Jak/STAT pathway. In particular, IL-9 induces activation of T helper cells and affects the function of various tissue resident cells such as mast cells and epithelial cells in the mucosa. Importantly, recent findings suggest that blockade of IL-9 signaling is effective in treating experimental models of autoimmune and chronic inflammatory diseases such as inflammatory bowel diseases, allergic disorders such as food allergy and asthma. Thus, blockade of IL-9 and IL-9R signaling emerges as potentially novel approach for therapy of inflammatory diseases in the mucosal immune system.
EVALuna2:2054

ILC2 Lung-Homing in Cystic Fibrosis Patients: Functional Involvement of CCR6 and Impact on Respiratory Failure - Schulz-Kuhnt, Anja; Greif, Vicky; Hildner, Kai; Knipfer, Lisa; Döbrönti, Michael; Zirlik, Sabine; Fuchs, Florian; Atreya, Raja; Zundler, Sebastian; Lopez Posadas, Rocío; Neufert, Clemens; Ramming, Andreas; et al. (Frontiers in Immunology, 2020)
Cystic fibrosis patients suffer from a progressive, often fatal lung disease, which is based on a complex interplay between chronic infections, locally accumulating immune cells and pulmonary tissue remodeling. Although group-2 innate lymphoid cells (ILC2s) act as crucial initiators of lung inflammation, our understanding of their involvement in the pathogenesis of cystic fibrosis remains incomplete. Here we report a marked decrease of circulating CCR6+ ILC2s in the blood of cystic fibrosis patients, which significantly correlated with high disease severity and advanced pulmonary failure, strongly implicating increased ILC2 homing from the peripheral blood to the chronically inflamed lung tissue in cystic fibrosis patients. On a functional level, the CCR6 ligand CCL20 was identified as potent promoter of lung-directed ILC2 migration upon inflammatory conditions in vitro and in vivo using a new humanized mouse model with light-sheet fluorescence microscopic visualization of lung-accumulated human ILC2s. In the lung, blood-derived human ILC2s were able to augment local eosinophil and neutrophil accumulation and induced a marked upregulation of pulmonary type-VI collagen expression. Studies in primary human lung fibroblasts additionally revealed ILC2-derived IL-4 and IL-13 as important mediators of this type-VI collagen-inducing effect. Taken together, the here acquired results suggest that pathologically increased CCL20 levels in cystic fibrosis airways induce CCR6-mediated lung homing of circulating human ILC2s. Subsequent ILC2 activation then triggers local production of type-VI collagen and might thereby drive extracellular matrix remodeling potentially influencing pulmonary tissue destruction in cystic fibrosis patients. Thus, modulating the lung homing capacity of circulating ILC2s and their local effector functions opens new therapeutic avenues for cystic fibrosis treatment.
CRIS-Team Scopus Importer:2020-06-02
Keywords: CCR6; cystic fibrosis; group-2 innate lymphoid cells; tissue remodeling; type-VI collagen

Ileal and colonic Crohn's disease: Does location makes a difference in therapy efficacy? - Atreya, Raja; Bojarski, Christian; Kühl, Anja A.; Trajanoski, Zlatko; Neurath, Markus; Siegmund, Britta (Current Research in Pharmacology and Drug Discovery, 2022)
Within the IBD entity of Crohn's disease, there is currently no differentiation between ileal and colonic manifestation for recruitment of patients in clinical trials, well-powered analysis of study results or therapeutic decisions in daily clinical practice. However, there is accumulating evidence from epidemiological, genetic, microbial, immunological, and clinical characteristics that clearly indicate that ileal Crohn's disease represents a distinct disease entity, which differentiates itself from colonic Crohn's disease. This is also reflected by lower efficacy of targeted therapies in isolated ileal compared to colonic Crohn's disease. The distinct site-specific mechanisms that drive heightened non-response in ileal disease need to be analysed in-depth in the future, to enable optimized therapy in the individual Crohn's disease patient.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Colonic Crohn's disease; Crohn's disease; Ileal Crohn's disease; Segment; Therapy

Immune Cell Circuits in Mucosal Wound Healing: Clinical Implications - Zundler, Sebastian; Tauschek, Verena; Neurath, Markus (Visceral Medicine, 2020)
Background: An intact mucosal barrier is essential for homeostasis in the gastrointestinal tract. Various pathological conditions such as infection or immune-mediated inflammation as well as therapeutic interventions like bowel surgery can result in injury of the intestinal mucosa. To counteract potential negative sequelae and to restore integrity of the tissue, a tightly regulated machinery of mechanisms exists, which crucially depends on the presence and absence of various immune cell subsets in different phases of intestinal wound healing. Cell trafficking is an increasingly acknowledged process that steers the localization of cells in tissues and the circulation. Thus, such cell circuits also crucially impact on the recruitment of immune cells in wound healing. Summary: We performed a selective literature research. In our review, we will shortly delineate some basic principles of intestinal immune cell trafficking before discussing the contribution of different immune cells to wound healing. Finally, we will discuss potential clinical implications of immune cell trafficking and wound healing interactions in inflammatory bowel disease (IBD) and bowel surgery. Key Messages: Intestinal wound healing has immense importance in pathological conditions like IBD, anastomotic healing, and others. Immune cell trafficking is indispensable for the correct temporal and spatial interaction of the cells involved. Further research is required to understand the final consequences of interfering with immune cell trafficking for intestinal wound healing.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Immune cell trafficking; Mucosal healing; Vedolizumab; Wound healing

Immune cell trafficking and retention in inflammatory bowel disease: Mechanistic insights and therapeutic advances - Zundler, Sebastian; Becker, Elisabeth; Schulze, Lisa; Neurath, Markus (Gut, 2019)
Intestinal immune cell trafficking has been identified as a central event in the pathogenesis of inflammatory bowel diseases (IBD). Intensive research on different aspects of the immune mechanisms controlling and controlled by T cell trafficking and retention has led to the approval of the anti-α4β7 antibody vedolizumab, the ongoing development of a number of further anti-trafficking agents (ATAs) such as the anti-β7 antibody etrolizumab or the anti-MAdCAM-1 antibody ontamalimab and the identification of potential future targets like G-protein coupled receptor 15. However, several aspects of the biology of immune cell trafficking and regarding the mechanism of action of ATAs are still unclear, for example, which impact these compounds have on the trafficking of non-lymphocyte populations like monocytes and how precisely these therapies differ with regard to their effect on immune cell subpopulations. This review will summarise recent advances of basic science in the field of intestinal immune cell trafficking and discuss these findings with regard to different pharmacological approaches from a translational perspective.
CRIS-Team Scopus Importer:2019-06-18
Keywords: cell adhesion; Crohn's disease; inflammatory bowel disease; integrins; ulcerative colitis

Immune deficiency vs. immune excess in inflammatory bowel diseases-STAT3 as a rheo-STAT of intestinal homeostasis - Leppkes, Moritz; Neurath, Markus; Herrmann, Martin; Becker, Christoph (Journal of Leukocyte Biology, 2016)
Genome-wide association studies have provided many genetic alterations, conferring susceptibility to multifactorial polygenic diseases, such as inflammatory bowel diseases. Yet, how specific genetic alterations functionally affect intestinal inflammation often remains elusive. It is noteworthy that a large overlap of genes involved in immune deficiencies with those conferring inflammatory bowel disease risk has been noted. This has provided new arguments for the debate on whether inflammatory bowel disease arises from either an excess or a deficiency in the immune system. In this review, we highlight the functional effect of an inflammatory bowel disease-risk allele, which cannot be deduced from genome-wide association studies data alone. As exemplified by the transcription factor signal transducer and activator of transcription 3 (STAT3), we show that a single gene can have a plethora of effects in various cell types of the gut. These effects may individually contribute to the restoration of intestinal homeostasis on the one hand or pave the way for excessive immunopathology on the other, as an inflammatory "rheo-STAT".
EVALuna2:1967

Immune-epithelial crosstalk at the intestinal surface - Wittkopf, Nadine; Neurath, Markus; Becker, Christoph (Journal of Gastroenterology, 2014)
The intestinal tract is one of the most complex organs of the human body. It has to exercise various functions including food and water absorption, as well as barrier and immune regulation. These functions affect not only the gut itself, but influence the overall health of the organism. Diseases involving the gastrointestinal tract such as inflammatory bowel disease and colorectal cancer therefore severely affect the patient's quality of life and can become life-threatening. Intestinal epithelial cells (IECs) play an important role in intestinal inflammation, infection, and cancer development. IECs not only constitute the first barrier in the gut against the lumen, they also constantly signal information about the gut lumen to immune cells, thereby influencing their behaviour. In contrast, by producing various antimicrobial peptides, IECs shape the microbial community within the gut. IECs also respond to cytokines and other mediators of immune cells in the lamina propria. Interactions between epithelial cells and immune cells in the intestine are responsible for gut homeostasis, and modulations of this crosstalk have been reported in studies of gut diseases. This review discusses the wide field of immune-epithelial interactions and shows the importance of immune-epithelial crosstalk in the intestine to gut homeostasis and the overall health status.
EVALuna2:1842

IMMUNOLOGY OF IL-12: AN UPDATE ON FUNCTIONAL ACTIVITIES AND IMPLICATIONS FOR DISEASE - Ullrich, Karen; Schulze, Lisa; Paap, Eva-Maria; Müller, Tanja; Neurath, Markus; Zundler, Sebastian (Excli Journal, 2020)
As its first identified member, Interleukin-12 (IL-12) named a whole family of cytokines. In response to pathogens, the heterodimeric protein, consisting of the two subunits p35 and p40, is secreted by phagocytic cells. Binding of IL-12 to the IL-12 receptor (IL-12R) on T and natural killer (NK) cells leads to signaling via signal transducer and activator of transcription 4 (STAT4) and subsequent interferon gamma (IFN-gamma) production and secretion. Signaling downstream of IFN-gamma includes activation of T-box transcription factor TBX21 (Tbet) and induces pro-inflammatory functions of T helper 1 (T(H)1) cells, thereby linking innate and adaptive immune responses. Initial views on the role of IL-12 and clinical efforts to translate them into therapeutic approaches had to be re-interpreted following the discovery of other members of the IL-12 family, such as IL-23, sharing a subunit with IL-12. However, the importance of IL-12 with regard to immune processes in the context of infection and (auto-) inflammation is still beyond doubt. In this review, we will provide an update on functional activities of IL-12 and their implications for disease. We will begin with a summary on structure and function of the cytokine itself as well as its receptor and outline the signal transduction and the transcriptional regulation of IL-12 secretion. In the second part of the review, we will depict the involvement of IL-12 in immune-mediated diseases and relevant experimental disease models, while also providing an outlook on potential translational approaches.
CRIS-Team WoS Importer:2021-01-15

Immunopathogenesis of IBD: Batf as a Key Driver of Disease Activity - Hildner, Kai; Punkenburg, Elise; Abendroth, Benjamin; Neurath, Markus (Digestive Diseases, 2016)
Inflammatory bowel diseases (IBDs) represent a group of chronic immune-mediated disorders that are influenced by a genetic predisposition and additional environmental triggers. Genome-wide association studies strongly implicate that a number of immune system-related genetic variations are critically contributing to the initiation and promotion of intestinal inflammation. Especially the identification of the strong association of a series of single nucleotide polymorphisms including interleukin (IL)-23R, CCR6, signal transducer and activator of transcription 3 (Stat3) and Stat4 with IBD susceptibility point at a critical involvement of T cells and especially of IL-17a-producing Th17 cells in the immune pathogenesis of IBD. In line with this hypothesis, a series of preclinical studies have unequivocally established that T cells are key drivers of immune-mediated colitis. Interestingly, especially Th17 cells were identified to be highly prevalent in inflamed IBD tissues, a finding that seems to be functionally relevant as genetic inactivation studies in the mouse resulted in almost complete suppression of colitis development.While targeting Th17 cell differentiation regulating transcription factors, as retinoic acid-related orphan receptor gamma t (ROR?t) is effective in preventing murine colitis, one concern of drugs targeting ROR?t in a clinical setting represents the large body of murine data unambiguously demonstrating that additional pathways within and outside the immune system are equally ROR?t-dependent increasing the risk of undesirable side effects. The AP1 transcription factor Batf (B cell-activating transcription factor) appears to exclusively regulate pathways within lymphocytes. Importantly, Batf represents a central regulator of Th17 cell development and is strongly upregulated within IBD-affected tissues. Employing 2 acute colitis models, we demonstrate in this study that Batf-expressing T cells are critical drivers of T cell-mediated colitis while in contrast to Stat3 loss of Batf does not affect intestinal epithelial cell homeostasis ex vivo.Targeting Batf in IBD emerges as an attractive therapeutic approach disabling colitogenic T cell activities while sparing off-target effects in the intestinal epithelial cell compartment.
EVALuna2:2187

Immunopathogenesis of inflammatory bowel diseases: functional role of T cells and T cell homing - Zundler, Sebastian; Neurath, Markus (Clinical and Experimental Rheumatology, 2015)
Inflammatory bowel diseases (IBD) are believed to arise from a complex interplay of environmental factors, genetic susceptibility, epithelial barrier defects and dysregulation of the intestinal immune system. Although the exact mechanisms of contribution and interference of these players are still not clear, significant advances have been achieved in understanding the immunopathogenesis of IBD in recent years resulting in novel and targeted therapeutic strategies. We will begin this review by giving a brief outline of current pathogenetic concepts of IBD and then focus on the description of the present knowledge of T cell function and regulation in the context of IBD. Moreover, we will summarise the progress on the emerging field of gut homing and delineate some implications for future therapeutic approaches.
EVALuna2:1978

Impact of acoustic radiation force impulse imaging in clinical practice of patients after orthotopic liver transplantation - Wildner, Dane; Strobel, Deike; Konturek, Peter C.; Görtz, Rüdiger; Croner, Roland S.; Neurath, Markus; Zopf, Steffen (Medical Science Monitor, 2014)
Acoustic radiation force impulse (ARFI) elastography is a reliable diagnostic device for quantitative non-invasive assessment of liver fibrosis in patients with chronic liver disease. The aim of our prospective study was to evaluate the impact of ARFI in patients after orthotopic liver transplantation (OLT). Therefore, we compared ARFI shear wave velocities with clinical features, non-invasive markers, and the histology of patients following OLT.Post-transplant patients underwent a clinical examination and blood samples were taken. B-mode and Doppler ultrasound (US) of the portal vein and the hepatic artery were performed. Subsequently, a minimum of 10 valid ARFI values were measured in the left and right liver lobe. Liver biopsy was performed if indicated.Between May 2012 and May 2014, 58 Patients after OLT were included in the prospective study. Laboratory markers and aspartate aminotransferase-to-platelet ratio index (APRI) correlated with ARFI values (r=0.44, p<0.001). The histological (n=22) fibrosis score (Ludwig) was significantly correlated with the ARFI of the biopsy site (r=0.55, p=0.008). The mean shear-wave velocities were significantly increased in advanced fibrosis (F<=2 1.57±0.57 m/s; F>=3 2.85±0.66 m/s; p<0.001), obstructive cholestasis and active viral hepatitis. The area under the receiver operating characteristic (AUROC) curves for the accuracy of ARFI were 74% (F>=1), 73% (F>=2), 93% (F>=3), and 80% (=F4).ARFI elastography correlates well with laboratory values and with noninvasive and invasive markers of fibrosis in patients after OLT. In this regard, elevated ARFI-velocities should be interpreted with caution in the context of obstructive cholestasis and active viral disease.
EVALuna2:1855

Impact of Cytokine Inhibitor Therapy on the Prevalence, Seroconversion Rate, and Longevity of the Humoral Immune Response Against SARS-CoV-2 in an Unvaccinated Cohort - Simon, David; Tascilar, Koray; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, Johanna; Liphardt, Anna-Maria; Schönau, Verena; et al. (Arthritis and Rheumatology, 2022)
Objective To investigate the impact of biologic disease-modifying antirheumatic drug (bDMARD) treatment on the prevalence, seroconversion rate, and longevity of the humoral immune response against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods Anti-SARS-CoV-2 IgG antibodies were measured in a prospective cohort of health care professional controls and non-health care controls and IMID patients receiving no treatment or receiving treatment with conventional or biologic DMARDs during the first and second COVID-19 waves. Regression models adjusting for age, sex, sampling time, and exposure risk behavior were used to calculate relative risks (RRs) of seropositivity. Seroconversion rates were assessed in participants with polymerase chain reaction (PCR)-positive SARS-CoV-2 infection. Antibody response longevity was evaluated by reassessing participants who tested positive during the first wave. Results In this study, 4,508 participants (2,869 IMID patients and 1,639 controls) were analyzed. The unadjusted RR (0.44 [95% confidence interval (95% CI) 0.31-0.62]) and adjusted RR (0.50 [95% CI 0.34-0.73]) for SARS-CoV-2 IgG antibodies were significantly lower in IMID patients treated with bDMARDs compared to non-health care controls (P < 0.001), primarily driven by treatment with tumor necrosis factor inhibitors, interleukin-17 (IL-17) inhibitors, and IL-23 inhibitors. Adjusted RRs for untreated IMID patients (1.12 [95% CI 0.75-1.67]) and IMID patients receiving conventional synthetic DMARDs (0.70 [95% CI 0.45-1.08]) were not significantly different from non-health care controls. Lack of seroconversion in PCR-positive participants was more common among bDMARD-treated patients (38.7%) than in non-health care controls (16%). Overall, 44% of positive participants lost SARS-CoV-2 antibodies by follow-up, with higher rates in IMID patients treated with bDMARDs (RR 2.86 [95% CI 1.43-5.74]). Conclusion IMID patients treated with bDMARDs have a lower prevalence of SARS-CoV-2 antibodies, seroconvert less frequently after SARS-CoV-2 infection, and may exhibit a reduced longevity of their humoral immune response.
CRIS-Team WoS Importer:2022-04-08

Impact of Epithelial Cell Shedding on Intestinal Homeostasis - Ngo, Phuong A.; Neurath, Markus; Lopez Posadas, Rocío (International Journal of Molecular Sciences, 2022)
The gut barrier acts as a first line of defense in the body, and plays a vital role in nutrition and immunoregulation. A layer of epithelial cells bound together via intercellular junction proteins maintains intestinal barrier integrity. Based on a tight equilibrium between cell extrusion and cell restitution, the renewal of the epithelium (epithelial turnover) permits the preservation of cell numbers. As the last step within the epithelial turnover, cell shedding occurs due to the pressure of cell division and migration from the base of the crypt. During this process, redistribution of tight junction proteins enables the sealing of the epithelial gap left by the extruded cell, and thereby maintains barrier function. Disturbance in cell shedding can create transient gaps (leaky gut) or cell accumulation in the epithelial layer. In fact, numerous studies have described the association between dysregulated cell shedding and infection, inflammation, and cancer; thus epithelial cell extrusion is considered a key defense mechanism. In the gastrointestinal tract, altered cell shedding has been observed in mouse models of intestinal inflammation and appears as a potential cause of barrier loss in human inflammatory bowel disease (IBD). Despite the relevance of this process, there are many unanswered questions regarding cell shedding. The investigation of those mechanisms controlling cell extrusion in the gut will definitely contribute to our understanding of intestinal homeostasis. In this review, we summarized the current knowledge about intestinal cell shedding under both physiological and pathological circumstances.
CRIS-Team Scopus Importer:2022-04-29
Keywords: cell extrusion; colorectal cancer; epithelial cell shedding; inflammatory bowel disease (IBD); leaky gut

Impact of Microbiome–Brain Communication on Neuroinflammation and Neurodegeneration - Stolzer, Iris; Scherer, Eveline; Süß, Patrick; Rothhammer, Veit; Winner, Beate; Neurath, Markus; Günther, Claudia (International Journal of Molecular Sciences, 2023)
The gut microbiome plays a pivotal role in maintaining human health, with numerous studies demonstrating that alterations in microbial compositions can significantly affect the development and progression of various immune-mediated diseases affecting both the digestive tract and the central nervous system (CNS). This complex interplay between the microbiota, the gut, and the CNS is referred to as the gut–brain axis. The role of the gut microbiota in the pathogenesis of neurodegenerative diseases has gained increasing attention in recent years, and evidence suggests that gut dysbiosis may contribute to disease development and progression. Clinical studies have shown alterations in the composition of the gut microbiota in multiple sclerosis patients, with a decrease in beneficial bacteria and an increase in pro-inflammatory bacteria. Furthermore, changes within the microbial community have been linked to the pathogenesis of Parkinson’s disease and Alzheimer’s disease. Microbiota–gut–brain communication can impact neurodegenerative diseases through various mechanisms, including the regulation of immune function, the production of microbial metabolites, as well as modulation of host-derived soluble factors. This review describes the current literature on the gut–brain axis and highlights novel communication systems that allow cross-talk between the gut microbiota and the host that might influence the pathogenesis of neuroinflammation and neurodegeneration.
CRIS-Team Scopus Importer:2023-11-03
Keywords: gut–brain-axis; microbial dysbiosis; neurodegenerative diseases

Impact of patient characteristics on the clinical efficacy of mongersen (GED-0301), an oral Smad7 antisense oligonucleotide, in active Crohn's disease - Monteleone, G.; Di Sabatino, Antonio; Ardizzone, Sandro; Pallone, F.; Usiskin, K.; Zhan, X.; Rossiter, G.; Neurath, Markus (Alimentary Pharmacology & Therapeutics, 2016)
In a phase 2 study, mongersen, an oral antisense oligonucleotide targeting Smad7, was effective in inducing clinical remission in approximately 60% of patients with active Crohn's disease (CD).In a post hoc analysis to evaluate those patient disease characteristics that may have influenced the efficacy and safety of mongersen therapy.Patients with steroid-dependent/resistant, active CD were randomised to mongersen 10, 40 or 160 mg/day or placebo for 2 weeks; patients were followed for 10 weeks. Clinical remission [Crohn's Disease Activity Index (CDAI) score <150] and clinical response (CDAI score reduction >=100 points) were assessed at weeks 2, 4 and 12 for these subgroups: disease duration <5/>=5 years, human serum C-reactive protein (hsCRP) <3/>=3 mg/L, and CDAI at baseline <=260/>260. Additional patient baseline and disease characteristics were explored.Clinical remission and response rates were significantly higher in patients receiving mongersen 40 and 160 mg/day but not 10 mg/day vs. placebo and independent of disease duration and hsCRP. Patients with baseline CDAI <=260 had significantly higher remission rates with 40 and 160 mg/day. In patients with baseline CDAI >260, remission rates were statistically greater with 160 mg/day and numerically better with 40 mg/day vs. placebo. Adverse event rates were similar across treatment groups. Mongersen was safe and well tolerated.Patients with higher CDAI scores achieved clinical remission most frequently with the highest mongersen dose. Disease duration and baseline human serum C-reactive protein did not appear to significantly impact efficacy of mongersen in this study (EudraCT Number: 2011-002640-27.).
EVALuna2:2086

Improvement of clinical management and outcome in hepatocellular carcinoma nowadays compared with historical cohorts - Schellhaas, Barbara; Strobel, Deike; Stumpf, Miriam; Ganslmayer, Marion; Pfeifer, Lukas; Görtz, Rüdiger; Neurath, Markus; Zopf, Steffen (European Journal of Gastroenterology & Hepatology, 2018)
OBJECTIVES: Therapeutic approaches in the treatment of hepatocellular carcinoma (HCC) depend on tumour stage, liver function and patient comorbidities. The aim of this study was to investigate the influence of tumour stage and therapeutic approach on overall survival in HCC. MATERIALS AND METHODS: Two hundred and fourteen patients with HCC diagnosed between December 2012 and May 2017 were assessed retrospectively for tumour stage [Barcelona Clinic Liver Cancer (BCLC)], liver function (Child-Pugh score), therapeutic approach and outcome (mean survival time). The results were compared to two historical cohorts from our centre diagnosed between 1999 and 2013 and 1988 and 1999, respectively. RESULTS: Nowadays, HCC is diagnosed in earlier tumour stages and with better liver function compared with the historical cohorts (P<0.001). Survival times depend on both BCLC stages and liver function for all therapeutic approaches. The 1-year survival rate in the present cohort was 79.4% compared with 58.6% in the historical cohort.In terms of BCLC stages, therapeutic approaches followed HCC guidelines in 43.9% of cases.Whereas the percentage of patients receiving resection or ablation did not change between the historical and the present cohort, there was a tendency towards a decrease in transarterial chemoembolization, with a shift towards selective internal radiotherapy, accompanied by an increase in systemic therapy with sorafenib.Also, the percentage of patients receiving single instead of multiple therapies was significantly higher in the present cohort compared with the historical cohort (P=0.016). In 62/83 patients receiving single therapy (64.7%), tumour remission was maintained during the period of follow-up. CONCLUSION: HCC is increasingly being diagnosed in earlier stages, so that single therapy is often sufficient. Besides BCLC stages, therapy in HCC must consider liver function, tumour location, local expertise and patients' comorbidities and preferences. Further research is needed to evaluate the benefit of early multimodal concepts. Therapeutic approaches in HCC remain individual decisions.
EVALuna2:35130

Increased Motility and Suppression of Ex Vivo–Expanded Regulatory T Cells Designed for Adoptive Transfer Therapy in Ulcerative Colitis - Müller, Tanja; Liu, Lijuan; Czerwinski, Tina; Wiesinger, Manuel; Dedden, Mark; Paap, Eva-Maria; Ullrich, Karen; Atreya, Imke; Siegmund, Britta; Atreya, Raja; Fabry, Ben; Berking, Carola; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2023)
CRIS-Team Scopus Importer:2023-06-02

Increase of liver stiffness and altered bile acid metabolism after triple CFTR modulator initiation in children and young adults with cystic fibrosis - Schnell, Alexander; Jüngert, Jörg M.; Klett, Daniel; Hober, Hannah; Kaiser, Natalie; Ruppel, Renate; Geppert, Annika; Tremel, Christina; Sobel, Julia; Plattner, Erika; Schmitt-Grohe, Sabina; Zirlik, Sabine; et al. (Liver International, 2023)
Background: Novel cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies (elexacaftor/tezacaftor/ivacaftor—ETI) promise clinically significant and sustained improvements for patients with cystic fibrosis (CF). In this study, we investigated the impact of ETI therapy on liver stiffness and bile acid metabolism in a cohort of children and young adults with CF. Methods: A prospective observational study (NCT05576324) was conducted from September 2020 to November 2021 enrolling CF patients naive to ETI. Standard laboratory chemistry, sweat test, lung function, share wave velocity (SWV) derived by acoustic radiation force impulse imaging (ARFI) and serum bile acid profiles were assessed before and 6 months after induction of ETI therapy. Results: A total of 20 patients (10 aged <20 years) completed the study. While lung function and BMI improved after ETI therapy, ARFI SWV increased in CF patients <20 years of age (from 1.27 to 1.43 m/s, p = 0.023). Bile acid (BA) profiles revealed a decrease in unconjugated (5.75 vs 1.46, p = 0.007) and increase in glycine-conjugated derivatives (GCDCA) (4.79 vs 6.64 p = 0.016). There was a positive correlation between ARFI SWV values and GCDCA (r = 0.80, p < 0.0001). Glycine-conjugated BA provided high diagnostic accuracy to predict increased ARFI measurements (AUC 0.90) and clinical (Colombo) CFLD grading (AUC 0.97). Conclusions: ARFI SWV and bile acid profiles provide evidence for early increase in liver stiffness and altered bile acid metabolism in young CF patients after initiation of ETI and may serve as synergistic measures for detection of hepatic complications during ETI therapy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: ARFI; bile acids; CFLD; cystic fibrosis

Inducible mouse models of colon cancer for the analysis of sporadic and inflammation-driven tumor progression and lymph node metastasis - Neufert, Clemens; Heichler, Christina; Brabletz, Thomas; Scheibe, Kristina; Boonsanay, Verawan; Greten, Florian R.; Neurath, Markus (Nature Protocols, 2020)
Despite advances in the detection and therapy of colorectal cancer (CRC) in recent years, CRC has remained a major challenge in clinical practice. Although alternative methods for modeling CRC have been developed, animal models of CRC remain helpful when analyzing molecular aspects of pathogenesis and are often used to perform preclinical in vivo studies of potential therapeutics. This protocol updates our protocol published in 2007, which provided an azoxymethane (AOM)-based setup for investigations into sporadic (Step 5A) and, when combined with dextran sodium sulfate (Step 5B), inflammation-associated tumor growth. This update also extends the applications beyond those of the original protocol by including an option in which AOM is serially applied to mice with p53 deficiency in the intestinal epithelium (Step 5C). In this model, the combination of p53 deficiency and AOM promotes tumor development, including growth of invasive cancers and lymph node metastasis. It also provides details on analysis of colorectal tumor growth and metastasis, including analysis of partial epithelial-to-mesenchymal transition, cell isolation and co-culture studies, high-resolution mini-endoscopy, light-sheet fluorescence microscopy and micro-CT imaging in mice. The target audience for our protocol is researchers who plan in vivo studies to address mechanisms influencing sporadic or inflammation-driven tumor development, including the analysis of local invasiveness and lymph node metastasis. It is suitable for preclinical in vivo testing of novel drugs and other interventional strategies for clinical translation, plus the evaluation of emerging imaging devices/modalities. It can be completed within 24 weeks (using Step 5A/C) or 10 weeks (using Step 5B).
CRIS-Team WoS Importer:2021-01-01

Induction of Intestinal Graft-versus-host Disease and Its Mini-endoscopic Assessment in Live Mice - Buchele, Vera; Büttner-Herold, Maike; Vogler, Tina; Neurath, Markus; Hildner, Kai (Journal of Visualized Experiments, 2019)
Acute graft-versus-host disease (GvHD) represents the most severe complication that patients previously undergoing allogeneic hematopoietic stem cell transplantation (allo-HCT) face and is frequently associated with a poor clinical outcome. While, for instance, GvHD manifestations of the skin are usually responsive to established immune-suppressive therapies and are, hence, not taking a fatal course, the presence and the intensity of intestinal GvHD, especially of the mid-to-lower parts of the gut, strongly influence the outcome and overall survival of patients with acute GvHD. Therapeutic options are essentially limited to the classic immune-suppressive agents yielding only moderate disease-mitigating effects. Hence, detailed knowledge about the tissue-resident immune cascade, changes in the intestinal microbiota, and the stromal response prior, upon, and after intestinal GvHD onset are urgently needed to understand the events and mechanisms underlying its pathogenesis and to develop innovative therapeutic options. Murine models of GvHD are frequently employed to identify and functionally assess molecules and pathways putatively driving intestinal GvHD. However, means to specifically monitor and evaluate intestinal inflammation over time are essentially lacking since established scores to assess and grade acute GvHD are routinely comprised of various parameters which rather reflect systemic GvHD manifestations. The detailed evaluation of intestinal GvHD has been restricted to studies using euthanized mice, thereby essentially excluding longitudinal (i.e., kinetic) analyses of the colonic compartment under a given experimental condition (e.g., antibody-mediated blockade of a proinflammatory cytokine) in live mice (i.e., in vivo). The mini-endoscopic in situ assessment of the distal colon of alloHCT-treated mice described here allows a) a detailed macroscopic evaluation of different aspects of intestinal inflammation and b) the option to collect tissue samples for downstream analyses at various time points over the course of the observation period. Overall, the mini-endoscopic approach provides a major advance in preclinical noninvasive monitoring and assessment of intestinal GvHD.
CRIS-Team WoS Importer:2019-04-12

Induction of microRNA-124 as a novel therapeutic concept in ulcerative colitis - Atreya, Raja; Neurath, Markus (Lancet Gastroenterology and Hepatology, 2022)
CRIS-Team Scopus Importer:2022-10-21

Induction therapy with the selective interleukin-23 inhibitor risankizumab in patients with moderate-to-severe Crohn's disease: a randomised, double-blind, placebo-controlled phase 2 study - Feagan, Brian G.; Sandborn, William J.; D'Haens, Geert; Panes, Julian; Kaser, Arthur; Ferrante, Marc; Louis, Edouard; Franchimont, Denis; Dewit, Olivier; Seidler, Ursula; Kim, Kyung-Jo; Neurath, Markus; et al. (Lancet, 2017)
BACKGROUND: The interleukin-23 pathway is implicated genetically and biologically in the pathogenesis of Crohn's disease. We aimed to assess the efficacy and safety of risankizumab (BI 655066, Boehringer Ingelheim, Ingelheim, Germany), a humanised monoclonal antibody targeting the p19 subunit of interleukin-23, in patients with moderately-to-severely active Crohn's disease. METHODS: In this randomised, double-blind, placebo-controlled phase 2 study, we enrolled patients at 36 referral sites in North America, Europe, and southeast Asia. Eligible patients were aged 18-75 years, with a diagnosis of Crohn's disease for at least 3 months, assessed as moderate-to-severe Crohn's disease at screening, defined as a Crohn's Disease Activity Index (CDAI) of 220-450, with mucosal ulcers in the ileum or colon, or both, and a Crohn's Disease Endoscopic Index of Severity (CDEIS) of at least 7 (≥4 for patients with isolated ileitis) on ileocolonoscopy scored by a masked central reader. Patients were randomised 1:1:1 using an interactive response system to a double-blind investigational product, and stratified by previous exposure to TNF antagonists (yes vs no). Patients received intravenous 200 mg risankizumab, 600 mg risankizumab, or placebo, at weeks 0, 4, and 8. The primary outcome was clinical remission (CDAI <150) at week 12 (intention-to-treat population). Safety was assessed in patients who received at least one dose of study drug. This study is registered with ClinicalTrials.gov, number NCT02031276. FINDINGS: Between March, 2014, and September, 2015, 213 patients were screened, and 121 patients randomised. At baseline, 113 patients (93%) had been previously treated with at least one tumour necrosis factor (TNF) antagonist (which had failed in 96 [79%]). At week 12, 25 (31%) of 82 risankizumab patients (pooled 41 patients in 200 mg and 41 patients in 600 mg arms) had clinical remission versus six (15%) of 39 placebo patients (difference vs placebo 15·0%, 95% CI 0·1 to 30·1; p=0·0489). Ten (24%) of 41 patients who received 200 mg risankizumab had clinical remission (9·0%, -8·3 to 26·2; p=0·31) and 15 (37%) of 41 who received the 600 mg dose (20·9%, 2·6 to 39·2; p=0·0252). 95 (79%) patients had adverse events (32 in the placebo group, 32 randomised to 200 mg risankizumab, 31 randomised to 600 mg risankizumab); 18 had severe adverse events (nine, six, three); 12 discontinued (six, five, one); 24 had serious adverse events (12, nine, three). The most common adverse event was nausea and most common serious adverse event was worsening of underlying Crohn's disease. No deaths occurred. INTERPRETATION: In this short-term study, risankizumab was more effective than placebo for inducing clinical remission in patients with active Crohn's disease. Therefore, selective blockade of interleukin-23 via inhibition of p19 might be a viable therapeutic approach in Crohn's disease. FUNDING: Boehringer Ingelheim.
EVALuna2:33817

Inflammatory bowel diseases : Crohn's disease and ulcerative colitis - Fischer, Sören; Rath, T.; Neurath, Markus (Internist, 2018)
Inflammatory bowel diseases (IBD) are complex diseases. Epidemiological studies suggest rising incidences in industrialized countries. The article is based on a literature search in PubMed and is oriented on the current guidelines published by the European Crohn's and Colitis Organisation. IBD are characterized by chronic diarrhoea, abdominal pain and peranal haemorrhage. Extraintestinal manifestations commonly affect joints, skin, eyes and bile tracts. Early diagnosis and therapeutic intervention determine individual patient outcome. Medical treatment currently includes aminosalicylates, corticosteroids, thiopurines, calcineurin inhibitors and biologicals. IBDs require anti-inflammatory and if necessary immunosuppressive therapy. Due to extraintestinal complications and the possible need for surgical intervention, an interdisciplinary approach is important.
EVALuna2:35158

Inflammatory bowel diseases - therapy update 2022 Chronisch-entzündliche Darmerkrankungen - Atreya, Raja; Neurath, Markus (Deutsche Medizinische Wochenschrift, 2022)
Growing insights into the underlying immunopathogenesis of inflammatory bowel diseases (IBD) have led to the advent of targeted therapies, which selectively target pivotal mediators of the inflammatory process. This has enabled us to define and achieve novel therapeutic outcomes to prevent disease-associated complications and halt the progressive course of disease. In addition to already available treatment options, the selective Janus kinase type 1 inhibitor filgotinib and the selective sphingosine-1-phosphate receptor modulator Ozanimod have recently been approved for the treatment of ulcerative colitis patients. Furthermore, positive phase 2/3 induction and maintenance trial results have been reported for representatives of the class of IL-23p19 inhibitors, which are expected to further increase our therapeutic possibilities. All these agents can be applied as first-line or also subsequent treatment options and recent head-to-head trials have helped us to position these substances in our therapeutic algorithm. Nevertheless, there is still the currently unmet clinical need do establish predictive markers of response to identify the subgroup of IBD patients, that have a heightened probability of response to each therapy. In the following, we will give an overview of the recently approved or in late-stage clinical development tested substances and discuss their positioning in our therapeutic armamentarium.
CRIS-Team Scopus Importer:2022-04-01

Influence of Amino Acids and Exercise on Muscle Protein Turnover, Particularly in Cancer Cachexia - Pradhan, Rashmita; Dieterich, Walburga; Natarajan, Anirudh; Schwappacher, Raphaela; Reljic, Dejan; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (Cancers, 2024)
Cancer cachexia is a multifaceted syndrome that impacts individuals with advanced cancer. It causes numerous pathological changes in cancer patients, such as inflammation and metabolic dysfunction, which further diminish their quality of life. Unfortunately, cancer cachexia also increases the risk of mortality in affected individuals, making it an important area of focus for cancer research and treatment. Several potential nutritional therapies are being tested in preclinical and clinical models for their efficacy in improving muscle metabolism in cancer patients. Despite promising results, no special nutritional therapies have yet been validated in clinical practice. Multiple studies provide evidence of the benefits of increasing muscle protein synthesis through an increased intake of amino acids or protein. There is also increasing evidence that exercise can reduce muscle atrophy by modulating protein synthesis. Therefore, the combination of protein intake and exercise may be more effective in improving cancer cachexia. This review provides an overview of the preclinical and clinical approaches for the use of amino acids with and without exercise therapy to improve muscle metabolism in cachexia.
CRIS-Team Scopus Importer:2024-06-07
Keywords: amino acids; cancer cachexia; exercise; inflammation; oxidative stress

Influence of cancer and acute inflammatory disease on taste perception: a clinical pilot study - Schalk, Priska; Kohl, M.; Herrmann, H. J.; Schwappacher, R.; Rimmele, Martina; Büttner, Andrea; Neurath, Markus; Zopf, Yurdagül; Siebler, Jürgen (Supportive Care in Cancer, 2018)
Cancer patients are at high risk of malnutrition and tumor cachexia further increasing morbidity and mortality. Reasons for cachexia are not clear yet, but inflammatory processes as well as the occurrence of taste disorders reducing nutrient uptake are discussed to play key roles. The purpose of this study was to gain insight into causative factors of taste disturbance in cancer patients. Does the cancer itself, inflammatory processes or cancer therapy influence taste disorders?To capture an underlying taste disorder patients with cancer (n = 42), acutely hospitalized inflammatory disease patients (n = 57) and healthy controls (n = 39) were examined. To assess the influence of chemotherapy, patients with and without chemotherapy were compared. Taste tests were performed according to DIN ISO 3972:2011. Inflammation was recorded using laboratory parameters. Statistical evaluation was conducted using the Software R.Cancer patients showed significantly increased taste thresholds for sweet, salty, and umami compared to healthy controls. There were no significant differences in taste detection and recognition between patients with former, current, or without chemotherapeutical treatment. Patients with an acute inflammatory disease showed an increased taste threshold for umami compared to healthy controls.It could be shown that cancer patients suffer from taste disorders irrespective of an existing chemotherapeutical treatment. Cancer-related inflammation appears to have a greater impact on taste perception than an acute inflammatory process. Therefore, an adapted dietary adjustment should be carried out at an early stage for cancer patients in order to avoid nutritional disorders caused by a taste disorder.
Keywords: Cancer; Taste disturbance; Inflammatory disease; Cachexia; Malnutrition

Influence of low FODMAP and gluten-free diets on disease activity and intestinal microbiota in patients with non-celiac gluten sensitivity - Dieterich, Walburga; Schuppan, Detlef; Schink, Monic; Schwappacher, Raphaela; Wirtz, Stefan; Agaimy, Abbas; Neurath, Markus; Zopf, Yurdagül (Clinical Nutrition, 2019)
Background & aims: Non-celiac gluten sensitivity (NCGS) is characterized by intestinal and extra intestinal symptoms triggered by ingestion of gluten. However, non-gluten triggers have recently been implicated, and a FODMAP (fermentable oligo-, di-, monosaccharides and polyols)-reduced diet can partially improve symptoms in NCGS. Our aim was to analyze the effect of a low FODMAP versus a gluten-free diet (GFD) on clinical symptoms, psychological well-being, intestinal inflammation and integrity, and stool microbiota.
CRIS-Team WoS Importer:2019-05-21

Inhibiting Interleukin 36 Receptor Signaling Reduces Fibrosis in Mice with Chronic Intestinal Inflammation - Scheibe, Kristina; Kersten, Christina; Schmied, Anabel; Vieth, Michael; Primbs, Tatjana; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Claussen, Jing; Klimowicz, Alexander C.; Zheng, Jie; Baum, Patrick; Meyer, Sebastian; et al. (Gastroenterology, 2018)
BACKGROUND & AIMS: Intestinal fibrosis is a long-term complication in inflammatory bowel diseases (IBD) frequently resulting in functional damage, bowel obstruction, and surgery. Interleukin 36 (IL36) is a group of cytokines in the IL1 family with inflammatory effects. We studied expression of IL36 and its receptor, interleukin 1 receptor like 2 (IL1RL2 or IL36R) in development of intestinal fibrosis in human tissues and mice. METHODS: We obtained intestinal tissues from 92 patients with Crohn´s disease (CD), 48 patients with ulcerative colitis (UC), and 26 patients without inflammatory bowel diseases (controls). Tissues were analyzed by histology to detect fibrosis and immunohistochemistry to determine the distribution of fibroblasts and levels of IL36R ligands. Human and mouse fibroblasts were incubated with IL36 or control medium, and transcriptome-wide RNA sequences were analyzed. Mice were given neutralizing antibodies against IL36R and we studied intestinal tissues from Il1rl2-/- mice; colitis and fibrosis was induced in mice by repetitive administration of DSS or TNBS. Bone marrow cells were transplanted from Il1rl2-/- to irradiated wild-type mice and intestinal tissues were analyzed. Antibodies against IL36R were applied to mice with established chronic colitis and fibrosis and intestinal tissues were studied. RESULTS: Mucosal and submucosal tissues from patients with CD or UC had higher levels of collagens including type VI collagen compared to tissues from controls. In tissues from patients with fibrostenotic CD, significantly higher levels of IL36A were noted, which correlated with high numbers of activated fibroblasts that expressed alpha smooth muscle actin. IL36R activation of mouse and human fibroblasts resulted in expression of genes that regulate fibrosis and tissue remodeling, as well as expression of collagen type VI. Il1rl2-/- mice and mice given injections of an antibody against IL36R developed less severe colitis and fibrosis following administration of DSS or TNBS, but bone marrow cells from Il1rl2-/- mice did not prevent induction of colitis and fibrosis. Injection of antibodies against IL36R significantly reduced established fibrosis in mice with chronic intestinal inflammation. CONCLUSION: We found higher levels of IL36A in fibrotic intestinal tissues from patients with IBD, compared with controls. IL36 induced expression of genes that regulate fibrogenesis in fibroblasts. Inhibition or knockout of the IL36R in mice reduces chronic colitis and intestinal fibrosis. Agents designed to block IL36R signaling could be developed for prevention and treatment of intestinal fibrosis in patients with IBD.
EVALuna2:35123

Inhibiting PGGT1B Disrupts Function of RHOA, Resulting in T-cell Expression of Integrin α4β7 and Development of Colitis in Mice - Lopez Posadas, Rocío; Fastancz, Petra; Martínez-Sánchez, Luz del Carmen; Panteleev-Ivlev, Julia; Thonn, Veronika; Kisseleva, Tatyana; Becker, Lukas S.; Schulz-Kuhnt, Anja; Zundler, Sebastian; Wirtz, Stefan; Atreya, Raja; Carlé, Birgitta-Elisabeth; et al. (Gastroenterology, 2019)
Background & Aims: It is not clear how regulation of T-cell function is altered during development of inflammatory bowel diseases (IBD). We studied the mechanisms by which geranylgeranyltransferase-mediated prenylation controls T-cell localization to the intestine and chronic inflammation. Methods: We generated mice with T-cell–specific disruption of the geranylgeranyltransferase type I, beta subunit gene (Pggt1b), called Pggt1bΔCD4 mice, or the ras homolog family member A gene (Rhoa), called RhoaΔCD4 mice. We also studied mice with knockout of CDC42 or RAC1 and wild-type mice (controls). Intestinal tissues were analyzed by histology, multiphoton and confocal microscopy, and real-time polymerase chain reaction. Activation of CDC42, RAC1, and RHOA were measured with G-LISA, cell fractionation, and immunoblots. T cells and lamina propria mononuclear cells from mice were analyzed by flow cytometry or transferred to Rag1–/– mice. Mice were given injections of antibodies against integrin alpha4beta7 or gavaged with the RORC antagonist GSK805. We obtained peripheral blood and intestinal tissue samples from patients with and without IBD and analyzed them by flow cytometry. Results: Pggt1bΔCD4 mice developed spontaneous colitis, characterized by thickening of the intestinal wall, edema, fibrosis, accumulation of T cells in the colon, and increased expression of inflammatory cytokines. Compared with control CD4+ T cells, PGGT1B-deficient CD4+ T cells expressed significantly higher levels of integrin alpha4beta7, which regulates their localization to the intestine. Inflammation induced by transfer of PGGT1B-deficient CD4+ T cells to Rag1–/– mice was blocked by injection of an antibody against integrin alpha4beta7. Lamina propria of Pggt1bΔCD4 mice had increased numbers of CD4+ T cells that expressed RORC and higher levels of cytokines produced by T-helper 17 cells (granulocyte-macrophage colony-stimulating factor, interleukin [IL]17A, IL17F, IL22, and tumor necrosis factor [TNF]). The RORC inverse agonist GSK805, but not antibodies against IL17A or IL17F, prevented colitis in Pggt1bΔCD4 mice. PGGT1B-deficient CD4+ T cells had decreased activation of RHOA. RhoAΔCD4 mice had a similar phenotype to Pggt1bΔCD4 mice, including development of colitis, increased numbers of CD4+ T cells in colon, increased expression of integrin alpha4beta7 by CD4+ T cells, and increased levels of IL17A and other inflammatory cytokines in lamina propria. T cells isolated from intestinal tissues from patients with IBD had significantly lower levels of PGGT1B than tissues from individuals without IBD. Conclusion: Loss of PGGT1B from T cells in mice impairs RHOA function, increasing CD4+ T-cell expression of integrin alpha4beta7 and localization to colon, resulting in increased expression of inflammatory cytokines and colitis. T cells isolated from gut tissues from patients with IBD have lower levels of PGGT1B than tissues from patients without IBD.
CRIS-Team Scopus Importer:2019-10-08
Keywords: IBD; Immune Regulation; Mouse Models; Prenylation

Innate Lymphoid Cells as Regulators of Epithelial Integrity: Therapeutic Implications for Inflammatory Bowel Diseases - Schulz-Kuhnt, Anja; Neurath, Markus; Wirtz, Stefan; Atreya, Imke (Frontiers in Medicine, 2021)
The occurrence of epithelial defects in the gut relevantly contributes to the pathogenesis of inflammatory bowel diseases (IBD), whereby the impairment of intestinal epithelial barrier integrity seems to represent a primary trigger as well as a disease amplifying consequence of the chronic inflammatory process. Besides epithelial cell intrinsic factors, accumulated and overwhelmingly activated immune cells and their secretome have been identified as critical modulators of the pathologically altered intestinal epithelial cell (IEC) function in IBD. In this context, over the last 10 years increasing levels of attention have been paid to the group of innate lymphoid cells (ILCs). This is in particular due to a preferential location of these rather newly described innate immune cells in close proximity to mucosal barriers, their profound capacity to secrete effector cytokines and their numerical and functional alteration under chronic inflammatory conditions. Aiming on a comprehensive and updated summary of our current understanding of the bidirectional mucosal crosstalk between ILCs and IECs, this review article will in particular focus on the potential capacity of gut infiltrating type-1, type-2, and type-3 helper ILCs (ILC1s, ILC2s, and ILC3s, respectively) to impact on the survival, differentiation, and barrier function of IECs. Based on data acquired in IBD patients or in experimental models of colitis, we will discuss whether the different ILC subgroups could serve as potential therapeutic targets for maintenance of epithelial integrity and/or mucosal healing in IBD.
CRIS-Team Scopus Importer:2021-04-23
Keywords: colitis; cytokines; ILC plasticity; inflammatory bowel diseases; innate lymphoid cells; intestinal epithelium

Innovative Diagnostic Endoscopy in Inflammatory Bowel Diseases: From High-Definition to Molecular Endoscopy - Bojarski, Christian; Waldner, Maximilian; Rath, Timo; Schürmann, Sebastian; Neurath, Markus; Atreya, Raja; Siegmund, Britta (Frontiers in Medicine, 2021)
High-definition endoscopy is one essential step in the initial diagnosis of inflammatory bowel disease (IBD) characterizing the extent and severity of inflammation, as well as discriminating ulcerative colitis (UC) from Crohn's disease (CD). Following general recommendations and national guidelines, individual risk stratification should define the appropriate surveillance strategy, biopsy protocol and frequency of endoscopies. Beside high-definition videoendoscopy the application of dyes applied via a spraying catheter is of additional diagnostic value with a higher detection rate of intraepithelial neoplasia (IEN). Virtual chromoendoscopy techniques (NBI, FICE, I-scan, BLI) should not be recommended as a single surveillance strategy in IBD, although newer data suggest a higher comparability to dye-based chromoendoscopy than previously assumed. First results of oral methylene blue formulation are promising for improving the acceptance rate of classical chromoendoscopy. Confocal laser endomicroscopy (CLE) is still an experimental but highly innovative endoscopic procedure with the potential to contribute to the detection of dysplastic lesions. Molecular endoscopy in IBD has taken application of CLE to a higher level and allows topical application of labeled probes, mainly antibodies, against specific target structures expressed in the tissue to predict response or failure to biological therapies. First pre-clinical and in vivo data from label-free multiphoton microscopy (MPM) are now available to characterize mucosal and submucosal inflammation on endoscopy in more detail. These new techniques now have opened the door to individualized and highly specific molecular imaging in IBD in the future and pave the path to personalized medicine approaches. The quality of evidence was stated according to the Oxford Center of evidence-based medicine (March 2009). For this review a Medline search up to January 2021 was performed using the words “inflammatory bowel disease,” “ulcerative colitis,” “crohn's disease,” “chromoendoscopy,” “high-definition endoscopy,” “confocal laser endomicroscopy,” “confocal laser microscopy,” “molecular imaging,” “multiphoton microscopy.”
CRIS-Team Scopus Importer:2021-08-13
Keywords: chromoendoscopy; confocal laser microscopy; high-definition endoscopy; molecular endoscopy; multiphoton microscopy

Innovative techniques in evaluating the esophagus; imaging of esophageal morphology and function; and drugs for esophageal disease - Neumann, Helmut; Neurath, Markus; Vieth, Michael; Lever, Frederiek M.; Meijer, Gert J.; Lips, Irene M.; Mcmahon, Barry P.; Ruurda, J. P.; van Hillegersberg, R.; Siersema, P.; Levine, Marc S.; Scharitzer, Martina; et al. (Blackwell Publishing Inc., 2013)
This paper reporting on techniques for esophageal evaluation and imaging and drugs for esophageal disease includes commentaries on endoscopy techniques including dye-based high-resolution and dye-less high-definition endoscopy; the shift from CT to MRI guidance in tumor delineation for radiation therapy; the role of functional lumen imaging in measuring esophageal distensibility; electrical stimulation of the lower esophageal sphincter (LES) as an alternative to fundoduplication for treatment of gastroesophageal reflux disease (GERD); the morphological findings of reflux esophagitis and esophageal dysmotility on double-contrast esophagography; the value of videofluoroscopy in assessing protecting mechanisms in patients with chronic reflux or swallowing disorders; targeting visceral hypersensitivity in the treatment of refractory GERD; and the symptoms and treatments of nighttime reflux and nocturnal acid breakthrough (NAB). © 2013 New York Academy of Sciences.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Endoscopy; EndoStim; FLIP; GERD; Nighttime breakthrough; PPI; Swallowing; Videofluoroscopy

Integrating Immunologic Signaling Networks: The JAK/STAT Pathway in Colitis and Colitis-Associated Cancer - Zundler, Sebastian; Neurath, Markus (Vaccines, 2016)
Cytokines are believed to be crucial mediators of chronic intestinal inflammation in inflammatory bowel diseases (IBD) such as Crohn's disease (CD) and ulcerative colitis (UC). Many of these cytokines trigger cellular effects and functions through signaling via janus kinase (JAK) and signal transducer and activator of transcription (STAT) molecules. In this way, JAK/STAT signaling controls important events like cell differentiation, secretion of cytokines or proliferation and apoptosis in IBD in both adaptive and innate immune cells. Moreover, JAK/STAT signaling, especially via the IL-6/STAT3 axis, is believed to be involved in the transition of inflammatory lesions to tumors leading to colitis-associated cancer (CAC). In this review, we will introduce the main cellular players and cytokines that contribute to pathogenesis of IBD by JAK/STAT signaling, and will highlight the integrative function that JAK/STATs exert in this context as well as their divergent role in different cells and processes. Moreover, we will explain current concepts of the implication of JAK/STAT signaling in CAC and finally discuss present and future therapies for IBD that interfere with JAK/STAT signaling.
EVALuna2:2080

Integrin αVβ6: Autoantigen and Driver of Epithelial Remodeling in Colon and Bile Ducts in Primary Sclerosing Cholangitis and Inflammatory Bowel Disease. - Roth, Dominik; Düll, Miriam; Horst, Ludwig J.; Lindemann, Aylin; Malzer, Xenia; Koop, Kristina; Zundler, Sebastian; Vetter, Marcel; Jefremow, André; Atreya, Raja; Geppert, Carol-Immanuel; Weidemann, Sören; et al. (Journal of Crohns & Colitis, 2025)
BACKGROUND: Recently, autoantibodies directed against the epithelial adhesion protein integrin αVβ6 have been identified that are strongly associated with ulcerative colitis (UC). We aimed to elucidate whether anti-integrin αVβ6 (anti-αVβ6) is present in primary sclerosing cholangitis (PSC), its associated inflammatory bowel disease, or other cholestatic liver diseases and their persistence after proctocolectomy. METHODS: We detected anti-αVβ6 by an enzyme-linked immunosorbent assay in sera collected at 2 German tertiary centers, including healthy controls (N = 62), UC (N = 36), Crohn's disease (CD, N = 65), PSC-inflammatory bowel diseases (IBD) (78 samples from N = 41 patients), PSC without IBD (PSC, 41 samples from N = 18 patients), primary biliary cholangitis (PBC, N = 24), autoimmune hepatitis (AIH, N = 32), secondary sclerosing cholangitis (SSC, N = 12), and metabolic dysfunction-associated steatotic liver disease (MASLD, N = 24). In addition, sera after proctocolectomy were studied (44 samples/N = 10 patients). Immunofluorescent analyses were performed in tissue samples from liver, large bile duct from surgical resections, and colon of PSC patients. RESULTS: Anti-αVβ6 occurred in 91% of UC, 17% of CD, 73% of PSC-IBD, 39% of PSC, 4% of PBC, 14% of AIH, and 0% of healthy controls, SSC, or MASLD. Integrin αVβ6 is selectively expressed in disease-associated epithelia of both bile duct and colon. Anti-αVβ6 levels correlate moderately with intestinal disease activity in PSC-IBD, but only weakly with biliary disease. CONCLUSIONS: Anti-αVβ6 frequently occurs in patients suffering from PSC, especially in PSC-IBD. Anti-αVβ6 levels positively correlate to IBD activity in PSC-IBD, but may also occur in the absence of clinically manifest IBD in PSC.
EVALuna2:578869

Intensity and longevity of SARS-CoV-2 vaccination response in patients with immune-mediated inflammatory disease: a prospective cohort study. - Simon, David; Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Mößner, Johanna; Taubmann, Jule; Mutlu, Melek Yalcin; Knitza, Johannes; et al. (The Lancet Rheumatology, 2022)
Background: Concerns have been raised about the reduced immunogenicity of vaccines against SARS-CoV-2 in patients with immune-mediated inflammatory diseases and the higher risk of breakthrough infections. The objective of our study was to investigate the intensity and longevity of SARS-CoV-2 vaccination responses in patients with immune-mediated inflammatory diseases, and to assess the effects of diagnosis, treatment, and adapted vaccination schedules. Methods: SARS-CoV-2 IgG antibody response after SARS-CoV-2 vaccination was measured over time in a large prospective cohort of healthy controls and participants with immune-mediated inflammatory diseases (attending or admitted to affiliated centres) between Dec 15, 2020, and Dec 1, 2021. Cohort participants with immune-mediated inflammatory diseases and control participants with no diagnosis of immune-mediated inflammatory diseases, were eligible for this analysis. Demographic data and disease-specific data were collected using a questionnaire. Humoral response was compared across treatment and disease groups, and with respect to the receipt of additional vaccinations. SARS-CoV-2 antibody response was measured by ELISA using optical density ratio units and modelled over time with age and sex adjustment using mixed-effects models. Using these models, marginal mean antibody titres and marginal risks of a poor response (optical density ratio <1·1) were calculated for each week starting from week 8 after the first vaccination to week 40. Findings: Among 5076 individuals registered, 2535 participants with immune-mediated inflammatory diseases (mean age 55·0 [15·2] years; 1494 [58·9%] women and 1041 [41·1%] men) and 1198 healthy controls (mean age 40·7 [13·5] years; 554 [46·2%] women and 644 [53·8%] men) were included in this analysis. Mean antibody titres were higher in healthy controls compared with people with immune-mediated inflammatory diseases at all timepoints, with a peak antibody response in healthy controls (mean optical density ratio 12·48; 95% CI 11·50-13·53) of more than twice that in participants with immune-mediated inflammatory diseases (5·50; 5·23-5·77; mean difference 6·98; 5·92-8·04). A poor response to vaccination was observed in participants with immune-mediated inflammatory diseases who were taking B-cell inhibitors (peak mean difference from healthy controls 11·68; 10·07-13·29) and T-cell inhibitors (peakmean difference from healthy controls 10·43; 8·33-12·53). Mean differences in antibody responses between different immune-mediated inflammatory diseases were small. Participants with immune-mediated inflammatory diseases who were given a third vaccine dose had higher mean antibody titres than did healthy controls vaccinated with two vaccine doses at 40 weeks after the initial vaccination (mean difference 1·34; 0·01-2·69). Interpretation: People with immune-mediated inflammatory diseases show a lower and less durable SARS-CoV-2 vaccination response and are at risk of losing humoral immune protection. Adjusted vaccination schedules with earlier booster doses or more frequent re-doses, or both, could better protect people with immune-mediated inflammatory diseases. Funding: Deutsche Forschungsgemeinschaft, Bundesministerium für Bildung und Forschung, European Research Council, Innovative Medicine Initiative, Friedrich-Alexander-Universität Erlangen-Nürnberg, Else Kröner-Memorial Foundation.
EVALuna2:506737

Interferon Lambda Promotes Paneth Cell Death Via STAT1 Signaling in Mice and Is Increased in Inflamed Ileal Tissues of Patients With Crohn's Disease - Günther, Claudia; Ruder, Barbara; Stolzer, Iris; Dorner, Heidrun; He, Gui-Wei; Aden, Konrad; Strigli, Anne; Bittel, Miriam; Zeissig, Sebastian; Rosenstiel, Philip; Atreya, Raja; Neurath, Markus; et al. (Gastroenterology, 2019)
BACKGROUND & AIMS: Interferon lambda (IFNL) is expressed at high levels by intestinal epithelial cells (IECs) and mucosal immune cells in response to infection and inflammation. We investigated whether IFNL might contribute to pathogenesis of Crohn's disease (CD). METHODS: We obtained serum samples and terminal ileum biopsies from 47 patients with CD and 16 healthy individuals (controls). We measured levels of IFNL by enzyme-linked immunosorbent assay and immunohistochemistry and location of expression by confocal microscopy. Activation of IFNL signaling via STAT1 was measured in areas of no, mild, moderate, and severe inflammation and correlated with Paneth cell homeostasis and inflammation. IFNL expression and function were studied in wild-type mice and mice with intestinal epithelial cell-specific (Delta IEC) disruption or full-body disruption of specific genes (Mlkl(-/-), Stat1(Delta IEC), Casp8(Delta IEC), Casp8(Delta IEC)Ripk3(-/-), Casp8(Delta IEC)Tnfr(-/-), Casp8(Delta IEC)Mlkl(-/-), and Nod2(-/-) mice). Some mice were given tail vein injections of a vector encoding a secreted form of IFNL. Intestinal tissues were collected from mice and analyzed by immunohistochemistry and immunoblots. We generated 3-dimensional small intestinal organoids from mice and studied the effects of IFNL and inhibitors of STAT-signaling pathway. RESULTS: Patients with CD had significant increases in serum and ileal levels of IFNL compared with controls. Levels of IFNL were highest in ileum tissues with severe inflammation. High levels of IFNL associated with a reduced number of Paneth cells and increased cell death at the crypt bottom in inflamed ileum samples. Intestinal tissues from the ileum of wild-type mice injected with a vector expressing IFNL had reduced numbers of Paneth cells. IFNL-induced death of Paneth cells in mice did not occur via apoptosis, but required Mixed Lineage Kinase Domain Like (MLKL) and activation of Signal transducer and activator of transcription 1 (STAT1). In organoids, inhibitors of Janus kinase (JAK) signaling via STAT1 (glucocorticoids, tofacitinib, or filgotinib) reduced expression of proteins that mediate cell death and prevented Paneth cell death. CONCLUSIONS: Levels of IFNL are increased in serum and inflamed ileal tissues from patients with CD and associated with a loss of Paneth cells. Expression of a secreted form of IFNL in mice results in loss of Paneth cells from intestinal tissues, via STAT1 and MLKL, controlled by caspase 8. Strategies to reduce IFNL or block its effects might be developed for treatment of patients with CD affecting the terminal ileum.
Keywords: Inflammatory Bowel Diseases; Ileitis; Necroptosis; Cytokine

Interferon regulatory factor 1 (IRF-1) promotes intestinal group 3 innate lymphoid responses during Citrobacter rodentium infection - Schmalzl, Angelika; Leupold, Tamara; Kreiß, Lucas; Waldner, Maximilian; Schürmann, Sebastian; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Nature Communications, 2022)
Group 3 innate lymphoid cells (ILC3s) are crucial mediators of immunity and epithelial barrier function during immune responses against extracellular bacteria. Here, we identify Interferon regulatory factor 1 (IRF-1), a transcription factor previously associated with type 1 immunity, as an essential regulator of intestinal ILC3 accumulation and effector cytokine production. We demonstrate that IRF-1 is upregulated in the context of infection with the enteropathogen Citrobacter rodentium and that its presence is central for anatomical containment and prevention of pathogen dissemination. We furthermore show that IRF-1 is required in order for intestinal ILC3s to produce large amounts of the protective effector cytokine IL-22 early in the course of infection. On a molecular level, our data indicate that IRF-1 controls ILC3 numbers and their activation by direct transcriptional regulation of the IL-12Rβ1 chain, thereby allowing ILCs to physiologically respond to IL-23 stimulation.
CRIS-Team Scopus Importer:2022-10-14

Interferons at the crossroad of cell death pathways during gastrointestinal inflammation and infection - Stolzer, Iris; Ruder, Barbara; Neurath, Markus; Günther, Claudia (International Journal of Medical Microbiology, 2021)
Interferons (IFNs) are pleiotropic immune-modulatory cytokines that are well known for their essential role in host defense against viruses, bacteria, and other pathogenic microorganisms. They can exert both, protective or destructive functions depending on the microorganism, the targeted tissue and the cellular context. Interferon signaling results in the induction of IFN-stimulated genes (ISGs) influencing different cellular pathways including direct anti-viral/anti-bacterial response, immune-modulation or cell death. Multiple pathways leading to host cell death have been described, and it is becoming clear that depending on the cellular context, IFN-induced cell death can be beneficial for both: host and pathogen. Accordingly, activation or repression of corresponding signaling mechanisms occurs during various types of infection but is also an important pathway for gastrointestinal inflammation and tissue damage. In this review, we summarize the role of interferons at the crossroad of various cell death pathways in the gut during inflammation and infection.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Cell death; Gastrointestinal infection; IBD; Interferons

Interleukin-12: Functional activities and implications for disease - Zundler, Sebastian; Neurath, Markus (Cytokine & Growth Factor Reviews, 2015)
Interleukin-12 (IL-12) was the first member of the IL-12 family of cytokines to be identified and has therefore become its eponym. It is a heterodimeric protein of two subunits (p35, p40) secreted by phagocytic cells in response to pathogens and mainly acts through STAT4 to induce IFN-? production in T and NK cells. IFN-? in turn mediates proinflammatory functions and activates T-bet. As IL-12 engages in TH1 development, it is believed to represent an important link between innate and adaptive immunity. Following its identification and the finding of its association to TH1 commitment, great hopes were placed in IL-12 to become a target for therapeutic applications in multiple settings of autoimmunity and cancer. Though, the discovery of the related members of the IL-12 family and several rather disappointing attempts to translate experimental results into clinical practice, have relativized these hopes. Nevertheless, IL-12 remains a cytokine of outstanding importance with lots of unresolved questions. In this review, we will first briefly depict the biochemistry of the cytokine, its receptor and the related signal transduction, before summarizing the regulation of IL-12 production and its biological functions. We will then describe the current knowledge about the implication of IL-12 in different murine disease models as well as in the corresponding human conditions and comment on possible consequences for future clinical applications.
EVALuna2:2016

Interleukin 17 drives vascular inflammation, endothelial dysfunction, and arterial hypertension in psoriasis-like skin disease - Karbach, Susanne; Croxford, Andrew L.; Oelze, Matthias; Schueler, Rebecca; Minwegen, Daniel; Wegner, Joanna; Koukes, Lija; Yogev, Nir; Nikolaev, Alexei; Reissig, Sonja; Ullmann, Alexander; Knorr, Maike; et al. (Arteriosclerosis, Thrombosis, and Vascular Biology, 2014)
Interleukin (IL)-17A is regarded as an important cytokine to drive psoriasis, an inflammatory skin disease marked by increased cardiovascular mortality. We aimed to test the hypothesis that overproduction of IL-17A in the skin leading to dermal inflammation may systemically cause vascular dysfunction in psoriasis-like skin disease.Conditional overexpression of IL-17A in keratinocytes caused severe psoriasis-like skin inflammation in mice (K14-IL-17A(ind/+) mice), associated with increased reactive oxygen species formation and circulating CD11b(+) inflammatory leukocytes in blood, with endothelial dysfunction, increased systolic blood pressure, left ventricular hypertrophy, and reduced survival compared with controls. In K14-IL-17A(ind/+) mice, immunohistochemistry and flow cytometry revealed increased vascular production of the nitric oxide/superoxide reaction product peroxynitrite and infiltration of the vasculature with myeloperoxidase(+)CD11b(+)GR1(+)F4/80(-) cells accompanied by increased expression of the inducible nitric oxide synthase and the nicotinamide dinucleotide phosphate (NADPH) oxidase, nox2. Neutrophil depletion by anti-GR-1 antibody injections reduced oxidative stress in blood and vessels. Neutralization of tumor necrosis factor-? and IL-6 (both downstream of IL-17A) reduced skin lesions, attenuated oxidative stress in heart and blood, and partially improved endothelial dysfunction in K14-IL-17A(ind/+) mice.Dermal overexpression of IL-17A induces systemic endothelial dysfunction, vascular oxidative stress, arterial hypertension, and increases mortality mainly driven by myeloperoxidase(+)CD11b(+)GR1(+)F4/80(-) inflammatory cells. Depletion of the GR-1(+) immune cells or neutralization of IL-17A downstream cytokines by biologicals attenuates the vascular phenotype in K14-IL-17A(ind/+) mice.
EVALuna2:1859

Interleukin 36 receptor-inducible matrix metalloproteinase 13 mediates intestinal fibrosis - Koop, Kristina; Enderle, Karin; Hillmann, Miriam; Ruspeckhofer, Laura; Vieth, Michael; Sturm, Gregor; Trajanoski, Zlatko; Kühl, Anja A.; Atreya, Raja; Leppkes, Moritz; Baum, Patrick; Roy, Janine; et al. (Frontiers in Immunology, 2023)
Background: Fibrostenotic disease is a common complication in Crohn’s disease (CD) patients hallmarked by transmural extracellular matrix (ECM) accumulation in the intestinal wall. The prevention and medical therapy of fibrostenotic CD is an unmet high clinical need. Although targeting IL36R signaling is a promising therapy option, downstream mediators of IL36 during inflammation and fibrosis have been incompletely understood. Candidate molecules include matrix metalloproteinases which mediate ECM turnover and are thereby potential targets for anti-fibrotic treatment. Here, we have focused on understanding the role of MMP13 during intestinal fibrosis. Methods: We performed bulk RNA sequencing of paired colon biopsies taken from non-stenotic and stenotic areas of patients with CD. Corresponding tissue samples from healthy controls and CD patients with stenosis were used for immunofluorescent (IF) staining. MMP13 gene expression was analyzed in cDNA of intestinal biopsies from healthy controls and in subpopulations of patients with CD in the IBDome cohort. In addition, gene regulation on RNA and protein level was studied in colon tissue and primary intestinal fibroblasts from mice upon IL36R activation or blockade. Finally, in vivo studies were performed with MMP13 deficient mice and littermate controls in an experimental model of intestinal fibrosis. Ex vivo tissue analysis included Masson’s Trichrome and Sirius Red staining as well as evaluation of immune cells, fibroblasts and collagen VI by IF analysis. Results: Bulk RNA sequencing revealed high upregulation of MMP13 in colon biopsies from stenotic areas, as compared to non-stenotic regions of patients with CD. IF analysis confirmed higher levels of MMP13 in stenotic tissue sections of CD patients and demonstrated αSMA+ and Pdpn+ fibroblasts as a major source. Mechanistic experiments demonstrated that MMP13 expression was regulated by IL36R signaling. Finally, MMP13 deficient mice, as compared to littermate controls, developed less fibrosis in the chronic DSS model and showed reduced numbers of αSMA+ fibroblasts. These findings are consistent with a model suggesting a molecular axis involving IL36R activation in gut resident fibroblasts and MMP13 expression during the pathogenesis of intestinal fibrosis. Conclusion: Targeting IL36R-inducible MMP13 could evolve as a promising approach to interfere with the development and progression of intestinal fibrosis.
CRIS-Team Scopus Importer:2023-06-02
Keywords: collagen type VI; collagenase 3; extracellular matrix (ECM); IL-36; il36 receptor; intestinal fibrosis; matrix metalloproteinase 13 (MMP13); αSMA+ fibroblasts

Interobserver Agreement for Contrast-Enhanced Ultrasound (CEUS)-Based Standardized Algorithms for the Diagnosis of Hepatocellular Carcinoma in High-Risk Patients - Schellhaas, Barbara; Pfeifer, Lukas; Kielisch, Christian; Görtz, Rüdiger; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2018)
OBJECTIVES: This pilot study aimed at assessing interobserver agreement with two contrast-enhanced ultrasound (CEUS) algorithms for the diagnosis of hepatocellular carcinoma (HCC) in high-risk patients. METHODS: Focal liver lesions in 55 high-risk patients were assessed independently by three blinded observers with two standardized CEUS algorithms: ESCULAP (Erlanger Synopsis of Contrast-Enhanced Ultrasound for Liver Lesion Assessment in Patients at risk) and ACR-CEUS-LI-RADSv.2016 (American College of Radiology CEUS-Liver Imaging Reporting and Data System). Lesions were categorized according to size and ultrasound contrast enhancement in the arterial, portal-venous and late phase. Interobserver agreement for assessment of enhancement pattern and categorization was compared between both CEUS algorithms. Additionally, diagnostic accuracy for the definitive diagnosis of HCC was compared. Histology and/or CE-MRI and follow-up served as reference standards. RESULTS: 55 patients were included in the study (male/female, 44/ 11; mean age: 65.9 years). 90.9 % had cirrhosis. Histological findings were available in 39/55 lesions (70.9 %). Reference standard of the 55 lesions revealed 48 HCCs, 2 intrahepatic cholangiocellular carcinomas (ICCs), and 5 non-HCC-non-ICC lesions. Interobserver agreement was moderate to substantial for arterial phase hyperenhancement (ĸ = 0.53 - 0.67), and fair to moderate for contrast washout in the portal-venous or late phase (ĸ = 0.33 - 0.53). Concerning the CEUS-based algorithms, the interreader agreement was substantial for the ESCULAP category (ĸ = 0.64 - 0.68) and fair for the CEUS-LI-RADS® category (ĸ = 0.3 - 0.39). Disagreement between observers was mostly due to different perception of washout. CONCLUSION: Interobserver agreement is better for ESCULAP than for CEUS-LI-RADS®. This is mostly due to the fact that perception of contrast washout varies between different observers. However, interobserver agreement is good for arterial phase hyperenhancement, which is the key diagnostic feature for the diagnosis of HCC with CEUS in the cirrhotic liver.
EVALuna2:35127

Interobserver and intermodality agreement of standardized algorithms for non-invasive diagnosis of hepatocellular carcinoma in high-risk patients: CEUS-LI-RADS versus MRI-LI-RADS - Schellhaas, Barbara; Hammon, Matthias; Strobel, Deike; Pfeifer, Lukas; Kielisch, Christian; Görtz, Rüdiger; Janka, Rolf Matthias; Neurath, Markus; Uder, Michael; Seuß, Hannes; Cavallaro, Alexander Josef (European Radiology, 2018)
OBJECTIVES: We compared the interobserver agreement for the recently introduced contrast-enhanced ultrasound (CEUS)-based algorithm CEUS-LI-RADS (Liver Imaging Reporting and Data System) versus the well-established magnetic resonance imaging (MRI)-LI-RADS for non-invasive diagnosis of hepatocellular carcinoma (HCC) in high-risk patients. METHODS: Focal liver lesions in 50 high-risk patients (mean age 66.2 ± 11.8 years; 39 male) were assessed retrospectively with CEUS and MRI. Two independent observers reviewed CEUS and MRI examinations, separately, classifying observations according to CEUS-LI-RADSv.2016 and MRI-LI-RADSv.2014. Interobserver agreement was assessed with Cohen's kappa. RESULTS: Forty-three lesions were HCCs; two were intrahepatic cholangiocarcinomas; five were benign lesions. Arterial phase hyperenhancement was perceived less frequently with CEUS than with MRI (37/50 / 38/50 lesions = 74%/78% [CEUS; observer 1/observer 2] versus 46/50 / 44/50 lesions = 92%/88% [MRI; observer 1/observer 2]). Washout appearance was observed in 34/50 / 20/50 lesions = 68%/40% with CEUS and 31/50 / 31/50 lesions = 62%/62%) with MRI. Interobserver agreement was moderate for arterial hyperenhancement (ĸ = 0.511/0.565 [CEUS/MRI]) and "washout" (ĸ = 0.490/0.582 [CEUS/MRI]), fair for CEUS-LI-RADS category (ĸ = 0.309) and substantial for MRI-LI-RADS category (ĸ = 0.609). Intermodality agreement was fair for arterial hyperenhancement (ĸ = 0.329), slight to fair for "washout" (ĸ = 0.202) and LI-RADS category (ĸ = 0.218) CONCLUSION: Interobserver agreement is substantial for MRI-LI-RADS and only fair for CEUS-LI-RADS. This is mostly because interobserver agreement in the perception of washout appearance is better in MRI than in CEUS. Further refinement of the LI-RADS algorithms and increasing education and practice may be necessary to improve the concordance between CEUS and MRI for the final LI-RADS categorization. KEY POINTS: • CEUS-LI-RADS and MRI-LIRADS enable standardized non-invasive diagnosis of HCC in high-risk patients. • With CEUS, interobserver agreement is better for arterial hyperenhancement than for "washout". • Interobserver agreement for major features is moderate for both CEUS and MRI. • Interobserver agreement for LI-RADS category is substantial for MRI, and fair for CEUS. • Interobserver-agreement for CEUS-LI-RADS will presumably improve with ongoing use of the algorithm.
EVALuna2:34689

Interplay of GTPases and Cytoskeleton in Cellular Barrier Defects during Gut Inflammation - Lopez Posadas, Rocío; Stürzl, Michael; Atreya, Imke; Neurath, Markus; Britzen-Laurent, Nathalie (Frontiers in Immunology, 2017)
An essential role of the intestine is to build and maintain a barrier preventing the luminal gut microbiota from invading the host. This involves two coordinated physical and immunological barriers formed by single layers of intestinal epithelial and endothelial cells, which avoid the activation of local immune responses or the systemic dissemination of microbial agents, and preserve tissue homeostasis. Accordingly, alterations of epithelial and endothelial barrier functions have been associated with gut inflammation, for example during inflammatory bowel disease (IBD). The discriminative control of nutriment uptake and sealing toward potentially pathological microorganisms requires a profound regulation of para- and transcellular permeability. On the subcellular level, the cytoskeleton exerts key regulatory functions in the maintenance of cellular barriers. Increased epithelial/endothelial permeability occurs primarily as a result of a reorganization of cytoskeletal-junctional complexes. Pro-inflammatory mediators such as cytokines can induce cytoskeletal rearrangements, causing inflammation-dependent defects in gut barrier function. In this context, small GTPases of the Rho family and large GTPases from the Dynamin superfamily appear as major cellular switches regulating the interaction between intercellular junctions and actomyosin complexes, and in turn cytoskeleton plasticity. Strikingly, some of these proteins, such as RhoA or guanylate-binding protein-1 (GBP-1) have been associated with gut inflammation and IBD. In this review, we will summarize the role of small and large GTPases for cytoskeleton plasticity and epithelial/endothelial barrier in the context of gut inflammation.
EVALuna2:15286

Intestinal Barrier Healing Is Superior to Endoscopic and Histologic Remission for Predicting Major Adverse Outcomes in Inflammatory Bowel Disease: The Prospective ERIca Trial - Rath, Timo; Atreya, Raja; Bodenschatz, Julia; Uter, Wolfgang; Geppert, Carol-Immanuel; Vitali, Francesco; Fischer, Sarah; Waldner, Maximilian; Colombel, Jean Frédéric; Hartmann, Arndt; Neurath, Markus (Gastroenterology, 2023)
Background & Aims: Endoscopic and histologic remission have emerged as key therapeutic goals in the management of inflammatory bowel diseases (IBD) that are associated with favorable long-term disease outcomes. Here, we prospectively compared the predictive value of barrier healing with endoscopic and histologic remission for predicting long-term disease behavior in a large cohort of patients with IBD in clinical remission. Methods: At baseline, patients with IBD in clinical remission underwent ileocolonoscopy with assessment of intestinal barrier function by confocal endomicroscopy. Endoscopic and histologic disease activity, as well as barrier healing, was prospectively assessed along established scores. During subsequent follow-up, patients were closely monitored for clinical disease activity and the occurrence of major adverse outcomes (MAOs): disease flares, IBD-related hospitalization or surgery, and initiation or dose escalation of systemic steroids, immunosuppressants, small molecules, or biological therapy. Results: The final analysis included 181 patients, 100 with Crohn's disease [CD] and 81 with ulcerative colitis (UC). During a mean follow-up of 35 (CD) and 25 (UC) months, 73% of patients with CD and 69% of patients with UC experienced at least 1 MAO. The probability of MAO-free survival was significantly higher in patients with IBD with endoscopic remission compared with endoscopically active disease. In addition, histologic remission predicted MAO-free survival in patients with UC but not CD. Barrier healing on endomicroscopy was superior to endoscopic and histologic remission for predicting MAO-free survival in both UC and CD. Conclusions: Barrier healing is associated with decreased risk of disease progression in patients with clinically remittent IBD, with superior predictive performance compared with endoscopic and histologic remission. Analysis of barrier function might be considered as a future treatment target in clinical trials. ClinicalTrials.gov number, NCT05157750.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Confocal Laser Endomicroscopy; Endoscopy; Histology; Inflammatory Bowel Diseases; Intestinal Barrier

Intestinal epithelial Caspase-8 signaling is essential to prevent necroptosis during Salmonella Typhimurium induced enteritis - Hefele, Manuela; Stolzer, Iris; Ruder, Barbara; He, Gui-Wei; Mahapatro, Mousumi; Wirtz, Stefan; Neurath, Markus; Günther, Claudia (Mucosal Immunology, 2018)
Although induction of host cell death is a pivotal step during bacteria-induced gastroenteritis, the molecular regulation remains to be fully characterized. To expand our knowledge, we investigated the role of the central cell death regulator Caspase-8 in response to Salmonella Typhimurium. Here, we uncovered that intestinal salmonellosis was associated with strong upregulation of members of the host cell death machinery in intestinal epithelial cells (IECs) as an early event, suggesting that elimination of infected IECs represents a host defense strategy. Indeed, Casp8∆IEC mice displayed severe tissue damage and high lethality after infection. Additional deletion of Ripk3 or Mlkl rescued epithelial cell death and lethality of Casp8∆IEC mice, demonstrating the crucial role of Caspase-8 as a negative regulator of necroptosis. While Casp8∆IECTnfr1-/- mice showed improved survival after infection, tissue destruction was similar to Casp8∆IEC mice, indicating that necroptosis partially depends on TNF-α signaling. Although there was no impairment in antimicrobial peptide secretion during the early phase of infection, functional Caspase-8 seems to be required to control pathogen colonization. Collectively, these results demonstrate that Caspase-8 is essential to prevent Salmonella Typhimurium induced enteritis and to ensure host survival by two different mechanisms: maintenance of intestinal barrier function and restriction of pathogen colonization.
EVALuna2:35156

Intestinal epithelial Gasdermin C is induced by IL-4R/STAT6 signaling but is dispensable for gut immune homeostasis - Gámez Belmonte, Maria de los Reyes; Wagner, Yara; Mahapatro, Mousumi; Wang, Ru; Erkert, Lena; Gonzalez Acera, Miguel; Cineus, Roodline; Hainbuch, Saskia; Patankar, Jay; Vöhringer, David; Hegazy, Ahmed N.; Neurath, Markus; et al. (Scientific Reports, 2024)
Gasdermin C is one of the least studied members of the gasdermin family of proteins, known for their critical involvement in pyroptosis and host defense. Furthermore, evidence for the role of Gasdermin C in the intestine is scarce and partly controversial. Here, we tested the functional role of Gasdermin C in intestinal homeostasis, inflammation and tumorigenesis. : We studied Gasdermin C in response to cytokines in intestinal organoids. We evaluated epithelial differentiation, cell death and immune infiltration under steady state conditions in a new mouse line deficient in Gasdermin C. The role of Gasdermin C was analyzed in acute colitis, infection and colitis-associated cancer. Gasdemin C is highly expressed in the intestinal epithelium and strongly induced by the type 2 cytokines IL-4 and IL-13 in a STAT6-dependent manner. Gasdermin C-deficient mice show no changes in tissue architecture and epithelial homeostasis. Epithelial organoids deficient in Gasdermin C develop normally and show no alterations in proliferation or cell death. No changes were found in models of acute colitis, type 2 intestinal infection and colitis-associated cancer. Gasdermin C genes are upregulated by type 2 immunity, yet appear dispensable for the development of intestinal inflammation, infection and colitis-associated cancer.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Gasdermin; Gut pathology; Intestinal homeostasis

Intestinal ex vivo organoid culture reveals altered programmed crypt stem cells in patients with celiac disease - Dieterich, Walburga; Neurath, Markus; Zopf, Yurdagül (Scientific Reports, 2020)
The ex vivo generation of gastrointestinal organoids from crypt stem cells opens up the possibility of new research approaches investigating gastrointestinal diseases. We used this technology to study differences between healthy controls and patients with celiac disease (CD). We noticed distinct dissimilarities in the phenotypes of organoids between our study groups and found considerable variations in their gene expression. Extracellular matrix genes involved in epithelial-mesenchymal transition are expressed most differently. In addition, we demonstrated epigenetic modifications that might be responsible for the different organoid gene expression thus accounting for a deranged crypt/villus axis development in CD. The organoids have proven valuable to demonstrate fundamental differences in duodenal derived organoids between healthy controls and patients with CD and thus are a suitable tool to gain new insights in pathogenesis of CD.
CRIS-Team Scopus Importer:2020-03-10

Intestinal graft-versus-host disease is driven by BATF-dependent IL-7R(hi)GM-CSF+ T cells - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Buettner-Herold, Maike; Kitowski, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (2018)
EVALuna2:207769

Intestinal Mucosal Wound Healing and Barrier Integrity in IBD–Crosstalk and Trafficking of Cellular Players - Sommer, Katrin; Wiendl, Maximilian; Müller, Tanja; Heidbreder, Karin; Voskens, Caroline; Neurath, Markus; Zundler, Sebastian (Frontiers in Medicine, 2021)
The intestinal epithelial barrier is carrying out two major functions: restricting the entry of potentially harmful substances while on the other hand allowing the selective passage of nutrients. Thus, an intact epithelial barrier is vital to preserve the integrity of the host and to prevent development of disease. Vice versa, an impaired intestinal epithelial barrier function is a hallmark in the development and perpetuation of inflammatory bowel disease (IBD). Besides a multitude of genetic, molecular and cellular alterations predisposing for or driving barrier dysintegrity in IBD, the appearance of intestinal mucosal wounds is a characteristic event of intestinal inflammation apparently inducing breakdown of the intestinal epithelial barrier. Upon injury, the intestinal mucosa undergoes a wound healing process counteracting this breakdown, which is controlled by complex mechanisms such as epithelial restitution, proliferation and differentiation, but also immune cells like macrophages, granulocytes and lymphocytes. Consequently, the repair of mucosal wounds is dependent on a series of events including coordinated trafficking of immune cells to dedicated sites and complex interactions among the cellular players and other mediators involved. Therefore, a better understanding of the crosstalk between epithelial and immune cells as well as cell trafficking during intestinal wound repair is necessary for the development of improved future therapies. In this review, we summarize current concepts on intestinal mucosal wound healing introducing the main cellular mediators and their interplay as well as their trafficking characteristics, before finally discussing the clinical relevance and translational approaches to therapeutically target this process in a clinical setting.
CRIS-Team Scopus Importer:2021-04-16
Keywords: IBD; intestinal epithelial barrier function; intestinal epithelial cells; mucosal healing; wound healing

In Vivo Assessment of Deep Vascular Patterns in Murine Colitis Using Optoacoustic Mesoscopic Imaging - Bühler, Adrian; Brown, Emma L.; Nedoschill, Emmanuel; Eckstein, Markus; Ludwig, Petra; Wachter, Felix; Mandelbaum, Henriette; Raming, Roman; Oraiopoulou, Mariam Eleni; Paulus, Lars-Philip; Rother, Ulrich; Friedrich, Oliver; et al. (Advanced Science, 2024)
The analysis of vascular morphology and functionality enables the assessment of disease activity and therapeutic effects in various pathologies. Raster-scanning optoacoustic mesoscopy (RSOM) is an imaging modality that enables the visualization of superficial vascular networks in vivo. In murine models of colitis, deep vascular networks in the colon wall can be visualized by transrectal absorber guide raster-scanning optoacoustic mesoscopy (TAG-RSOM). In order to accelerate the implementation of this technology in translational studies of inflammatory bowel disease, an image-processing pipeline for TAG-RSOM data has been developed. Using optoacoustic data from a murine model of chemically-induced colitis, different image segmentation methods are compared for visualization and quantification of deep vascular patterns in terms of vascular network length and complexity, blood volume, and vessel diameter. The presented image-processing pipeline for TAG-RSOM enables label-free in vivo assessment of changes in the vascular network in murine colitis with broad applications for inflammatory bowel disease research.
CRIS-Team Scopus Importer:2024-11-01
Keywords: dextran sodium sulfate induced colitis; inflammatory bowel disease; murine acute colitis; optoacoustic imaging; photoacoustic imaging; raster-scanning optoacoustic mesoscopy; vessel morphology analysis

In vivo diagnosis and characterisation of Whipple's disease - Neufert, Clemens; Vieth, Michael; Mönkemüller, Klaus; Neurath, Markus; Neumann, Helmut (Lancet Infectious Diseases, 2011)
CRIS-Team Scopus Importer:2025-03-05

In vivo imaging using fluorescent antibodies to tumor necrosis factor predicts therapeutic response in Crohn's disease - Atreya, Raja; Neumann, Helmut; Neufert, Clemens; Waldner, Maximilian; Billmeier, Ulrike; Zopf, Yurdagül; Willma, Marcus; App, Christine; Münster, Tino; Kessler, Hermann; Maas, Stefanie; Gebhardt, Bernd; et al. (Nature Medicine, 2014)
As antibodies to tumor necrosis factor (TNF) suppress immune responses in Crohn's disease by binding to membrane-bound TNF (mTNF), we created a fluorescent antibody for molecular mTNF imaging in this disease. Topical antibody administration in 25 patients with Crohn's disease led to detection of intestinal mTNF(+) immune cells during confocal laser endomicroscopy. Patients with high numbers of mTNF(+) cells showed significantly higher short-term response rates (92%) at week 12 upon subsequent anti-TNF therapy as compared to patients with low amounts of mTNF(+) cells (15%). This clinical response in the former patients was sustained over a follow-up period of 1 year and was associated with mucosal healing observed in follow-up endoscopy. These data indicate that molecular imaging with fluorescent antibodies has the potential to predict therapeutic responses to biological treatment and can be used for personalized medicine in Crohn's disease and autoimmune or inflammatory disorders.
EVALuna2:1838

In vivo multi spectral colonoscopy in mice - Hohmann, Martin; Ganzleben, Ingo; Grünberg, Alexander; Menezes, Jean Gonzales; Klämpfl, Florian; Lengenfelder, Benjamin; Liebing, Eva; Heichler, Christina; Neufert, Clemens; Becker, Christoph; Neurath, Markus; Waldner, Maximilian; et al. (Scientific Reports, 2022)
Multi- and hyperspectral endoscopy are possibilities to improve the endoscopic detection of neoplastic lesions in the colon and rectum during colonoscopy. However, most studies in this context are performed on histological samples/biopsies or ex vivo. This leads to the question if previous results can be transferred to an in vivo setting. Therefore, the current study evaluated the usefulness of multispectral endoscopy in identifying neoplastic lesions in the colon. The data set consists of 25 mice with colonic neoplastic lesions and the data analysis is performed by machine learning. Another question addressed was whether adding additional spatial features based on Gauss-Laguerre polynomials leads to an improved detection rate. As a result, detection of neoplastic lesions was achieved with an MCC of 0.47. Therefore, the classification accuracy of multispectral colonoscopy is comparable with hyperspectral colonoscopy in the same spectral range when additional spatial features are used. Moreover, this paper strongly supports the current path towards the application of multi/hyperspectral endoscopy in clinical settings and shows that the challenges from transferring results from ex vivo to in vivo endoscopy can be solved.
CRIS-Team WoS Importer:2022-06-10

In-vivo multispectral Video Endoscopy towards in-vivo hyperspectral Video Endoscopy - Hohmann, Martin; Kanawade, Rajesh; Klämpfl, Florian; Douplik, Alexandre; Mudter, Jonas; Neurath, Markus; Albrecht, Heinz (Journal of Biophotonics, 2016)

In-vivo multispectral video endoscopy towards in-vivo hyperspectral video endoscopy - Hohmann, Martin; Kanawade, R.; Klämpfl, Florian; Douplik, Alexandre; Mudter, J.; Neurath, Markus; Albrecht, Heinz (Journal of Biophotonics, 2017)
For in-vivo diagnostics of cancer and pre-cancer in the stomach, there is no endoscopic procedure offering both high sensitivity and high specificity. Our data suggest that multispectral or hyperspectral imaging may be helpful to solve this problem. It is successfully applied to the detection and analysis of easily reachable carcinomas, ex-vivo samples of hollow organ mucosal carcinomas and also histological samples. An endoscopy system which allows flexible multispectral videoendoscopy for in-vivo diagnostics has so far been unavailable. To overcome this problem, we modified a standard Olympus endoscopy system to conduct in-vivo multispectral imaging of the upper GI tract. The pilot study is performed on 14 patients with adeno carcinomas in the stomach. For analysis, Support Vector Machine with linear and Gaussian Kernel, AdaBoost, RobustBoost and Random-Forest-walk are used and compared for the data classification with a leave-one-out strategy. The margin of the carcinoma for the training of the classifier is drawn by expert-labeling. The cancer findings are cross-checked by biopsies. We expect that the present study will help to improve the further development of hyperspectral endoscopy and to overcome some of the problems to be faced in this process.
EVALuna2:33820

In vivo real-time assessment of colorectal polyp histology using an optical biopsy forceps system based on laser-induced fluorescence spectroscopy - Rath, Timo; Tontini, Gian E.; Naegel, Andreas; Neurath, Markus; Neumann, Helmut; Vieth, Michael (Endoscopy, 2016)
In order to reduce time, costs, and risks associated with resection of diminutive colorectal polyps, the American Society for Gastrointestinal Endoscopy (ASGE) recently proposed performance thresholds that new technologies should meet for the accurate real-time assessment of histology of colorectal polyps. In this study, we prospectively assessed whether laser-induced fluorescence spectroscopy (LIFS), using the new WavSTAT4 optical biopsy system, can meet the ASGE criteria.27 patients undergoing screening or surveillance colonoscopy were included. The histology of 137 diminutive colorectal polyps was predicted in real time using LIFS and findings were compared with the results of conventional histopathological examination. The accuracy of predicting polyp histology with WavSTAT4 was assessed according to the ASGE criteria.The overall accuracy of LIFS using WavSTAT4 for predicting polyp histology was 84.7 % with sensitivity, specificity, and negative predictive value (NPV) of 81.8 %, 85.2 %, and 96.1 %. When only distal colorectal diminutive polyps were considered, the NPV for excluding adenomatous histology increased to 100 % (accuracy 82.4 %, sensitivity 100 %, specificity 80.6 %). On-site, LIFS correctly predicted the recommended surveillance intervals with an accuracy of 88.9 % (24/27 patients) when compared with histology-based United States guideline recommendations; in the 3 patients for whom LIFS- and histopathology-based recommended surveillance intervals differed, LIFS predicted shorter surveillance intervals.From the data of this pilot study, LIFS using the WavSTAT4 system appears accurate enough to allow distal colorectal polyps to be left in place and nearly reaches the threshold to "resect and discard" them without pathologic assessment. WavSTAT4 therefore has the potential to reduce costs and risks associated with the removal of diminutive colorectal polyps.
EVALuna2:2067

IRAK-M Expression in Tumor Cells Supports Colorectal Cancer Progression through Reduction of Antimicrobial Defense and Stabilization of STAT3 - Kesselring, Rebecca; Glaesner, Joachim; Hiergeist, Andreas; Naschberger, Elisabeth; Neumann, Helmut; Brunner, Stefan M.; Wege, Anja K.; Seebauer, Caroline; Koehl, Gudrun; Merkl, Susanne; Croner, Roland S.; Hackl, Christina; et al. (Cancer Cell, 2016)
Colorectal cancer (CRC) is associated with loss of epithelial barrier integrity, which facilitates the interaction of the immunological microenvironment with the luminal microbiome, eliciting tumor-supportive inflammation. An important regulator of intestinal inflammatory responses is IRAK-M, a negative regulator of TLR signaling. Here we investigate the compartment-specific impact of IRAK-M on colorectal carcinogenesis using a mouse model. We demonstrate that IRAK-M is expressed in tumor cells due to combined TLR and Wnt activation. Tumor cell-intrinsic IRAK-M is responsible for regulation of microbial colonization of tumors and STAT3 protein stability in tumor cells, leading to tumor cell proliferation. IRAK-M expression in human CRCs is associated with poor prognosis. These results suggest that IRAK-M may be a potential therapeutic target for CRC treatment.
EVALuna2:2089

Iron beats electricity: Resistance training but not whole-body electromyostimulation improves cardiometabolic health in obese metabolic syndrome patients during caloric restriction—a randomized-controlled study - Reljic, Dejan; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (Nutrients, 2021)
Caloric restriction (CR) and exercise are cornerstones in the treatment of obesity and cardiometabolic disorders. Recently, whole body electromyostimulation (WB-EMS) has emerged as a more time-efficient alternative to traditional resistance training (RT). However, the effects of WB-EMS compared to RT on cardiometabolic health in obese metabolic syndrome (MetS) patients performed during CR are still unclear. In total, 118 obese MetS patients (52.7 ± 11.8 years, BMI: 38.1 ± 6.9 kg/m2 ) undergoing CR over 12 weeks (aim: −500 kcal deficit/day) were randomly allocated to either WB-EMS, single-set RT (1-RT), 3-set RT (3-RT) or an inactive control group (CON). Primary outcome was MetS severity (MetS z-score). Secondary outcomes were body composition, muscle strength and quality of life (QoL). All groups significantly reduced body weight ( 3%) and fat mass ( 2.6 kg) but only 1-RT and 3-RT preserved skeletal muscle mass (SMM). All exercise groups increased muscle strength in major muscle groups (20–103%). However, only the two RT-groups improved MetS z-score (1-RT: −1.34, p = 0.003; 3-RT: −2.06, p < 0.001) and QoL (1-RT: +6%, p = 0.027; 3-RT: +12%, p < 0.001), while WB-EMS and CON had no impact on these outcomes. We conclude that traditional RT has superior effects on cardiometabolic health, SMM and QoL in obese MetS patients undergoing CR than WB-EMS.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Cardiovascular disease; Electrical stimulation; Exercise; Fasting; Hyper-tension; Muscle mass; Muscular strength; Obesity; Psychological health; Strength training

I-scan optical enhancement for the in vivo prediction of diminutive colorectal polyp histology: Results from a prospective three-phased multicentre trial - Klenske, Entcho; Zopf, Steffen; Neufert, Clemens; Naegel, Andreas; Gschossmann, Juergen; Muehldorfer, Steffen; Pfeifer, Lukas; Fischer, Sören; Vitali, Francesco; Iacucci, Marietta; Ghosh, Subrata; Rath, Michelle G.; et al. (PLoS ONE, 2018)
BACKGROUND AND AIMS: Dye-less chromoendoscopy is an emerging technology for colorectal polyp characterization. Herein, we investigated whether the newly introduced I-scan optical enhancement (OE) can accurately predict polyp histology in vivo in real-time. METHODS: In this prospective three-phased study, 84 patients with 230 diminutive colorectal polyps were included. During the first two study phases, five endoscopists assessed whether analysis of polyp colour, surface and vascular pattern under i-scan OE can differentiate in vivo between adenomatous and hyperplastic polyps. Finally, junior and experienced endoscopists (JE, EE, each n = 4) not involved in the prior study phases made a post hoc diagnosis of polyp histology using a static i-scan OE image database. Histopathology was used as a gold-standard in all study phases. RESULTS: The overall accuracy of i-scan OE for histology prediction was 90% with a sensitivity, specificity, positive (PPV) and negative prediction value (NPV) of 91%, 90%, 86% and 94%, respectively. In high confidence predictions, the diagnostic accuracy increased to 93% with sensitivity, specificity, PPV and NPV of 94%, 91%, 89% and 96%. Colonoscopy surveillance intervals were predicted correctly in ≥ 90% of patients. In the post hoc analysis EE predicted polyp histology under i-scan OE with an overall accuracy of 91%. After a single training session, JE achieved a comparable diagnostic performance for predicting polyp histology with i-scan OE. CONCLUSION: The histology of diminutive colorectal polyps can be accurately predicted with i-scan OE in vivo in real-time. Furthermore, polyp differentiation with i-scan OE appears to require only a short learning curve.
EVALuna2:35169

Is histological healing a feasible endpoint in ulcerative colitis? - Rath, Timo; Atreya, Raja; Neurath, Markus (Expert Review of Gastroenterology and Hepatology, 2021)
Introduction: Currently, treatment goals in ulcerative colitis aim to achieve clinical remission and endoscopic mucosal healing. Emerging evidence suggests that histologic assessment of inflammation is a sensitive marker that can outcompete mucosal healing in predicting the clinical course of disease in patients with ulcerative colitis. Based on this, histologic healing is frequently included as a secondary endpoint in pharmacological trials. Areas covered: We introduce currently used clinical and endoscopic treatment goals, summarize commonly used histologic scoring systems and then provide an overview on the relevance of histologic healing on the outcome in patients with ulcerative colitis. Finally, we review the efficacy of existing UC therapies for inducing histologic remission. Expert opinion: Histologic healing is achievable in a substantial portion of UC patients. Further, histologic healing is, as consolidated by several meta-analyses, associated with better disease outcome compared to clinical remission and/or endoscopic healing. However, before becoming a widely acceptable treatment endpoint, consensus definitions for histologic healing and the technical aspects as well as for the timing for obtaining biopsies are needed. And finally, we need more evidence to show that resolution of microscopic inflammation as a means of therapy change or dose escalation is indeed a superior endpoint.
CRIS-Team Scopus Importer:2021-02-12
Keywords: endoscopic healing; histologic healing; histologic remission; Inflammatory bowel diseases; mucosal healing; ulcerative colitis

Is non-invasive Cytosponge the holy grail for Barrett's neoplasia? - Neurath, Markus; Vieth, Michael (The Lancet. Oncology, 2022)
CRIS-Team Scopus Importer:2022-02-11

Issues in histopathological reporting: A crucial crossroad between surgeons and pathologists after oesophago-gastrectomy - Neurath, Markus; Vieth, Michael (Diseases of the Esophagus, 2021)
CRIS-Team Scopus Importer:2021-09-17

Label-free analysis of experimental lung fibrosis using multiphoton microscopy and Raman spectroscopy - Ganzleben, Ingo; Kreiß, Lucas; Mühlberg, Alexander; Friedrich, Oliver; Neurath, Markus; Schürmann, Sebastian; Waldner, Maximilian (EUROPEAN RESPIRATORY JOURNAL, 2021)
CRIS-Team WoS Importer:2022-02-25

Label-free analysis of inflammatory tissue remodeling in murine lung tissue based on multiphoton microscopy, Raman spectroscopy and machine learning - Kreiß, Lucas; Ganzleben, Ingo; Mühlberg, Alexander; Ritter, Paul; Schneidereit, Dominik; Becker, Christoph; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; Waldner, Maximilian (Journal of Biophotonics, 2022)
Inflammatory fibrotic tissue remodeling can lead to severe morbidity. Histopathology grading requires extraction of biopsies and elaborate tissue processing. Label-free optical technologies can provide diagnostic readout without preparation and artificial stainings and show potential for in vivo applications. Here, we present an integration of Raman spectroscopy (RS) and multiphoton microscopy for joint investigation of the bio-chemical composition and morphological features related to cellular components and connective tissue. Both modalities show that collagen signatures were significantly increased in a murine fibrosis model. Furthermore, autofluorescence signatures assigned to immune cells show high correlation with disease severity. RS indicates increased levels of elastin and lipids. Further, we investigated the effect of joint data sets on prediction performance in machine learning models. Although binary classification did not benefit from adding more features, multi-class classification was improved by integrated data sets.
CRIS-Team WoS Importer:2022-07-08

Label-Free Characterization and Quantification of Mucosal Inflammation in Common Murine Colitis Models With Multiphoton Imaging - Kreiß, Lucas; Thoma, Oana-Maria; Lemire, Sarah; Lechner, Kristina; Carlé, Birgitta-Elisabeth; Dilipkumar, Ashwathama; Kunert, Timo; Scheibe, Kristina; Heichler, Christina; Merten, Anna-Lena; Weigmann, Benno; Neufert, Clemens; et al. (Inflammatory Bowel Diseases, 2022)
Background Clinical challenges in inflammatory bowel diseases require microscopic in vivo evaluation of inflammation. Here, label-free imaging holds great potential, and recently, our group demonstrated the advantage of using in vivo multiphoton endomicroscopy for longitudinal animal studies. This article extends our previous work by in-depth analysis of label-free tissue features in common colitis models quantified by the multiphoton colitis score (MCS). Methods Fresh mucosal tissues were evaluated from acute and chronic dextran sulfate sodium (DSS), TNBS, oxazolone, and transfer colitis. Label-free imaging was performed by using second harmonic generation and natural autofluorescence. Morphological changes in mucosal crypts, collagen fibers, and cellularity in the stroma were analyzed and graded. Results Our approach discriminated between healthy (mean MCS = 2.5) and inflamed tissue (mean MCS > 5) in all models, and the MCS was validated by hematoxylin and eosin scoring of the same samples (85.2% agreement). Moreover, specific characteristics of each phenotype were identified. While TNBS, oxazolone, and transfer colitis showed high cellularity in stroma, epithelial damage seemed specific for chronic, acute DSS and transfer colitis. Crypt deformations were mostly observed in acute DSS. Conclusions Quantification of label-free imaging is promising for in vivo endoscopy. In the future, this could be valuable for monitoring of inflammatory pathways in murine models, which is highly relevant for the development of new inflammatory bowel disease therapeutics.
CRIS-Team WoS Importer:2022-10-07

Label-free imaging of inflammatory bowel disease using multiphoton microscopy. - Schürmann, Sebastian; Försch, Sebastian; Atreya, Raja; Neumann, Helmut; Friedrich, Oliver; Neurath, Markus; Waldner, Maximilian (Gastroenterology, 2013)
Multiphoton microscopy (MPM) became one of the most important optical in vivo imaging techniques for basic research during recent years. In comparison with single photon excitation during confocal microscopy, MPM provides a superior effective resolution in thick tissue samples and an increased penetration depth.1 Because of the effects of nonlinear optics, various molecular components can be discriminated with MPM in vivo and in vitro without the need to apply fluorophores. The detection of these molecules is based on specific autofluorescence or second harmonic generation (SHG) signals generated by multiphoton excitation.

Label-Free In Vivo Histopathology of Experimental Colitis via 3-Channel Multiphoton Endomicroscopy - Kreiß, Lucas; Thoma, Oana Maria; Dilipkumar, Ashwathama; Carlé, Birgitta-Elisabeth; Longequeue, Pascal; Kunert, Timo; Rath, Timo; Hildner, Kai; Neufert, Clemens; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; et al. (Gastroenterology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Label-Free Multiphoton Endomicroscopy for Minimally Invasive In Vivo Imaging - Dilipkumar, Ashwathama; Al-Shemmary, Alaa; Kreiß, Lucas; Cvecek, Kristian; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Menezes, Jean Gonzales; Thoma, Oana-Maria; Schmidt, Michael; Neurath, Markus; Waldner, Maximilian; Friedrich, Oliver; et al. (Advanced Science, 2019)
Multiphoton microscopy of cellular autofluorescence and second harmonic generation from collagen facilitates imaging of living cells and tissues without the need for additional fluorescent labels. Here, a compact multiphoton endomicroscope for label-free in vivo imaging in small animals via side-viewing needle objectives is presented. Minimal invasive imaging at cellular resolution is performed in colonoscopy of mice without surgical measures and without fluorescent dyes as a contrast agent. The colon mucosa is imaged repeatedly in the same animal in a mouse model of acute intestinal inflammation to study the process of inflammation at the tissue level within a time period of ten days, demonstrating the capabilities of label-free endomicroscopy for longitudinal studies for the first time.
CRIS-Team Scopus Importer:2019-05-02
Keywords: endoscopy; inflammatory bowel disease; multiphoton microscopy; optical imaging

Lack of intestinal epithelial atg7 affects paneth cell granule formation but does not compromise immune homeostasis in the gut. - Günther, Claudia; Martini, Eva; Waldner, Maximilian; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph; et al. (Clinical & Developmental Immunology, 2012)
Genetic polymorphisms of autophagy-related genes have been associated with an increased risk to develop inflammatory bowel disease (IBD). Autophagy is an elementary process participating in several cellular events such as cellular clearance and nonapoptotic programmed cell death. Furthermore, autophagy may be involved in intestinal immune homeostasis due to its participation in the digestion of intracellular pathogens and in antigen presentation. In the present study, the role of autophagy in the intestinal epithelial layer was investigated. The intestinal epithelium is essential to maintain gut homeostasis, and defects within this barrier have been associated with the pathogenesis of IBD. Therefore, mice with intestinal epithelial deletion of Atg7 were generated and investigated in different mouse models. Knockout mice showed reduced size of granules and decreased levels of lysozyme in Paneth cells. However, this was dispensable for gut immune homeostasis and had no effect on susceptibility in mouse models of experimentally induced colitis.

Learning curve of virtual chromoendoscopy for the prediction of hyperplastic and adenomatous colorectal lesions: A prospective 2-center study - Neumann, Helmut; Fry, Lucia C.; Günther, Claudia; Atreya, Raja; Neurath, Markus; Moenkemueller, Klaus; Vieth, Michael (Gastrointestinal Endoscopy, 2013)
Background: Computed virtual chromoendoscopy (CVC) enables high-definition imaging of mucosal lesions with improved tissue contrast. Previous studies have shown that CVC yields an improved detection rate of colorectal lesions. However, the learning curve for interpretation of CVC images is unknown. Objective: To examine the learning curve of correctly identifying hyperplastic and adenomatous colorectal lesions by using CVC. Design: Prospective, 2-center study. Patients: Consecutive patients undergoing screening colonoscopy were included. CVC images were analyzed by using corresponding polypectomies as the reference standard followed by a prospective, double-blind review of i-scan images. Methods: A training set containing 20 images with known histology was reviewed to standardize image interpretation, followed by a blind review of 110 unknown images. Overall, 4 endoscopists from 2 different endoscopy centers evaluated the images, which were obtained by 1 endoscopist using high-definition endoscopy with CVC. Results: Patients were included in a prospective fashion. Seventy-seven of 110 colorectal lesions were adenomas and 33 were hyperplastic lesions. Mean diameter of colonic polyps was 4 mm (range, 2-20 mm). Overall accuracy for the group was 73.9% for lesions 1 to 22, 79.6% for lesions 23 to 44, 84.1% for lesions 45 to 66, 87.5% for lesions 67 to 88, and 94.3% for lesions 89 to 110. Accuracy of i-scan for prediction of polyp histology was not dependent on polyp size (≤5 mm, 6-10 mm, or > 10 mm). The ability to obtain high-quality images was stable over time, and high-quality images were constantly produced. Limitation: Post-hoc assessment. Conclusion: Accurate interpretation of CVC images for prediction of hyperplastic and adenomatous colorectal lesions follows a learning curve but can be learned rapidly. © 2013 American Society for Gastrointestinal Endoscopy.
CRIS-Team Scopus Importer:2020-10-28
Keywords: computed virtual chromoendoscopy; CVC; FICE; Fuji intelligent color enhancement; PIVI; Preservation and Incorporation of Valuable Endoscopic Innovations

Leitliniengerechte Therapie des Morbus Crohn: Aktuelle Handlungsempfehlungen - Fischer, Sören; Neurath, Markus (Gastroenterologe, 2019)
Background: Crohn’s disease is a complex condition with rising incidence worldwide. The approval of multiple new therapeutic options results in growing challenges for physicians and guidelines. Objectives: The aim of this paper is to describe a plausible algorithm for the treatment of Crohn’s disease based on the current scientific knowledge. Materials and methods: We refer to the current guidelines of the German Gastroenterology Organization (DGVS), the European Crohn’s and Colitis Organization (ECCO), the American College of Gastroenterology (ACG) as well as the drug professional information. Results: The therapy of Crohn’s disease depends on the affected tract regions, severity of inflammation, individual patient characteristics, previous therapies, and the patient’s preferences. Conclusions: The therapeutic options in Crohn’s disease are constantly evolving. The prediction of therapy response is a continued challenge for medical science. In the principle of participatory medicine, shared decision-making of patient and physician leads to better adherence to the therapy.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Biologicals; Colorectal surgery; Drug therapy; Glucocorticoids; Inflammatory bowel diseases

Limited Dose-Dependent Effects of Vedolizumab on Various Leukocyte Subsets - Becker, Emily; Schweda, Anna; Ullrich, Karen; Voskens, Caroline; Atreya, Raja; Müller, Tanja; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Clinical and Translational Gastroenterology, 2022)
OBJECTIVES: The anti-α4β7 integrin antibody vedolizumab (VDZ) is successfully used for the treatment of inflammatory bowel diseases. However, only a subgroup of patients respond to therapy. VDZ is administered at a fixed dose, leading to a wide range of serum concentrations in patients. Previous work from our group showed a dose-dependent preferential binding of VDZ to effector compared with regulatory CD4 + T cells. Therefore, we aimed to determine the dose-dependent binding profile of VDZ to other leukocyte subsets. METHODS: We characterized α4β7 integrin expression on CD8 + T cells, CD19 + B cells, CD14 + monocytes, natural killer cells, and eosinophils from patients with inflammatory bowel disease and healthy controls. We studied the binding of VDZ to these cells at different concentrations and investigated the functional consequences for dynamic adhesion and transmigration in vitro . RESULTS: The expression of α4β7 differed between the analyzed leukocyte subsets and was significantly higher on eosinophils from inflammatory bowel disease patients compared with controls. Almost all α4β7-expressing cells from these subsets were bound by VDZ at a concentration of 10 μg/mL. Dynamic cell adhesion was significantly impaired in all subsets, but there were no dose-dependent differences in the inhibition of adhesion. DISCUSSION: Our data suggest that α4β7-expressing CD8 + T cells, CD19 + B cells, CD14 + monocytes, natural killer cells, and eosinophils are a target of VDZ. However, there do not seem to be concentration-dependent differences, regarding the effects on these cells in the clinically relevant range. Thus, the reported exposure-efficacy characteristic of VDZ can probably mainly be attributed to CD4 + T-cell subsets.
CRIS-Team Scopus Importer:2022-07-08

Linking IL-10 signaling with lipid metabolic programs in macrophages: dysregulated ceramide homeostasis drives colitis - Atreya, Imke; Neurath, Markus (Signal Transduction and Targeted Therapy, 2024)
CRIS-Team Scopus Importer:2024-06-21

LI-RADS-CEUS - Proposal for a Contrast-Enhanced Ultrasound Algorithm for the Diagnosis of Hepatocellular Carcinoma in High-Risk Populations - Schellhaas, B.; Wildner, Dane; Pfeifer, Lukas; Görtz, Rüdiger; Hagel, Alexander; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2016)
Purpose: To develop a contrast-enhanced ultrasound algorithm (LI-RADS-CEUS = liver imaging reporting and data system with contrast-enhanced ultrasound) for the diagnosis of hepatocellular carcinoma (HCC) in patients at risk. Materials and Methods: A CEUS algorithm (LI-RADS-CEUS) was designed analogously to CT- and MRI-based LI-RADS. LI-RADS-CEUS was evaluated retrospectively in 50 patients at risk with confirmed HCC or non-HCC lesions (test group) with subsequent validation in a prospective cohort of 50 patients (validation group). Results were compared to histology, CE-CT and CE-MRI as reference standards. Results: Tumor diagnosis in the test group/validation group (n = 50/50) were 46/41 HCCs, 3/3 intrahepatic cholangiocellular carcinomas (ICCs) and 1/6 benign lesions. The diagnostic accuracy of LI-RADS-CEUS for HCC, ICC and non-HCC-non-ICC-lesions was 89 %. For the diagnosis of HCC, the diagnostic accuracy was 93.5 % (43/46 cases) in the test group and 95.1 % (39/41 cases) in the validation group. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were 94.3 %, 66.6 %, 94.3 % and 66.6 %, respectively (mean values from both cohorts). Histological findings of HCC were available in 40 versus 23 cases (in total: G1 / G2/G3: 15/35/13). Arterial hyperenhancement was seen in 68/87 (78.2 %) of HCCs. Arterial hyperenhancement with subsequent portal venous or late phase hypoenhancement was seen in 66 % of HCCs. Conclusion: LI-RADS-CEUS offers a CEUS algorithm for standardized assessment and reporting of focal liver lesions in patients at risk for HCC. Arterial hyperenhancement in CEUS is the key feature for the diagnosis of HCC in patients at risk, whereas washout is not a necessary prerequisite.
EVALuna2:2223

Liver stiffness assessed by acoustic radiation force impulse (ARFI) technology is considerably increased in patients with cholestasis - Pfeifer, Lukas; Strobel, Deike; Neurath, Markus; Wildner, D. (Ultraschall in der Medizin, 2014)
To explore the impact of cholestasis on liver stiffness assessed by acoustic radiation force impulse (ARFI) technology.Over a period of four months, patients with sonographic cholestasis and increased cholestatic blood values (Bilirubin, ?GT, AP > 2 times ULN) scheduled for endoscopic therapy were recruited. Exclusion criteria were: known liver disease; signs of cirrhosis at ultrasound (irregular liver veins and/or surface); heart insufficiency (NYHA III-VI). ARFI (Siemens S2000), ultrasound and blood examinations were performed before and in a subgroup after successful biliary drainage.In total, 21 patients with cholestasis were included in the study. ARFI measurements were above the cut-off for cirrhosis (1.8 m/s) in all patients with a mean of 2.91 m/s ± 0.89 m/s without a history or signs of cirrhosis. Bilirubin, ?GT and AP were elevated on average to 9.7 ± 5.3 mg/dl, 1192 ± 960 U/l and 730 ± 389 U/l. A subgroup of 10 patients was measured after successful drainage. ARFI measurements declined in all patients of that subgroup on average by 0.76 m/s at a mean time interval of 4.5 days (p < 0.001).Cholestasis significantly increases liver stiffness assessed by ARFI. Therefore, it is important to exclude profound cholestasis when using ARFI for evaluating patients for liver fibrosis.
EVALuna2:1875

Long-term Combination Therapy with Anti-TNF plus Vedolizumab Induces and Maintains Remission in Therapy-refractory Ulcerative Colitis - Fischer, Sören; Rath, Timo; Geppert, Carol-Immanuel; Manger, Bernhard; Schett, Georg; Neurath, Markus; Atreya, Raja (American Journal of Gastroenterology, 2017)
EVALuna2:6885

Long-term effectiveness, safety and immunogenicity of the biosimilar SB2 in inflammatory bowel disease patients after switching from originator infliximab - Fischer, Sören; Cohnen, Sarah; Klenske, Entcho; Schmitt, Heike; Vitali, Francesco; Hirschmann, Simon; Ramming, Andreas; Zundler, Sebastian; Rath, Timo; Krebs, Sabine; Dörje, Frank; Uter, Wolfgang; et al. (Therapeutic Advances in Gastroenterology, 2021)
Background: Long-term data on inflammatory bowel disease (IBD) patients switched from originator to biosimilar infliximab SB2 are lacking. The aim of the conducted study was to investigate the effectiveness, immunogenicity and safety of a large prospectively followed-up IBD patient cohort that was entirely switched from originator infliximab to biosimilar SB2 treatment. Methods: This was a prospective, single-center, longitudinal, observational study describing clinical outcomes in IBD patients, over an 80-week period following switch from originator infliximab to SB2. Primary outcome measures were change of disease activity [Harvey-Bradshaw Index for Crohn’s disease (CD), partial Mayo Score for ulcerative colitis (UC)], C-reactive protein (CRP), infliximab trough levels (TLs), anti-drug antibodies (ADAs) and adverse events. Results: One hundred and forty-four IBD patients (94 CD, 50 UC), with median duration of 30.5 months’ (range 2–110) treatment with originator infliximab were evaluated. Mean change of disease activity compared with baseline was −0.9 (SD 2.6), –0.4 (2.2) and –0.4 (2.0) in CD; 0.1 (1.1), 0.1 (1.1) and 0.1 (1.3) in UC patients at weeks 24, 48 and 72. Median infliximab TLs were 6.2 µg/ml (interquartile range 2.3–12.2), 5.0 µg/ml (2.7–10.0), 6.6 µg/ml (3.5–12.4) and 5.1 µg/ml (2.7–10.9) at baseline and weeks 24, 48 and 72. Median CRP levels were within normal ranges throughout the study. After the switch, 9.8% of the patients developed new ADAs. Persistence on SB2 was 90% (95% confidence interval 0.85–0.95), 79% (0.72–0.86), 72% (0.64–0.80) at weeks 26, 52 and 78. Serious adverse events occurred in 11 patients. Conclusion: Over the individual patient follow-up of 80 weeks, switch to biosimilar SB2 from originator infliximab does not result in increased disease activity or changed immunogenicity patterns. The switch to SB2 was well tolerated.
CRIS-Team Scopus Importer:2021-02-05
Keywords: biosimilar; inflammatory bowel diseases; infliximab; SB2; switch

Long term follow up of through-the-scope balloon dilation as compared to strictureplasty and bowel resection of intestinal strictures in crohn's disease - Krauss, Ekaterina; Agaimy, Abbas; Gottfried, Angelina; Maiss, Juergen; Weidinger, Thomas; Albrecht, Heinz; Hartmann, Arndt; Hohenberger, Werner; Neurath, Markus; Kessler, Hermann; Mudter, Jonas (International Journal of Clinical and Experimental Pathology, 2014)
Ileo-colonic strictures are common complication of Crohn's disease (CD), and may result in repeated endoscopic or surgical therapy with a risk of further complications, such as perforation or short bowel syndrome. Strictures develop as a consequence of tissue remodelling and fibrosis due to chronic inflammation. This study compares the outcome of CD patients undergoing primarily endoscopic treatment with those undergoing surgery at an university hospital.In this study we retrospectively included 88 CD patients with intestinal strictures (37 males, 51 females, mean age 40 years, range 19-65 years) of both our medical and our surgical department, who underwent either surgical or endoscopic therapy between January 2002 and January 2006 with prospective, controlled follow-up, extended till January 2010 (mean follow-up period: 5 years; range 4-8 years). The primary end-point was operation- and symptom-free time. Patients were primarily divided into four groups: only surgical therapy, only endoscopic therapy, endoscopy with subsequent surgery, and initial surgical therapy followed by endoscopic dilations.53% of all patients remained surgery-free with mean follow-up of 49 months; a single endoscopic dilation was sufficient enough in 9 patients to achieve a surgery-free time of 51 months, other patients required up to 5 dilations. The average interval between first and second dilation was 6.5 months, between second and third 10.5 months. In the group of patients with only endoscopic therapy, surgery- and symptom-free time was shorter, as compared to the group of only surgical therapy. We found that stenoses in the surgical group with an average length of 6.5 cm were as expected longer, as compared to the endoscopic group (3 cm, ranging from 2-4 cm). The surgery-free time was 49 months (42-71 months, P = 0.723) with a symptom-free time of 12 months (4.5-46 months, P = 0.921). In the group of only surgically treated patients, 68.4% of the patients had only one stenosis, 18.4% had 2-3 stenoses and 13.2% more than 3 stenoses. In all patients the surgery- and symptoms- free time was 69 months (57-83 months, P = 0.850 and 0.908). The other two groups showed similar results. We found no significant effect of characteristic of stenosis (length, inflammation, the number of stenoses), injection of prednisolone, disease activity at the time of dilation and medication at the time of dilation on the long-term outcome. Importantly, the success of symptom free time correlated with the diameter of the balloon.Endoscopic dilation should be considered as a first-line therapy for short, accessible, fibrotic strictures. Careful patient selection and proper diagnostic imaging pre-procedure are essential requirements for safe and successful treatment. The balloon diameter seems to correlate positively with the long term outcome of dilation. However, at ever shorter intervals between endoscopic interventions, surgery should be discussed as an option for further treatment.
EVALuna2:1853

LONG-TERM HUMORAL RESPONSE TO SARS-COV-2 VACCINATION IN PATIENTS WITH IMMUNE-MEDIATED INFLAMMATORY DISEASE - Tascilar, Koray; Simon, David; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, J.; Liphardt, Anna-Maria; Schönau, Verena; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Long-term outcomes of cyclosporin induction and ustekinumab maintenance combination therapy in patients with steroid-refractory acute severe ulcerative colitis - Vitali, Francesco; Rath, Timo; Klenske, Entcho; Vögele, Anna-Lena; Ganzleben, Ingo; Zundler, Sebastian; Strobel, Deike; Geppert, Carol-Immanuel; Hartmann, Arndt; Neurath, Markus; Atreya, Raja (Therapeutic Advances in Gastroenterology, 2024)
Background: Effective management of patients with acute severe ulcerative colitis (ASUC) is a major challenge and there remains a paucity of available maintenance treatment options after efficacious cyclosporin induction therapy. Objectives: We investigated the long-term effectiveness and safety of cyclosporin and ustekinumab combination therapy in patients with steroid refractory ASUC. Design: Monocentric, prospective study. Methods: We included patients with steroid refractory ASUC with multiple failed prior advanced therapies, who were treated with cyclosporin and ustekinumab combination therapy. Results: Among the 11 included patients, 10 had prior failure to infliximab and 8 failed at least three previous biological therapies. The mean baseline Mayo and Lichtiger scores were 10.9 (9–12) and 13.3 (11–14), respectively. Ustekinumab was initiated 3.2 weeks (1–8) after initiation of cyclosporin treatment and combination therapy was continued for a mean of 11.5 (4–20) weeks. Clinical response was achieved in six patients at week 16 and clinical steroid-free clinical remission in five patients at week 48. Endoscopic remission was achieved in five patients at week 16 and together with histological remission in five patients at week 52. Intestinal ultrasound demonstrated mean bowel wall thickening in the sigmoid colon of 5.5 mm at baseline and 3.5 mm at week 52, respectively. Two patients had to undergo colectomy (mean 4.5 months, range 3–6) and three stopped ustekinumab therapy due to ineffectiveness. Overall, combination therapy was well tolerated. Conclusion: Combination of cyclosporin and ustekinumab therapy allowed nearly half of ASUC patients to reach clinical and endoscopic remission after 52 weeks, warranting further studies. Trial registration: Not applicable.
CRIS-Team Scopus Importer:2024-01-19
Keywords: cyclosporin; proctocolectomy; severe ulcerative colitis; sonography; ustekinumab

Loss of Survivin in Intestinal Epithelial Progenitor Cells Leads to Mitotic Catastrophe and Breakdown of Gut Immune Homeostasis - Martini, Eva; Wittkopf, Nadine; Günther, Claudia; Leppkes, Moritz; Okada, Hitoshi; Watson, Alastair J.; Podstawa, Eva; Backert, Ingo; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph (Cell Reports, 2016)
A tightly regulated balance of proliferation and cell death of intestinal epithelial cells (IECs) is essential for maintenance of gut homeostasis. Survivin is highly expressed during embryogenesis and in several cancer types, but little is known about its role in adult gut tissue. Here, we show that Survivin is specifically expressed in transit-amplifying cells and Lgr5(+) stem cells. Genetic loss of Survivin in IECs resulted in destruction of intestinal integrity, mucosal inflammation, and death of the animals. Survivin deletion was associated with decreased epithelial proliferation due to defective chromosomal segregation. Moreover, Survivin-deficient animals showed induced phosphorylation of p53 and H2AX and increased levels of cell-intrinsic apoptosis in IECs. Consequently, induced deletion of Survivin in Lgr5(+) stem cells led to cell death. In summary, Survivin is a key regulator of gut tissue integrity by regulating epithelial homeostasis in the stem cell niche.
EVALuna2:2058

Low Pretreatment Acoustic Radiation Force Impulse Imaging (ARFI) Values Predict Sustained Virological Response in Antiviral Hepatitis C Virus (HCV) Therapy - Zopf, Steffen; Rösch, Lara; Konturek, Peter; Görtz, Rüdiger; Neurath, Markus; Strobel, Deike (Medical Science Monitor, 2016)
BACKGROUND Non-invasive procedures such as acoustic radiation force impulse imaging (ARFI) shear-wave elastography are currently used for the assessment of liver fibrosis. In the course of chronic hepatitis C, significant liver fibrosis or cirrhosis develops in approximately 25% of patients, which is a negative predictor of antiviral treatment response. Cirrhosis can be prevented by successful virus elimination. In this prospective study, a pretreatment ARFI cutoff value of 1.5 m/s was evaluated in relation to sustained virological response to anti-HCV therapy. MATERIAL AND METHODS In 23 patients with chronic hepatitis C, liver stiffness was examined with ARFI at defined times before and under antiviral triple therapy (peginterferon, ribavirin in combination with a first-generation protease inhibitor, and telaprevir or boceprevir). Patients were stratified into 2 groups based on pretreatment ARFI values (<1.5 m/s and >=1.5 m/s) for the assessment of virological response. RESULTS The liver stiffness at baseline for all patients was 1.57±0.79 m/s (ARFI median ± standard deviation; margin: 0.81 m/s to 3.45 m/s). At week 4 of triple therapy, patients with low pretreatment ARFI values had higher rates of HCV-RNA negativity (69% vs. 43%), reflecting an early rapid virological response (eRVR). Sustained virological response (SVR) was found in 75% (12/16) of patients with an ARFI value <1.5 m/s and only 57% (4/7) of patients with ARFI value >=1.5 m/s. CONCLUSIONS Patients with chronic hepatitis C and pretreatment ARFI <1.5 m/s showed earlier virus elimination and better response to treatment.
EVALuna2:2192

Low-volume high-intensity interval training improves cardiometabolic health, work ability and well-being in severely obese individuals: a randomized-controlled trial sub-study - Reljic, Dejan; Frenk, Fabienne; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (Journal of Translational Medicine, 2020)
Background: Obesity is associated with impaired health and lower work ability. Increased physical activity is a cornerstone in the treatment of obesity and related risk factors. Recently, high-intensity interval training (HIIT) has emerged as a popular exercise option. However, data regarding the effects on cardiometabolic health, perceived work ability and well-being in severely obese individuals are lacking. Methods: Sixty-five obese individuals with sedentary occupation (48.7 ± 9.9 years, BMI: 39.6 ± 7.1 kg/m2) were randomly allocated to an extremely time-efficient HIIT (5 × 1 min at 80–95% maximal heart rate on cycle ergometers, 2×/week for 12 weeks) or an inactive control group (CON). Both groups received nutritional counseling to support weight loss. Primary outcome was maximal oxygen uptake (VO2max), secondary outcomes were cardiometabolic risk indices, body composition, work ability index (WAI), quality of life (QoL, EQ-5D-5L-questionnaire) and perceived stress (PSQ-questionnaire). Results: Mean body weight reduction was 5.3 kg [95% confidence interval (95% CI) − 7.3 to − 3.3 kg] in the HIIT group (P < 0.001) and 3.7 kg (95% CI − 5.3 to − 2.1 kg) in CON (P < 0.001), respectively. Only the HIIT group showed significant (P < 0.001) changes in VO2max [+ 3.5 mL/kg/min (95% CI 2.5 to 4.6 mL/kg/min)], waist circumference [–7.5 cm (95% CI − 9.8 to − 5.1 kg)], mean arterial blood pressure [− 11 mmHg (95% CI − 14 to − 8 mmHg)], WAI [+ 3.0 points (95% CI 1.7 to 4.3 points)] and QoL [+ 10% (95% CI 5 to 16%)]. In CON, none of these parameters improved significantly. Conclusions: Low-volume HIIT may induce significant improvements in cardiometabolic health, especially VO2max, WAI and well-being in obese individuals after only 12 weeks. Our results underpin the wide range of benefits on health and subjective measures through exercise that go well beyond simple weight loss through dietary restriction alone. Trial registration: ClinicalTrials.gov Id: NCT03306069. Registered 10 October 2017, https://clinicaltrials.gov/ct2/show/NCT03306069.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Aerobic exercise; Cardiorespiratory fitness; High-intensity interval training; Metabolic syndrome; Obesity; Psychological health; Weight loss; Work ability

Luminal application of a GATA3-specific DNAzyme ameliorates mucosal inflammation in a randomised trial with active ulcerative colitis patients - Atreya, Raja; Kuehbacher, T.; Schmitt, H.; Hirschmann, S.; Waldner, Maximilian; Drvarov, O.; Fischer, Sven Moritz; Vetter, Marcel; Weigmann, Benno; Turowska, A.; Muhl, T.; Homburg, U.; et al. (2018)
EVALuna2:34074

Magnification endoscopy with optical chromoendoscopy for in vivo assessment of histological inflammation in patients with inflammatory bowel disease - Klenske, E.; Atreya, Raja; Hartmann, Arndt; Fischer, Sören; Hirschmann, Simon; Zundler, Sebastian; Iacucci, M.; Neurath, Markus; Rath, Timo (JOURNAL OF CROHNS & COLITIS, 2019)
CRIS-Team WoS Importer:2019-03-20

Magnification endoscopy with optical chromoendoscopy shows strong correlation with histologic inflammation in patients with inflammatory bowel disease - Klenske, Entcho; Atreya, Raja; Hartmann, Arndt; Fischer, Sören; Hirschmann, Simon; Zundler, Sebastian; Iaccuci, Marietta; Neurath, Markus; Rath, Timo (Endoscopy International Open, 2019)
Background and study aims Apart from mucosal healing as an established treatment goal in inflammatory bowel diseases (IBD), recent evidence suggests that histologic healing may become another key prognostic parameter in IBD patients. We aimed to evaluate whether magnification endoscopy with optical chromoendoscopy can accurately assess histologic inflammation in IBD patients.
CRIS-Team WoS Importer:2019-09-13

Malnutrition in Hospitals: It Was, Is Now, and Must Not Remain a Problem! - Konturek, Peter C.; Herrmann, Hans J.; Schink, Kristin; Neurath, Markus; Zopf, Yurdagül (Medical Science Monitor, 2015)
BACKGROUND Malnutrition is an under-recognized problem in hospitalized patients. Despite systematic screening, the prevalence of malnutrition in the hospital did not decrease in the last few decades. The aim of our study was to evaluate the prevalence of malnutrition and to determine the explicit daily calorie intake of hospitalized patients, to identify the risk factors of developing malnutrition during hospitalization and the effect on the financial reimbursement according to the German DRG-system. MATERIAL AND METHODS 815 hospitalized patients were included in this study. The detection of malnutrition was based on the nutritional-risk-screening (NRS) and subjective-global-assessment (SGA) scores. A trained investigator recorded the daily calorie and fluid intake of each patient. Furthermore, clinical parameters, and the financial reimbursement were evaluated. RESULTS The prevalence of malnutrition was 53.6% according to the SGA and 44.6% according the NRS. During hospitalization, patients received on average 759.9±546.8 kcal/day. The prevalence of malnutrition was increased in patients with hepatic and gastrointestinal disease and with depression or dementia. The most important risk factors for malnutrition were bed rest and immobility (OR=5.88, 95% CI 2.25-15.4). In 84.5% of patient records, malnutrition was not correctly coded, leading to increased financial losses according to the DRG-system (94.908 Euros). CONCLUSIONS Hospitalized patients suffer from inadequate nutritional therapy and the risk for developing malnutrition rises during the hospital stay. The early screening of patients for malnutrition would not only improve management of nutritional therapy but also, with adequate coding, improve financial reimbursement according to the DRG-system.
EVALuna2:1991

Manual cell selection in single cell transcriptomics using scSELpy supports the analysis of immune cell subsets - Dedden, Mark; Wiendl, Maximilian; Müller, Tanja; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2023)
Introduction: Single cell RNA sequencing plays an increasing and indispensable role in immunological research such as in the field of inflammatory bowel diseases (IBD). Professional pipelines are complex, but tools for the manual selection and further downstream analysis of single cell populations are missing so far. Methods: We developed a tool called scSELpy, which can easily be integrated into Scanpy-based pipelines, allowing the manual selection of cells on single cell transcriptomic datasets by drawing polygons on various data representations. The tool further supports the downstream analysis of the selected cells and the plotting of results. Results: Taking advantage of two previously published single cell RNA sequencing datasets we show that this tool is useful for the positive and negative selection of T cell subsets implicated in IBD beyond standard clustering. We further demonstrate the feasibility for subphenotyping T cell subsets and use scSELpy to corroborate earlier conclusions drawn from the dataset. Moreover, we also show its usefulness in the context of T cell receptor sequencing. Discussion: Collectively, scSELpy is a promising additive tool fulfilling a so far unmet need in the field of single cell transcriptomic analysis that might support future immunological research.
CRIS-Team Scopus Importer:2023-05-26
Keywords: chronic inflammation; gut homing; inflammatory bowel disease; single cell RNA sequencing; transcriptomics

Master regulator of intestinal disease: IL-6 in chronic inflammation and cancer development - Waldner, Maximilian; Neurath, Markus (Seminars in Immunology, 2014)
IL-6 signaling is of central importance for the maintenance of chronic intestinal inflammation in inflammatory bowel diseases (IBD) such as Crohn's disease and ulcerative colitis. IL-6 regulates T cell differentiation, activation and resistance against apoptosis and thereby controls the balance between pro-inflammatory T cell subsets such as Th1 or Th17 cells and immunosuppressive regulatory T cells. Furthermore, IL-6 has been implicated in the pathogenesis of colorectal cancer (CRC). In fact, IL-6 directly promotes tumor cell proliferation and survival through STAT3 activation. Due to its role in both types of diseases, IL-6 has been proposed as a missing link between inflammation and tumor development. During recent years, several therapeutics targeting IL-6 dependent pathways have been developed. Although clinical data about anti-IL-6 treatment in intestinal diseases are currently scarce, targeting this pathway might be a promising strategy in IBD and CRC.
EVALuna2:1873

Maximizing the diagnostic information from biopsies in chronic inflammatory bowel diseases: recommendations from the Erlangen International Consensus Conference on Inflammatory Bowel Diseases and presentation of the IBD-DCA score as a proposal for a new index for histologic activity assessment in ulcerative colitis and Crohn's disease - Lang-Schwarz, Corinna; Agaimy, Abbas; Atreya, Raja; Becker, Christoph; Danese, Silvio; Flejou, Jean-Francois; Gassler, Nikolaus; Grabsch, Heike I.; Hartmann, Arndt; Kamaradova, Katerina; Kuehl, Anja A.; Lauwers, Gregory Y.; et al. (Virchows Archiv, 2020)
CRIS-Team WoS Importer:2021-01-22

Maximum Heart Rate- and Lactate Threshold-Based Low-Volume High-Intensity Interval Training Prescriptions Provide Similar Health Benefits in Metabolic Syndrome Patients - Reljic, Dejan; Frenk, Fabienne; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (Healthcare, 2023)
Exercise is an integral part of metabolic syndrome (MetS) treatment. Recently, low-volume high-intensity interval training (LOW-HIIT) has emerged as a time-efficient approach to improving cardiometabolic health. Intensity prescriptions for LOW-HIIT are typically based on maximum heart rate (HRmax) percentages. However, HRmax determination requires maximal effort during exercise testing, which may not always be feasible/safe for MetS patients. This trial compared the effects of a 12-week LOW-HIIT program based on: (a) HRmax (HIIT-HR), or (b) submaximal lactate threshold (HIIT-LT), on cardiometabolic health and quality of life (QoL) in MetS patients. Seventy-five patients were randomized to HIIT-HR (5 × 1 min at 80–95% HRmax), HIIT-LT (5 × 1 min at 95–105% LT) groups, both performed twice weekly on cycle ergometers, or a control group (CON). All patients received nutritional weight loss consultation. All groups reduced their body weight (HIIT-HR: −3.9 kg, p < 0.001; HTT-LT: −5.6 kg, p < 0.001; CON: −2.6 kg, p = 0.003). The HIIT-HR and HIIT-LT groups similarly, improved their maximal oxygen uptake (+3.6 and +3.7 mL/kg/min, p < 0.001), glycohemoglobin (−0.2%, p = 0.005, and −0.3%, p < 0.001), homeostasis model assessment index (−1.3 units, p = 0.005, and −1.0 units, p = 0.014), MetS z-score (−1.9 and −2.5 units, p < 0.001) and QoL (+10 points, p = 0.029, and +11 points, p = 0.002), while the CON did not experience changes in these variables. We conclude that HIIT-LT is a viable alternative to HIIT-HR for patients who are not able/willing to undergo maximal exercise testing.
CRIS-Team Scopus Importer:2023-03-23
Keywords: cardiometabolic health; cardiorespiratory fitness; exercise prescription; glycemic control; heart rate; interval training; lactate; maximal oxygen uptake; obesity; quality of life

Mechanism-based treatment strategies for IBD: Cytokines, cell adhesion molecules, JAK inhibitors, gut flora, and more - Schreiner, Philipp; Neurath, Markus; Ng, Siew C.; El-Omar, Emad M.; Sharara, Ala I.; Kobayashi, Taku; Hisamatsu, Tadakazu; Hibi, Toshifumi; Rogler, Gerhard (Inflammatory Intestinal Diseases, 2019)
Background: Although TNF inhibitors revolutionized the therapy of inflammatory bowel disease (IBD), we have been reaching a point where other therapies with different mechanisms of action are necessary. A rising number of elderly IBD patients with contraindications to established therapies and a growing group of patients losing response to anti-TNF therapy compel us to find safer, better-tolerated, and, ideally, personalized treatment options. However, in order to choose the right drug to fit a patient, it is indispensable to understand the pathomechanism involved in IBD. Summary: The aim of this review is to explain the inflammatory signaling pathways in IBD and how to inhibit them with current and future therapeutic approaches. Next to biologic agents targeting inflammatory cytokines (anti-TNF agents, anti-IL-12/-23 agents, and specific inhibitors of IL-23), biologics blocking leukocyte trafficking to the gut (anti-integrin antibodies) are available nowadays. More recently, small molecules inhibiting the JAK-STAT pathway (JAK inhibitors) or preventing lymphocyte trafficking (sphingosine-1-phosphate modulators) have been approved or are under investigation. Furthermore, modifying the microbiota has potential therapeutic effects on IBD, and autologous hematopoietic or mesenchymal stem cell transplantation may be considered for a highly selected group of IBD patients. Key Message: Physicians should understand the different mechanisms of action of the potential therapies for IBD to select the right drug for the right patient.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Biologics; Crohn's disease; Inflammatory bowel disease; Small molecules; Ulcerative colitis

Mechanisms of molecular resistance and predictors of response to biological therapy in inflammatory bowel disease - Atreya, Raja; Neurath, Markus (Lancet Gastroenterology and Hepatology, 2018)
Biological therapy has led to marked improvements in treatment of patients with inflammatory bowel disease, and an increasing number of drugs has been approved for treatment. However, only a subgroup of patients responds to therapy, highlighting the need to identify biomarkers for therapeutic response to allow personalised medicine in inflammatory bowel disease. Potential markers of response to biological therapy have been identified; however, studies also suggest that changes in the composition of immune cell infiltrates in response to therapeutic pressure lead to molecular resistance to these drugs. For instance, the cytokine interleukin 23 has been identified as a driver of evasion of apoptosis in response to anti-tumour necrosis factor drugs in patients with Crohn's disease, leading to expansion of apoptosis-resistant T cells and drug resistance. In this Review, we examine the concept of molecular resistance to biological therapy and discuss implications for future therapy.
EVALuna2:35134

Medication safety in patients treated with new oral antitumor agents: A prospective, randomized investigation on the impact of intensified clinical pharmaceutical/clinical pharmacological care on patient safety, patient knowledge and patient well-being (AMBORA). Supported by the German Cancer Aid within the Comprehensive Cancer Center Erlangen-EMN - Schlichtig, Katja; Lechner, P.; Grafe, Carolin; Ferstl, B.; Fuchs, F.; Hein, Alexander; Meidenbauer, N.; Sell, C.; Semrau, S.; Pavel, Marianne Ellen; Wullich, Bernd; Neurath, Markus; et al. (2018)
EVALuna2:33795

Ménage-à-Trois: The Ratio of Bicarbonate to CO2 and the pH Regulate the Capacity of Neutrophils to Form NETs - Maueröder, Christian; Mahajan, Aparna; Paulus, Susanne; Goesswein, Stefanie; Hahn, Jonas; Kienhoefer, Deborah; Biermann, Mona H.; Tripal, Philipp; Friedrich, Ralf P.; Munoz Becerra, Luis; Neurath, Markus; Becker, Christoph; et al. (Frontiers in Immunology, 2016)
In this study, we identified and characterized the potential of a high ratio of bicarbonate to CO2 and a moderately alkaline pH to render neutrophils prone to undergo neutrophil extracellular trap (NET) formation. Both experimental settings increased the rate of spontaneous NET release and potentiated the NET-inducing capacity of phorbol esters (phorbol-2-myristate-13-acetate), ionomycin, monosodium urate, and LPS. In contrast, an acidic environment impaired NET formation both spontaneous and induced. Our findings indicate that intracellular alkalinization of neutrophils in response to an alkaline environment leads to an increase of intracellular calcium and neutrophil activation. We further found that the anion channel blocker DIDS strongly reduced NET formation induced by bicarbonate. This finding suggests that the effects observed are due to a molecular program that renders neutrophils susceptible to NET formation. Inflammatory foci may be characterized by an acidic environment. Our data indicate that NET formation is favored by the higher pH at the border regions of inflamed areas. Moreover, our findings highlight the necessity for strict pH control during assays of NET formation.
EVALuna2:2182

Mend Your Fences: The Epithelial Barrier and its Relationship With Mucosal Immunity in Inflammatory Bowel Disease - Martini, Eva; Krug, Susanne M.; Siegmund, Britta; Neurath, Markus; Becker, Christoph (Cellular and Molecular Gastroenterology and Hepatology, 2017)
The intestinal epithelium can be easily disrupted during gut inflammation as seen in inflammatory bowel disease (IBD), such as ulcerative colitis or Crohn's disease. For a long time, research into the pathophysiology of IBD has been focused on immune cell-mediated mechanisms. Recent evidence, however, suggests that the intestinal epithelium might play a major role in the development and perpetuation of IBD. It is now clear that IBD can be triggered by disturbances in epithelial barrier integrity via dysfunctions in intestinal epithelial cell-intrinsic molecular circuits that control the homeostasis, renewal, and repair of intestinal epithelial cells. The intestinal epithelium in the healthy individual represents a semi-permeable physical barrier shielding the interior of the body from invasions of pathogens on the one hand and allowing selective passage of nutrients on the other hand. However, the intestinal epithelium must be considered much more than a simple physical barrier. Instead, the epithelium is a highly dynamic tissue that responds to a plenitude of signals including the intestinal microbiota and signals from the immune system. This epithelial response to these signals regulates barrier function, the composition of the microbiota, and mucosal immune homeostasis within the lamina propria. The epithelium can thus be regarded as a translator between the microbiota and the immune system and aberrant signal transduction between the epithelium and adjacent immune cells might promote immune dysregulation in IBD. This review summarizes the important cellular and molecular barrier components of the intestinal epithelium and emphasizes the mechanisms leading to barrier dysfunction during intestinal inflammation.
EVALuna2:35239

Metastatic adenocarcinomas of the stomach or esophagogastric junction (UICC stage IV) are not always a palliative situation: a retrospective analysis - Schildberg, Claus W.; Weidinger, Thomas; Hohenberger, Werner; Wein, Axel; Langheinrich, Melanie; Neurath, Markus; Boxberger, Frank (World Journal of Surgery, 2014)
Gastric cancer is one of the most common cancers. Unfortunately, it is often diagnosed at the advanced stage International Union Against Cancer stage IV. This induced us to carry out an interdisciplinary analysis of this patient group with the Department of Internal Medicine 1. Our aim was to discuss cancers classified initially as unresectable in a meeting of the interdisciplinary tumor board after palliative chemotherapy, and to refer selected patients for surgery after establishing resectability. The outcome of the chemotherapy, operation method, complication rate, and long-term survival were analyzed.From 1999 to 2008, 76 patients with metastatic gastric cancer or carcinoma of the esophagogastric junction were discussed by the interdisciplinary tumor board of the University of Erlangen and classified initially as unresectable. The patients then received palliative chemotherapy according to the AIO regimen (weekly high-dose 5-fluorouracil/folinic acid [FU/FA] in a 24 h infusion), plus irinotecan. If the tumor was subsequently classified as resectable, the patient underwent either gastric resection or gastrectomy with DII-III dissection. Metastases were resected depending on their location (liver). Peritoneal carcinomatosis was treated additionally by HIPEC. Statistical analysis was with SPSSS version 20.Surgical and general complications and hospital mortality were acceptable. There were no cases of anastomotic leak, but one patient died of fulminant pneumonia. The R0 resection rate was 69 %, and four patients had long-term survival of more than 60 months. There were significant survival advantages.Metastatic gastric cancer or carcinoma of the esophagogastric junction can become resectable after downsizing the tumor with palliative chemotherapy. Long-term survival is achieved in some cases. Therefore, every patient with this type of cancer should be discussed by the interdisciplinary tumour board after palliative chemotherapy to provide him with a chance of cure after re-evaluation.
EVALuna2:1716

Methotrexate Hampers Immunogenicity to BNT162b2 mRNA COVID-19 Vaccine in Immune-Mediated Inflammatory Disease - Haberman, Rebecca; Herati, Ramin; Simon, David; Samanovic, Marie; Tuen, Michael; Blank, Rebecca; Koralov, Sergei; Atreya, Raja; Tascilar, Koray; Allen, Joseph; Castillo, Rochelle; Cornelius, Amber; et al. (ARTHRITIS & RHEUMATOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Methotrexate hampers immunogenicity to BNT162b2 mRNA COVID-19 vaccine in immune-mediated inflammatory disease - Haberman, Rebecca H.; Herati, Ramin Sedaghat; Simon, David; Samanovic, Marie; Blank, Rebecca B.; Tuen, Michael; Koralov, Sergei B.; Atreya, Raja; Tascilar, Koray; Allen, Joseph R.; Castillo, Rochelle; Cornelius, Amber R.; et al. (Annals of the Rheumatic Diseases, 2021)
Objective To investigate the humoral and cellular immune response to messenger RNA (mRNA) COVID-19 vaccines in patients with immune-mediated inflammatory diseases (IMIDs) on immunomodulatory treatment.
CRIS-Team WoS Importer:2021-10-08

Microbial patterns in patients with histamine intolerance - Schink, Monic; Konturek, P. C.; Tietz, E.; Dieterich, Walburga; Pinzer, T. C.; Wirtz, Stefan; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2018)
Histamine intolerance represents a controversially discussed disorder. Besides an impaired degradation of orally supplied histamine due to diamine oxidase (DAO) deficiency, a deranged gut flora may also contribute to elevated histamine levels. Our aim was to determine the intestinal bacterial composition in patients with proven histamine intolerance in comparison to other food intolerances and healthy controls. A total of 64 participants were included in the study, encompassing 8 patients with histamine intolerance (HIT), 25 with food hypersensitivity (FH), 21 with food allergy and 10 healthy controls (HC). All participants underwent blood testing for total and food-specific immunoglobulin E, plasma histamine and DAO serum activity. Stool samples were used to analyze stool histamine and zonulin levels and bacterial composition by 16s rRNA sequencing. No significant differences in stool histamine levels were observed, but HIT patients showed elevated levels of stool zonulin. Microbiota analysis revealed increased levels of Proteobacteria (5.4%) and a significantly reduced alpha-diversity in the HIT group (P = 0.019). On family level, HC showed a significantly higher abundance of Bifidobacteriaceae compared to other study groups (P = 0.005), with lowest levels in the HIT group (P = 0.036). Also significantly reduced abundances of the genera Butyricimonas (P = 0.026) and Hespellia (P = 0.025) were observed in the HIT patients, whereas Roseburia were significantly elevated (P = 0.021). We concluded that the altered occurrence of Proteobacteria and Bifidobacteriaceae, reduced alpha-diversity as well as elevated stool zonulin levels suggest a dysbiosis and intestinal barrier dysfunction in histamine intolerant patients, which in turn may play an important role in driving disease pathogenesis.
EVALuna2:184493

Microbiota: relevant player in thiopurine metabolisation? - Atreya, Imke; Neurath, Markus (Gut, 2017)
EVALuna2:33832

Microscopic colitis and colorectal neoplastic lesion rate in chronic nonbloody diarrhea: a prospective, multicenter study - Tontini, Gian Eugenio; Pastorelli, Luca; Spina, Luisa; Fabris, Federica; Bruni, Barbara; Clemente, Claudio; De Nucci, Germana; Cavallaro, Flaminia; Marconi, Stefano; Neurath, Markus; Neumann, Helmut; Tacconi, Milena; et al. (Inflammatory Bowel Diseases, 2014)
Lymphocytic and collagenous colitis are emerging as common findings in subjects undergoing colonoscopy for chronic non-bloody diarrhea (CNBD). Data concerning microscopic colitis (MC) are still limited and affected by controversial epidemiological evidences. Recent converging lines of evidence suggest that MC correlates a lower risk of colorectal neoplasia. Accordingly, we prospectively assessed MC prevalence in a multicenter cohort of subjects submitted to colonoscopy for CNBD, thereby defining whether MC influences the risk of colorectal neoplasia.Consecutive patients with CNBD of unknown origin underwent pan-colonoscopy with multiple biopsies. The prevalence of neoplastic patients in MC was compared with that observed in negative CNBD subjects.Among 8006 colonoscopy, 305 subjects were enrolled for CNBD. Patients with CNBD were more likely to be women than men (odds ratio = 1.5; P = 0.001). Histopathology detected high prevalence of MC (16%) with a clear predominance of collagenous colitis (70%). A striking age-dependent rise in MC-associated risk was observed, depicting outstanding differences among varying age groups, as in the number needed to screen 1 new case. Gender distribution was balanced within MC patients (Female/Male = 1.5/1), especially among lymphocytic colitis (Female/Male = 1.2/1). MC patients were negatively associated with the risk of neoplastic polyps compared with negative CNBD subjects (odds ratio = 0.22; P = 0.035).MC is the first cause of CNBD in subjects submitted to colonoscopy. Multiple biopsies are strongly recommended, even in the case of uneventful endoscopic inspection, especially for age >=40 years. MC has a reduced risk of colorectal neoplasia, suggesting that this model of chronic inflammation plays a protective effect against colorectal carcinogenesis.
EVALuna2:1899

Mild COVID-19 Symptoms in an Infliximab-Treated Ulcerative Colitis Patient: Can Ongoing Anti-TNF Therapy Protect against the Viral Hyperinflammatory Response and Avoid Aggravated Outcomes? - Abdullah, Abdullah; Neurath, Markus; Atreya, Raja (Visceral Medicine, 2020)
The ongoing coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2, represents a potentially major challenge to patients with immune-mediated inflammatory diseases who are treated with immunomodulatory therapies. We report the case of an 18-year-old ulcerative colitis patient in sustained clinical remission who 4 days after application of her ongoing therapy with the anti-TNF antibody infliximab developed mild respiratory and abdominal symptoms. The patient was subsequently diagnosed with COVID-19 but did not need hospitalization. The clinical symptoms completely resolved within 1 week after onset and there was no change in ulcerative colitis activity. The recently applied anti-TNF therapy did not lead to exacerbation of the infectious symptoms. Current recommendations strongly favor continuation of effective maintenance anti-TNF therapy in inflammatory bowel disease patients, as there is no evidence for aggravated CO-VID-19 upon infection. It is unclear whether anti-TNF treatment might even have assisted in preventing worsening of COVID-19 and improving outcome. Further data in the group of immune-mediated inflammatory disease patients under anti-TNF therapy are urgently needed.
CRIS-Team Scopus Importer:2020-06-19

Modulation of the extrinsic cell death signaling pathway by viral Flip induces acute-death mediated liver failure - Bittel, Miriam; Kremer, Andreas; Stürzl, Michael; Wirtz, Stefan; Stolzer, Iris; Neurath, Markus; Ballon, Gianna; Günther, Claudia (Cell Death & Disease, 2019)
During viral infections viruses express molecules that interfere with the host-cell death machinery and thus inhibit cell death responses. For example the viral FLIP (vFLIP) encoded by Kaposi’s sarcoma-associated herpesvirus interacts and inhibits the central cell death effector, Caspase-8. In order to analyze the impact of anti-apoptotic viral proteins, like vFlip, on liver physiology in vivo, mice expressing vFlip constitutively in hepatocytes (vFlipAlbCre+) were generated. Transgenic expression of vFlip caused severe liver tissue injury accompanied by massive hepatocellular necrosis and inflammation that finally culminated in early postnatal death of mice. On a molecular level, hepatocellular death was mediated by RIPK1-MLKL necroptosis driven by an autocrine TNF production. The loss of hepatocytes was accompanied by impaired bile acid production and disruption of the bile duct structure with impact on the liver-gut axis. Notably, embryonic development and tissue homeostasis were unaffected by vFlip expression. In summary our data uncovered that transgenic expression of vFlip can cause severe liver injury in mice, culminating in multiple organ insufficiency and death. These results demonstrate that viral cell death regulatory molecules exhibit different facets of activities beyond the inhibition of cell death that may merit more sophisticated in vitro and in vivo analysis.
CRIS-Team Scopus Importer:2019-12-03

Molecular Communication Between Neuronal Networks and Intestinal Epithelial Cells in Gut Inflammation and Parkinson's Disease - Drobny, Alice; Ngo, Phuong A.; Neurath, Markus; Zunke, Friederike; Lopez-Posadas, Rocio (Frontiers in Medicine, 2021)
Intestinal symptoms, such as nausea, vomiting, and constipation, are common in Parkinson's disease patients. These clinical signs normally appear years before the diagnosis of the neurodegenerative disease, preceding the occurrence of motor manifestations. Moreover, it is postulated that Parkinson's disease might originate in the gut, due to a response against the intestinal microbiota leading to alterations in alpha-synuclein in the intestinal autonomic nervous system. Transmission of this protein to the central nervous system is mediated potentially via the vagus nerve. Thus, deposition of aggregated alpha-synuclein in the gastrointestinal tract has been suggested as a potential prodromal diagnostic marker for Parkinson's disease. Interestingly, hallmarks of chronic intestinal inflammation in inflammatory bowel disease, such as dysbiosis and increased intestinal permeability, are also observed in Parkinson's disease patients. Additionally, alpha-synuclein accumulations were detected in the gut of Crohn's disease patients. Despite a solid association between neurodegenerative diseases and gut inflammation, it is not clear whether intestinal alterations represent cause or consequence of neuroinflammation in the central nervous system. In this review, we summarize the bidirectional communication between the brain and the gut in the context of Parkinson's disease and intestinal dysfunction/inflammation as present in inflammatory bowel disease. Further, we focus on the contribution of intestinal epithelium, the communication between intestinal epithelial cells, microbiota, immune and neuronal cells, as well as mechanisms causing alterations of epithelial integrity.
CRIS-Team WoS Importer:2021-09-03

Molecular cross-talk between Y5-receptor and neuropeptide Y drives liver cancer - Dietrich, Peter; Wormser, Laura; Fritz, Valerie; Seitz, Tatjana; de Maria, Monica; Schambony, Alexandra; Kremer, Andreas; Günther, Claudia; Itzel, Timo; Thasler, Wolfgang E.; Teufel, Andreas; Trebicka, Jonel; et al. (Journal of Clinical Investigation, 2020)
Hepatocellular carcinoma (HCC) is clearly age-related and represents one of the deadliest cancer types worldwide. Due to globally increasing risk factors including metabolic disorders, the incidence rates of HCC are still rising. However, the molecular hallmarks of HCC remain poorly understood. Neuropeptide Y (NPY) and NPY-receptors represent a highly conserved, stress-activated system which is involved in diverse cancer-related hallmarks including aging and metabolic alterations, but its impact on liver cancer had been unclear. Here, we observed increased NPY5-receptor (Y5R) expression in HCC which correlated with tumor growth and survival. Furthermore, we found that its ligand NPY was secreted by peri-tumorous hepatocytes. Hepatocyte-derived NPY promoted HCC progression by Y5R-activation. Transforming growth factor beta 1 (TGFβ1) was identified as a regulator of NPY in hepatocytes and induced Y5R in invasive cancer cells. Moreover, NPY-conversion by dipeptidylpeptidase 4 (DPP4) augmented Y5R-activation and function in liver cancer. The TGFβ-NPY-Y5R-axis and DPP4 represent attractive therapeutic targets for controlling liver cancer progression.
EVALuna2:212290
Keywords: Aging; Cancer; Hepatology

Molecular Endoscopic Imaging in Cancer - Rath, Timo; Neurath, Markus; Atreya, Raja (Elsevier, 2021)
Through the combination of administration of fluorescently labeled molecular dyes that specifically bind to defined molecular targets and their subsequent visualization with endoscopic devices, molecular endoscopic imaging enables in vivo real-time imaging of single molecules or receptors.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Barrett’s esophagus; Cancer; Colorectal cancer; Endoscopy; Gastric cancer; Molecular imaging

Molecular Endoscopy and in vivo Imaging in Inflammatory Bowel Diseases - Neurath, Markus (Digestive Diseases, 2015)
Studies in recent years have shown that standard imaging modalities such as endoscopy, ultrasonography or MRI are essential for assessment of gut inflammation in patients with inflammatory bowel diseases (IBDs). In addition, endoscopy plays a pivotal role in the analysis of mucosal healing in these disorders. However, these techniques do not allow a detailed analysis of the molecular pathways driving gut inflammation in IBD patients. Here, we discuss the role of new techniques for the molecular imaging of gut inflammation in IBD with special reference to the prediction of responses to therapy using antibodies to tumor necrosis factor (anti-TNF). Key Messages: Several in vivo imaging studies have been performed in IBD patients before and after anti-TNF therapy. In one study, (99m)Technetium-labeled annexin V was given to patients with active Crohn's disease before and after anti-TNF therapy with infliximab. Subsequently, single-photon emission CT (SPECT) was performed to study the effect of anti-TNF treatment on apoptosis in the intestine during active colitis. This study showed enrichment of technetium signals in the gut of patients who responded to anti-TNF therapy. The findings suggested that anti-TNF treatment induces T-cell apoptosis in vivo and that SPECT imaging can be used for prediction of response to anti-TNF therapy. In another study, fluorescent anti-TNF antibodies (fluorescent adalimumab) were chosen for molecular imaging during confocal laser endomicroscopy in patients with active Crohn's disease. This study revealed that an increase of membrane-bound TNF expressing mucosal immune cells predicts response to subsequent adalimumab therapy.Molecular in vivo imaging is an exciting new field in patients with IBD. It is expected that this field will allow new insights into the pathophysiology of IBD and may be used for personalized medicine in the future.
EVALuna2:2170

Molecular Endoscopy for the Diagnosis and Therapeutic Monitoring of Colorectal Cancer - Waldner, Maximilian; Neurath, Markus (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is one of the leading causes of cancer related death in the western world. Its successful treatment requires early detection and removal of precursor lesions as well as individualized treatment of advanced disease. During recent years, molecular imaging techniques have shown promising results to improve current clinical practice. For instance, molecular endoscopy resulted in higher detection rates of precursors in comparison to conventional endoscopy in preclinical and clinical studies. Molecular confocal endomicroscopy allowed a further classification of suspect lesions as well as the prediction and monitoring of the therapeutic response. In this review, we summarize recent achievements for molecular imaging of CRC in preclinical studies, initial clinical trials and the remaining challenges for future translation into clinical practice.
CRIS-Team Scopus Importer:2022-03-25
Keywords: adenoma; colorectal cancer; confocal endomicroscopy; endoscopy; fluorescence; molecular imaging; near-infrared imaging; Raman

Molecular Imaging and its Applications in Selected GI Diseases - Rath, Timo; Neurath, Markus; Atreya, Raja (Techniques and Innovations in Gastrointestinal Endoscopy, 2021)
During the past decade, molecular imaging has emerged as a new and innovative field combining clinical endoscopy with methods prior used in basic science. Through the labeling of cellular targets with certain molecular probes and their subsequent detection with dedicated endoscopic devices, molecular imaging enables the visualization of single molecules or receptors during ongoing endoscopy. Early studies in the field have provided proof-of-principle that molecular imaging can improve visualization, or even unmask, previously unrecognized early dysplasia or cancer. Building on this, further studies then used molecular imaging for grading and detecting inflammation and inflammation associated cancer. Most recently, molecular imaging has been used to phenotype the expression of single receptors and targets of biological therapy and thereby enables molecular tissue profile in vivo. With this live molecular fingerprinting, molecular imaging can be used to guide expression-tailored individualized therapy, and due to the diversification of biological therapy in both cancer and intestinal inflammation, it can be expected that molecular imaging will gain further traction in the foreseeable future. Within this review, we first summarize the technical components commonly used for molecular imaging and then review preclinical and clinical studies and possible and evolving clinical applications on molecular imaging within the entire the GI tract.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Barretts esophagus; Colorectal cancer; Endoscopy; Inflammatory bowel disease; Molecular imaging

Molecular imaging in gastroenterology: A route for personalized endoscopy - Klenske, Entcho; Neurath, Markus; Atreya, Raja; Rath, Timo (Digestive and Liver Disease, 2018)
With the rapid expansion and diversification of the repertoire of biological agents utilized in inflammatory bowel diseases and cancer and the increase in oncological patients in gastroenterology, visualization of single receptor or molecular target expression and the subsequent initiation of expression tailored therapy are gaining increasing attention. Through the combination of utilizing fluorescently labeled probes with high specificity towards defined molecular targets and their subsequent detection and visualization with endoscopic devices, molecular imaging is a new emerging field focusing on the receptor expression within the mucosa on a cellular level rather than on macroscopic changes. In the past years various new technological and molecular probes have been successfully utilized for molecular imaging. Within this review, we summarize different technologies as well as molecular probes applied in molecular imaging and review current and past approaches for functional imaging with molecular endoscopy within the GI Tract and resulting clinical applications. It can be expected that molecular imaging allows for individualized diagnostic approaches and patient tailored medicine in the future.
EVALuna2:35144

Molecular imaging in inflammatory bowel disease - Rath, Timo; Neurath, Markus; Atreya, Raja (Elsevier, 2020)
Recent advances in biological therapy in inflammatory bowel diseases (IBDs) and early detection of colitis-associated neoplasia have increased the popularity of molecular endoscopy with visualization of single receptor or molecular target expression and the subsequent initiation of expression tailored therapy. Molecular imaging is an emerging field in the receptor expression within the mucosa on a cellular level rather than on macroscopic changes. Various new technological and molecular probes have been utilized for molecular imaging. These new technologies have found their applications in diagnosis, disease monitoring, and assessment of treatment response in IBD. They may also play a role in the detection of colitis-associated neoplasia.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Biological therapy; Crohn’s disease; endomicroscopy; inflammation; therapeutic response; ulcerative colitis

Molecular Imaging of alpha 4 beta 7 Integrin Expression by Confocal Laser Endomicroscopy With Fluorescent Vedolizumab in Crohn's Disease - Rath, Timo; Bojarski, Christian; Neurath, Markus; Atreya, Raja (2017)
EVALuna2:33904

Molecular imaging of mucosal α4β7 integrin expression with the fluorescent anti-adhesion antibody vedolizumab in Crohn's disease - Rath, Timo; Bojarski, Christian; Neurath, Markus; Atreya, Raja (Gastrointestinal Endoscopy, 2017)
EVALuna2:33806

Molecular Imaging: The New Frontier for Endoscopic Diagnosis and Personalization in Inflammatory Bowel Disease - Atreya, Raja; Rath, Timo; Neurath, Markus (Gastrointestinal Endoscopy Clinics of North America, 2024)
CRIS-Team Scopus Importer:2024-10-18
Keywords: Fluorescence; Fluorescent antibody; IBD; Molecular endoscopy; Molecular imaging; Mucosa; Prediction of response; Target cell

Molecular imaging within the lower gastrointestinal tract: From feasibility to future - Rath, Timo; Kiesslich, Ralf; Neurath, Markus; Atreya, Raja (Digestive Endoscopy, 2018)
Molecular imaging is based on the labelling of defined molecular targets through the utilization of fluorescently linked probes and their subsequent detection with high-resolution endoscopic devices, thereby enabling visualization of single molecules including receptors. Whereas early studies have used molecular imaging for improved visualization and detection of early dysplasia and cancer as well as for assessing intestinal inflammation and inflammation-associated cancer within the gastrointestinal (GI) tract, more recent studies have impressively demonstrated that molecular imaging can also be used to characterize and visualize the molecular fingerprint of cancer and inflammation in vivo and in real time. With this, molecular imaging can be used to guide expression-tailored individualized therapy. With the rapid expansion and diversification of the repertoire of biological agents utilized in inflammatory bowel disease and cancer, this approach is gaining increasing attention. Within this review, we first summarize the technical components commonly used for molecular imaging and then review preclinical and clinical studies and evolving clinical applications on molecular imaging within the lower GI tract. Molecular imaging has the potential to significantly change endoscopic diagnosis and subsequent targeted therapy of gastrointestinal cancer and chronic gastrointestinal diseases.
EVALuna2:35133

Molecular mechanism of action of anti-tumor necrosis factor antibodies in inflammatory bowel diseases - Billmeier, Ulrike; Dieterich, Walburga; Neurath, Markus; Atreya, Raja (World Journal of Gastroenterology, 2016)
Anti-tumor necrosis factor (TNF) antibodies are successfully used in the therapy of inflammatory bowel diseases (IBD). However, the molecular mechanism of action of these agents is still a matter of debate. Apart from neutralization of TNF, influence on the intestinal barrier function, induction of apoptosis in mucosal immune cells, formation of regulatory macrophages as well as other immune modulating properties have been discussed as central features. Nevertheless, clinically effective anti-TNF antibodies were shown to differ in their mode-of-action in vivo and in vitro. Furthermore, the anti-TNF agent etanercept is effective in the treatment of rheumatoid arthritis but failed to induce clinical response in Crohn's disease patients, suggesting different contributions of TNF in the pathogenesis of these inflammatory diseases. In the following, we will review different aspects regarding the mechanism of action of anti-TNF agents in general and analyze comparatively different effects of each anti-TNF agent such as TNF neutralization, modulation of the immune system, reverse signaling and induction of apoptosis. We discuss the relevance of the membrane-bound form of TNF compared to the soluble form for the immunopathogenesis of IBD. Furthermore, we review reports that could lead to personalized medicine approaches regarding treatment with anti-TNF antibodies in chronic intestinal inflammation, by predicting response to therapy.
EVALuna2:2196

Molecular pathways driving disease-specific alterations of intestinal epithelial cells - Lopez Posadas, Rocío; Neurath, Markus; Atreya, Imke (Cellular and Molecular Life Sciences, 2017)
Due to the fact that chronic inflammation as well as tumorigenesis in the gut is crucially impacted by the fate of intestinal epithelial cells, our article provides a comprehensive overview of the composition, function, regulation and homeostasis of the gut epithelium. In particular, we focus on those aspects which were found to be altered in the context of inflammatory bowel diseases or colorectal cancer and also discuss potential molecular targets for a disease-specific therapeutic intervention.
EVALuna2:33826

Mongersen, an oral SMAD7 antisense oligonucleotide, and Crohn's disease - Monteleone, Giovanni; Neurath, Markus; Ardizzone, Sandro; Di Sabatino, Antonio; Fantini, Massimo C.; Castiglione, Fabiana; Scribano, Maria L.; Armuzzi, Alessandro; Caprioli, Flavio; Sturniolo, Giacomo C.; Rogai, Francesca; Vecchi, Maurizio; et al. (New England Journal of Medicine, 2015)
Crohn's disease-related inflammation is characterized by reduced activity of the immunosuppressive cytokine transforming growth factor ?1 (TGF-?1) due to high levels of SMAD7, an inhibitor of TGF-?1 signaling. Preclinical studies and a phase 1 study have shown that an oral SMAD7 antisense oligonucleotide, mongersen, targets ileal and colonic SMAD7.In a double-blind, placebo-controlled, phase 2 trial, we evaluated the efficacy of mongersen for the treatment of persons with active Crohn's disease. Patients were randomly assigned to receive 10, 40, or 160 mg of mongersen or placebo per day for 2 weeks. The primary outcomes were clinical remission at day 15, defined as a Crohn's Disease Activity Index (CDAI) score of less than 150, with maintenance of remission for at least 2 weeks, and the safety of mongersen treatment. A secondary outcome was clinical response (defined as a reduction of 100 points or more in the CDAI score) at day 28.The proportions of patients who reached the primary end point were 55% and 65% for the 40-mg and 160-mg mongersen groups, respectively, as compared with 10% for the placebo group (P<0.001). There was no significant difference in the percentage of participants reaching clinical remission between the 10-mg group (12%) and the placebo group. The rate of clinical response was significantly greater among patients receiving 10 mg (37%), 40 mg (58%), or 160 mg (72%) of mongersen than among those receiving placebo (17%) (P=0.04, P<0.001, and P<0.001, respectively). Most adverse events were related to complications and symptoms of Crohn's disease.We found that study participants with Crohn's disease who received mongersen had significantly higher rates of remission and clinical response than those who received placebo. (Funded by Giuliani; EudraCT number, 2011-002640-27.).
EVALuna2:2001

Monitoring spinal muscular atrophy with three-dimensional optoacoustic imaging - Nedoschill, Emmanuel; Wagner, Alexandra L.; Danko, Vera; Bühler, Adrian; Raming, Roman; Jüngert, Jörg M.; Neurath, Markus; Waldner, Maximilian; Rother, Ulrich; Wölfle, Joachim; Trollmann, Regina; Knieling, Ferdinand; et al. (Med, 2024)
Background: Spinal muscular atrophy is a progressive neuromuscular disorder and among the most frequent genetic causes of infant mortality. While recent advancements in gene therapy provide the potential to ameliorate the disease severity, there is currently no modality in clinical use to visualize dynamic pathophysiological changes in disease progression and regression after therapy. Methods: In this prospective diagnostic clinical study, ten pediatric patients with spinal muscular atrophy and ten age- and sex-matched controls have been examined with three-dimensional optoacoustic imaging and clinical standard examinations to compare the spectral profile of muscle tissue and correlate it with motor function (ClinicalTrials.gov: NCT04115475). Findings: We observed a reduced optoacoustic signal in muscle tissue of pediatric patients with spinal muscular atrophy. The reduction in signal intensity correlated with disease severity as assessed by grayscale ultrasound and standard motor function tests. In a cohort of patients who received disease-modifying therapy prior to the study, the optoacoustic signal intensity was similar to healthy controls. Conclusions: This translational study provides early evidence that three-dimensional optoacoustic imaging could have clinical implications in monitoring disease activity in spinal muscular atrophy. By visualizing and quantifying molecular changes in muscle tissue, disease progression and effects of gene therapy can be assessed in real time. Funding: The project was funded by ELAN Fonds (P055) at the University Hospital of the Friedrich-Alexander-Universität (FAU) Erlangen-Nurnberg to A.P.R.
CRIS-Team Scopus Importer:2024-05-03
Keywords: gene therapy; non-invasive imaging; optoacoustic imaging; pediatric spinal muscular atrophy; photoacoustic imaging; spinal muscular atrophy; Translation to patients

Morbus Crohn und Colitis ulcerosa in der Hausarztpraxis - Baer, Eva; Jesper, Daniel; Neurath, Markus; Atreya, Raja (MMW Fortschritte der Medizin, 2020)
CRIS-Team Scopus Importer:2020-11-20

Motorized spiral enteroscopy: Results of an international multicenter prospective observational clinical study in patients with normal and altered gastrointestinal anatomy - Beyna, Torsten; Moreels, Tom; Arvanitakis, Marianna; Pioche, Mathieu; Saurin, Jean-Christophe; May, Andrea; Knabe, Mate; Agnholt, Jorgen Steen; Bjerregaard, Niels Christian; Puustinen, Lauri; Schlag, Christoph; Aabakken, Lars; et al. (Endoscopy, 2022)
Background Motorized spiral enteroscopy (MSE) has been shown to be safe and effective for deep enteroscopy in studies performed at expert centers with limited numbers of patients without previous abdominal surgery. This study aimed to investigate the safety, efficacy, and learning curve associated with MSE in a real-life scenario, with the inclusion of patients after abdominal surgery and with altered anatomy. Methods Patients with indications for deep enteroscopy were enrolled in a prospective observational multicenter study. The primary objective was the serious adverse event (SAE) rate; secondary objectives were the diagnostic and therapeutic yield, procedural success, time, and insertion depth. Data analysis was subdivided into training and core (post-training) study phases at centers with different levels of MSE experience. Results 298 patients (120 women; median age 68, range 19-92) were enrolled. In the post-training phase, 21.5 % (n = 54) had previous abdominal surgery, 10.0 % (n = 25) had surgically altered anatomy. Overall, SAEs occurred in 2.3 % (7/298; 95 %CI 0.9 %-4.8 %). The SAE rate was 2.0 % (5/251) in the core group and 4.3 % (2/47) in the training group, and was not increased after abdominal surgery (1.9 %). Total enteroscopy was achieved in half of the patients (n = 42) undergoing planned total enteroscopy. In 295/337 procedures (87.5 %), the anatomical region of interest could be reached. Conclusions This prospective multicenter study showed that MSE was feasible and safe in a large cohort of patients in a real-life setting, after a short learning curve. MSE was shown to be feasible in postsurgical patients, including those with altered anatomy, without an increase in the SAE rate.
CRIS-Team Scopus Importer:2022-07-22

Mucosal Biofilms Are an Endoscopic Feature of Irritable Bowel Syndrome and Ulcerative Colitis - Baumgartner, Maximilian; Lang, Michaela; Holley, Hunter; Crepaz, Daniel; Hausmann, Bela; Pjevac, Petra; Moser, Doris; Haller, Felix; Hof, Fabian; Beer, Andrea; Orgler, Elisabeth; Frick, Adrian; et al. (Gastroenterology, 2021)
Background & Aims: Irritable bowel syndrome (IBS) and inflammatory bowel diseases result in a substantial reduction in quality of life and a considerable socioeconomic impact. In IBS, diagnosis and treatment options are limited, but evidence for involvement of the gut microbiome in disease pathophysiology is emerging. Here we analyzed the prevalence of endoscopically visible mucosal biofilms in gastrointestinal disease and associated changes in microbiome composition and metabolism. Methods: The presence of mucosal biofilms was assessed in 1426 patients at 2 European university-based endoscopy centers. One-hundred and seventeen patients were selected for in-depth molecular and microscopic analysis using 16S ribosomal RNA gene amplicon-sequencing of colonic biopsies and fecal samples, confocal microscopy with deep learning–based image analysis, scanning electron microscopy, metabolomics, and in vitro biofilm formation assays. Results: Biofilms were present in 57% of patients with IBS and 34% of patients with ulcerative colitis compared with 6% of controls (P < .001). These yellow-green adherent layers of the ileum and right-sided colon were microscopically confirmed to be dense bacterial biofilms. 16S-sequencing links the presence of biofilms to a dysbiotic gut microbiome, including overgrowth of Escherichia coli and Ruminococcus gnavus. R. gnavus isolates cultivated from patient biofilms also formed biofilms in vitro. Metabolomic analysis found an accumulation of bile acids within biofilms that correlated with fecal bile acid excretion, linking this phenotype with a mechanism of diarrhea. Conclusions: The presence of mucosal biofilms is an endoscopic feature in a subgroup of IBS and ulcerative colitis with disrupted bile acid metabolism and bacterial dysbiosis. They provide novel insight into the pathophysiology of IBS and ulcerative colitis, illustrating that biofilm can be seen as a tipping point in the development of dysbiosis and disease.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Bacterial–Epithelial Interaction; Endoscopy; Functional Gastrointestinal Disorders; Microbiota

MULTICENTER ANALYSIS OF ENDOCLOT AS HEMOSTATIC POWDER IN DIFFERENT ENDOSCOPIC SETTINGS OF THE UPPER GASTROINTESTINAL TRACT - Hagel, Alexander; Raithel, M.; Hempen, P.; Preclik, G.; Dauth, W.; Neurath, Markus; Gschossmann, J.; Konturek, P. C.; Albrecht, Heinz (Journal of Physiology and Pharmacology, 2020)
Gastrointestinal bleeding (GIB) still presents a demanding situation with high morbidity and mortality rates; thus hemostatic powders such as EndoClot (EC) have been developed to improve endoscopic armament. The aim of the present study was to determine which indications triggered the application of EC and to assess resulting hemostasis rates. Forty three patients undergoing endoscopical procedures in three hospitals; two tertiary care and one university hospital, were included. EC was applied in 48 endoscopies in 43 patients (27 male, age 65.5 years, range 28 - 92 years) following four different indications. EC was used in active GIB as rescue or first-line therapy giving a short-term and long-term hemostasis in 13/17 patients (76.5%). In the setting of non-active GIB, following conventionally achieved hemostasis or endoscopic interventions, EC was found to prevent bleeding in 19/21 patients (90.4%). EC induced hemostasis in 8/10 patients (80%) with impaired coagulation. EC failures resulted from tumor bleeding, Forrest I lesions or perforated duodenal ulcers. No major adverse events were recorded and one technical failure (2.1%) occurred. EC was applied as first line or salvage treatment in ongoing bleedings with promising results. Furthermore, EC was used after successful hemostasis or following endoscopic interventions to further reduce re-bleeding rates. We saw promising results in all indications, albeit lacking a control group.
CRIS-Team WoS Importer:2021-02-19

Multiscale Bowel Sound Event Spotting in Highly Imbalanced Wearable Monitoring Data: Algorithm Development and Validation Study. - Baronetto, Annalisa; Graf, Luisa; Fischer, Sarah; Neurath, Markus; Amft, Oliver (JMIR AI, 2024)
BACKGROUND: Abdominal auscultation (i.e., listening to bowel sounds (BSs)) can be used to analyze digestion. An automated retrieval of BS would be beneficial to assess gastrointestinal disorders noninvasively. OBJECTIVE: This study aims to develop a multiscale spotting model to detect BSs in continuous audio data from a wearable monitoring system. METHODS: We designed a spotting model based on the Efficient-U-Net (EffUNet) architecture to analyze 10-second audio segments at a time and spot BSs with a temporal resolution of 25 ms. Evaluation data were collected across different digestive phases from 18 healthy participants and 9 patients with inflammatory bowel disease (IBD). Audio data were recorded in a daytime setting with a smart T-Shirt that embeds digital microphones. The data set was annotated by independent raters with substantial agreement (Cohen κ between 0.70 and 0.75), resulting in 136 hours of labeled data. In total, 11,482 BSs were analyzed, with a BS duration ranging between 18 ms and 6.3 seconds. The share of BSs in the data set (BS ratio) was 0.0089. We analyzed the performance depending on noise level, BS duration, and BS event rate. We also report spotting timing errors. RESULTS: Leave-one-participant-out cross-validation of BS event spotting yielded a median F1-score of 0.73 for both healthy volunteers and patients with IBD. EffUNet detected BSs under different noise conditions with 0.73 recall and 0.72 precision. In particular, for a signal-to-noise ratio over 4 dB, more than 83% of BSs were recognized, with precision of 0.77 or more. EffUNet recall dropped below 0.60 for BS duration of 1.5 seconds or less. At a BS ratio greater than 0.05, the precision of our model was over 0.83. For both healthy participants and patients with IBD, insertion and deletion timing errors were the largest, with a total of 15.54 minutes of insertion errors and 13.08 minutes of deletion errors over the total audio data set. On our data set, EffUNet outperformed existing BS spotting models that provide similar temporal resolution. CONCLUSIONS: The EffUNet spotter is robust against background noise and can retrieve BSs with varying duration. EffUNet outperforms previous BS detection approaches in unmodified audio data, containing highly sparse BS events.
EVALuna2:590878

Multispectral optoacoustic tomography enables assessment of disease activity in paediatric inflammatory bowel disease - Regensburger, Adrian; Eckstein, Markus; Wetzl, Matthias; Raming, Roman; Paulus, Lars-Philip; Bühler, Adrian; Nedoschill, Emmanuel; Danko, Vera; Jüngert, Jörg; Wagner, Alexandra; Schnell, Alexander; Rückel, Aline; et al. (Photoacoustics, 2024)
Multispectral optoacoustic tomography (MSOT) allows non-invasive molecular disease activity assessment in adults with inflammatory bowel disease (IBD). In this prospective pilot-study, we investigated, whether increased levels of MSOT haemoglobin parameters corresponded to inflammatory activity in paediatric IBD patients, too. 23 children with suspected IBD underwent MSOT of the terminal ileum and sigmoid colon with standard validation (e.g. endoscopy). In Crohn‘s disease (CD) and ulcerative colitis (UC) patients with endoscopically confirmed disease activity, MSOT total haemoglobin (HbT) signals were increased in the terminal ileum of CD (72.1 ± 13.0 a.u. vs. 32.9 ± 15.4 a.u., p = 0.0049) and in the sigmoid colon of UC patients (62.9 ± 13.8 a.u. vs. 35.1 ± 16.3 a.u., p = 0.0311) as compared to controls, respectively. Furthermore, MSOT haemoglobin parameters correlated well with standard disease activity assessment (e.g. SES-CD and MSOT HbT (rs =0.69, p = 0.0075). Summarizing, MSOT is a novel technology for non-invasive molecular disease activity assessment in paediatric patients with inflammatory bowel disease.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Multispectral optoacoustic tomography; Optoacoustic imaging; Paediatric inflammatory bowel disease

Multispectral Optoacoustic Tomography for Assessment of Crohn's Disease Activity - Knieling, Ferdinand; Neufert, Clemens; Hartmann, Arndt; Claussen, Jing; Urich, Alexander; Egger, Cornelia; Vetter, Marcel; Fischer, Sarah; Pfeifer, Lukas; Hagel, Alexander; Kielisch, Christian; Görtz, Rüdiger; et al. (New England Journal of Medicine, 2017)
EVALuna2:33821

Multispectral optoacoustic tomography for non-invasive disease phenotyping in pediatric spinal muscular atrophy patients - Regensburger, Adrian; Wagner, Alexandra; Danko, Vera; Jüngert, Jörg M.; Federle, Anna; Klett, Daniel; Schüssler, Stephanie; Buehler, Adrian; Neurath, Markus; Roos, Andreas; Lochmüller, Hanns; Wölfle, Joachim; et al. (Photoacoustics, 2022)
Proximal spinal muscular atrophy (SMA) is a rare progressive, life limiting genetic motor neuron disease. While promising causal therapies are available, meaningful prognostic biomarkers for therapeutic monitoring are missing. We demonstrate handheld Multispectral Optoacoustic Tomography (MSOT) as a novel non-invasive imaging approach to visualize and quantify muscle wasting in pediatric SMA. While MSOT signals were distributed homogeneously in muscles of healthy volunteers (HVs), SMA patients showed moth-eaten optoacoustic signal patterns. Further signal quantification revealed greatest differences between groups at the isosbestic point for hemoglobin (SWL 800 nm). The SWL 800 nm signal intensities further correlated with clinical phenotype tested by standard motor outcome measures. Therefore, handheld MSOT could enable non-invasive assessment of disease burden in SMA patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Multispectral optoacoustic tomography; Optoacoustics; Photoacoustics; Spinal muscular atrophie

Multispectral optoacoustic tomography for the non-invasive identification of patients with severe anemia in vivo - Ganzleben, Ingo; Klett, Daniel; Hartz, Wiebke; Götzfried, Lisa; Vitali, Francesco; Neurath, Markus; Waldner, Maximilian (Photoacoustics, 2022)
The immediate diagnosis of severe anemia is crucial for patient outcome. However, reliable non-invasive point-of-care diagnostic tools for e.g., ICU monitoring are currently lacking. Using an advanced Multispectral Optoacoustic Tomography (MSOT) research device, we first substantiated a strong positive correlation of MSOT-signal and absolute hemoglobin concentration ex vivo in blood samples. In a clinical exploratory proof-of-concept study, we then evaluated 19 patients with different severities of anemia and controls by non-invasive in vivo measurement of hemoglobin in the radial artery. Our approach proved excellent in identifying patients with severe anemia triggering RBC transfusion based on a strong positive correlation of MSOT-signal intensity and hemoglobin concentration for 700 nm single wavelength and HbR unmixed MSOT-parameter analysis. In conclusion, our study lays the foundation to further develop MSOT-based real-time quantitative perfusion analyses in follow-up preclinical and clinical imaging studies and as a promising diagnostic tool to improve patient care in the future. DRKS00021442
CRIS-Team Scopus Importer:2022-10-28
Keywords: Anemia; Clinical study; Hemoglobin; Optoacoustic imaging

Multispectral Optoacoustic Tomography in Crohn's Disease: Noninvasive Imaging of Disease Activity - Waldner, Maximilian; Knieling, Ferdinand; Egger, Cornelia; Morscher, Stefan; Claussen, Jing; Vetter, Marcel; Kielisch, Christian; Fischer, Sören; Pfeifer, Lukas; Hagel, Alexander; Görtz, Rüdiger; Wildner, Dane; et al. (Gastroenterology, 2016)
EVALuna2:2071

Multispectral optoacoustic tomography of the human intestine – temporal precision and the influence of postprandial gastrointestinal blood flow - Paulus, Lars-Philip; Wagner, Alexandra; Buehler, Adrian; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Günther, Josefine; Rother, Ulrich; Lang, Werner; Hörning, André; et al. (Photoacoustics, 2023)
Multispectral optoacoustic tomography (MSOT) holds great promise as a non-invasive diagnostic tool for inflammatory bowel diseases. Yet, reliability and the impact of physiological processes during fasting and after food intake on optoacoustic signals have not been studied. In the present investigator initiated trial (NCT05160077) the intestines of ten healthy subjects were examined by MSOT at eight timepoints on two days, one fasting and one after food intake. While within-timepoint and within-day reproducibility were good for single wavelength 800 nm and total hemoglobin (ICC 0.722–0.956), between-day reproducibility was inferior (ICC −0.137 to 0.438). However, temporal variability was smaller than variation between individuals (coefficients of variation 8.9%−33.7% vs. 17.0%−48.5%). After food intake and consecutive increased intestinal circulation, indicated by reduced resistance index of simultaneous Doppler ultrasound, optoacoustic signals did not alter significantly. In summary, this study demonstrates high reliability and temporal stability of MSOT for imaging the human intestine during fasting and after food intake.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Gut; Inflammatory bowel disease; Intestinal blood flow; Multispectral optoacoustic imaging; Optoacoustic; Photoacoustic; Postprandial; Reliability; Reproducibility

Muscle‐derived cytokines reduce growth, viability and migratory activity of pancreatic cancer cells - Schwappacher, Raphaela; Dieterich, Walburga; Reljic, Dejan; Pilarsky, Christian; Mukhopadhyay, Debabrata; Chang, David K.; Biankin, Andrew; Siebler, Jürgen; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (Cancers, 2021)
The evidence that regular physical exercise reduces the risk of developing cancer is well described. However, the interaction between physical exercise and cancer is not fully clarified yet. Several myokines released by skeletal muscle appear to have a direct anti‐tumour function. There are few data on myokine secretion after exercise in patients with advanced tumours. Pancreatic cancer (PC) is a very aggressive and usually fatal cancer. To investigate the effects of exercise in PC, the blood of advanced‐stage PC patients was analysed after 12 weeks of resistance training using whole‐body electromyostimulation. After the 12‐week training period, the patient serum inhibited the proliferation and the motility of PC cells and enhanced PC cell apoptosis. The impact of exercise training was also investigated in an exercise‐mimicking in vitro model using electric pulse stimulation of human myotubes and revealed similar anti‐tumour effects on PC cells, clearly indicating direct cancer‐protective properties of activated skeletal muscle. Protein and gene expression analyses in plasma from exercise‐trained patients and in myotube cultures after in vitro exercise showed that interleukin 10 (IL10), C‐X‐C motif ligand 1 (CXCL1) and C‐C motif chemokine ligand 4 (CCL4) are myokines released from activated skeletal muscle. In accordance with the effects of serum from exercise‐trained patients, the supplementation with recombinant IL10, CXCL1 and CCL4 impaired growth and migration of PC cells. Treatment of PC cells with these myokines upregulated caspase 3/7 expression and the cleavage of poly(ADP‐ribose) polymerase, leading to enhanced PC cell death. The identification of myokines with anti‐tumour properties in advanced‐stage PC patients after exercise opens a new perspective in supportive therapy with sports and exercise for cancer patients.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Apoptosis; Electric pulse stimulation; Exercise; Migration; Myokine; Pancreatic cancer; Physical activity; Proliferation; Whole‐body electromyostimulation

Nanoparticles in Gastrooncology - Jefremow, André; Neurath, Markus (Visceral Medicine, 2020)
Background: Gastrointestinal malignancies have the greatest incidence and cancer-associated death rates worldwide. Routine therapeutic modalities include surgery, chemotherapy and radiation but they often fail to reach the goal of cancer-free survival. Summary: In the light of this urgent medical need for the treatment of GI tumors, nanotech-nology-based approaches, i.e. nanomedicine, promise new therapeutic options. Using nanoparticles instead of classically designed drugs, targeting anticancer agents directly to the tumor site may revolutionize both diagnostic and therapeutic tools thereby facilitating the identification and elimination of malignant cells. Importantly, diagnostic insight and therapeutic effects can be achieved simultaneously through the same nanoparticle. Additionally, a nanoparticle may be loaded with more than one agent, thereby further increasing the value and power of the nanotechnology approach in oncologic therapeutic concepts. Although most insight into mechanisms of nanomedicine has been gained from in vitro and preclinical in vivo models, few clinical trials have been conducted, and nanomedicine-based concepts are already part of standard treatment algorithms. However, despite substantial progress it remains a challenge to design nanoparticles that feature all desirable characteristics at the same time. Key Messages: This review seeks to provide substantial insight into the current status of nanomedicine-based approaches employed for diagnostic and/or therapeutic purposes in the field of gastrointestinal cancers by highlighting achievements and pointing out unresolved issues that need to be further addressed by future research attempts.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Gastrointestinal tumors; Gastrooncology; Nanomedicine; Nanoparticles

Natural NADH and FAD Autofluorescence as Label-Free Biomarkers for Discriminating Subtypes and Functional States of Immune Cells - Lemire, Sarah; Thoma, Oana-Maria; Kreiß, Lucas; Völkl, Simon; Friedrich, Oliver; Neurath, Markus; Schürmann, Sebastian; Waldner, Maximilian (International Journal of Molecular Sciences, 2022)
Immune cell activity is a major factor for disease progression in inflammatory bowel diseases (IBD). Classifying the type and functional state of immune cells is therefore crucial in clinical diagnostics of IBD. Label-free optical technologies exploiting NADH and FAD autofluorescence, such as multiphoton microscopy, have been used to describe tissue morphology in healthy and inflamed colon samples. Nevertheless, a strategy for the identification of single immune cell subtypes within the tissue is yet to be developed. This work aims to initiate an understanding of autofluorescence changes depending on immune cell type and activation state. For this, NADH and FAD autofluorescence signals of different murine immune cell subtypes under native conditions, as well as upon in vitro stimulation and cell death, have been evaluated. Autofluorescence was assessed using flow cytometry and multiphoton microscopy. Our results reveal significantly increased NADH and FAD signals in innate immune cells compared to adaptive immune cells. This allowed identification of relative amounts of neutrophils and CD4+ T cells in mixed cell suspensions, by using NADH signals as a differentiation marker. Furthermore, in vitro stimulation significantly increased NADH and FAD autofluorescence in adaptive immune cells and macrophages. Cell death induced a significant drop in NADH autofluorescence, while FAD signals were hardly affected. Taken together, these results demonstrate the value of autofluorescence as a tool to characterize immune cells in different functional states, paving the way to the label-free clinical classification of IBD in the future.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Cell autofluorescence; FAD; Flow cytometry; Immune cells; Inflammatory bowel diseases; Multiphoton microscopy; NADH

Neutrophil Extracellular Traps Initiate Gallstone Formation - Munoz, Luis Enrique; Boeltz, Sebastian; Bilyy, Rostyslav; Schauer, Christine; Mahajan, Aparna; Widulin, Navena; Grüneboom, Anika; Herrmann, Irmgard; Boada, Edgyda; Rauh, Manfred; Krenn, Veit; Biermann, Mona H.C.; et al. (Immunity, 2019)
The presence of gallstones (cholelithiasis) is a highly prevalent and severe disease and one of the leading causes of hospital admissions worldwide. Due to its substantial health impact, we investigated the biological mechanisms that lead to the formation and growth of gallstones. We show that gallstone assembly essentially requires neutrophil extracellular traps (NETs). We found consistent evidence for the presence of NETs in human and murine gallstones and describe an immune-mediated process requiring activation of the innate immune system for the formation and growth of gallstones. Targeting NET formation via inhibition of peptidyl arginine deiminase type 4 or abrogation of reactive oxygen species (ROS) production, as well as damping of neutrophils by metoprolol, effectively inhibit gallstone formation in vivo. Our results show that after the physicochemical process of crystal formation, NETs foster their assembly into larger aggregates and finally gallstones. These insights provide a feasible therapeutic concept to prevent cholelithiasis in patients at risk.
CRIS-Team Scopus Importer:2019-09-17
Keywords: calcium carbonate crystals; cholesterol crystals; gallstone growth; gallstones; lisosomal leakage; lithogenic diet; neutrophil extracellular traps; neutrophils; NOX2; PADi4

Neutrophils prevent rectal bleeding in ulcerative colitis by peptidyl-arginine deiminase-4-dependent immunothrombosis - Leppkes, Moritz; Lindemann, Aylin; Goesswein, Stefanie; Paulus, Susanne; Roth, Dominik; Hartung, Anne; Liebing, Eva; Zundler, Sebastian; Gonzalez-Acera, Miguel; Patankar, Jay; Mascia, Fabrizio; Scheibe, Kristina; et al. (Gut, 2021)
Objective Bleeding ulcers and erosions are hallmarks of active ulcerative colitis (UC). However, the mechanisms controlling bleeding and mucosal haemostasis remain elusive. Design We used high-resolution endoscopy and colon tissue samples of active UC (n = 36) as well as experimental models of physical and chemical mucosal damage in mice deficient for peptidyl-arginine deiminase-4 (PAD4), gnotobiotic mice and controls. We employed endoscopy, histochemistry, live-cell microscopy and flow cytometry to study eroded mucosal surfaces during mucosal haemostasis. Results Erosions and ulcerations in UC were covered by fresh blood, haematin or fibrin visible by endoscopy. Fibrin layers rather than fresh blood or haematin on erosions were inversely correlated with rectal bleeding in UC. Fibrin layers contained ample amounts of neutrophils coaggregated with neutrophil extracellular traps (NETs) with detectable activity of PAD. Transcriptome analyses showed significantly elevated PAD4 expression in active UC. In experimentally inflicted wounds, we found that neutrophils underwent NET formation in a PAD4-dependent manner hours after formation of primary blood clots, and remodelled clots to immunothrombi containing citrullinated histones, even in the absence of microbiota. PAD4-deficient mice experienced an exacerbated course of dextrane sodium sulfate-induced colitis with markedly increased rectal bleeding (96 % vs 10 %) as compared with controls. PAD4-deficient mice failed to remodel blood clots on mucosal wounds eliciting impaired healing. Thus, NET-associated immunothrombi are protective in acute colitis, while insufficient immunothrombosis is associated with rectal bleeding. Conclusion Our findings uncover that neutrophils induce secondary immunothrombosis by PAD4-dependent mechanisms. Insufficient immunothrombosis may favour rectal bleeding in UC.
CRIS-Team WoS Importer:2021-12-17

Neutrophils prevent rectal bleeding in Ulcerative Colitis by peptidyl-arginine deiminase-4-dependent immunothrombosis - Leppkes, Moritz; Lindemann, Aylin; Goesswein, S.; Paulus, S.; Roth, Dominik; Hartung, A.; Liebing, Eva; Zundler, Sebastian; Gonzalez Acera, Miguel; Patankar, Jay; Mascia, Fabrizio; Scheibe, Kristina; et al. (JOURNAL OF CROHNS & COLITIS, 2022)
CRIS-Team WoS Importer:2022-05-13

New agents for immunosuppression - Jefremow, André; Neurath, Markus (Best Practice & Research in Clinical Gastroenterology, 2021)
The human abdomen harbors organs that the host's immune system can attack easily. This immunological storm front leads to diseases like Crohn's Disease, Ulcerative Colitis or Autoimmune Hepatitis. Serious symptoms like pain, diarrhea, fatigue, or malnutrition accompany these diseases. Moreover, many patients have an increased risk for developing special kind of malignancies and some autoimmune disease can show a high mortality. The key to treat them consists of a deep understanding of their pathophysiology. In vitro and especially in vivo basic research laid the foundation for our increasing knowledge about it during the past years. This enabled the development of new therapeutic approaches that interact directly with cytokines or immune cells instead of building the treatment on a total immunosuppression. Different kind of antibodies, kinase inhibitors, and regulatory T cells build the base for these approaches. This review shows new therapeutical approaches in gastrointestinal autoimmune diseases in context to their pathophysiological basis.
CRIS-Team Scopus Importer:2021-09-10
Keywords: AIH; Autoimmune diseases; Autoimmune hepatitis; CD; Coeliac disease; Crohn's disease; Immunosuppressive therapy; PBC; PSC; UC; Ulcerative colitis

New targets for mucosal healing and therapy in inflammatory bowel diseases - Neurath, Markus (Mucosal Immunology, 2014)
Healing of the inflamed mucosa (mucosal healing) is an emerging new goal for therapy and predicts clinical remission and resection-free survival in inflammatory bowel diseases (IBDs). The era of antitumor necrosis factor (TNF) antibody therapy was a remarkable progress in IBD therapy and anti-TNF agents led to mucosal healing in a subgroup of IBD patients; however, many patients do not respond to anti-TNF treatment highlighting the relevance of finding new targets for therapy of IBD. In particular, current studies are addressing the role of other anticytokine agents including antibodies against interleukin (IL)-6R, IL-13, and IL-12/IL-23 as well as new anti-inflammatory concepts (regulatory T cell therapy, Smad7 antisense, Jak inhibition, Toll-like receptor 9 stimulation, worm eggs). In addition, blockade of T-cell homing via the integrins ?4?7 and the addressin mucosal vascular addressin cell adhesion molecule 1 (MAdCAM-1) emerges as a promising new approach for IBD therapy. Here, new approaches for achieving mucosal healing are discussed as well as their implications for future therapy of IBD.
EVALuna2:1787

NLRP3 Inhibition Leads to Impaired Mucosal Fibroblast Function in Patients with Inflammatory Bowel Diseases - Weber, Simone; Sitte, Selina; Vögele, Anna-Lena; Sologub, Ludmilla; Wilfer, Angelika; Rath, Timo; Nägel, Andreas; Zundler, Sebastian; Franchi, Luigi; Opipari, Anthony W.; Sonnewald, Sophia; Reid, Stephen; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: Inflammatory bowel diseases (IBD) are characterized by mucosal inflammation and sequential fibrosis formation, but the exact role of the hyperactive NLRP3 inflammasome in these processes is unclear. Thus, we studied the expression and function of the NLRP3 inflammasome in the context of inflammation and fibrosis in IBD. Methods: We analysed intestinal NLRP3 expression in mucosal immune cells and fibroblasts from IBD patients and NLRP3-associated gene expression via single-cell RNA sequencing and microarray analyses. Furthermore, cytokine secretion of NLRP3 inhibitor treated blood and mucosal cells, as well as proliferation, collagen production, and cell death of NLRP3 inhibitor treated intestinal fibroblasts from IBD patients were studied. Results: We found increased NLRP3 expression in the inflamed mucosa of IBD patients and NLRP3 inhibition led to reduced IL-1β and IL-18 production in blood cells and diminished the bioactive form of mucosal IL-1β. Single cell analysis identified overlapping expression patterns of NLRP3 and IL-1β in classically activated intestinal macrophages and we also detected NLRP3 expression in CD163+ macrophages. In addition, NLRP3 expression was also found in intestinal fibroblasts from IBD patients. Inhibition of NLRP3 led to reduced proliferation of intestinal fibroblasts, which was associated with a marked decrease in production of collagen type I and type VI in IBD patients. Moreover, NLRP3 inhibition in intestinal fibroblasts induced autophagy, a cellular process involved in collagen degradation. Conclusions: In the presented study, we demonstrate that inhibiting NLRP3 might pave the way for novel therapeutic approaches in IBD, especially to prevent the severe complication of intestinal fibrosis formation.
CRIS-Team Scopus Importer:2023-11-17
Keywords: fibroblasts; fibrosis; IL-18; IL-1β; Inflammatory bowel diseases; mucosal immune system; NLRP3 inflammasome; small molecule inhibitor

Non-classical monocyte homing to the gut via α4β7 integrin mediates macrophage-dependent intestinal wound healing - Schleier, Lena; Wiendl, Maximilian; Heidbreder, Karin; Binder, Marie Theres; Atreya, Raja; Rath, Timo; Becker, Elisabeth; Schulz-Kuhnt, Anja; Stahl, Annette; Schulze, Lisa; Ullrich, Karen; Merz, Simon F.; et al. (Gut, 2019)
Objective: To study the role of α4β7 integrin for gut homing of monocytes and to explore the biological consequences of therapeutic α4β7 inhibition with regard to intestinal wound healing. Design: We studied the expression of homing markers on monocyte subsets in the peripheral blood and on macrophage subsets in the gut of patients with IBD and controls with flow cytometry and immunohistochemistry. Integrin function was addressed with dynamic adhesion assays and in vivo gut homing assays. In vivo wound healing was studied in mice deficient for or depleted of α4β7 integrin. Results: Classical and non-classical monocytes were clearly dichotomous regarding homing marker expression including relevant expression of α4β7 integrin on human and mouse non-classical monocytes but not on classical monocytes. Monocyte-expressed α4β7 integrin was functionally important for dynamic adhesion to mucosal vascular addressin cell adhesion molecule 1 and in vivo gut homing. Impaired α4β7-dependent gut homing was associated with reduced (effect size about 20%) and delayed wound healing and suppressed perilesional presence of wound healing macrophages. Non-classical monocytes in the peripheral blood were increased in patients with IBD under clinical treatment with vedolizumab. Conclusion: In addition to reported effects on lymphocytes, anti-α4β7 therapy in IBD also targets non-classical monocytes. Impaired gut homing of such monocytes might lead to a reduction of wound healing macrophages and could potentially explain increased rates of postoperative complications in vedolizumab-treated patients, which have been observed in some studies.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Crohn's disease; gut immunology; inflammatory bowel disease; surgery for IBD; ulcerative colitis

Non-invasive assessment of intestinal inflammatory activity in Ulcerative Colitis by Multispectral Optoacoustic Tomography (MSOT) - Klett, Daniel; Jesper, D.; Vitali, Francesco; Federle, Anna; Atreya, Raja; Strobel, Deike; Leppkes, Moritz; Neufert, Clemens; Rath, Timo; Neurath, Markus; Waldner, Maximilian (JOURNAL OF CROHNS & COLITIS, 2022)
CRIS-Team WoS Importer:2022-05-13

NON-INVASIVE IN VIVO METABOLIC PROFILING OF INFLAMMATION IN JOINTS AND ENTHESES BY OPTOACOUSTIC IMAGING - Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Bayat, Sara; Heidemann, Robert; Steiger, F.; Krönke, Gerhard; Bohr, D.; Ramming, Andreas; Hartmann, F.; Klett, Daniel; Federle, Anna; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Non-invasive metabolic profiling of inflammation in joints and entheses by multispectral optoacoustic tomography - Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Bayat, Sara; Heidemann, Robert; Steiger, Florian; Krönke, Gerhard; Bohr, Daniela; Ramming, Andreas; Hartmann, Fabian; Klett, Daniel; Federle, Anna; et al. (Rheumatology, 2022)
Objective To explore the metabolic characteristics of arthritis and enthesitis using multispectral opto-acoustic tomography (MSOT), a technology using near-infrared multispectral laser to stimulate tissues and detect the emitted acoustic energy, enabling non-invasive quantification of tissue components in vivo based on differential absorbance at multiple wavelengths. Methods We performed a cross-sectional study in patients with RA or PsA and healthy controls (HCs). Participants underwent clinical, ultrasonographic and MSOT examination of MCP and wrist joints as well as the entheses of the common extensor tendon at the lateral humeral epicondyles and of the patellar, quadriceps and Achilles tendon. MSOT-measured haemoglobin (Hb), oxygen saturation, collagen and lipid levels were quantified and scaled mean differences between affected and unaffected joints and entheses were calculated as defined by clinical examination or ultrasonography using linear mixed effects models. Results We obtained 1535 MSOT and 982 ultrasonography scans from 87 participants (34 PsA, 17 RA, 36 HCs). Entheseal tenderness was not associated with significant metabolic changes, whereas enthesitis-related sonographic changes were associated with increased total Hb, oxygen saturation and collagen content. In contrast, the presence of arthritis-related clinical and sonographic findings showed increased Hb levels, reduced oxygen saturation and reduced collagen content. Synovial hypertrophy was associated with increased lipid content in the joints. Conclusion MSOT allows determination of distinct metabolic differences between arthritis and enthesitis in a non-invasive setting in humans in vivo.
CRIS-Team WoS Importer:2022-07-22

Novel imaging modalities for immune cell monitoring in the intestine - Atreya, Raja; Neurath, Markus (Current Opinion in Gastroenterology, 2014)
The introduction of novel molecular imaging modalities that can not only define disease states on the basis of structural changes and morphology, but also allow in-vivo visualization and characterization of molecular and biochemical alterations on a cellular level add a new dimension to our current diagnostic possibilities. The advents of innovative endoscopic devices coupled with the introduction of novel targeting ligands contribute to the recent advances made in the field of molecular imaging. The purpose of this review is to present and discuss the concepts and the potential of novel endoscopic imaging modalities for immune cell monitoring in the intestine.Recent progress concerning molecular imaging studies in animals and human patients implicates that this approach can be used to improve detection of mucosal lesions in wide-field imaging and for in-vivo characterization of the mucosa with the ultimate goal of assessing the likelihood of response to targeted therapy with biological agents. In particular, molecular endomicroscopy for assessment of mucosal immune responses ('immunoendoscopy') emerges as a novel approach for optimized endoscopic diagnosis and individualized therapy.Molecular imaging modalities in the intestine have the immediate potential to have an impact on current clinical practice and could therefore open new frontiers for clinical endoscopy and give hope for improved diagnosis and targeted therapies.
EVALuna2:1881

Novel Insights into the Mechanisms of Gut Homing and Antiadhesion Therapies in Inflammatory Bowel Diseases - Zundler, Sebastian; Neurath, Markus (Inflammatory Bowel Diseases, 2017)
Therapeutic compounds interfering with T cell trafficking are a new column of inflammatory bowel disease (IBD) treatment. Currently, the anti-α4β7 integrin antibody vedolizumab is successfully used in the clinic and further drugs are likely to follow. Despite these clinical advances, the precise mechanistic background of their action is only gradually elucidated and still a matter of intensive research. Only recently, advances made with the help of new in vivo models and human studies have contributed to shape our concept of T cell trafficking in IBD by deciphering some important and so far unanswered questions. At the same time, basic and clinical data have generated new issues to be addressed on the way toward a clear perception of trafficking mechanisms and toward elucidation of the action of compounds interfering with this process. In this review, we will give a comprehensive outline of all components of T cell trafficking in regard to IBD before discussing the current knowledge concerning targeted interference with integrins in this complex network. Moreover, we will summarize remaining ambiguity and give an outlook on potential future targets.
EVALuna2:33819

Novel Small Molecules in IBD: Current State and Future Perspectives - Jefremow, André; Neurath, Markus (Cells, 2023)
Biologicals have dominated the therapeutic scenery in inflammatory bowel diseases (IBDs), namely ulcerative colitis (UC) and Crohn’s disease (CD), for the past 20 years. The development of tofacitinib was the starting point for an era of small molecules after the era of biologicals. These new agents may challenge the use of biological agents in the future. They share properties that appeal to both patients and physicians. Low production costs, a lack of immunogenicity, and ease of use are only some of their benefits. On the other hand, patients and their physicians must manage the potential side effects of small molecules such as JAK inhibitors or S1P1R modulators. Here, we present agents that have already entered the clinical routine and those that are still being investigated in clinical trials.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Crohn’s; inflammatory bowel diseases; JAK; small molecular drugs; small molecules; ulcerative colitis

Novel T cell/organoid culture system allows ex vivo modeling of intestinal graft-versus-host disease - Matthe, Diana; Dinkel, Martin; Schmid, Benjamin; Vogler, Tina; Neurath, Markus; Poeck, Hendrik; Neufert, Clemens; Büttner-Herold, Maike; Hildner, Kai (Frontiers in Immunology, 2023)
Acute graft-versus-host disease (GvHD) remains the biggest clinical challenge and prognosis-determining complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Donor T cells are acceptedly key mediators of alloreactivity against host tissues and here especially the gut. In support of previous studies, we found that the intestinal intra-epithelial lymphocyte (IEL) compartment was dynamically regulated in the course of MHC class I full mismatch allo-HSCT. However, while intestinal epithelial cell (IEC) damage endangers the integrity of the intestinal barrier and is a core signature of intestinal GvHD, the question whether and to what degree IELs are contributing to IEC dysregulation is poorly understood. To study lymphoepithelial interaction, we employed a novel ex vivo T cell/organoid co-culture model system. Here, allogeneic intra-epithelial T cells were superior in inducing IEC death compared to syngeneic IEL and allogeneic non-IEL T cells. The ability to induce IEC death was predominately confined to TCRβ+ T cells and was executed in a largely IFNγ-dependent manner. Alloreactivity required a diverse T cell receptor (TCR) repertoire since IELs genetically modified to express a TCR restricted to a single, non-endogenous antigen failed to mediate IEC pathology. Interestingly, minor histocompatibility antigen (miHA) mismatch was sufficient to elicit IEL-driven IEC damage. Finally, advanced live cell imaging analyses uncovered that alloreactive IELs patrolled smaller areas within intestinal organoids compared to syngeneic controls, indicating their unique migratory properties within allogeneic IECs. Together, we provide here experimental evidence for the utility of a co-culture system to model the cellular and molecular characteristics of the crosstalk between IELs and IEC in an allogeneic setting ex vivo. In the light of the emerging concept of dysregulated immune-epithelial homeostasis as a core aspect of intestinal GvHD, this approach represents a novel experimental system to e.g. screen therapeutic strategies for their potential to normalize T cell/IEC- interaction. Hence, analyses in pre-clinical in vivo allo-HSCT model systems may be restricted to hereby positively selected, promising approaches.
CRIS-Team Scopus Importer:2023-09-22
Keywords: allogeneic hematopoietic stem cell transplantation; alloreactive T cell; epithelial cell death; ex vivo model; graft-versus-host disease; GvHD; intestinal organoids; intraepithelial lymphocytes

Novel therapeutic approaches in inflammatory bowel diseases - Atreya, Raja; Neurath, Markus (Deutsche Medizinische Wochenschrift, 2016)
Increasing knowledge regarding the immunopathogenesis of IBD has led to the development or approval of novel therapeutic agents for the treatment of Crohn's disease or ulcerative colitis. The new substances for example include antibodies against IL-12 / 23, anti-adhesion molecules and antisense oligonucleotides. The increase of therapeutic options will lead to a change of currently used therapeutic algorithms. Biomarkers to ensure a more individualized therapeutic approach are urgently needed to improve an efficient therapy of IBD patients.
EVALuna2:2198

Nr4a1-dependent non-classical monocytes are important for macrophage-mediated wound healing in the large intestine - Heidbreder, Karin; Sommer, Katrin; Wiendl, Maximilian; Müller, Tanja; Atreya, Imke; Hildner, Kai; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2023)
Introduction: Macrophages play an important role in intestinal wound healing. However, the trajectories from circulating monocytes to gut macrophages are incompletely understood. Methods: Taking advantage of mice depleted for non-classical monocytes due to deficiency for the transcription factor Nr4a1, we addressed the relevance of non-classical monocytes for large intestinal wound healing using flow cytometry, in vivo wound healing assays and immunofluorescence. Results: We show that wound healing in Nr4a1-deficient mice is substantially delayed and associated with reduced peri-lesional presence of macrophages with a wound healing phenotype. Discussion: Our data suggest that non-classical monocytes are biased towards wound healing macrophages. These insights might help to understand, how targeting monocyte recruitment to the intestine can be used to modulate intestinal macrophage functions.
CRIS-Team Scopus Importer:2023-02-10
Keywords: gut homing; intestinal wound healing; macrophages; monocytes; Nr4a1 (Nur77)

Nuclear factor of activated T cells - a transcription factor family as critical regulator in lung and colon cancer - Daniel, Carolin; Gerlach, Katharina; Vaeth, Martin; Neurath, Markus; Weigmann, Benno (International Journal of Cancer, 2014)
Nuclear factor of activated T cells (NFAT) was first identified as a transcription factor which is activated upon T cell stimulation. Subsequent studies uncovered that a whole family of individual NFAT proteins exists with pleiotropic functions not only in immune but also in nonimmune cells. However, dysregulation of NFAT thereby favors malignant growth and cancer. Summarizing the recent advances in understanding how individual NFAT factors regulate the immune system, this review gives new insights into the critical role of NFAT in cancer development with special focus on inflammation-associated colorectal cancer.
EVALuna2:1902

Nutritional Status and Body Composition of Patients with Glioblastomas - Reljic, Dejan; Herrmann, Joachim; Neurath, Markus; Zopf, Yurdagül (INTERNIST, 2019)
CRIS-Team WoS Importer:2019-05-17

Nutrition and sports in cancer - What should we consider? - Zopf, Yurdagül; Herrmann, Hans Joachim; Neurath, Markus; Reljic, Dejan (gynäkologische praxis, 2019)
In cancer, various inflammatory and disease-related processes typically lead to muscle mass loss. Muscle wasting is associated with a reduction in physical performance and quality of life and may affect the tolerability of anticancer therapy. In order to compensate the increased protein turnover and to counteract the progression of muscle breakdown or to reactivate muscle building, respectively, a high-protein diet is recommended. Physical exercise is another crucial component in the multimodal treatment of cancer cachexia with the aim of improving muscle mass, physical performance, and metabolism. The additional anabolic stimulus provided by physical exercise, especially strength training, can effectively support the maintenance of muscle mass and functional capacity during oncologic therapy. Time-efficient exercise interventions are recommended because they can be better integrated into the overall oncologic therapy regimen and thus increase patient compliance. In sum, current data suggest that the combination of an individualized, protein-rich nutritional therapy and targeted physical exercise can have synergistic effects on stabilizing or improving nutritional and performance status. This can positively affect the quality of life of patients.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Cancer cachexia; Exercise; Inflammation; Muscle wasting; Nutrition; Protein intake; Supportive cancer therapy

Oligonucleotides-A Novel Promising Therapeutic Option for IBD - Scarozza, Patrizio; Schmitt, Heike; Monteleone, Giovanni; Neurath, Markus; Atreya, Raja (Frontiers in Pharmacology, 2019)
Inflammatory Bowel Diseases (IBD), whose denomination comprehends Crohn's Disease (CD) and Ulcerative Colitis (UC), are intestinal chronic diseases that often require lifelong medical therapy. In the last two decades monoclonal antibodies against the cytokine TNF have become integral parts in the treatment of IBD patients, however there are unwanted side-effects and one third of patients show primary non-response while another subgroup loses response over time. Finding novel drugs which could act as therapies against precise pro-inflammatory molecular targets to avoid unwanted systemic side effects and additionally the process of immunization, represents an important aim for subsequent therapeutic approaches. Oligonucleotide based therapies represent a promising novel concept for the treatment of IBD. The molecular action of oligonucleotides ranges from inhibition of the translational process of mRNA transcripts of pro-inflammatory molecules, to mimicking bacterial DNA which can activate cellular targets for immunomodulation. Alicaforsen, selectively targets ICAM-1 mRNA. ICAM-1 is an adhesion molecule which is upregulated on endothelial cells during IBD, thereby mediating the adhesion and migration of leucocytes from blood to sites of active inflammation. In CD parenteral application of alicaforsen did not show therapeutic efficacy in phase II trials, but it demonstrated an improved efficacy as a topical enema in distal UC. Topical application of alicaforsen might represent a therapeutic perspective for refractory pouchitis as well. SMAD7 is a protein that inhibits the signaling of TGF beta, which is the mainstay of a regulatory counterpart in cellular immune responses. An antisense oligonucleotide against SMAD7 mRNA (mongersen) demonstrated pre-clinical and phase II efficacy in CD, but a phase III clinical trial was stopped due to lack of efficacy. Cobitolimod is a single strand oligonucleotide, which mimics bacterial DNA as its CpG dinucleotide sequences can be recognized by the Toll-like receptor 9 on different immune cells thereby causing induction of different cytokines, for example IL10 and IFN alpha. Topical application of cobitolimod was studied in UC patients. We will also discuss two other novel oligonucleotides which act on the GATA3 transcription factor (SB012) and on carbohydrate sulfotransferase 15 (STNM01), which could both represent novel promising therapeutic options for the treatment of UC.
CRIS-Team WoS Importer:2019-05-09

Organoids in gastrointestinal diseases: from experimental models to clinical translation - Günther, Claudia; Winner, Beate; Neurath, Markus; Stappenbeck, Thaddeus S. (Gut, 2022)
We are entering an era of medicine where increasingly sophisticated data will be obtained from patients to determine proper diagnosis, predict outcomes and direct therapies. We predict that the most valuable data will be produced by systems that are highly dynamic in both time and space. Three-dimensional (3D) organoids are poised to be such a highly valuable system for a variety of gastrointestinal (GI) diseases. In the lab, organoids have emerged as powerful systems to model molecular and cellular processes orchestrating natural and pathophysiological human tissue formation in remarkable detail. Preclinical studies have impressively demonstrated that these organs-in-a-dish can be used to model immunological, neoplastic, metabolic or infectious GI disorders by taking advantage of patient-derived material. Technological breakthroughs now allow to study cellular communication and molecular mechanisms of interorgan cross-talk in health and disease including communication along for example, the gut-brain axis or gut-liver axis. Despite considerable success in culturing classical 3D organoids from various parts of the GI tract, some challenges remain to develop these systems to best help patients. Novel platforms such as organ-on-a-chip, engineered biomimetic systems including engineered organoids, micromanufacturing, bioprinting and enhanced rigour and reproducibility will open improved avenues for tissue engineering, as well as regenerative and personalised medicine. This review will highlight some of the established methods and also some exciting novel perspectives on organoids in the fields of gastroenterology. At present, this field is poised to move forward and impact many currently intractable GI diseases in the form of novel diagnostics and therapeutics.
CRIS-Team WoS Importer:2022-06-17
Keywords: gastrointestinal pathology; gastrointestinal physiology; intestinal stem cell; stem cells

Outcome analysis of liver stiffness by ARFI (acoustic radiation force impulse) elastometry in patients with chronic viral hepatitis B and C - Görtz, Rüdiger; Sturm, Jörg; Zopf, Steffen; Wildner, D.; Neurath, Markus; Strobel, Deike (Clinical Radiology, 2014)
To evaluate the association between liver stiffness measured by acoustic radiation force impulse (ARFI) elastometry and the outcome of antiviral treatment in patients with chronic viral hepatitis B and C.Thirty-eight patients with chronic viral hepatitis B (n = 16) or hepatitis C (n = 22) underwent liver biopsy and ARFI elastometry of the right hepatic lobe. A follow-up assessment using ARFI was performed a mean of 2.3 years after the baseline evaluation. The patients with favourable outcome were classified in group S and those receiving no treatment, showing no response to treatment, or experiencing a relapse were classified in group N.The 38 patients had an initial mean ARFI value of 1.56 ± 0.62 m/s as compared with 1.54 ± 0.64 m/s in the follow-up evaluation. Group S showed a significant decline in ARFI values (1.55 ± 0.60 m/s versus 1.34 ± 0.47 m/s; p < 0.05) and included 16 (64%) patients with lower shear wave velocities at follow-up. In group N, liver stiffness values showed a slight but not significant increase (1.57 ± 0.70 m/s versus 1.93 ± 0.77 m/s).Changes in liver stiffness during antiviral therapy can be assessed by ARFI reflecting response or no response. ARFI elastometry is an additional, useful tool for the follow-up assessment of treatment outcome in patients with chronic viral hepatitis B or C infection.
EVALuna2:1862

Outcome and complications of endoscopic balloon dilatations in various types of ileocaecal and colonic stenosis in patients with Crohn's disease - Hagel, Alexander; Hahn, Anna; Dauth, Wolfgang; Matzel, Klaus; Konturek, Peter C.; Neurath, Markus; Raithel, Martin (Surgical Endoscopy, 2014)
We examined the outcome and the complications of endoscopic balloon dilatation (EBD) of ileocaecal and colonic strictures due to Crohn's disease.We examined 237 dilatation procedures in 77 patients with symptomatic ileocaecal and colonic stenosis regarding outcome, individual perforation risk, the need for further interventions, and other complications within a 10 years observation period.In 50 of 77 patients (64.9%), endoscopic dilatation procedures were successful within a median follow-up period of 24 months (25th and 75th percentile 10-38.5 months). Thirty five patients (45.5%) were successfully dilated with only one endoscopic procedure, while the remaining patients required two or more EBDs. Albeit the EBD, 27 patients of the whole cohort (35.1%) underwent surgical repair of the stenosis in due course. Overall complication rate was 7.6%, with postdilatation bleeding in 1.7% and abdominal pain longer than 24 h in 4.2%. Perforation occurred in 4 of 77 patients (5.2%), resulting in a perforation rate of 1.7% per intervention, or, more importantly, for the individual patient in a long-term perforation rate of 5.2% per patient, respectively.Endoscopic balloon dilatation (EBD) is a safe and effective approach to ileocaecal and colonic stenosis in approximately 65% of Crohn's disease patients. Even in case of recurrence, further endoscopic treatments can be undertaken. The perforation rate depending on the number of interventions is low, but for the individual patient a cumulative per patient perforation risk of 5.2% in the long-term should be considered during patient information and decisions for or against surgical interventions.
EVALuna2:1834

Outcome, comorbidity, hospitalization and 30-day mortality after closure of acute perforations and postoperative anastomotic leaks by the over-the-scope clip (OTSC) in an unselected cohort of patients - Raithel, M.; Albrecht, H.; Scheppach, W.; Farnbacher, M.; Haupt, Werner; Hagel, Alexander; Schellerer, Vera; Vitali, Francesco; Neurath, Markus; Schneider, H. T. (Surgical Endoscopy, 2016)
Acute gastrointestinal (GI) wall defects contain a high risk of morbidity and mortality and may be closed endoscopically by a full-thickness over-the-scope clip (OTSC).Unselected consecutive patients presenting with acute non-surgical perforations or postoperative anastomotic leaks or perforations underwent attempted OTSC placement as primary closure method after interdisciplinary consensus in three tertiary referral centres. Their clinical data and intervention characteristics were evaluated in an intention to treat analysis during a 24-month period to assess closure rates, 30-day mortality, hospitalization and comorbidity.In total, 34 patients (16 females, 18 males, 69.5 years) were included with 22 non-surgical perforations and 12 postoperative anastomotic leaks or perforations. Definitive closure of the perforations and leaks was achieved in 26/34 patients (76.5 %). Successful closure of the GI wall defect resulted in a significantly shorter hospital stay (8 days, p = 0.03) and was significantly correlated with comorbidity (r = 0.56, p = 0.005). In the group with OTSC failure, hospitalization was 18 days and 6 of 8 patients (75 %) required immediate surgery. Three deaths occurred in the group with successful OTSC closure due to comorbidity, while one death in the OTSC failure group was related to a refractory perforation. Favourable indications and locations for a successful OTSC procedure were identified as PEG complications, endoscopic or postoperative leaks of stomach, colon or rectum, respectively.In unselected patients, OTSC was effective for closure of acute GI wall defects in more than 75 % of all patients. Clinical success and short hospitalization were best achieved in patients without comorbidity, but closure of the perforation or the anastomotic leak was found to be not the only parameter relevant for patient outcome and mortality.
EVALuna2:2224

Over-the-scope-clipping in colonic perforation caused small-bowel fixation and pneumoperitoneum requiring surgical repair - Albrecht, Heinz; Naegel, Andreas; Hagel, Alexander; Rösler, Wolf; Förtsch, Thomas; Neurath, Markus; Atreya, Raja; Raithel, Martin (Endoscopy, 2014)
EVALuna2:1835

Oxazolone-Induced Colitis as a Model of Th2 Immune Responses in the Intestinal Mucosa - Weigmann, Benno; Neurath, Markus (Methods in Molecular Biology, 2016)
Murine models of intestinal inflammation have been widely used in biomedical research. Similarities in anatomy and physiology between such murine models and patients with inflammatory bowel diseases may allow a better understanding of the pathogenesis of Crohn's disease and ulcerative colitis. Additionally, models of intestinal inflammation may be used for the analysis of potentially new therapeutic agents. One key class of models consists of chemically induced inflammation models. Within this group, colitis induced by the haptenizing agent oxazolone is an important model that results in induction of acute or chronic inflammation of the large bowel. Here, we describe the induction and the analysis of this experimental colitis model.
EVALuna2:2163

p21 Prevents the Exhaustion of CD4+ T Cells Within the Antitumor Immune Response Against Colorectal Cancer - Thoma, Oana-Maria; Naschberger, Elisabeth; Kubánková, Markéta; Larafa, Imen; Kramer, Viktoria; Menchicchi, Bianca; Merkel, Susanne; Britzen-Laurent, Nathalie; Jefremow, André; Grützmann, Robert; Koop, Kristina; Neufert, Clemens; et al. (Gastroenterology, 2024)
Background & Aims: T cells are crucial for the antitumor response against colorectal cancer (CRC). T-cell reactivity to CRC is nevertheless limited by T-cell exhaustion. However, molecular mechanisms regulating T-cell exhaustion are only poorly understood. Methods: We investigated the functional role of cyclin-dependent kinase 1a (Cdkn1a or p21) in cluster of differentiation (CD) 4+ T cells using murine CRC models. Furthermore, we evaluated the expression of p21 in patients with stage I to IV CRC. In vitro coculture models were used to understand the effector function of p21-deficient CD4+ T cells. Results: We observed that the activation of cell cycle regulator p21 is crucial for CD4+ T-cell cytotoxic function and that p21 deficiency in type 1 helper T cells (Th1) leads to increased tumor growth in murine CRC. Similarly, low p21 expression in CD4+ T cells infiltrated into tumors of CRC patients is associated with reduced cancer-related survival. In mouse models of CRC, p21-deficient Th1 cells show signs of exhaustion, where an accumulation of effector/effector memory T cells and CD27/CD28 loss are predominant. Immune reconstitution of tumor-bearing Rag1−/− mice using ex vivo-treated p21-deficient T cells with palbociclib, an inhibitor of cyclin-dependent kinase 4/6, restored cytotoxic function and prevented exhaustion of p21-deficient CD4+ T cells as a possible concept for future immunotherapy of human disease. Conclusions: Our data reveal the importance of p21 in controlling the cell cycle and preventing exhaustion of Th1 cells. Furthermore, we unveil the therapeutic potential of cyclin-dependent kinase inhibitors such as palbociclib to reduce T-cell exhaustion for future treatment of patients with colorectal cancer.
CRIS-Team Scopus Importer:2024-01-19
Keywords: CD4; Colorectal Cancer; p21; Palbociclib

Palliative treatment of colorectal cancer in Germany: cost of care and quality of life - Emmert, Martin; Pohl-Dernick, Katharina; Wein, Axel; Dörje, Frank; Merkel, Susanne; Boxberger, Frank; Männlein, Gudrun; Joost, Robert; Harich, Hans-Detlev; Lamberti, Christof; Neurath, Markus; Hohenberger, Werner; et al. (European Journal of Health Economics, 2012)
<div class="AbstractSection" id="ASec1" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; color: rgb(51, 51, 51);"> <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Introduction <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> To estimate the costs of palliative care for colorectal cancer (CRC) from the perspective of German statutory health insurance and to measure the patients’ quality of life (QoL) for a 2-year time period. <div class="AbstractSection" id="ASec2" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; color: rgb(51, 51, 51);"> <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Methods <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> A prospective observational multicentre study was carried out to estimate the direct costs of care over a 2-year period. Case report forms, medical records, and claims data were all applied to document medical and resource usage data in real-world settings. QoL was measured by using the Short Form-12 Health Survey. <div class="AbstractSection" id="ASec3" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; color: rgb(51, 51, 51);"> <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Results <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> In total 101 patients (mean age 67.09 ± 11.13 years, 68 % male) from 12 different settings were included. The mean costs per patient during the 1st and 2nd years were calculated to be 42,361€ and 32,023€, respectively. Highest mean costs were calculated for the second quarter, which reached an amount of 12,900€ (95 % CI: 11,127€–14,673€). Mean physical summary scores and mean mental summary scores were 41.8 and 49.7, respectively. <div class="AbstractSection" id="ASec4" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; color: rgb(51, 51, 51);"> <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Discussion <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> This is the first study assessing the costs of palliative care and the quality of life of patients with CRC in real-world health-care delivery in Germany. It could be shown that CRC treatment represents an enormous economic burden to the German health-care system. Increased efforts in promoting effective and efficient treatment options, or performance-based medication reimbursement schemes, might be helpful in reducing the costs.
WiSo-Import:2015-03-26:4180
Keywords: Colorectal cancer; Palliative care; Cost of care Health service research; Quality of life; SF-12

Palliative Treatment of Colorectal Cancer with Secondary Metastasis Resection in Germany - Impact of the Multidisciplinary Treatment Approach on Prognosis and Cost: The Northern Bavaria IVOPAK I Project - Wein, Axel; Emmert, Martin; Merkel, Susanne; Harich, Hans-Detlev; Thiemann, Roland; Lamberti, Christof; Göttler, Bernhard; Fries, Stefan; Kiani, Alexander; Schlag, Rudolf; Grüner, Marcus; Steinbild, Simone; et al. (Oncology, 2015)
Purpose The aim of this study was to evaluate the quality of care and interdisciplinary cooperation in the palliative treatment of colorectal cancer (CRC), including the associated costs. Patients and Methods 103 patients were enrolled from 13 institutions to reflect the existing clinical treatment reality and costs of palliative CRC treatment. We present the clinical outcome of the patients and compare the results obtained in the 3 centers with double-figure recruitment numbers (centers A, B, and C). Results First-line treatment with 5-fluorouracil monotherapy was applied in exceptional cases. The regular treatment method comprised either an irinotecan- (30%) or an oxaliplatin-based regimen (32%). Biological agents were added to the treatment of 33 patients (32%). The median overall survival (OS) of the total patient collective was 25 months. The OS differed significantly in 2 out of the 3 centers, ranging between 27 and 11 months. Secondary metastasis resections were performed in 26% of the total patient collective. The center with the most favorable outcome results also had the lowest costs for palliative treatment and care, including the lowest drug costs. Conclusion A combined chemotherapy treatment was the rule. Concerning biological agents, a significant lack of their application in first-line treatment and the quality of interdisciplinary cooperation have to be addresse
Keywords: Interdisciplinary cooperation; Costs; Colorectal cancer; Palliative treatment results

Palliative treatment of malignant intestinal obstruction with EUS-guided ileosigmoidostomy – a case report - Zundler, Sebastian; Wolff, Kerstin; Leppkes, Moritz; Gaza, Anne; Haberkamp, Sophie; Strobel, Deike; Siebler, Jürgen; Neurath, Markus; Waldner, Maximilian (Zeitschrift für Gastroenterologie, 2024)
We present the case of a 70-year-old patient of Caucasian origin under palliative chemotherapy for metastasized colorectal cancer, who presented with signs of complete small bowel obstruction six months after placement of a diverting ileostomy. Following previous tumor perforation, he was not considered a candidate for further surgical intervention. Thus, endoscopic ultrasound-guided enterocolostomy (i.e., ileosigmoidostomy) with a lumen-apposing metal stent was successfully performed in a coloenteric approach to restore the passage. Oral nutrition could be resumed the next day, and the patient could be discharged in substantially improved condition after three days.
CRIS-Team Scopus Importer:2024-12-13
Keywords: endoscopic ultrasound; endoscopy; oncology

Pancreatic Panniculitis and Polyarthritis - Zundler, Sebastian; Strobel, Deike; Manger, Bernhard; Neurath, Markus; Wildner, Dane (Current Rheumatology Reports, 2017)
Polyarthritis can have numerous reasons and may thus constitute a challenge for differential diagnosis. One rare potential reason for sterile polyarthritis is underlying pancreatic disease with systemic hyperlipasemia, most often accompanied by painful skin lesions caused by a subcutaneous inflammatory process known as panniculitis. Systematic evidence on pancreatic panniculitis and polyarthritis is limited, particularly regarding its feature as facultative paraneoplasia with underlying intra- or even extra-pancreatic malignancy. Therefore, we will summarize the current knowledge about this orphan disease including epidemiological, pathophysiological, diagnostic, and treatment aspects in the present review.Although direct evidence is lacking, it is highly probable that pancreatic polyarthritis and panniculitis are caused by peripheral lipolytic activity of lipase systemically circulating due to benign (e.g., acute or chronic pancreatitis) or malign (e.g., acinar cell carcinoma (ACC) or adenocarcinoma) pancreatic disease. In the latter case, pancreatic polyarthritis and panniculitis are associated with poor outcome. Pancreatic polyarthritis and panniculitis should always be included into diagnostic considerations, and once suspected, a thorough work-up to identify the underlying disease has to be performed.
EVALuna2:13446

Pancreatic panniculitis in a patient with pancreatic-type acinar cell carcinoma of the liver–case report and review of literature - Zundler, Sebastian; Erber, Ramona; Agaimy, Abbas; Hartmann, Arndt; Kiesewetter, Franklin; Strobel, Deike; Neurath, Markus; Wildner, Dane (BMC Cancer, 2016)
Pancreatic panniculitis is a rare condition, which has only been described in relation with pancreatic diseases up to now. It is characterized by necrotizing subcutaneous inflammation and is thought to be triggered by adipocyte necrosis due to systemic release of pancreatic enzymes with consecutive infiltration of neutrophils. We present the first case of a patient with pancreatic panniculitis caused by pancreatic-type primary acinar cell carcinoma (ACC) of the liver and without underlying pancreatic disease.A 73-year old Caucasian female patient was referred to our department with painful cutaneous nodules persisting for eight weeks and with marked lipasemia ( 15000 U/l; normal range <60 U/l). Four weeks prior, several liver lesions had been detected. Empiric treatment with steroids did not show any effect. A biopsy of the skin nodules revealed "pancreatic" panniculitis, while abdominal imaging with ultrasound, computed tomography and magnetic resonance imaging detected no abnormal pancreatic findings. Ultrasound-guided biopsy of the liver lesions showed infiltrates of an ACC. The patient died soon thereafter. Autopsy failed to reveal any other primary for the ACC, so that a pancreatic-type ACC of the liver was diagnosed by exclusion. One hundred thirty cases of pancreatic panniculitis published within the last 20 years are reviewed. ACC of the pancreas is the most common underlying neoplastic condition. Patients with associated neoplasm are significantly older, take longer to be diagnosed and have higher lipase levels than patients with underlying pancreatitis. Extrapancreatic pancreatic-type ACC is very rare, but shows the same biological features as ACC of the pancreas. It is believed to develop from metaplastic or ectopic pancreatic tissue. Up to now, no pancreatic panniculitis in extrapancreatic ACC has been described.Pancreatic panniculitis should always be included in the differential diagnosis of lipolytic panniculitic lesions. It can be regarded as a facultative paraneoplastic phenomenon. When suspected, a thorough work-up for identification of the underlying disease is mandatory and extrapancreatic lesions (e.g. liver) should also be considered. While administration of octreotide or steroids can sometimes alleviate symptoms, immediate treatment of the associated condition is the only effective management option.
EVALuna2:2057

Paraduodenal pancreatitis as diagnostic challenge: clinical and morphological features of patients with pancreatic pathology involving the pancreatic groove. - Vitali, Francesco; Heinrich, Marc Christopher; Strobel, Deike; Zundler, Sebastian; Aghdassi, Ali A; Uder, Michael; Neurath, Markus; Grützmann, Robert; Wiesmüller, Marco; Frulloni, Luca; Wildner, Dane (Annals of Gastroenterology, 2024)
BACKGROUND: Paraduodenal pancreatitis (PP) is an inflammation involving the groove zone, delimited by the duodenum lumen, bile duct, and the head of the pancreas. This area may also be involved during acute pancreatitis (AP). The differential diagnosis is clinically relevant, since PP generally persists, whereas AP resolves. Hence, we compared a cohort of patients with PP and AP involving the groove area. METHODS: We retrospectively evaluated patients with pathology involving the groove area. The primary aim was to define the diagnostic features of PP compared to non-PP pancreatitis involving the groove area. PP was diagnosed by imaging, while AP was diagnosed according to the revised Atlanta classification and the clinical course, to exclude chronic pancreatitis. RESULTS: The study population consisted of 37 patients (32 men, age 56.9±9.1 years), 25 with a diagnosis of PP (23 men, mean age 54.9±8.5 years), and 12 (9 men, mean age 61.2±9.2 years) with AP involving the groove. All 25 patients with PP and 4 (33.3%) with AP reported a history of alcohol abuse, 23 patients (92%) with PP, and 3 (25%) with AP had a history of smoking. On imaging, PP patients presented a significantly thicker duodenal wall compared to the AP group (P=0.010). Chronic pancreatitis in the body/tail and exocrine insufficiency was prevalent in PP (P<0.001 and P=0.02). The medial displacement of the gastroduodenal artery was more frequent in the PP group (P=0.011). CONCLUSION: PP has a different clinical and imaging profile compared to AP involving the groove area.
EVALuna2:583244

Participation of the intestinal microbiota in the mechanism of beneficial effect of treatment with synbiotic syngut on experimental colitis under stress conditions - Konturek, P. C.; Konturek, K.; Brzozowski, T.; Wojcik, D.; Magierowski, M.; Targosz, A.; Krzysiek-Maczka, G.; Sliwowski, Z.; Strzalka, M.; Magierowska, K.; Szczyrk, U.; Kwiecien, S.; et al. (Journal of Physiology and Pharmacology, 2020)
Gut-brain axis plays a central role in the regulation of stress related diseases such as irritable bowel syndrome (iBs) or inflammatory bowel disease (iBD). it is increasingly recognized that stress modulates gut microbiota community structure and activity and represents an important causal factor in dysbiosis. this study was designed to determine the effect of daily treatment with synbiotic (syngut) containing inulin, Lactobacillus acidophilus, Bifidobacterium lactisw51, Lactobacillus plantarumw21 and Lactococcus lactis applied i.g. at a dose of 50 mg/kg i.g. on the colonic damage and colonic mucosal blood flow in rats with experimentally induced tnBs-colitis that were additionally exposed or not to acute stress (episodes of cold restraint stress every other day before colitis induction). Control rats received daily treatment with vehicle (saline, i.g.) or mesalazine (50 mg/kg-d i.g.), the standard drug recommended in therapy of iBD. at the termination of tnBs colitis, the histologic evaluation of colonic mucosa, mucosal malonyldialdehyde (MDa) level and plasma concentrations of proinflammatory cytokines (tnf-α, iL-1β) and adipokine adiponectin were assessed. the samples of colonic mucosa not involving colonic lesions and surrounding the flared mucosa were excised for the determination of mrna expression for proinflammatory biomarkers tnf-α, iL-1β, iL-10 and Cox-2 as well as antioxidazing factors soD-1 and soD-2. finally, the gut microbial profiles were analyzed by 16s rrna sequencing at phylum, family and genus level. episodes of cold stress significantly aggravated the course of tnBs colitis, and significantly increased the release of proinflammatory cytokines as well as the significant increase in the MDa concentration has been observed as compared with non-stressed tnBs rats. these changes were followed by the significant fall in the CBf and plasma adiponectin levels and by the overexpression of mrna of proinflammatory biomarkers. synbiotic treatment with syngut significantly reduced the area of colonic lesions observed macroscopically and microscopically in rats with tnBs colitis with or without exposure to cold stress, significantly increased the CBf, normalized plasma adiponectin levels and significantly attenuated the release and colonic expression of proinflammatory cytokines and biomarkers. the analysis of the gut microbiota showed a significant reduction of microbial diversity (shannon index) in rats with tnBs colitis with or without exposure to stress. the therapy with syngut failed to significantly affect the alpha diversity. at the phylum level, the significant rise in Proteobacteria has been observed in stressed rats with tnBs colitis and this effects was attenuated by treatment with syngut. at family level, tnBs colitis alone or in combination with stress led to a significant decrease of sCfa producing bacterial taxa such as Ruminococaceae and Lachnospiraceae and syngut counteracted this effect. we conclude that: 1) cold stress exacerbates the gastrointestinal inflammation in experimental colitis; 2) the synbiotic therapy with syngut ameliorates the gut inflammation in rats with tnBs colitis combined with cold stress; 3) the beneficial effect of syngut is accompanied by increase of anti-inflammatory taxa such as Ruminococaceae and Lachnospiraceae, and 4) the modulation of gut microbiota with syngut alleviates stressrelated intestinal inflammation suggesting a potential usefulness of synbiotic therapy in intestinal disorders accompanied by stress in patients with iBD.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Adiponectin; Bacterial diversity; Colonic blood flow; Experimental colitis; Malonyldialdehyde; Microbiota; Oxidative stress; Proinflammatory cytokines; Stress; Synbiotic Syngut

Pathogenic T cell subsets in allergic and chronic inflammatory bowel disorders - Zundler, Sebastian; Neurath, Markus (Immunological Reviews, 2017)
Homeostasis in the gastrointestinal tract relies on a sensitive equilibrium between permissive and protective functions. This is closely reflected in the regulation of the intestinal immune system and especially T cells in the gut. This balance, however, is susceptible to disturbances as demonstrated by pathological conditions like food allergy, celiac disease, or inflammatory bowel disease. In these allergic and chronic inflammatory bowel disorders, luminal antigens get access to the lamina propria where they trigger a dysregulated immune response with crucial involvement of different T cell subsets. We will begin this review with some comprehensive remarks on current concepts on the pathogenesis of these diseases before taking a closer look at the life cycle of intestinal T cells consisting of priming, homing, differentiation and proliferation and apoptosis respectively. Subsequently we will discuss the specific implication of distinct T cell subsets in allergic and chronic inflammatory conditions of the gastrointestinal tract in detail and comment on current and future approaches to targeted therapy in this context.
EVALuna2:33809

Patients Receiving Cytokine Inhibitors Have Low Prevalence of SARS-CoV-2 Infection - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

PATIENTS WITH IMMUNE MEDIATED INFLAMMATORY DISEASES ARE OVERREPRESENTED IN LOW-FREQUENCY VIRAL SYMPTOM CLUSTERS - Tascilar, Koray; Simon, David; Krönke, Gerhard; Kleyer, Arnd; Ramming, Andreas; Atreya, Raja; Tenbusch, Matthias; Überla, Klaus; Berking, Carola; Sticherling, Michael; Neurath, Markus; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Patients with immune-mediated inflammatory diseases receiving cytokine inhibitors have low prevalence of SARS-CoV-2 seroconversion - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (Nature Communications, 2020)
Immune-mediated inflammatory diseases (IMIDs) of the joints, gut and skin are treated with inhibitors of inflammatory cytokines. These cytokines are involved in the pathogenesis of coronavirus disease 2019 (COVID-19). Investigating anti-SARS-CoV-2 antibody responses in IMIDs we observe a reduced incidence of SARS-CoV-2 seroconversion in IMID patients treated with cytokine inhibitors compared to patients receiving no such inhibitors and two healthy control populations, despite similar social exposure. Hence, cytokine inhibitors seem to at least partially protect from SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2020-08-07

Perceived distress, personality characteristics, coping strategies and psychosocial impairments in a national German multicenter cohort of patients with Crohn's disease and ulcerative colitis - Petruo, Vanessa A.; Krauss, Ekaterina; Kleist, Anika; Hardt, Juliane; Hake, Karsten; Peirano, Julia; Krause, Thomas; Ehehalt, Robert; De La Perriere, Philipp Von Arnauld; Buening, Juergen; Treml, Oliver; Krauss, Norbert; et al. (Zeitschrift für Gastroenterologie, 2019)
BACKGROUND AND AIMS: This study examined differences in personality, psychological distress, and stress coping in inflammatory bowel disease (IBD) depending on type of disease and disease activity. We compared patients suffering from Crohn's disease (CD) and ulcerative colitis (UC) with controls. While the literature is replete with distinctive features of the pathogenesis of IBD, the specific differences in psychological impairments are not well studied. METHODS: In this German national multicenter study, participants were recruited from 32 centers. Two hundred ninety-seven questionnaires were included, delivering vast information on disease status and psychological well-being based on validated instruments with a total of 285 variables. RESULTS: CD patients were more affected by psychological impairments than patients suffering from UC or controls. Importantly, patients with active CD scored higher in neuroticism (p < 0.01), psychological distress (p < 0.001) and maladaptive stress coping (escape, p = 0.03; rumination, p < 0.03), but less need for social support (p = 0.001) than controls. In contrast, patients suffering from active UC showed psychological distress (p < 0.04) and maladaptive coping (avoidance, p < 0.03; escape, p = 0.01). Patients in remission seemed to be less affected. In particular, patients with UC in remission were not inflicted by psychological impairments. The group of CD patients in remission however, showed insecurity (p < 0.01) and paranoid ideation (p = 0.04). CONCLUSIONS: We identified specific aspects of psychological impairment in IBD depending on disease and disease activity. Our results underscore the need for psychological support and treatment particularly in active CD.
EVALuna2:209006

Perforations after routine biopsy in IBD patients, their management and potential risk reductions by microscopic imaging with endocytoscopy - Klenske, Entcho; Hartmann, Arndt; Atreya, Raja; Neurath, Markus; Rath, Timo (Journal of Gastrointestinal and Liver Diseases, 2020)
CRIS-Team Scopus Importer:2020-09-25

Personalizing Treatment in IBD: Hype or Reality in 2020? Can We Predict Response to Anti-TNF? - Atreya, Raja; Neurath, Markus; Siegmund, Britta (Frontiers in Medicine, 2020)
The advent of anti-TNF agents as the first approved targeted therapy in the treatment of inflammatory bowel disease (IBD) patients has made a major impact on our existing therapeutic algorithms. They have not only been approved for induction and maintenance treatment in IBD patients, but have also enabled us to define and achieve novel therapeutic outcomes, such as combination of clinical symptom control and endoscopic remission, as well as mucosal healing. Nevertheless, approximately one third of treated patients do not respond to initiated anti-TNF therapy and these treatments are associated with sometimes severe systemic side-effects. There is therefore the currently unmet clinical need do establish predictive markers of response to identify the subgroup of IBD patients, that have a heightened probability of response. There have so far been approaches from different fields of IBD research, to descry markers that would empower us to apply TNF-inhibitors in a more rational manner. These markers encompass findings from disease-related and clinical factors, pharmacokinetics, biochemical markers, blood and stool derived parameters, pharmacogenomics, microbial species, metabolic compounds, and mucosal factors. Furthermore, changes in the intestinal immune cell composition in response to therapeutic pressure of anti-TNF treatment have recently been implicated in the process of molecular resistance to these drugs. Insights into factors that determine resistance to anti-TNF therapy give reasonable hope, that a more targeted approach can then be utilized in these non-responders. Here, IL-23 could be identified as one of the key factors determining resistance to TNF-inhibitors. Growing insights into the molecular mechanism of action of TNF-inhibitors might also enable us to derive critical molecular markers that not only mediate the clinical effects of anti-TNF therapy, but which level of expression might also correlate with its therapeutic efficacy. In this narrative review, we present an overview of currently identified possible predictive markers for successful anti-TNF therapy and discuss identified molecular pathways that drive resistance to these substances. We will also point out the necessity and difficulty of developing and validating a diagnostic marker concerning clinically relevant outcome parameters, before they can finally enter daily clinical practice and enable a more personalized therapeutic approach.
CRIS-Team Scopus Importer:2020-09-25
Keywords: anti-TNF; inflammatory bowel diseases; personalized medicine; prediction; response

Perspectives, potentials and trends of ex vivo and in vivo optical molecular pathology - Krafft, Christoph; Von Eggeling, Ferdinand; Guntinas-Lichius, Orlando; Hartmann, Arndt; Waldner, Maximilian; Neurath, Markus; Popp, Juergen (Journal of Biophotonics, 2018)
It is pivotal for medical applications, such as noninvasive histopathologic characterization of tissue, to realize label-free and molecule-specific representation of morphologic and biochemical composition in real-time with subcellular spatial resolution. This unmet clinical need requires new approaches for rapid and reliable real-time assessment of pathologies to complement established diagnostic tools. Photonic imaging combined with digitalization offers the potential to provide the clinician the requested information both under in vivo and ex vivo conditions. This report summarizes photonic approaches and their use in combination with image processing, machine learning and augmented virtual reality that might solve current challenges in modern medicine. Details are given for pathology, intraoperative diagnosis in head and neck cancer and endoscopic diagnosis in gastroenterology.
EVALuna2:33796

PGAM5 acts as a key mediator of lung fibrosis by disrupting mitochondrial homeostasis - Ganzleben, Ingo; He, Gui-Wei; Günther, Claudia; Prigge, Elena-Sophie; Richter, Karsten; Rieker, Ralf; Mougiakakos, Dimitrios; Neurath, Markus; Becker, Christoph (EUROPEAN RESPIRATORY JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

PGAM5 is a key driver of mitochondrial dysfunction in experimental lung fibrosis - Ganzleben, Ingo; He, Gui Wei; Günther, Claudia; Prigge, Elena Sophie; Richter, Karsten; Rieker, Ralf; Mougiakakos, Dimitrios; Neurath, Markus; Becker, Christoph (Cellular and Molecular Life Sciences, 2019)
Rationale: Mitochondrial homeostasis has recently emerged as a focal point in the pathophysiology of idiopathic pulmonary fibrosis (IPF), but conflicting data have been reported regarding its regulation. We speculated that phosphoglycerate mutase family member 5 (PGAM5), a mitochondrial protein at the intersection of multiple cell death and mitochondrial turnover pathways, might be involved in the pathogenesis of IPF. Methods: PGAM5-deficient mice and human pulmonary epithelial cells were analyzed comparatively with PGAM5-proficient controls in a bleomycin-based model of pulmonary fibrogenesis. Mitochondria were visualized by confocal and transmission electron microscopy. Mitochondrial homeostasis was assessed using JC1 (ΔΨ) and flow cytometry. Results: PGAM5 plays an important role in pulmonary fibrogenesis. Pgam5−/− mice displayed significantly attenuated lung fibrosis compared to controls. Complementary, in vitro studies demonstrated that PGAM5 impaired mitochondrial integrity on a functional and structural level independently of mtROS-production. On a molecular level, reduced mitophagy caused by PGAM5 deficiency improved mitochondrial homeostasis. Conclusions: Our study identifies PGAM5 as an important regulator of mitochondrial homeostasis in pulmonary fibrosis. Our data further indicate PGAM5-mediated mitophagy itself as a pivotal gateway event in the mediation of self-sustaining mitochondrial damage and membrane depolarization. Our work hereby highlights the importance of mitochondrial dynamics and identifies a potential therapeutic target that warrants further studies. Graphical abstract: Toxic agents lead to mitochondrial damage resulting in depolarization of the mitochondrial membrane potential (ΔΨ) which is a gateway event for the initiation of PGAM5-mediated mitophagy. PGAM5-mediated mitophagy in turn leads to a self-perpetuating escalation of ΔΨ depolarization. Loss of the mitophagy-based damage-enhancing loop under PGAM5-deficient conditions breaks this vicious cycle, leading to improved mitochondrial homeostasis.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-06-21
Keywords: Bleomycin; IPF; Mitophagy

PGAM5-MAVS interaction regulates TBK1/ IRF3 dependent antiviral responses - Yu, Yidong; Zielinska, Marta; Li, Wei; Bernkopf, Dominic; Heilingloh, Christiane; Neurath, Markus; Becker, Christoph (Scientific Reports, 2020)
Viral infections trigger host innate immune responses, characterized by the production of type-I interferons (IFN) including IFNβ. IFNβ induces cellular antiviral defense mechanisms and thereby contributes to pathogen clearance. Accumulating evidence suggests that mitochondria constitute a crucial platform for the induction of antiviral immunity. Here we demonstrate that the mitochondrial protein phosphoglycerate mutase family member 5 (PGAM5) is important for the antiviral cellular response. Following challenge of HeLa cells with the dsRNA-analog poly(I:C), PGAM5 oligomers and high levels of PGAM5 were found in mitochondrial aggregates. Using immunoprecipitation, a direct interaction of PGAM5 with the mitochondrial antiviral-signaling protein (MAVS) was demonstrated. In addition, PGAM5 deficient cells showed diminished expression of IFNβ and IFNβ target genes as compared to WT cells. Moreover, PGAM5 deficient mouse embryonic fibroblasts (MEFs) exhibited decreased phosphorylation levels of IRF3 and TBK1 when challenged with poly(I:C) intracellularly. Finally, PGAM5 deficient MEFs, upon infection with vesicular stomatitis virus (VSV), revealed diminished IFNβ expression and increased VSV replication. Collectively, our study highlights PGAM5 as an important regulator for IFNβ production mediated via the TBK1/IRF3 signaling pathway in response to viral infection.
CRIS-Team Scopus Importer:2020-06-02

PGAM5-mediated programmed necrosis of hepatocytes drives acute liver injury - He, Gui-Wei; Günther, Claudia; Kremer, Andreas; Thonn, Veronika; Amann, Kerstin Ute; Poremba, Christopher; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Gut, 2016)
Autoimmune hepatitis (AIH) is a severe necroinflammatory liver disease associated with significant mortality. Although loss of hepatocytes is generally recognised as a key trigger of liver inflammation and liver failure, the regulation of hepatic cell death causing AIH remains poorly understood. The aim of this study was to identify molecular mechanisms that drive hepatocyte cell death in the pathogenesis of acute liver injury.Acute liver injury was modelled in mice by intravenous administration of concanavalin A (ConA). Liver injury was demonstrated by serum transaminases and histological assessment of liver sections. PGAM5-deficient mice (PGAM5-/-) were used to determine its role in experimental hepatitis. Mdivi-1 was used as an inhibitor of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission. Mitochondrial fission and the expression of PGAM5 were compared between liver biopsies derived from patients with AIH and control patients.PGAM5 was highly expressed in hepatocytes of patients with AIH and in mice with ConA-induced experimental hepatitis. Deficiency of PGAM5 protected mice from ConA-induced hepatocellular death and liver injury. PGAM5 regulated ConA-induced mitochondrial fission in hepatocytes. Administration of the Drp1-inhibitor Mdivi-1 blocked mitochondrial fission, diminished hepatocyte cell death and attenuated liver tissue damage induced by ConA.Our data demonstrate for the first time that PGAM5 plays an indispensable role in the pathogenesis of ConA-induced liver injury. Downstream of PGAM5, Drp1-mediated mitochondrial fission is an obligatory step that drives the execution of hepatic necrosis and tissue damage. Our data highlight the PGAM5-Drp1 axis as a potential therapeutic target for acute immune-mediated liver injury.
EVALuna2:2219

Phase 1 Clinical Study of siRNA Targeting Carbohydrate Sulphotransferase 15 in Crohn's Disease Patients with Active Mucosal Lesions - Suzuki, Kenji; Yokoyama, Junji; Kawauchi, Yusuke; Honda, Yutaka; Sato, Hiroki; Aoyagi, Yutaka; Terai, Shuji; Okazaki, Kazuichi; Suzuki, Yasuo; Sameshima, Yukinori; Fukushima, Tsuneo; Sugahara, Kazuyuki; et al. (Journal of Crohns & Colitis, 2017)
BACKGROUND AND AIMS: Carbohydrate sulphotransferase 15 [CHST15] is a specific enzyme biosynthesizing chondroitin sulphate E that binds various pathogenic mediators and is known to create local fibrotic lesions. We evaluated the safety of STNM01, a synthetic double-stranded RNA oligonucleotide directed against CHST15, in Crohn's disease [CD] patients whose mucosal lesions were refractory to conventional therapy. METHODS: This was a randomized, double-blind, placebo-controlled, concentration-escalation study of STNM01 by a single-dose endoscopic submucosal injection in 18 CD patients. Cohorts of increasing concentration of STNM01 were enrolled sequentially as 2.5nM [n = 3], 25nM [n = 3], and 250nM [n = 3] were applied. A cohort of placebo [n = 3] was included in each concentration. Safety was monitored for 30 days. Pharmacokinetics was monitored for 24h. The changes from baseline in the segmental Simple Endoscopic Score for CD [SES-CD] as well as the histological fibrosis score were evaluated. RESULTS: STNM01 was well tolerated and showed no drug-related adverse effects in any cohort of treated patients. There were no detectable plasma concentrations of STNM01 at all measured time points in all treatment groups. Seven of nine subjects who received STNM01 showed reduction in segmental SES-CD at Day 30, when compared with those who received placebo. Histological analyses of biopsy specimens revealed that STNM01 reduced the extent of fibrosis. CONCLUSION: Local application of STNM01 is safe and well tolerated in CD patients with active mucosal lesions.
EVALuna2:33828

Phase angle and vector analysis from multifrequency segmental bioelectrical impedance analysis: New reference data for older adults - Reljic, Dejan; Zarafat, Daniel; Jensen, B.; Herrmann, H. J.; Neurath, Markus; Konturek, P. C.; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2020)
Phase angle (PA) and bioelectrical impedance vector analysis (BIVA) have been recommended as useful prognostic markers in various clinical settings. However, reference data for older adults measured by the novel segmental multifrequency bioelectrical impedance analysis (SMF-BIA) technique are currently lacking. This study examined 567 (286 men, 281 women) healthy older adults (65 – 97 years) and new SMF-BIA-based PA and BIVA reference values were generated stratified according to gender and 3 age groups (65 – 75 years, 76 – 85 years, > 85 years). Mean PA-values (women: 4.30 ± 0.6°, men: 4.77 ± 0.7°) were significantly lower than those previously reported for a younger reference population. Age and gender were significant determinants of PA and BIVA. PA showed a significant decrease with increasing age in both genders. The greatest changes occurred in the age group > 85 years. Men had higher PAs compared to women (except for the oldest age group), but showed a substantially steeper decline in PA, possibly due to a more pronounced reduction of muscle mass. Compared to published reference data for younger adults, there was a clear downward migration of the BIVA vector points in older adults, indicating an age-related reduction of body cell mass. Accordingly, the equation for the BIVA chart generation was modified by adding the factor age. In conclusion, this is the first study to present SMF-BIA-determined PA and BIVA reference data for healthy subjects aged ³ 65 years. These data can be used for clinical purposes to identify individuals at increased risk for adverse health events or to monitor treatment responses.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Age and gender stratification; Bioimpedance analysis; Body composition; Geriatric medicine; Health risk diagnostic and prediction; Nutrition status monitoring

Physical activity and advanced cancer: evidence of exercise-sensitive genes regulating prostate cancer cell proliferation and apoptosis - Schwappacher, Raphaela; Schink, Kristin; Sologub, Svetlana; Dieterich, Walburga; Reljic, Dejan; Friedrich, Oliver; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (The Journal of Physiology, 2020)
Key points: Physical activity is known to protect against cancer. The resistance exercise method whole-body electromyostimulation (WB-EMS) has a significant anti-cancer effect. WB-EMS-conditioned serum from advanced prostate cancer patients decreased human prostate carcinoma cell growth and viability in vitro. Multiplex analysis revealed that genes associated with human prostate cancer cell proliferation and apoptosis are sensitive for exercise. Feasible exercise should be part of multimodal anti-cancer therapies, also for physically weakened patients. Abstract: Regular physical activity is known to protect against cancer development. In cancer survivors, exercise reduces the risk of cancer recurrence and mortality. However, the link between exercise and decreased cancer risk and improved survival is still not well understood. Serum from exercising healthy individuals inhibits proliferation and activates apoptosis in various cancer cells, suggesting that mechanisms regulating cancer cell growth are affected by exercise. For the first time, we analysed serum from advanced-stage cancer patients with prostate (exercise group n = 8; control group n = 10) or colorectal (exercise n = 6; control n = 6) cancer, after a 12-week whole-body electromyostimulation training (20 min/session, 2×/week; frequency 85 Hz; pulse width 350 µs; 6 s stimulation, 4 s rest), a tolerable, yet effective, resistance exercise for physically weakened patients. We report that serum from these advanced cancer patients inhibits proliferation and enhances apoptosis of human prostate and colon cancer cells in vitro using cell growth and death assays (5-bromo-2′-deoxyuridine incorporation, cell counting, DNA fragmentation). Exercise-mimicking electric pulse stimulation of human primary myotubes showed that electric pulse stimulation-conditioned myotube medium also impairs human cancer cell viability. Gene expression analysis using a multiplex array of cancer-associated genes and subsequent quantitative RT-PCR revealed the presence of exercise-sensitive genes in human prostate cancer cells that potentially participate in the exercise-mediated regulation of malignant cell growth and apoptosis. Our data document the strong efficiency of the anti-oncogenic effects of physical activity and will further support the application of regular therapeutic exercise during cancer disease.
CRIS-Team Scopus Importer:2020-08-07
Keywords: apoptosis; cancer cells; colorectal cancer; electric pulse stimulation; exercise; gene expression; physical activity; proliferation; prostate cancer; whole-body electromyostimulation

Physiological intermolecular modification spectroscopy for the prediction of response to anti-tumor necrosis factor therapy in patients with inflammatory bowel diseases - Eftekhari, Pierre; Glaubitz, Lisa; Breidert, Matthias; Neurath, Markus; Atreya, Raja (Digestive Diseases, 2014)
Anti-tumor necrosis factor (TNF) antibodies have clinical efficiency only in a subgroup of patients with inflammatory bowel diseases (IBD). Prediction of clinical response is a critical clinical problem. Physiological intermolecular modification spectroscopy (PIMS) is a label-free technology performed in physiological conditions. PIMS enables real-time monitoring of dynamic molecular resonance of entire proteins and macromolecules of an individual. The aim of this study was to explore the capacity of PIMS to discriminate IBD patients regarding response to anti-TNF treatment.Protein extracts of peripheral blood mononuclear cells (PBMC) from 30 outpatients diagnosed with ulcerative colitis (UC) or Crohn's disease (CD) and treated with infliximab were subjected to PIMS analysis in a blinded transversal study. Total protein from each patient's PBMCs was challenged with infliximab. Dynamic changes in macromolecular interaction were registered while the temperature rose from -37 to 37°C. Individual macromolecular volume and molecular elasticity were determined for each patient.Clinical data revealed that 67% of UC and 79% of CD patients responded to infliximab therapy during the 3-month study period based on their respective clinical activity score. These results confirm that PIMS data predicted response to anti-TNF therapy with an accuracy of 96%.PIMS stratified IBD patients into two groups, responders and nonresponders, which correlated with the clinical efficacy of anti-TNF therapy. PIMS seems to be a powerful technology to adapt IBD treatment to the individual patient. Further studies with PIMS might enable to predict clinical response to biological treatment in IBD patients before the therapy is initiated.
EVALuna2:1885

Pivotal Role of Carbohydrate Sulfotransferase 15 in Fibrosis and Mucosal Healing in Mouse Colitis - Suzuki, Kenji; Arumugam, Somasundaram; Yokoyama, Junji; Kawauchi, Yusuke; Honda, Yutaka; Sato, Hiroki; Aoyagi, Yutaka; Terai, Shuji; Okazaki, Kazuichi; Suzuki, Yasuo; Mizumoto, Shuji; Sugahara, Kazuyuki; et al. (PLoS ONE, 2016)
Induction of mucosal healing (MH) is an important treatment goal in inflammatory bowel disease (IBD). Although the molecular mechanisms underlying MH in IBD is not fully explored, local fibrosis would contribute to interfere mucosal repair. Carbohydrate sulfotransferase 15 (CHST15), which catalyzes sulfation of chondroitin sulfate to produce rare E-disaccharide units, is a novel mediator to create local fibrosis. Here we have used siRNA-based approach of silencing CHST15 in dextran sulfate sodium (DSS) induced colitis in mice, human colon fibroblasts and cancer cell lines. In a DSS-induced acute colitis model, CHST15 siRNA reduced CHST15 mRNA in the colon, serum IL-6, disease activity index (DAI) and accumulation of F4/80+ macrophages and ER-TR7+ fibroblasts, while increased Ki-67+ epithelial cells. In DSS-induced chronic colitis models, CHST15 siRNA reduced CHST15 mRNA in the colon, DAI, alpha-smooth muscle actin+ fibroblasts and collagen deposition, while enhanced MH as evidenced by reduced histological and endoscopic scores. We also found that endoscopic submucosal injection achieved effective pancolonic delivery of CHST15 siRNA in mice. In human CCD-18 Co cells, CHST15 siRNA inhibited the expression of CHST15 mRNA and selectively reduced E-units, a specific product biosynthesized by CHST15, in the culture supernatant. CHST15 siRNA significantly suppressed vimentin in both TGF-ß-stimulated CCD18-Co cells and HCT116 cells while up-regulated BMP7 and E-cadherin in HCT116 cells. The present study demonstrated that blockade CHST15 represses colonic fibrosis and enhances MH partly though reversing EMT pathway, illustrating a novel therapeutic opportunity to refractory and fibrotic lesions in IBD.
EVALuna2:2164

Plasma concentrations of ascorbic acid in a cross section of the German population - Hagel, Alexander; Albrecht, Heinz; Dauth, Wolfgang; Hagel, Wolfgang; Vitali, Francesco; Ganzleben, Ingo; Schultis, Hans W.; Konturek, Peter C.; Stein, Juergen; Neurath, Markus; Raithel, Martin (Journal of International Medical Research, 2018)
Objectives Vitamin C deficiency is considered extremely rare in modern industrialized countries. This study was performed to assess vitamin C concentrations in the German population. Methods As part of a consultant-patient seminar on nutrition and food intolerances, patients were asked to participate in this study on a voluntary basis. Blood samples were taken for analysis of serum vitamin C concentrations, and all patients were asked to complete a questionnaire. The vitamin C concentration was determined by high-performance liquid chromatography. Results Of approximately 300 patients attending the seminar, 188 (62.6%) consented to vitamin C blood sample analysis and 178 (59.3%) answered the questionnaire. The mean vitamin C concentration was 7.98 mg/L (range, 0.50-17.40; reference range, 5-15 mg/L). A low plasma level with vitamin C insufficiency (<5 mg/L) was found in 31 patients (17.4%), and a potential scorbutogenic deficiency (<1.5 mg/L) was found in 6 (3.3%). Conclusions Potential vitamin C insufficiency and deficiency is common. It is therefore possible, even in modern developed populations, that certain individuals may require a higher intake of vitamin C.
EVALuna2:33798

Pleiotropic functions of TNF-? in the regulation of the intestinal epithelial response to inflammation - Leppkes, Moritz; Roulis, Manolis; Neurath, Markus; Kollias, George; Becker, Christoph (International Immunology, 2014)
An important function of intestinal epithelial cells (IECs) is to maintain the integrity of the mucosal barrier. Inflammation challenges the integrity of the mucosal barrier and the intestinal epithelium needs to adapt to a multitude of signals in order to perform the complex process of maintenance and restitution of its barrier function. Dysfunctions in epithelial barrier integrity and restoration contribute to the pathogenesis of inflammatory bowel diseases (IBDs) such as Crohn's disease and ulcerative colitis. Mucosal healing has developed to a significant treatment goal in IBD. In this review, we would like to highlight physiologic and pathologic adaptations of the intestinal epithelium to inflammation, exemplified by its responses to TNF-?. A large body of literature exists that highlights the diverse effects of this cytokine on IECs. TNF-? modulates intestinal mucus secretion and constitution. TNF-? stimulation modulates paracellular flow via tight junctional control. TNF-? induces intracellular signaling cascades that determine significant cell fate decisions such as survival, cell death or proliferation. TNF-? impacts epithelial wound healing in ErbB- and Wnt-dependent pathways while also importantly guiding immune cell attraction and function. We selected important studies from recent years with a focus on functional in vivo data providing crucial insights into the complex process of intestinal homeostasis.
EVALuna2:1867

Point of Care detection of anti-infliximab antibodies in inflammatory bowel disease patients treated with the biosimilar SB2: performance comparison with ELISA - Atreya, Raja; Schmitt, H.; Fischer, Sven Moritz; Neurath, Markus; Rekalde, X.; Nagore, D.; Ametzazurra, A. (JOURNAL OF CROHNS & COLITIS, 2019)
CRIS-Team WoS Importer:2019-03-20

Postinterventional pain and complications of sonographically guided interventions in the liver and pancreas - Lindner, A.; Frieser, M.; Heide, R.; Wildner, D.; Neurath, Markus; Dauth, W.; Bernatik, T.; Strobel, Deike (Ultraschall in der Medizin, 2014)
Sonographically guided interventions in abdominal organs are routine procedures with rare severe complications. However, potential patient discomfort or pain is frequently not addressed in the literature.In a prospective 1-year study, the peri- and postinterventional pain of patients undergoing sonographically guided punctures of the liver and pancreas was analyzed. Data acquisition was done with a standardized questionnaire. This included three numeric rating scales (NRS) ranging from "0" to "10" to be answered at puncture and 1 hour and 4 hours later. Data concerning complications and administered analgesic medication was acquired from the patients' charts.223/274 patients could be analyzed (83 %). 91 women (40.8 %) and 132 men (59.2 %) were included. The mean age was 56.0 yrs. Overall the average level of pain was 2.98 at puncture, 1.21 after 1 hour and 0.71 after 4 hours. In patients with diagnostic biopsies, the pain levels were 3.37(0 h)/1.33(1 h)/0.71(4 h) for liver parenchyma, 2.64(0 h)/0.95(1 h)/0.65(4 h) for focal liver lesions and 3.1(0 h)/1.9(1 h)/1.1(4 h) for pancreatic punctures. The pain levels at therapeutic interventions were 3.00(0 h)/2.00(1 h)/0.50(4 h). Female and younger (< 50 yrs) patients had statistically significantly more pain at puncture and 1 hour postintervention. Only minor complications occurred (0.9 %).Severe pain after sonographically guided interventions is rare. Most patients suffer only from mild pain postinterventionally.
EVALuna2:1874

Precision Medicine in Inflammatory Bowel Diseases - Fischer, Sören; Neurath, Markus (Clinical Pharmacology & Therapeutics, 2017)
Inflammatory bowel diseases (IBDs) are a lifelong condition of chronic, recurrent inflammation in the gut. The introduction of immunomodulators and biologic agents markedly improved the treatment of IBDs. Therefore, the use of biologics became an essential element in the rational therapy of IBDs. Various substances are currently evaluated in clinical trials, addressing different target structures and offering further approaches in the field of IBD. Regarding the growing number of treatment options, the need for prediction of therapy response became a necessity and is the subject of the present research.
EVALuna2:33803

Precision of handheld multispectral optoacoustic tomography for muscle imaging - Wagner, Anna; Danko, Vera; Federle, Anna; Klett, Daniel; Simon, David; Heiß, Rafael; Jüngert, Jörg M.; Uder, Michael; Schett, Georg; Neurath, Markus; Wölfle, Joachim; Waldner, Maximilian; et al. (Photoacoustics, 2021)
Photo-or optoacoustic imaging (OAI) allows quantitative imaging of target tissues. Using multi-wavelength illumination with subsequent ultrasound detection, it may visualize a variety of different chromophores at centimeter depth. Despite its non-invasive, label-free advantages, the precision of repeated measurements for clinical applications is still elusive. We present a multilayer analysis of n = 1920 imaging datasets obtained from a prospective clinical trial (NCT03979157) in n = 10 healthy adult volunteers. All datasets were analyzed for 13 single wavelengths (SWL) between 660 nm–1210 nm and five MSOT-parameters (deoxygenated/oxygenated/total hemoglobin, collagen and lipid) by a semi-automated batch mode software. Intraclass correlation coefficients (ICC) were good to excellent for intrarater (SWL: 0.82–0.92; MSOT-parameter: 0.72−0.92) and interrater reproducibility (SWL: 0.79−0.87; MSOT-parameter: 0.78−0.86), with the exception for MSOT-parameter lipid (interrater ICC: 0.56). Results were stable over time, but exercise-related effects as well as inter-and intramuscular variability were observed. The findings of this study provide a framework for further clinical OAI implementation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: MSOT; Multispectral optoacoustic tomography; Muscle imaging; Optoacoustics; Photoacoustics

Predicting Therapeutic Response by in vivo Molecular Imaging in Inflammatory Bowel Diseases - Atreya, Raja; Neurath, Markus (Digestive Diseases, 2016)
Different invasive and non-invasive imaging modalities are indispensable tools in the management of inflammatory bowel disease (IBD) patients. Standard imaging procedures like white light endoscopy or MRI are used to define gut inflammation based on structural changes and altered morphology of the mucosa. Nevertheless, it has thus far not been possible to analyse biological processes at the cellular level, which drive intestinal inflammation in IBD patients. The recent advent of molecular imaging in the field of IBD has opened new promising avenues to allow personalized medicine approaches based on in vivo-detected molecular findings.Recent clinical studies have attempted to address the issue of predicting therapeutic response to anti-tumor necrosis factor (TNF) treatment in IBD patients based on the molecular mechanism of action of these agents and corresponding in vivo assessment of mucosal immune responses. Several experimental studies have indicated that one of the main functions of efficacious anti-TNF therapy in IBD is the induction of intestinal cell apoptosis. Fittingly, a corresponding molecular-imaging study using single-photon emission CT for the localization and quantification of cell apoptosis, demonstrated that induction of mucosal T-cell apoptosis correlated with the therapeutic response to anti-TNF therapy in Crohn's disease patients. There was moreover a predictive capacity regarding therapeutic efficacy. As the main biological properties of anti-TNF antibodies in IBD are mediated through binding to membrane-bound TNF (mTNF) expressing intestinal cells, another study used molecular imaging for in vivo visualization of these cells via fluorescent anti-TNF antibodies to predict therapeutic efficacy of these agents. It could be shown that patients with high amounts of mTNF positive cells showed significantly better response rates compared to patients with low amounts of mTNF positive cells.In vivo molecular imaging in IBD has the potential to have an impact on our current treatment approaches and may allow us to individualize specific therapies based on molecular level analysis.
EVALuna2:2092

Prediction of clinical outcomes in Crohn's disease by using confocal laser endomicroscopy: results from a prospective multicenter study - Tontini, Gian Eugenio; Mudter, Jonas; Günther, Claudia; Milani, Valentina; Atreya, Raja; Rath, Timo; Nagel, Andreas; Hatem, Giorgia; Sturniolo, Giacomo Carlo; Vecchi, Maurizio; Neurath, Markus; Galle, Peter R.; et al. (Gastrointestinal Endoscopy, 2018)
BACKGROUND AND AIMS: Assessment of prognostic factors in patients with Crohn's disease (CD) is of pivotal importance for early intervention and "treat-to-target" strategies. Confocal laser endomicroscopy (CLE) enables on-demand in vivo characterization of mucosal inflammatory and architectural changes during endoscopy. We prospectively assessed the value of CLE for prediction of clinical outcome parameters in CD. METHODS: Consecutive patients with CD undergoing colonoscopy were included in a multicenter study. Confocal imaging focused on 2 highly reproducible histologic hallmarks of active colonic inflammation: focal cryptitis and crypt architectural abnormality. We evaluated whether CLE, CD endoscopic index of severity (CDEIS), serum C-reactive protein (CRP), and CD activity index (CDAI) were associated with the risk of medical treatment escalation, transmural adverse events, and CD-related hospitalization or surgery during a 4-year follow-up. RESULTS: Among 49 patients (53% men, median age, 39 years), baseline CRP was ≥5 mg/L in 47%, CDEIS ≥3 in 75%, and CDAI >150 in 51%. Focal cryptitis and crypt architectural abnormality were observed in 63% (CLE+ group). CLE+ patients showed an increased incidence of medical treatment escalation (P < .001; relative risk [RR] = 3.27) and transmural lesions (P = .025; RR = 1.70), whereas patients with CRP ≥5 mg/L had increased CD-related hospitalization and surgery (P = .020, RR = 2.71) at 1-year follow-up. No further association with prognostic clinical outcomes was found over the 1-year follow-up as well as for CDEIS and CDAI at any time. CONCLUSIONS: CLE reveals CD-related features of mucosal inflammation and allows for early prediction of relevant clinical outcomes. Further studies should now address whether this promising prognostic tool could refine the timing of treatment strategies in patients with CD.
EVALuna2:35166

Predictors of Delayed Response to Tofacitinib: Results of the OCTAVE Open Study for Delayed Responders - Regueiro, Miguel; Kinnucan, Jami A.; Ungaro, Ryan; Quirk, Daniel; Su, Chinyu; Lawendy, Nervin; Fan, Haiyun; Woodworth, Deborah A.; Neurath, Markus (AMERICAN JOURNAL OF GASTROENTEROLOGY, 2019)
CRIS-Team WoS Importer:2020-02-28

Preliminary results for hyperspectral videoendoscopy diagnostics on the phantoms of normal and abnormal tissues: towards gastrointestinal diagnostics - Hohmann, Martin; Douplik, Alexandre; Varadhachari, Janani; Nasution, Aulia; Mudter, Jonas; Neurath, Markus; Schmidt, Michael (mudter jonas, 2011)

PREVALENCE AND CHARACTERISTICS OF SPONDYLOARTHRITIS ACCORDING TO ASAS CRITERIA IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE - RESULTS FROM THE SPICE COHORT - Haschka, J.; Hirschmann, S.; Kleyer, Arnd; Englbrecht, Matthias; Zimmermann, Julia; Faustini, F.; Simon, David; Figueiredo, C. P.; Muschitz, C.; Kocijan, R.; Resch, H.; Atreya, Raja; et al. (2017)
EVALuna2:33811

Primary Manifestation of Inflammatory Bowel Disease Following Subcutaneous Autovaccination - Raithel, Martin; Weidenhiller, Michael; Hahn, Markus; Hagel, Alexander; Bechthold, Caroline; Neurath, Markus; Rieker, Ralf J.; Stein, Juergen (Journal of Crohns & Colitis, 2015)
Onset of inflammatory bowel disease [IBD] is nowadays seen as an interplay or a combination of genetic susceptibility, disturbed intestinal immunity, and environmental factors including gut microbiome. However, the initiation of inflammation and progression to IBD pathogenesis in a given individual is poorly understood. In this case report we describe the clinical course of a 17-year-old female patient developing symptoms suggestive of IBD after 'autovaccine therapy', in which sterilised samples of the patient's own stool were injected subcutaneously for improvement of her general immunity. The patient presented with a severe onset of disease, which was first suspected to be ulcerative colitis on outpatient examination and was later corrected to IBD with Crohn's-like features due to high systemic inflammation, mixed lymphocytic-granulocytic infiltrates in gastric biopsies, and further characteristics suggestive of Crohn's disease. A prolonged and complicated course was seen with intermittent steroid dependency in the long term. Numerous publications postulate that [auto-]immune reactions against resident bacterial stool flora may play a role in IBD. It is possible that in this patient tolerance to endogenous bacteria was disrupted by systemic pro-inflammatory mechanisms induced by autovaccination.
EVALuna2:1971

Prognostic relevance of ARFI elastography in comparison to liver histology and the FIB-4 score - Klüppel, Moritz; Adler, Werner; Schellhaas, Barbara; Jesper, Daniel; Neurath, Markus; Pfeifer, Lukas (Ultraschall in der Medizin, 2024)
Purpose Liver histology has prognostic relevance and is used in surveillance and therapeutic strategies. This longitudinal study was designed to evaluate the prognostic relevance of ARFI elastography in comparison to liver histology and to the FIB-4 score in a 5-year observation interval. Materials and Methods Based on the hospital database, patients with an elastography examination of the liver between 2010-2012, a liver biopsy, and a follow-up of 5 years were included in the study. The AUROCs of the events liver-related death, HCC, and liver decompensation/variceal bleeding were calculated for ARFI elastography, liver histology, and FIB-4 and compared using the DeLong test. Results In the final analysis 113 patients were included with 30 (26.5 %) patients having high-grade fibrosis and 19 (16.8 %) having liver cirrhosis in histology. The AUROC for liver-related death in the 5-year interval (9.7 %, n=11) was 0.80 [0.68-0.92] for ARFI elastography, 0.79 [0.66-0.92] for liver histology, and 0.66 [0.53-0.79] for FIB-4 with a p-value of 0.83 comparing ARFI to histology and a p-value of 0.02 comparing ARFI to FIB-4. The AUROC for liver decompensation/variceal bleeding (13.3 %, n=15) was 0.86 [0.76-0.94] for ARFI, which is significantly higher than the AUROC of liver histology with 0.71 [0.56-0.86] (p=0.02) and FIB-4 with 0.67 [0.54-0.80] (p=0.003). There was no significant difference for the event HCC when comparing ARFI to histology (p=0.33) or FIB-4 (p=0.14). Conclusion The prognostic value of ARFI elastography seems to not be inferior to liver histology regarding liver-related survival and might even outperform histology and the FIB-4 score for predicting some liver-related complications.
CRIS-Team Scopus Importer:2024-06-21
Keywords: ARFI elastography; FIB-4 Score; liver cirrhosis; liver fibrosis; liver histology

Programming of Intestinal Epithelial Differentiation by IL-33 Derived from Pericryptal Fibroblasts in Response to Systemic Infection - Mahapatro, Mousumi; Försch, Sebastian; Hefele, Manuela; He, Gui-Wei; Giner-Ventura, Elisa; Mchedlidze, Tamar; Kindermann, Markus; Vetrano, Stefania; Danese, Silvio; Günther, Claudia; Neurath, Markus; Wirtz, Stefan; et al. (Cell Reports, 2016)
The intestinal epithelium constitutes an efficient barrier against the microbial flora. Here, we demonstrate an unexpected function of IL-33 as a regulator of epithelial barrier functions. Mice lacking IL-33 showed decreased Paneth cell numbers and lethal systemic infection in response to Salmonella typhimurium. IL-33 was produced upon microbial challenge by a distinct population of pericryptal fibroblasts neighboring the intestinal stem cell niche. IL-33 programmed the differentiation of epithelial progenitors toward secretory IEC including Paneth and goblet cells. Finally, IL-33 suppressed Notch signaling in epithelial cells and induced expression of transcription factors governing differentiation into secretory IEC. In summary, we demonstrate that gut pericryptal fibroblasts release IL-33 to translate bacterial infection into an epithelial response to promote antimicrobial defense.
EVALuna2:2065

Prospective Evaluation of Acoustic Radiation Force Impulse (ARFI) Elastography and High-Frequency B-Mode Ultrasound in Compensated Patients for the Diagnosis of Liver Fibrosis/Cirrhosis in Comparison to Mini-Laparoscopic Biopsy - Pfeifer, Lukas; Zopf, Steffen; Schwitulla, Judith; Wildner, Dane; Wachter, David; Neurath, Markus; Strobel, Deike; Siebler, Jürgen (Ultraschall in der Medizin, 2015)
Purpose: Ultrasound is a well-established noninvasive test for assessing patients with liver disease. This study aims to prospectively compare ultrasound to the new technique elastography (ARFI) for the assessment of liver fibrosis/cirrhosis. Materials and Methods: High-frequency B-mode ultrasound (liver surface/vein irregularity, liver homogeneity, spleen size), ARFI quantification, mini-laparoscopic liver evaluation including biopsy were prospectively obtained in compensated patients scheduled for liver biopsy. For the diagnosis of cirrhosis, a combined gold standard (cirrhosis at histology and/or at macroscopic liver evaluation) was used. Results: Out of 157 patients, 35 patients were diagnosed cirrhotic. Ultrasound (combination of liver vein and/or surface irregularity) showed no significant difference compared to ARFI quantification for the diagnosis of significant liver fibrosis (Ishak> = 3) and cirrhosis. Diagnosis of cirrhosis had a sensitivity/specificity/PPV/NPV of 83 %(± 12) / 82 %(± 7) / 57 %(± 14) / 94 %(± 4), respectively, with ultrasound and 86 %(± 12) / 81 %(± 7) / 57 %(± 13) / 95 %(± 4), respectively, with ARFI quantification. The sensitivity/specificity/PPV/NPV for the detection of significant fibrosis were 68 %(± 13) / 86 %(± 7) / 71 %(± 13) / 84 %(± 7), respectively, for ultrasound and 70 %(± 12) / 84 %(± 7) / 69 %(± 12) / 84 %(± 7), respectively, for ARFI quantification. Conclusion: ARFI elastography and high-frequency B-mode ultrasound show similar and good results for the diagnosis of compensated liver cirrhosis and high-grade fibrosis. A key benefit of both methods is the high NPV suggesting them as noninvasive exclusion tests.
EVALuna2:2049

Prospective long-term assessment of sedation-related adverse events and patient satisfaction for upper endoscopy and colonoscopy - Kilgert, Beate; Rybizki, Lydia; Grottke, Michael; Neurath, Markus; Neumann, Helmut (Digestion, 2014)
Fear of pain and sedation-related adverse events are impediments for patients to attend endoscopic screening or surveillance programs.To investigate the long-term effect of different sedation protocols in patients undergoing screening or surveillance endoscopy. Moreover, motivation of patients to decline endoscopic procedures was evaluated by focusing on the patient's satisfaction, fear and pain in relation to type of sedation used.A prospective, double-blind controlled trial data collection was performed by using a standardized clinical questionnaire followed by a telephone interview 3-4 weeks after the initial endoscopic procedure.The study was conducted at the Department of Medicine I at the University Hospital of Erlangen-Nuremberg. Data collection was performed during June 2012 till April 2013.Overall, 307 patients were prospectively evaluated (44.3% female, mean age 51 ± 17.4 years; mean BMI 25.5 ± 5.7). 247 patients (80.5%) were outpatients, 60 inpatients (19.5%).Endoscopic procedures were divided into five groups: (i) procedures in the upper gastrointestinal tract, (ii) complete colonoscopies, (iii) ileocolonoscopies, (iv) incomplete colonoscopies, and (v) other procedures.Patient satisfaction, fear and pain were measured in a structured and standardized clinical interview using a 6-point numerical rating scale, where 1 was 'very satisfied/no pain' and 6 was 'very unsatisfied/unsupportable pain'.Different types of sedation were assessed: propofol in monosedation (6.5%), combination of propofol + meperidine (41.0%), combination of midazolam + meperidine (48.5%) and other combinations (3.9%). Patient satisfaction was significantly reduced regarding fear and pain during the endoscopic procedure (p = 0.001 and p = 0.0001, respectively). All patients receiving propofol monosedation indicated significantly less pain in comparison to other sedation groups (p < 0.0001). Moreover, sedation with midazolam + meperidine increased the fear during the procedure significantly in comparison to monosedation with propofol (p = 0.082). Propofol/meperidine in combination and midazolam/meperidine increased the probability for cardiovascular events in comparison to monosedation with propofol (p = 0.005; p = 0.039). Finally, we observed significantly lower doses of propofol when used in monosedation than propofol in combination with meperidine (p = 0.066).Single-center study at a tertiary referral center.Propofol in monosedation should preferably be used for patient sedation in screening and surveillance endoscopies. Whether this approach could also improve participation rates in screening and surveillance endoscopies requires further investigations.
EVALuna2:1882

Protective effect of the novel calcineurin inhibitor voclosporin in experimental colitis - Lindemann, Aylin; Roth, Dominik; Koop, Kristina; Neufert, Clemens; Zundler, Sebastian; Atreya, Raja; Neurath, Markus; Leppkes, Moritz (Frontiers in Medicine, 2023)
Background and aims: Acute severe steroid-refractory ulcerative colitis remains a medically challenging condition with frequent need of surgery. It can be treated with the calcineurin inhibitor cyclosporine A with the need for therapeutic drug monitoring and significant toxicity. Recently, a novel calcineurin inhibitor, voclosporin, has been approved for the treatment of lupus nephritis with no need for therapeutic drug monitoring and an improved long-term safety profile. However, the therapeutic effect of voclosporin in acute severe steroid-refractory ulcerative colitis is still uncertain. We aimed to assess the therapeutic potential of voclosporin to ameliorate inflammation in an experimental model of colitis. Methods: We used the dextran sodium sulfate-induced model of colitis in C57BL/6 J wildtype mice treated with either cyclosporine A, voclosporin or solvent control. We employed endoscopy, histochemistry, immunofluorescence, bead-based multiplex immunoassays and flow cytometry to study the therapeutic effect of calcineurin inhibitors in a preventive setting. Results: Acute colitis was induced by dextran sodium sulfate characterized by weight loss, diarrhea, mucosal erosions and rectal bleeding. Both cyclosporine A and voclosporin strongly ameliorated the course of disease and reduced colitis severity in a similar manner. Conclusion: Voclosporin was identified as biologically effective in a preclinical model of colitis and may be a potential therapeutic option in treating acute severe steroid-refractory ulcerative colitis.
CRIS-Team Scopus Importer:2023-07-28
Keywords: calcineurin inhibitors; IBD; steroid refractory colitis; ulcerative colitis; voclosporin

Proteins from Modern and Ancient Wheat Cultivars: Impact on Immune Cells of Healthy Individuals and Patients with NCGS - Dieterich, Walburga; Schuster, Charlotte; Gundel, Paulina; Scherf, Katharina A.; Pronin, Darina; Geisslitz, Sabrina; Boerner, Andreas; Neurath, Markus; Zopf, Yurdagül (Nutrients, 2022)
In non-celiac gluten sensitivity (NCGS), the elimination of wheat results in a clear symptom improvement, but gluten has still not been proven as (the sole) trigger. Due to the increase in the prevalence of gluten-related diseases, the breeding of high-performance wheat cultivars is discussed as a trigger. To analyze the immune stimulation and signal pathways, the immune cells of healthy subjects and patients with NCGS were stimulated with gliadins from wheat, and the expression and secretion of interleukin 1ss (IL1ss) and interleukin 6 (IL6) were studied. To determine the impact of wheat breeding, the monocyte cell line THP1 and human immune cells were stimulated with gliadin, glutenin, and albumin/globulin fractions of ancient and modern cereals, and expression of inflammatory molecules was checked. Immune cells of patients with NCGS showed an increased expression of IL1ss and IL6 after stimulation with gliadins compared to immune cells of healthy controls. Gliadins caused a strong activation of P-STAT3 in immune cells of healthy controls, and inhibitors of JAK and NF kappa B pathways considerably reduced this response. In addition to gliadins, we further showed that glutenins and albumin/globulins from all wheat cultivars from the last century, and especially from einkorn and spelt, also markedly induced the expression of inflammatory genes in THP1 and human immune cells. There was no correlation between enhanced immune stimulation and ancient or modern cultivars. This does not support the hypothesis that modern wheat breeding is responsible for the increase in gluten-related diseases. An altered immune situation is suggested in patients with NCGS.
CRIS-Team WoS Importer:2022-11-11

Protein Supplementation Does Not Maximize Adaptations to Low-Volume High-Intensity Interval Training in Sedentary, Healthy Adults: A Placebo-Controlled Double-Blind Randomized Study - Reljic, Dejan; Zieseniss, Nilas; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (Nutrients, 2022)
There is ample evidence that specific nutritional strategies can enhance adaptions to resistance and endurance training. However, it is still unclear whether post-session protein supplementation may increase the effects of low-volume high-intensity interval training (LOW-HIIT). We examined the impact of LOW-HIIT combined with protein vs. placebo supplementation on cardiometabolic health indices in sedentary healthy individuals. Forty-seven participants (31.1 ± 8.0 yrs) performed cycle ergometer LOW-HIIT (5–10x1 min at 80–95% maximum heart rate) for eight weeks and randomly received double-blinded 40 g of whey protein (PRO-HIIT, N = 24) or an isocaloric placebo (maltodextrin, PLA-HIIT, N = 23) after each session. The maximum oxygen uptake (VO2max, primary outcome) and several secondary cardiometabolic outcomes were determined pre-/post-intervention. VO2max increased in PRO-HIIT (+2.8 mL/kg/min, p = 0.003) and PLA-HIIT (+3.5 mL/kg/min, p < 0.001). Systolic and diastolic blood pressure decreased in PRO-HIIT (−7/3 mmHg, p < 0.05) and PLA-HIIT (−8/5 mmHg, p < 0.001). Gamma glutamyl transferase (−2 U/L, p = 0.003) decreased in PRO-HIIT and alanine aminotransferase (−3 U/L, p = 0.014) in PLA-HIIT. There were no significant between-group differences in any of the outcome changes. In conclusion, LOW-HIIT improved VO2max and other cardiometabolic markers irrespective of the supplementation condition. Post-session protein supplementation does not seem to provide any additional benefit to LOW-HIIT in improving cardiometabolic health in sedentary healthy individuals.
CRIS-Team Scopus Importer:2022-10-28
Keywords: cardiometabolic health; cardiorespiratory fitness; HIIT; whey protein

Protein Supplementation Increases Adaptations to Low-Volume, Intra-Session Concurrent Training in Untrained Healthy Adults: A Double-Blind, Placebo-Controlled, Randomized Trial - Reljic, Dejan; Zieseniss, Nilas; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (Nutrients, 2024)
Combined endurance and resistance training, also known as “concurrent training”, is a common practice in exercise routines. While concurrent training offers the benefit of targeting both cardiovascular and muscular fitness, it imposes greater physiological demands on the body compared to performing each modality in isolation. Increased protein consumption has been suggested to support adaptations to concurrent training. However, the impact of protein supplementation on responses to low-volume concurrent training is still unclear. Forty-four untrained, healthy individuals (27 ± 6 years) performed two sessions/week of low-volume high-intensity interval training on cycle ergometers followed by five machine-based resistance training exercises for 8 weeks. Volunteers randomly received (double-blinded) 40 g of whey-based protein (PRO group) or an isocaloric placebo (maltodextrin, PLA group) after each session. Maximal oxygen consumption (VO2max) and overall fitness scores (computed from volunteers’ VO2max and one-repetition maximum scores, 1-RM) significantly increased in both groups. The PRO group showed significantly improved 1-RM in all major muscle groups, while the PLA group only improved 1-RM in chest and upper back muscles. Improvements in 1-RM in leg muscles were significantly greater in the PRO group versus the PLA group. In conclusion, our results indicate that adaptations to low-volume concurrent training, particularly leg muscle strength, can be improved with targeted post-exercise protein supplementation in untrained healthy individuals.
CRIS-Team Scopus Importer:2024-09-06
Keywords: HIIT; interference effect; low-volume exercise; resistance training; whey protein

Proteolytic Activity of the Paracaspase MALT1 Is Involved in Epithelial Restitution and Mucosal Healing - Wittner, Leonie; Wagener, Lukas; Wiese, Jakob J.; Stolzer, Iris; Krug, Susanne M.; Naschberger, Elisabeth; Jackstadt, Rene; Beyaert, Rudi; Atreya, Raja; Kühl, Anja A.; Sturm, Gregor; Gonzalez-Acera, Miguel; et al. (International Journal of Molecular Sciences, 2023)
The paracaspase MALT1 is a crucial regulator of immune responses in various cellular contexts. Recently, there is increasing evidence suggesting that MALT1 might represent a novel key player in mucosal inflammation. However, the molecular mechanisms underlying this process and the targeted cell population remain unclear. In this study, we investigate the role of MALT1 proteolytic activity in the context of mucosal inflammation. We demonstrate a significant enrichment of MALT1 gene and protein expression in colonic epithelial cells of UC patients, as well as in the context of experimental colitis. Mechanistically we demonstrate that MALT1 protease function inhibits ferroptosis, a form of iron-dependent cell death, upstream of NF-κB signaling, which can promote inflammation and tissue damage in IBD. We further show that MALT1 activity contributes to STAT3 signaling, which is essential for the regeneration of the intestinal epithelium after injury. In summary, our data strongly suggests that the protease function of MALT1 plays a critical role in the regulation of immune and inflammatory responses, as well as mucosal healing. Understanding the mechanisms by which MALT1 protease function regulates these processes may offer novel therapeutic targets for the treatment of IBD and other inflammatory diseases.
CRIS-Team Scopus Importer:2023-05-19
Keywords: ferroptosis; mucosal wound healing; ulcerative colitis

PU.1-driven Th9 Cells Promote Colorectal Cancer in Experimental Colitis Models Through Il-6 Effects in Intestinal Epithelial Cells - Gerlach, Katharina; Popp, Vanessa; Wirtz, Stefan; Al-Saifi, Ragheed; Gonzalez Acera, Miguel; Atreya, Raja; Dregelis, Theresa; Vieth, Michael; Fichtner-Feigl, Stefan; Mckenzie, Andrew N. J.; Rosenbauer, Frank; Weigmann, Benno; et al. (Journal of Crohns & Colitis, 2022)
Background and Aims Colorectal cancer [CRC] is one of the most frequent malignancies, but the molecular mechanisms driving cancer growth are incompletely understood. We characterised the roles of the cytokine IL-9 and Th9 cells in regulating CRC development. Methods CRC patient samples and samples from AOM/DSS treated mice were analysed for expression of IL-9, CD3, and PU.1 by FACS analysis and immunohistochemistry. IL-9 citrine reporter mice, IL-9 knockout mice, and PU.1 and GATA3 CD4-Cre conditional knockout mice were studied in the AOM/DSS model. DNA minicircles or hyper-IL-6 were used for overexpression of cytokines in vivo. Effects of IL-6 and IL-9 were determined in organoid and T cell cultures. Claudin2/3 expression was studied by western blotting and bacterial translocation by FISH. Results We uncovered a significant expansion of IL-9- and PU.1-expressing mucosal Th9 cells in CRC patients, with particularly high levels in patients with colitis-associated neoplasias. PU.1(+) Th9 cells accumulated in experimental colorectal neoplasias. Deficiency of IL-9 or inactivation of PU.1 in T cells led to impaired tumour growth in vivo, suggesting a protumoral role of Th9 cells. In contrast, GATA3 inactivation did not affect Th9-mediated tumour growth. Mechanistically, IL-9 controls claudin2/3 expression and T cell-derived IL-6 production in colorectal tumours. IL-6 abrogated the anti-proliferative effects of IL-9 in epithelial organoids in vivo. IL-9-producing Th9 cells expand in CRC and control IL-6 production by T cells. Conclusions IL-9 is a crucial regulator of tumour growth in colitis-associated neoplasias and emerges as potential target for therapy.
CRIS-Team WoS Importer:2022-09-16

Public spirometry for primary prevention of COPD - Zirlik, Sabine; Wich, Christina; Frieser, Markus; Hildner, Kai; Kleye, Christin; Neurath, Markus; Fuchs, Florian S. (Journal of Evaluation in Clinical Practice, 2014)
The most effective action for primary prevention of chronic obstructive lung disease is smoking cessation early enough. In secondary prevention, smokers with airway obstruction were more likely to quit smoking. The aim of this study was to evaluate the impact of a public spirometry on smoking habits in terms of primary prevention.Spirometry with its medical analysis was offered to visitors of a local public event called 'Lange Nacht der Wissenschaften' ('Long night of sciences'). The impact of results on smoking habits was evaluated in all smokers with an anonymized questionnaire afterwards.Two hundred fifty-seven people with the median age of 30 years (interquartile range 22-46) were examined. Out of 44 current smokers (17.1%), only two individuals showed a prebronchodilator FEV1/forced vital capacity-value <0.7. Fourteen smokers stated to have an increased motivation to quit smoking whereas 28 smokers declared that their motivation to quit smoking was independent of spirometry result. These smokers were significantly younger (median age 28 vs. 40 years, P = 0.025) without differences in spirometry results or smoking habits.In an unselected population with a high amount of younger adults, normal spirometry did not show a short-term benefit for primary prevention of chronic obstructive lung disease in terms of increasing motivation to quit smoking.
EVALuna2:1869

Purple urine in a patient after recovery from a SARS-CoV-2 infection - Vetter, Marcel; Kaufmann, Matthias; Neurath, Markus; Kremer, Andreas (International Journal of Infectious Diseases, 2021)
CRIS-Team Scopus Importer:2021-04-02
Keywords: COVID-19; PUBS; Purple urine bag syndrome

Quantitative contrast-enhanced ultrasound for monitoring vedolizumab therapy in inflammatory bowel disease patients: a pilot study - Görtz, Rüdiger; Klett, Daniel; Wildner, Dane; Atreya, Raja; Neurath, Markus; Strobel, Deike (Acta Radiologica, 2018)
Background Microvascularization of the bowel wall can be visualized and quantified non-invasively by software-assisted analysis of derived time-intensity curves. Purpose To perform software-based quantification of bowel wall perfusion using quantitative contrast-enhanced ultrasound (CEUS) according to clinical response in patients with inflammatory bowel disease treated with vedolizumab. Material and Methods In a prospective study, in 18 out of 34 patients, high-frequency ultrasound of bowel wall thickness using color Doppler flow combined with CEUS was performed at baseline and after 14 weeks of treatment with vedolizumab. Clinical activity scores at week 14 were used to differentiate between responders and non-responders. CEUS parameters were calculated by software analysis of the video loops. Results Nine of 18 patients (11 with Crohn's disease and seven with ulcerative colitis) showed response to treatment with vedolizumab. Overall, the responder group showed a significant decrease in the semi-quantitative color Doppler vascularization score. Amplitude-derived CEUS parameters of mural microvascularization such as peak enhancement or wash-in rate decreased in responders, in contrast with non-responders. Time-derived parameters remained stable or increased during treatment in all patients. Conclusion Analysis of bowel microvascularization by CEUS shows statistically significant changes in the wash-in-rate related to response of vedolizumab therapy.
EVALuna2:35140

Quantitative perfusion analysis in pancreatic contrast enhanced ultrasound (DCE-US): a promising tool for the differentiation between autoimmune pancreatitis and pancreatic cancer - Vitali, Francesco; Pfeifer, Lukas; Janson, C.; Görtz, Rüdiger; Neurath, Markus; Strobel, Deike; Wildner, Dane (Zeitschrift für Gastroenterologie, 2015)
In the work-up of focal pancreatic lesions autoimmune pancreatitis (AIP) is a rare differential diagnosis to pancreatic cancer (PC) with similar clinical constellations. The aim of our study was to compare differences between proven AIP and PC using transabdominal dynamic contrast enhanced ultrasound (DCE-US). Therefore we recorded 3-minute-clips of CEUS examinations and analyzed perfusion parameters with VueBox(®)-quantification software. To obtain DCE-US Parameters, Regions-of-Interest were selected within the lesions and the surrounding pancreas parenchyma, serving as reference tissue. We compared 3 patients with AIP (mean age: 58 years; lesion mean size: 40 mm) to 17 patients with PC (mean age: 68 years; lesion mean size: 35.9 mm). Significant differences between PC and parenchyma could be found in the following parameters: Peak-Enhancement (PE), Wash-in-and-Wash-out-AUC, Wash-in Perfusion-Index. PE of AIP was comparable to normal parenchyma. The relation of PE between parenchyma and lesion (?PE) AIP and PC was significantly different [AIP: 0.21 (± 0.06); PC: 0.81 (± 0.1); p < 0.01]. PE of neoplastic lesions was significantly lower as AIP and normal parenchyma (p < 0.01). Therefore perfusion analysis in DCE-US can help to differentiate hypovascular PC from AIP presenting nearly isovascular time intensity curves. Diagnostic accuracy of DCE-US in this setting has to be validated in future prospective studies in comparison to CT and MRI.
EVALuna2:1985

QuickView video preview software of colon capsule endoscopy: reliability in presenting colorectal polyps as compared to normal mode reading - Farnbacher, Michael J.; Krause, Horst H.; Hagel, Alexander; Raithel, Martin; Neurath, Markus; Schneider, Thomas (Scandinavian Journal of Gastroenterology, 2014)
OBJECTIVE. Colon capsule endoscopy (CCE) proved to be highly sensitive in detection of colorectal polyps (CP). Major limitation is the time-consuming video reading. The aim of this prospective, double-center study was to assess the theoretical time-saving potential and its possible impact on the reliability of "QuickView" (QV), in the presentation of CP as compared to normal mode (NM). METHODS. During NM reading of 65 CCE videos (mean patient´s age 56 years), all frames showing CPs were collected and compared to the number of frames presented by QV at increasing QV settings (10, 20, ... 80%). Reliability of QV in presenting polyps <6 mm and >=6 mm (significant polyp), and identifying patients for subsequent therapeutic colonoscopy, capsule egestion rate, cleansing level, and estimated time-saving potential were assessed. RESULTS. At a 30% QV setting, the QV video presented 89% of the significant polyps and 86% of any polyps with >=1 frame (per-polyp analysis) identified in NM before. At a 10% QV setting, 98% of the 52 patients with significant polyps could be identified (per-patient analysis) by QV video analysis. Capsule excretion rate was 74% and colon cleanliness was adequate in 85%. QV´s presentation rate correlates to the QV setting, the polyp size, and the number of frames per finding. CONCLUSIONS. Depending on its setting, the reliability of QV in presenting CP as compared to NM reading is notable. However, if no significant polyp is presented by QV, NM reading must be performed afterwards. The reduction of frames to be analyzed in QV might speed up identification of candidates for therapeutic colonoscopy.
EVALuna2:1915

Rapid single-cell physical phenotyping of mechanically dissociated tissue biopsies - Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Lopez Posadas, Rocío; Pradhan, Rashmita; Thoma, Oana-Maria; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Waldner, Maximilian; Distler, Jörg; Scheuermann, Stefan; Langejuergen, Jens; et al. (Nature Biomedical Engineering, 2023)
A method for the sequential assessment of the physical phenotypes of suspended cells singularized from tissue biopsies by mechanical dissociation allows for rapid diagnoses.
CRIS-Team WoS Importer:2023-05-05

Raster-Scanning Optoacoustic Mesoscopy for Gastrointestinal Imaging at High Resolution - Knieling, Ferdinand; Menezes, Jean Gonzales; Claussen, Jing; Schwarz, Mathias; Neufert, Clemens; Fahlbusch, Fabian B.; Rath, Timo; Thoma, Oana-Maria; Kramer, Viktoria; Menchicchi, Bianca; Kersten, Christina; Scheibe, Kristina; et al. (Gastroenterology, 2018)
EVALuna2:33792

Rationale for IL-36 receptor antibodies in ulcerative colitis - Neufert, Clemens; Neurath, Markus; Atreya, Raja (Expert Opinion on Biological Therapy, 2019)
CRIS-Team Scopus Importer:2019-12-10
Keywords: IL-36; IL-36R; tissue remodeling; ulcerative colitis

Real Life Study of Lenvatinib Therapy for Hepatocellular Carcinoma: RELEVANT Study - Casadei-Gardini, Andrea; Rimini, Margherita; Kudo, Masatoshi; Shimose, Shigeo; Tada, Toshifumi; Suda, Goki; Goh, Myung Ji; Jefremow, Andre; Scartozzi, Mario; Cabibbo, Giuseppe; Campani, Claudia; Tamburini, Emiliano; et al. (Liver Cancer, 2022)
Introduction: In the REFLECT trial, lenvatinib was found to be noninferior compared to sorafenib in terms of overall survival. Here, we analyze the effects of lenvatinib in the real-life experience of several centers across the world and identify clinical factors that could be significantly associated with survival outcomes. Methods: The study population was derived from retrospectively collected data of HCC patients treated with lenvatinib. The overall cohort included western and eastern populations from 23 center in five countries. Results: We included 1,325 patients with HCC and treated with lenvatinib in our analysis. Median OS was 16.1 months. Overall response rate was 38.5%. Multivariate analysis for OS highlighted that HBsAg positive, NLR >3, and AST >38 were independently associated with poor prognosis in all models. Conversely, NAFLD/NASH-related etiology was independently associated with good prognosis. Median progression-free survival was 6.3 months. Multivariate analysis for progression-free survival revealed that NAFLD/NASH, BCLC, NLR, and AST were independent prognostic factors for progression-free survival. A proportion of 75.2% of patients suffered from at least one adverse effect during the study period. Multivariate analysis exhibited the appearance of decreased appetite grade ≥2 versus grade 0-1 as an independent prognostic factor for worse progression-free survival. 924 patients of 1,325 progressed during lenvatinib (69.7%), and 827 of them had a follow-up over 2 months from the beginning of second-line treatment. From first-line therapy, the longest median OS was obtained with the sequence lenvatinib and immunotherapy (47.0 months), followed by TACE (24.7 months), ramucirumab (21.2 months), sorafenib (15.7 months), regorafenib (12.7 months), and best supportive care (10.8 months). Conclusions: Our study confirms in a large and global population of patients with advanced HCC, not candidates for locoregional treatment the OS reported in the registration study and a high response rate with lenvatinib.
CRIS-Team Scopus Importer:2022-12-23
Keywords: ALBI; Hepatocellular carcinoma; Lenvatinib; Neutrophils to lymphocyte ratio; Nonalcoholic fatty liver disease; Nonalcoholic steatohepatitis; Outcome; Second line; Tyrosine kinase inhibitors

Real-time in vivo histologic examination using a probe-based endocytoscopy system for differentiating duodenal polyps - Neumann, Helmut; Kudo, S.; Vieth, M.; Neurath, Markus (Endoscopy, 2013)
CRIS-Team Scopus Importer:2025-03-05

Rear Window—What Can the Gut Tell Us About Long-COVID? - Leppkes, Moritz; Neurath, Markus (Gastroenterology, 2022)
CRIS-Team Scopus Importer:2022-08-05

Recording and Optimizing the Nutritional Behavior of oncological Patients by using a Smartphone App (OncoFood) - Orlemann, Till; Zenker, Björn; Reljic, Dejan; Meyer, Julia; Oberlaender, Jana; Herrmann, Hans Joachim; Eskofier, Björn; Neurath, Markus; Zopf, Yurdagül (2018)
EVALuna2:35184

Rectal Cancer Presenting with Absceding Infection Due to Fusobacterium nucleatum - Zundler, Sebastian; Mardin, Christian; Bertz, Simone; Vitali, Francesco; Strauss, Richard; Fürst, Julia; Neurath, Markus; Strobel, Deike (Pathogens, 2022)
Intestinal microbiota such as Fusobacterium nucleatum play an important role in the pathogenesis of colorectal cancer. Here, we describe the case of a 47-year-old patient presenting with endophthalmitis and a liver abscess due to Fusobacterium nucleatum that prompted the diagnosis of colorectal cancer as the most likely source of infection. This case highlights that colorectal cancer needs to be considered in patients with systemic infection with Fusobacterium nucleatum and colonoscopy should be performed.
CRIS-Team Scopus Importer:2022-11-04
Keywords: endophthalmitis; Fusobacterium nucleatum; liver abscess; rectal cancer

Rectal Delivery of a DNAzyme That Specifically Blocks the Transcription Factor GATA3 and Reduces Colitis in Mice - Popp, Vanessa; Gerlach, Katharina; Mott, Stefanie; Turowska, Agnieszka; Garn, Holger; Atreya, Raja; Lehr, Hans-Anton; Ho, I-Cheng; Renz, Harald; Weigmann, Benno; Neurath, Markus (Gastroenterology, 2017)
BACKGROUND & AIMS: GATA3 is a transcription factor that regulates T-cell production of cytokines. We investigated the role of GATA3 in development of colitis in mice. METHODS: We performed quantitative polymerase chain reaction and immunofluorescence analyses of colon tissues from patients with Crohn's disease (n = 61) or ulcerative colitis (UC, n = 74) or from patients without inflammatory bowel diseases (n = 22), to measure levels of GATA3. Colitis was induced by administration of oxazolone or 2,4,6-trinitrobenzenesulfonic acid to control mice, mice with T-cell-specific deletion of GATA3, and mice with deletion of tumor necrosis factor receptor (TNFR) 1 and TNFR2 (TNFR double knockouts); some mice were given a GATA3-specific DNAzyme (hgd40) or a control DNAzyme via intrarectal administration, or systemic injections of an antibody to TNF before or during sensitization and challenge phase of colitis induction. Colon tissues were collected and immunofluorescence and histochemical analyses were performed. Lamina propria mononuclear cells and T cells were isolated and analyzed by flow cytometry or cytokine assays. Colonic distribution of labeled DNAzyme and inflammation were monitored by in vivo imaging (endoscopy) of mice. RESULTS: Levels of GATA3 messenger RNA were higher in colon tissues from patients with UC, but not ileal Crohn's disease, than control tissues; levels of GATA3 correlated with levels of inflammatory cytokines (interleukin [IL] 9, IL17A, IL6, IL5, IL4, IL13, and TNF). We observed increased expression of GATA3 by lamina propria T cells from mice with colitis compared with controls. Mice with T-cell-specific deletion of GATA3 did not develop colitis and their colonic tissues did not produce inflammatory cytokines (IL6, IL9, or IL13). The DNAzyme hgd40 inhibited expression of GATA3 messenger RNA by unstimulated and stimulated T cells, and distributed throughout the inflamed colons of mice with colitis. Colon tissues from mice given hgd40 had reduced expression of GATA3 messenger RNA, compared with mice given a control DNAzyme. Mice given hgd40 did not develop colitis after administration of oxazolone or 2,4,6-trinitrobenzenesulfonic acid; lamina propria cells from these mice expressed lower levels of IL6, IL9, and IL13 than cells from mice given the control DNAzyme. Mini-endoscopic images revealed that hgd40 and anti-TNF reduced colon inflammation over 3 days; hgd40 reduced colitis in TNFR double-knockout mice. CONCLUSIONS: Levels of GATA3 are increased in patients with UC and correlate with production of inflammatory cytokines in mice and humans. A DNAzyme that prevents expression of GATA3 reduces colitis in mice, independently of TNF, and reduces levels of cytokines in the colon. This DNAzyme might be developed for treatment of patients with UC.
EVALuna2:33833

Recurrent Ileal Invagination in Crohn's Disease - Görtz, Rüdiger; Atreya, Raja; Neurath, Markus (Deutsches Ärzteblatt international, 2020)
CRIS-Team WoS Importer:2020-05-05

Reframing immune-mediated inflammatory diseases - Boutrid, Nada; Rahmoune, Hakim; Schett, Georg; McInnes, Iain; Neurath, Markus (New England Journal of Medicine, 2021)
We were surprised to find that celiac disease was not among the panel of disorders discussed by Schett et al. (Aug. 12 issue)1 in their review article on cytokines and immune-mediated inflammatory conditions. It is well established that cytokine release is at the core of the structural damage and subsequent clinical manifestations in celiac disease, and we note in particular the evolving role of interleukins (mainly interleukin-15).2 In fact, interleukin-15 has a crucial role in innate and adaptive immune responses and is overexpressed in various autoimmune conditions, including celiac disease.3 This interleukin-15 action is orchestrated by tumor necrosis factor α and implicates the innate lymphoid cells; these two components are involved in the celiac-immunomediated enteropathy and several extraintestinal manifestations of celiac disease.4 It is not surprising that numerous trials — including trials in animal models and clinical trials, notably the PRV-015 in Gluten-free Diet Non-responsive Celiac Disease (PROACTIVE) trial5 — are exploring the option of blocking interleukin-15 to decrease or resolve lesions caused by celiac disease.5
CRIS-Team Scopus Importer:2021-12-10

Reframing Immune-Mediated Inflammatory Diseases through Signature Cytokine Hubs - Schett, Georg; Mcinnes, Iain B.; Neurath, Markus (New England Journal of Medicine, 2021)
Immune-mediated inflammatory diseases (IMIDs) are a heterogeneous group of diseases characterized by chronic inflammation and organ damage. IMIDs were traditionally classified on the basis of the predominant organ involvement. Improving the pathogenic characterization of IMIDs, however, should allow for a refined mechanistic understanding of these diseases and should make it possible to develop a molecular-based classification. The transition from organ-based to molecular-based classification was initiated by insights into associated genetic mutations and polymorphisms of key immune pathways and the development of monoclonal antibodies that target signature cytokine hubs in IMIDs. As compared with an organ-based classification, molecular classification better addresses pathophysiological commonalities across IMIDs that affect different organs but also accounts for substantial mechanistic differences among IMIDs that affect the same organ (Fig. 1).
CRIS-Team Scopus Importer:2021-08-27

Regression of apoptosis-resistant colorectal tumors by induction of necroptosis in mice - He, Gui-Wei; Günther, Claudia; Thonn, Veronika; Yu, Yu-Qiang; Martini, Eva; Buchen, Barbara; Neurath, Markus; Stürzl, Michael; Becker, Christoph (Journal of Experimental Medicine, 2017)
Cancer cells often acquire capabilities to evade cell death induced by current chemotherapeutic treatment approaches. Caspase-8, a central initiator of death receptor-mediated apoptosis, for example, is frequently inactivated in human cancers via multiple mechanisms such as mutation. Here, we show an approach to overcome cell death resistance in caspase-8-deficient colorectal cancer (CRC) by induction of necroptosis. In both a hereditary and a xenograft mouse model of caspase-8-deficient CRC, second mitochondria-derived activator of caspase (SMAC) mimetic treatment induced massive cell death and led to regression of tumors. We further demonstrate that receptor-interacting protein kinase 3 (RIP3), which is highly expressed in mouse models of CRC and in a subset of human CRC cell lines, is the deciding factor of cancer cell susceptibility to SMAC mimetic-induced necroptosis. Thus, our data implicate that it may be worthwhile to selectively evaluate the efficacy of SMAC mimetic treatment in CRC patients with caspase-8 deficiency in clinical trials for the development of more effective personalized therapy.
EVALuna2:15307

Regulation and pathophysiological role of epithelial turnover in the gut. - Günther, Claudia; Buchen, Barbara; Neurath, Markus; Becker, Christoph (Seminars in Cell & Developmental Biology, 2014)
Cell death in the intestinal epithelium has to be tightly controlled. Excessive or misplaced epithelial cell death can result in barrier dysfunction and, as a consequence thereof, uncontrolled translocation of components of the microbial flora from the lumen into the bowel wall. Susceptibility to gastrointestinal infections or chronic inflammation of the gut, as observed in patients with inflammatory bowel disease, can be the result of such dysregulation. Conversely, defects in cell death initiation might lead to an irregular accumulation of epithelial cells and cause intestinal cancer development. Until recently, activation of caspases in the intestinal epithelium was considered as a potential contributor to barrier dysfunction and as a pathogenic factor in the development of intestinal inflammation. Thus blocking of caspases appeared to be a potential therapeutic option for patients with inflammatory bowel disease. Recent studies on necroptosis however demonstrated that also inhibition of caspases can cause barrier dysfunction and intestinal inflammation. Caspase-8 on top of its functions in the extrinsic apoptosis pathway also controls necroptosis and turns out to be an essential molecule in regulating tissue homeostasis in the gut. Epithelial caspase-8 therefore emerges as a checkpoint not only of cell survival and cell death, but also as a regulator of the mode of cell death. According to this model, both excessive activity as well as a lack of activity of caspase-8 results in epithelial cell death and intestinal inflammation and caspase-8 needs to be tightly controlled to warrant tissue homeostasis in the gut.
Keywords: Inflammation; Necroptosis; Ripoptosome

Regulation of Human Innate Lymphoid Cells in the Context of Mucosal Inflammation - Schulz-Kuhnt, Anja; Wirtz, Stefan; Neurath, Markus; Atreya, Imke (Frontiers in Immunology, 2020)
Since their identification as a unique cell population, innate lymphoid cells (ILCs) have revolutionized our understanding of immune responses, leaving their impact on multiple inflammatory and fibrotic pathologies without doubt. Thus, a tightly controlled regulation of local ILC numbers and their activity is of crucial importance. Even though this has been extensively studied in murine ILCs in the last few years, our knowledge of human ILCs is still lagging behind. Our review article will therefore summarize recent insights into the function of human ILCs and will particularly focus on their regulation under inflammatory conditions. The quality and intensity of ILC involvement into local immune responses at mucosal sites of the human body can potentially be modulated via three different axes: (1) activation of tissue-resident mature ILCs, (2) plasticity and local transdifferentiation of specific ILC subsets, and (3) tissue migration and accumulation of peripheral ILCs. Despite a still ongoing scientific effort in this field, already existing data on the fate of human ILCs under different pathologic conditions clearly indicate that all three of these mechanisms are of relevance for the clinical course of chronic inflammatory and autoimmune diseases and might likewise provide new target structures for future therapeutic strategies.
CRIS-Team Scopus Importer:2020-07-17
Keywords: cytokine; human immune system; ILC plasticity; innate lymphoid cells; mucosal inflammation; tissue migration

Residual homing of alpha 4 beta 7-expressing beta 1(+)PI16(+) regulatory T cells with potent suppressive activity correlates with exposure-efficacy of vedolizumab - Becker, Emily; Dedden, Mark; Gall, Christine; Wiendl, Maximilian; Ekici, Arif Bülent; Schulz-Kuhnt, Anja; Schweda, Anna; Bosch-Voskens, Caroline; Hegazy, Ahmed; Vitali, Francesco; Atreya, Raja; Müller, Tanja; et al. (Gut, 2021)
Objective The anti-alpha 4 beta 7 integrin antibody vedolizumab is administered at a fixed dose for the treatment of IBDs. This leads to a wide range of serum concentrations in patients and previous studies had suggested that highest exposure levels are associated with suboptimal clinical response. We aimed to determine the mechanisms underlying these non-linear exposure-efficacy characteristics of vedolizumab. Design We characterised over 500 samples from more than 300 subjects. We studied the binding of vedolizumab to T cells and investigated the functional consequences for dynamic adhesion, transmigration, gut homing and free binding sites in vivo. Employing single-cell RNA sequencing, we characterised alpha 4 beta 7 integrin-expressing T cell populations 'resistant' to vedolizumab and validated our findings in vitro and in samples from vedolizumab-treated patients with IBD. We also correlated our findings with a post-hoc analysis of the Gemini II and III studies. Results Regulatory T (T-Reg) cells exhibited a right-shifted vedolizumab binding profile compared with effector T (T-Eff) cells. Consistently, in a certain concentration range, the residual adhesion, transmigration, homing of and availability of functional alpha 4 beta 7 on T-Reg cells in vivo was higher than that of/on T-Eff cells. We identified a vedolizumab-'resistant' alpha 4 beta 7-expressing beta 1(+)PI16(+) T-Reg cell subset with pronounced regulatory properties as the substrate for this effect. Our observations correlated with exposure-efficacy data from Gemini II and III trials. Conclusion Completely blocking T-Eff cell trafficking with vedolizumab, while simultaneously permitting residual homing of powerful T-Reg cells in an optimal 'therapeutic window' based on target exposure levels might be a strategy to optimise treatment outcomes in patients with IBD.
CRIS-Team WoS Importer:2021-12-10

Resolution of acute intestinal graft-versus-host disease - Thiagarajan, Sindhu; Neurath, Markus; Hildner, Kai (Seminars in Immunopathology, 2019)
Allogeneic transplantation of hematopoietic stem cells (allo-HCT) represents an increasingly employed therapeutic approach to potentially cure patients suffering from life-threatening malignant and autoimmune disorders. Despite its lifesaving potential, immune-mediated allo-reactivity inherent to the allogeneic transplantation can be observed within up to 50% of all allo-HCT patients regularly resulting in the manifestation of acute and/or chronic graft-versus-host disease (GvHD). Mechanistically, especially donor T cells are assumed to chiefly drive inflammation that can occur in virtually all organs, with the skin, liver, and gut representing as the most frequently affected anatomic sites. Especially in the presence of intestinal manifestations of GvHD, the risk that the disease takes a life-threatening, potentially fatal course is significantly increased. In the light of a rapid gain of knowledge in respect to decode innate and adaptive immunity related mechanisms as, e.g., cytokine networks, intracellular signaling pathways or environmental triggers as, e.g., the intestinal microbiota and the development of novel therapeutic approaches, detailed insight into endogenous mechanisms seeking to counterbalance the proinflammatory machinery or to proactively foster signals promoting the resolution of allo-driven intestinal inflammation is emerging. Here, we seek to highlight the key aspects of those mechanisms involved in and contributing to the resolution of GvHD-associated intestinal inflammation. Concomitantly, we would like to briefly outline and discuss promising future experimental targets suitable to be therapeutically employed to directionally deflect the tissue response from a proinflammatory to an inflammation-resolving type of intestinal GvHD after allo-HCT.
CRIS-Team WoS Importer:2019-11-15

Resolution of chronic inflammatory disease: universal and tissue-specific concepts - Schett, Georg; Neurath, Markus (Nature Communications, 2018)
Inflammation and its resolution is under-studied in medicine despite being essential for understanding the development of chronic inflammatory disease. In this review article, we discuss the resolution of inflammation in both a biological and translational context. We introduce the concept of impaired resolution leading to diseases like rheumatoid arthritis, Crohn's disease, and asthma, as well as the cellular and molecular components that contribute to resolution of joint, gut, and lung inflammation, respectively. Finally, we discuss potential intervention strategies for fostering the resolution process, and their implications for the therapy of inflammatory diseases.
EVALuna2:34476

Resolution of Crohn’s disease - Schmitt, Heike; Neufert, Clemens; Neurath, Markus; Atreya, Raja (Seminars in Immunopathology, 2019)
Crohn’s disease (CD) is characterized by chronic inflammation of the gastrointestinal tract and represents one of the main inflammatory bowel disease (IBD) forms. The infiltration of immune cells into the mucosa and uncontrolled production of pro-inflammatory cytokines and other mediators trigger the chronic inflammatory reaction in the intestine [1]. The inflammatory setting consists of subsequent events that comprise an induction phase, the peak of inflammation which is subsequently followed by the resolution phase. The induction phase, which represents the first phase of inflammation, is important for the rapid and efficient activation of the immune system for sufficient host defense. The permanent sensing of exogenous or endogenous danger signals enables the fast initiation of the inflammatory reaction. The immune cell infiltrate initiates an inflammatory cascade where released lipid and protein mediators play an indispensable role [2, 3]. The last decades of research strongly suggest that resolution of inflammation is similarly a tightly coordinated and active process. The basic concept that resolution of inflammation has to be regarded as an active process has been thoroughly described by others [4–6]. The following review focuses on mechanisms, pathways, and specific mediators that are actively involved in the resolution of inflammation in CD.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Anti-TNF therapy; Apoptosis; Crohn’s disease; IL23; Intestine; Resolution of inflammation

Resolution of inflammation by interleukin-9-producing type 2 innate lymphoid cells - Rauber, Simon; Luber, Markus; Weber, Stefanie; Maul, Lisa; Soare, Alina; Wohlfahrt, Thomas; Lin, Neng-Yu; Dietel, Katharina; Bozec, Aline; Herrmann, Martin; Kaplan, Mark H.; Weigmann, Benno; et al. (Nature Medicine, 2017)
Inflammatory diseases such as arthritis are chronic conditions that fail to resolve spontaneously. While the cytokine and cellular pathways triggering arthritis are well defined, those responsible for the resolution of inflammation are incompletely characterized. Here we identified interleukin (IL)-9-producing type 2 innate lymphoid cells (ILC2s) as the mediators of a molecular and cellular pathway that orchestrates the resolution of chronic inflammation. In mice, the absence of IL-9 impaired ILC2 proliferation and activation of regulatory T (Treg) cells, and resulted in chronic arthritis with excessive cartilage destruction and bone loss. In contrast, treatment with IL-9 promoted ILC2-dependent Treg activation and effectively induced resolution of inflammation and protection of bone. Patients with rheumatoid arthritis in remission exhibited high numbers of IL-9(+) ILC2s in joints and the circulation. Hence, fostering IL-9-mediated ILC2 activation may offer a novel therapeutic approach inducing resolution of inflammation rather than suppression of inflammatory responses.
EVALuna2:13255

Resolution of inflammation: from basic concepts to clinical application - Neurath, Markus (Seminars in Immunopathology, 2019)
CRIS-Team Scopus Importer:2019-12-10

Resolution of ulcerative colitis - Neurath, Markus; Leppkes, Moritz (Seminars in Immunopathology, 2019)
Ulcerative colitis designates an idiopathic chronic inflammatory bowel disease leading to bloody diarrhea and inflammatory alterations mostly restricted to the large intestine. Many studies continue to unravel important aspects of its etiopathogenesis, and recent pharmaceutical developments broaden the arsenal of therapeutic opportunity. In this review, we delve into the cellular and molecular determinants of successful resolution of ulcerative colitis, describing novel insights in each of the phases of mucosal healing starting from damaging insults to the mucosa, epithelial restitution, and its adaption to inflammation as well as lymphocyte-driven maintenance and resolution of chronic inflammation. Additionally, molecular switches from inflammation to resolution are explored, paving the way for future avenues to resolve ulcerative colitis.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Epithelium; Intestine; Lymphocytes; Resolution of inflammation; Ulcerative colitis

Retrograde inspection vs standard forward view for the detection of colorectal adenomas during colonoscopy: A back-to-back randomized clinical trial - Rath, Timo; Pfeifer, Lukas; Neufert, Clemens; Kremer, Andreas; Leppkes, Moritz; Hoffman, Arthur; Neurath, Markus; Zopf, Steffen (World Journal of Gastroenterology, 2020)
BACKGROUND: The adenoma detection rate (ADR) is inversely associated with the incidence of interval colorectal cancer and serves as a benchmark quality criterion during screening colonoscopy. However, adenoma miss rates reach up to 26% and studies have shown that a second inspection of the right colon in retroflected view (RFV) can increase ADR. AIM: To assess whether inspection of the whole colon in RFV compared to standard forward view (SFV) can increase ADR. METHODS: Patients presenting for screening or surveillance colonoscopy were invited to participate in this randomized controlled trial and randomized into two arms. In RFV arm colonoscopy was initially performed with SFV, followed by a second inspection of the whole colon in RFV. In the SFV arm first withdrawal was performed with SFV, followed by a second inspection of the whole colon again with SFV. Number, size and morphology of polyps found during first and second inspection in each colonic segment were recorded and all polyps were removed and sent for histopathology in separate containers. RESULTS: Two hundred and five patients were randomly assigned to the RFV (n = 101) and SFV (n = 104) arm. In the RFV arm, both polyp detection rate (PDR) and ADR were increased under second inspection in RFV (PDR 1st SFV: 39.8%, PDR 2nd RFV: 46.6%; ADR 1st SFV: 35.2%, ADR 2nd RFV: 42%). Likewise, in the SFV arm, PDR and ADR were increased under second inspection (PDR 1st SFV: 37.5%, PDR 2nd SFV: 46.6%; ADR 1st SFV: 34.1%, ADR 2nd SFV: 44.3%) with no significant differences in ADR and PDR between the SFV and RFV arm. Mean number of adenomas per patient (APP) was increased in the RFV and SFV (APP RFV arm: 1st SFV: 1.71; 2nd RFV: 2.38; APP SFV arm: 1st SFV: 1.83, 2nd SFV:2.2). The majority of adenomas additionally found during second inspection in RFV or in SFV were located in the transverse and left-sided colon and were > 5 mm in size. CONCLUSION: Second inspection of the whole colon leads to increased adenoma detection with no differences between SFV and RFV. Hence, increased detection is most likely a feature of the second inspection itself but not of the inspection mode.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Adenoma; Adenoma detection rate; Colonoscopy; Colorectal cancer

Reverse switching from the biosimilar SB2 to the originator infliximab in previously switched patients with inflammatory bowel diseases: results of a prospective long-term cohort study - Fischer, Sarah; Donhauser, Moritz; Cohnen, Sarah Ellen; Fietkau, Konstantin; Vetter, Marcel; Grübel-Liehr, Maria; Dietrich, Peter; Rath, Timo; Wilfer, Angelika; Sologub, Ludmilla; Krebs, Sabine; Dörje, Frank; et al. (Therapeutic Advances in Gastroenterology, 2024)
A clinical study investigating the interchangeability between infliximab, a previously patented biotechnological produced drug (biological) and its successor product biosimilar SB2, which is highly similar to the existing reference product, in the treatment of patients with inflammatory bowel diseases Why was the study done? Biological drugs (like infliximab) are produced using various methods under the involvement of biotechnology. In contrary to generic drugs, due to their complex structure, biosimilars are not exactly the same molecule as the original substance. After the introduction of biosimilars, which are mostly less expensive than the original product, concerns were raised regarding the interchangeability of these substances. This study was conducted to investigate potential changes in efficacy and safety after multiple, so called switches (from the original product to its biosimilar and back). What did the researchers do? The research team switched a group of 95 patients diagnosed with inflammatory bowel disease and therefore treated with the original biologic drug infliximab to the biosimilar SB2, reverse switched them back to the original drug after 96 weeks and observed the patients for another 48 weeks. During the observational phase the disease activity, drug levels and potential side effects were monitored. What did the researchers find? The initial and the reverse switch had no relevant impact on the course of disease and additionally no safety issues occurred. During the 48 weeks observational period, 14.7% of patients discontinued therapy, which was not out of the expected range. Most potential side effects were not considered to be therapy-associated and only 4 of 95 patients discontinued treatment due to safety concerns. The drug levels remained stable during the switches. What do the findings mean? In this study, the research team found no impact of multiple switches on the disease activity in inflammatory bowel disease patients and moreover no safety issues. These findings support the practice of switching between the biologic originator substance infliximab and its biosimilar

Review and Analysis of German Mobile Apps for Inflammatory Bowel Disease Management Using the Mobile Application Rating Scale: Systematic Search in App Stores and Content Analysis - Gerner, Maximilian; Vuillerme, Nicolas; Aubourg, Timothée; Messner, Eva Maria; Terhorst, Yannik; Hörmann, Verena; Ganzleben, Ingo; Schenker, Hannah; Schett, Georg; Atreya, Raja; Neurath, Markus; Knitza, Johannes; et al. (JMIR mHealth and uHealth, 2022)
Background: Patients suffering from inflammatory bowel disease (IBD) frequently need long-term medical treatment. Mobile apps promise to complement and improve IBD management, but so far there has been no scientific analysis of their quality. Objective: This study evaluated the quality of German mobile apps targeting IBD patients and physicians treating IBD patients using the Mobile Application Rating Scale (MARS). Methods: The German Apple App Store and Google Play Store were systematically searched to identify German IBD mobile apps for patient and physician use. MARS was used by 6 physicians (3 using Android smartphones and 3 using iPhones) to independently assess app quality. Apps were randomly assigned so that the 4 apps with the most downloads were rated by all raters and the remaining apps were rated by 1 Android and 1 iOS user. Results: In total, we identified 1764 apps in the Apple App Store and Google Play Store. After removing apps that were not related to IBD (n=1386) or not available in German (n=317), 61 apps remained. After removing duplicates (n=3) and apps for congresses (n=7), journals (n=4), and clinical studies (n=6), as well as excluding apps that were available in only 1 of the 2 app stores (n=20) and apps that could only be used with an additional device (n=7), we included a total of 14 apps. The app “CED Dokumentation und Tipps” had the highest overall median MARS score at 4.11/5. On the whole, the median MARS scores of the 14 apps ranged between 2.38/5 and 4.11/5. As there was no significant difference between iPhone and Android raters, we used the Wilcoxon comparison test to calculate P values. Conclusions: The MARS ratings showed that the quality of German IBD apps varied. We also discovered a discrepancy between app store ratings and MARS ratings, highlighting the difficulty of assessing perceived app quality. Despite promising results from international studies, there is little evidence for the clinical benefits of German IBD apps. Clinical studies and patient inclusion in the app development process are needed to effectively implement mobile apps in routine care.
CRIS-Team Scopus Importer:2022-05-20
Keywords: app store; chronic disease; Crohn disease; IBD; IBS; inflammatory bowel disease; mHealth; mobile apps; quality; rating; rating scale; telemedicine; ulcerative colitis; usability

Review article: In vivo imaging by endocytoscopy - Neumann, Helmut; Fuchs, Friederike; Vieth, M.; Atreya, Raja; Siebler, Jürgen; Kiesslich, R.; Neurath, Markus (Alimentary Pharmacology & Therapeutics, 2011)
Background Endocytoscopy (EC) enables in vivo microscopic imaging at 1400-fold magnification, thereby allowing the analysis of mucosal structures at the cellular level. In contrast to fluorescence imaging with confocal laser endomicroscopy which allows analysis of mucosal structures up to 250 μm in depth, EC is based on the principle of contact light microscopy and only allows visualisation of the very superficial mucosal layer. Aim To systematically review the feasibility and diagnostic yield of EC for in vivo diagnosis of diseases. Methods A systematic search of the literature on diagnostic interventions in the gastrointestinal tract using EC was performed by searches in MEDLINE, Current Contents, PubMed, cross-references and references from relevant articles using the search terms 'endocytoscopy', 'endocytoscope', 'magnification endoscopy', 'endocytoscopic imaging', 'virtual histology' and 'optical biopsy'. Only full manuscripts and case reports published in English were included. Results Overall twenty-nine relevant reports were identified. EC was feasible to detect oesophageal squamous cell cancer with sensitivity, specificity and accuracy of 95%, 84% and 82%, respectively. Moreover, EC reached excellent sensitivity and specificity for in vivo diagnosis of colon polyps (91% and 100%, respectively). Other diagnostic applications of EC included diagnosis of Barrett's oesophagus, Helicobacter pylori, coeliac disease and small cell lung cancer. No serious complications of EC have yet been reported. Conclusions Endocytoscopy is a safe and effective new endoscopic imaging technique to obtain in vivo histology and guided biopsies with high diagnostic accuracy. Therefore, endocytoscopy has the potential to facilitate both diagnosis and patient management. © 2011 Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2025-03-05

Rho GTPases as Key Molecular Players within Intestinal Mucosa and GI Diseases - Pradhan, Rashmita; Ngo, Phuong A.; Martínez Sánchez, Luz del Carmen; Neurath, Markus; Lopez Posadas, Rocío (Cells, 2021)
Rho proteins operate as key regulators of the cytoskeleton, cell morphology and trafficking. Acting as molecular switches, the function of Rho GTPases is determined by guanosine triphosphate (GTP)/guanosine diphosphate (GDP) exchange and their lipidation via prenylation, allowing their binding to cellular membranes and the interaction with downstream effector proteins in close proximity to the membrane. A plethora of in vitro studies demonstrate the indispensable function of Rho proteins for cytoskeleton dynamics within different cell types. However, only in the last decades we have got access to genetically modified mouse models to decipher the intricate regulation between members of the Rho family within specific cell types in the complex in vivo situation. Translationally, alterations of the expression and/or function of Rho GTPases have been associated with several pathological conditions, such as inflammation and cancer. In the context of the GI tract, the continuous crosstalk between the host and the intestinal microbiota requires a tight regulation of the complex interaction between cellular components within the intestinal tissue. Recent studies demonstrate that Rho GTPases play important roles for the maintenance of tissue homeostasis in the gut. We will summarize the current knowledge on Rho protein function within individual cell types in the intestinal mucosa in vivo, with special focus on intestinal epithelial cells and T cells.
CRIS-Team WoS Importer:2021-02-05

Rifaximin and Saccharomyces boulardii increase stress resilience in TNBS-induced colitis - Konturek, P.; Zopf, Yurdagül; Dieterich, Walburga; Wirtz, Stefan; Neurath, Markus; Brzozowski, T. (2018)
EVALuna2:34076

Risankizumab in patients with moderate to severe Crohn's disease: an open-label extension study - Feagan, Brian G.; Panes, Julian; Ferrante, Marc; Kaser, Arthur; D'Haens, Geert R.; Sandborn, William J.; Louis, Edouard; Neurath, Markus; Franchimont, Denis; Dewit, Olivier; Seidler, Ursula; Kim, Kyung-Jo; et al. (Lancet Gastroenterology and Hepatology, 2018)
BACKGROUND: Risankizumab, an anti-interleukin 23 antibody, was superior to placebo in achieving clinical and endoscopic remission at week 12 in a randomised, phase 2 induction study in patients with moderately to severely active Crohn's disease. Here we aimed to assess the efficacy and safety of extended intravenous induction and subcutaneous maintenance therapy with risankizumab. METHODS: All patients who completed the 12-week induction phase of the double-blind phase 2 induction study were included in this open-label extension study. Patients who did not achieve deep remission, defined as clinical remission (Crohn's Disease Activity Index [CDAI] <150) and endoscopic remission (Crohn's Disease Endoscopic Index of Severity [CDEIS] ≤4, or ≤2 for patients with isolated ileitis), at week 12 received open-label intravenous therapy with 600 mg risankizumab every 4 weeks for 12 weeks; patients in deep remission at week 12 entered a 12-week washout phase. Patients in clinical remission at week 26 were invited to participate in the maintenance phase of the study, in which they received open-label subcutaneous risankizumab (180 mg) every 8 weeks for 26 weeks. 26-week efficacy endpoints were the proportion of patients in clinical remission (CDAI <150), and the proportion of patients who achieved clinical response (either CDAI of <150 or a reduction from baseline of at least 100 points). 52-week efficacy endpoints were the proportion of patients achieving: clinical remission; clinical response; endoscopic response (>50% CDEIS reduction from baseline); endoscopic remission, as defined previously; mucosal healing; and deep remission. Safety was assessed in patients who received at least one dose of the study drug during the open-label phases of the study. This study is registered with ClinicalTrials.gov, number NCT02031276. FINDINGS: Of the 108 patients who completed the 12-week double-blind induction trial, six patients were in deep remission and entered the 12-week washout phase. 102 patients were not in deep remission, 101 of whom received 12 weeks of 600 mg risankizumab (33 from the original placebo group, 34 from the 200 mg risankizumab group, and 34 from the 600 mg risankizumab group); the other patient declined to continue the study. At week 26, 54 (53%) of 101 patients treated with 600 mg rizankizumab were in clinical remission. Among patients included in the open-label extension trial, clinical remission rates at week 26 versus week 12 were: 18 (55%) versus six (18%) of 33 patients in the original placebo group; 20 (59%) versus seven (21%) of 34 patients in the original 200 mg risankizumab group; and 16 (47%) versus nine (26%) of 34 patients in the original 600 mg risankizumab group. 62 patients received risankizumab maintenance treatment, including the 54 patients who achieved clinical remission at week 26, the six patients who had achieved deep remission at week 12, and one patient because of a protocol violation. At week 52, clinical remission was maintained in 44 (71%) patients; 50 (81%) patients had a clinical response, 22 (35%) patients were in endoscopic remission, and 34 (55%) patients had an endoscopic response. 15 (24%) patients had mucosal healing and 18 (29%) patients achieved deep remission at week 52. Risankizumab was well tolerated with no new safety signals noted. The most frequent treatment-emergent adverse events were arthralgia (25 [22%] of 115 patients), headache (23 [20%]), abdominal pain (21 [18%]), nasopharyngitis (18 [16%]), nausea (18 [16%]), and pyrexia (15 [13%]). Most adverse events were mild or moderate and considered to be unrelated to study treatment. There were no treatment-related deaths. INTERPRETATION: Extended induction treatment with open-label intravenous risankizumab was effective in increasing clinical response and remission rates at week 26. Open-label subcutaneous risankizumab maintained remission until week 52 in most patients who were in clinical remission at week 26. Selective blockade of interleukin 23 warrants further investigation as a treatment for Crohn's disease. FUNDING: Boehringer Ingelheim.
EVALuna2:35139

Risk factors associated with complications of palliative drainage of ascites with tunneled peritoneal catheters - Machnik, Domenique; Fischer, Sarah; Vetter, Marcel; Lamprecht-Bailer, Ricarda; Rouse-Merkel, Rachel; Klett, Daniel; Neurath, Markus; Strobel, Deike; Zundler, Sebastian; Haberkamp, Sophie (Therapeutic Advances in Gastroenterology, 2025)
Background: Medically intractable ascites causes substantial distress in patients with palliative disease. Tunneled peritoneal catheters have been established as a feasible treatment option allowing patient-controlled paracentesis in a homecare setting. However, while a range of complications is associated with these drainages, risk factors for complications have not been identified so far. Objectives: To explore potential risk factors associated with complications of tunneled peritoneal catheters. Design: Retrospective observational cohort study. Methods: Single-center cohort comprising 49 patients with palliative disease receiving 57 tunneled peritoneal catheters at a tertiary care hospital. Results: Catheter placement was successful in all patients and associated with low numbers of severe complications. Our data suggest a higher risk for severe late complications in patients with benign disease, with drainage replacement, and when performed by less experienced physicians. Conclusion: Tunneled peritoneal catheters are an effective and safe option to treat symptomatic ascites in patients with end-stage palliative disease. The indication should be carefully considered in patients with benign disease and after removal or dislocation of a previous catheter.
CRIS-Team Scopus Importer:2025-01-31
Keywords: ascites; palliative care; peritoneal carcinomatosis; tunneled peritoneal catheter

Role of the IL23/IL17 Pathway in Crohn’s Disease - Schmitt, Heike; Neurath, Markus; Atreya, Raja (Frontiers in Immunology, 2021)
Crohn’s disease (CD) is a chronic relapsing disorder of the gastrointestinal tract and represents one of the main entities of inflammatory bowel disease (IBD). CD affects genetically susceptible patients that are influenced by environmental factors and the intestinal microbiome, which results in excessive activation of the mucosal immune system and aberrant cytokine responses. Various studies have implicated the pro-inflammatory cytokines IL17 and IL23 in the pathogenesis of CD. IL23 is a member of the IL12 family of cytokines and is able to enhance and affect the expansion of pathogenic T helper type 17 (Th17) cells through various mechanisms, including maintenance of Th17 signature genes, upregulation of effector genes or suppression of repressive factors. Moreover, IL17 and IL23 signaling is able to induce a cascade of pro-inflammatory molecules like TNF, IFNγ, IL22, lymphotoxin, IL1β and lipopolysaccharide (LPS). Here, IL17A and TNF are known to mediate signaling synergistically to drive expression of inflammatory genes. Recent advances in understanding the immunopathogenetic mechanisms underlying CD have led to the development of new biological therapies that selectively intervene and inhibit inflammatory processes caused by pro-inflammatory mediators like IL17 and IL23. Recently published data demonstrate that treatment with selective IL23 inhibitors lead to markedly high response rates in the cohort of CD patients that failed previous anti-TNF therapy. Macrophages are considered as a main source of IL23 in the intestine and are supposed to play a key role in the molecular crosstalk with T cell subsets and innate lymphoid cells in the gut. The following review focuses on mechanisms, pathways and specific therapies in Crohn’s disease underlying the IL23/IL17 pathway.
CRIS-Team Scopus Importer:2021-04-23
Keywords: anti-TNF therapy; Crohn’s disease; IL17/IL23 axis; inflammation; intestinal immunity; non-responder; resistance to apoptosis

Role of the IL-2 inducible tyrosine kinase ITK and its inhibitors in disease pathogenesis - Lechner, Kristina S.; Neurath, Markus; Weigmann, Benno (Journal of Molecular Medicine, 2020)
ITK (IL-2-inducible tyrosine kinase) belongs to the Tec family kinases and is mainly expressed in T cells. It is involved in TCR signalling events driving processes like T cell development as well as Th2, Th9 and Th17 responses thereby controlling the expression of pro-inflammatory cytokines. Studies have shown that ITK is involved in the pathogenesis of autoimmune diseases as well as in carcinogenesis. The loss of ITK or its activity either by mutation or by the use of inhibitors led to a beneficial outcome in experimental models of asthma, inflammatory bowel disease and multiple sclerosis among others. In humans, biallelic mutations in the ITK gene locus result in a monogenetic disorder leading to T cell dysfunction; in consequence, mainly EBV infections can lead to severe immune dysregulation evident by lymphoproliferation, lymphoma and hemophagocytic lymphohistiocytosis. Furthermore, patients who suffer from angioimmunoblastic T cell lymphoma have been found to express significantly more ITK. These findings put ITK in the strong focus as a target for drug development.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Autoimmune diseases; Cancer; Inhibitor; ITK

Safety and efficacy of intravenous cyclophosphamide pulse therapy in therapy refractory Crohn's disease patients - Hirschmann, S; Atreya, Raja; Englbrecht, Matthias; Neurath, Markus (Journal of Physiology and Pharmacology, 2017)
A major challenge in the management of persistently active Crohn's disease patient's refractory to treatment regimen following the current guidelines is the induction of remission, which is a prerequisite for subsequent maintenance therapy. The aim of this study was to evaluate both the clinical and endoscopic benefit of intravenous cyclophosphamide pulse therapy in patients with active and therapy refractory Crohn's disease. Nine patients with acute moderate to severe Crohn's disease, not responding to conventional as well as biological therapy regimen received 3 - 9 cycles of monthly treatments with intravenous cyclophosphamide (680 - 1000 mg) in an uncontrolled setting and were retrospectively analyzed. Eight of nine patients (88.9%) had a clinical response (measured by a decrease in the Harvey-Bradshaw index, HBI >= 3) and two of nine patients (22.2%) achieved clinical remission (HBI <= 4) at week 8 after two applications of intravenous cyclophosphamide therapy. These response and remission rates remained unchanged after individual completion of cyclophosphamide therapy. Median HBI decreased from 18 (7 - 25) at the beginning of therapy to 7 (3 - 18) at week 8. 5 of 9 patients (56%) showed endoscopic response (defined by a reduction of ulcers) and one patient (11%) reached endoscopic remission (defined by the absence of ulcers) after the last application of cyclophosphamide. Arthralgia, which was present in 4 of 9 (44%) patients, was unchanged in most patients after cyclophosphamide therapy, although one patient described a marked reduction in joint pain. Cyclophosphamide pulse therapy was well tolerated during the whole treatment course in all subjects. One patient with long-standing Crohn's disease was diagnosed with a high-grade intraepithelial neoplasia in the rectum and underwent surgical intervention, where the diagnosis of an early stage adenocarcinoma was made. We concluded that intravenous cyclophosphamide pulse therapy was well tolerated by most patients and effective for inducing clinical and endoscopic response and remission in patients with therapy refractory Crohn's disease. In patients who are unresponsive to available therapies, including available biological treatment options, cyclophosphamide therefore represents a potential option to induce therapeutic response, which must then be maintained by other treatment modalities.
EVALuna2:13423

Safety and tolerability of a single infusion of autologous ex vivo expanded regulatory T cells in adults with ulcerative colitis (ER-TREG 01): protocol of a phase 1, open-label, fast-track dose-escalation clinical trial - Voskens, Caroline; Stoica, Diane; Roessner, Susanne; Vitali, Francesco; Zundler, Sebastian; Rosenberg, Marita; Wiesinger, Manuel; Wunder, Jutta; Siegmund, Britta; Schuler-Thurner, Beatrice; Schuler, Gerold; Berking, Carola; et al. (BMJ Open, 2021)
Introduction Accumulating evidence suggests that the adoptive transfer of ex vivo expanded regulatory T cells (Treg) may overcome colitogenic immune responses in patients with inflammatory bowel diseases. The objective of the ER-TREG 01 trial is to assess safety and tolerability of a single infusion of autologous ex vivo expanded Treg in adults with ulcerative colitis.
CRIS-Team WoS Importer:2021-12-24

SARS-CoV-2 Virus Manifestations in the Gastrointestinal Tract: Therapeutic Implications - Jefremow, Andre; Neurath, Markus (Visceral Medicine, 2020)
Background: About 1 year ago a novel virus - SARS-CoV-2 - began to spread around the world. It can lead to the disease COVID-19, which has caused more than 1 million deaths already. Summary: While it was first recognized as a disease leading to pneumonia and lung failure, we know by now that COVID-19 is more complex. COVID-19 is a systemic hyperinflammatory disease affecting not only the lungs, but also many other organs. Especially the gastrointestinal (GI) tract is often involved in COVID-19. Key Messages: This review provides an overview of the different affected organs of the GI tract and offers information on how gastroenterologists should take care of their patients with different GI disorders.
CRIS-Team WoS Importer:2020-12-11

Segment-Based Spotting of Bowel Sounds Using Pretrained Models in Continuous Data Streams - Baronetto, Annalisa; Graf, Luisa; Fischer, Sarah; Neurath, Markus; Amft, Oliver (IEEE journal of biomedical and health informatics, 2023)
We analyse pretrained and non-pretrained deep neural models to detect 10-seconds Bowel Sounds (BS) audio segments in continuous audio data streams. The models include MobileNet, EfficientNet, and Distilled Transformer architectures. Models were initially trained on AudioSet and then transferred and evaluated on 84 hours of labelled audio data of eighteen healthy participants. Evaluation data was recorded in a semi-naturalistic daytime setting including movement and background noise using a smart shirt with embedded microphones. The collected dataset was annotated for individual BS events by two independent raters with substantial agreement (Cohen's Kappa κ =0.74). Leave-One-Participant-Out cross-validation for detecting 10-second BS audio segments, i.e. segment-based BS spotting, yielded a best F1 score of 73% and 67%, with and without transfer learning respectively. The best model for segment-based BS spotting was EfficientNet-B2 with an attention module. Our results show that pretrained models could improve F1 score up to 26%, in particular, increasing robustness against background noise. Our segment-based BS spotting approach reduces the amount of audio data to be reviewed by experts from 84 h to 11 h, thus by 87%.
CRIS-Team Scopus Importer:2023-06-02
Keywords: audio tagging; Bowel sound detection; Convolution; Data models; deep learning; Feature extraction; Neural networks; Recording; Training; transfer learning; Transfer learning

Seroprevalence of SARS-CoV2 in IBD patients treated with biologic therapy - Berte, Roberto; Mazza, Stefano; Stefanucci, Marta Rachele; Noviello, Daniele; Costa, Stefania; Ciafardini, Clorinda; Mileti, Erika; Mapelli, Marina; Pasqualato, Sebastiano; Pinto, Sergio; Favale, Agnese; Vecchi, Maurizio; et al. (Journal of Crohns & Colitis, 2021)
Background and Aims: A similar course of COVID-19 in patients with inflammatory bowel diseases [IBD] and in the general population has been reported. However, disease prevalence in IBD patients is presently unknown. In this prospective observational study, we aimed at determining SARS-CoV2 infection prevalence in IBD patients treated with biologic therapy. Methods: From IBD patients under biologic therapy and recruited from three different locations in Italy and Germany, 354 sera were evaluated for antibody presence by RBD ELISA. Control groups were: i] age-matched healthy subjects tested in the same time period in Milan, Italy; ii] healthy subjects collected in the pre-COVID era; iii] IBD patients under biologic therapy collected in the pre-COVID era. Results: Eight out of 354 patients tested positive for the anti-RBD-SARS-CoV2 IgG antibody [prevalence 2.3%]. The percentage of IgG-positive patients among those recruited from Milan was significantly higher than among those recruited from other locations [prevalence 5.4% vs 0.4%, p<0.005]. IgG-positive patients reported a significantly higher incidence of fever, anosmia, and ageusia, and were more likely to have entered into close contact with COVID-19-positive subjects before the study enrolment. Conclusions: Seroprevalence of SARS-CoV2 in IBD patients treated with biologic therapy reflects values measured in the local general population. Specific symptoms and contact history with SARS-CoV2-infected individuals strongly increase the likelihood of SARS-CoV2 seropositivity.
CRIS-Team Scopus Importer:2021-06-04
Keywords: anti-SARS-CoV2 antibodies; COVID-19; IBD; seroconversion

Serum Autotaxin is a Marker of the Severity of Liver Injury and Overall Survival in Patients with Cholestatic Liver Diseases - Wunsch, Ewa; Krawczyk, Marcin; Milkiewicz, Malgorzata; Trottier, Jocelyn; Barbier, Olivier; Neurath, Markus; Lammert, Frank; Kremer, Andreas; Milkiewicz, Piotr (Scientific Reports, 2016)
Autotaxin (ATX) is involved in the synthesis of lysophosphatidic acid. Both have recently been linked to cholestatic pruritus and liver injury. We aimed to investigate whether ATX is an indicator of cholestatic liver injury, health-related quality of life (HRQoL) and prognosis based on a group of 233 patients, 118 with primary biliary cholangitis (PBC) and 115 with primary sclerosing cholangitis (PSC). Patients were followed for 1-60 months, cumulative survival rates were calculated. ATX activity was significantly higher in both groups than in the 103 controls, particularly in patients with cirrhosis and in patients with longer disease duration. Ursodeoxycholic acid (UDCA) non-responders with PBC exhibited increased ATX activity. ATX activity was correlated with liver biochemistry, MELD, Mayo Risk scores and was associated with worse disease-specific HRQoL aspects. In both groups, Cox model analysis indicated that ATX was a negative predictor of survival. Increased ATX levels were associated with a 4-fold higher risk of death/liver transplantation in patients with PBC and a 2.6-fold higher risk in patients with PSC. We conclude that in patients with cholestatic conditions, ATX is not only associated with pruritus but also indicates impairment of other HRQoL aspects, liver dysfunction, and can serve as a predictor of survival.
EVALuna2:2194

Severe Acute Respiratory Syndrome Coronavirus 2 Attachment Receptor Angiotensin-Converting Enzyme 2 Is Decreased in Crohn's Disease and Regulated By Microbial and Inflammatory Signaling - Patankar, Jay Vasant; Lehmann, Malte; Kühl, Anja A.; Atreya, Raja; Becker, Christoph; Gonzalez-Acera, Miguel; Schmitt, Heike; Gamez-Belmonte, Reyes; Mahapatro, Mousumi; Diemand, Leonard; Hartmann, Leonie; Mascia, Fabrizio; et al. (Gastroenterology, 2021)
CRIS-Team Scopus Importer:2021-02-12

Shear Wave Dispersion Imaging for the Characterization of Focal Liver Lesions - A Pilot study - Jesper, Daniel; Fiedler, Steffen; Klett, Daniel; Waldner, Maximilian; Schellhaas, Barbara; Zundler, Sebastian; Neurath, Markus; Pfeifer, Lukas (Ultraschall in der Medizin, 2021)
Purpose Shear wave dispersion imaging is a novel ultrasound-based technique, which analyzes the speed of different shear wave components depending on their frequency. The dispersion of shear wave speed correlates with the viscosity of the liver parenchyma. The aim of this prospective study was to evaluate the use of shear wave dispersion imaging in focal liver lesions in the non-cirrhotic liver. Methods Patients with unclear focal liver lesions in B-mode ultrasound were prospectively assigned to shear wave dispersion imaging (m/s/kHz). Measurements were conducted within the lesion and in the liver parenchyma of the right liver lobe using an intercostal window. Histology and contrast-enhanced ultrasound served as the reference for the characterization of the lesions. Results Out of 46 patients included in this study, 24 had liver metastases and 22 had benign liver lesions. Benign lesions consisted mostly of hemangiomas (n=12) and focal nodular hyperplasia (n=8). Malignant lesions showed significantly lower shear wave dispersion (13.0±2.45 m/s/kHz) compared to benign tumors (15.2±2.74 m/s/kHz, p<0.01). In further subgroup analysis, the difference was significant for hemangiomas (15.32±2.42 m/s/kHz, p=0.04) but not for FNHs (14.98±3.36 m/s/kHz, p=0.38). The dispersion of reference liver parenchyma did not differ significantly between the groups (p=0.54). Conclusion The quantification of viscosity by shear wave dispersion is a new parameter for the characterization of focal liver lesions with higher dispersion values in hemangiomas and lower dispersion values in metastases. However, it cannot differentiate reliably between benign and malignant lesions.
CRIS-Team Scopus Importer:2021-10-29
Keywords: focal liver lesion; shear wave dispersion; shear wave elastography; ultrasound

Similar Inhibition of Dynamic Adhesion of Lymphocytes From IBD Patients to MAdCAM-1 by Vedolizumab and Etrolizumab-s - Binder, Marie-Theres; Becker, Emily; Wiendl, Maximilian; Schleier, Lena; Fuchs, Florian; Leppkes, Moritz; Atreya, Raja; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Inflammatory Bowel Diseases, 2018)
Background: Although anti-adhesion therapies are a novel mainstay in the treatment of inflammatory bowel diseases (IBDs), the mechanisms controlling integrin-dependent gut homing are poorly elucidated, and the available techniques for translational functional investigations are limited. Methods: We used dynamic adhesion assays to study adhesion of CD4+ T cells, CD8+ T cells, CD19+ B cells, and granulocytes to the addressins MAdCAM-1, VCAM-1, and ICAM-1. The effects of vedolizumab, natalizumab, etrolizumab-s, anti-CD11a, and anti-CD18 antibodies were explored. Results: Adhesion of peripheral blood leukocytes from IBD patients and control donors could be validly assessed, and integrin-mediated addressin adhesion could be specifically inhibited by anti-integrin antibodies. Numbers of adhering cells were partly, but not completely, related to integrin expression. Vedolizumab and etrolizumab-s resulted in similar reduction of adhesion to MAdCAM-1, and preliminary data proposed an association of dynamic adhesion to MAdCAM-1 with response to vedolizumab therapy. Conclusions: Dynamic adhesion assays are an easy and broadly applicable method for IBD research that is useful for future translational studies and potentially also for supporting clinical treatment decisions. 10.1093/ibd/izy077_video1izy077_Video_15786486962001.
EVALuna2:35167

Smad7 Antisense Oligonucleotide-Based Therapy in Crohn's Disease: Is it Time to Re-Evaluate? - Monteleone, Giovanni; Stolfi, Carmine; Marafini, Irene; Atreya, Raja; Neurath, Markus (Molecular Diagnosis & Therapy, 2022)
Abundant preclinical work showed that in Crohn's disease (CD), the defective activity of the immunosuppressive cytokine tumor necrosis factor (TGF)-beta 1 due to high levels of the intracellular inhibitor Smad7 contributes to amplify the tissue-damaging inflammatory response. Consistently, phase I and II studies documented clinical and endoscopic benefit in active CD patients treated with mongersen, an oral antisense oligonucleotide targeting Smad7. However, a multicenter, randomized, double-blind, placebo-controlled, phase III study was prematurely discontinued as a futility analysis showed that mongersen was not effective in CD patients. The reasons why the phase III study failed despite the fact that previous clinical trials documented the efficacy of the drug remain unknown. The primary objective of this Viewpoint was to provide clues about the factors explaining discrepancies among the clinical trials. We illustrate the recent data indicating that the various batches of mongersen, used during the phase III program, are chemically different, with some of them being unable to downregulate Smad7 expression. Overall, these findings suggest the necessity of new clinical studies to further evaluate the efficacy of chemically homogenous batches of mongersen in patients with inflammatory bowel diseases (IBDs), and, at the same time, they can help understand the failure of other clinical trials with antisense oligonucleotides in IBD (i.e. alicaforsen).
CRIS-Team WoS Importer:2022-07-29

Smad7 induces plasticity in tumor-infiltrating Th17 cells and enables TNF-alpha-mediated killing of colorectal cancer cells - Rizzo, Angelamaria; De Mare, Vincenzo; Rocchi, Chiara; Stolfi, Carmine; Colantoni, Alfredo; Neurath, Markus; Macdonald, Thomas T.; Pallone, Francesco; Monteleone, Giovanni; Fantini, Massimo C. (Carcinogenesis, 2014)
Transforming growth factor-beta (TGF-?) is deeply involved in colorectal cancer development and the disruption of the TGF-? signaling in dysplastic cells is required for tumor to grow. Nevertheless, tumor cells express TGF-? to escape the immune surveillance mediated by T cells. T-cell expression of Smad7, an intracellular inhibitor of the TGF-? signaling, protects against colitis-associated colorectal cancer. However, whether Smad7 in T cells might influence colorectal cancer growth independently of chronic inflammation and which T-cell subset is involved in this process is unknown. To address this issue, T-cell-specific Smad7 transgenic mice and wild-type (WT) littermates were subcutaneously transplanted with syngenic MC38 colon carcinoma cells. Smad7Tg mice were resistant to tumor development compared with WT mice and protection was dependent on CD4(+) T cells. Smad7 expression in T cells increased the number of tumor-infiltrating Tbet/ROR-?-t double-positive CD4 T cells characterized by the expression of tumor necrosis factor-alpha (TNF-?) and interferon-gamma but lower IL17A. The low expression of IL17A caused by the Smad7 expression in tumor-infiltrating CD4(+) T cells enabled the TNF-?-mediated killing of cancer cells both in vitro and in vivo, thus indicating that the Smad7-mediated plastic effect on T-cell phenotype induces protection against colorectal cancer.
EVALuna2:1879

Small but powerful: will nanoparticles be the future state‐of‐the‐art therapy for IBD? - Lechner, Kristina; Zeeshan, Mahira; Noack, Maxi; Ali, Hussain; Neurath, Markus; Weigmann, Benno (Expert Opinion on Drug Delivery, 2022)
Introduction: Inflammatory bowel disease (IBD) is the inflammatory condition of the gastrointestinal tract particularly affecting the colon and the ileum. IBD patients can have a very poor quality of life because of the limited therapeutic efficacy and accompanied adverse effects. Areas covered: The potential ways to employ nanoparticles to deliver drugs to a certain site of inflammation are discussed. The focus was set on the microenvironment in the gut as well as the mucosa, epithelial layer and the microbiota. Moreover, experimental animal colitis models were nanoparticles were used as a potential treatment are presented. Lastly, challenges for the potential clinical use in humans are discussed. Expert opinion: Although there still remain many open questions e.g. regarding the toxicity, the metabolism or the pharmacokinetics of nanoparticles further research on this topic could overcome these challenges. For example, instead of synthetically engineered particles, biodegradable components could be used. Since there have been a lot pf promising results in the recent years, we are sure that in the future nanoparticles will be developed in a way to ensure safe and targeted delivery of drugs to the site of inflammation.
CRIS-Team Scopus Importer:2022-03-18
Keywords: colon targeting; IBD; nanocarrier; nanoparticles; T cells

SMYD2 Inhibition Downregulates TMPRSS2 and Decreases SARS-CoV-2 Infection in Human Intestinal and Airway Epithelial Cells - Yu, Yidong; Herrmann, Alexandra; Thonn, Veronika; Cordsmeier, Arne; Neurath, Markus; Enßer, Armin; Becker, Christoph (Cells, 2022)
The COVID-19 pandemic caused by SARS-CoV-2 has lasted for more than two years. Despite the presence of very effective vaccines, the number of virus variants that escape neutralizing antibodies is growing. Thus, there is still a need for effective antiviral treatments that target virus replication independently of the circulating variant. Here, we show for the first time that deficiency or pharmacological inhibition of the cellular lysine-methyltransferase SMYD2 decreases TMPRSS2 expression on both mRNA and protein levels. SARS-CoV-2 uses TMPRSS2 for priming its spike protein to infect target cells. Treatment of cultured cells with the SMYD2 inhibitors AZ505 or BAY598 significantly inhibited viral replication. In contrast, treatment of Vero E6 cells, which do not express detectable amounts of TMPRSS2, had no effect on SARS-CoV-2 infection. Moreover, by generating a recombinant reporter virus that expresses the spike protein of the Delta variant of SARS-CoV-2, we demonstrate that BAY598 exhibits similar antiviral activity against this variant of concern. In summary, SMYD2 inhibition downregulates TMPRSS2 and blocks viral replication. Targeting cellular SMYD2 represents a promising tool to curtail SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2022-04-29
Keywords: antiviral treatment; AZ505; BAY598; COVID-19; SARS-CoV-2; SMYD2; TMPRSS2

SMYD2 targets RIPK1 and restricts TNF-induced apoptosis and necroptosis to support colon tumor growth - Yu, Yidong; Thonn, Veronika; Patankar, Jay; Thoma, Oana-Maria; Waldner, Maximilian; Zielinska, Marta; Bao, Lili; Gonzalez Acera, Miguel; Wallmueller, Stefan; Engel, Felix; Stürzl, Michael; Neurath, Markus; et al. (Cell Death & Disease, 2022)
SMYD2 is a histone methyltransferase, which methylates both histone H3K4 as well as a number of non-histone proteins. Dysregulation of SMYD2 has been associated with several diseases including cancer. In the present study, we investigated whether and how SMYD2 might contribute to colorectal cancer. Increased expression levels of SMYD2 were detected in human and murine colon tumor tissues compared to tumor-free tissues. SMYD2 deficiency in colonic tumor cells strongly decreased tumor growth in two independent experimental cancer models. On a molecular level, SMYD2 deficiency sensitized colonic tumor cells to TNF-induced apoptosis and necroptosis without affecting cell proliferation. Moreover, we found that SMYD2 targeted RIPK1 and inhibited the phosphorylation of RIPK1. Finally, in a translational approach, pharmacological inhibition of SMYD2 attenuated colonic tumor growth. Collectively, our data show that SMYD2 is crucial for colon tumor growth and inhibits TNF-induced apoptosis and necroptosis.
CRIS-Team WoS Importer:2022-01-21

Spatial Single Cell Profiling Using Imaging Mass Cytometry: Inflammatory Versus Penetrating Crohn's Disease - Lehmann, Malte; Weixler, Benjamin; Elezkurtaj, Sefer; Loddenkemper, Christopher; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Fistula formation is a major complication in Crohn's disease [CD] and the role of the immune cell compartment remains to be elucidated. Thus, we compared the immune cell compartment of CD fistula to inflammatory CD colitis using imaging mass cytometry [IMC] and immunofluorescence. Methods: A 36-marker panel including structural, functional, and lineage markers for use in IMC was established. This panel was applied to analyse paraffin-embedded CD fistula tract [n = 11], CD colitis [n = 10], and colon samples from non-inflamed controls [n = 12]. Computational methods for cell segmentation, dimensionality reduction, and cell type clustering were used to define cell populations for cell frequency, marker distribution, and spatial neighbourhood analysis. Multiplex immunofluorescence was used for higher resolution spatial analysis. Results: Analysis of cell frequencies in CD fistulas compared to CD colitis and control colonic samples revealed a significant increase in neutrophils, effector cytotoxic T cells, and inflammatory macrophages in CD fistula samples, whereas regulatory T cells were decreased. Neutrophils in CD fistula expressed significantly more matrix metalloproteinase 9 [MMP9], correlating with extracellular matrix remodelling. Neighbourhood analysis revealed a strong association between MMP9+ neutrophils and effector cytotoxic T cells in both CD fistulas and colitis. Conclusions: This study presents the first highly multiplexed single cell analysis of the immune cell compartment of CD fistulas and their spatial context. It links immune cell dynamics, particularly MMP9+ neutrophils, to extracellular matrix remodelling in CD fistulas, offering insights into the complex network of cellular interactions and potential therapeutic targets for CD complications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: fistula; imaging mass cytometry; Penetrating Crohn's disease

STAT1 coordinates intestinal epithelial cell death during gastrointestinal infection upstream of Caspase-8 - Stolzer, Iris; Schickedanz, Laura; Chiriac, Mircea T.; López-Posadas, Rocío; Grassl, Guntram A.; Mattner, Jochen; Wirtz, Stefan; Neurath, Markus; Günther, Claudia; Winner, Beate (Mucosal Immunology, 2021)
Intestinal homeostasis and the maintenance of the intestinal epithelial barrier are essential components of host defense during gastrointestinal Salmonella Typhimurium infection. Both require a strict regulation of cell death. However, the molecular pathways regulating epithelial cell death have not been completely understood. Here, we elucidated the contribution of central mechanisms of regulated cell death and upstream regulatory components during gastrointestinal infection. Mice lacking Caspase-8 in the intestinal epithelium are highly sensitive towards bacterial induced enteritis and intestinal inflammation, resulting in an enhanced lethality of these mice. This phenotype was associated with an increased STAT1 activation during Salmonella infection. Cell death, barrier breakdown and systemic infection were abrogated by an additional deletion of STAT1 in Casp8ΔIEC mice. In the absence of epithelial STAT1, loss of epithelial cells was abolished which was accompanied by a reduced Caspase-8 activation. Mechanistically, we demonstrate that epithelial STAT1 acts upstream of Caspase-8-dependent as well as -independent cell death and thus might play a major role at the crossroad of several central cell death pathways in the intestinal epithelium. In summary, we uncovered that transcriptional control of STAT1 is an essential host response mechanism that is required for the maintenance of intestinal barrier function and host survival.
CRIS-Team Scopus Importer:2021-09-17

STAT2 Controls Colorectal Tumorigenesis and Resistance to Anti-Cancer Drugs - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Becker, Christoph; Neurath, Markus (Cancers, 2023)
Colorectal cancer (CRC) is a significant socioeconomic burden in modern society and is accountable for millions of premature deaths each year. The role of signal transducer and activator of transcription 2 (STAT2)-dependent signaling in this context is not yet fully understood, and no therapies targeting this pathway are currently being pursued. We investigated the role of STAT2 in CRC using experimental mouse models coupled with RNA-sequencing (RNA-Seq) data and functional assays with anti-cancer agents in three-dimensional tumoroids. Stat2−/− mice showed greater resistance to the development of CRC in both inflammation-driven and inflammation-independent experimental CRC models. In ex vivo studies, tumoroids derived from Stat2−/− mice with the multiple intestinal neoplasia (Min) mutant allele of the adenomatous polyposis coli (Apc) locus exhibited delayed growth, were overall smaller and more differentiated as compared with tumoroids from ApcMin/+ wildtype (WT) mice. Notably, tumoroids from ApcMin/+ Stat2−/− mice were more susceptible to anti-cancer agents inducing cell death by different mechanisms. Our findings clearly indicated that STAT2 promotes CRC and suggested that interventions targeting STAT2-dependent signals might become an attractive therapeutic option for patients with CRC.
CRIS-Team Scopus Importer:2023-12-15
Keywords: anti-cancer therapy; Apc; colorectal cancer mouse model; STAT2; tumoroid

STAT3 Activation in Th17 and Th22 Cells Controls IL-22-Mediated Epithelial Host Defense during Infectious Colitis - Backert, Ingo; Koralov, Sergei B.; Wirtz, Stefan; Kitowski, Vera; Billmeier, Ulrike; Martini, Eva; Hofmann, Katharina; Hildner, Kai; Wittkopf, Nadine; Brecht, Katrin; Waldner, Maximilian; Rajewsky, Klaus; et al. (Journal of Immunology, 2014)
The Citrobacter rodentium model mimics the pathogenesis of infectious colitis and requires sequential contributions from different immune cell populations, including innate lymphoid cells (ILCs) and CD4(+) lymphocytes. In this study, we addressed the role of STAT3 activation in CD4(+) cells during host defense in mice against C. rodentium. In mice with defective STAT3 in CD4(+) cells (Stat3(?CD4)), the course of infection was unchanged during the innate lymphoid cell-dependent early phase, but significantly altered during the lymphocyte-dependent later phase. Stat3(?CD4) mice exhibited intestinal epithelial barrier defects, including downregulation of antimicrobial peptides, increased systemic distribution of bacteria, and prolonged reduction in the overall burden of C. rodentium infection. Immunomonitoring of lamina propria cells revealed loss of virtually all IL-22-producing CD4(+) lymphocytes, suggesting that STAT3 activation was required for IL-22 production not only in Th17 cells, but also in Th22 cells. Notably, the defective host defense against C. rodentium in Stat3(?CD4) mice could be fully restored by specific overexpression of IL-22 through a minicircle vector-based technology. Moreover, expression of a constitutive active STAT3 in CD4(+) cells shaped strong intestinal epithelial barrier function in vitro and in vivo through IL-22, and it promoted protection from enteropathogenic bacteria. Thus, our work indicates a critical role of STAT3 activation in Th17 and Th22 cells for control of the IL-22-mediated host defense, and strategies expanding STAT3-activated CD4(+) lymphocytes may be considered as future therapeutic options for improving intestinal barrier function in infectious coliti
EVALuna2:1843

STAT3 activation through IL-6/IL-11 in cancer-associated fibroblasts promotes colorectal tumour development and correlates with poor prognosis - Heichler, Christina; Scheibe, Kristina; Schmied, Anabel; Geppert, Carol-Immanuel; Schmid, Benjamin; Wirtz, Stefan; Thoma, Oana Maria; Kramer, Viktoria; Waldner, Maximilian; Büttner, Christian; Farin, Henner; Pešić, Marina; et al. (Gut, 2019)
Objective: Cancer-associated fibroblasts (CAFs) influence the tumour microenvironment and tumour growth. However, the role of CAFs in colorectal cancer (CRC) development is incompletely understood. Design: We quantified phosphorylation of STAT3 (pSTAT3) expression in CAFs of human colon cancer tissue using a tissue microarray (TMA) of 375 patients, immunofluorescence staining and digital pathology. To investigate the functional role of CAFs in CRC, we took advantage of two murine models of colorectal neoplasia and advanced imaging technologies. In loss-of-function and gain-of-function experiments, using genetically modified mice with collagen type VI (COLVI)-specific signal transducer and activator of transcription 3 (STAT3) targeting, we evaluated STAT3 signalling in fibroblasts during colorectal tumour development. We performed a comparative gene expression profiling by whole genome RNA-sequencing of fibroblast subpopulations (COLVI+ vs COLVI-) on STAT3 activation (IL-6 vs IL-11). Results: The analysis of pSTAT3 expression in CAFs of human TMAs revealed a negative correlation of increased stromal pSTAT3 expression with the survival of colon cancer patients. In the loss-of-function and gain-of-function approach, we found a critical role of STAT3 activation in fibroblasts in driving colorectal tumourigenesis in vivo. With different imaging technologies, we detected an expansion of activated fibroblasts in colorectal neoplasias. Comparative gene expression profiling of fibroblast subpopulations on STAT3 activation revealed the regulation of transcriptional patterns associated with angiogenesis. Finally, the blockade of proangiogenic signalling significantly reduced colorectal tumour growth in mice with constitutive STAT3 activation in COLVI+ fibroblasts. Conclusion: Altogether our work demonstrates a critical role of STAT3 activation in CAFs in CRC development.
CRIS-Team Scopus Importer:2019-11-19
Keywords: colorectal cancer

Strategies for targeting cytokines in inflammatory bowel disease - Neurath, Markus (Nature reviews. Immunology, 2024)
Cytokines produced by immune cells contribute to the development and perpetuation of inflammatory bowel disease (IBD), namely Crohn’s disease and ulcerative colitis, by regulating various aspects of the inflammatory response. Pro-inflammatory cytokines trigger chronic intestinal inflammation, tissue damage, carcinogenesis and perpetuation of disease and suppress the resolution of inflammation in IBD. The clinical success of antibodies that neutralize tumour necrosis factor (TNF) and the cytokine IL-12p40 in individuals with IBD has underscored this concept. Moreover, genetic and preclinical studies have emphasized the crucial role of IL-23 in IBD, leading to clinical approval of antibodies targeting this cytokine. Multiple studies have also investigated the administration of cytokines with assumed anti-inflammatory effects, but this approach has yet to show any real clinical benefit in individuals with IBD. Recent studies have targeted the cytokine network through the use of multi-cytokine blockers (for example, Janus kinase (JAK) inhibitors), IL-2-induced regulatory T cells or advanced combination therapies that use multiple cytokine blockers simultaneously (for example, anti-TNF along with anti-IL-23 antibodies). This Review will focus on our current understanding of how cytokines produced by innate and adaptive immune cells contribute to IBD pathogenesis and discuss how their modulation may inform future treatments for IBD.
CRIS-Team Scopus Importer:2024-03-29

Stresswahrnehmung, Persönlichkeitsmerkmale, psychosoziale Beeinträchtigungen und Bewältigungsstrategien bei Patienten mit chronisch-entzündlichen Darmerkrankungen - Petruo, Vanessa A.; Krauss, Ekaterina; Kleist, Anika; Hardt, Juliane; Hake, Karsten; Peirano, Julia; Krause, Thomas; Ehehalt, Robert; von Arnauld de la Perriére, Philipp; Büning, Jürgen; Treml, Oliver; Krauss, Norbert; et al. (Zeitschrift für Gastroenterologie, 2019)
BACKGROUND AND AIMS: This study examined differences in personality, psychological distress, and stress coping in inflammatory bowel disease (IBD) depending on type of disease and disease activity. We compared patients suffering from Crohn's disease (CD) and ulcerative colitis (UC) with controls. While the literature is replete with distinctive features of the pathogenesis of IBD, the specific differences in psychological impairments are not well studied. METHODS: In this German national multicenter study, participants were recruited from 32 centers. Two hundred ninety-seven questionnaires were included, delivering vast information on disease status and psychological well-being based on validated instruments with a total of 285 variables. RESULTS: CD patients were more affected by psychological impairments than patients suffering from UC or controls. Importantly, patients with active CD scored higher in neuroticism (p < 0.01), psychological distress (p < 0.001) and maladaptive stress coping (escape, p = 0.03; rumination, p < 0.03), but less need for social support (p = 0.001) than controls. In contrast, patients suffering from active UC showed psychological distress (p < 0.04) and maladaptive coping (avoidance, p < 0.03; escape, p = 0.01). Patients in remission seemed to be less affected. In particular, patients with UC in remission were not inflicted by psychological impairments. The group of CD patients in remission however, showed insecurity (p < 0.01) and paranoid ideation (p = 0.04). CONCLUSIONS: We identified specific aspects of psychological impairment in IBD depending on disease and disease activity. Our results underscore the need for psychological support and treatment particularly in active CD.
CRIS-Team Scopus Importer:2019-05-02

Submucosal injection of the oligonucleotide STNM01 is able to induce clinical remission, mucosal healing and histological response in left-sided ulcerative colitis patients with moderate-to-severe disease - Atreya, Raja; Kuehbacher, T.; Waldner, Maximilian; Hirschmann, S.; Drvarov, O.; Abu Hashem, R.; Maaser, C.; Kucharzik, T.; Dinter, J.; Schramm, C.; Mertens, J.; Holler, B.; et al. (2017)
EVALuna2:33827

Submucosal Injection of the RNA Oligonucleotide GUT-1 in Active Ulcerative Colitis Patients: A Randomized, Double-Blind, Placebo-Controlled Phase 2a Induction Trial. - Atreya, Raja; Kühbacher, Tanja; Waldner, Maximilian; Hirschmann, Simon; Drvarov, Oliver; Abu Hashem, Raed; Maaser, Christian; Kucharzik, Torsten; Dinter, Johanna; Mertens, Jessica; Schramm, Christoph; Holler, Babett; et al. (Journal of Crohns & Colitis, 2024)
BACKGROUND AND AIMS: Carbohydrate sulfotransferase 15 [CHST15] biosynthesizes sulphated matrix glycosaminoglycans and is implicated in intestinal inflammation and fibrosis. Here, we evaluate the efficacy and safety of the double-stranded RNA oligonucleotide GUT-1, a specific blocker of CHST15, as induction therapy in patients with ulcerative colitis [UC]. METHODS: In this randomized, double-blind, placebo-controlled, phase 2a study, we enrolled endoscopically active UC patients, refractory to conventional therapy, in five hospital centres across Germany. Patients were randomized 1:1:1 using a block randomized technique to receive a single dosing of 25 nM GUT-1, 250 nM GUT-1, or placebo by endoscopic submucosal injections. The primary outcome measure was improvement of endoscopic lesions at weeks 2 or 4. The secondary outcome measures included clinical and histological responses. Safety was assessed in all patients who received treatment. RESULTS: Twenty-eight patients were screened, 24 were randomized, and 21 were evaluated. Endoscopic improvement at weeks 2 or 4 was achieved by 71.4% in the GUT-1 250 nM, 0% in the GUT-1 25 nM, and 28.6% in the placebo group. Clinical remission was shown by 57.1% in the GUT-1 250 nM, 0% in the GUT-1 25 nM, and 14.3% in the placebo groups. Histological improvement was shown by 42.9% in the GUT-1 250 nM, 0% in the GUT-1 25 nM, and 0% in the placebo groups. GUT-1 250 nM reduced CHST15 expression significantly and suppressed mucosal inflammation and fibrosis. GUT-1 application was well tolerated. CONCLUSION: Single dosing by submucosal injection of GUT-1 repressed CHST15 mucosal expression and may represent a novel induction therapy by modulating tissue remodelling in UC.
EVALuna2:550699

Successful cyclosporin and ustekinumab combination therapy in a patient with severe steroid-refractory ulcerative colitis - Ganzleben, Ingo; Geppert, Carol-Immanuel; Osaba, Lourdes; Hirschmann, Simon; Nägel, Andreas; Glück, Christian; Hoffman, Arthur; Rath, Timo; Nagore, Daniel; Neurath, Markus; Atreya, Raja (Therapeutic Advances in Gastroenterology, 2020)
The therapeutic management of patients with severe steroid-refractory ulcerative colitis still represents a critical clinical challenge. In this setting, cyclosporin is an effective and rapidly acting induction treatment that is applied in combination with maintenance therapeutic agents like thiopurines or vedolizumab. Here, we present the case of a 33-year-old ulcerative colitis patient with severe steroid-refractory ulcerative colitis who refused surgical intervention and previously demonstrated no long-term benefit to anti-TNF antibody, vedolizumab, cyclosporin, thiopurines or tofacitinib treatment. Intravenous cyclosporin therapy was re-initiated in the patient and, after signs of clinical response, therapy with ustekinumab was additionally applied. After 11 weeks of well tolerated cyclosporin and ustekinumab combination therapy, cyclosporin was discontinued upon clinical and endoscopic remission. Subsequently, ustekinumab treatment has been effective in maintaining remission during the follow-up period of 195 days.
CRIS-Team Scopus Importer:2020-10-23
Keywords: cyclosporin; trough levels; ulcerative colitis; ustekinumab

Successful Long-term Treatment of Diversion Colitis with Topical Coconut Oil Application - Zundler, Sebastian; Dietz, Lisa; Matzel, Klaus E.; Geppert, Carol-Immanuel; Becker, Emily; Rath, Timo; Neurath, Markus; Atreya, Raja (American Journal of Gastroenterology, 2018)
CRIS-Team WoS Importer:2019-02-22

Successful Multidisciplinary Treatment with Secondary Metastatic Liver Resection after Downsizing by Palliative Second-Line Treatment of Colorectal Cancer: A Curative Option - Wein, Axel; Görtz, Rüdiger; Wolff, Kerstin; Ostermeier, Nicola; Busse, Daniel; Kremer, Andreas; Koch, Franz; Hagel, Alexander; Farnbacher, Michael; Kammerer, Ferdinand J.; Neurath, Markus; Grützmann, Robert; et al. (Case Reports in Oncology, 2016)
The prognostic outcome following progression after palliative first-line treatment for patients suffering from metastatic colorectal adenocarcinoma is generally poor. Long-term relapse-free survival with palliative second-line treatment may be achieved in only a limited number of individual cases.A 37-year-old patient presented with bilobar liver metastases of colon cancer confirmed by histology with wild-type K-RAS (exon 2). Due to progressive disease after eight cycles of first-line therapy with FOLFIRI plus cetuximab, second-line chemotherapy with modified FOLFOX4 (mFOLFOX4) plus bevacizumab was initiated. During four cycles of mFOLFOX4 plus bevacizumab (2 months), no higher-grade toxicity occurred. Liver MRI with contrast medium revealed downsizing of the segment II/III metastases, as well as regressive, small, faint, hardly definable lesions in segments VI and IVb. The interdisciplinary tumor board of the University of Erlangen thus decided to perform resection of the liver metastases. Segments II and III were resected, and the liver metastases in segments IVa and VI were excised (R0). Histopathology confirmed three of the R0-resected metastases to be completely necrotic, with residual scarring. As perioperative therapy, four additional cycles of mFOLFOX4 plus bevacizumab were administered postoperatively. No higher-grade toxicity was observed. Three years after the initial diagnosis, the patient is relapse free, professionally fully reintegrated, and has an excellent performance status.Patients suffering from metastatic colorectal cancer may benefit from multidisciplinary treatment with secondary metastatic liver resection after downsizing by palliative second-line treatment. In individual cases, patients may even have a curative treatment option, provided that close interdisciplinary collaboration exists.
EVALuna2:2220

Successful therapy of Clostridium difficile infection with fecal microbiota transplantation - Konturek, P C; Koziel, J; Dieterich, Walburga; Haziri, D; Wirtz, Stefan; Glowczyk, I; Konturek, K; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2016)
Clostridium difficile infection (CDI) is the most common cause of infectious diarrhea and represents an important burden for healthcare worldwide. Symptoms of severe CDI include watery, foul-smelling diarrhea, peripheral leucocytosis, increased C-reactive protein (CRP), acute renal failure, hypotension and pseudomembranous colitis. Recent studies indicate that the main cause of CDI is dysbiosis, an imbalance in the normal gut microbiota. The restoration of a healthy gut microbiota composition via fecal microbiota transplantation (FMT) recently became more popular. The aim of the present study was to assess the effect of FMT on the healing of CDI and to analyze the changes in the level of pro-inflammatory markers (C-reactive protein, fecal calprotectin) and pro-inflammatory cytokines. Eighteen patients with CDI were included in our study (6 males and 12 females) with recurrent and/or severe CDI. The FMT was performed in 17 patients using colonoscopy, including 16 patients receiving a one-time FMT and 1 patient who needed 2 additional FMTs. One patient was treated with a single round of FMT using push-and-pull enteroscopy. In all CDI patients, before and 3 weeks after FMT, the following parameters were analyzed: C-reactive protein, fecal calprotectin, and plasma interleukin (IL)-6, IL-8 and IL-12, and tumor necrosis factor-alpha (TNF-?). In addition, the plasma level of LL-37, a cathelicidine peptide was assessed by fluorescence-activated cell sorting (FACS) before and 3 months after FMT. Finally, in 7 patients a microbiome analysis was performed by sequencing of 16SrRNA in stool probes obtained before and 3 weeks after FMT. The healing rate of CDI was 94%. In all successfully treated patients no recurrent CDI was observed during follow-up (16 months). The serum level of pro-inflammatory cytokines (TNF-?, IL-1?, IL-6, IL-8 and IL-12) significantly decreased after FMT. Similarly, CRP and fecal calprotectin normalized after FMT. 3 months after FMT a significant increase of LL-37 in the plasma of successfully treated patients was monitored. The sequencing analysis demonstrated an elevated abundance of beneficial bacterial species such as Lactobacillaceae, Ruminococcaceae, Desulfovibrionaceae, Sutterellaceae and Porphyromonodacea after FMT. No serious side effects were observed. We concluded that FMT represented a very effective and safe treatment of recurrent and/or severe CDI and led to favorable shifts in the composition of gut microbiome.
EVALuna2:2225

Successful Therapy of Crohn's Disease-Associated Pulmonary Necrobiotic Nodules on Ustekinumab Therapy - Ganzleben, Ingo; Hirschmann, Simon; Köhler, Juliane; Fuchs, Florian; Rieker, Ralf; Baer, Eva; Klenske, Entcho; Nagore, Daniel; Neurath, Markus; Atreya, Raja (American Journal of Gastroenterology, 2020)
CRIS-Team Scopus Importer:2020-07-10

Successful treatment of COVID-19 infection with convalescent plasma in B-cell-depleted patients may promote cellular immunity - Kremer, Andreas E.; Kremer, Anita; Willam, Carsten; Völkl, Simon; Verhagen, Johan; Achenbach, Susanne; van der Meijden, Edith; Lang, Vanessa; Aigner, Michael; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; et al. (European Journal of Immunology, 2021)
Treatment with convalescent plasma has been shown to be safe in coronavirus disease in 2019 (COVID-19) infection, although efficacy reported in immunocompetent patients varies. Nevertheless, neutralizing antibodies are a key requisite in the fight against viral infections. Patients depleted of antibody-producing B cells, such as those treated with rituximab (anti-CD20) for hematological malignancies, lack a fundamental part of their adaptive immunity. Treatment with convalescent plasma appears to be of general benefit in this particularly vulnerable cohort. We analyzed clinical course and inflammation markers of three B-cell-depleted patients suffering from COVID-19 who were treated with convalescent plasma. In addition, we measured serum antibody levels as well as peripheral blood CD38/HLA-DR-positive T-cells ex vivo and CD137-positive T-cells after in vitro stimulation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-derived peptides in these patients. We observed that therapy with convalescent plasma was effective in all three patients and analysis of CD137-positive T-cells after stimulation with SARS-CoV-2 peptides showed an increase in peptide-specific T-cells after application of convalescent plasma. In conclusion, we here demonstrate efficacy of convalescent plasma therapy in three B-cell-depleted patients and present data that suggest that while application of convalescent plasma elevates systemic antibody levels only transiently, it may also boost specific T-cell responses.
CRIS-Team Scopus Importer:2021-09-17
Keywords: B-cell deficiency; convalescent plasma; COVID-19; SARS-CoV-2; T-cell immunity

Successful treatment of COVID-19 with convalescent plasma in B-cell depleted patients may promote cellular immunity - Kremer, Andreas; Kremer, Anita; Willam, Carsten; Verhagen, Johan; Achenbach, Susanne; Van Der Meiden, E.; Lang, Vanessa; Aigner, M.; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Lutzny-Geier, Gloria; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Surface Design Options in Polymer- and Lipid-Based siRNA Nanoparticles Using Antibodies - Gabel, Michael; Knauß, Annkathrin; Fischer, Dagmar; Neurath, Markus; Weigmann, Benno (International Journal of Molecular Sciences, 2022)
The mechanism of RNA interference (RNAi) could represent a breakthrough in the therapy of all diseases that arise from a gene defect or require the inhibition of a specific gene expression. In particular, small interfering RNA (siRNA) offers an attractive opportunity to achieve a new milestone in the therapy of human diseases. The limitations of siRNA, such as poor stability, inefficient cell uptake, and undesired immune activation, as well as the inability to specifically reach the target tissue in the body, can be overcome by further developments in the field of nanoparticulate drug delivery. Therefore, types of surface modified siRNA nanoparticles are presented and illustrate how a more efficient and safer distribution of siRNA at the target site is possible by modifying the surface properties of nanoparticles with antibodies. However, the development of such efficient and safe delivery strategies is currently still a major challenge. In consideration of that, this review article aims to demonstrate the function and targeted delivery of siRNA nanoparticles, focusing on the surface modification via antibodies, various lipid- and polymer-components, and the therapeutic effects of these delivery systems.
CRIS-Team Scopus Importer:2022-12-09
Keywords: antibody; gene delivery; lipid nanoparticle; polymer nanoparticle; siRNA; surface-functionalized nanoparticles; targeted drug delivery

Survivin is a guardian of the intestinal stem cell niche and its expression is regulated by TGF-? - Martini, Eva; Schneider, Evelyn; Neufert, Clemens; Neurath, Markus; Becker, Christoph (Cell Cycle, 2016)
As an inhibitor of apoptosis (IAP) family member, Survivin is known for its role during regulation of apoptosis. More recently its function as a cell cycle regulator has become evident. Survivin was shown to play a pivotal role during embryonic development and is highly expressed in regenerative tissue as well as in many cancer types. We examined the function of Survivin during mouse intestinal organogenesis and in gut pathophysiology. We found high expression of Survivin in experimentally induced colon cancer in mice but also in colon tumors of humans. Moreover, Survivin was regulated by TGF-? and was found to be highly expressed during mucosal healing following intestinal inflammation. We identified that expression of Survivin is essential early on in life, as specific deletion of Survivin in Villin expressing cells led to embryonic death around day 12 post coitum. Together with our recent study on the role of Survivin in the gut of adult mice our data demonstrate that Survivin is an essential guardian of embryonic gut development and adult gut homeostasis protecting the epithelium from cell death promoting the proliferation of intestinal stem and progenitor cells.
EVALuna2:2186

Systemic desensitization through TRPA1 channels by capsazepine and mustard oil - a novel strategy against inflammation and pain - Kistner, Katrin; Siklosi, Norbert; Babes, Alexandru; Khalil, Mohammad; Selescu, Tudor; Zimmermann, Katharina; Wirtz, Stefan; Becker, Christoph; Neurath, Markus; Reeh, Peter; Engel, Matthias (Scientific Reports, 2016)
We demonstrate a novel dual strategy against inflammation and pain through body-wide desensitization of nociceptors via TRPA1. Attenuation of experimental colitis by capsazepine (CPZ) has long been attributed to its antagonistic action on TRPV1 and associated inhibition of neurogenic inflammation. In contrast, we found that CPZ exerts its anti-inflammatory effects via profound desensitization of TRPA1. Micromolar CPZ induced calcium influx in isolated dorsal root ganglion (DRG) neurons from wild-type (WT) but not TRPA1-deficient mice. CPZ-induced calcium transients in human TRPA1-expressing HEK293t cells were blocked by the selective TRPA1 antagonists HC 030031 and A967079 and involved three cysteine residues in the N-terminal domain. Intriguingly, both colonic enemas and drinking water with CPZ led to profound systemic hypoalgesia in WT and TRPV1(-/-) but not TRPA1(-/-) mice. These findings may guide the development of a novel class of disease-modifying drugs with anti-inflammatory and anti-nociceptive effects.
EVALuna2:2084

Targeted inhibition of the WEE1 kinase as a novel therapeutic strategy in neuroendocrine neoplasms - Weindl, Lena; Atreya, Imke; Dietrich, Peter; Neubeck, Sabine; Neurath, Markus; Pavel, Marianne Ellen (Endocrine-Related Cancer, 2021)
Neuroendocrine neoplasms (NENs) represent a rare and heterogeneous group of malignancies, sharing features of both neural and endocrine cells. NENs G3 appear as a highly aggressive subset with a poor prognosis and limited therapeutic options. The small-molecule inhibitor of the WEE1 tyrosine kinase, adavosertib (AZD1775), has previously demonstrated potent anti-tumor effects on various types of cancer in preclinical and clinical studies. However, the role of adavosertib in NENs G3 had remained elusive. We evaluated the effects of adavosertib on pancreatic (BON-1, QGP-1) and bronchopulmonary (NCI-H720) neuroendocrine tumor cell lines applying 2D and 3D spheroid models. We newly demonstrated that adavosertib is sufficient to reduce cell viability and proliferation in neuroendocrine cell lines with features of high-grade NENs. As underlying mechanisms, we identified adavosertib-mediated DNA double-strand breaks and a G2/M cell cycle checkpoint abrogation leading into mitotic catastrophe and cancer cell apoptosis. Silencing of WEE1 via siRNA transfection resulted in a phenotype similar to adavosertib treatment. Together, inhibition of the WEE1 tyrosine kinase applying adavosertib on NENs G3 outlines a promising novel therapeutic strategy.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D cell culture; Cell cycle; G3; Neuroendocrine neoplasm; WEE1

Targeting cytokines in inflammatory bowel disease. - Neurath, Markus (Science Translational Medicine, 2022)
Targeting cytokines in inflammatory bowel disease (IBD) is a useful clinical approach. Potential therapies for IBD include regulatory T cell transfer to restore cytokine balance, blocking proinflammatory cytokines (e.g., IL-12 and IL-23) or their receptors (sIL-6R and IL-36R), or inhibiting signaling kinases (e.g., JAK). An emerging trend in IBD therapy is to combine several anti-cytokine agents simultaneously.
EVALuna2:540209

Targeting immune cell circuits and trafficking in inflammatory bowel disease - Neurath, Markus (Nature Immunology, 2019)
Inflammatory bowel diseases (IBDs) such as Crohn’s disease and ulcerative colitis are characterized by uncontrolled activation of intestinal immune cells in a genetically susceptible host. Due to the progressive and destructive nature of the inflammatory process in IBD, complications such as fibrosis, stenosis or cancer are frequently observed, which highlights the need for effective anti-inflammatory therapy. Studies have identified altered trafficking of immune cells and pathogenic immune cell circuits as crucial drivers of mucosal inflammation and tissue destruction in IBD. A defective gut barrier and microbial dysbiosis induce such accumulation and local activation of immune cells, which results in a pro-inflammatory cytokine loop that overrides anti-inflammatory signals and causes chronic intestinal inflammation. This Review discusses pathogenic cytokine responses of immune cells as well as immune cell trafficking as a rational basis for new translational therapies in IBD.
CRIS-Team Scopus Importer:2019-07-09

Targeting Immune Cell Trafficking – Insights From Research Models and Implications for Future IBD Therapy - Wiendl, Maximilian; Becker, Elisabeth; Müller, Tanja; Voskens, Caroline; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2021)
Inflammatory bowel diseases (IBDs), including Crohn’s disease (CD) and ulcerative colitis (UC) are multifactorial diseases with still unknown aetiology and an increasing prevalence and incidence worldwide. Despite plentiful therapeutic options for IBDs, the lack or loss of response in certain patients demands the development of further treatments to tackle this unmet medical need. In recent years, the success of the anti-α4β7 antibody vedolizumab highlighted the potential of targeting the homing of immune cells, which is now an important pillar of IBD therapy. Due to its complexity, leukocyte trafficking and the involved molecules offer a largely untapped resource for a plethora of potential therapeutic interventions. In this review, we aim to summarise current and future directions of specifically interfering with immune cell trafficking. We will comment on concepts of homing, retention and recirculation and particularly focus on the role of tissue-derived chemokines. Moreover, we will give an overview of the mode of action of drugs currently in use or still in the pipeline, highlighting their mechanisms and potential to reduce disease burden.
CRIS-Team Scopus Importer:2021-06-04
Keywords: homing; IBD; retention; T cell; therapy; trafficking

Targeting Immune Cell Wiring in Ulcerative Colitis - Neurath, Markus; Chiriac, Mircea T. (Immunity, 2019)
The cytokine TNF is thought to play a major role in the immunopathogenesis of ulcerative colitis, and anti-TNF antibodies are considered as cornerstones of clinical therapy. Two clinical trials published in The New England Journal of Medicine now challenge this paradigm and suggest new avenues for research. The cytokine TNF is thought to play a major role in the immunopathogenesis of ulcerative colitis, and anti-TNF antibodies are considered as cornerstones of clinical therapy. Two clinical trials published in The New England Journal of Medicine now challenge this paradigm and suggest new avenues for research.
CRIS-Team Scopus Importer:2019-11-19

Targeting Inflammatory T Helper Cells via Retinoic Acid-Related Orphan Receptor Gamma t Is Ineffective to Prevent Allo-Response-Driven Colitis - Buchele, Vera; Abendroth, Benjamin; Buettner-Herold, Maike; Vogler, Tina; Rothamer, Johanna; Ghimire, Sakhila; Ullrich, Evelyn; Holler, Ernst; Neurath, Markus; Hildner, Kai (Frontiers in Immunology, 2018)
Intestinal graft-versus-host disease (GvHD) is a life-threatening, inflammatory donor T cell-mediated complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). In the light of the reported efficacy of interleukin-23 (IL-23)-blockade to mitigate syngeneic intestinal inflammation in inflammatory bowel disease patients, targeting IL-23 and thereby interleukin-17a (IL-17a) producing T helper (Th17) cells as the T cell subset assumed to be mostly regulated by IL-23, has emerged as a putatively general concept to harness immune-mediated mucosal inflammation irrespective of the underlying trigger. However, the role of Th17 cells during allo-response driven colitis remains ambiguous due to a series of studies with inconclusive results. Interestingly, we recently identified granulocyte-macrophage colony-stimulating factor (GM-CSF+) T cells to be promoted by interleukin-7 (IL-7) signaling and controlled by the activating protein-1 transcription factor family member basic leucine zipper transcription factor ATF-like (BATF) as critical mediators of intestinal GvHD in mice. Given the dual role of BATF, the contribution of IL-23-mediated signaling within donor T cells and bona fide Th17 cells remains to be delineated from the regulation of GM-CSF+ T cells in the absence of BATF. Here, we found in a complete MHC class I-mismatched model that genetic inactivation of the IL-23 receptor (IL-23R) or the transcription factor retinoic acid-related orphan receptor gamma t (RORγt) within donor T cells similarly ablated Th17 cell formation in vivo but preserved the T cells' ability to induce intestinal GvHD in a compared to wild-type controls indistinguishable manner. Importantly, RORγt-independent manifestation of intestinal GvHD was completely dependent on BATF-regulated GM-CSF+ T cells as BATF/RORγt double-deficient T cells failed to induce colitis and the antibody-mediated blockage of IL-7/IL-7R interaction and GM-CSF significantly diminished signs of intestinal GvHD elicited by RORγt-deficient donor T cells. Finally, in analogy to our murine studies, colonic RORC expression levels inversely correlated with the presence of GvHD in allo-HSCT patients. Together, this study provides a crucial example of a BATF-dependent, however, IL-23R signaling- and RORγt-, i.e., Th17 fate-independent regulation of a colitogenic T cell population critically impacting the current understanding of intestinal GvHD.
EVALuna2:34273

Targeting interleukins for the treatment of inflammatory bowel disease-what lies beyond anti-TNF therapy? - Mclean, Mairi H.; Neurath, Markus; Durum, Scott K. (Inflammatory Bowel Diseases, 2014)
: Inflammatory bowel disease accounts for significant patient morbidity in the Western world. Several immunosuppressive therapies are available but are associated with potential significant adverse effects. In addition, there remains a cohort of patients with refractory or relapsing disease. Therefore, the search for novel therapeutic agents continues. In this review, we evaluate the role of a number of designated cytokines that are candidates in the pathogenesis of inflammatory bowel disease and discuss how their manipulation has been explored as a therapeutic strategy for this disease. The interleukins (ILs) chosen for discussion reflect those that currently show most promise as future therapeutic targets, as well as discussing the role of some of the most recently identified ILs, such as IL-27, IL-33, IL-35, and IL-22, in this context.
EVALuna2:1898

Targeting mucosal healing in Crohn’s disease: what the clinician needs to know - Klenske, Entcho; Bojarski, Christian; Waldner, Maximilian; Rath, Timo; Neurath, Markus; Atreya, Raja (Therapeutic Advances in Gastroenterology, 2019)
In recent years, mucosal healing has emerged as a key therapeutic goal in the clinical management of patients with Crohn’s disease, as it has been associated with improved long-term clinical outcomes. With the vast improvements in endoscopic imaging techniques and the increase in available treatment options, which reportedly are able to induce mucosal healing, the practising physician is left to wonder: how is endoscopic mucosal healing exactly defined in Crohn’s disease, and how can it effectively be achieved and monitored in daily clinical practice? Within this review, we will give an overview of the ongoing debate about the definition of mucosal healing and the modalities to monitor inflammation, and finally present available therapies with the capacity to induce mucosal healing.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Crohn’s disease; endoscopy; imaging; mucosal healing

Targeting Muscular Hemoglobin Content for Classification of Peripheral Arterial Disease by Noninvasive Multispectral Optoacoustic Tomography - Günther, Josefine; Knieling, Ferdinand; Träger, Anna P.; Lang, Werner; Meyer, Alexander; Regensburger, Adrian; Wagner, Alexandra; Trollmann, Regina; Wölfle, Joachim; Klett, Daniel; Uter, Wolfgang; Uder, Michael; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2023)
Created from Fastlane, Scopus look-up

Targeting of the Tec Kinase ITK Drives Resolution of T Cell–Mediated Colitis and Emerges as Potential Therapeutic Option in Ulcerative Colitis - Lechner-Grimm, Kristina; Mott, Stefanie; Al-Saifi, Ragheed; Knipfer, Lisa; Wirtz, Stefan; Atreya, Raja; Vieth, Michael; Rath, Timo; Fraass, Tina; Winter, Zoltan; August, Avery; Luban, Jeremy; et al. (Gastroenterology, 2021)
Background & Aims: The molecular checkpoints driving T cell activation and cytokine responses in ulcerative colitis (UC) are incompletely understood. Here, we studied the Tec kinase ITK in UC. Methods: We analyzed patients with inflammatory bowel disease (n = 223) and evaluated ITK activity as well as the functional effects of cyclosporine-A (CsA). In addition, 3 independent murine colitis models were used to investigate the functional role of ITK. Finally, the activity of ITK was blocked via pharmacological inhibitors and genetically engineered mice. Readout parameters were mini-endoscopy, histopathology, mucosal T cell apoptosis, and cytokine production. Results: We found an expansion of pITK-expressing mucosal CD4+ T cells in UC rather than Crohn's disease that correlated with disease severity. CsA suppressed activation of ITK in cultured CD4+ T cells and calcineurin-containing microclusters adjacent to the T cell receptor signaling complex. Functionally, the capacity of CsA to suppress activity of experimental colitis was critically dependent on ITK. Genetic inactivation of Itk via gene targeting or induction of allele-sensitive Itk mutants prevented experimental colitis in 3 colitis models, and treatment with pharmacological ITK blockers suppressed established colitis. In addition, ITK controlled apoptosis and activation of mucosal Th2 and Th17 lymphocytes via NFATc2 signaling pathways. Conclusions: ITK activation was detected in UC and could be down-regulated in cultured T cells by CsA administration. Selective targeting of ITK emerges as an attractive approach for treatment of chronic intestinal inflammation and potentially UC by driving resolution of mucosal inflammation.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Cyclosporine A; Cytokines; IBD; ITK; Therapeutic Strategies

Targeting STAT3 Signaling in COL1+ Fibroblasts Controls Colitis-Associated Cancer in Mice - Heichler, Christina; Schmied, Anabel; Enderle, Karin; Scheibe, Kristina; Murawska, Marta; Schmid, Benjamin; Waldner, Maximilian; Neurath, Markus; Neufert, Clemens (Cancers, 2022)
Colorectal cancer (CRC) is a common disease and has limited treatment options. The importance of cancer-associated fibroblasts (CAFs) within the tumor microenvironment (TME) in CRC has been increasingly recognized. However, the role of CAF subsets in CRC is hardly understood and opposing functions of type I (COL1+) vs. type VI (COL6+) collagen-expressing subsets were reported before with respect to NFκB-related signaling. Here, we have focused on COL1+ fibroblasts, which represent a frequent CAF population in CRC and studied their role upon STAT3 activation in vivo. Using a dual strategy with a conditional gain-of-function and a conditional loss-of-function approach in an in vivo model of colitis-associated cancer, tumor development was evaluated by different readouts, including advanced imaging methodologies, e.g., light sheet microscopy and CT-scan. Our data demonstrate that the inhibition of STAT3 activation in COL1+ fibroblasts reduces tumor burden, whereas the constitutive activation of STAT3 promotes the development of inflammation-driven CRC. In addition, our work characterizes the co-expression and distribution of type I and type VI collagen by CAFs in inflammation-associated colorectal cancer using reporter mice. This work indicates a critical contribution of STAT3 signaling in COL1+ CAFs, suggesting that the blockade of STAT3 activation in type I collagen-expressing fibroblasts could serve as promising therapeutic targets in colitis-associated CRC. In combination with previous work by others and us, our current findings highlight the context-dependent roles of COL1+ CAFs and COL6+ CAFs that might be variable according to the specific pathway activated.
CRIS-Team Scopus Importer:2022-03-25
Keywords: AOM/DSS model; Collagen; Colorectal cancer; Fibroblast; Inflammation; Tumorigenesis

T cell aging in patients with colorectal cancer—what do we know so far? - Thoma, Oana-Maria; Neurath, Markus; Waldner, Maximilian (Cancers, 2021)
Colorectal cancer (CRC) continues to be one of the most frequently diagnosed types of cancers in the world. CRC is considered to affect mostly elderly patients, and the number of diagnosed cases increases with age. Even though general screening improves outcomes, the overall survival and recurrence-free CRC rates in aged individuals are highly dependent on their history of comorbidities. Furthermore, aging is also known to alter the immune system, and especially the adaptive immune T cells. Many studies have emphasized the importance of T cell responses to CRC. Therefore, understanding how age-related changes affect the outcome in CRC patients is crucial. This review focuses on what is so far known about age-related T cell dysfunction in elderly patients with colorectal cancer and how aged T cells can mediate its development. Last, this study describes the advances in basic animal models that have potential to be used to elucidate the role of aged T cells in CRC.
CRIS-Team Scopus Importer:2021-12-31
Keywords: Aging; Colorectal cancer; CRC; Exhaustion; Senescence; T cell aging

Teachability of multispectral optoacoustic tomography - Li, Yi; Gröhl, Janek; Haney, Briain; Caranovic, Milenko; Lorenz-Meyer, Eva; Papatheodorou, Nikolaos; Kempf, Julius; Regensburger, Adrian; Nedoschill, Emmanuel; Bühler, Adrian; Siebenlist, Gregor; Lang, Werner; et al. (Journal of Biophotonics, 2024)
To date, the appropriate training required for the reproducible operation of multispectral optoacoustic tomography (MSOT) is poorly discussed. Therefore, the aim of this study was to assess the teachability of MSOT imaging. Five operators (two experienced and three inexperienced) performed repositioning imaging experiments. The inexperienced received the following introductions: personal supervision, video meeting, or printed introduction. The task was to image the exact same position on the calf muscle for seven times on five volunteers in two rounds of investigations. In the first session, operators used ultrasound guidance during measurements while using only photoacoustic data in the second session. The performance comparison was carried out with full-reference image quality measures to quantitatively assess the difference between repeated scans. The study demonstrates that given a personal supervision and hybrid ultrasound real-time imaging in MSOT measurements, inexperienced operators are able to achieve the same level as experienced operators in terms of repositioning accuracy.
CRIS-Team Scopus Importer:2024-05-17
Keywords: MSOT; multispectral optoacoustic imaging; teachability; ultrasound

Telomerase deficiency reflects age-associated changes in CD4+T cells - Matthe, Diana; Thoma, Oana-Maria; Sperka, Tobias; Neurath, Markus; Waldner, Maximilian (Immunity & Ageing, 2022)
Background Amongst other systemic changes, aging leads to an immune dysfunction. On the molecular level, a hallmark of aging is telomere shortening. The functional relevance of telomerase, an enzyme capable of elongating telomeres in T cells upon antigen stimulation, is not fully understood. Studying the impact of telomere shortening on CD4+ T cells and especially Th1 effector function can provide a better understanding on immune dysfunctions in elderly. Results We investigated T cell numbers and differentiation in telomerase-deficient (mTerc-/-) mice under steady-state conditions and the functional role of telomerase in CD4+ T cells using in vitro stimulation and Th1 polarization protocols by comparing T cells from mTerc-/- and control mice. We report reduced relative CD4+ T cell numbers in blood and secondary lymphoid organs and a relative decline in the naive T cell population in thymus, blood and spleen of mTerc-/- mice compared to control mice. Importantly, after in vitro polarization, mTerc-/- G3 CD4+ T cells showed higher numbers of IFN gamma-producing cells and reduced expression of CD28. Notably, telomerase-deficient T cells were more susceptible to inhibition of Th1 polarization by IL-6 in vitro. These results demonstrate that telomerase deficiency recapitulates several changes of CD4+ T cells seen in aged humans regarding the naive T cell population, expression of CD28 and cytokine production. Conclusion Our data suggest that telomere shortening could play a key role in the aging of T cell immunity, with clinical implications for immune diseases and tumor development and that mTerc-/- mice are a suitable model to study aging-related defects of adaptive immunity.
CRIS-Team WoS Importer:2022-04-08

Temporally Distinct Functions of the Cytokines IL-12 and IL-23 Drive Chronic Colon Inflammation in Response to Intestinal Barrier Impairment - Eftychi, Christina; Schwarzer, Robin; Vlantis, Katerina; Wachsmuth, Laurens; Basic, Marijana; Wagle, Prerana; Neurath, Markus; Becker, Christoph; Bleich, André; Pasparakis, Manolis (Immunity, 2019)
Epithelial barrier defects are implicated in the pathogenesis of inflammatory bowel disease (IBD); however, the role of microbiome dysbiosis and the cytokine networks orchestrating chronic intestinal inflammation in response to barrier impairment remain poorly understood. Here, we showed that altered Schaedler flora (ASF), a benign minimal microbiota, was sufficient to trigger colitis in a mouse model of intestinal barrier impairment. Colitis development required myeloid-cell-specific adaptor protein MyD88 signaling and was orchestrated by the cytokines IL-12, IL-23, and IFN-γ. Colon inflammation was driven by IL-12 during the early stages of the disease, but as the mice aged, the pathology shifted toward an IL-23-dependent inflammatory response driving disease chronicity. These findings reveal that IL-12 and IL-23 act in a temporally distinct, biphasic manner to induce microbiota-driven chronic intestinal inflammation. Similar mechanisms might contribute to the pathogenesis of IBD particularly in patients with underlying intestinal barrier defects.
CRIS-Team Scopus Importer:2019-08-23
Keywords: altered Schaedler flora; dysbiosis; IFN-γ; IL-12; IL-23; inflammatory bowel disease; intestinal barrier impairment; intestinal inflammation; microbiota; MyD88

TGFβ and the Tumor Microenvironment in Colorectal Cancer - Waldner, Maximilian; Neurath, Markus (Cells, 2023)
Growing evidence supports an important role of the tumor microenvironment (TME) in the pathogenesis of colorectal cancer (CRC). Resident cells such as fibroblasts or immune cells infiltrating into the TME maintain continuous crosstalk with cancer cells and thereby regulate CRC progression. One of the most important molecules involved is the immunoregulatory cytokine transforming growth factor-β (TGFβ). TGFβ is released by various cells in the TME, including macrophages and fibroblasts, and it modulates cancer cell growth, differentiation, and cell death. Mutations in components of the TGF pathway, including TGFβ receptor type 2 or SMAD4, are among the most frequently detected mutations in CRC and have been associated with the clinical course of disease. Within this review, we will discuss our current understanding about the role of TGFβ in the pathogenesis of CRC. This includes novel data on the molecular mechanisms of TGFβ signaling in TME, as well as possible strategies for CRC therapy targeting the TGFβ pathway, including potential combinations with immune checkpoint inhibitors.
CRIS-Team Scopus Importer:2023-05-12
Keywords: colorectal cancer; immune response; SMAD4; TGFβ; tumor microenvironment

Th17 Cell-Mediated Colitis Is Positively Regulated by Interferon Regulatory Factor 4 in a T Cell-Extrinsic Manner - Buchele, Vera; Konein, Patrick; Vogler, Tina; Kunert, Timo; Enderle, Karin; Khan, Hanif; Büttner-Herold, Maike; Lehmann, Christian; Amon, Lukas; Wirtz, Stefan; Dudziak, Diana; Neurath, Markus; et al. (Frontiers in Immunology, 2021)
Inflammatory bowel diseases (IBDs) are characterized by chronic, inflammatory gastrointestinal lesions and often require life-long treatment with immunosuppressants and repetitive surgical interventions. Despite progress in respect to the characterization of molecular mechanisms e.g. exerted by TNF-alpha, currently clinically approved therapeutics fail to provide long-term disease control for most patients. The transcription factor interferon regulatory factor 4 (IRF4) has been shown to play important developmental as well as functional roles within multiple immune cells. In the context of colitis, a T cell-intrinsic role of IRF4 in driving immune-mediated gut pathology is established. Here, we conversely addressed the impact of IRF4 inactivation in non-T cells on T cell driven colitis in vivo. Employing the CD4+CD25− naïve T cell transfer model, we found that T cells fail to elicit colitis in IRF4-deficient compared to IRF4-proficient Rag1−/− mice. Reduced colitis activity in the absence of IRF4 was accompanied by hampered T cell expansion both within the mesenteric lymph node (MLN) and colonic lamina propria (cLP). Furthermore, the influx of various myeloids, presumably inflammation-promoting cells was abrogated overall leading to a less disrupted intestinal barrier. Mechanistically, gene profiling experiments revealed a Th17 response dominated molecular expression signature in colon tissues of IRF4-proficient, colitic Rag1−/− but not in colitis-protected Rag1−/−Irf4−/− mice. Colitis mitigation in Rag1−/−Irf4−/− T cell recipients resulted in reduced frequencies and absolute numbers of IL-17a-producing T cell subsets in MLN and cLP possibly due to a regulation of conventional dendritic cell subset 2 (cDC2) known to impact Th17 differentiation. Together, extending the T cell-intrinsic role for IRF4 in the context of Th17 cell driven colitis, the provided data demonstrate a Th17-inducing and thereby colitis-promoting role of IRF4 through a T cell-extrinsic mechanism highlighting IRF4 as a putative molecular master switch among transcriptional regulators driving immune-mediated intestinal inflammation through both T cell-intrinsic and T cell-extrinsic mechanisms. Future studies need to further dissect IRF4 controlled pathways within distinct IRF4-expressing myeloid cell types, especially cDC2s, to elucidate the precise mechanisms accounting for hampered Th17 formation and, according to our data, the predominant mechanism of colitis protection in Rag1−/−Irf4−/− T cell receiving mice.
CRIS-Team Scopus Importer:2021-02-26
Keywords: inflammatory bowel disease (IBD); interferon regulatory factor 4 (IRF4); intestinal inflammation; myeloid cells; Th17

Th9 cells in immunity and immunopathological diseases - Neurath, Markus; Kaplan, Mark H. (Seminars in Immunopathology, 2017)
EVALuna2:33830

Th9 cells in inflammatory bowel diseases - Weigmann, Benno; Neurath, Markus (Seminars in Immunopathology, 2017)
Inflammatory bowel diseases are chronic, relapsing, immunologically mediated disorders of the gastrointestinal tract. Emerging evidence suggests a critical functional role of transcription factors and T cell-related cytokines in ulcerative colitis and Crohn's disease. Gut-residing T cells from patients with inflammatory bowel disease produce high amounts of IL-9. Experimental models of colitis highlighted that IL-9-producing T cells critically interfered with an intact barrier function of the intestinal epithelium by impacting cellular proliferation and tight junction molecules. The blockade of IL-9 was suited to significantly ameliorate the disease activity and severity in experimental models of inflammatory bowel disease thereby suggesting that targeting IL-9 might function as a novel targeted approach for therapy.
EVALuna2:33831

TH9 cells that express the transcription factor PU.1 drive T cell-mediated colitis via IL-9 receptor signaling in intestinal epithelial cells - Gerlach, Katharina; Hwang, Youyi; Nikolaev, Alexej; Atreya, Raja; Dornhoff, Heike; Steiner, Stefanie; Lehr, Hans-Anton; Wirtz, Stefan; Waisinan, Ari; Rosenbauer, Frank; Mckenzie, Andrew N. J.; Weigmann, Benno; et al. (Nature Immunology, 2014)
The molecular checkpoints that drive inflammatory bowel diseases are incompletely understood. Here we found more T cells expressing the transcription factor PU.1 and interleukin 9 (IL-9) in patients with ulcerative colitis. In an animal model, citrine reporter mice had more IL-9-expressing mucosal T cells in experimental oxazolone-induced colitis. IL-9 deficiency suppressed acute and chronic colitis. Mice with PU.1 deficiency in T cells were protected from colitis, whereas treatment with antibody to IL-9 suppressed colitis. Functionally, IL-9 impaired intestinal barrier function and prevented mucosal wound healing in vivo. Thus, our findings suggest that the TH9 subset of helper T cells serves an important role in driving ulcerative colitis by regulating intestinal epithelial cells and that TH9 cells represent a likely target for the treatment of chronic intestinal inflammation.
EVALuna2:1845

The activating protein 1 transcription factor basic leucine zipper transcription factor, ATF-like (BATF), regulates lymphocyte- and mast cell-driven immune responses in the setting of allergic asthma - Ubel, Caroline; Sopel, Nina; Graser, Anna; Hildner, Kai; Reinhardt, Cornelia; Zimmermann, Theodor; Rieker, Ralf Joachim; Maier, Anja; Neurath, Markus; Murphy, Kenneth M.; Finotto, Susetta (Journal of Allergy and Clinical Immunology, 2014)
Mice without the basic leucine zipper transcription factor, ATF-like (BATF) gene (Batf(-/-)) lack TH17 and follicular helper T cells, which demonstrates that Batf is a transcription factor important for T- and B-cell differentiation.In this study we examined whether BATF expression would influence allergic asthma.In a cohort of preschool control children and children with asthma, we analyzed BATF mRNA expression using real-time PCR in PBMCs. In a murine model of allergic asthma, we analyzed differences in this allergic disease between wild-type, Batf transgenic, and Batf(-/-) mice.In the absence of corticosteroid treatment, children with recurrent asthma have a significant increase in BATF mRNA expression in their PBMCs. Batf(-/-) mice display a significant reduction in the pathophysiologic responses seen in asthmatic wild-type littermates. Moreover, we discovered a decrease in IL-3 production and IL-3-dependent mast cell development in Batf(-/-) mice. By contrast, IFN-? was induced in lung CD4(+) and CD8(+) T cells. Intranasal delivery of anti-IFN-? antibodies induced airway hyperresponsiveness and inflammation in wild-type but not in Batf(-/-) mice. Transgenic overexpression of Batf under the control of the CD2 promoter/enhancer augmented lung inflammation and IgE levels in the setting of experimental asthma.BATF is increased in non-steroid-treated asthmatic children. Targeting BATF expression resulted in amelioration of the pathophysiologic responses seen in children with allergic asthma, and BATF has emerged as a novel target for antiasthma interventions.
EVALuna2:1742

THE AMOUNT OF LIVER TISSUE IS ESSENTIAL FOR ACCURATE HISTOLOGICAL STAGING IN PATIENTS WITH AUTOIMMUNE HEPATITIS - Vetter, Marcel; Kremer, Andreas; Agaimy, Abbas; Konturek, P. C.; Pfeifer, L.; Neurath, Markus; Zopf, Steffen; Siebler, Jürgen (Journal of Physiology and Pharmacology, 2021)
The gold standard for the evaluation of liver fibrosis is histology. However, the heterogenous distribution of fibrosis limits the sensitivity of histology. The collection of two samples with a 16G needle is therefore recommended to reduce the risk of sampling error. The aim of this study was to investigate whether this standard is also applicable to patients with autoimmune hepatitis (AIH). This retrospective study included patients with AIH, who underwent mini-laparoscopic biopsy at our center between 2011 and 2020 (n = 32). Diagnosis was verified by usage of the simplified AIH score (>= 6). Patients were categorized into three groups, based on the number of portal fields (PF) in the collected liver tissue (< 10 PF, 10 - 19 PF, >= 20 PF). We correlated the histological staging for these groups with the mini-laparoscopic fibrosis score (MLFS). Furthermore, non-invasive methods for the assessment of fibrosis were correlated with the histological staging (acoustic radiation force impulse (ARFI) and FIB-4 score). MLFS correlated well with histological staging (r = 0.649, p = 0.0001). The correlation between MLFS and histology improved with higher numbers of histologically analyzed portal fields (< 10 PF: r = 0.400, p = 0.378; 10 - 19 PF: r = 0.5467, p = 0.023; >= 20 PF: r = 0.956, p = 0.0002). The probability of collecting at least 10 or 20 portal fields was dependent on the number and diameter of the samples. For all patients with at least two 16G biopsies, 10 or more PF were available. With three 16G biopsies, at least 20 PF were obtained for all patients. ARFI correlated with MLFS and histological staging only in patients with low/moderate-grade inflammation as defined by ALT < 10xULN (upper limit of normal) (MLFS: r = 0.723; p = 0.004; histology: r = 0.619, p = 0.018). FIB-4 did not correlate with histological staging. The amount of liver tissue obtained by liver biopsy is crucial to minimalize the risk of sampling error and thus underestimation of fibrosis. This study was the first to investigate the amount of liver tissue required for histological staging in AIH. Our data suggest that diagnostic accuracy is likely to be higher with 20 PF compared to the generally recommended 10 PF. We therefore recommend to perform three biopsies with a 16G needle in (suspected) AIH patients. ARFI correlated well with histological staging unless inflammatory activity is high.
CRIS-Team WoS Importer:2021-10-29

The Application of Hemospray in Gastrointestinal Bleeding during Emergency Endoscopy - Hagel, Alexander; Albrecht, Heinz; Naegel, Andreas; Vitali, Francesco; Vetter, Marcel; Dauth, Christine; Neurath, Markus; Raithel, Martin (Gastroenterology Research and Practice, 2017)
Introduction . Gastrointestinal bleeding represents the main indication for emergency endoscopy (EE). Lately, several hemostatic powders have been released to facilitate EE.Methods. We evaluated all EE in which Hemospray was used as primary or salvage therapy, with regard to short- and long-term hemostasis and complications.Results. We conducted 677 EE in 474 patients (488 examinations in 344 patients were upper GI endoscopies). Hemospray was applied during 35 examinations in 27 patients (19 males), 33 during upper and 2 during lower endoscopy. It was used after previous treatment in 21 examinations (60%) and in 14 (40%) as salvage therapy. Short-term success was reached in 34 of 35 applications (97.1%), while long-term success occurred in 23 applications (65.7%). Similar long-term results were found after primary application (64,3%) or salvage therapy (66,7%). Rebleeding was found in malignant and extended ulcers. One major adverse event (2.8%) occurred with gastric perforation after Hemospray application.Discussion. Hemospray achieved short-term hemostasis in virtually all cases. The long-term effect is mainly determined by the type of bleeding source, but not whether it was applied as first line or salvage therapy. But, even in the failures, patients had benefit from hemodynamic stabilization and consecutive interventions in optimized conditions.
EVALuna2:33829

The Clinical Research Group 257, "CEDER" Molecular Pathogenesis and Optimized Therapy of Chronic inflammatory Bowel Diseases - Becker, Christoph; Neurath, Markus (Zeitschrift für Gastroenterologie, 2017)
EVALuna2:33814

The G protein-coupled receptor MRGX4 is a novel receptor for bile salts expressed on sensory neurons - Wolf, Katharina; Kühn, Helen; Leibl, Victoria; Gebhardt, Lisa; Glaudo, Markus; Reeh, Peter; Fischer, Michael J. M.; Neurath, Markus; Namer, Barbara; Kremer, Andreas (SWISS MEDICAL WEEKLY, 2021)
CRIS-Team WoS Importer:2022-03-11

The gut-brain axis in inflammatory bowel disease—current and future perspectives - Günther, Claudia; Rothhammer, Veit; Karow, Marisa; Neurath, Markus; Winner, Beate (International Journal of Molecular Sciences, 2021)
The gut–brain axis is a bidirectional communication system driven by neural, hormonal, metabolic, immunological, and microbial signals. Signaling events from the gut can modulate brain function and recent evidence suggests that the gut–brain axis may play a pivotal role in linking gastrointestinal and neurological diseases. Accordingly, accumulating evidence has suggested a link between inflammatory bowel diseases (IBDs) and neurodegenerative, as well as neuroinflammatory diseases. In this context, clinical, epidemiological and experimental data have demonstrated that IBD predisposes a person to pathologies of the central nervous system (CNS). Likewise, a number of neurological disorders are associated with changes in the intestinal environment, which are indicative for disease-mediated gut–brain inter-organ communication. Although this axis was identified more than 20 years ago, the sequence of events and underlying molecular mechanisms are poorly defined. The emergence of precision medicine has uncovered the need to take into account non-intestinal symptoms in the context of IBD that could offer the opportunity to tailor therapies to individual patients. The aim of this review is to highlight recent findings supporting the clinical and biological link between the gut and brain, as well as its clinical significance for IBD as well as neurodegeneration and neuroinflammation. Finally, we focus on novel human-specific preclinical models that will help uncover disease mechanisms to better understand and modulate the function of this complex system.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Ex vivo organ models; Gut-brain axis; IBD; MS; PD

The impact of hospitalization on the performance of capsule endoscopy (CE) - Albrecht, Heinz; Vetter, Marcel; Dauth, Wolfgang; Zoicas, Flavius; Neurath, Markus; Hagel, Alexander (Digestive and Liver Disease, 2017)
BACKGROUND: For proper evaluation of capsule endoscopy (CE), a complete examination is necessary. AIM: We evaluated risk factors of an incomplete CE with focus on patient hospitalization. METHODS: We retrospectively evaluated 161 consecutive patients who underwent CE between 01.07.2013 and 13.03.2016. Main indications were active bleeding, iron deficiency anemia (IDA), inflammatory bowel disease (IBD), abdominal pain, and familial adenomatous polyposis (FAP). RESULTS: We report the results of 103 in-patients and 56 out-patients. Eighty-two patients were male, average age was 58.9 years (range 18-90). Indications for CE were active bleeding (103 patients), IDA and IBD (16 patients), and FAP, abdominal pain and others (eight examinations each). All FAP patients were out-patients, but showed the longest small bowel transit time (SBTT) of 443.6min (p=0.0001). The shortest SBTT was found in out-patients without FAP (267.5min, p<0.05). In the in-patient group, nine endoscopies did not record the entire small bowel (8.7%) due to battery depletion, compared with only one incomplete examination in the out-patients (1.8%, p=0.036). We found pathologic lesions in the last 30min of the SBTT in 43 patients, and this indicates the necessity for complete examination. Thirteen of these 43 patients showed major lesions such as ulcers or angiodysplasia in this last region alone. CONCLUSION: In-patients might require special treatment to ensure complete examination, since a considerable amount of pathologies can only be found in the ileum.
EVALuna2:33812

The importance of pancreatic inflammation in endosonographic diagnostics of solid pancreatic masses - Vitali, Francesco; Strobel, Deike; Frulloni, Luca; Heinrich, Marc Christopher; Pfeifer, Lukas; Görtz, Rüdiger; Hundorfean, Gheorghe; Wachter, David Lukas; Wachter, David; Grützmann, Robert; Bernatik, Thomas; Neurath, Markus; et al. (Medical Ultrasonography, 2018)
AIMS: Endosonography (EUS) is one of the main diagnostic tools for the differential diagnosis of pancreatic masses. The aim of our study was to describe the value of this technique in the work-up of solid pancreatic lesions, considering the influence of the morphological evidence of pancreatic inflammation in the diagnostic process. MATERIAL AND METHODS: Retrospective analysis of prospectively collected data in our tertiary University center. From March 2007 to October 2015, 218 patients underwent EUS for a suspected solid pancreatic neoplasm (based on previous cross-sectional imaging results, idiopatic acute pancreatitis, weight loss, pancreatic hyperenzymemia, painless jaundice or elevated Ca 19-9 values). RESULTS: Malignant lesions were diagnosed in 98 (45%) patients. Sensitivity of EUS for malignancy was 91% and specificity 89.2%. Signs of pancreatic inflammation in the surrounding pancreatic parenchyma around the focal lesion were present in 97 patients (44.4%)(more often in men, smokers and drinkers, and the most common etiology was focal chronic pancreatitis) and in these patients the sensitivity and sensibility dropped to 44% and 87.1%, respectively. In patients without signs of pancreatic inflammation, the pancreatic focal lesions were adenocarcinoma, neuroendocrine tumor, ventral/dorsal split, non-pancreatic pathology, pancreatic lipomatosis and autoimmune pancreatitis. CONCLUSION: Pancreatic inflammation (either focal or involving the whole gland) lowers the diagnostic sensibility of EUS in the work- up of pancreatic masses suspected for cancer, requiring further invasive diagnostic methods. Focal autoimmune pancreatitis and paraduodenal pancreatitis are still confused with pancreatic cancer, even in the absence of pancreatic inflammation.
EVALuna2:35194

The Influence of Physical Training on Breast Cancer: The Role of Exercise-Induced Myokines in Regulating Breast Cancer Cell Growth and Survival - Natarajan, Anirudh; Pradhan, Rashmita; Dieterich, Walburga; Schwappacher, Raphaela; Reljic, Dejan; Herrmann, Hans Joachim; Neurath, Markus; Hack, Carolin; Beckmann, Matthias; Zopf, Yurdagül (International Journal of Molecular Sciences, 2024)
The beneficial impact of physical training in lowering cancer risk is well known. However, the precise mechanisms linking physical training and cancer are not fully understood. Skeletal muscle releases various myokines that seem to possess a direct anti-tumor effect. Although breast cancer (BC) is the prevalent form of cancer among women on a global scale, only limited data are available about the secretion of myokines following exercise in patients with BC. To study the effects of exercise on BC, the blood samples of patients with varied stages of BC were analyzed after 12 weeks of resistance training with whole-body electromyostimulation (WB-EMS). Following the training period, we observed that resistance training helps these patients to improve their physical characteristics and performance function by increasing skeletal muscle mass and strengthening their hand grip. Notably, the patient’s serum was found to inhibit the growth and promote the apoptosis of BC cells in vitro. Moreover, the conditioned medium collected from in vitro stimulated human myotubes using electric pulse stimulation (EPS), an in vitro simulation of WB-EMS training, induced the cell death of BC cells. These results highlighted the direct cancer-protective effects of activated skeletal muscle. In line with our observed effects of serum from exercise-trained pancreatic and prostate cancer patients, the growth of BC cells was notably inhibited when supplemented directly with recombinant myokines C-X-C motif ligand 1 (CXCL1), Interleukin 10 (IL10), and C-C motif chemokine ligand 4 (CCL4). Notably, treatment with these myokines also increased the expression of caspase 3/7 (Casp3/7), resulting in enhanced BC cell death. Our data strongly suggest that physical exercise has a positive impact on skeletal muscle mass and hand grip strength in BC patients, along with a significant anti-tumor effect in BC cells. This shows promising potential for considering sports and physical training as supportive therapies for achieving more impactful cancer treatment.
CRIS-Team Scopus Importer:2024-11-22
Keywords: apoptosis; breast cancer; electric pulse stimulation; myokines; proliferation; resistance training; whole-body electromyostimulation

The Intestinal Microbiota in Inflammatory Bowel Disease - Becker, Christoph; Neurath, Markus; Wirtz, Stefan (IlAR Journal, 2015)
The intestinal microbiota has important metabolic and host-protective functions. Conversely to these beneficial functions, the intestinal microbiota is thought to play a central role in the etiopathogenesis of inflammatory bowel disease (IBD; Crohn's disease and ulcerative colitis), a chronic inflammation of the gut mucosa. Genetic screens and studies in experimental mouse models have clearly demonstrated that IBD can develop due to excessive translocation of bacteria into the bowel wall or dysregulated handling of bacteria in genetically susceptible hosts. In healthy individuals, the microbiota is efficiently separated from the mucosal immune system of the gut by the gut barrier, a single layer of highly specialized epithelial cells, some of which are equipped with innate immune functions to prevent or control access of bacterial antigens to the mucosal immune cells. It is currently unclear whether the composition of the microbial flora or individual bacterial strains or pathogens induces or supports the pathogenesis of IBD. Further research will be necessary to carefully dissect the contribution of individual bacterial species to this disease and to ascertain whether specific modulation of the intestinal microbiome may represent a valuable further option for future therapeutic strategies.
EVALuna2:2000

The JAK1/3 Inhibitor to Tofacitinib Suppresses T Cell Homing and Activation in Chronic Intestinal Inflammation - Gerlach, Katharina; Lechner, Kristina; Popp, Vanessa; Offensperger, Laura; Zundler, Sebastian; Wiendl, Maximilian; Becker, Emily; Atreya, Raja; Rath, Timo; Neurath, Markus; Weigmann, Benno (Journal of Crohns & Colitis, 2021)
Background and Aims: The molecular mechanism of action of the Janus kinase [JAK] inhibitor tofacitinib is poorly understood. Methods: Here we analysed the inhibitory effect of tofacitinib on mucosal and blood T cells from patients with ulcerative colitis [UC]. Furthermore, tofacitinib treatment was analysed in experimental colitis models and wound healing. Additionally, tofacitinib effects were analysed in bioassays. Results: Tofacitinib significantly reduced T cell-derived inflammatory cytokine production [Th2, Th9, Th17] in patients with active UC. Additionally, impaired expression of the homing receptors alpha4/beta1 and alpha4/beta7, as well as reduced gut homing capacity of T cells in a humanised mouse model of colitis, were observed. Tofacitinib suppressed acute and chronic oxazolone colitis, compared with untreated wild-type mice, associated with downregulation of cytokines produced by Th2, Th9, and Th17 cells. Functionally, tofacitinib induced apoptosis of intestinal epithelial cells and prevented mucosal wound healing in vivo at higher concentration. Thus, our findings suggest that tofacitinib is quite effective in protecting from colitis, by inhibition of a bundle of T cell-derived cytokines like IL-5, IL-6, IL-9, IL-13, and IL-17A. Conclusions: Application of tofacitinib emerges as an attractive concept for treatment of chronic intestinal inflammation at lower concentrations, whereas higher concentrations require attention due to prolonged wound healing.
CRIS-Team Scopus Importer:2021-05-07
Keywords: cytokines; inflammatory bowel disease; T cells; Tofacitinib; wound healing

The Memory T Cell “Communication Web” in Context with Gastrointestinal Disorders—How Memory T Cells Affect Their Surroundings and How They Are Influenced by It - Knauß, Annkathrin; Gabel, Michael; Neurath, Markus; Weigmann, Benno (Cells, 2022)
Gut-related diseases like ulcerative colitis, Crohn’s disease, or colorectal cancer affect millions of people worldwide. It is an ongoing process finding causes leading to the development and manifestation of those disorders. This is highly relevant since understanding molecular processes and signalling pathways offers new opportunities in finding novel ways to interfere with and apply new pharmaceuticals. Memory T cells (mT cells) and their pro-inflammatory properties have been proven to play an important role in gastrointestinal diseases and are therefore increasingly spotlighted. This review focuses on mT cells and their subsets in the context of disease pathogenesis and maintenance. It illustrates the network of regulatory proteins and metabolites connecting mT cells with other cell types and tissue compartments. Furthermore, the crosstalk with various microbes will be a subject of discussion. Characterizing mT cell interactions will help to further elucidate the sophisticated molecular and cellular networking system in the intestine and may present new ideas for future research approaches to control gut-related diseases.
CRIS-Team Scopus Importer:2022-10-07
Keywords: colorectal cancer; Crohn’s disease; etrolizumab; IBD; immune cells; interactions; memory T cells; metabolites; microbiota; ozanimod; ulcerative colitis; vedolizumab

The Microbiome in Visceral Medicine: Inflammatory Bowel Disease, Obesity and Beyond - Chiriac, Mircea T.; Mahapatro, Mousumi; Neurath, Markus; Becker, Christoph (Visceral Medicine, 2017)
It has become increasingly evident over the past two decades that the microbiota plays a nurturing role in the development of the immune system. This appears to be important since the amplitude of immune responses has a crucial regulatory function in homeostasis and the prevention of unwanted inflammation. Hence, a malfunctioning gut flora has been shown to play a key role in visceral medicine. Strong evidence demonstrates for example that intestinal inflammation can develop as a result of a dysregulated microbiota, deficient antimicrobial responses, and aberrant bacterial translocation into the bowel wall. In healthy individuals, the bacterial translocation is blocked by a single layer of highly specialized intestinal epithelial cells which forms a strong barrier that lines the gut wall. This structure is responsible for an efficient absorption of nutrients while keeping the luminal flora at bay. In susceptible individuals, for yet incompletely understood reasons, either defective epithelial barrier function or dysregulated microbial composition or microbial pathogens drive intestinal inflammation. Many therapeutic strategies focusing on the modulation of the microbiota have been proposed recently but future research including prospective human studies and gnotobiotic mouse models are still needed to evaluate the contribution and potential therapeutic value of individual bacteria to human health.
EVALuna2:35240

The Ominous Ouzo Party - A Case Series of Four Patients with Accidental Alkali Ingestion - Vetter, Marcel; Rath, Timo; Siebler, Jürgen; Waldner, Maximilian; Neurath, Markus; Pfeifer, Lukas (Clinical and Experimental Gastroenterology, 2021)
Background: Ingestion of alkaline fluids is a common problem, which can lead to perforations, strictures and malignancy. We present a rare case series of several patients who accidentally ingested the same alkaline substance in different doses.
CRIS-Team WoS Importer:2021-07-30

The outcome of patients with inflammatory bowel disease-associated colorectal cancer is not worse than that of patients with sporadic colorectal cancer-a matched-pair analysis of survival - Vitali, Francesco; Wein, Axel; Rath, Timo; Eckstein, Markus; Neufert, Clemens; Siebler, Jürgen; Atreya, Raja; Hartmann, Arndt; Hohenberger, Werner; Weber, Klaus; Neurath, Markus; Grützmann, Robert; et al. (International Journal of Colorectal Disease, 2021)
Purpose Patients with inflammatory bowel disease (IBD) have an increased risk for colorectal cancer (CRC). In IBD patients, cancer is often diagnosed in advanced stages and conflicting data on survival compared to sporadic CRC have been reported. The aim of this study was to directly compare clinical characteristics and prognosis of patients with IBD-CRC and sporadic CRC. Methods The clinical and pathological data of 63 patients with IBD-CRC and 3710 patients with sporadic CRC treated at the University Hospital of Erlangen between 1995 and 2015 were compared. Forty-seven M0 patients with IBD were matched with sporadic CRC patients after curative resection (R0) according to tumor localization, stage, sex, and year of treatment. Overall and disease-free survival were compared. Results Sixty-three patients presented IBD-CRC. Fifty were affected with ulcerative colitis (UC) and 13 with Crohn's disease (CD). CRC was diagnosed within 1.45 years since last endoscopic surveillance. Twelve patients (19%) had a diagnosis of primary sclerosing cholangitis. In matched analysis, IBD patients were diagnosed with CRC at younger age compared to sporadic CRC and were more likely to have right-sided CRC (40% versus 23.3%) and rare histological subtypes (19% versus 9.2%). No differences in 5-year overall (78.7 versus 80.9 months) and 5-year disease-free survival (74.5 versus 70.2 months) were noted. Conclusion IBD-CRC patients were younger and more frequently had right-sided carcinomas compared to sporadic CRC. CRC in IBD patients did not show survival difference compared to matched-pair sporadic CRC patients without distant metastases after curative resection. Surveillance might be important for early detection of CRC in IBD patients.
CRIS-Team WoS Importer:2021-12-17

The Positive Rate of Pulmonary Embolism by CT Pulmonary Angiography Is High in an Emergency Department, even in Low-Risk or Young Patients - Al-Zaher, Nizam; Vitali, Francesco; Neurath, Markus; Görtz, Rüdiger (Medical Principles and Practice, 2021)
Objective: The clinical presentation of pulmonary embolism (PE) can be various and misleading. We analyzed patients with suspicion of PE and subsequently performed computed tomography pulmonary angiography (CTPA) in an emergency department of Internal Medicine, focusing on patient groups in which PE might be underestimated in the emergency setting, such as young patients and patients with low clinical probability. Material and Methods: In 2016 and 2017, all patients receiving a CTPA for investigation of PE were retrospectively evaluated for clinical parameters (age, symptoms, and vital parameters) and D-dimers. The Wells score was calculated. Results: CTPA was performed in 323 patients (158 female and 165 male; mean age 62 years). The leading symptoms for admission were dyspnea or chest pain; 62% showed intermediate or high risk for PE, calculated by applying the Wells score. In 123 (38%) of all patients, a PE was proved and pathologic age-Adjusted D-dimers were found in 97.6%. Thirty of 121 (25%) patients with low risk according to Wells score had a PE. Deep vein thrombosis was verified in 67/123 (55%) patients; 43% (15/35) of all suspicions for PE in patients <40 years were positive with 4/15 (26%), showing a central PE. Younger patients (<40 years) with PE presented more often with tachycardia or tachypnea and chest pain or dyspnea than elderly patients with PE. Conclusion: CTPA frequently proves a PE in patients with suspicion of PE in an emergency department of Internal Medicine. If PE is suspected and CTPA performed accordingly, the presence of PE is quite common even in low-risk patient groups (Wells score) or in young patients <40 years with chest pain or dyspnea.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Chest pain; CT pulmonary angiography; Dyspnea; Emergency; Pulmonary embolisms

The Proteomic Signature of Tissue Remodeling in Chronic Intestinal Inflammation - Neurath, Markus (Cellular and Molecular Gastroenterology and Hepatology, 2024)
CRIS-Team Scopus Importer:2024-03-22

The pseudokinase MLKL mediates programmed hepatocellular necrosis independently of RIPK3 during hepatitis - Lopez Posadas, Rocío; Becker, Christoph; Günther, Claudia; Tenzer, Stefan; Amann, Kerstin Ute; Billmeier, Ulrike; Atreya, Raja; Fiorino, Gionata; Vetrano, Stefania; Danese, Silvio; Ekici, Arif Bülent; Wirtz, Stefan; et al. (Journal of Clinical Investigation, 2016)
Although necrosis and necroinflammation are central features of many liver diseases, the role of programmed necrosis in the context of inflammation-dependent hepatocellular death remains to be fully determined. Here, we have demonstrated that the pseudokinase mixed lineage kinase domain-like protein (MLKL), which plays a key role in the execution of receptor-interacting protein (RIP) kinase-dependent necroptosis, is upregulated and activated in human autoimmune hepatitis and in a murine model of inflammation-dependent hepatitis. Using genetic and pharmacologic approaches, we determined that hepatocellular necrosis in experimental hepatitis is driven by an MLKL-dependent pathway that occurs independently of RIPK3. Moreover, we have provided evidence that the cytotoxic activity of the proinflammatory cytokine IFN-? in hepatic inflammation is strongly connected to induction of MLKL expression via activation of the transcription factor STAT1. In summary, our results reveal a pathway for MLKL-dependent programmed necrosis that is executed in the absence of RIPK3 and potentially drives the pathogenesis of severe liver diseases.
EVALuna2:2178

The Randomized AMBORA Trial: Impact of Pharmacological/Pharmaceutical Care on Medication Safety and Patient-Reported Outcomes During Treatment With New Oral Anticancer Agents - Dürr, Pauline; Schlichtig, Katja; Kelz, Carolin; Deutsch, Birgit; Maas, Renke; Eckart, Michael J.; Wilke, Jochen; Wagner, Harald; Wolff, Kerstin; Preuß, Caroline; Brückl, Valeska; Meidenbauer, Norbert; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Oral anticancer drugs (eg, kinase inhibitors) play an important role in cancer therapy. However, considerable challenges regarding medication safety of oral anticancer drugs have been reported. Randomized, controlled, multicenter studies on the impact of intensified clinical pharmacological/pharmaceutical care on patient safety and patient treatment perception are lacking. METHODS: Patients were eligible for the randomized, multicenter AMBORA study, if they were newly started on any of the oral anticancer drugs approved in 2001 or later without restriction to certain tumor entities. Patients were randomly assigned to receive either standard of care (control group) or an additional, intensified clinical pharmacological/pharmaceutical care, which included medication management and structured patient counseling, over a period of 12 weeks (intervention group). Primary end points were the number of antitumor drug-related problems (ie, side effects and unresolved medication errors) and patient treatment satisfaction with the oral anticancer therapy after 12 weeks measured with the Treatment Satisfaction Questionnaire for Medication, category convenience. RESULTS: Two hundred two patients were included. Antitumor drug-related problems were significantly lower in the intervention compared with the control group (3.85 v 5.81 [mean], P < .001). Patient treatment satisfaction was higher in the intervention group (Treatment Satisfaction Questionnaire for Medication, convenience; 91.6 v 74.4 [mean], P < .001). The hazard ratio for the combined end point of severe side effects (Common Terminology Criteria for Adverse Events ≥ 3), treatment discontinuation, unscheduled hospital admission, and death was 0.48 (95% CI, 0.32 to 0.71, P < .001) in favor of the intervention group. CONCLUSION: Treatment with oral anticancer drugs is associated with a broad range of medication errors and side effects. An intensified clinical pharmacological/pharmaceutical care has considerable, positive effects on the number of medication errors, patient treatment perception, and severe side effects.
CRIS-Team Scopus Importer:2021-07-02

The role of IRF-1 during pathogen-induced intestinal Inflammation - Schmalzl, Angelika; Neurath, Markus; Wirtz, Stefan (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

The role of the chemokine receptor CCR8 in migration and effector function of innate lymphoid cells type 2 - Knipfer, Lisa; Schulz-Kuhnt, Anja; Symowski, Cornelia; Vöhringer, David; Neurath, Markus; Atreya, I.; Wirtz, Stefan (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

The sphingosine-1-phosphate receptor agonist etrasimod in ulcerative colitis - Atreya, Raja; Neurath, Markus (Lancet, 2023)
CRIS-Team Scopus Importer:2023-03-23

The TLR9 agonist cobitolimod induces anti-inflammatory effects and balances the Th17/T-reg cell response in ulcerative colitis - Schmitt, H.; Billmeier, Ulrike; Ulmschneider, J.; Admyre, C.; Knittel, T.; Zargari, A.; Neurath, Markus; Atreya, Raja (2018)
EVALuna2:34112

The TLR9 agonist cobitolimod induces IL10 producing wound healing macrophages and regulatory T cells in ulcerative colitis - Schmitt, Heike; Ulmschneider, Julia; Billmeier, Ulrike; Scarozza, Patrizio; Sonnewald, Sophia; Reid, Stephen; Atreya, Imke; Rath, Timo; Zundler, Sebastian; Langheinrich, Melanie; Schüttler, Jürgen; Hartmann, Arndt; et al. (Journal of Crohns & Colitis, 2020)
BACKGROUND AND AIMS: The topically applied Toll-like receptor 9 (TLR9) agonist cobitolimod is a first-in-class DNA-based oligonucleotide that demonstrated therapeutic efficacy in clinical trials with ulcerative colitis (UC) patients. We here characterized its anti-inflammatory mechanism in UC. METHODS: Luminal cobitolimod administration was evaluated in an experimental DSS-induced colitis model. Cultured blood and mucosal cells from UC patients were treated with cobitolimod and analyzed via microarray, qRT-PCR, ELISA and flow cytometry. Intestinal slides of cobitolimod treated UC patients were analyzed by immunohistochemistry. RESULTS: Cobitolimod administration markedly suppressed experimental colitis activity and microarrays analyses demonstrated mucosal IL10 upregulation and suppression of IL17 signaling pathways. Cobitolimod treatment was associated with significant induction of mucosal IL10+ Tr1 and Treg cells and suppression of Th17 cells. TLR9 knockout mice indicated that cobitolimod requires TLR9 signaling for IL10 induction. In UC patients, mucosal TLR9 levels correlated with severity of inflammation. Cobitolimod inhibited IL17A and IL17F, but increased IL10 and FoxP3 expression in cultured intestinal UC T cells. Cobitolimod-mediated suppression of intestinal IL17+ T cells was abrogated by IL10 blockade. Furthermore, cobitolimod led to heightened IL10 production by wound healing macrophages. Immunohistochemistry in intestinal biopsies of cobitolimod treated UC patients indicated increased presence of IL10+ mononuclear and regulatory T cells, as well as reduction of IL17+ cells. CONCLUSION: Our studies suggest that activation of TLR9 via cobitolimod might represent a novel therapeutic approach in UC, as it suppresses Th17 cells and induces anti-inflammatory IL10+ macrophages and regulatory T cells, thereby modifying the dysregulated intestinal cytokine balance.
EVALuna2:212910
Keywords: Ulcerative colitis; TLR9; cobitolimod

The transcription factor NFATc3 promotes intestinal inflammation by suppression of regulatory T cells - Gerlach, Katharina; Popp, Vanessa; Neurath, Markus; Weigmann, Benno (2017)
EVALuna2:33799

The α4β1 Homing Pathway Is Essential for Ileal Homing of Crohn's Disease Effector T Cells In Vivo - Zundler, Sebastian; Fischer, Anika; Schillinger, Daniela; Binder, Marie-Theres; Atreya, Raja; Rath, Timo; Lopez Posadas, Rocío; Voskens, Caroline J.; Watson, Alastair; Atreya, Imke; Neufert, Clemens; Neurath, Markus (Inflammatory Bowel Diseases, 2017)
BACKGROUND: The precise mechanisms controlling homing of T effector (Teff) cells to the inflamed gut in Crohn's disease (CD) are still unclear, and clinical outcome data from patients with inflammatory bowel disease treated with the anti-α4β7 integrin antibody vedolizumab suggest differences between ulcerative colitis and CD. METHODS: Expression of homing molecules was studied with flow cytometry and immunohistochemistry. Their functional role was investigated in in vitro adhesion assays and in a humanized mouse model of T cell homing to the inflamed gut in vivo. RESULTS: Despite in vitro blockade of CD Teff adhesion to mucosal vascular addressin cell adhesion molecule-1 (MadCAM-1) and in contrast to previous observations in ulcerative colitis, anti-α4β7 treatment did not result in reduced Teff cell homing to the colon in vivo. However, the integrin α4β1 was expressed in higher levels on Teffs from patients with CD compared with controls, while its expression in the peripheral blood declined, and its expression in the intestine increased during the course of clinical vedolizumab treatment. Consistently, adhesion of CD Teffs to vascular cell adhesion molecule-1 (VCAM-1) was blocked by inhibition of α4 and α4β1 in vitro. Moreover, in vivo homing of CD Teffs to the ileum was reduced by inhibition of α4 and α4β1 integrins, but not α4β7 integrins. CONCLUSIONS: Our findings suggest that Teff cell homing to the ileum through the axis α4β1-VCAM-1 is an essential and nonredundant pathway in CD in vivo, possibly affecting efficacy of clinical treatment with antiadhesion compounds.
EVALuna2:33825

Thiopurines in Inflammatory Bowel Disease: New Findings and Perspectives - De Boer, Nanne K. H.; Peyrin-Biroulet, Laurent; Jharap, Bindia; Sanderson, Jeremy D.; Meijer, Berrie; Atreya, Imke; Barclay, Murray L.; Colombel, Jean-Frederic; Lopez, Anthony; Beaugerie, Laurent; Marinaki, Anthony M.; Van Bodegraven, Adriaan A.; et al. (Journal of Crohns & Colitis, 2018)
Thiopurines, available as azathioprine, mercaptopurine, and thioguanine, are immunomodulating agents primarily used to maintain corticosteroid-free remission in patients with inflammatory bowel disease. To provide a state-of-the-art overview of thiopurine treatment in inflammatory bowel disease, this clinical review critically summarises the available literature, as assessed by several experts in the field of thiopurine treatment and research in inflammatory bowel disease.
EVALuna2:35180

Three-Dimensional Cross-Sectional Light-Sheet Microscopy Imaging of the Inflamed Mouse Gut - Zundler, Sebastian; Klingberg, Anika; Schillinger, Daniela; Fischer, Sören; Neufert, Clemens; Atreya, Imke; Gunzer, Matthias; Neurath, Markus (Gastroenterology, 2017)
EVALuna2:33801

Tofacitinib Affects M1-like and M2-like Polarization and Tissue Factor Expression in Macrophages of Healthy Donors and IBD Patients. - Lethen, Isabelle; Lechner-Grimm, Kristina; Gabel, Michael; Knauß, Annkathrin; Atreya, Raja; Neurath, Markus; Weigmann, Benno (Inflammatory Bowel Diseases, 2024)
BACKGROUND: Tofacitinib, as inhibitor of Janus kinases (JAK), interrupts the transmission of numerous pro-inflammatory cytokines involved in the pathogenesis of inflammatory bowel diseases (IBD). Therefore, tofacitinib provides a potent option to treat ulcerative colitis (UC). Besides the anti-inflammatory potential, inhibition of widespread JAKs carries the risk of side effects. Macrophages are involved in the form of different subtypes in inflammation, wound healing, and even coagulation. This study aimed to explore the balanced use of tofacitinib in M1-like as well as M2-like macrophages of healthy donors and patients with IBD. METHODS: Monocytes of healthy donors and patients with chronic courses of IBD were obtained from blood samples. Macrophage colony-stimulating factor (M-CSF)-derived macrophages were treated with tofacitinib (1 µM, 5 µM, 10 µM) and polarized with either lipopolysaccharide and interferon (IFN)-γ towards M1-like-phenotype or with interleukin (IL)-4 towards M2-like-phenotype. ELISA and flow cytometry were used to evaluate cytokine levels and surface molecules. RESULTS: Tofacitinib had a modulating effect on M1-like macrophages whereby the effect on pro-inflammatory cytokines (TNF-α, IL-6, IL-1β, IL-12, IL-23) was less pronounced than the induction of anti-inflammatory IL-10. However, during M2-like polarization tofacitinib impaired the development of the corresponding phenotype becoming evident through decreased IL-10 levels and CD206 expression in treated macrophages. In both phenotypes, tofacitinib strongly downregulated the expression of immunostimulatory molecules (CD80, CD86, CD83, CD40). Furthermore, a dose-dependent correlation between treatment with tofacitinib and expressed tissue factor was noticed. CONCLUSIONS: Tofacitinib influences both polarizations (M1/M2) and the expression of tissue factor in a dose-dependent manner.
EVALuna2:550695

Top-down approach to biological therapy of Crohn's disease - Hirschmann, Simon; Neurath, Markus (Expert Opinion on Biological Therapy, 2017)
INTRODUCTION: Crohn's disease (CD) is a chronic, immune-mediated condition with a potentially disabling and destructive course. Despite growing data on when to use a therapeutic 'top-down' strategy, clinical management of this complex disorder is still challenging. Currently, the discussion of 'top-down' strategy in CD mostly includes biological therapy alone or in combination. Areas covered: This article is based on a review of existing literature regarding the use of biological therapy in a 'top-down' approach for the treatment of Crohn's disease. The authors reviewed all the major databases including MEDLINE as well as DDW and ECCO abstracts, respectively. Expert opinion: A 'top-down' therapeutic approach in Crohn's disease is strongly supported by existing data in patients with several risk factors for a severe course of disease. Moreover, there is an increasing amount of published data recommending a more individualised therapeutic strategy to identify candidates for 'top-down' treatment, based on enhanced diagnostics using biomarkers. Emerging therapeutic approaches besides existing therapy concepts using biologicals may possibly redefine the 'top-down' therapeutic strategy for Crohn's disease in the future.
EVALuna2:33823

Topical application of Chlorin e6-PVP (Ce6-PVP) for improved endoscopic detection of neoplastic lesions in a murine colitis-associated cancer model - Ganzleben, Ingo; Hohmann, Martin; Grünberg, Alexander; Menezes, Jean Gonzales; Liebing, Eva; Günther, Claudia; Thonn, Veronika; Beß, Daniel; Becker, Christoph; Schmidt, Michael; Neurath, Markus; Waldner, Maximilian; et al. (Scientific Reports, 2020)
Screening colonoscopy is crucial in reducing the mortality of colorectal cancer. However, detecting adenomas against the backdrop of an inflamed mucosa (e.g. in ulcerative colitis) remains exceedingly difficult. Therefore, we aimed to improve neoplastic lesion detection by employing a fluorescence-based endoscopic approach. We used the well-established murine AOM/DSS model to induce inflammation-driven carcinogenesis in the colon. In our diagnostic approach, we evaluated Chlorin e6 polyvinylpyrrolidone (Ce6-PVP)-based fluorescence endoscopy in comparison to standard white-light endoscopy. A specialized pathologist then analyzed the histology of the detected lesions. Complementary in vitro studies were performed using human cell lines and a murine organoid system. Ce6-PVP-based fluorescence endoscopy had an improved detection rate of 100% (8/8) in detecting high-grade dysplasias and carcinomas over white-light detection alone with 75% (6/8). Trade-off for this superior detection rate was an increased rate of false positive lesions with an increase in the false discovery rate from 45% for white-light endoscopy to 81% for fluorescence endoscopy. We demonstrate in a proof-of-concept study that Ce6-PVP-based fluorescence endoscopy is a highly sensitive red flag technology to identify biopsy-worthy lesions in the colon.
CRIS-Team Scopus Importer:2020-08-14

Total Recall: Intestinal T-RM Cells in Health and Disease - Paap, Eva-Maria; Müller, Tanja; Sommer, Katrin; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2021)
Tissue-resident memory T cells (T-RM cells) have crucial functions in host defense in mucosal tissues. They provide local adaptive immune surveillance and allow the fast initiation of targeted adaptive immune responses in case of antigen re-exposure. Recently, an aberrant activation in the case of immunologically mediated diseases has been increasingly acknowledged. As the organ with the largest interface to the environment, the gastrointestinal tract faces billions of antigens every day. Tightly balanced processes are necessary to ensure tolerance towards non-hazardous antigens, but to set up a powerful immune response against potentially dangerous ones. In this complex nexus of immune cells and their mediators, T-RM cells play a central role and have been shown to promote both physiological and pathological events. In this review, we will summarize the current knowledge on the homeostatic functions of T-RM cells and delineate their implication in infection control in the gut. Moreover, we will outline their commitment in immune dysregulation in gastrointestinal chronic inflammatory conditions and shed light on T-RM cells as current and potential future therapeutic targets.
CRIS-Team WoS Importer:2021-02-19

Towards a Computable Data Corpus of Temporal Correlations between Drug Administration and Lab Value Changes - Newe, Axel; Wimmer, Stefan; Neubert, Antje; Becker, Linda; Prokosch, Hans-Ulrich; Beckmann, Matthias; Fietkau, Rainer; Forster, Christian; Neurath, Markus; Schett, Georg; Ganslandt, Thomas (PLoS ONE, 2015)
Background The analysis of electronic health records for an automated detection of adverse drug reactions is an approach to solve the problems that arise from traditional methods like spontaneous reporting or manual chart review. Algorithms addressing this task should be modeled on the criteria for a standardized case causality assessment defined by the World Health Organization. One of these criteria is the temporal relationship between drug intake and the occurrence of a reaction or a laboratory test abnormality. Appropriate data that would allow for developing or validating related algorithms is not publicly available, though. Methods In order to provide such data, retrospective routine data of drug administrations and temporally corresponding laboratory observations from a university clinic were extracted, transformed and evaluated by experts in terms of a reasonable time relationship between drug administration and lab value alteration. Result The result is a data corpus of 400 episodes of normalized laboratory parameter values in temporal context with drug administrations. Each episode has been manually classified whether it contains data that might indicate a temporal correlation between the drug administration and the change of the lab value course, whether such a change is not observable or whether a decision between those two options is not possible due to the data. In addition, each episode has been assigned a concordance value which indicates how difficult it is to assess. This is the first open data corpus of a computable ground truth of temporal correlations between drug administration and lab value alterations. Discussion The main purpose of this data corpus is the provision of data for further research and the provision of a ground truth which allows for comparing the outcome of other assessments of this data with the outcome of assessments made by human experts. It can serve as a contribution towards systematic, computerized ADR detection in retrospective data. With this lab value curve data as a basis, algorithms for detecting temporal relationships can be developed, and with the classification made by human experts, these algorithms can immediately be validated. Due to the normalization of the lab value data, it allows for a generic approach rather than for specific or solitary drug/lab value combination

Toxic megacolon - Leppkes, M.; Ganslmayer, M.; Strauss, R.; Neurath, Markus (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2015)
Toxic megacolon constitutes a feared, life-threatening complication of severe intestinal inflammation and is a challenge for interdisciplinary medical care.Specific aspects of conservative treatment based on current scientific evidence derived from guidelines, qualified reviews, and scientific studies are presented, which provide a rational approach and maximize therapeutic success.This work is based on a selective literature review and the authors' experience of many years in gastroenterology and intensive care.Toxic megacolon requires a rapid interdisciplinary assessment. Depending on the underlying etiology, an individual treatment concept needs to be developed. If an infectious or inflammatory cause is probable, a conservative approach can reduce perioperative morbidity and mortality. A step-wise approach with controlled reevaluations of the response to therapy after 72 h and 7 days avoids uncontrolled delay of surgical options further ensuring patient safety.Despite a decreasing incidence of toxic megacolon, it remains an interdisciplinary therapeutic challenge.
EVALuna2:2018

Transabdominal ultrasonography for confirmation of accurate percutaneous endoscopic gastrostomy tube placement: analysis of patient- and procedure-related complications - Wildner, Dane; Pfeifer, Lukas; Vitali, Francesco; Neurath, Markus; Albrecht, Heinz (Medical Ultrasonography, 2022)
Aims: Technique-related factors, patient-related factors, and localization determine the risk for complications in percutaneous endoscopic gastrostomy (PEG) tube placement. The objective of this study was to identify patient characteristics and ultrasonographic parameters after PEG tube placement concerning localization, which correlate with complications. Material and methods: Patients undergoing PEG-tube placement were examined by abdominal ultrasound after dismissal from the endoscopic recovery room. Patient demographics, PEG characteristics, ultrasonographic parameters and complications were retrospectively analyzed. Results: Of 64 enrolled patients, 59.4% were male and the mean age was 62.3 years. A significant negative correlation between complications at PEG placement and Body-Mass-Index (BMI; kg/m(2)) was observed (Spearman's Rho: -0.382; p=0.002). A low BMI <18 tended to be more frequent in the group with complication-related PEG removal compared to patients without (18.2% vs. 1.9%). Further descriptive analysis revealed that 4 patients (36.4% of N=11) with and 5 patients (9.4% of N=53) without PEG removal due to complications already had complications at the time of PEG placement. Of the patients with complications during follow-up, those with a peritoneal course (N=10) in ultrasound tended to have a lower BMI (mean +/- standard deviation: 22.5 +/- 6.5 vs. 26.8 +/- 5.9) compared to those without (N=5). In all 4 patients with a triad of follow-up complications, peritoneal course, and complications at PEG placement, the tube was removed due to complications. Conclusions: Post-PEG-placement ultrasonography can help to determine complications in specific procedure-related conditions. A low BMI was found to be a relevant predictor of PEG-related complications, substantiating the need for early intervention in potentially PEG-relevant indications.
CRIS-Team WoS Importer:2023-03-03

Transient receptor potential melastatin 8 ion channel in macrophages modulates colitis through a balance-shift in TNF-alpha and interleukin-10 production - Khalil, Mohammad; Babes, Alexandru; Lakra, R.; Försch, Sebastian; Reeh, Peter; Wirtz, Stefan; Becker, Christoph; Neurath, Markus; Engel, Matthias (Mucosal Immunology, 2016)
The transient receptor potential (TRP) ion channel family is well characterized in sensory neurons; however, little is known about its role in the immune system. Here we show that the cold-sensing TRPM8 has an unexpected role in innate immunity. TRPM8 expression and function in macrophages were demonstrated in vitro using molecular techniques and calcium imaging. In addition, adoptive macrophage transfer and systemic interleukin (IL)-10 overexpression were performed in experimental colitis. TRPM8 activation induced calcium-transients in murine peritoneal macrophages (PM) and bone marrow-derived macrophages of wild-type (WT) but not TRPM8-deficient mice. TRPM8-deficient PM exhibited defective phagocytosis and increased motility compared with those in WT, whereas the opposite effects of TRPM8 activation were induced in WT PM. TRPM8 activation or blockage/genetic deletion induced a anti- or pro-inflammatory macrophage cytokine profile, respectively. WT mice treated with repeated menthol (TRPM8 agonist) enemas were consistently protected from experimental colitis, whereas TRPM8-deficient mice showed increased colitis susceptibility. Adoptive transfer of TRPM8-deficient macrophages aggravated colitis, whereas systemic IL-10 overexpression rescued this phenotype. TRPM8 activation in peptidergic sensory neurons did not affect neuropeptide release from the inflamed colon. TRPM8 in macrophages determines pro- or anti-inflammatory actions by regulating tumor necrosis factor-? and interleukin-10 production. These findings suggest novel TRPM8-based options for immunomodulatory intervention.
EVALuna2:2053

Transrectal Absorber Guide Raster-Scanning Optoacoustic Mesoscopy for Label-Free In Vivo Assessment of Colitis - Bühler, Adrian; Brown, Emma; Paulus, Lars-Philip; Eckstein, Markus; Thoma, Oana-Maria; Oraiopoulou, Mariam-Eleni; Rother, Ulrich; Hörning, André; Hartmann, Arndt; Neurath, Markus; Wölfle, Joachim; Friedrich, Oliver; et al. (Advanced Science, 2023)
Optoacoustic imaging (OAI) enables microscale imaging of endogenous chromophores such as hemoglobin at significantly higher penetration depths compared to other optical imaging technologies. Raster-scanning optoacoustic mesoscopy (RSOM) has recently been shown to identify superficial microvascular changes associated with human skin pathologies. In animal models, the imaging depth afforded by RSOM can enable entirely new capabilities for noninvasive imaging of vascular structures in the gastrointestinal tract, but exact localization of intra-abdominal organs is still elusive. Herein the development and application of a novel transrectal absorber guide for RSOM (TAG-RSOM) is presented to enable accurate transabdominal localization and assessment of colonic vascular networks in vivo. The potential of TAG-RSOM is demonstrated through application during mild and severe acute colitis in mice. TAG-RSOM enables visualization of transmural vascular networks, with changes in colon wall thickness, blood volume, and OAI signal intensities corresponding to colitis-associated inflammatory changes. These findings suggest TAG-RSOM can provide a novel monitoring tool in preclinical IBD models, refining animal procedures and underlines the capabilities of such technologies to address inflammatory bowel diseases in humans.
CRIS-Team WoS Importer:2023-05-12

Treatment Perspectives in Crohn's Disease - Vetter, Marcel; Neurath, Markus (Digestion, 2018)
BACKGROUND: Crohn's disease (CD) is a chronic immune-mediated disorder of the gastrointestinal tract. The pathophysiological understanding of this disease is limited and no curative therapy is available so far. Therefore, most patients require long-lasting or even life-long immunosuppressive therapies for the suppression of symptoms to improve quality of life and reduction of long-term risks. However, in a relevant subgroup of patients, these therapeutic goals cannot be sufficiently attained. SUMMARY: Clinically established therapies in active CD comprise corticosteroids and immunosuppressants such as azathioprine. After the introduction of anti-TNFα (Tumor necrosis factor alpha) antibodies, other biologicals (e.g., vedolizumab and ustekinumab) have also been approved. New drugs in the pipeline like filgotinib, upadacitinib, risankizumab or rifaximin could improve the therapy of CD in the near future. Thus, an individualized therapy management, based on optimal selection of therapeutic agents will become more important. Additionally, the local application of mesenchymal stem cells might be helpful in the management of fistulas. Key Messages: The targeted biological therapeutic agents (anti-TNFα antibodies, vedolizumab, ustekinumab) are well established for therapy in CD. There are several new substances in the pipeline with promising results in phase II trials (filgotinib, rifaximin, risankizumab, upadacitinib). The upcoming extension of the therapeutic arsenal will require methods for an optimized selection of substances, thus enabling a more individualized therapy.
EVALuna2:35196

Treatment trajectories and outcomes in inflammatory bowel disease: a tertiary single-centre experience - Wagner, Kim; Müller, Tanja; Vitali, Francesco; Fischer, Sarah; Haberkamp, Sophie; Rouse-Merkel, Rachel; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (Therapeutic Advances in Gastroenterology, 2024)
Background: There is an increasing diversification in the treatment landscape for inflammatory bowel diseases (IBD) leading to therapeutic challenges that can only incompletely be covered by prospective randomized double-blind trials. Real-world observations are therefore an important tool to provide insights into therapeutic strategies. Objectives: To describe the real-world treatment algorithms in an IBD referral centre. Design: Single-centre retrospective cohort study. Methods: We retrospectively analysed prospectively collected data on treatment sequences and outcomes from 502 patients with Crohn’s disease (CD) and ulcerative colitis (UC) treated with infliximab, adalimumab, vedolizumab or ustekinumab at a large German tertiary referral centre. Results: Treatment decisions correlated to baseline patient characteristics. Over time, infliximab continued to be the preferred first-line option in CD and UC, although ustekinumab and vedolizumab, respectively, became increasingly important choices. Remission rates decreased with the advancement of therapy lines. Conclusion: We provide insights into the evolution of tertiary centre real-world treatment sequences that might – together with other observations – help to guide the selection of therapies in IBD. Our data also strongly underscore the unmet need for biomarkers supporting treatment decisions. Trial registration: None.
CRIS-Team Scopus Importer:2024-10-18
Keywords: biological therapy; Crohn’s disease; inflammatory bowel disease; real-world study; treatment algorithms; ulcerative colitis

TRPA1 and substance P mediate colitis in mice - Engel, Matthias; Leffler, Andreas; Niedermirtl, Florian; Babes, Alexandru; Zimmermann, Katharina; Filipovic, Milos; Izydorczyk, Iwona; Eberhardt, Mirjam; Kichko, Tetyana; Müller-Tribbensee, Sonja; Khalil, Mohammad; Siklosi, Norbert; et al. (Gastroenterology, 2011)

Two-dimensional shear-wave elastography: a new method comparable to acoustic radiation force impulse imaging? - Schellhaas, Barbara; Strobel, Deike; Wildner, Dane; Görtz, Rüdiger; Neurath, Markus; Pfeifer, Lukas (European Journal of Gastroenterology & Hepatology, 2017)
OBJECTIVES: Two-dimensional shear-wave elastography (2D-SWE) is an ultrasound-based technique for the noninvasive assessment of tissue stiffness. In contrast to the well-established point-shear-wave elastography (pSWE) method acoustic radiation force impulse imaging, there is little evidence on the performance and usefulness of 2D-SWE in the assessment of liver stiffness. Thus, the aim of our study was to compare 2D-SWE versus pSWE. MATERIALS AND METHODS: 2D-SWE and pSWE were performed in 20 cirrhotic patients, 20 healthy individuals and an elasticity phantom. Stiffness values, examination time and number of measurements were compared. For 2D-SWE, the influence of size of the region of interest (ROI) was assessed. RESULTS: Elastography values in healthy individuals were slightly higher for 2D-SWE versus pSWE (1.4 m/s, range: 1.21-1.68 vs. 1.23 m/s, range: 1.07-1.39). In cirrhotic patients, there were no significant differences (3.06 m/s, range: 1.83-5.35 vs. 3 m/s, range: 1.67-4.37 m/s). Examination times were significantly longer for 2D-SWE in both patient groups (mean values for healthy/cirrhotic patients: 129.6/157.1 vs. 75/71.6 s). For 2D-SWE, variation of ROI size (5, 10, 20 mm) produced comparable results. After eight measurements, 90% of cirrhotic patients showed less than 5% of deviation from the results after the gold standard of 10 measurements; for healthy individuals, this was observed after six measurements. CONCLUSION: 2D-SWE seems to be comparable to pSWE (acoustic radiation force impulse-imaging) in cirrhotic patients, with slightly higher values in healthy individuals. 2D-SWE measurements require considerably more time. For 2D-SWE, ROI size seems to be of minor importance; multiple measurements should be obtained as single measurements differ. These preliminary results should be confirmed in larger patient collectives with histology as the reference standard.
EVALuna2:33813

Type 1 Autoimmune Pancreatitis in Europe: Clinical Profile and Response to Treatment - Overbeek, Kasper A.; Poulsen, Jakob L.; Lanzillotta, Marco; Vinge-Holmquist, Olof; Macinga, Peter; Demirci, A. Fatih; Sindhunata, Daniko P.; Backhus, Johanna; Algül, Hana; Buijs, Jorie; Levy, Philippe; Kiriukova, Mariia; et al. (Clinical Gastroenterology and Hepatology, 2024)
Background & Aims: Autoimmune pancreatitis (AIP) is an immune-mediated disease of the pancreas with distinct pathophysiology and manifestations. Our aims were to characterize type 1 AIP in a large pan-European cohort and study the effectiveness of current treatment regimens. Methods: We retrospectively analyzed adults diagnosed since 2005 with type 1 or not-otherwise-specified AIP in 42 European university hospitals. Type 1 AIP was uniformly diagnosed using specific diagnostic criteria. Patients with type 2 AIP and those who had undergone pancreatic surgery were excluded. The primary end point was complete remission, defined as the absence of clinical symptoms and resolution of the index radiologic pancreatic abnormalities attributed to AIP. Results: We included 735 individuals with AIP (69% male; median age, 57 years; 85% White). Steroid treatment was started in 634 patients, of whom 9 (1%) were lost to follow-up. The remaining 625 had a 79% (496/625) complete, 18% (111/625) partial, and 97% (607/625) cumulative remission rate, whereas 3% (18/625) did not achieve remission. No treatment was given in 95 patients, who had a 61% complete (58/95), 19% partial (18/95), and 80% cumulative (76/95) spontaneous remission rate. Higher (≥0.4 mg/kg/day) corticosteroid doses were no more effective than lower (<0.4 mg/kg/day) doses (odds ratio, 0.428; 95% confidence interval, 0.054–3.387) and neither was a starting dose duration >2 weeks (odds ratio, 0.908; 95% confidence interval, 0.818–1.009). Elevated IgG4 levels were independently associated with a decreased chance of complete remission (odds ratio, 0.639; 95% confidence interval, 0.427–0.955). Relapse occurred in 30% of patients. Relapses within 6 months of remission induction were independent of the steroid-tapering duration, induction treatment duration, and total cumulative dose. Conclusions: Patients with type 1 AIP and elevated IgG4 level may need closer monitoring. For remission induction, a starting dose of 0.4 mg/kg/day for 2 weeks followed by a short taper period seems effective. This study provides no evidence to support more aggressive regimens.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Autoimmune Pancreatitis; IgG4-Related Disease; IgG4-Related Pancreatitis

Ultrasensitive molecular imaging of intestinal mucosal inflammation using leukocyte-mimicking particles targeted to MAdCAM-1 in mice - Fournier, Antoine P.; De Lizarrondo, Sara Martinez; Rateau, Adrien; Gerard-Brisou, Axel; Waldner, Maximilian; Neurath, Markus; Vivien, Denis; Docagne, Fabian; Gauberti, Maxime (Science Translational Medicine, 2020)
Mucosal tissues play critical roles in health and disease as the primary barrier between the external world and the inner body, lining the digestive, respiratory, urinary, mammary, and reproductive tracts. Clinical evaluation of mucosal tissues is currently performed using endoscopy, such as ileocolonoscopy for the intestinal mucosa, which causes substantial patient discomfort and can lead to organ damage. Here, we developed a contrast agent for molecular magnetic resonance imaging (MRI) that is targeted to mucosal vascular addressin cell adhesion molecule 1 (MAdCAM-1), an adhesion molecule overexpressed by inflamed mucosal tissues. We investigated the diagnostic performance of molecular MRI of MAdCAM-1 to detect mucosal inflammation in several models of acute and chronic intestinal inflammation in mice. We demonstrated that molecular MRI of MAdCAM-1 reveals disease activity and can evaluate the response to inflammatory treatments along the whole intestinal mucosa in clinically relevant models of inflammatory bowel diseases. We also provide evidence that this technique can detect low, subclinical mucosal inflammation. Molecular MRI of MAdCAM-1 has potential applications in early diagnosis, longitudinal follow-up, and therapeutic response monitoring in diseases affecting mucosal tissues, such as inflammatory bowel diseases.
CRIS-Team WoS Importer:2020-09-25

Ultrasound-Based Attenuation Imaging for the Non-Invasive Quantification of Liver Fat-A Pilot Study on Feasibility and Inter-Observer Variability - Jesper, Daniel; Klett, Daniel; Schellhaas, Barbara; Pfeifer, Lukas; Leppkes, Moritz; Waldner, Maximilian; Neurath, Markus; Strobel, Deike (IEEE Journal of Translational Engineering in Health and Medicine, 2020)
Attenuation imaging is a novel, ultrasound-based technique to objectively detect and quantify liver steatosis. In this study, we evaluated the performance and inter-observer variability of attenuation imaging and compared it to a known quantification method of liver fat, the hepatorenal index (HRI). Two observers measured attenuation coefficients (AC) in an attenuation phantom, 20 healthy volunteers and 27 patients scheduled for biopsy for suspected diffuse liver disease. Results were compared with the HRI and histological findings. Both observers were blinded to the results of the biopsy and the measurements of the other observer. Our results showed that patients with moderate (S2, 33-66%) and severe fatty infiltration of the liver (S3, >66%) showed significantly higher ACs in comparison to patients with a liver fat fraction of less than 33% (S0/1). There was no significant difference in AC-values of patients with fatty infiltration of less than 5% (S0) and 5-32% (S1). In the Receiver Operating Characteristic (ROC)-analysis, the area under the curve (AUC)-values for the detection of moderate and severe steatosis were excellent at 0.98. Cut-off values were 0.64 dB/cm/MHz for the detection of S2- A nd 0.68 dB/cm/MHz for the detection of S3-steatosis. The inter-observer agreement of attenuation imaging was very good with an intraclass correlation coefficient (ICC) of 0.92 in patient and 0.96 in phantom measurements. The ICC decreased with depth in the phantom measurements. In summary, attenuation imaging showed very good inter-observer agreement and is a promising tool for the detection and quantification of moderate and severe hepatic steatosis.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Attenuation imaging; fatty liver; hepatic fat; hepatic steatosis; hepatorenal index; inter-observer; liver steatosis; NAFLD; NASH; ultrasound

Unveiling Metabolic Similarities of Entheses in Patients with Psoriasis and Psoriatic Arthritis Using Noninvasive In Vivo Molecular Imaging: Results From a Cross-sectional Exploratory Study - Fagni, Filippo; Tascilar, Koray; Noversa de Sousa, Rita; Bayat, Sara; Sollfrank, Lukas; Kleyer, Arnd; Sticherling, Michael; Regensburger, Adrian; Knieling, Ferdinand; Neurath, Markus; Schett, Georg; Waldner, Maximilian; et al. (Arthritis and Rheumatology, 2024)
Objective: We assessed and compared molecular tissue changes at the entheses in patients with psoriasis (PsO) and psoriatic arthritis (PsA) and in healthy controls (HCs) in vivo using multispectral optoacoustic tomography (MSOT) and described their relationship with clinical and ultrasound findings of enthesitis. Methods: A cross-sectional study (MSOT and Arthrosonography in PsA) in biologic disease-modifying antirheumatic drug–naïve patients with PsA and PsO and HCs was performed. Participants underwent clinical, ultrasonographic, and MSOT examination of six entheses (lateral humeral epicondyle, distal patellar tendon attachment, and Achilles tendon attachment). MSOT-measured hemoglobin (Hb), oxygen saturation (SO2), collagen, and lipid levels were quantified, and mean differences between groups were calculated using linear mixed effects models. MSOT-measured analytes were compared between entheses with and without clinical and ultrasound anomalies. Results: Ninety participants were included (30 PsO, 30 PsA, and 30 HCs), 540 entheses were clinically assessed, and 540 ultrasound and 830 MSOT scans were obtained. Patients with PsA and PsO showed increased oxygenated Hb (PsA: P = 0.003; PsO: P = 0.054) and SO2 (PsA: P < 0.001; PsO: P = 0.001) levels and decreased collagen signals (PsA: P < 0.001; PsO: P < 0.001) compared with HCs, with more pronounced changes in PsA. Significantly lower collagen levels (P = 0.01) and increased lipids (P = 0.03) were recorded in tender entheses compared with nontender ones. Erosions and enthesophytes on ultrasound were associated with significant differences in SO2 (P = 0.014) and lipid signals (P = 0.020), respectively. Conclusion: Patients with PsA and PsO exhibit an analogous metabolic pattern at the entheses that is exacerbated in the presence of inflammation. These findings support the notion of a psoriatic disease spectrum characterized by common immunometabolic tissue changes.
CRIS-Team Scopus Importer:2024-07-19

Update: chronisch entzündliche Darmerkrankungen - Atreya, Raja; Neumann, Helmut; Neurath, Markus (Deutsche Medizinische Wochenschrift, 2015)
Crohn's disease and ulcerative colitis are the major entities of inflammatory bowel diseases (IBD). IBD is a clinical diagnosis, which is supported by endoscopic, histologic, radiologic, sonographic and laboratory findings. IBD are not restricted to the GI-tract but are instead systemic diseases that often involve extra-intestinal manifestations. Aim of the rational medical therapy is the induction and maintenance of a steroid-free remission. The medical therapy depends on the severity, activity and extent of disease as well as the disease course of the patient. There is the dire necessity for an individualized therapeutic concept as the natural disease course differs between the patients.
EVALuna2:1989

Update zur Pathophysiologie, Prädiktion und Prävention chronisch-entzündlicher Darmerkrankungen - Fischer, Sarah; Neurath, Markus (Innere Medizin, 2025)
Background: The pathophysiology of inflammatory bowel diseases is not fully understood. In a staged model by the European Crohn’s and Colitis Organization (ECCO) regarding disease development, it is assumed that there is a population at risk for manifestation of disease following subtle changes over time. Objective: This work aims to summarize the current state of knowledge regarding the pathophysiology, prediction and prevention of chronic inflammatory bowel diseases. Materials and Methods: Selective literature research via PubMed. Results: Several genetic, biochemical, and microbiome scores have the potential to identify individuals at increased risk of developing inflammatory bowel disease, possibly up to a decade before onset. Discussion: The growing knowledge regarding the pathogenesis of inflammatory bowel diseases makes prediction before disease onset a possible future diagnostic goal. Hypothetically, early changes before the disease manifests could be reversible and may be amenable to prevention programs.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Environmental factors; Genetic factors; Inflammatory bowel diseases/risk factors; Intestinal barrier; Microbiome

Upregulation of CCR4 in activated CD8(+) T cells indicates enhanced lung homing in patients with severe acute SARS-CoV-2 infection - Spoerl, Silvia; Kremer, Anita; Aigner, Michael; Eisenhauer, Nina; Koch, Pauline; Meretuk, Lina; Loeffler, Patrick; Tenbusch, Matthias; Maier, Clara; Überla, Klaus; Heinzerling, Lucie; Frey, Benjamin; et al. (European Journal of Immunology, 2021)
COVID-19 is a life-threatening disease leading to bilateral pneumonia and respiratory failure. The underlying reasons why a smaller percentage of patients present with severe pulmonary symptoms whereas the majority is only mildly affected are to date not well understood.
CRIS-Team WoS Importer:2021-05-07

Usefulness of recombinant ?-gliadin 1 for identifying patients with celiac disease and monitoring adherence to a gluten-free diet - Srinivasan, Bharani; Focke-Tejkl, Margarete; Weber, Milena; Pahr, Sandra; Baar, Alexandra; Atreya, Raja; Neurath, Markus; Vogelsang, Harald; Huber, Wolf-Dietrich; Valenta, Rudolf (Journal of Allergy and Clinical Immunology, 2015)
Celiac disease (CD) is an inflammatory disease of the small intestine caused by an immunologic hypersensitivity reaction to dietary wheat gluten.We sought to clone, express, and perform IgA epitope mapping of a CD-specific wheat antigen and to study its usefulness for identifying patients with CD and monitoring adherence to a gluten-free diet.A synthetic gene coding for ?-gliadin 1 (GG1) was expressed in Escherichia coli. Recombinant ?-gliadin 1 (rGG1) was purified and characterized biochemically, structurally, and immunologically by using sera from patients with CD and control subjects. Overlapping GG1 peptides were synthesized for IgA and IgG epitope mapping. GG1 and peptide-specific antibodies were raised for tracing GG1 in cereals and dietary wheat products and to study its resistance to digestion.rGG1 was expressed and purified. rGG1-based IgA ELISAs performed in populations of patients with CD and control subjects showed a specificity of 92.9%, which was higher than that of gliadin extract (e). Furthermore, it allowed monitoring of adherence to a gluten-free diet in patients. A 26-amino-acid peptide from the proline-glutamine-rich repetitive N-terminal region was identified as the immunodominant IgA epitope. GG1-related antigens were found in rye, barley, and spelt but not in oat, rice, or maize. GG1 was detected in dietary wheat products after baking, and in particular, the major IgA epitope-containing region was resistant against digestion.rGG1 and its epitope might be useful for identifying patients with CD, monitoring treatment, and studying the pathomechanisms of CD and development of preventive and therapeutic strategies.
EVALuna2:2102

Use of Fluorescent Dyes in Endoscopy and Diagnostic Investigation - Hoffman, Arthur; Atreya, Raja; Rath, Timo; Neurath, Markus (Visceral Medicine, 2020)
Background: The advancement of innovative endoscopic technology in terms of improving the visualization of the mucosa has been of significant benefit. Summary: Advancements in image resolution, software processing, and optical filter technology have resulted in several techniques complemental to traditional white light endoscopy. These new techniques provide a real-time optical diagnosis as well as virtual histology of detected lesions. Optical molecular imaging permits a functional assessment within cells. Key Message: Optical molecular imaging provides an understanding of cellular processes and permits validation of the specificity of fluorescent tracers and the possibility of quantifying the signal.
CRIS-Team Scopus Importer:2020-04-07

Validation of the 'Inflammatory Bowel Disease-Distribution, Chronicity, Activity [IBD-DCA] Score' for Ulcerative Colitis and Crohn ' s Disease - Lang-Schwarz, Corinna; Angeloni, Miriam; Agaimy, Abbas; Atreya, Raja; Becker, Christoph; Dregelies, Theresa; Danese, Silvio; Flejou, Jean-Francois; Gassler, Nikolaus; Grabsch, Heike; Hartmann, Arndt; Kamaradova, Katerina; et al. (Journal of Crohns & Colitis, 2021)
Background and Aims: Histological scoring plays a key role in the assessment of disease activity in ulcerative colitis [UC] and is also important in Crohns disease [CD]. Currently, there is no common scoring available for UC and CD. We aimed to validate the Inflammatory Bowel Disease [IBD]-Distribution [D], Chronicity [C], Activity [A] score [IBD-DCA score] for histological disease activity assessment in IBD.
CRIS-Team WoS Importer:2021-11-12

Vascular occlusion by neutrophil extracellular traps in COVID-19 - Leppkes, Moritz; Knopf, Jasmin; Naschberger, Elisabeth; Lindemann, Aylin; Singh, Jeeshan; Herrmann, Irmgard; Stürzl, Michael; Staats, Léonie; Mahajan, Aparna; Kremer, Anita; Amann, Kerstin Ute; Evert, Katja; et al. (EBioMedicine, 2020)
Background: Coronavirus induced disease 2019 (COVID-19) can be complicated by severe organ damage leading to dysfunction of the lungs and other organs. The processes that trigger organ damage in COVID-19 are incompletely understood. Methods: Samples were donated from hospitalized patients. Sera, plasma, and autopsy-derived tissue sections were examined employing flow cytometry, enzyme-linked immunosorbent assays, and immunohistochemistry. Patient findings: Here, we show that severe COVID-19 is characterized by a highly pronounced formation of neutrophil extracellular traps (NETs) inside the micro-vessels. Intravascular aggregation of NETs leads to rapid occlusion of the affected vessels, disturbed microcirculation, and organ damage. In severe COVID-19, neutrophil granulocytes are strongly activated and adopt a so-called low-density phenotype, prone to spontaneously form NETs. In accordance, markers indicating NET turnover are consistently increased in COVID-19 and linked to disease severity. Histopathology of the lungs and other organs from COVID-19 patients showed congestions of numerous micro-vessels by aggregated NETs associated with endothelial damage. Interpretation: These data suggest that organ dysfunction in severe COVID-19 is associated with excessive NET formation and vascular damage. Funding: Deutsche Forschungsgemeinschaft (DFG), EU, Volkswagen-Stiftung
CRIS-Team Scopus Importer:2020-08-14
Keywords: Aggregated neutrophil extracellular traps; Coagulopathy; Endothelialitis; Immunothrombosis; SARS-CoV-2

VAV1 as a putative therapeutic target in autoimmune and chronic inflammatory diseases - Neurath, Markus; Berg, Leslie J. (Trends in Immunology, 2024)
The guanine nucleotide exchange factor (GEF) VAV1, a previously ‘undruggable’ protein integral to T/B lymphocyte antigen–receptor signaling, promotes actin polymerization, immunological synapse formation, T cell activation and differentiation, and cytokine production. With the development of novel modalities for targeting proteins, we hypothesize that interventions targeting VAV1 will have therapeutic potential in T and T/B cell-mediated autoimmune and chronic inflammatory diseases. This opinion is supported by recent CRISPR-Cas9 studies showing VAV1 as a key positive regulator of T cell receptor (TCR) activation and cytokine production in primary human CD4+ and CD8+ T cells; data demonstrating that loss/suppression of VAV1 regulates autoimmunity and inflammation; and promising preclinical data from T and T/B cell-mediated disease models of arthritis and colitis showing the effectiveness of selective VAV1 targeting via protein degradation.
CRIS-Team Scopus Importer:2024-08-23
Keywords: autoimmune diseases; B-cell receptor; inflammation; molecular targeted therapy; T-cell receptor; VAV1

Vedolizumab-associated enthesitis: correlation or causality? - Vitali, Francesco; Simon, David; Neurath, Markus; Schett, Georg; Zundler, Sebastian (Rheumatology, 2021)
CRIS-Team WoS Importer:2022-02-04

Vedolizumab blocks alpha 4 beta 7 integrin-mediated T cell adhesion to MAdCAM-1 in microscopic colitis - Besendorf, Laura; Müller, Tanja; Geppert, Carol-Immanuel; Schneider, Ines; Mühl, Laura; Atreya, Imke; Vitali, Francesco; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (Therapeutic Advances in Gastroenterology, 2022)
Background: In Crohn's disease and ulcerative colitis, the anti-alpha 4 beta 7 integrin antibody vedolizumab has demonstrated efficacy in phase III trials and has been successfully used under real-world conditions. Occasionally, it has also been used in other forms of inflammatory bowel disease (IBD) such as microscopic colitis (MC). However, the mechanisms of vedolizumab in MC have not been studied to date. Therefore, we aimed to investigate the expression and functional role of gut-homing integrins and in particular alpha 4 beta 7 integrin in a cohort study in MC.
CRIS-Team WoS Importer:2022-07-08
Keywords: α4β7 integrin; microscopic colitis; T cell trafficking; vedolizumab

Vedolizumab provides clinical benefit over 1 year in patients with active inflammatory bowel disease - a prospective multicenter observational study - Stallmach, A.; Langbein, C.; Atreya, Raja; Bruns, T.; Dignass, A.; Ende, K.; Hampe, J.; Hartmann, F.; Neurath, Markus; Maul, J.; Preiss, J. C.; Schmelz, R.; et al. (Alimentary Pharmacology & Therapeutics, 2016)
Vedolizumab, a monoclonal antibody targeting the ?4?7-integrin, is effective in inducing and maintaining clinical remission in Crohn's disease and ulcerative colitis according to randomised clinical trials.To determine the long-term effectiveness of vedolizumab in a real-world clinical setting.This observational registry assessed the clinical outcome in patients treated with vedolizumab for clinically active Crohn's disease (n = 67) or ulcerative colitis (n = 60). Primary endpoint was clinical remission (HBI <= 4/pMayo <= 1) at week 54. Secondary endpoints included clinical response rates (HBI/pMayo score drop >=3) and steroid-free clinical remission at weeks 30 and 54.Vedolizumab was stopped in 69/127 (56%) patients after a median time of 18 weeks (range 2-49) predominantly owing to lack or loss of response. Using nonresponder imputation analysis, clinical remission and steroid-free remission rates were 21% and 15% in Crohn's disease and 25% and 22% in ulcerative colitis, respectively. Lack of clinical remission was associated with prior treatment with anti-TNF or with steroids for more than 3 months in the last 6 months in ulcerative colitis. At week 14, the absence of remission in Crohn's disease or nonresponse in ulcerative colitis indicated a low likelihood of clinical remission at week 54 [2/31 (7%) in Crohn's disease, 4/41 (10%) in ulcerative colitis]. Accordingly, declining C-reactive protein in inflammatory bowel disease and/or lower faecal calprotectin in ulcerative colitis at week 14 predicted remission at week 54.Among patients who started vedolizumab for active inflammatory bowel disease, clinical remission rates are 21-25% after 54 weeks.
EVALuna2:2185

VEGFR2 Signaling Prevents Colorectal Cancer Cell Senescence to Promote Tumorigenesis in Mice With Colitis - Försch, Sebastian; Sperka, Tobias; Lindner, Christina; Taut, Astrid; Rudolph, Karl L.; Breier, Georg; Boxberger, Frank; Rau, Tilman; Hartmann, Arndt; Stürzl, Michael; Wittkopf, Nadine; Haep, Lisa; et al. (Gastroenterology, 2015)
Senescence prevents cellular transformation. We investigated whether vascular endothelial growth factor (VEGF) signaling via its receptor, VEGFR2, regulates senescence and proliferation of tumor cells in mice with colitis-associated cancer (CAC).CAC was induced in VEGFR2(?IEC) mice, which do not express VEGFR2 in the intestinal epithelium, and VEGFR2(fl/fl) mice (controls) by administration of azoxymethane followed by dextran sodium sulfate. Tumor development and inflammation were determined by endoscopy. Colorectal tissues were collected for immunoblot, immunohistochemical, and quantitative polymerase chain reaction analyses. Findings from mouse tissues were confirmed in human HCT116 colorectal cancer cells. We analyzed colorectal tumor samples from patients before and after treatment with bevacizumab.After colitis induction, VEGFR2(?IEC) mice developed significantly fewer tumors than control mice. A greater number of intestinal tumor cells from VEGFR2(?IEC) mice were in senescence than tumor cells from control mice. We found VEGFR2 to activate phosphatidylinositol-4,5-bisphosphate-3-kinase and AKT, resulting in inactivation of p21 in HCT116 cells. Inhibitors of VEGFR2 and AKT induced senescence in HCT116 cells. Tumor cell senescence promoted an anti-tumor immune response by CD8(+) T cells in mice. Patients whose tumor samples showed an increase in the proportion of senescent cells after treatment with bevacizumab had longer progression-free survival than patients in which the proportion of senescent tumor cells did not change before and after treatment.Inhibition of VEGFR2 signaling leads to senescence of human and mouse colorectal cancer cells. VEGFR2 interacts with phosphatidylinositol-4,5-bisphosphate-3-kinase and AKT to inactivate p21. Colorectal tumor senescence and p21 level correlate with patient survival during treatment with bevacizumab.
EVALuna2:1356

Very Low-Volume, High-Intensity Interval Training Mitigates Negative Health Impacts of COVID-19 Pandemic-Induced Physical Inactivity - Reljic, Dejan; Eichhorn, Annalena; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (International Journal of Environmental Research and Public Health, 2022)
Initially, we aimed to investigate the impact of a one-year worksite low-volume, high-intensity interval training (LOW-HIIT) on cardiometabolic health in 114 sedentary office workers. Due to the COVID-19 pandemic outbreak, LOW-HIIT was discontinued after 6 months and participants were followed up for 6 months to analyze physical activity/exercise behavior and outcome changes during lockdown. Health examinations, including cardiopulmonary exercise testing and the assessment of cardiometabolic markers were performed baseline (T-1), after 6 months (T-2, termination of worksite LOW-HIIT) and 12 months (T-3, follow-up). Cycle ergometer LOW-HIIT (5 x 1 min at 85-95% HRmax) was performed 2x/week. For follow-up analyses, participants were classified into three groups: HIIT-group (continued home-based LOW-HIIT), EX-group (continued other home-based exercises), and NO-EX-group (discontinued LOW-HIIT/exercise). At T-2, VO2max (+1.5 mL/kg/min, p = 0.002), mean arterial blood pressure (MAB, -4 mmHg, p < 0.001), HbA(1c) (-0.2%, p = 0.005) and self-reported quality of life (QoL, +5 points, p < 0.001) were improved. At T-3, HIIT-group maintained VO2max and QoL and further improved MAB. EX-group maintained MAB and QoL but experienced a VO2max decrease. In NON-EX, VO2max, MAB and QoL deteriorated. We conclude that LOW-HIIT can be considered a promising option to improve cardiometabolic health in real-life conditions and to mitigate physical inactivity-related negative health impacts during lockdowns.
CRIS-Team WoS Importer:2022-10-21

VERY LOW-VOLUME INTERVAL TRAINING IMPROVES NONALCOHOLIC FATTY LIVER DISEASE FIBROSIS SCORE AND CARDIOMETABOLIC HEALTH IN ADULTS WITH OBESITY AND METABOLIC SYNDROME - Reljic, Dejan; Konturek, P. C.; Herrmann, H. J.; Siebler, Jürgen; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2021)
Non-alcoholic fatty liver disease (NAFLD) and cardiometabolic disorders are highly prevalent in obese individuals. Physical exercise is an important element in obesity and metabolic syndrome (MetS) treatment. However, the vast majority of individuals with obesity do not meet the general physical activity recommendations (i.e. 150 min of moderate activity per week). The present study aimed to investigate the impact of a highly time-saving high-intensity interval training (HIIT) protocol (28 min time requirement per week) on NAFLD fibrosis (NFS) and cardiometabolic risk scores in obese patients with MetS and elevated NFS values. Twenty-nine patients performed HIIT on cycle ergometers (5 x 1 min at an intensity of 80 - 95% maximal heart rate) twice weekly for 12 weeks and were compared to a control group without exercise (CON, n = 17). Nutritional counseling for weight loss was provided to both groups. NFS, cardiometabolic risk indices, MetS z-score, cardiorespiratory fitness (VO2max) and body composition were assessed before and after intervention. The HIIT (-4.3 kg, P < 0.001) and CON (-2.3 kg, P = 0.003) group significantly reduced body weight. There were no significant group differences in relative weight reduction (HIIT: -3.5%, CON: -2.4%). However, only the HIIT group improved NFS (-0.52 units, P = 0.003), MetS z-score (-2.0 units, P < 0.001), glycemic control (HbA1c: -0.20%, P = 0.014) and VO2max (+3.1 mL/kg/min, P < 0.001). Decreases in NFS (-0.50 units, P = 0.025) and MetS z-score (-1.4 units, P = 0.007) and the increment in VO2max (3.3 mL/kg/min, P < 0.001) were significantly larger in the HIIT than in the CON group. In conclusion, only 28 min of HIIT per week can elicit significant improvements in NFS and a several cardiometabolic health indices in obese MetS patients with increased NFS grades. Our results underscore the importance of exercise in NAFLD and MetS treatment and suggest that our low-volume HIIT protocol can be regarded as viable alternative to more time-consuming exercise programs.
CRIS-Team WoS Importer:2022-05-13
Keywords: obesity; interval training; non-alcoholic fatty liver disease; physical activity; metabolic syndrome; cardiopulmonary exercise test; blood pressure; liver fibrosis

Viral FLIP blocks Caspase-8 driven apoptosis in the gut in vivo - Ruder, Barbara; Günther, Claudia; Stürzl, Michael; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; Becker, Christoph (PLoS ONE, 2020)
A strict cell death control in the intestinal epithelium is indispensable to maintain barrier integrity and homeostasis. In order to achieve a balance between cell proliferation and cell death, a tight regulation of Caspase-8, which is a key player in controlling apoptosis, is required. Caspase-8 activity is regulated by cellular FLIP proteins. These proteins are expressed in different isoforms (cFLIPlong and cFLIPshort) which determine cell death and survival. Interestingly, several viruses encode FLIP proteins, homologous to cFLIPshort, which are described to regulate Caspase-8 and the host cell death machinery. In the current study a mouse model was generated to show the impact of viral FLIP (vFLIP) from Kaposi's Sarcoma-associated Herpesvirus (KSHV)/ Human Herpesvirus-8 (HHV-8) on cell death regulation in the gut. Our results demonstrate that expression of vFlip in intestinal epithelial cells suppressed cFlip expression, but protected mice from lethality, tissue damage and excessive apoptotic cell death induced by genetic cFlip deletion. Finally, our model shows that vFlip expression decreases cFlip mediated Caspase-8 activation in intestinal epithelial cells. In conclusion, our data suggests that viral FLIP neutralizes and compensates for cellular FLIP, efficiently counteracting host cell death induction and facilitating further propagation in the host organism.
CRIS-Team Scopus Importer:2020-02-11

Virtual chromoendoscopy for prediction of severity and disease extent in patients with inflammatory bowel disease: A randomized controlled study - Neumann, Helmut; Günther, Claudia; Neufert, Clemens; Kiesslich, Ralf; Grauer, Martin; Atreya, Raja; Neurath, Markus; Vieth, Michael (Inflammatory Bowel Diseases, 2013)
Background: Increased vascular permeability and angiogenesis play a crucial role in the pathogenesis of inflammatory bowel disease (IBD). Aim was to determine whether computed virtual chromoendoscopy has the potential to enhance assessment of disease severity and extent in patients with mild or inactive IBD in comparison to high-definition white-light endoscopy. Methods: Consecutive patients with IBD were randomly assigned at a 1:1 ratio to undergo colonoscopy with high-definition white light (group A) or computed virtual chromoendoscopy (group B). The mucosal vascular pattern and any mucosal abnormalities were recorded. Subsequent to endoscopic characterization targeted, biopsies were obtained from every segment for subsequent histopathological analysis of disease activity. Results: Overall, 100 patients were screened to participate in this study of whom 78 patients (high-definition white light, n = 39; computed virtual chromoendoscopy, n = 39) completed the study protocol thereby matching the previously calculated sample size. Average duration of the examination was 18 minutes in group A and 20.5 minutes in group B that was not statistically significant. When comparing the endoscopic prediction of inflammatory extent and activity with the histological results, an overall agreement of 48.71% and 53.85% (group A) and 92.31% and 89.74% (group B) was found, respectively. These differences were statistically significant (P = 0.0009 and P = 0.066). Conclusions: This study indicates that computed virtual chromoendoscopy significantly improves the diagnosis of the severity and extent of mucosal inflammation in patients with IBD. This newly developed imaging technique may therefore have important implications for therapeutic interventions in patients with IBD. Copyright © 2013 Crohn's & Colitis Foundation of America, Inc.
CRIS-Team Scopus Importer:2020-10-28
Keywords: Advanced imaging; Chromoendoscopy; Endocytoscopy; Endomicroscopy; FICE; I-scan; IBD; Mucosal healing; Prediction

Visualizing transfer of microbial biomolecules by outer membrane vesicles in microbe-host-communication in vivo - Bittel, Miriam; Reichert, Patrick; Sarfati, Ilann; Dressel, Anja; Leikam, Stefanie; Uderhardt, Stefan; Stolzer, Iris; Phu, Tuan Anh; Ng, Martin; Vu, Ngan K.; Tenzer, Stefan; Distler, Ute; et al. (Journal of Extracellular Vesicles, 2021)
The intestinal microbiota influences mammalian host physiology in health and disease locally in the gut but also in organs devoid of direct contact with bacteria such as the liver and brain. Extracellular vesicles (EVs) or outer membrane vesicles (OMVs) released by microbes are increasingly recognized for their potential role as biological shuttle systems for inter-kingdom communication. However, physiologically relevant evidence for the transfer of functional biomolecules from the intestinal microbiota to individual host cells by OMVs in vivo is scarce. By introducing Escherichia coli engineered to express Cre-recombinase (E. coliCre) into mice with a Rosa26.tdTomato-reporter background, we leveraged the Cre-LoxP system to report the transfer of bacterial OMVs to recipient cells in vivo. Colonizing the intestine of these mice with E. coliCre, resulted in Cre-recombinase induced fluorescent reporter gene-expression in cells along the intestinal epithelium, including intestinal stem cells as well as mucosal immune cells such as macrophages. Furthermore, even far beyond the gut, bacterial-derived Cre induced extended marker gene expression in a wide range of host tissues, including the heart, liver, kidney, spleen, and brain. Together, our findings provide a method and proof of principle that OMVs can serve as a biological shuttle system for the horizontal transfer of functional biomolecules between bacteria and mammalian host cells.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Cre-Loxp; extracellular vesicles; inflammation; intestinal stem cells; microbiome; outer membrane vesicles

Wall of Resilience: How the Intestinal Epithelium Prevents Inflammatory Onslaught in the Gut - Liebing, Eva; Krug, Susanne M.; Neurath, Markus; Siegmund, Britta; Becker, Christoph (Cellular and Molecular Gastroenterology and Hepatology, 2025)
The intestinal epithelium forms the boundary between the intestinal immune system in the lamina propria and the outside world, the intestinal lumen, which contains a diverse array of microbial and environmental antigens. Composed of specialized cells, this epithelial monolayer has an exceptional turnover rate. Differentiated epithelial cells are released into the intestinal lumen within a few days, at the villus tip, a process that requires strict regulation. Dysfunction of the epithelial barrier increases the intestinal permeability and paves the way for luminal antigens to pass into the intestinal serosa. Stem cells at the bottom of Lieberkühn crypts provide a constant supply of mature epithelial cells. Differentiated intestinal epithelial cells exhibit a diverse array of mechanisms that enable communication with surrounding cells, fortification against microorganisms, and orchestration of nutrient absorption and hormonal balance. Furthermore, tight junctions regulate paracellular permeability properties, and their disruption can lead to an impairment of the intestinal barrier, allowing inflammation to develop or further progress. Intestinal epithelial cells provide a communication platform through which they maintain homeostasis with a spectrum of entities including immune cells, neuronal cells, and connective tissue cells. This homeostasis can be disrupted in disease, such as inflammatory bowel disease. Patients suffering from inflammatory bowel disease show an impaired gut barrier, dysregulated cellular communication, and aberrant proliferation and demise of cells. This review summarizes the individual cellular and molecular mechanisms pivotal for upholding the integrity of the intestinal epithelial barrier and shows how these can be disrupted in diseases, such as inflammatory bowel disease.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Barrier Dysfunction; Inflammatory Bowel Diseases; Intestinal Epithelium

Weekly High-dose 5-Fluorouracil as 24-hour Infusion Combined with Sodium Folinic Acid (AIO regimen) Plus Irinotecan in Second-line and Sequential Therapy of Metastatic Colorectal Cancer (CRC) - Wein, Axel; Wolff, Kerstin; Ostermeier, Nicola; Busse, Daniel; Hagel, Alexander; Koch, Franz; Merx, Kirsten; Neurath, Markus; Hofheinz, Ralf-Dieter; Siebler, Jürgen (Anticancer Research, 2017)
BACKGROUND/AIM: The aim of this work was to evaluate the efficacy and safety of second-line treatment with weekly high-dose 5-fluorouracil (5-FU) as a 24-hour infusion (24-h inf.) combined with sodium folinic acid (FA) (AIO-regimen) plus irinotecan (Iri.) after pretreatment with AIO-regimen plus oxaliplatin (L-OHP). PATIENTS AND METHODS: Patients with non-resectable distant CRC metastases were enrolled in a prospective phase II study for palliative second-line treatment after previous progression of first-line treatment in accordance with the AIO-regimen plus oxaliplatin. On an outpatient basis, the patients received a treatment regimen comprising of weekly 80 mg/m2 irinotecan in the form of a 1-hour i.v. infusion and 2,000 mg/m2 5-FU combined with 500 mg/m2 sodium folinic acid administered as a 24-h infusion i.v. once weekly. RESULTS: During second-line treatment, a total of 59 patients received 520 chemotherapy applications. As the main higher-grade symptom of toxicity, diarrhea (NCI-CTC-toxicity grade 3) presented in 8 patients (13.6%, 95%CI=5.1-23.7), followed by leukocytopenia (CTC grade 3) in 3 patients (5.1%, 95%CI=0-11.9), followed by thrombocytopenia (CTC grade 3) in 1 patient (1.7%, 95%CI=0-5.1). Fifty-nine patients were evaluable for treatment response. The remission data can be summarized as follows: complete remission (CR); n=0; partial remission (PR); n=6 (10%; 95%CI=3.4-18.6); stable disease (SD); n=31 (53%; 95%CI=39.0-64.4); progressive disease (PD); n=19 (33%; 95%CI=20.3-44.1). The median progression-free survival (PFS) rate (n=59) was 4.2 months (range=3.8-5.8 months). The median survival time counted from the start of second-line treatment (n=59) 14.2 months (range 8.2-17.3 months) and the median survival time counted from the start of first-line therapy (n=59) 25 months (range 19-27 months). CONCLUSION: Palliative second-line treatment according to the AIO regimen plus irinotecan offers both a favourable toxicity profile and promising efficacy in second-line and palliative sequential therapy.
EVALuna2:33808

What Gastroenterologists and Hepatologists should know about organoids in 2019 - Günther, Claudia; Brevini, Teresa; Sampaziotis, Fotios; Neurath, Markus (Digestive and Liver Disease, 2019)
Most of the research behind new medical advances is carried out using either animal models or cancer cells, which both have their disadvantage in particular with regard to medical applications such as personalized medicine and novel therapeutic approaches. However, recent advances in stem cell biology have enabled long-term culturing of organotypic intestinal or hepatic tissues derived from tissue resident or pluripotent stem cells. These 3D structures, denoted as organoids, represent a substantial advance in structural and functional complexity over traditional in vitro cell culture models that are often non-physiological and transformed. They can recapitulate the in vivo architecture, functionality and genetic signature of the corresponding tissue. The opportunity to model epithelial cell biology, epithelial turnover, barrier dynamics, immune-epithelial communication and host-microbe interaction more efficiently than previous culture systems, greatly enhance the translational potential of organotypic hepato-gastrointestinal culture systems. Thus there is increasing interest in using such cultured cells as a source for tissue engineering, regenerative medicine and personalized medicine. This review will highlight some of the established and also some exciting novel perspectives on organoids in the fields of gastroenterology and hepatology.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Gastroenterology; Hepatology; Organoids

What rheumatologists can learn from gastroenterologists - Fischer, Sören; Beyer, Christian; Neurath, Markus (Zeitschrift für Rheumatologie, 2018)
BACKGROUND: Chronic inflammatory diseases are complex disorders, which due to their multitude of manifestations require interdisciplinary treatment. OBJECTIVE: The aim of this article is to provide a brief overview of current strategies and innovations for chronic inflammatory bowel diseases. METHODS: A literature search was carried out in PubMed. RESULTS: Shared pathophysiological pathways in chronic inflammatory diseases sometimes lead to common targets in treatment; however, there are also relevant specific differences with respect to treatment. CONCLUSION: Due to the many extraintestinal organ manifestations, chronic inflammatory bowel diseases require interdisciplinary treatment.
EVALuna2:35151

Whole-Body Electromyostimulation Combined With Individualized Nutritional Support Improves Body Composition in Patients With Hematological Malignancies - A Pilot Study - Schink, Kristin; Relijic, Dejan; Herrmann, Hans J.; Meyer, Julia; Mackensen, Andreas; Neurath, Markus; Zopf, Yurdagül (Frontiers in Physiology, 2018)
Patients undergoing the complex treatment for hematological malignancies are exposed to a high physiological and psychological distress inducing fatigue and physical inactivity. In line with cancer-related metabolic changes patients are predisposed for skeletal muscle mass loss that leads to a functional decline, affects therapeutic success, and quality of life. Benefits of physical exercise and nutritional interventions on muscle maintenance are observed in solid cancer patients, but marginally investigated in patients with hematological cancer. We here studied the effects of a combined supportive exercise and nutrition intervention using whole-body electromyostimulation (WB-EMS) training and individualized nutritional support in patients actively treated for hematological malignancy. In a controlled pilot trial, 31 patients (67.7% male; 58.0 +/- 16.7 years) with various hematological cancers were allocated to a control group (n = 9) receiving nutritional support of usual care regarding a high protein intake (> 1.0 g/kg/d) or to a physical exercise group (n = 22) additionally performing WB-EMS training twice weekly for 12 weeks. Bodyweight and body composition assessed by bioelectrical impedance analysis were measured every 4 weeks. Physical function, blood parameters, quality of life and fatigue were assessed at baseline and after 12 weeks. No WB-EMS-related adverse effects occurred. Patients attending the exercise program presented a higher skeletal muscle mass than controls after 12-weeks (1.51 kg [0.41, 2.60]; p = 0.008). In contrast, patients of the control group showed a higher fat mass percentage than patients of the WB-EMS group (-4.46% [-7.15, -1.77]; p = 0.001) that was accompanied by an increase in serum triglycerides in contrast to a decrease in the WB-EMS group (change +/- SD, control 36.3 +/- 50.6 mg/dl; WB-EMS -31.8 +/- 68.7 mg/dl; p = 0.064). No significant group differences for lower limb strength, quality of life, and fatigue were detected. However, compared to controls the WB-EMS group significantly improved in physical functioning indicated by a higher increase in the 6-min-walking distance (p = 0.046). A combined therapeutic intervention of WB-EMS and protein-rich nutritional support seems to be safe and effective in improving skeletal muscle mass and body composition in hematological cancer patients during active oncological treatment.
EVALuna2:35109

Whole-Body Electromyostimulation combined with personalized Nutritional Support improves the Body Composition of Patients with advanced Cancer - Schink, Kristin; Herrmann, Hans Joachim; Schwappacher, Raphaela; Orlemann, Till; Meyer, Julia; Waldmann, Elisabeth; Wullich, Bernd; Kahlmeyer, Andreas; Fietkau, Rainer; Lubgan, Dorota; Beckmann, Matthias; Hack, Carolin; et al. (2018)
EVALuna2:35187

Whole-Body Electrostimulation in Combination with protein-rich Nutrition in Patients with metastatic or advanced Stage gynecological Cancer: An innovative Therapy Concept - Zopf, Yurdagül; Herrmann, Hans Joachim; Neurath, Markus; Reljic, Dejan (2018)
EVALuna2:35189

Wireless capsule endoscopy of the small intestine: a review with future directions - Neumann, Helmut; Fry, Lucia C.; Naegel, Andreas; Neurath, Markus (Current Opinion in Gastroenterology, 2014)
Here, we review the clinical applications of small bowel capsule endoscopy. Moreover, we provide an outlook on the exceptional future developments of small bowel capsule endoscopy. We discuss clinical algorithms for diagnosis of small bowel diseases. Multiple studies have shown the potential of capsule endoscopy for identification of the bleeding source located in the small bowel and the increased diagnostic yield over radiographic studies. Capsule endoscopy could detect villous atrophy and severe complications in patients with nonresponsive celiac disease. In addition, small bowel capsule endoscopy was proven as a valid tool to diagnose polyps and tumors and Crohn's disease.Major current clinical indications of capsule endoscopy in the small bowel include evaluation of obscure gastrointestinal bleeding, diagnosis and surveillance of small bowel polyps and tumors, celiac disease and Crohn's disease. Recent developments have also passed the way for small bowel capsule endoscopy to become a therapeutic instrument.
EVALuna2:1880

α4β7 integrin-dependent adhesion of T cells to MAdCAM-1 is blocked by vedolizumab in patients with chronic refractory pouchitis - Melde, Michaela; Müller, Tanja; Schneider, Ignaz Hans Friedrich; Geppert, Carol-Immanuel; Mühl, Laura; Besendorf, Laura; Allner, Clarissa; Becker, Emily; Atreya, Imke; Vitali, Francesco; Atreya, Raja; Neurath, Markus; et al. (Therapeutic Advances in Gastroenterology, 2021)
Background: The anti-α4β7 integrin antibody vedolizumab is an established therapeutic option for the treatment of inflammatory bowel disease (IBD). It has also been successfully used in patients with chronic antibiotic-refractory pouchitis following proctocolectomey with ileal pouch-anal anastomosis. However, the expression and function of gut-homing markers as well as strategies to predict the response to vedolizumab in pouchitis are understudied so far. Methods: We used flow cytometry and dynamic adhesion assays to study the expression and function of gut-homing integrins on T cells from patients with pouchitis and controls as well as longitudinally during therapy of pouchitis with vedolizumab. Moreover, we describe clinical effects of vedolizumab in a cohort of patients with pouchitis. Results: T cells from patients with pouchitis express a specific profile of gut-homing integrins. Integrin α4β7 on T cells from patients with pouchitis mediates adhesion to mucosal addressin cell adhesion molecule (MAdCAM)-1, which can be blocked by vedolizumab in vitro. Vedolizumab efficiently treats pouchitis in a portion of patients and response correlates with dynamic adhesion profiles to MAdCAM-1. Conclusion: Our data suggest that T cell trafficking seems to be important for the pathogenesis of pouchitis and support the therapeutic use of vedolizumab. Integrin function might serve as a biomarker to predict response to vedolizumab.
CRIS-Team Scopus Importer:2021-12-17
Keywords: ileal pouch-anal anastomosis; pouchitis; proctocolectomy; T cells trafficking; vedolizumab